3D hydrodynamic simulations of the Galactic supernova remnant CTB 109 - Bolte, Jan; Sasaki, Manami; Breitschwerdt, Dieter (Astronomy & Astrophysics, 2015)
Context. Using detailed 3D hydrodynamic simulations we study the nature of the Galactic supernova remnant (SNR) CTB 109 (G109.1-1.0), which is well known for its semicircular shape and a bright diffuse X-ray emission feature inside the SNR. Aims. Our model has been designed to explain the observed morphology, with a special emphasis on the bright emission feature inside the SNR. Moreover, we determine the age of the remnant and compare our findings with X-ray observations. With CTB 109 we test a new method of detailed numerical simulations of diffuse young objects, using realistic initial conditions derived directly from observations. Methods. We performed numerical 3D simulations with the RAMSES code. The initial density structure has been directly taken from 12CO emission data, adding an additional dense cloud, which, when it is shocked, causes the bright emission feature. Results. From parameter studies we obtained the position (l, b) = (109.1545 , −1.0078 ) for an elliptical cloud with ncloud = 25 cm^-3 based on the preshock density from Chandra data and a maximum diameter of 4.54 pc, whose encounter with the supernova (SN) shock wave generates the bright X-ray emission inside the SNR. The calculated age of the remnant is about 11 000 yr according to our simulations. In addition, we can also determine the most probable site of the SN explosion. Conclusions. Hydrodynamic simulations can reproduce the morphology and the observed size of the SNR CTB 109 remarkably well. Moreover, the simulations show that it is very plausible that the bright X-ray emission inside the SNR is the result of an elliptical dense cloud shocked by the SN explosion wave. We show that numerical simulations using observational data for an initial model can produce meaningful results.
Keywords: ISM: supernova remnants; evolution; shock waves; hydrodynamics; methods: numerical

3D mapping of the neutral X-ray absorption in the local interstellar medium: the Gaia and XMM-Newton synergy - Gatuzz, Efrain; Rezaei, S. Kh; Kallman, Timothy R.; Kreikenbohm, Annika; Oertel, Mirjam; Wilms, Jörn; Garcia, Javier (Monthly Notices of the Royal Astronomical Society, 2018)
We present a three-dimensional map of the hydrogen density distribution in the Galactic interstellar medium. The hydrogen-equivalent column densities were obtained from the Exploring the X-ray Transient and variable Sky project (EXTRAS) which provides equivalent NH values from X-ray spectral fits of observations within the XMM-Newton Data Release. EXTRAS include multiple fits for each source, allowing an accurate determination of the equivalent column densities, which depends on the continuum modelling of the spectra. A cross-correlation between the EXTRAS catalogue and the first Gaia Data Release was performed in order to obtain accurate parallax and distance measurements. We use a Bayesian method explained in Rezaei Kh. et al. (2017) in order to predict the most probable distribution of the density at any arbitrary point, even for lines of sight along which there are no initial observation. The resulting map shows small-scale density structures which could not have been modelled by using analytic density profiles. In this paper, we present a proof of concept of the kind of science possible with the synergy of these catalogues. However, given the systematic uncertainties connected to the source identification and to the dependence of NH on the spectral model, the present maps should be considered qualitatively at this point.
Keywords: ISM: atoms; ISM: structure; Galaxy: structure; X-rays: ISM

4U 1909+07: a well-hidden pearl - Fürst, Felix; Kreykenbohm, Ingo; Suchy, S.; Barragan, L.; Wilms, Jörn; Rothschild, R. E.; Pottschmidt, K. (Astronomy & Astrophysics, 2011)
We present the first detailed spectral and timing analysis of the high mass X-ray binary (HMXB) 4U1909+07 with INTEGRAL and RXTE. 4U1909+07 is detected in the ISGRI 20-40 keV energy band with an average countrate of 2.6 cts s(-1). The pulse period of similar to 604 s is not stable, but changing erratically on timescales of years. The pulse profile is strongly energy dependent: it shows a double peaked structure at low energies, the secondary pulse decreases rapidly with increasing energy and above 20 keV only the primary pulse is visible. This evolution is consistent between PCA, HEXTE, and ISGRI. The phase averaged spectrum can be well described by the sum of a photoabsorbed power law with a cutoff at high energies and a blackbody component. To investigate the pulse profile, we performed phase resolved spectral analysis. We find that the changing spectrum can be best described with a variation of the folding energy. We rule out a correlation between the black body component and the continuum variation and discuss possible accretion geometries.
Keywords: accretion; accretion disks; X-rays: binaries; stars: neutron

5.9-keV Mn K-shell X-ray luminosity from the decay of Fe-55 in Type Ia supernova models - Seitenzahl, I. R.; Summa, A.; Krauss, F.; Sim, S. A.; Diehl, R.; Elsaesser, D.; Fink, M.; Hillebrandt, W.; Kromer, M.; Maeda, K.; Mannheim, K.; Pakmor, R.; et al. (Monthly Notices of the Royal Astronomical Society, 2015)
We show that the X-ray line flux of the Mn Ka line at 5.9 keV from the decay of Fe-55 is a promising diagnostic to distinguish between Type Ia supernova (SN Ia) explosion models. Using radiation transport calculations, we compute the line flux for two three-dimensional explosion models: a near-Chandrasekhar mass delayed detonation and a violent merger of two (1.1 and 0.9 M-circle dot) white dwarfs. Both models are based on solar metallicity zero-age main-sequence progenitors. Due to explosive nuclear burning at higher density, the delayed-detonation model synthesizes similar to 3.5 times more radioactive Fe-55 than the merger model. As a result, we find that the peak Mn K alpha line flux of the delayed-detonation model exceeds that of the merger model by a factor of similar to 4.5. Since in both models the 5.9-keV X-ray flux peaks five to six years after the explosion, a single measurement of the X-ray line emission at this time can place a constraint on the explosion physics that is complementary to those derived from earlier phase optical spectra or light curves. We perform detector simulations of current and future X-ray telescopes to investigate the possibilities of detecting the X-ray line at 5.9 keV. Of the currently existing telescopes, XMM-Newton/pn is the best instrument for close (less than or similar to 1-2 Mpc), non-background limited SNe Ia because of its large effective area. Due to its low instrumental background, Chandra/ACIS is currently the best choice for SNe Ia at distances above similar to 2 Mpc. For the delayed-detonation scenario, a line detection is feasible with Chandra up to similar to 3 Mpc for an exposure time of 10(6) s. We find that it should be possible with currently existing X-ray instruments (with exposure times less than or similar to 5 x 10(5) s) to detect both of our models at sufficiently high S/N to distinguish between them for hypothetical events within the Local Group. The prospects for detection will be better with future missions. For example, the proposed Athena/X-IFU instrument could detect our delayed-detonation model out to a distance of similar to 5 Mpc. This would make it possible to study future events occurring during its operational life at distances comparable to those of the recent supernovae SN 2011 fe (similar to 6.4 Mpc) and SN 2014J (similar to 3.5 Mpc).
Keywords: line: formation; nuclear reactions; nucleosynthesis; abundances; radiative transfer; supernovae: general; white dwarfs; X-rays: general

A 33 hour period for the Wolf-Rayet/black hole X-ray binary candidate NGC 300 X-1 - Wilms, Jörn; et al. (Astronomy & Astrophysics, 2007)
Context. NGC 300 X-1 is the second extragalactic candidate, after IC 10 X-1, in the rare class of Wolf-Rayet/compact object X-ray binary systems exemplified in the Galaxy by Cyg X-3. From a theoretical point of view, accretion onto a black hole in a detached system is possible for large orbital periods only if the mass of the relativistic object is high or the velocity of the accreted wind is low.Aims. We analysed a 2 week SWIFT XRT light curve of NGC 300 X-1 and searched for periodicities. Methods. Period searches were made using Lomb-Scargle periodogram analysis. We evaluated the confidence level using Monte Carlo simulations.Results. A period of 32.8 +/- 0.4 h (3 sigma error) was found for NGC 300 X-1 with a confidence level > 99%. Furthermore, we confirm the high irregular variability during the high flux level, as already observed in the XMM-Newton observations of the source. A folded XMM-Newton light curve is shown, with a profile that is in agreement with SWIFT. The mean absorbed X-ray luminosity in the SWIFT observations was 1.5 x 10(38) erg s(-1), close to the value derived from the XMM-Newton data.Conclusions. While Cyg X-3 has a short period of 4.8 h, the period of NGC 300 X-1 is very close to that of IC 10 X-1 (34.8 +/- 0.9 h). These are likely orbital periods. Possibility of formation of accretion disk for such high orbital periods strongly depends on the terminal velocity of the Wolf-Rayet star wind and black-hole mass. While low masses are possible for wind velocities <= 1000 km s(-1), these increase to several tens of solar masses for velocities > 1600 km s(-1) and no accretion disk may form for terminal velocities larger than 1900 km s(-1).
Keywords: X-rays : individuals : NGC 300 X-1; X-rays : binaries; stars : Wolf-Rayet

About the Kerr Nature of the Stellar-mass Black Hole in GRS 1915+105 - Zhang, Yuexin; Abdikamalov, Askar B.; Ayzenberg, Dimitry; Bambi, Cosimo; Dauser, Thomas; Garcia, Javier; Nampalliwar, Sourabh (Astrophysical Journal, 2019)
We employ the accretion disk reflection model RELXILL_NK to test the spacetime geometry around the stellar-mass black hole in GRS 1915+105. We adopt the Johannsen metric with the deformation parameters alpha(13) and alpha(22), for which the Kerr solution is recovered when alpha(13) = alpha(22) = 0. We analyze a NuSTAR observation of 2012, obtaining vanishing and non-vanishing values of the deformation parameters depending on the astrophysical model adopted. Similar difficulties were not found in our previous tests with other sources. The results of this work can shed light on the choice of sources suitable for testing the Kerr metric using X-ray reflection spectroscopy and on the parts of our reflection models that more urgently require improvement.
CRIS-Team WoS Importer:2019-04-25

A Broadband X-Ray View of the Precessing Accretion Disk and Pre-eclipse Dip in the Pulsar Her X-1 with NuSTAR and XMM-Newton - Brumback, Mckinley C.; Hickox, Ryan C.; Furst, Felix S.; Pottschmidt, Katja; Tomsick, John A.; Wilms, Jörn; Staubert, Ruediger; Vrtilek, Saeqa (Astrophysical Journal, 2021)
We present a broadband X-ray timing study of the variations in pulse behavior with the superorbital cycle in the low-mass X-ray binary Her X-1. This source shows a 35 day superorbital modulation in X-ray flux that is likely caused by occultation by a warped, precessing accretion disk. Our data set consists of four joint XMM-Newton and NuSTAR observations of Her X-1 which sample a complete superorbital cycle. We focus our analysis on the first and fourth observations, which occur during the bright "main-on" phase, because these observations have strongly detected pulsations. We added an archival XMM-Newton observation during the "short-on" phase of the superorbital cycle because our observations at that phase are lower in signal to noise. We find that the energy-resolved pulse profiles show the same shape at similar superorbital phases, and the profiles are consistent with expectations from a precessing disk. We demonstrate that a simple precessing accretion disk model is sufficient to reproduce the observed pulse profiles. The results of this model suggest that the similarities in the observed pulse profiles are due to reprocessing by a precessing disk that has returned to its original precession phase. We determine that the broadband spectrum is well fit by an absorbed power law with a soft blackbody component and show that the spectral continuum also exhibits a dependence on the superorbital cycle. We also present a brief analysis of the energy-resolved light curves of a pre-eclipse dip, which shows soft X-ray absorption and hard X-ray variability during the dip.
CRIS-Team WoS Importer:2021-12-10

Absorption lines from magnetically driven winds in X-ray binaries - II. High resolution observational signatures expected from future X-ray observatories - Chakravorty, Susmita; Petrucci, Pierre-Olivier; Datta, Sudeb Ranjan; Ferreira, Jonathan; Wilms, Jörn; Jacquemin-Ide, Jonatan; Clavel, Maica; Marcel, Gregoire; Rodriguez, Jerome; Malzac, Julien; Belmont, Renaud; Corbel, Stephane; et al. (Monthly Notices of the Royal Astronomical Society, 2023)
In our self-similar, analytical, magnetohydrodynamic (MHD) accretion-ejection solution, the density at the base of the outflow is explicitly dependent on the disc accretion rate - a unique property of this class of solutions. We had earlier found that the ejection index p >similar to 0.1 (M-acc proportional to r(p)) is a key MHD parameter that decides if the flow can cause absorption lines in the high resolution X-ray spectra of black hole binaries. Here, we choose three dense warm solutions with p = 0.1, 0.3, 0.45 and carefully develop a methodology to generate spectra which are convolved with the Athena and XRISM response functions to predict what they will observe seeing through such MHD outflows. In this paper two other external parameters were varied - extent of the disc, r(o)|(max) = 10(5), 10(6) r(G), and the angle of the line of sight, i similar to 10-25 degrees. Resultant absorption lines (H and He-like Fe, Ca, Ar) change in strength and their profiles manifest varying degrees of asymmetry. We checked if (a) the lines and (ii) the line asymmetries are detected, in our suit of synthetic Athena and XRISM spectra. Our analysis shows that Athena should detect the lines and their asymmetries for a standard 100 ks observation of a 100 mCrab source - lines with equivalent width as low as a few eV should be detected if the 6-8 keV counts are larger than 10(4)-10(5) even for the least favourable simulated cases.
CRIS-Team WoS Importer:2023-02-03

Abundance and temperature of the outer hot circumgalactic medium: The SRG/eROSITA view of the soft X-ray background in the eFEDS field - Ponti, G.; Zheng, X.; Locatelli, N.; Bianchi, S.; Zhang, Y.; Anastasopoulou, K.; Comparat, J.; Dennerl, K.; Freyberg, M.; Haberl, F.; Merloni, A.; Reiprich, T. H.; et al. (Astronomy & Astrophysics, 2023)
Context. Despite their vital importance to understanding galaxy evolution and our own Galactic ecosystem, our knowledge of the physical properties of the hot X-ray emitting phase of the Milky Way is still inadequate. However, sensitive SRG/eROSITA large area surveys are now providing us with the long-sought data needed to mend this state of affairs. Aims. Our aim is to constrain the properties of the Milky Way hot halo emission toward intermediate Galactic latitudes close to the Galactic anti-center. Methods. We analyzed the spectral properties of the integrated soft X-ray emission observed by eROSITA in the relatively deep eFEDS feld. Results. We observe a flux of 12.6 and 5.1 × 10-12erg cm-2s-1deg-2in the total (0.3-2) and soft (0.3-0.6 keV) band. We measure the temperature and metal (oxygen) abundance of the hot circumgalactic medium (CGM) to be within kTCGM = 0.153-0.178 keV and ZCGM = 0.052-0.072 Z·, depending on the contribution of solar wind charge exchange (SWCX). Slightly higher CGM abundances ZCGM = 0.05-0.10 Z·are possible, considering the uncertain extrapolation of the extragalactic cosmic X-ray background (CXB) emission below ∼1 keV. To recover CGM abundances as high as ZCGM = 0.3 Z·, the presence of an additional component must be postulated, likely associated with the warm-hot intergalactic medium, providing ∼15-20% of the flux in the soft X-ray band. We observe line widths of the CGM plasma smaller than δv = 500 km s-1. The emission in the soft band is dominated (∼47%) by the circumgalactic medium (CGM), whose contribution reduces to ∼30% if heliospheric SWCX contributes at the level of ∼15% also during solar minimum. The remaining flux is provided by the CXB (∼33%) and the local hot bubble (∼18%). Moreover, the eROSITA data require the presence of an additional component associated with the elusive Galactic corona plus a possible contribution from unresolved M dwarf stars. This component has a temperature of kT ∼ 0.4- 0.7 keV, a considerable (∼ kiloparsec) scale height, and might be out of thermal equilibrium. It contributes ∼9% to the total emission in the 0.6-2 keV band, and is therefore a likely candidate to produce part of the unresolved CXB flux observed in X-ray ultra-deep felds. We also observe a signifcant contribution to the soft X-ray flux due to SWCX, during periods characterized by stronger solar wind activity, and causing the largest uncertainty on the determination of the CGM temperature. Conclusions. We constrain temperature, emission measure, abundances, thermal state, and spectral shape of the outer hot CGM of the Milky Way.
CRIS-Team Scopus Importer:2023-09-01
Keywords: Galaxy: abundances; Galaxy: halo; ISM: general; ISM: structure; Local insterstellar matter; X-rays: diffuse background

Acceleration of petaelectronvolt protons in the Galactic Centre - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E. O.; Backes, M.; Balzer, A.; Becherini, Y.; Tjus, J. Becker; Berge, D.; Bernhard, S.; Bernloehr, K.; et al. (Nature, 2016)
Galactic cosmic rays reach energies of at least a few petaelectronvolts(1) (of the order of 1015 electronvolts). This implies that our Galaxy contains petaelectronvolt accelerators ('PeVatrons'), but all proposed models of Galactic cosmic-ray accelerators encounter difficulties at exactly these energies(2). Dozens of Galactic accelerators capable of accelerating particles to energies of tens of teraelectronvolts (of the order of 10(13) electronvolts) were inferred from recent gamma-ray observations(3). However, none of the currently known accelerators-not even the handful of shell-type supernova remnants commonly believed to supply most Galactic cosmic rays-has shown the characteristic tracers of petaelectronvolt particles, namely, power-law spectra of.-rays extending without a cut-off or a spectral break to tens of teraelectronvolts(4). Here we report deep.-ray observations with arcminute angular resolution of the region surrounding the Galactic Centre, which show the expected tracer of the presence of petaelectronvolt protons within the central 10 parsecs of the Galaxy. We propose that the supermassive black hole Sagittarius A* is linked to this PeVatron. Sagittarius A* went through active phases in the past, as demonstrated by X-ray outbursts(5) and an outflow from the Galactic Centre(6). Although its current rate of particle acceleration is not sufficient to provide a substantial contribution to Galactic cosmic rays, Sagittarius A* could have plausibly been more active over the last 10(6)-10(7) years, and therefore should be considered as a viable alternative to supernova remnants as a source of petaelectronvolt Galactic cosmic rays.

Accreting on the Edge: A Luminosity-dependent Cyclotron Line in the Be/X-Ray Binary 2S 1553-542 Accompanied by Accretion Regimes Transition - Malacaria, C.; Bhargava, Y.; Coley, Joel B.; Ducci, L.; Pradhan, P.; Ballhausen, R.; Fuerst, F.; Islam, N.; Jaisawal, G. K.; Jenke, P.; Kretschmar, P.; Kreykenbohm, Ingo; et al. (Astrophysical Journal, 2022)
Accreting X-ray pulsars undergo luminous X-ray outbursts during which the luminosity-dependent spectral and timing features of the neutron star's emission can be analyzed in detail, thus shedding light on the accretion regime at work. We took advantage of a monitoring campaign that was performed with NuSTAR, Swift/XRT, AstroSat and NICER to follow the Be/X-ray Binary 2S 1553-542 along one of its rare outbursts, and thus trace its spectral and timing evolution. We report the discovery of a luminosity-dependent cyclotron line energy for the first time in this source. The pulse profiles and pulsed fraction also show variability along the outburst, which is consistent with the interpretation that the source transitions from the subcritical to the supercritical accretion regime, separated by a critical luminosity of L (crit) approximate to 4 x 10(37) erg s(-1).
CRIS-Team WoS Importer:2022-04-01

Accreting X-ray pulsars observed with integral - Wilms, Jörn; et al. (2007)
In this paper, we review the observational properties of two accreting X-ray pulsars, the persistent source 4U 1907+09 and the transient V 0332+53. Accreting X-ray pulsars are among the brightest sources in the Xray sky and are frequently observed by INTEGRAL and other X-ray missions. Nevertheless they are still very enigmatic sources as fundamental questions on the X-ray production mechanism still remain largely unanswered. These questions are addressed by performing detailed temporal and spectral studies on several objects over a long time range.Of vital importance is the study of cyclotron lines as they provide the only direct link to the magnetic field of the pulsar. While some objects show cyclotron lines which are extremely stable with time and with pulse phase, in other objects the lines strongly depend on the pulse phase, the luminosity of the source, or both.Of special interest in any case are transient sources where it is possible to study the evolution of the cyclotron line and the source in general from the onset until the end of the outburst through a wide range of different luminosity states.We present an observational review of a transient and a persistent accreting X-ray pulsar observed with Integral.
Keywords: X-rays : stars; stars : magnetic fields; stars : flare; stars : pulsars : individual : 4U 1907+09; stars : pulsars : individual : V0332+53

Accretion disk versus jet orientation in H2O megamaser galaxies - Kamali, F.; Henkel, C.; Koyama, S.; Kuo, C. Y.; Condon, J. J.; Brunthaler, A.; Reid, M. J.; Greene, J. E.; Menten, K. M.; Impellizzeri, C. M.; Braatz, J. A.; Litzinger, Eugenia; et al. (Astronomy & Astrophysics, 2019)
Context. An essential part of the paradigm describing active galactic nuclei is the alignment between the radio jet and the associated rotation axis of the sub-pc accretion disks. Because of the small linear and angular scales involved, this alignment has not yet been checked in a sufficient number of low luminosity active galactic nuclei (LLAGNs).
CRIS-Team WoS Importer:2019-04-16

Accretion in strong field gravity with eXTP - De Rosa, Alessandra; Uttley, Phil; Gou, Lijun; Liu, Yuan; Bambi, Cosimo; Barret, Didier; Belloni, Tomaso; Berti, Emanuele; Bianchi, Stefano; Caiazzo, Ilaria; Casella, Piergiorgio; Feroci, Marco; et al. (Science China-Physics Mechanics & Astronomy, 2019)
In this paper we describe the potential of the enhanced X-ray Timing and Polarimetry (eXTP) mission for studies related to accretion flows in the strong field gravity regime around both stellar-mass and supermassive black-holes. eXTP has the unique capability of using advanced “spectral-timing-polarimetry” techniques to analyze the rapid variations with three orthogonal diagnostics of the flow and its geometry, yielding unprecedented insight into the inner accreting regions, the effects of strong field gravity on the material within them and the powerful outflows which are driven by the accretion process. X-spinmeasurements.
CRIS-Team Scopus Importer:2021-04-20
Keywords: accretion; black holes physics; X-ray

Accretion processes in astrophysics - Shakura, N.; Kolesnikov, D. A.; Postnov, K. A.; Volkov, I. M.; Bikmaev, I. F.; Irsmambetova, T. R.; Staubert, R.; Wilms, Jörn; Irtuganov, E.; Shurygin, P.; Golysheva, P. Yu; Shugarov, S. Yu; et al. (Physics-Uspekhi, 2019)
Accretion onto magnetized neutron stars is considered using as a case study long-term X-ray and optical observations of HZ Her/Her X-1, an X-ray binary system with a 1.7-day orbital period where disc accretion occurs from the optical donor star (HZ Her) onto a neutron star (Her X-1). On top of orbital variability and pulsating X-ray emission from the neutron star rotating with a period of about one second, a 35-day X-ray modulation of emission is observed. The 35-day variability is due to a tilted precessing accretion disc that periodically screens X-ray emission from the neutron star. The disc precession that occurs in the direction opposite to the orbital motion is determined by the joint action of the tidal torque from the donor and dynamical torque from the gas streams. Several dozen thousand broadband UBV photometric observations of HZ Her have been obtained since 1972. The shape of the orbital light curves of HZ Her also changes with the 35-day cycle phase. The orbital variability can be reproduced in a model that includes a precessing tilted and warped accretion disc around a freely precessing neutron star. The disc is warped near its inner edge due to interaction with the rotating neutron star magnetosphere. The magnetic torque depends on the precessional phase of the neutron star. The X-ray emission flux from the neutron star also depends on the free precession phase that modulates the heating of the optical-star atmosphere and the intensity of gas streams. We show that this model reproduces well both optical observations of HZ Her and the behavior of the 35-day X-ray cycle.
CRIS-Team WoS Importer:2020-03-24

Accurate Treatment of Comptonization in X-Ray Illuminated Accretion Disks - Garcia, Javier A.; Sokolova-Lapa, Ekaterina; Dauser, Thomas; Madej, Jerzy; Rozanska, Agata; Majczyna, Agnieszka; Harrison, Fiona A.; Wilms, Jörn (Astrophysical Journal, 2020)
A large fraction of accreting black hole and neutron star systems present clear evidence of the reprocessing of X-rays in the atmosphere of an optically thick accretion disk. The main hallmarks of X-ray reflection include fluorescent K-shell emission lines from iron (∼6.4-6.9 keV), the absorption iron K-edge (∼7-9 keV), and a broad featureless component known as the Compton hump (∼20-40 keV). This Compton hump is produced as the result of the scattering of high-energy photons (E ⪆ 10 keV) of the relatively colder electrons (T e ∼ 105-107 K) in the accretion disk, in combination with photoelectric absorption from iron. The treatment of this process in most current models of ionized X-ray reflection has been done using an approximated Gaussian redistribution kernel. This approach works sufficiently well up to ∼100 keV, but it becomes largely inaccurate at higher energies and at relativistic temperatures (T e ∼ 109 K). We present new calculations of X-ray reflection using a modified version of our code xillver, including an accurate solution for Compton scattering of the reflected unpolarized photons in the disk atmosphere. This solution takes into account quantum electrodynamic and relativistic effects allowing the correct treatment of high photon energies and electron temperatures. We show new reflection spectra computed with this model, and discuss the improvements achieved in reproducing the correct shape of the Compton hump, the discrepancies with previous calculations, and the expected impact of these new models in the interpretation of observational data.
CRIS-Team Scopus Importer:2021-04-19

A CHANDRA OBSERVATION OF THE BURSTING MILLISECOND X-RAY PULSAR IGR J17511-3057 - Paizis, Adamantia; Nowak, M. A.; Rodriguez, Jerome; Wilms, Jörn; Chaty, Sylvain; Del Santo, Melania; Ubertini, P. (Astrophysical Journal, 2012)
IGR J17511-3057 is a low-mass X-ray binary hosting a neutron star and is one of the few accreting millisecond X-ray pulsars with X-ray bursts. We report on a 20 ks Chandra grating observation of IGR J17511-3057, performed on 2009 September 22. We determine the most accurate X-ray position of IGRJ17511-3057, alpha(J2000) = 17(h)51(m)08(s).66, delta(J2000) = -30 degrees.57'41 ''.0 (90% uncertainty of 0 ''.6). During the observation, a similar to 54 s long type-I X-ray burst is detected. The persistent (non-burst) emission has an absorbed 0.5-8 keV luminosity of 1.7 x 10(36) erg s(-1) (at 6.9 kpc) and can be well described by a thermal Comptonization model of soft, similar to 0.6 keV, seed photons upscattered by a hot corona. The type-I X-ray burst spectrum, with average luminosity over the 54 s duration L0.5-8 (keV) = 1.6 x 10(37) erg s(-1), can be well described by a blackbody with kT(bb) similar to 1.6 keV and R-bb similar to 5 km. While an evolution in temperature of the blackbody can be appreciated throughout the burst (average peak kT(bb) = 2.5(-0.4)(+0.8) keV to tail kT(bb) = 1.3(-0.1)(+0.2) keV), the relative emitting surface shows no evolution. The overall persistent and type-I burst properties observed during the Chandra observation are consistent with what was previously reported during the 2009 outburst of IGR J17511-3057.
Keywords: accretion; accretion disks; pulsars: individual (IGR J17511-3057); stars: neutron; X-rays: binaries; X-rays: bursts

A CLUMPY STELLAR WIND AND LUMINOSITY-DEPENDENT CYCLOTRON LINE REVEALED BY THE FIRST SUZAKU OBSERVATION OF THE HIGH-MASS X-RAY BINARY 4U 1538-522 - Hemphill, Paul B.; Rothschild, Richard E.; Markowitz, Alex; Fuerst, Felix; Pottschmidt, Katja; Wilms, Jörn (Astrophysical Journal, 2014)
We present results from the first Suzaku observation of the high-mass X-ray binary 4U 1538-522. The broadband spectral coverage of Suzaku allows for a detailed spectral analysis, characterizing the cyclotron resonance scattering feature at 23.0 +/- 0.4 keV and the iron K alpha line at 6.426 +/- 0.008 keV, as well as placing limits on the strengths of the iron K beta line and the iron K edge. We track the evolution of the spectral parameters both in time and in luminosity, notably finding a significant positive correlation between cyclotron line energy and luminosity. A dip and spike in the light curve is shown to be associated with an order-of-magnitude increase in column density along the line of sight, as well as significant variation in the underlying continuum, implying the accretion of a overdense region of a clumpy stellar wind. We also present a phase-resolved analysis, with most spectral parameters of interest showing significant variation with phase. Notably, both the cyclotron line energy and the iron K alpha line intensity vary significantly with phase, with the iron line intensity significantly out of phase with the pulse profile. We discuss the implications of these findings in the context of recent work in the areas of accretion column physics and cyclotron resonance scattering feature formation.
Keywords: pulsars: individual (4U 1538-522); stars: magnetic field; stars: oscillations; X-rays: binaries; X-rays: stars

A COMPREHENSIVE SPECTRAL ANALYSIS OF THE X-RAY PULSAR 4U 1907+09 FROM TWO OBSERVATIONS WITH THE SUZAKU X-RAY OBSERVATORY - Rivers, Elizabeth; Markowitz, Alex; Pottschmidt, Katja; Roth, Stefanie; Barragan, Laura; Fürst, Felix; Suchy, Slawomir; Kreykenbohm, Ingo; Wilms, Jörn; Rothschild, Richard (Astrophysical Journal, 2010)
We present results from two observations of the wind-accreting X-ray pulsar 4U 1907+09 using the Suzaku Observatory. The broadband time-averaged spectrum allows us to examine the continuum emission of the source and the cyclotron resonance scattering feature at similar to 19 keV. Additionally, using the narrow CCD response of Suzaku near 6 keV allows us to study in detail the Fe K bandpass and to quantify the Fe K beta line for this source for the first time. The source is absorbed by fully covering material along the line of sight with a column density of N-II similar to 2 x 10(22) cm(-2), consistent with a wind-accreting geometry, and a high Fe abundance (similar to 3-4 times solar). Time-and phase-resolved analyses allow us to study variations in the source spectrum. In particular, dips found in the 2006 observation which are consistent with earlier observations occur in the hard X-ray bandpass, implying a variation of the whole continuum rather than occultation by intervening material, while a dip near the end of the 2007 observation occurs mainly in the lower energies implying an increase in N-H along the line of sight, perhaps indicating clumpiness in the stellar wind.
Keywords: pulsars: individual (4U 1907+09); stars: magnetic field; X-rays: binaries; X-rays: stars

A detailed look at the thermal and nonthermal X-ray emission from the Vela supernova remnant with SRG/eROSITA - Mayer, Martin G.F.; Becker, Werner; Predehl, Peter; Sasaki, Manami (Astronomy & Astrophysics, 2023)
Context.The Vela supernova remnant (SNR) is one of the most nearby and extended objects in the X-ray sky. It constitutes a unique laboratory for studying the thermal and nonthermal X-ray emission from an evolved SNR and its central plerion at an unprecedented level of detail. Aims.Our goal is to characterize the hot ejecta and shocked interstellar medium (ISM) associated with the Vela SNR, as well as the synchrotron-emitting relativistic electrons injected into the ambient medium by the central pulsar. To achieve this, we analyzed the dataset of Vela acquired by SRG/eROSITA during its first four all-sky surveys. Methods.We present and analyze the energy-dependent morphology of Vela using X-ray images extracted in multiple energy bands. A quantitative view of the physical parameters affecting the observed thermal and nonthermal emission is obtained by performing spatially resolved X-ray spectroscopy of over 500 independent regions using multicomponent spectral models. Results.Imaging demonstrates that the X-ray emission of the Vela SNR consists of at least three morphologically and energetically distinct components, with shell-like structures dominating below 0.6 keV, radial outward-directed features becoming apparent at medium energies, and the pulsar wind nebula (PWN) dominating the hard emission above 1.4 keV. Our spectroscopy reveals a highly structured distribution of X-ray absorption column densities, which intriguingly appears to lack any correlation with optical extinction measurements, possibly due to dust destruction or a clumpy ISM. The shock-heated plasma in Vela is found to be comparatively cool, with a median temperature of 0.19 keV, but exhibits several, often ejecta-rich, warmer regions. Within the observed ejecta clumps, we find an unexpectedly high concentration of neon and magnesium relative to oxygen, when compared to nucleosynthetic predictions. This includes the bright shrapnel D , in which we can separate shocked ISM in the soft bow-shock from a hot, ejecta-rich clump at its apex, based on the new data. Finally, we find an extremely extended, smoothly decreasing distribution of synchrotron emission from the PWN, which extends up to three degrees (14 pc) from the pulsar. The integrated X-ray luminosity of the PWN in the 0.5 8.0 keV energy band corresponds to 1.5 10-3 of the pulsar s present-day spin-down power. The extended PWN emission likely traces the diffusion of a high-energy electron population in an ISM-level magnetic field, which requires the existence of a TeV counterpart powered by inverse Compton radiation.
CRIS-Team Scopus Importer:2023-12-08
Keywords: ISM: abundances; ISM: supernova remnants; Pulsars: individual: B0833-45; X-rays: individuals: Vela

A detailed study on the reflection component for the black hole candidate MAXI J1836-194 - Dong, Yanting; Garcia, Javier; Liu, Zhu; Zhao, Xueshan; Zheng, Xueying; Gou, Lijun (Monthly Notices of the Royal Astronomical Society, 2020)
We present a detailed spectral analysis of the black hole candidate MAXI J1836-194. The source was caught in the intermediate state during its 2011 outburst by Suzaku and RXTE. We jointly fit the X-ray data from these two missions using the relxill model to study the reflection component, and a steep inner emissivity profile indicating a compact corona as the primary source is required in order to achieve a good fit. In addition, a reflection model with a lamp-post configuration (relxilllp), which is normally invoked to explain the steep emissivity profile, gives a worse fit and is excluded at 99 per cent confidence level compared to relxill. We also explore the effect of the ionization gradient on the emissivity profile by fitting the data with two relativistic reflection components, and it is found that the inner emissivity flattens. These results may indicate that the ionization state of the disc is not constant. All the models above require a supersolar iron abundance higher than ∼4.5. However, we find that the high-density version of reflionx can describe the same spectra even with solar iron abundance well. A moderate rotating black hole = 0.84-0.94) is consistently obtained by our models, which is in agreement with previously reported values.
CRIS-Team Scopus Importer:2021-04-19
Keywords: accretion; accretion discs; black hole physics; relativistic processes; X-rays: individual: MAXI J1836-194

A DOUBLE-PEAKED OUTBURST OF A 0535+26 OBSERVED WITH INTEGRAL, RXTE, AND SUZAKU - Caballero, I.; Pottschmidt, K.; Marcu, D. M.; Barragan, L.; Ferrigno, C.; Klochkov, D.; Heras, J. A. Zurita; Suchy, S.; Wilms, Jörn; Kretschmar, Peter; Santangelo, A.; Kreykenbohm, Ingo; et al. (Astrophysical Journal Letters, 2013)
The Be/X-ray binary A 0535+26 showed a normal (type I) outburst in 2009 August. It is the fourth in a series of normal outbursts associated with the periastron, but is unusual because it presented a double-peaked light curve. The two peaks reached a flux of similar to 450 mCrab in the 15-50 keV range. We present results of the timing and spectral analysis of INTEGRAL, RXTE, and Suzaku observations of the outburst. The energy-dependent pulse profiles and their evolution during the outburst are studied. No significant differences with respect to other normal outbursts are observed. The centroid energy of the fundamental cyclotron line shows no significant variation during the outburst. A spectral hardening with increasing luminosity is observed. We conclude that the source is accreting in the sub-critical regime. We discuss possible explanations for the double-peaked outburst.
Keywords: pulsars: individual (A 0535+26); stars: magnetic field; X-rays: binaries; X-rays: stars

Advances in Understanding High-Mass X-ray Binaries with INTEGRALand Future Directions - Kretschmar, Peter; Furst, Felix; Sidoli, Lara; Bozzo, Enrico; Alfonso-Garzon, Julia; Bodaghee, Arash; Chaty, Sylvain; Chernyakova, Masha; Ferrigno, Carlo; Manousakis, Antonios; Negueruela, Ignacio; Postnov, Konstantin; et al. (New Astronomy Reviews, 2019)
High mass X-ray binaries are among the brightest X-ray sources in the Milky Way, as well as in nearby Galaxies. Thanks to their highly variable emissions and complex phenomenology, they have attracted the interest of the high energy astrophysical community since the dawn of X-ray Astronomy. In more recent years, they have challenged our comprehension of physical processes in many more energy bands, ranging from the infrared to very high energies. In this review, we provide a broad but concise summary of the physical processes dominating the emission from high mass X-ray binaries across virtually the whole electromagnetic spectrum. These comprise the interaction of stellar winds with the high gravitational and magnetic fields of compact objects, the behaviour of matter under extreme magnetic and gravity conditions, and the perturbation of the massive star evolutionary processes by presence in a binary system. We highlight the role of the INTEGRAL mission in the discovery of many of the most interesting objects in the high mass X-ray binary class and its contribution in reviving the interest for these sources over the past two decades. We show how the INTEGRAL discoveries have not only contributed to significantly increase the number of high mass X-ray binaries known, thus advancing our understanding of the population as a whole, but also have opened new windows of investigation that stimulated the multi-wavelength approach nowadays common in most astrophysical research fields. We conclude the review by providing an overview of future facilities being planned from the X-ray to the very high energy domain that will hopefully help us in finding an answer to the many questions left open after more than 18 years of INTEGRAL scientific observations.
CRIS-Team Scopus Importer:2021-04-20
Keywords: accretion; gamma rays: observations; INTEGRAL observatory; pulsars: general; stars: neutron; X-rays: binaries

A first search for coincident gravitational waves and high energy neutrinos using LIGO, Virgo and ANTARES data from 2007 - Adrian-Martinez, S.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Astraatmadja, T.; Aubert, J-J.; Baret, B.; Basa, S.; et al. (Journal of Cosmology and Astroparticle Physics, 2013)
We present the results of the first search for gravitational wave bursts associated with high energy neutrinos. Together, these messengers could reveal new, hidden sources that are not observed by conventional photon astronomy, particularly at high energy. Our search uses neutrinos detected by the underwater neutrino telescope ANTARES in its 5 line configuration during the period January - September 2007, which coincided with the fifth and first science runs of LIGO and Virgo, respectively. The LIGO-Virgo data were analysed for candidate gravitational-wave signals coincident in time and direction with the neutrino events. No significant coincident events were observed. We place limits on the density of joint high energy neutrino - gravitational wave emission events in the local universe, and compare them with densities of merger and core-collapse events.
Keywords: gravitational waves / experiments; neutrino astronomy

A full characterization of the supermassive black hole in IRAS09149-6206 - Walton, D. J.; Alston, W. N.; Kosec, P.; Fabian, A. C.; Gallo, L. C.; Garcia, J. A.; Miller, J. M.; Nardini, E.; Reynolds, M. T.; Ricci, C.; Stern, D.; Dauser, Thomas; et al. (Monthly Notices of the Royal Astronomical Society, 2020)
We present new broad-band X-ray observations of the type-I Seyfert galaxy IRAS 09149-6206, taken in 2018 with XMM- Newton, NuSTAR, and Swift. The source is highly complex, showing a classic 'warm' X-ray absorber, additional absorption from highly ionized iron, strong relativistic reflection from the innermost accretion disc and further reprocessing by more distant material. By combining X-ray timing and spectroscopy, we have been able to fully characterize the supermassive black hole in this system, constraining both its mass and - for the first time - its spin. The mass is primarily determined by X-ray timing constraints on the break frequency seen in the power spectrum, and is found to be log [MBH/M⊙] = 8.0 ± 0.6 (1s uncertainties). This is in good agreement with previous estimates based on the Ha and Hβ line widths, and implies that IRAS 09149-6206 is radiating at close to (but still below) its Eddington luminosity. The spin is constrained via detailed modelling of the relativistic reflection, and is found to be a* = 0.94+0.02-0.07 (90 per cent confidence), adding IRAS 09149-6206 to the growing list of radio-quiet active galactic nuclei (AGNs) that host rapidly rotating black holes. The outflow velocities of the various absorption components are all relatively modest (vout ≤ 0.03c), implying these are unlikely to drive significant galaxy-scale AGN feedback.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Black hole physics; Galaxies: active; X-rays: individual (IRAS 09149-6206)

A Gaia Data Release 2 catalogue of white dwarfs and a comparison with SDSS - Fusillo, Nicola Pietro Gentile; Tremblay, Pier-Emmanuel; Gansicke, Boris T.; Manser, Christopher J.; Cunningham, Tim; Cukanovaite, Elena; Hollands, Mark; Marsh, Thomas; Raddi, Roberto; Jordan, Stefan; Toonen, Silvia; Geier, Stephan; et al. (Monthly Notices of the Royal Astronomical Society, 2019)
We present a catalogue of white dwarf candidates selected from the second data release of Gaia (DR2). We used a sample of spectroscopically confirmed white dwarfs from the Sloan Digital Sky Survey (SDSS) to map the entire space spanned by these objects in the Gaia Hertzsprung-Russell diagram. We then defined a set of cuts in absolute magnitude, colour, and a number of Gaia quality flags to remove the majority of contaminating objects. Finally, we adopt a method analogous to the one presented in our earlier SDSS photometric catalogues to calculate a probability of being a white dwarf (P-WD) for all Gaia sources that passed the initial selection. The final catalogue is composed of 486 641 stars with calculated P-WD from which it is possible to select a sample of similar or equal to 260 000 high-confidence white dwarf candidates in the magnitude range 8 < G < 21. By comparing this catalogue with a sample of SDSS white dwarf candidates, we estimate an upper limit in completeness of 85 per cent for white dwarfs with G <= 20 mag and T-eff > 7000 K, at high Galactic latitudes (vertical bar b vertical bar > 20 degrees). However, the completeness drops at low Galactic latitudes, and the magnitude limit of the catalogue varies significantly across the sky as a function of Gaia's scanning law. We also provide the list of objects within our sample with available SDSS spectroscopy. We use this spectroscopic sample to characterize the observed structure of the white dwarf distribution in the H-R diagram.
CRIS-Team WoS Importer:2019-04-09

A giant radio flare from Cygnus X-3 with associated ?-ray emission - Corbel, S.; Dubus, G.; Tomsick, J. A.; Szostek, A.; Corbet, R. H. D.; Miller-Jones, J. C. A.; Richards, J. L.; Pooley, G.; Trushkin, S.; Dubois, R.; Hill, A. B.; Kerr, M.; et al. (Monthly Notices of the Royal Astronomical Society, 2012)
With frequent flaring activity of its relativistic jets, Cygnus X-3 (Cyg X-3) is one of the most active microquasars and is the only Galactic black hole candidate with confirmed high-energy ?-ray emission, thanks to detections by Fermi Large Area Telescope (Fermi/LAT) and AGILE. In 2011, Cyg X-3 was observed to transit to a soft X-ray state, which is known to be associated with high-energy ?-ray emission. We present the results of a multiwavelength campaign covering a quenched state, when radio emission from Cyg X-3 is at its weakest and the X-ray spectrum is very soft. A giant (similar to 20 Jy) optically thin radio flare marks the end of the quenched state, accompanied by rising non-thermal hard X-rays. Fermi/LAT observations (E= 100 MeV) reveal renewed ?-ray activity associated with this giant radio flare, suggesting a common origin for all non-thermal components. In addition, current observations unambiguously show that the ?-ray emission is not exclusively related to the rare giant radio flares. A three-week period of ?-ray emission is also detected when Cyg X-3 was weakly flaring in radio, right before transition to the radio quenched state. No ?-rays are observed during the similar to 1-month long quenched state, when the radio flux is weakest. Our results suggest transitions into and out of the ultrasoft X-ray (radio-quenched) state trigger ?-ray emission, implying a connection to the accretion process, and also that the ?-ray activity is related to the level of radio flux (and possibly shock formation), strengthening the connection to the relativistic jets.
Keywords: black hole physics; stars: individual: Cyg X-3; ISM: jets and outflows; gamma-rays: stars; radio continuum: stars; X-rays: binaries

A giant X-ray dust scattering ring discovered with SRG/eROSITA around the black hole transient MAXI J1348-630 - Lamer, G.; Schwope, A. D.; Predehl, P.; Traulsen, I.; Wilms, Jörn; Freyberg, M. (Astronomy & Astrophysics, 2021)
We report the discovery of a giant dust scattering ring around the Black Hole transient MAXI J1348-630 with SRG/eROSITA during its first X-ray all-sky survey. During the discovery observation in February 2020, the ring had an outer diameter of 1.3 deg, growing to 1.6 deg by the time of the second all-sky survey scan in August 2020. This makes the new dust ring by far the largest X-ray scattering ring observed so far. Dust scattering halos, in particular the rings found around transient sources, provide an opportunity to make precise distance measurements towards the original X-ray sources. We combine data from SRG/eROSITA, XMM-Newton, MAXI, and Gaia to measure the geometrical distance of MAXI J1348-630. The Gaia data place the scattering dust at a distance of 2050 pc. Based on the measured time lags and the geometry of the ring we find MAXI J1348-630 at a distance of 3390 pc with a statistical uncertainty of only 1.1% and a systematic uncertainty of 10% caused mainly by the parallax offset of Gaia. This result makes MAXI J1348-630 one of the black hole transients with the most accurately determined distances. The new distance leads to a revised mass estimate for the black hole of 11 ± 2 MâŠ . The transition to the soft state during the outburst occurred when the bolometric luminosity of MAXI J1348-630 reached 1.7% of its Eddington luminosity.
CRIS-Team Scopus Importer:2021-03-19
Keywords: Dust; extinction; Stars: black holes; Stars: distances; Stars: individual: MAXI J1648-630; X-rays: binaries; X-rays: ISM

A global view of shocked plasma in the supernova remnant Puppis A provided by SRG/eROSITA star - Mayer, Martin G. F.; Becker, Werner; Predehl, Peter; Sasaki, Manami; Freyberg, Michael (Astronomy & Astrophysics, 2022)
Context. Puppis A is a medium-age supernova remnant (SNR), which is visible as a very bright extended X-ray source. While numerous studies have investigated individual features of the SNR, at this time, no comprehensive study of the entirety of its X-ray emission exists. Aims. Using field-scan data acquired by the SRG/eROSITA telescope during its calibration and performance verification phase, we aim to investigate the physical conditions of shocked plasma and the distribution of elements throughout Puppis A. In doing so, we take advantage of the uniform target coverage, excellent statistics, and decent spatial and spectral resolution of our data set. Methods. Using broad- and narrow-band imaging, we investigate the large-scale distribution of absorption and the plasma temperature as well as that of typical emission lines. This approach is complemented by a spatially resolved spectral analysis of the shocked plasma in Puppis A, for which we divided the SNR into around 700 distinct regions, resulting in maps of key physical quantities over its extent. Results. We find a strong peak of foreground absorption in the southwest quadrant, which in conjunction with high temperatures at the northeast rim creates the well-known strip of hard emission crossing Puppis A. Furthermore, using the observed distribution of ionization ages, we attempt to reconstruct the age of the shock in the individual regions. We find a rather recent shock interaction for the prominent northeast filament and ejecta knot, as well as for the outer edge of the bright eastern knot. Finally, elemental abundance maps reveal only a single clear enhancement of the plasma with ejecta material, consistent with a previously identified region, and no obvious ejecta enrichment in the remainder of the SNR. Within this region, we confirm the spatial separation of silicon-rich ejecta from those dominated by lighter elements. The apparent elemental composition of this ejecta-rich region would imply an unrealistically large silicon-to-oxygen ratio when compared to the integrated yield of a core-collapse supernova. In reality, both the observed ejecta composition and their apparent distribution may be biased by the unknown location and strength of the reverse shock.
CRIS-Team WoS Importer:2022-06-17

A halo blue straggler on a highly eccentric retrograde orbit - Tillich, A.; Przybilla, Norbert; Scholz, R. -D.; Heber, Ulrich (Astronomy & Astrophysics, 2010)
Context. Blue stragglers, which are stars that appear to be younger than they should be, are an important population of unusual stars in both stellar clusters and the halo field of the Galaxy. Most formation scenarios evoke either stellar collisions or binary stars that transfer mass or merge. Aims. We investigate high-velocity stars in the Galactic halo and perform a spectral and kinematical analysis to shed light on their nature and origin. Here we report that SDSSJ130005.62+042201.6 (J1300+0422 for short) is an A-type star of unusually large radial velocity (504.6 ± 5 km s-1). Methods. From a quantitative NLTE (and LTE) spectral analysis of medium-resolution optical spectra, the elemental composition is derived. Proper motion measurements combined with a spectroscopic distance estimate allow us to determine its present space velocity. Its kinematical properties are derived by integrating the equation of motion in the Galactic potential. Results. We find J1300+0422 to be metal poor ([M/H]=-1.2) and exhibit an α-element enrichment (0.3-0.4 dex) that is characteristic of the halo population, as confirmed by a kinematical analysis of its 3D space motions, which places it on a highly eccentric retrograde Galactic orbit. Conclusions. The mass of J1300+0422 (1.15 ± 0.10 &Modot) is higher than the globular cluster turn-off masses indicating that it is a halo blue straggler star. At a Galactic rest-frame velocity of ≈467 km s-1, the star travels faster than any known blue straggler but is still bound to the Galaxy. © 2010 ESO.
CRIS-Team Scopus Importer:2020-12-21
Keywords: Blue stragglers; Galaxy: halo; Stars: atmospheres; Stars: individual: SDSSJ130005.62+042201.6; Stars: kinematics and dynamics; Stars: Population II

A HARD X-RAY POWER-LAW SPECTRAL CUTOFF IN CENTAURUS X-4 - Chakrabarty, Deepto; Tomsick, John A.; Grefenstette, Brian W.; Psaltis, Dimitrios; Bachetti, Matteo; Barret, Didier; Boggs, Steven E.; Christensen, Finn E.; Craig, William W.; Fuerst, Felix; Hailey, Charles J.; Harrison, Fiona A.; et al. (Astrophysical Journal, 2014)
The low-mass X-ray binary (LMXB) Cen X-4 is the brightest and closest (<1.2 kpc) quiescent neutron star transient. Previous 0.5-10 keV X-ray observations of Cen X-4 in quiescence identified two spectral components: soft thermal emission from the neutron star atmosphere and a hard power-law tail of unknown origin. We report here on a simultaneous observation of Cen X-4 with NuSTAR (3-79 keV) and XMM-Newton (0.3-10 keV) in 2013 January, providing the first sensitive hard X-ray spectrum of a quiescent neutron star transient. The 0.3-79 keV luminosity was 1.1 x 10(33) D-kpc(2) erg s(-1), with similar or equal to 60% in the thermal component. We clearly detect a cutoff of the hard spectral tail above 10 keV, the first time such a feature has been detected in this source class. We show that thermal Comptonization and synchrotron shock origins for the hard X-ray emission are ruled out on physical grounds. However, the hard X-ray spectrum is well fit by a thermal bremsstrahlung model with kT(e) = 18 keV, which can be understood as arising either in a hot layer above the neutron star atmosphere or in a radiatively inefficient accretion flow. The power-law cutoff energy may be set by the degree of Compton cooling of the bremsstrahlung electrons by thermal seed photons from the neutron star surface. Lower thermal luminosities should lead to higher (possibly undetectable) cutoff energies. We compare Cen X-4's behavior with PSR J1023+0038, IGR J18245-2452, and XSS J12270-4859, which have shown transitions between LMXB and radio pulsar modes at a similar X-ray luminosity.
Keywords: accretion; accretion disks; binaries: close; stars: individual (Cen X-4); stars: neutron; X-rays: binaries

A highly magnetized twin-jet base pinpoints a supermassive black hole - Baczko, Anne-Kathrin; Schulz, Robert; Kadler, Matthias; Ros, Eduardo; Perucho, Manel; Krichbaum, T. P.; Boeck, M.; Bremer, M.; Großberger, Christoph; Lindqvist, M.; Lobanov, A. P.; Mannheim, K.; et al. (Astronomy & Astrophysics, 2016)
Supermassive black holes (SMBH) are essential for the production of jets in radio-loud active galactic nuclei (AGN). Theoretical models based on (Blandford & Znajek 1977, MNRAS, 179, 433) extract the rotational energy from a Kerr black hole, which could be the case for NGC 1052, to launch these jets. This requires magnetic fields on the order of 10G to 10G. We imaged the vicinity of the SMBH of the AGN NGC 1052 with the Global Millimetre VLBI Array and found a bright and compact central feature that is smaller than 1.9 light days (100 Schwarzschild radii) in radius. Interpreting this as a blend of the unresolved jet bases, we derive the magnetic field at 1 Schwarzschild radius to lie between 200 G and 8.3 × 10 G consistent with Blandford & Znajek models.
Keywords: Galaxies: active; Galaxies: jets; Galaxies: magnetic fields; Galaxies: nuclei; Magnetic fields

A hot subdwarf-white dwarf super-Chandrasekhar candidate supernova Ia progenitor - Pelisoli, Ingrid; Neunteufel, P.; Geier, S.; Kupfer, T.; Heber, Ulrich; Irrgang, Andreas; Schneider, David; Bastian, A.; Van Roestel, J.; Schaffenroth,; Barlow, B. N. (Nature Astronomy, 2021)
Supernovae Ia are bright explosive events that can be used to estimate cosmological distances, allowing us to study the expansion of the Universe. They are understood to result from a thermonuclear detonation in a white dwarf that formed from the exhausted core of a star more massive than the Sun. However, the possible progenitor channels leading to an explosion are a long-standing debate, limiting the precision and accuracy of supernovae Ia as distance indicators. Here we present HD 265435, a binary system with an orbital period of less than a hundred minutes that consists of a white dwarf and a hot subdwarf, which is a stripped core-helium-burning star. The total mass of the system is 1.65 +/- 0.25 solar masses, exceeding the Chandrasekhar limit (the maximum mass of a stable white dwarf). The system will merge owing to gravitational wave emission in 70 million years, likely triggering a supernova Ia event. We use this detection to place constraints on the contribution of hot subdwarf-white dwarf binaries to supernova Ia progenitors.
CRIS-Team WoS Importer:2021-07-23

AIP Conference Proceedings: Preface - Schuh, Sonja; Drechsel, Horst; Heber, Ulrich (AIP Conference Proceedings, 2011)
CRIS-Team Scopus Importer:2020-12-21

All-flavor Search for a Diffuse Flux of Cosmic Neutrinos with Nine Years of ANTARES Data - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. -J.; Aublin, J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Belhorma, B.; et al. (Astrophysical Journal Letters, 2018)
The ANTARES detector is at present the most sensitive neutrino telescope in the northern hemisphere. The highly significant cosmic neutrino excess observed by the Antarctic IceCube detector can be studied with ANTARES, exploiting its complementing field of view, exposure, and lower energy threshold. Searches for an all-flavor diffuse neutrino signal, covering nine years of ANTARES data taking, are presented in this Letter. Upward-going events are used to reduce the atmospheric muon background. This work includes for the first time in ANTARES both track-like (mainly nu mu) and shower-like (mainly nu(e)) events in this kind of analysis. Track-like events allow for an increase of the effective volume of the detector thanks to the long path traveled by muons in rock and/ or sea water. Shower-like events are well reconstructed only when the neutrino interaction vertex is close to, or inside, the instrumented volume. A mild excess of high-energy events over the expected background is observed in nine years of ANTARES data in both samples. The best fit for a single power-law cosmic neutrino spectrum, in terms of perflavor flux at 100 TeV, is Phi(1f)(0) (100 TeV) = (1.7 +/- 1.0) x 10(-18) GeV-1 cm(-2) s(-1) sr(-1) with spectral index Gamma = 2.4(-0.4)(+0.5) .The null cosmic flux assumption is rejected with a significance of 1.6 sigma .
Keywords: astroparticle physics; neutrinos

All-sky search for high-energy neutrinos from gravitational wave event GW170104 with the Antares neutrino telescope: The ANTARES Collaboration - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. -J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Belhorma, B.; Bertin, V.; et al. (European Physical Journal C, 2017)
Advanced LIGO detected a significant gravitational wave signal (GW170104) originating from the coalescence of two black holes during the second observation run on January 4th, 2017. Anall-sky high-energy neutrino follow-up search has been made using data from the Antares neutrino telescope, including both upgoing and downgoing events in two separate analyses. No neutrino candidates were found within +/- 500 s around the GW event time nor any time clustering of events over an extended time window of +/- 3 months. The non-detection is used to constrain isotropic-equivalent high-energy neutrino emission from GW170104 to less than similar to 1.2 x 10(55) erg for a E-2 spectrum. This constraint is valid in the energy range corresponding to the 5-95% quantiles of the neutrino flux [3.2 TeV; 3.6 PeV], if the GW emitter was below the Antares horizon at the alert time.

ALMA CO observations of a giant molecular cloud in M33: Evidence for high-mass star formation triggered by cloud-cloud collisions - Sano, Hidetoshi; Tsuge, Kisetsu; Tokuda, Kazuki; Muraoka, Kazuyuki; Tachihara, Kengo; Yamane, Yumiko; Kohno, Mikito; Fujita, Shinji; Enokiya, Rei; Rowell, Gavin; Maxted, Nigel; Filipovic, Miroslav D.; et al. (Publications of the Astronomical Society of Japan, 2021)
We report the first evidence for high-mass star formation triggered by collisions of molecular clouds in M33. Using the Atacama Large Millimeter/submillimeter Array, we spatially resolved filamentary structures of giant molecular cloud 37 in M33 using (CO)-C-12(J = 2-1), (CO)-C-13(J = 2-1), and (CO)-O-18(J = 2-1) line emission at a spatial resolution of similar to 2pc. There are two individual molecular clouds with a systematic velocity difference of similar to 6kms(-1). Three continuum sources representing up to similar to 10 high-mass stars with spectral types of B0V-O7.5V are embedded within the densest parts of molecular clouds bright in the (CO)-O-18(J = 2-1) line emission. The two molecular clouds show a complementary spatial distribution with a spatial displacement of similar to 6.2pc, and show a V-shaped structure in the position-velocity diagram. These observational features traced by CO and its isotopes are consistent with those in high-mass star-forming regions created by cloud-cloud collisions in the Galactic and Magellanic Cloud H II regions. Our new finding in M33 indicates that cloud-cloud collision is a promising process for triggering high-mass star formation in the Local Group.
CRIS-Team WoS Importer:2021-05-28

ALMA CO Observations of Gamma-Ray Supernova Remnant N132D in the Large Magellanic Cloud: Possible Evidence for Shocked Molecular Clouds Illuminated by Cosmic-Ray Protons - Sano, Hidetoshi; Plucinsky, P. P.; Bamba, A.; Sharda, P.; Filipovic, M. D.; Law, C. J.; Alsaberi, R. Z. E.; Yamane, Y.; Tokuda, K.; Acero, F.; Sasaki, Manami; Vink, J.; et al. (Astrophysical Journal, 2020)
N132D is the brightest gamma-ray supernova remnant (SNR) in the Large Magellanic Cloud (LMC). We carried out(12)CO(J = 1-0, 3-2) observations toward the SNR using the Atacama Large Millimeter/submillimeter Array (ALMA) and Atacama Submillimeter Telescope Experiment. We find diffuse CO emission not only at the southern edge of the SNR as previously known, but also inside the X-ray shell. We spatially resolved nine molecular clouds using ALMA with an angular resolution of 5 '', corresponding to a spatial resolution of similar to 1 pc at the distance of the LMC. Typical cloud sizes and masses are similar to 2.0 pc and similar to 100M, respectively. High intensity ratios of COJ = 3-2/1-0 > 1.5 are seen toward the molecular clouds, indicating that shock heating has occurred. Spatially resolved X-ray spectroscopy reveals that thermal X-rays in the center of N132D are produced not only behind a molecular cloud but also in front of it. Considering the absence of a thermal component associated with the forward shock toward one molecular cloud located along the line of sight to the center of the remnant, this suggests that this particular cloud is engulfed by shock waves and is positioned on the near side of the remnant. If the hadronic process is the dominant contributor to the gamma-ray emission, the shock-engulfed clouds play a role as targets for cosmic rays. We estimate the total energy of cosmic-ray protons accelerated in N132D to be similar to 0.5-3.8 x 10(49)erg as a conservative lower limit, which is similar to that observed in Galactic gamma-ray SNRs.
CRIS-Team WoS Importer:2020-10-30

ALMA CO Observations of Supernova Remnant N63A in the Large Magellanic Cloud: Discovery of Dense Molecular Clouds Embedded within Shock-ionized and Photoionized Nebulae - Sano, H.; Matsumura, H.; Nagaya, T.; Yamane, Y.; Alsaberi, R. Z. E.; Filipovic, M. D.; Tachihara, K.; Fujii, K.; Tokuda, K.; Tsuge, K.; Yoshiike, S.; Onishi, T.; et al. (Astrophysical Journal, 2019)
We carried out new (CO)-C-12(J = 1-0, 3-2) observations of a N63A supernova remnant (SNR) from the LMC using the Atacama Large Millimeter/submillimeter Array (ALMA) and Atacama Submillimeter Telescope Experiment. We find three giant molecular clouds toward the northeast, east, and near the center of the SNR. Using the ALMA data, we spatially resolved clumpy molecular clouds embedded within the optical nebulae in both the shock-ionized and photoionized lobes discovered by previous H alpha and [S II] observations. The total mass of the molecular clouds is similar to 800 M-circle dot for the shock-ionized region and similar to 1700 M-circle dot for the photoionized region. Spatially resolved X-ray spectroscopy reveals that the absorbing column densities toward the molecular clouds are similar to(1.5-6.0) x 10(21) cm(-2), which are similar to 1.5-15 times less than the averaged interstellar proton column densities for each region. This means that the X-rays are produced not only behind the molecular clouds, but also in front of them. We conclude that the dense molecular clouds have been completely engulfed by the shock waves, but have still survived erosion owing to their high density and short interacting time. The X-ray spectrum toward the gas clumps is well explained by an absorbed power-law model or a high-temperature plasma model, in addition to thermal plasma components, implying that the shock-cloud interaction is efficiently working for both cases through the shock ionization and magnetic field amplification. If the hadronic gamma-ray is dominant in the GeV. band, the total energy of the cosmic-ray protons is calculated to be similar to(0.3-1.4) x 10(49) erg, with an estimated interstellar proton density of similar to 190 +/- 90 cm(-3), containing both the shock-ionized gas and neutral atomic hydrogen.
CRIS-Team WoS Importer:2019-03-15

A low-flux state in IRAS 00521−7054 seen with NuSTAR and XMM-Newton: Relativistic reflection and an ultrafast outflow - Walton, D. J.; Nardini, Emanuele; Gallo, L. C.; Reynolds, M. T.; Ricci, C.; Dauser, Thomas; Fabian, A. C.; Garcia, Javier; Harrison, F. A.; Risaliti, G.; Stern, D. (Monthly Notices of the Royal Astronomical Society, 2019)
We present results from a deep, coordinated XMM-Newton + NuSTAR observation of the Seyfert 2 galaxy IRAS 00521−7054. The NuSTAR data provide the first detection of this source in high-energy X-rays (E > 10 keV), and the broad-band data show this to be a highly complex source which exhibits relativistic reflection from the inner accretion disc, further reprocessing by more distant material, neutral absorption, and evidence for ionized absorption in an extreme, ultrafast outflow (vout ∼ 0.4c). Based on lamppost disc reflection models, we find evidence that the central supermassive black hole is rapidly rotating (a > 0.77), consistent with previous estimates from the profile of the relativistic iron line, and that the accretion disc is viewed at a fairly high inclination (i ∼ 59◦). Based on extensive simulations, we find the ultrafast outflow is detected at ∼4σ significance (or greater). We also estimate that the extreme outflow should be sufficient to power galaxy-scale feedback, and may even dominate the energetics of the total output from the system.
CRIS-Team Scopus Importer:2021-04-20
Keywords: Black hole physics; Galaxies: active; X-rays: individual: (IRAS 00521−7054)

A MeerKAT, e-MERLIN, HESS, and Swift search for persistent and transient emission associated with three localized FRBs - Chibueze, J. O.; Caleb, M.; Spitler, L.; Ashkar, H.; Schussler, F.; Stappers, B. W.; Venter, C.; Heywood,; Richards, A. M. S.; Williams, D. R. A.; Kramer, M.; Beswick, R.; et al. (Monthly Notices of the Royal Astronomical Society, 2022)
We report on a search for persistent radio emission from the one-off fast radio burst (11(B) 20190714A, as well as from two repeating FRBs, 20190711A and 20171019A, using the MeerKAT radio telescope. For FRB 20171019A, we also conducted simultaneous observations with the High-Energy Stereoscopic System (H.E.S.S.) in very high-energy gamma rays and searched for signals in the ultraviolet, optical, and X-ray bands. For this FRB, we obtain a UV flux upper limit of 1.39 x 10(-16) erg cm(-2) s(-1) angstrom(-1), X-ray limit of similar to 6.6 x 10(-14) erg cm(-2) s(-1) and a limit on the very high energy gamma-ray flux Phi(E > 120 GeV) < 1.7 x 10(-12) erg cm(-2) S-1. We obtain a radio upper limit of similar to 15 mu Jy beam(-1) for persistent emission at the locations of both FRBs 20190711A and 20171019A with MeerKAT. However, we detected an almost unresolved (ratio of integrated flux to peak flux is similar to 1.7 beam) radio emission, where the synthesized beam size was similar to 8 arcsec size with a peak brightness of similar to 53 mu Jy beam(-1) at MeerKAT and similar to 86 mu Jy beam(-1) at e-MERLIN, possibly associated with FRB 20190714A at z = 0.2365. This represents the first detection of persistent continuum radio emission potentially associated with a (as-yet) non- repeating FRB. If the association is confirmed, one of the strongest remaining distinction between repeaters and non-repeaters would no longer be applicable. A parallel search for repeat bursts from these FRBs revealed no new detections down to a fluence of 0.08 Jy ms for a 1 ms duration burst.
CRIS-Team WoS Importer:2022-08-05

A method for detection of muon induced electromagnetic showers with the ANTARES detector - Aguilar, J. A.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Jesus, A. C. Assis; Astraatmadja, T.; Auberth, J. J.; Baret, B.; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2012)
The primary aim of ANTARES is neutrino astronomy with upward going muons created in charged current muon neutrino interactions in the detector and its surroundings. Downward going muons are background for neutrino searches. These muons are the decay products of cosmic-ray collisions in the Earth's atmosphere far above the detector. This paper presents a method to identify and count electromagnetic showers induced along atmospheric muon tracks with the ANTARES detector. The method is applied to both cosmic muon data and simulations and its applicability to the reconstruction of muon event energies is demonstrated. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Neutrino telescope; Electromagnetic shower identification; High energy muons; Energy reconstruction

A method to stabilise the performance of negatively fed KM3NeT photomultipliers - Adrián-Martínez, S.; Ageron, M.; Aiello, S.; Albert, A.; Ameli, F.; Anassontzis, E. G.; Andre, M.; Androulakis, G.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Avgitas, T.; et al. (Journal of Instrumentation, 2016)
The KM3NeT research infrastructure, currently under construction in the Mediterranean Sea, will host neutrino telescopes for the identification of neutrino sources in the Universe and for studies of the neutrino mass hierarchy. These telescopes will house hundreds of thousands of photomultiplier tubes that will have to be operated in a stable and reliable fashion. In this context, the stability of the dark counts has been investigated for photomultiplier tubes with negative high voltage on the photocathode and held in insulating support structures made of 3D printed nylon material. Small gaps between the rigid support structure and the photomultiplier tubes in the presence of electric fields can lead to discharges that produce dark count rates that are highly variable. A solution was found by applying the same insulating varnish as used for the high voltage bases directly to the outside of the photomultiplier tubes. This transparent conformal coating provides a convenient and inexpensive method of insulation.
Keywords: Instrument optimization; Large detector systems for particle and astroparticle physics; Neutrino detectors; Photon detectors for UV; visible and IR photons (gas) (gas-photocathodes; solid-photocathodes)

A model for cyclotron resonance scattering features - Wilms, Jörn; et al. (Astronomy & Astrophysics, 2007)
Aims. We study the physics of cyclotron line formation in the high-energy spectra of accreting X-ray pulsars. In particular, we link numerical predictions for the line profiles to results from observational data analysis. Therefore, first we investigate the theoretical predictions and the significance of our model parameters, and second we aim at the development of a model to fit cyclotron lines in observational data.Methods. Simulations were performed using Monte Carlo methods. The data were extracted with HEADAS 6.1.1 and INTEGRAL OSA 5.1. A convolution model for the cyclotron line shapes was implemented for the XSPEC spectral analysis software package and for data packages compatible with XSPEC local models.Results. We predict the shapes of cyclotron lines for different prescribed physical settings. The calculations assume that the line-forming region is a low-density electron plasma, which is of cylindrical or slab geometry and which is exposed to a uniform, sub-critical magnetic field. We investigate the dependence of the shape of the fundamental line on angle, geometry, optical depth and temperature. We also discuss variations of the line ratios for non-uniform magnetic fields. We have developed a new convolution and interpolation model to simulate line features regardless of any a priori assumed shape of the neutron star continuum. Fitting RXTE and INTEGRAL data of the accreting X-ray pulsar V0332+ 53 with this model gives a qualitative description of the data. Strong emission wings of the fundamental cyclotron feature as predicted by internally irradiated plasma geometries are in principle observable by todays instruments but are not formed in V0332+ 53, hinting at a bottom illuminated slab geometry for line formation.
Keywords: X-rays : binaries; stars : neutron; accretion; accretion disks; magnetic fields; line : formation; methods : numerical

A MULTIWAVELENGTH STUDY OF CYGNUS X-1: THE FIRST MID-INFRARED SPECTROSCOPIC DETECTION OF COMPACT JETS - Rahoui, Farid; Lee, Julia C.; Heinz, Sebastian; Hines, Dean C.; Pottschmidt, Katja; Wilms, Jörn; Grinberg, Victoria (Astrophysical Journal, 2011)
We report on a Spitzer/InfraRed Spectrograph (mid-infrared), RXTE/PCA+HEXTE (X-ray), and Ryle (radio) simultaneous multiwavelength study of the microquasar Cygnus X-1, which aimed at an investigation of the origin of its mid-infrared emission. Compact jets were present in two out of three observations, and we show that they strongly contribute to the mid-infrared continuum. During the first observation, we detect the spectral break-where the transition from the optically thick to the optically thin regime takes place-at about 2.9x10(13) Hz. We then show that the jet's optically thin synchrotron emission accounts for Cygnus X-1's emission beyond 400 keV, although it cannot alone explain its 3-200 keV continuum. A compact jet was also present during the second observation, but we do not detect the break, since it has likely shifted to higher frequencies. In contrast, the compact jet was absent during the last observation, and we show that the 5-30 mu m mid-infrared continuum of Cygnus X-1 stems from the blue supergiant companion star HD 226868. Indeed, the emission can then be understood as the combination of the photospheric Rayleigh-Jeans tail and the bremsstrahlung from the expanding stellar wind. Moreover, the stellar wind is found to be clumpy, with a filling factor f(infinity) approximate to 0.09-0.10. Its bremsstrahlung emission is likely anti-correlated to the soft X-ray emission, suggesting an anti-correlation between the mass-loss and mass-accretion rates. Nevertheless, we do not detect any mid-infrared spectroscopic evidence of interaction between the jets and Cygnus X-1's environment and/or the companion star's stellar wind.
Keywords: binaries: close; dust; extinction; infrared: stars; stars: individual (Cygnus X-1); X-rays: binaries

An accreting pulsar with extreme properties drives an ultraluminous x-ray source in NGC 5907 - Israel, Gian Luca; Belfiore, Andrea; Stella, Luigi; Esposito, Paolo; Casella, Piergiorgio; De Luca, Andrea; Marelli, Martino; Papitto, Alessandro; Perri, Matteo; Puccetti, Simonetta; Rodriguez Castillo, Guillermo A.; Salvetti, David; et al. (Science, 2017)
Ultraluminous x-ray sources (ULXs) in nearby galaxies shine brighter than any x-ray source in our Galaxy. ULXs are usually modeled as stellar-mass black holes (BHs) accreting at very high rates or intermediate-mass BHs. We present observations showing that NGC 5907 ULX is instead an x-ray accreting neutron star (NS) with a spin period evolving from 1.43 seconds in 2003 to 1.13 seconds in 2014. It has an isotropic peak luminosity of similar to 1000 times the Eddington limit for a NS at 17.1 megaparsec. Standard accretion models fail to explain its luminosity, even assuming beamed emission, but a strong multipolar magnetic field can describe its properties. These findings suggest that other extreme ULXs (x-ray luminosity >= 1041 erg second(-1)) might harbor NSs.

An algorithm for the reconstruction of high-energy neutrino-induced particle showers and its application to the ANTARES neutrino telescope - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, Miguel; Aubert, J. -J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; et al. (European Physical Journal C, 2017)
A novel algorithm to reconstruct neutrino-induced particle showers within the ANTARES neutrino telescope is presented. The method achieves a median angular resolution of 6. for shower energies below 100TeV. Applying this algorithm to 6 years of data taken with theANTARES detector, 8 events with reconstructed shower energies above 10TeV are observed. This is consistent with the expectation of about 5 events from atmospheric backgrounds, but also compatible with diffuse astrophysical flux measurements by the IceCube collaboration, from which 2-4 additional events are expected. A 90% C.L. upper limit on the diffuse astrophysical neutrino flux with a value per neutrino flavour of E-2.Phi(90%) = 4.9 . 10(-8) GeV.cm(-2).s(-1).sr(-1) is set, applicable to the energy range from 23TeV to 7.8PeV, assuming an unbroken E-2 spectrum and neutrino flavour equipartition at Earth.

An Algorithm for the Reconstruction of Neutrino-induced Showers in the ANTARES Neutrino Telescope - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. -J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Belhorma, B.; Bertin, V.; et al. (Astronomical Journal, 2017)
Muons created by nu(mu) charged current (CC) interactions in the water surrounding the ANTARES neutrino telescope have been almost exclusively used so far in searches for cosmic neutrino sources. Due to their long range, highly energetic muons inducing Cherenkov radiation in the water are reconstructed with dedicated algorithms that allow for the determination of the parent neutrino direction with a median angular resolution of about 0 degrees.4 for an E-2 neutrino spectrum. In this paper, an algorithm optimized for accurate reconstruction of energy and direction of shower events in the ANTARES detector is presented. Hadronic showers of electrically charged particles are produced by the disintegration of the nucleus both in CC and neutral current interactions of neutrinos in water. In addition, electromagnetic showers result from the CC interactions of electron neutrinos while the decay of a tau lepton produced in nu(tau) CC interactions will, in most cases, lead to either a hadronic or an electromagnetic shower. A shower can be approximated as a point source of photons. With the presented method, the shower position is reconstructed with a precision of about 1 m; the neutrino direction is reconstructed with a median angular resolution between 2 degrees and 3 degrees in the energy range of 1-1000 TeV. In this energy interval, the uncertainty on the reconstructed neutrino energy is about 5%-10%. The increase in the detector sensitivity due to the use of additional information from shower events in the searches for a cosmic neutrino flux is also presented.
Keywords: neutrinos; telescopes

An ALMA Study of the Massive Molecular Clump N159W-North in the Large Magellanic Cloud: A Possible Gas Flow Penetrating One of the Most Massive Protocluster Systems in the Local Group - Tokuda, Kazuki; Minami, Taisei; Fukui, Yasuo; Inoue, Tsuyoshi; Nishioka, Takeru; Tsuge, Kisetsu; Zahorecz, Sarolta; Sano, Hidetoshi; Konishi, Ayu; Chen, C-H Rosie; Sewilo, Marta; Madden, Suzanne C.; et al. (Astrophysical Journal, 2022)
Massive dense clumps in the Large Magellanic Cloud can be an important laboratory to explore the formation of populous clusters. We report multiscale ALMA observations of the N159W-North clump, which is the most CO-intense region in the galaxy. High-resolution CO isotope and 1.3 mm continuum observations with an angular resolution of similar to 0.'' 25 (similar to 0.07 pc) revealed more than five protostellar sources with CO outflows within the main ridge clump. One of the thermal continuum sources, MMS-2, shows an especially massive/dense nature whose total H-2 mass and peak column density are similar to 10(4) M (circle dot) and similar to 10(24) cm(-2), respectively, and harbors massive (similar to 100 M (circle dot)) starless core candidates identified as its internal substructures. The main ridge containing this source can be categorized as one of the most massive protocluster systems in the Local Group. The CO high-resolution observations found several distinct filamentary clouds extending southward from the star-forming spots. The CO (1-0) data set with a larger field of view reveals a conical, similar to 30 pc long complex extending toward the northern direction. These features indicate that a large-scale gas compression event may have produced the massive star-forming complex. Based on the striking similarity between the N159W-North complex and the other two previously reported high-mass star-forming clouds in the nearby regions, we propose a "teardrops inflow model" that explains the synchronized, extreme star formation across >50 pc, including one of the most massive protocluster clumps in the Local Group.
CRIS-Team WoS Importer:2022-07-08

Analysis of two eclipsing hot subdwarf binaries with a low mass stellar and a brown dwarf companion - Schaffenroth, Veronika; Geier, Stephan; Heber, Ulrich; Drechsel, Horst; Østensen, Roy H.; Maxted, Pierre F.L.; Kupfer, Thomas; Barlow, Brad N. (AIP Conference Proceedings, 2011)
The formation of hot subdwarf stars (sdBs), which are core helium-burning stars located on the extended horizontal branch, is still not understood. Many of the known hot subdwarf stars reside in close binary systems with short orbital periods between a few hours and a few days with either M star or white dwarf companions. Common envelope ejection is the most probable formation channel. Among these, eclipsing systems are of special importance because it is possible to constrain the parameters of both components tightly by combining spectroscopic and light curve analyses. We report the discovery of two eclipsing binaries with a brown dwarf (<0.07 M⊙) and a 0.15 M ⊙ late main sequence star companion in close orbits around sdB stars. © 2011 American Institute of Physics.
CRIS-Team Scopus Importer:2020-12-21
Keywords: brown dwarf; eclipsing binaries; HW Vir; sdB

Analyzing X-ray pulsar profiles: geometry and beam pattern of A0535+26 - Caballero, Isabel; Kraus, Ute; Santangelo, Andrea; Sasaki, Manami; Kretschmar, Peter (Astronomy & Astrophysics, 2011)
Aims. We applied a decomposition method to the energy dependent pulse profiles of the accreting binary pulsar A 0535+26, in order to identify the contribution of the two magnetic poles of the neutron star and to obtain constraints on the geometry of the system and on the beam pattern. Methods. We analyzed pulse profiles obtained from RXTE observations in the X-ray regime. Basic assumptions of the method are that the asymmetry observed in the pulse profiles is caused by non-antipodal magnetic poles and that the emission regions have ax- isymmetric beam patterns. Results. Constraints on the geometry of the pulsar and a possible solution of the beam pattern are given. We interpreted the recon- structed beam pattern in terms of a geometrical model of a hollow column plus a halo of scattered radiation on the neutron star surface, which includes relativistic light deflection.
Keywords: X-rays: binaries; pulsars: individual: A0535+26

An ancient F-type subdwarf from the halo crossing the Galactic plane - Scholz, R. -D.; Heber, Ulrich; Heuser, Christian; Ziegerer, Eva; Geier, Stephan; Niederhofer, F (Astronomy & Astrophysics, 2015)
Aims. We selected the bluest object, WISE J0725-2351, from Luhman's new high proper motion (HPM) survey based on observations with the Wide-field Infrared Survey Explorer (WISE) for spectroscopic follow-up observations. Our aim was to unravel the nature of this relatively bright (V similar to 12, J similar to 11) HPM star (mu = 267 mas/yr).Methods. We obtained low-and medium-resolution spectra with the European Southern Observatory (ESO) New Technology Telescope (NTT)/EFOSC2 and Very Large Telescope (VLT)/X-Shooter instruments, investigated the radial velocity and performed a quantitative spectral analysis that allowed us to determine physical parameters. The fit of the spectral energy distribution based on the available photometry to low-metallicity model spectra and the similarity of our target to a metal-poor benchmark star (HD 84937) allowed us to estimate the distance and space velocity.Results. As in the case of HD 84937, we classified WISE J0725-2351 as sdF5: or a metal-poor turnoff star with [Fe/H] = -2.0 +/- 0.2, T-eff = 6250 +/- 100 K, log g = 4.0 +/- 0.2, and a possible age of about 12 Gyr. At an estimated distance of more than 400 pc, its proper motion translates to a tangential velocity of more than 500 km s(-1). Together with its constant (on timescales of hours, days, and months) and large radial velocity (about +240 km s(-1)), the resulting Galactic restframe velocity is about 460 km s(-1), implying a bound retrograde orbit for this extreme halo object that currently crosses the Galactic plane at high speed.
Keywords: proper motions; stars: distances; stars: kinematics and dynamics; stars: Population II; subdwarfs; white dwarfs

An evaluation of the exposure in nadir observation of the JEM-EUSO mission - Adams, J. H.; Ahmad, S.; Albert, J. -N.; Allard, D.; Ambrosio, M.; Anchordoqui, L.; Anzalone, Anna; Arai, Y.; Aramo, Carla; Asano, K.; Ave, M.; Barrillon, P.; et al. (Astroparticle Physics, 2013)
We evaluate the exposure during nadir observations with JEM-EUSO, the Extreme Universe Space Observatory, on-board the Japanese Experiment Module of the International Space Station. Designed as a mission to explore the extreme energy Universe from space, JEM-EUSO will monitor the Earth's nighttime atmosphere to record the ultraviolet light from tracks generated by extensive air showers initiated by ultra-high energy cosmic rays. In the present work, we discuss the particularities of space-based observation and we compute the annual exposure in nadir observation. The results are based on studies of the expected trigger aperture and observational duty cycle, as well as, on the investigations of the effects of clouds and different types of background light. We show that the annual exposure is about one order of magnitude higher than those of the presently operating ground-based observatories. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Ultra High Energy Cosmic Rays; Space-based experiment; Extensive air showers; JEM-EUSO mission

A new benchmark of soft X-ray transition energies of Ne , CO 2 , and SF 6 : paving a pathway towards ppm accuracy - Stierhof, Jakob; Kühn, S.; Winter, Mirko; Micke, P.; Steinbrügge, R.; Shah, C.; Hell, N.; Bissinger, Matthias; Hirsch, Maria; Ballhausen, Ralf; Lang, Melanie; Gräfe, Christina; et al. (European Physical Journal D, 2022)
Abstract: A key requirement for the correct interpretation of high-resolution X-ray spectra is that transition energies are known with high accuracy and precision. We investigate the K-shell features of Ne , CO 2, and SF 6 gases, by measuring their photo ion-yield spectra at the BESSY II synchrotron facility simultaneously with the 1s–np fluorescence emission of He-like ions produced in the Polar-X EBIT. Accurate ab initio calculations of transitions in these ions provide the basis of the calibration. While the CO 2 result agrees well with previous measurements, the SF 6 spectrum appears shifted by ∼ 0.5 eV, about twice the uncertainty of the earlier results. Our result for Ne shows a large departure from earlier results, but may suffer from larger systematic effects than our other measurements. The molecular spectra agree well with our results of time-dependent density functional theory. We find that the statistical uncertainty allows calibrations in the desired range of 1–10 meV, however, systematic contributions still limit the uncertainty to ∼ 40–100 meV, mainly due to the temporal stability of the monochromator energy scale. Combining our absolute calibration technique with a relative energy calibration technique such as photoelectron energy spectroscopy will be necessary to realize its full potential of achieving uncertainties as low as 1–10 meV. Graphical abstract: [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2022-03-11

A new bright eclipsing hot subdwarf binary from the ASAS and SuperWASP surveys - Schaffenroth, Veronika; Geier, Stephan; Drechsel, Horst; Heber, Ulrich; Wils, P.; Ostensen, R. H.; Maxted, P. F. L.; Di Scala, G. (Astronomy & Astrophysics, 2013)
We report the discovery of a bright (mV = 11.6 mag), eclipsing, hot subdwarf binary of spectral type B with a late main sequence companion from the All Sky Automated Survey (ASAS 102322-3737.0). Such systems are called HW Vir stars after the prototype. The lightcurve shows a grazing eclipse and a strong reflection effect. An orbital period of P = 0.13927 d, an inclination of i = 65.86, a mass ratio q = 0.34, a radial velocity semiamplitude K1 = 81.0 km s-1, and other parameters were derived from a combined spectroscopic and photometric analysis. The short period can only be explained by a common envelope origin of the system. The atmospheric parameters (T eff = 28 400 K, log g = 5.60) are consistent with a core helium-burning star located on the extreme horizontal branch. In agreement with that we derived the most likely sdB mass to be MsdB = 0.46 M ⊙, close to the canonical mass of such objects. The companion is a late M-dwarf with a mass of Mcomp = 0.16 M⊙. ASAS 102322-3737.0 is the third brightest of only 12 known HW Virginis systems, which makes it an ideal target for detailed spectroscopic studies and long-term photometric monitoring to search for period variations, e.g., those caused by a substellar companion. © 2013 ESO.
CRIS-Team Scopus Importer:2020-12-21
Keywords: Binaries: eclipsing; Binaries: spectroscopic; Stars: early-type; Stars: fundamental parameters; Stars: individual: ASAS 102322-3737.0; Subdwarfs

A New Class of Roche Lobe-filling Hot Subdwarf Binaries - Kupfer, Thomas; Bauer, Evan; Burdge, Kevin; van Roestel, Jan; Bellm, Eric; Fuller, Jim; Hermes, JJ; Marsh, Thomas R.; Bildsten, Lars; Kulkarni, Shrinivas R; Phinney, E S; Prince, Thomas A; et al. (Astrophysical Journal Letters, 2020)
We present the discovery of the second binary with a Roche lobe-filling hot subdwarf transferring mass to a white dwarf (WD) companion. This 56 minute binary was discovered using data from the Zwicky Transient Facility. Spectroscopic observations reveal an He-sdOB star with an effective temperature ofT(eff) = 33,700 1000 K and a surface gravity of log(g) = 5.54 0.11. The GTC+HiPERCAM light curve is dominated by the ellipsoidal deformation of the He-sdOB star and shows an eclipse of the He-sdOB by an accretion disk as well as a weak eclipse of the WD. We infer a He-sdOB mass ofM(sdOB) = 0.41 0.04Mand a WD mass ofM(WD) = 0.68 0.05M. The weak eclipses imply a WD blackbody temperature of 63,000 10,000 K and a radiusR(WD) = 0.0148 0.0020Ras expected for a WD of such high temperature. The He-sdOB star is likely undergoing hydrogen shell burning and will continue transferring mass for 1 Myr at a rate of 10(-9)Myr(-1), which is consistent with the high WD temperature. The hot subdwarf will then turn into a WD and the system will merge in 30 Myr. We suggest that Galactic reddening could bias discoveries toward preferentially finding Roche lobe-filling systems during the short-lived shell-burning phase. Studies using reddening-corrected samples should reveal a large population of helium core-burning hot subdwarfs withT(eff) 25,000 K in binaries of 60-90 minutes with WDs. Though not yet in contact, these binaries would eventually come into contact through gravitational-wave emission and explode as a subluminous thermonuclear supernova or evolve into a massive single WD.
Keywords: B subdwarf stars; Stellar evolution; White dwarf stars; Compact binary stars; Stellar accretion

A new HW Vir binary from the Palomar Transient Factory PTF1 J072455.75+125300.3: An eclipsing subdwarf B binary with a M-star companion - Schindewolf, Markus; Levitan, D.; Heber, Ulrich; Drechsel, Horst; Schaffenroth, Veronika; Kupfer, Thomas; Prince, T. (Astronomy & Astrophysics, 2015)
We report the discovery of an eclipsing binary - PTF1 J072456+125301- composed of a subdwarf B (sdB) star (g' = 17.2(m)) with a faint companion. Subdwarf B stars are core helium-burning stars, which can be found on the extreme horizontal branch. About half of them reside in close binary systems, but few are known to be eclipsing, for which fundamental stellar parameters can be derived. We conducted an analysis of photometric data and spectra from the Palomar 60 '' and the 200 '' Hale telescope, respectively. A quantitative spectral analysis found an effective temperature of T-eff = 33 900 +/- 350 K, log g = 5.74 +/- 0.08, and log(n(He)/n(H)) = -2.02 +/- 0.07, typical for an sdB star. The companion does not contribute to the optical light of the system, except through a distinct reflection effect. From the light curve an orbital period of 0.09980(25) d and a system inclination of 83.56 +/- 0.30 degrees were derived. The radial velocity curve yielded an orbital semi-amplitude of K-1 = 95.8 +/- 8.1 km s(-1). The mass for the M-type dwarf companion is 0.155 +/- 0.020 M-circle dot. PTF1 J072456+125301 has similar atmospheric parameters to those of pulsating sdB stars (V346 Hya stars). Therefore it could be a high-priority object for asteroseismology, if pulsations were detected such as in the enigmatic case of NY Vir.
Keywords: binaries: eclipsing; stars: early-type; stars: evolution; stars: fundamental parameters; stars: horizontal-branch; subdwarfs

A new lepto-hadronic model applied to the first simultaneous multiwavelength data set for Cygnus X-1 - Kantzas, Dimitrios; Markoff, S.; Beuchert, T.; Lucchini, Matteo; Chhotray, Atul; Ceccobello, Chiara; Tetarenko, A. J.; Miller-Jones, J. C. A.; Bremer, M.; Garcia, J. A.; Grinberg,; Uttley, P.; et al. (Monthly Notices of the Royal Astronomical Society, 2021)
Cygnus X-1 is the first Galactic source confirmed to host an accreting black hole. It has been detected across the entire electromagnetic spectrum from radio to GeV gamma-rays. The source's radio through mid-infrared radiation is thought to originate from the relativistic jets. The observed high degree of linear polarization in the MeV X-rays suggests that the relativistic jets dominate in this regime as well, whereas a hot accretion flow dominates the soft X-ray band. The origin of the GeV non-thermal emission is still debated, with both leptonic and hadronic scenarios deemed to be viable. In this work, we present results from a new semi-analytical, multizone jet model applied to the broad-band spectral energy distribution of Cygnus X-1 for both leptonic and hadronic scenarios. We try to break this degeneracy by fitting the first-ever high-quality, simultaneous multiwavelength data set obtained from the CHOCBOX campaign (Cygnus X-1 Hard state Observations of a Complete Binary Orbit in X-rays). Our model parametrizes dynamical properties, such as the jet velocity profile, the magnetic field, and the energy density. Moreover, the model combines these dynamical properties with a self-consistent radiative transfer calculation including secondary cascades, both of leptonic and hadronic origin. We conclude that sensitive TeV gamma-ray telescopes like Cherenkov Telescope Array (CTA) will definitively answer the question of whether hadronic processes occur inside the relativistic jets of Cygnus X-1.
CRIS-Team WoS Importer:2021-12-10

A new method for an objective, X2 -based spectroscopic analysis of early-type stars: First results from its application to single and binary B- and late O-type stars - Irrgang, Andreas; Przybilla, Norbert; Heber, Ulrich; Boeck, M.; Hanke, Manfred; Nieva, M. -F.; Butler, K. (Astronomy & Astrophysics, 2014)
Context. A precise quantitative spectral analysis, encompassing atmospheric parameter and chemical elemental abundance determination, is time-consuming due to its iterative nature and the multi-parameter space to be explored, especially when done by the naked eye. Aims. A robust automated fitting technique that is as trustworthy as traditional methods would allow for large samples of stars to be analyzed in a consistent manner in reasonable time. Methods. We present a semi-automated quantitative spectral analysis technique for early-type stars based on the concept of X2 minimization. The method's main features are as follows: far less subjectivity than the naked eye, correction for inaccurate continuum normalization, consideration of the whole useful spectral range, and simultaneous sampling of the entire multi-parameter space (effective temperature, surface gravity, microturbulence, macroturbulence, projected rotational velocity, radial velocity, and elemental abundances) to find the global best solution, which is also applicable to composite spectra. Results. The method is fast, robust, and reliable as seen from formal tests and from a comparison with previous analyses. Conclusions. Consistent quantitative spectral analyses of large samples of early-type stars can be performed quickly with very high accuracy. © ESO, 2014.
CRIS-Team Scopus Importer:2020-12-21
Keywords: Binaries: spectroscopic; Methods: data analysis; Stars: abundances; Stars: early-type; Stars: fundamental parameters; Stars: general

AN EXTREMELY FAST HALO HOT SUBDWARF STAR IN A WIDE BINARY SYSTEM - Nemeth, Peter; Ziegerer, Eva; Irrgang, Andreas; Geier, Stephan; Fuerst, Felix; Kupfer, Thomas; Heber, Ulrich (Astrophysical Journal Letters, 2016)
New spectroscopic observations of the halo hyper-velocity star candidate SDSS J121150.27+143716.2 (V = 17.92 mag) revealed a cool companion to the hot subdwarf primary. The components have a very similar radial velocity and their absolute luminosities are consistent with the same distance, confirming the physical nature of the binary, which is the first double-lined hyper-velocity candidate. Our spectral decomposition of the Keck/ESI spectrum provided an sdB+K3V pair, analogous to many long-period subdwarf binaries observed in the Galactic disk. We found the subdwarf atmospheric parameters: T-eff = 30 600 +/- 500 K, log g= 5.57 +/- 0.06 cm s(-2), and He abundance log(nHe/nH)= -3.0 +/- 0.2. Oxygen is the most abundant metal in the hot subdwarf atmosphere, and Mg and Na lines are the most prominent spectral features of the cool companion, consistent with a metallicity of [Fe/H] = -1.3. The non-detection of radial velocity variations suggest the orbital period to be a few hundred days, in agreement with similar binaries observed in the disk. Using the SDSS-III flux calibrated spectrum we measured the distance to the system d = 5.5 +/- 0.5 kpc, which is consistent with ultraviolet, optical, and infrared photometric constraints derived from binary spectral energy distributions. Our kinematic study shows that the Galactic rest-frame velocity of the system is so high that an unbound orbit cannot be ruled out. On the other hand, a bound orbit requires a massive dark matter halo. We conclude that the binary either formed in the halo or was accreted from the tidal debris of a dwarf galaxy by the Milky Way.
Keywords: binaries: spectroscopic; Galaxy: halo; stars: atmospheres; stars: horizontal-branch; stars: kinematics and dynamics; subdwarfs

An intermediate-velocity H I cloud falling to the galactic disk; Possible evidence for low-metallicity H I gas originating outside the galactic disk - Fukui, Yasuo; Koga, Masako; Maruyama, Shohei; Hayakawa, Takahiro; Okamoto, Ryuji; Yamamoto, Hiroaki; Tachihara, Kengo; Shelton, Robin; Sasaki, Manami (Publications of the Astronomical Society of Japan, 2021)
We found that an intermediate-velocity cloud (IVC), IVC 86-36, in H I 21cm emission shows a head-tail distribution toward the Galactic plane with marked parallel filamentary streamers, which is extended over 40 degrees in the sky. The distance of IVC 86-36 is constrained to be less than similar to 3kpc from absorption of a background star as determined from optical spectroscopy. There is a bridge feature in velocity between the IVC and the local interstellar medium with velocity separation of similar to 50kms(-1), which may indicate dynamical interaction of the IVC with the disk. If the interaction is correct, the distance estimate d of the IVC ranges from 200pc to 3kpc, and the mass of the IVC head is estimated to be 7 x 10(3)(d/1 kpc)(2) M-circle dot . The IVC shares similar properties to the Smith Cloud located at 12kpc, including the head-tail distribution, streamers, and bridge feature, while the mass of the IVC is less than similar to 0.1 of the Smith Cloud. A comparison between the H I and the Planck/IRAS dust emission indicates that the dust emission of IVC 86-36 is not detectable in spite of its H I column density of 2 x 10(20)cm(-2), indicating a low metallicity for IVC 86-36, reduced by a factor of less than or similar to 0.2 as compared with the solar neighbor. We conclude that IVC 86-38 is an infalling cloud which likely originated in the low-metallicity environment of the Galactic halo or the Magellanic system.
CRIS-Team WoS Importer:2021-05-28

ANTARES constrains a blazar origin of two IceCube PeV neutrino events - Adrian-Martinez, S.; Albert, A.; Andre, M.; Anton, Gisela; Ardid, Miguel; Aubert, J. -J.; Baret, B.; Barrios, J.; Basa, S.; Bertin, V.; Biagi, Simone; Bogazzi, C.; et al. (Astronomy & Astrophysics, 2015)
Results. Both blazars predicted to be the most neutrino-bright in the TANAMI sample (1653-329 and 1714-336) have a signal flux fitted by the likelihood analysis corresponding to approximately one event. This observation is consistent with the blazar-origin hypothesis of the IceCube event IC 14 for a broad range of blazar spectra, although an atmospheric origin cannot be excluded. No ANTARES events are observed from any of the other four blazars, including the three associated with IceCube event IC20. This excludes at a 90% confidence level the possibility that this event was produced by these blazars unless the neutrino spectrum is flatter than -2.4.
Keywords: neutrinos; galaxies: active; quasars: general

ANTARES Neutrino Search for Time and Space Correlations with IceCube High-energy Neutrino Events - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J-J; Aublin, J.; Baret, B.; Barrios-Marti, J.; Basa, S.; Belhorma, B.; Bertin, V.; et al. (Astrophysical Journal, 2019)
In past years the IceCube Collaboration has reported the observation of astrophysical high-energy neutrino events in several analyses. Despite compelling evidence for the first identification of a neutrino source, TXS 0506+056, the origin of the majority of these events is still unknown. In this paper, we search for a possible transient origin of the IceCube astrophysical events using neutrino events detected by the ANTARES telescope. The arrival time and direction of 6894 track-like and 160 shower-like events detected over 2346 days of livetime are examined to search for coincidences with 54 IceCube high-energy track-like neutrino events, by means of a maximum likelihood method. No significant correlation is observed and upper limits on the one-flavor neutrino fluence from the direction of the IceCube candidates are derived. The nonobservation of time and space correlation within the time window of 0.1 days with the two most energetic IceCube events constrains the spectral index of a possible point-like transient neutrino source to be harder than -2.3 and -2.4 for each event, respectively.
CRIS-Team WoS Importer:2019-07-26

ANTARES Search for Point Sources of Neutrinos Using Astrophysical Catalogs: A Likelihood Analysis - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. -J.; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; Bertin, V.; Biagi, Simone; et al. (Astrophysical Journal, 2021)
A search for astrophysical pointlike neutrino sources using the data collected by the ANTARES detector between 2007 January 29 and 2017 December 31 is presented. A likelihood method is used to assess the significance of an excess of muon neutrinos inducing track-like events in correlation with the location of a list of possible sources. Different sets of objects are tested in the analysis: (a) a subsample of the Fermi 3LAC catalog of blazars, (b) a jet-obscured population of active galactic nuclei, (c) a sample of hard X-ray selected radio galaxies, (d) a star-forming galaxy catalog, and (e) a public sample of 56 very-high-energy track events from the IceCube experiment. None of the tested sources shows a significant association with the sample of neutrinos detected by ANTARES. The smallest p-value is obtained for the catalog of radio galaxies with an equal-weights hypothesis, with a pre-trial p-value equivalent to a 2.8 sigma excess, which is equivalent to 1.6 sigma post-trial. In addition, the results of a dedicated analysis for the blazar MG3 J225517+2409 are also reported: this source is found to be the most significant within the Fermi 3LAC sample, with five ANTARES events located less than one degree from the source. This blazar showed evidence of flaring activity in Fermi data, in spacetime coincidence with a high-energy track detected by IceCube. An a posteriori significance of 2.6 sigma for the combination of ANTARES and IceCube data is reported.
CRIS-Team WoS Importer:2021-04-30

ANTARES upper limits on the multi-TeV neutrino emission from the GRBs detected by IACTs - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. J.; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; Bertin, V.; Biagi, S.; et al. (Journal of Cosmology and Astroparticle Physics, 2021)
The first gamma-ray burst detections by Imaging Atmospheric Cherenkov Telescopes have been recently announced: GRB 190114C, detected by MAGIC, GRB 180720B and GRB 190829A, observed by H.E.S.S. A dedicated search for neutrinos in space and time coincidence with the gamma-ray emission observed by IACTs has been performed using ANTARES data. The search covers both the prompt and afterglow phases, yielding no neutrinos in coincidence with the three GRBs studied. Upper limits on the energetics of the neutrino emission are inferred. The resulting upper limits are several orders of magnitude above the observed gamma-ray emission, and they do not allow to constrain the available models.
CRIS-Team Scopus Importer:2021-04-16

An ultraluminous supersoft source with a 4 hour modulation in NGC 4631 - Wilms, Jörn; et al. (Astronomy & Astrophysics, 2007)
Context. Supersoft X- ray sources (SSSs) are characterised by very low temperatures (< 100 eV). Classical SSSs have bolometric luminosities in the range of 10(36)-10(38) erg s(-1) and are modelled with steady nuclear burning of hydrogen on the surfaces of white dwarfs. However, several SSSs have been discovered with much higher luminosities. Their nature is still unclear. Aims. We report the discovery of a 4 h modulation for an ultraluminous SSS in the nearby edge-on spiral galaxy NGC 4631, observed with XMM-Newton in 2002 June. Temporal and spectral analysis of the source is performed. Methods. We use a Lomb-Scargle periodogram analysis for the period search and evaluate the confidence level using Monte-Carlo simulations. We measure the source temperature, flux and luminosity through spectral fitting. Results. A modulation of 4.2 +/- 0.4 h (3 sigma error) was found for the SSS with a confidence level > 99%. Besides dips observed in the light curve, the flux decreased by a factor of 3 within similar to 10 h. The spectrum can be described with an absorbed blackbody model with kT similar to 67 eV. The absorbed luminosity in the 0.2-2 keV energy band was 2.7 x 1038 erg s-1 while the bolometric luminosity was a hundred time higher (3.2 x 1040 erg s(-1)), making the source one of the most luminous of its class, assuming the best fit model is correct. Conclusions. This source is another very luminous SSS for which the standard white dwarf interpretation cannot be applied, unless a strong beaming factor is considered. A stellar-mass black hole accreting at a super Eddington rate is a more likely interpretation, where the excess of accreted matter is ejected through a strong optically-thick outflow. The 4 h modulation could either be an eclipse from the companion star or the consequence of a warped accretion disk.
Keywords: galaxies : individual : NGC 4631; X-rays : galaxies; X-rays : binaries

An Unbiased CO Survey Toward the Northern Region of the Small Magellanic Cloud with the Atacama Compact Array. II. CO Cloud Catalog - Ohno, Takahiro; Tokuda, Kazuki; Konishi, Ayu; Matsumoto, Takeru; Sewiło, Marta; Kondo, Hiroshi; Sano, Hidetoshi; Tsuge, Kisetsu; Zahorecz, Sarolta; Goto, Nao; Neelamkodan, Naslim; Wong, Tony; et al. (Astrophysical Journal, 2023)
The nature of molecular clouds and their statistical behavior in subsolar metallicity environments are not fully explored yet. We analyzed data from an unbiased CO (J = 2-1) survey at the spatial resolution of ∼2 pc in the northern region of the Small Magellanic Cloud with the Atacama Compact Array to characterize the CO cloud properties. A cloud-decomposition analysis identified 426 spatially/velocity-independent CO clouds and their substructures. Based on the cross-matching with known infrared catalogs by Spitzer and Herschel, more than 90% CO clouds show spatial correlations with point sources. We investigated the basic properties of the CO clouds and found that the radius-velocity linewidth (R-σ v ) relation follows the Milky Way-like power-law exponent, but the intercept is ∼1.5 times lower than that in the Milky Way. The mass functions (dN/dM) of the CO luminosity and virial mass are characterized by an exponent of ∼1.7, which is consistent with previously reported values in the Large Magellanic Cloud and in the Milky Way.
CRIS-Team Scopus Importer:2023-06-30

A NuSTAR and Swift view of the hard state of MAXI J1813-095 - Jiang, Jiachen; Buisson, Douglas J. K.; Dauser, Thomas; Fabian, Andrew C.; Furst, Felix; Gallo, Luigi C.; Harrison, Fiona A.; Parker, Michael L.; Steiner, James F.; Tomsick, John A.; Ubach, Santiago; Walton, Dominic J. (Monthly Notices of the Royal Astronomical Society, 2022)
We present an analysis of the NuSTAR and Swift spectra of the black hole candidate MAXI J1813-095 in a failed-transition outburst in 2018. The NuSTAR observations show evidence of reflected emission from the inner region of the accretion disc. By modelling the reflection component in the spectra, we find a disc inner radius of Rin < 7 rg. This result suggests that either a slightly truncated disc or a non-truncated disc forms at a few per cent of the Eddington limit in MAXI J1813-095. Our best-fitting reflection models indicate that the geometry of the innermost accretion remains consistent during the period of NuSTAR observations. The spectral variability of MAXI J1813-095 from multi-epoch observations is dominated by the variable photon index of the Comptonization emission.
CRIS-Team Scopus Importer:2022-07-15
Keywords: accretion; accretion discs; black hole physics; X-rays: binaries

An X-ray interferometry concept for the ESA Voyage 2050 programme - Uttley, Phil; Den Hartog, Roland; Bambi, Cosimo; Barret, Didier; Bianchi, Stefano; Bursa, Michal; Cappi, Massimo; Casella, Piergiorgio; Cash, Webster; Costantini, Elisa; Dauser, Thomas; Trigo, Maria Diaz; et al. (SPACE TELESCOPES AND INSTRUMENTATION 2020: ULTRAVIOLET TO GAMMA RAY, 2021)
CRIS-Team WoS Importer:2021-08-27

An X-ray spectral analysis of the central regions of NGC 4593 - Wilms, Jörn; et al. (Astrophysical Journal, 2007)
We present a detailed analysis of XMM-Newton EPIC-pn data for the Seyfert 1 galaxy NGC 4593. We discuss the X-ray spectral properties of this source, as well as its variations with time. The 0.5-10 keV spectrum shows significant complexity beyond a simple power-law form, with clear evidence existing for a "soft excess,'' as well as absorption by highly ionized plasma ( a warm absorber) within the central engine of this active galactic nucleus. We show that the soft excess is best described as originating from thermal Comptonization by plasma that is appreciably cooler than the primary X-ray-emitting plasma; we find that the form of the soft excess cannot be reproduced adequately by reflection from an ionized accretion disk. The only measurable deviation from the power-law continuum in the hard spectrum comes from the presence of cold and ionized fluorescent iron K alpha emission lines at 6.4 and 6.97 keV, respectively. While constraints on the ionized iron line are weak, the cold line is found to be narrow at CCD resolution with a flux that does not track the temporal changes in the underlying continuum, implying an origin in the outer radii of the accretion disk or the putative molecular torus of Seyfert unification schemes. The X-ray continuum itself varies on all accessible timescales. We detect a similar to 230 s time lag between soft and hard EPIC-pn bands that, if interpreted as scattering timescales within a Comptonizing disk corona, can be used to constrain the physical size of the primary X-ray source to a characteristic length scale of similar to 2r(g). Taken together, the small implied coronal size and the large implied iron-line emitting region indicate a departure from the current picture of a "typical'' AGN geometry.
Keywords: accretion; accretion disks; black hole physics; galaxies : nuclei

An X-ray variable absorber within the broad line region in Fairall 51 - Svoboda, J.; Beuchert, Tobias; Guainazzi, M.; Longinotti, A. L.; Piconcelli, E.; Wilms, Jörn (Astronomy & Astrophysics, 2015)
Conclusions. A week-long scale of the variability indicates that the absorber is located at the distance approximate to 0.05 pc from the centre, i.e., in the broad line region.
Keywords: galaxies: active; galaxies: Seyfert; galaxies: individual: Fairall 51

A planetesimal orbiting within the debris disc around a white dwarf star - Manser, Christopher J.; Gansicke, Boris T.; Eggl, Siegfried; Hollands, Mark; Izquierdo, Paula; Koester, Detlev; Landstreet, John D.; Lyra, Wladimir; Marsh, Thomas R.; Meru, Farzana; Mustill, Alexander J.; Rodriguez-Gil, Pablo; et al. (Science, 2019)
Many white dwarf stars show signs of having accreted smaller bodies, implying that they may host planetary systems. A small number of these systems contain gaseous debris discs, visible through emission lines. We report a stable 123.4-minute periodic variation in the strength and shape of the Ca II emission line profiles originating from the debris disc around the white dwarf SDSS J122859.93+104032.9. We interpret this short-period signal as the signature of a solid-body planetesimal held together by its internal strength.
CRIS-Team Scopus Importer:2019-05-02

A polarized fast radio burst at low Galactic latitude - Petroff, E.; Burke-Spolaor, S.; Keane, E. F.; Mclaughlin, M. A.; Miller, R.; Andreoni, I.; Bailes, Matthew; Barr, E. D.; Bernard, S. R.; Bhandari, S.; Bhat, N. D. R.; Burgay, M.; et al. (Monthly Notices of the Royal Astronomical Society, 2017)
We report on the discovery of a new fast radio burst (FRB), FRB 150215, with the Parkes radio telescope on 2015 February 15. The burst was detected in real time with a dispersion measure (DM) of 1105.6 +/- 0.8 pc cm(-3), a pulse duration of 2.8(-0.5)(+1.2) ms, and a measured peak flux density assuming that the burst was at beam centre of 0.7(-0.1)(+0.2) Jy. The FRB originated at a Galactic longitude and latitude of 24.66 degrees, 5.28 degrees and 25 degrees away from the Galactic Center. The burst was found to be 43 +/- 5 per cent linearly polarized with a rotation measure (RM) in the range -9 < RM < 12 rad m(-2) (95 per cent confidence level), consistent with zero. The burst was followed up with 11 telescopes to search for radio, optical, X-ray, gamma-ray and neutrino emission. Neither transient nor variable emission was found to be associated with the burst and no repeat pulses have been observed in 17.25 h of observing. The sightline to the burst is close to the Galactic plane and the observed physical properties of FRB 150215 demonstrate the existence of sight lines of anomalously low RM for a given electron column density. The Galactic RM foreground may approach a null value due to magnetic field reversals along the line of sight, a decreased total electron column density from the Milky Way, or some combination of these effects. A lower Galactic DM contribution might explain why this burst was detectable whereas previous searches at low latitude have had lower detection rates than those out of the plane.
Keywords: polarization; methods: data analysis; surveys; ISM: structure

A Possible Phase-dependent Absorption Feature in the Transient X-Ray Pulsar SAX J2103.5+4545 - Brumback, M. C.; Hickox, R. C.; Furst, F. S.; Pottschmidt, K.; Hemphill, P.; Tomsick, J. A.; Wilms, Jörn; Ballhausen, Ralf (Astrophysical Journal, 2018)
We present an X-ray spectral and timing analysis of two Nuclear Spectroscopic Telescope Array (NuSTAR) observations of the transient Be X-ray binary SAX J2103.5+4545 during its 2016 April outburst, which was characterized by the highest flux since NuSTAR's launch. These observations provide detailed hard X-ray spectra of this source during its bright precursor flare and subsequent fainter regular outburst for the first time. In this work, we model the phase-averaged spectra for these observations with a negative and positive power law with an exponential cutoff (NPEX) model and compare the pulse profiles at different flux states. We found that the broadband pulse profile changes from a three-peaked pulse in the first observation to a two-peaked pulse in the second observation, and that each of the pulse peaks has some energy dependence. We also perform pulse-phase spectroscopy and fit phase-resolved spectra with NPEX to evaluate how spectral parameters change with pulse phase. We find that while the continuum parameters are mostly constant with pulse phase, a weak absorption feature at similar to 12 keV might, with further study, be classified as a cyclotron line, does show strong pulse-phase dependence.
Keywords: pulsars: individual (SAX J2103.5+4545); stars: neutron; X-rays: binaries

A precessing Be disc as a possible model for occultation events in GX 304-1 - Kühnel, Matthias; Rothschild, R. E.; Okazaki, A. T.; Müller, Sebastian; Pottschmidt, K.; Ballhausen, Ralf; Choi, J.; Kreykenbohm, Ingo; Fuerst, F.; Marcu-Cheatham, D. M.; Hemphill, P.; Sagredo, Macarena; et al. (Monthly Notices of the Royal Astronomical Society, 2017)
We report on the RXTE detection of a sudden increase in the absorption column density, N-H, during the 2011 May outburst of GX 304-1. The NH increased up to similar to 16 x 10(22) atoms cm(-2), which is a factor of 3-4 larger than what is usually measured during the outbursts of GX 304-1 as covered by RXTE. Additionally, an increase in the variability of the hardness ratio as calculated from the energy resolved RXTE-Proportional Counter Array light curves is measured during this time range. We interpret these facts as an occultation event of the neutron star by material in the line of sight. Using a simple 3D model of an inclined and precessing Be disc around the Be-type companion, we are able to qualitatively explain the NH evolution over time. We are able to constrain the Be disc density to be of the order of 10(-11) g cm(-3). Our model strengthens the idea of inclined Be discs as origin of double-peaked outbursts as the derived geometry allows accretion twice per orbit under certain conditions.
Keywords: occultations; stars: neutron; pulsars: individual: GX 304-1; X-rays: binaries

A progenitor binary and an ejected mass donor remnant of faint type Ia supernovae - Geier, S.; Marsh, T. R.; Wang, Bo; Dunlap, B.; Barlow, B. N.; Schaffenroth, Veronika; Chen, X.; Irrgang, Andreas; Maxted, P. F. L.; Ziegerer, Eva; Kupfer, Thomas; Miszalski, B.; et al. (Astronomy & Astrophysics, 2013)
Type Ia supernovae (SN Ia) are the most important standard candles for measuring the expansion history of the universe. The thermonuclear explosion of a white dwarf can explain their observed properties, but neither the progenitor systems nor any stellar remnants have been conclusively identified. Underluminous SN Ia have been proposed to originate from a so-called double-detonation of a white dwarf. After a critical amount of helium is deposited on the surface through accretion from a close companion, the helium is ignited causing a detonation wave that triggers the explosion of the white dwarf itself. We have discovered both shallow transits and eclipses in the tight binary system CD-30° 11223 composed of a carbon/oxygen white dwarf and a hot helium star, allowing us to determine its component masses and fundamental parameters. In the future the system will transfer mass from the helium star to the white dwarf. Modelling this process we find that the detonation in the accreted helium layer is sufficiently strong to trigger the explosion of the core. The helium star will then be ejected at such high velocity that it will escape the Galaxy. The predicted properties of this remnant are an excellent match to the so-called hypervelocity star US 708, a hot, helium-rich star moving at more than 750 km s-1, sufficient for it to leave the Galaxy. The identification of both progenitor and remnant provides a consistent picture of the formation and evolution of underluminous SNIa. © 2013 ESO.
CRIS-Team Scopus Importer:2020-12-21
Keywords: Binaries: spectroscopic; Subdwarfs; Supernovae: general

A proto-helium white dwarf stripped by a substellar companion via common-envelope ejection: Uncovering the true nature of a candidate hypervelocity B-type star - Irrgang, Andreas; Geier, S.; Heber, Ulrich; Kupfer, T.; El-Badry, K.; Bloemen, S. (Astronomy & Astrophysics, 2021)
In the past, SDSS J160429.12+100002.2 wass spectroscopically classified as a blue horizontal branch (BHB) star. Assuming a luminosity that is characteristic of BHB stars, the object's radial velocity and proper motions from Gaia Early Data Release 3 would imply that its Galactic rest-frame velocity exceeds its local escape velocity. Consequently, the object would be considered a hypervelocity star, which would prove particularly interesting because its Galactic trajectory points in our direction. However, based on the spectroscopic analysis of follow-up observations, we show that the object is actually a short-period (P ≈ 3.4 h) single-lined spectroscopic binary system with a visible B-type star (effective temperature Teff = 15 840 ± 160 K and surface gravity log(g) = 4.86 ± 0.04) that is less luminous than typical BHB stars. Accordingly, the distance of the system is lower than originally thought, which renders its Galactic orbit bound to the Galaxy. Nevertheless, it is still an extreme halo object on a highly retrograde orbit. The abundances of He, C, N, O, Ne, Mg, Al, Si, S, and Ca are subsolar by factors from 3 to more than 100, while Fe is enriched by a factor of about 6. This peculiar chemical composition pattern is most likely caused by atomic diffusion processes. Combining constraints from astrometry, orbital motion, photometry, and spectroscopy, we conclude that the visible component is an unevolved proto-helium white dwarf with a thin hydrogen envelope that was stripped by a substellar companion through common-envelope ejection. Its unique configuration renders the binary system an interesting test bed for stellar binary evolution in general and common-envelope evolution in particular.
CRIS-Team Scopus Importer:2021-07-02
Keywords: Binaries: Close; Binaries: Spectroscopic; Brown dwarfs; Stars: Chemically peculiar; Stars: Individual: SDSS J160429.12+100002.2; White dwarfs

A public relativistic transfer function model for X-ray reverberation mapping of accreting black holes - Ingram, Adam; Mastroserio, Guglielmo; Dauser, Thomas; Hovenkamp, Pieter; Van Der Klis, Michiel; Garcia, Javier (Monthly Notices of the Royal Astronomical Society, 2019)
We present the publicly available model RELTRANS that calculates the light-crossing delays and energy shifts experienced by X-ray photons originally emitted close to the black hole when they reflect from the accretion disc and are scattered into our line of sight, accounting for all general relativistic effects. Our model is fast and flexible enough to be simultaneously fit to the observed energy-dependent cross-spectrum for a large range of Fourier frequencies, as well as to the time-averaged spectrum. This not only enables better geometric constraints than only modelling the relativistically broadened reflection features in the time-averaged spectrum, but additionally enables constraints on the mass of supermassive black holes in active galactic nuclei and stellar-mass black holes in X-ray binaries. We include a self-consistently calculated radial profile of the disc ionization parameter and properly account for the effect that the telescope response has on the predicted time lags. We find that a number of previous spectral analyses have measured artificially low source heights due to not accounting for the former effect and that timing analyses have been affected by the latter. In particular, the magnitude of the soft lags in active galactic nuclei may have been underestimated, and the magnitude of lags attributed to thermal reverberation in X-ray binaries may have been overestimated. We fit RELTRANS to the lag-energy spectrum of the Seyfert galaxy Mrk 335, resulting in a best-fitting black hole mass that is smaller than previous optical reverberation measurements (similar to 7 million compared with similar to 14-26 million M-circle dot).
CRIS-Team WoS Importer:2019-09-24

A quantitative in-depth analysis of the prototype sdB plus BD system SDSS J08205+0008 revisited in the Gaia era - Schaffenroth, V.; Casewell, S. L.; Schneider, David; Kilkenny, D.; Geier, S.; Heber, Ulrich; Irrgang, Andreas; Przybilla, N.; Marsh, T. R.; Littlefair, S. P.; Dhillon, V. S. (Monthly Notices of the Royal Astronomical Society, 2021)
Subdwarf B stars are core-helium-burning stars located on the extreme horizontal branch (EHB). Extensive mass loss on the red giant branch is necessary to form them. It has been proposed that substellar companions could lead to the required mass loss when they are engulfed in the envelope of the red giant star. J08205+0008 was the first example of a hot subdwarf star with a close, substellar companion candidate to be found. Here, we perform an in-depth re-analysis of this important system with much higher quality data allowing additional analysis methods. From the higher resolution spectra obtained with ESO-VLT/XSHOOTER, we derive the chemical abundances of the hot subdwarf as well as its rotational velocity. Using the Gaia parallax and a fit to the spectral energy distribution in the secondary eclipse, tight constraints to the radius of the hot subdwarf are derived. From a long-term photometric campaign, we detected a significant period decrease of -3.2(8) x 10(-12) dd(-1). This can be explained by the non-synchronized hot subdwarf star being spun up by tidal interactions forcing it to become synchronized. From the rate of period decrease we could derive the synchronization time-scale to be 4 Myr, much smaller than the lifetime on EHB. By combining all different methods, we could constrain the hot subdwarf to a mass of 0.39-0.50 M-circle dot and a radius of R-sdB = 0.194 +/- 0.008 R-circle dot, and the companion to 0.061-0.071 M-circle dot with a radius of R-comp = 0.092 +/- 0.005 R-circle dot, below the hydrogen-burning limit. We therefore confirm that the companion is most likely a massive brown dwarf.
CRIS-Team WoS Importer:2021-03-26

A quantitative NLTE analysis of visual and ultraviolet spectra of four helium-rich subdwarf O stars - Schindewolf, Markus; Nemeth, Peter; Heber, Ulrich; Battich, Tiara; Miller Bertolami, Marcelo M.; Irrgang, Andreas; Latour, Marilyn (Astronomy & Astrophysics, 2018)
Aims. Hot subdwarf stars represent a poorly understood late phase of stellar evolution. While binary evolution plays an important role for the formation of B-type subdwarfs (sdB), the origin of the helium dominated subclass of O-type subdwarfs (He-sdO) is still unknown. We search for chemical signatures of their genesis by means of quantitative spectral analyses of high-quality visual and ultraviolet spectra.Methods. Four prototypical He-sdO stars, one belonging to the nitrogen-rich and three to the C-rich subclass, were selected for which archival far-ultraviolet spectra from the FUSE satellite as well as high-resolution visual and UVA spectra taken with the ESO-UVES/FEROS spectrographs are available. Using TLUSTY200/SYNSPEC49 to compute line blanketed-non-local thermodynamic equilibrium (NLTE) model atmospheres and synthetic spectra, atmospheric parameters and the abundances patterns have been derived. The final models included H, He, C, N, O, Ne, Mg, Al, Si, P, S, Fe, and Ni represented by the most detailed model atoms available. Because of the enrichment of either nitrogen or carbon, it turned out, that models including these elements at the appropriate high abundance provide sufficiently accurate approximations to the temperature stratification of full models.Results. No indications for binarity were found, neither radial velocity variations nor photometric evidence for the presence of a companion could be detected. All stars have helium-dominated atmospheres almost free of hydrogen and temperatures between 42 000K and 47 000K while their surface gravities lie between log g = 5.4 and 5.7. The abundance pattern of CD-31 degrees 4800 displays the signatures of CNO burning, while heavier elements are subsolar by about 0.4 dex, except for Ne and Si which are close to solar. The abundance patterns of the C-rich He-sdOs are more complex. A slightly subsolar metallicity is accompanied by N-enrichment and O-deficiency, less pronounced than in CD-31 degrees 4800. Neon is mildly to strongly enriched, up to a factor of ten with respect to the sun in LS IV + 10 degrees 9. The nickel-to-iron ratio is significantly super-solar. Using spectral energy distributions and Gaia parallaxes the masses of the stars were determined. They are found to scatter around the canonical mass for the core helium flash, although the uncertainties are large.Conclusions. The abundance pattern observed for CD-31 degrees 4800 is consistent with predictions of models for slow (cold) mergers of pairs of equal mass helium WDs except for the low oxygen abundance observed. Models for composite mergers were considered for the C-rich stars, but predict abundance pattern dissimilar to those determined. [CW83] 0904 02, though, may be a candidate for a composite He-WD merger, as it rotates and appears to be more massive than the other program stars. New evolutionary models for the hot flasher scenario predict abundance patterns similar to those determined for the C-rich stars. Hence, C-rich He-sdO may well result from late He flashes with deep-mixing episodes.
Keywords: stars: abundances; stars: atmospheres; stars: evolution; subdwarfs

Arcus: The X-ray grating spectrometer explorer - Smith, R. K.; Abraham, M. H.; Allured, R.; Bautz, M.; Bookbinder, J.; Bregman, J. N.; Brenneman, L.; Brickhouse, N. S.; Burrows, D. N.; Burwitz, V.; Carvalho, R.; Cheimets, P. N.; et al. (Space Telescopes and Instrumentation 2016: Ultraviolet to Gamma Ray, 2016)
Arcus will be proposed to the NASA Explorer program as a free-flying satellite mission that will enable high-resolution soft X-ray spectroscopy (8-50Å) with unprecedented sensitivity - effective areas of >500 sq cm and spectral resolution >2500. The Arcus key science goals are (1) to determine how baryons cycle in and out of galaxies by measuring the effects of structure formation imprinted upon the hot gas that is predicted to lie in extended halos around galaxies, groups, and clusters, (2) to determine how black holes influence their surroundings by tracing the propagation of out-flowing mass, energy and momentum from the vicinity of the black hole out to large scales and (3) to understand how accretion forms and evolves stars and circumstellar disks by observing hot infalling and outflowing gas in these systems. Arcus relies upon grazing-incidence silicon pore X-ray optics with the same 12m focal length (achieved using an extendable optical bench) that will be used for the ESA Athena mission. The focused X-rays from these optics will then be diffracted by high-efficiency off-plane reflection gratings that have already been demonstrated on sub-orbital rocket flights, imaging the results with flight-proven CCD detectors and electronics. The power and telemetry requirements on the spacecraft are modest. The majority of mission operations will not be complex, as most observations will be long (∼100 ksec), uninterrupted, and pre-planned, although there will be limited capabilities to observe targets of opportunity, such as tidal disruption events or supernovae with a 3-5 day turnaround. After the end of prime science, we plan to allow guest observations to maximize the science return of Arcus to the community.
Keywords: Gratings; Instrumentation; X-rays: spectroscopy

A Review of the EUSO-Balloon Pathfinder for the JEM-EUSO Program - Adams, J. H.; Ahmad, S.; Allard, D.; Anzalone, A.; Bacholle, S.; Barrillon, P.; Bayer, J.; Bertaina, M.; Bisconti, F.; Blaksley, C.; Blin-Bondil, S.; Bobik, P.; et al. (Space Science Reviews, 2022)
EUSO-Balloon is a pathfinder for JEM-EUSO, the mission concept of a spaceborne observatory which is designed to observe Ultra-High Energy Cosmic Ray (UHECR)-induced Extensive Air Showers (EAS) by detecting their UltraViolet (UV) light tracks "from above." On August 25, 2014, EUSO-Balloon was launched from Timmins Stratospheric Balloon Base (Ontario, Canada) by the balloon division of the French Space Agency CNES. After reaching a floating altitude of 38 km, EUSO-Balloon imaged the UV light in the wavelength range similar to 290-500 nm for more than 5 hours using the key technologies of JEM-EUSO. The flight allowed a good understanding of the performance of the detector to be developed, giving insights into possible improvements to be applied to future missions. A detailed measurement of the photoelectron counts in different atmospheric and ground conditions was achieved. By means of the simulation of the instrument response and by assuming atmospheric models, the absolute intensity of diffuse light was estimated. The instrument detected hundreds of laser tracks with similar characteristics to EASs shot by a helicopter flying underneath. These are the first recorded laser tracks measured from a fluorescence detector looking down on the atmosphere. The reconstruction of the direction of the laser tracks was performed. In this work, a review of the main results obtained by EUSO-Balloon is presented as well as implications for future space-based observations of UHECRs.
CRIS-Team WoS Importer:2022-02-11

AS ABOVE, SO BELOW: EXPLOITING MASS SCALING IN BLACK HOLE ACCRETION TO BREAK DEGENERACIES IN SPECTRAL INTERPRETATION - Markoff, Sera; Nowak, Michael A.; Gallo, Elena; Hynes, Robert; Wilms, Jörn; Plotkin, Richard M.; Maitra, Dipankar; Silva, Catia V.; Drappeau, Samia (Astrophysical Journal Letters, 2015)
Over the past decade, evidence has mounted that several aspects of black hole (BH) accretion physics proceed in a mass-invariant way. One of the best examples of this scaling is the empirical "fundamental plane of BH accretion" relation linking mass, radio, and X-ray luminosity over eight orders of magnitude in BH mass. The currently favored theoretical interpretation of this relation is that the physics governing power output in weakly accreting BHs depends more on relative accretion rate than on mass. In order to test this theory, we explore whether a mass-invariant approach can simultaneously explain the broadband spectral energy distributions from two BHs at opposite ends of the mass scale but that are at similar Eddington accretion fractions. We find that the same model, with the same value of several fitted physical parameters expressed in mass-scaling units to enforce self-similarity, can provide a good description of two data sets from V404 Cyg and M81*, a stellar and supermassive BH, respectively. Furthermore, only one of several potential emission scenarios for the X-ray band is successful, suggesting it is the dominant process driving the fundamental plane relation at this accretion rate. This approach thus holds promise for breaking current degeneracies in the interpretation of BH high-energy spectra and for constructing better prescriptions of BH accretion for use in various local and cosmological feedback applications.
Keywords: accretion; accretion disks; black hole physics; galaxies: active; galaxies: jets; radiation mechanisms: non-thermal; X-rays: binaries

A Search for Cosmic Neutrino and Gamma-Ray Emitting Transients in 7.3 yr of ANTARES and Fermi LAT Data - Solares, H. A. Ayala; Cowen, D. F.; Delaunay, J. J.; Fox, D. B.; Keivani, A.; Mostafa, M.; Murase, K.; Turley, C. F.; Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; et al. (Astrophysical Journal, 2019)
We analyze 7.3 yr of ANTARES high-energy neutrino and Fermi Large Area Telescope (LAT) gamma-ray data in search of cosmic neutrino + gamma-ray (nu + gamma) transient sources or source populations. Our analysis has the potential to detect either individual nu + gamma transient sources (durations delta t less than or similar to 1000 s), if they exhibit sufficient gamma-ray or neutrino multiplicity, or a statistical excess of nu + gamma transients of individually lower multiplicities. Individual high gamma-ray multiplicity events could be produced, for example, by a single ANTARES neutrino in coincidence with a LAT-detected gamma-ray burst. Treating ANTARES track and cascade event types separately, we establish detection thresholds by Monte Carlo scrambling of the neutrino data, and determine our analysis sensitivity by signal injection against these scrambled data sets. We find our analysis is sensitive to nu + gamma transient populations responsible for >5% of the observed gamma-coincident neutrinos in the track data at 90% confidence. Applying our analysis to the unscrambled data reveals no individual nu + gamma events of high significance; two ANTARES track + Fermi gamma-ray events are identified that exceed a once per decade false alarm rate threshold (p = 17%). No evidence for subthreshold nu + gamma source populations is found among the track (p = 39%) or cascade (p = 60%) events. Exploring a possible correlation of high-energy neutrino directions with Fermi gamma-ray sky brightness identified in previous work yields no added support for this correlation. While TXS.0506+056, a blazar and variable (nontransient) Fermi gamma-ray source, has recently been identified as the first source of high-energy neutrinos, the challenges in reconciling observations of the Fermi gamma-ray sky, the IceCube high-energy cosmic neutrinos, and ultrahigh-energy cosmic rays using only blazars suggest a significant contribution by other source populations. Searches for transient sources of high-energy neutrinos thus remain interesting, with the potential for either neutrino clustering or multimessenger coincidence searches to lead to discovery of the first nu + gamma transients.
CRIS-Team WoS Importer:2020-01-03

A search for neutrino emission from the Fermi bubbles with the ANTARES telescope - Adrian-Martinez, S.; Albert, A.; Al Samarai, I.; Andre, Michel; Anton, Gisela; Anvar, S.; Ardid, Miguel; Astraatmadja, T.; Aubert, J-J; Baret, B.; Barrios-Marti, J.; Basa, S.; et al. (European Physical Journal C, 2014)
Analysis of the Fermi-LAT data has revealed two extended structures above and below the Galactic Centre emitting gamma rays with a hard spectrum, the so-called Fermi bubbles. Hadronic models attempting to explain the origin of the Fermi bubbles predict the emission of high-energy neutrinos and gamma rays with similar fluxes. The ANTARES detector, a neutrino telescope located in the Mediterranean Sea, has a good visibility to the Fermi bubble regions. Using data collected from 2008 to 2011 no statistically significant excess of events is observed and therefore upper limits on the neutrino flux in TeV range from the Fermi bubbles are derived for various assumed energy cutoffs of the source.

A search for new supernova remnant shells in the Galactic plane with HESS - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Andersson, T.; Anguener, E. O.; Arakawa, M.; Arrieta, M.; Aubert, P.; Backes, Michael; Balzer, A.; et al. (Astronomy & Astrophysics, 2018)
A search for new supernova remnants (SNRs) has been conducted using TeV gamma-ray data from the H.E.S.S. Galactic plane survey. As an identification criterion, shell morphologies that are characteristic for known resolved TeV SNRs have been used. Three new SNR candidates were identified in the H.E.S.S. data set with this method. Extensive multiwavelength searches for counterparts were conducted. A radio SNR candidate has been identified to be a counterpart to HESS J1534-571. The TeV source is therefore classified as a SNR. For the other two sources, HESS J1614-518 and HESS J1912 + 101, no identifying counterparts have been found, thus they remain SNR candidates for the time being. TeV-emitting SNRs are key objects in the context of identifying the accelerators of Galactic cosmic rays. The TeV emission of the relativistic particles in the new sources is examined in view of possible leptonic and hadronic emission scenarios, taking the current multiwavelength knowledge into account.
CRIS-Team WoS Importer:2020-01-15

A search for Secluded Dark Matter in the Sun with the ANTARES neutrino telescope - Adrián-Martínez, S.; Albert, A.; André, M.; Anton, Gisela; Ardid, M.; Aubert, J. J.; Avgitas, T.; Baret, B.; Barrios-Martí, J.; Basa, S.; Bertin, V.; Biagi, S.; et al. (Journal of Cosmology and Astroparticle Physics, 2016)
A search for Secluded Dark Matter annihilation in the Sun using 2007-2012 data of the ANTARES neutrino telescope is presented. Three different cases are considered: a) detection of dimuons that result from the decay of the mediator, or neutrino detection from: b) mediator that decays into a dimuon and, in turn, into neutrinos, and c) mediator that decays directly into neutrinos. As no significant excess over background is observed, constraints are derived on the dark matter mass and the lifetime of the mediator.
Keywords: dark matter detectors; dark matter experiments; neutrino astronomy; neutrino detectors

Asteroseismology of Massive Stars with the TESS Mission: The Runaway β Cep Pulsator PHL 346 = HN Aqr - Handler, Gerald; Pigulski, Andrzej; Daszynska-Daszkiewicz, Jadwiga; Irrgang, Andreas; Kilkenny, David; Guo, Zhao; Przybilla, Norbert; Alicavus, Filiz Kahraman; Kallinger, Thomas; Pascual-Granado, Javier; Niemczura, Ewa; Rozanski, Tomasz; et al. (Astrophysical Journal Letters, 2019)
We report an analysis of the first known β Cep pulsator observed by the Transiting Exoplanet Survey Satellite (TESS) mission, the runaway star PHL 346 = HN Aqr. The star, previously known as a singly periodic pulsator, has at least 34 oscillation modes excited, 12 of those in the g-mode domain and 22 p modes. Analysis of archival data implies that the amplitude and frequency of the dominant mode and the stellar radial velocity were variable over time. A binary nature would be inconsistent with the inferred ejection velocity from the Galactic disk of 420 km s -1 , which is too large to be survivable by a runaway binary system. A kinematic analysis of the star results in an age constraint (23 +1 Myr) that can be imposed on asteroseismic modeling and that can be used to remove degeneracies in the modeling process. Our attempts to match the excitation of the observed frequency spectrum resulted in pulsation models that were too young. Hence, asteroseismic studies of runaway pulsators can become vital not only in tracing the evolutionary history of such objects, but to understand the interior structure of massive stars in general. TESS is now opening up these stars for detailed asteroseismic investigation.
CRIS-Team Scopus Importer:2019-07-02
Keywords: stars: early-type; stars: individual (HN Aqr); stars: interiors; stars: kinematics and dynamics; stars: massive; stars: oscillations (including pulsations

A stripped helium star in the potential black hole binary LB-1 - Irrgang, Andreas; Geier, Stephan; Kreuzer, Simon; Pelisoli, Ingrid; Heber, Ulrich (Astronomy & Astrophysics, 2020)
Context. The recently claimed discovery of a massive (M-BH = 68(-13)(+11) M-circle dot) black hole in the Galactic solar neighborhood has led to controversial discussions because it severely challenges our current view of stellar evolution.Aims. A crucial aspect for the determination of the mass of the unseen black hole is the precise nature of its visible companion, the B-type star LSV +22 25. Because stars of different mass can exhibit B-type spectra during the course of their evolution, it is essential to obtain a comprehensive picture of the star to unravel its nature and, thus, its mass.Methods. To this end, we study the spectral energy distribution of LSV +22 25 and perform a quantitative spectroscopic analysis that includes the determination of chemical abundances for He, C, N, O, Ne, Mg, Al, Si, S, Ar, and Fe.Results. Our analysis clearly shows that LSV +22 25 is not an ordinary main sequence B-type star. The derived abundance pattern exhibits heavy imprints of the CNO bi-cycle of hydrogen burning, that is, He and N are strongly enriched at the expense of C and O. Moreover, the elements Mg, Al, Si, S, Ar, and Fe are systematically underabundant when compared to normal main-sequence B-type stars. We suggest that LSV +22 25 is a stripped helium star and discuss two possible formation scenarios. Combining our photometric and spectroscopic results with the Gaia parallax, we infer a stellar mass of 1.1 +/- 0.5 M-circle dot. Based on the binary system's mass function, this yields a minimum mass of 2-3 M-circle dot for the compact companion, which implies that it may not necessarily be a black hole but a massive neutron- or main sequence star.Conclusions. The star LSV +22 25 has become famous for possibly having a very massive black hole companion. However, a closer look reveals that the star itself is a very intriguing object. Further investigations are necessary for complete characterization of this object.
Keywords: stars: abundances; stars: chemically peculiar; stars: early-type; pulsars: individual: LS V+22 25

A study on UV emission from clouds with Mini-EUSO - Golzio, Alessio; Battisti, Matteo; Bertaina, Mario; Bolmgren, Karl; Cambiè, Giorgio; Casolino, Marco; Cassardo, Claudio; Cremonini, Roberto; Ferrarese, Silvia; Fuglesang, Christer; Manfrin, Massimiliano; Marcelli, Laura; et al. (Proceedings of Science, 2022)
Mini-EUSO is the first mission of the JEM-EUSO program located on the International Space Station. One of the main goals of the mission is to provide valuable scientific data in view of future large missions devoted to study Ultra-High Energy Cosmic Rays (UHECRs) from space by exploiting the fluorescence emission generated by Extensive Air Showers (EAS) developing in the atmosphere. A space mission like Mini-EUSO experiences continuous changes in atmospheric conditions, including the cloud presence. The influence of clouds on space-based observation is, therefore, an important topic to investigate as it might alter the instantaneous exposure for EAS detection or deteriorate the quality of the EAS images with consequences on the reconstructed EAS parameters. For this purpose, JEM-EUSO is planning to have an IR camera and a lidar as part of its Atmospheric Monitoring System. At the same time, it would be extremely beneficial if the UV camera itself would be able to detect the presence of clouds, at least in some specific conditions. For this reason, we analyze a few case studies by comparing the pixel count rates from Mini-EUSO during orbits with the cloud cover (as cloud fraction). This quantity is retrieved from the Global Forecast System (GFS) model at different height levels over the Mini-EUSO trajectory. The results of this analysis are reported.
CRIS-Team Scopus Importer:2022-12-23

A Supernova Remnant Counterpart for HESS J1832-085 - Maxted, Nigel I.; Filipović, M. D.; Hurley-Walker, N.; Bojičić, I.; Rowell, G. P.; Haberl, F.; Ruiter, A. J.; Seitenzahl, I. R.; Panther, F.; Wong, G. F.; Braiding, C.; Burton, M.; et al. (Astrophysical Journal, 2019)
We examine the new Galactic supernova remnant (SNR) candidate, G23.11+0.18, as seen by the Murchison Widefield Array radio telescope. We describe the morphology of the candidate and find a spectral index of -0.63 ± 0.05 in the 70-170 MHz domain. Coincident TeV gamma-ray detection in High Energy Stereoscopic System (HESS) data supports the SNR nature of G23.11+0.18 and suggests that G23.11+0.18 is accelerating particles beyond TeV energies, thus making this object a promising new cosmic-ray hadron source candidate. The remnant cannot be seen in current optical, infrared and X-ray data sets. We do find, however, a dip in CO-traced molecular gas at a line-of-sight velocity of ∼85 km s-1, suggesting the existence of a G23.11+0.18 progenitor wind-blown bubble. Furthermore, the discovery of molecular gas clumps at a neighboring velocity toward HESS J1832-085 adheres to the notion that a hadronic gamma-ray production mechanism is plausible toward the north of the remnant. Based on these morphological arguments, we propose an interstellar medium association for G23.11+0.18 at a kinematic distance of 4.6 ± 0.8 kpc.
CRIS-Team Scopus Importer:2019-11-26

A Suzaku, NuSTAR, and XMM-Newton view on variable absorption and relativistic reflection in NGC 4151 - Beuchert, Tobias; Markowitz, A. G.; Dauser, Thomas; Garcia, Javier; Keck, M. L.; Wilms, Jörn; Kadler, M.; Brenneman, L. W.; Zdziarski, A. A. (Astronomy & Astrophysics, 2017)
We disentangle X-ray disk reflection from complex line-of-sight absorption in the nearby Seyfert NGC 4151, using a suite of Suzaku, NuSTAR, and XMM-Newton observations. Extending upon earlier published work, we pursue a physically motivated model using the latest angle-resolved version of the lamp-post geometry reflection model RELXILLCP_LP together with a Comptonization continuum. We use the long-look simultaneous Suzaku/NuSTAR observation to develop a baseline model wherein we model reflected emission as a combination of lamp-post components at the heights of 1.2 and 15.0 gravitational radii. We argue for a vertically extended corona as opposed to two compact and distinct primary sources. We find two neutral absorbers (one full-covering and one partial-covering), an ionized absorber (log xi = 2 : 8), and a highly-ionized ultra-fast outflow, which have all been reported previously. All analyzed spectra are well described by this baseline model. The bulk of the spectral variability between similar to 1 keV and similar to 6 keV can be accounted for by changes in the column density of both neutral absorbers, which appear to be degenerate and inversely correlated with the variable hard continuum component flux. We track variability in absorption on both short (2 d) and long (similar to 1 yr) timescales; the observed evolution is either consistent with changes in the absorber structure (clumpy absorber at distances ranging from the broad line region to the inner torus or a dusty radiatively driven wind) or a geometrically stable neutral absorber that becomes increasingly ionized at a rising flux level. The soft X-rays below 1 keV are dominated by photoionized emission from extended gas that may act as a warm mirror for the nuclear radiation.
Keywords: galaxies: active; galaxies: nuclei; galaxies: individual: NGC4151; galaxies: Seyfert; X-rays: galaxies

A Suzaku X-ray observation of one orbit of the supergiant fast X-ray transient IGR J16479-4514 - Sidoli, Lara; Esposito, Paolo; Sguera, Vito; Bodaghee, A.; Tomsick, J. A.; Pottschmidt, K.; Rodriguez, Jerome; Romano, Patrizia; Wilms, Jörn (Monthly Notices of the Royal Astronomical Society, 2013)
We report on a 250 ks long X-ray observation of the supergiant fast X-ray transient IGR J16479-4514 performed with Suzaku in 2012 February. During this observation, about 80 per cent of the short orbital period (P-orb similar to 3.32 d) was covered as continuously as possible for the first time. The source light curve displays variability of more than two orders of magnitude, starting with a very low emission state (10(-13) erg cm(-2) s(-1); 1-10 keV) lasting the first 46 ks, consistent with being due to the X-ray eclipse by the supergiant companion. The transition to the uneclipsed X-ray emission is energy dependent. Outside the eclipse, the source spends most of the time at a level of 6-7 x 10(-12) erg cm(-2) s(-1) punctuated by two structured faint flares with a duration of about 10 and 15 ks, respectively, reaching a peak flux of 3-4 x 10(-11) erg cm(-2) s(-1), separated by about 0.2 in orbital phase. Remarkably, the first faint flare occurs at a similar orbital phase of the bright flares previously observed in the system. This indicates the presence of a phase-locked large-scale structure in the supergiant wind, driving a higher accretion rate on to the compact object. The average X-ray spectrum is hard and highly absorbed, with a column density, N-H, of 1023 cm-2, clearly in excess of the interstellar absorption. There is no evidence for variability of the absorbing column density, except that during the eclipse, where a less absorbed X-ray spectrum is observed. A narrow Fe K alpha emission line at 6.4 keV is viewed along the whole orbit, with an intensity which correlates with the continuum emission above 7 keV. The scattered component visible during the X-ray eclipse allowed us to directly probe the wind density at the orbital separation, resulting in rho(w) = 7 x 10(-14) g cm(-3). Assuming a spherical geometry for the supergiant wind, the derived wind density translates into a ratio. M-w/v(infinity) = 7 x 10(-17) M-circle dot km(-1) which, assuming terminal velocities in a large range 500-3000 km s(-1), implies an accretion luminosity two orders of magnitude higher than that observed. As a consequence, a mechanism should be at work reducing the mass accretion rate. Different possibilities are discussed.
Keywords: accretion; accretion discs; X-rays: binaries; supergiants; X-rays: individual: IGR J16479-4514

Asymmetric jet production in the active galactic nucleus of NGC 1052 - Baczko, A-K; Schulz, R.; Kadler, M.; Ros, Eduardo; Perucho, M.; Fromm, C. M.; Wilms, Jörn (Astronomy & Astrophysics, 2019)
Context. Few active galactic nuclei (AGN) reveal double-sided jet systems. However, these systems are crucial to understand basic physical properties of extragalactic jets.
CRIS-Team WoS Importer:2019-03-08

ATCA study of Small Magellanic Cloud supernova remnant 1E 0102.2–7219 - Alsaberi, Rami Z.E.; Filipović, M. D.; Dai, S.; Sano, H.; Kothes, R.; Payne, J. L.; Bozzetto, L. M.; Brose, R.; Collischon, Caroline; Crawford, E. J.; Haberl, F.; Hill, T.; et al. (Monthly Notices of the Royal Astronomical Society, 2024)
We present new and archival Australia Telescope Compact Array and Atacama Large Millimeter/submillimeter Array data of the Small Magellanic Cloud supernova remnant 1E 0102.2–7219 at 2100, 5500, 9000, and 108 000 MHz; as well as H I data provided by the Australian Square Kilometre Array Pathfinder. The remnant shows a ring-like morphology with a mean radius of 6.2 pc. The 5500 MHz image reveals a bridge-like structure, seen for the first time in a radio image. This structure is also visible in both optical and X-ray images. In the 9000 MHz image, we detect a central feature that has a flux density of 4.3 mJy but rule out a pulsar wind nebula origin, due to the lack of significant polarization towards the central feature with an upper limit of 4 per cent. The mean fractional polarization for 1E 0102.2–7219 is 7 ± 1 and 12 ± 2 per cent for 5500 and 9000 MHz, respectively. The spectral index for the entire remnant is −0.61 ± 0.01. We estimate the line-of-sight magnetic field strength in the direction of 1E 0102.2–7219 of ∼44 μG with an equipartition field of 65 ± 5 μG. This latter model uses the minimum energy of the sum of the magnetic field and cosmic ray electrons only. We detect an H I cloud towards this remnant at the velocity range of ∼160–180 km s−1 and a cavity-like structure at the velocity of 163.7–167.6 km s−1. We do not detect CO emission towards 1E 0102.2–7219.
CRIS-Team Scopus Importer:2023-12-01
Keywords: ISM: individual objects; ISM: magnatic fields; ISM: supernova remnants; Radio continuum: ISM

Athena Wide Field Imager key science drivers - Rau, Arne; Nandra, Kirpal; Aird, James; Comastri, Andrea; Dauser, Thomas; Merloni, Andrea; Pratt, Gabriel W.; Reiprich, Thomas H.; Fabian, Andy C.; Georgakakis, Antonis; Güdel, Manuel; Rózańska, Agata; et al. (Space Telescopes and Instrumentation 2016: Ultraviolet to Gamma Ray, 2016)
The Wide Field Imager (WFI) is one of two instruments for the Advanced Telescope for High-ENergy Astrophysics (Athena). In this paper we summarise three of the many key science objectives for the WFI - the formation and growth of supermassive black holes, non-gravitational heating in clusters of galaxies, and spin measurements of stellar mass black holes - and describe their translation into the science requirements and ultimately instrument requirements. The WFI will be designed to provide excellent point source sensitivity and grasp for performing wide area surveys, surface brightness sensitivity, survey power, and absolute temperature and density calibration for in-depth studies of the outskirts of nearby clusters of galaxies and very good high-count rate capability, throughput, and low pile-up, paired with very good spectral resolution, for detailed explorations of bright Galactic compact objects.
Keywords: ATHENA; Wide Field Imager

Athena X-IFU synthetic observations of galaxy clusters to probe the chemical enrichment of the Universe - Cucchetti, E.; Pointecouteau, E.; Peille, P.; Clerc, N.; Rasia, Elena; Biffi, V.; Borgani, S.; Tornatore, L.; Dolag, K.; Roncarelli, M.; Gaspari, M.; Ettori, S.; et al. (Astronomy & Astrophysics, 2018)
Answers to the metal production of the Universe can be found in galaxy clusters, notably within their intra-cluster medium (ICM). The X-ray Integral Field Unit (X-IFU) on board the next-generation European X-ray observatory Athena (2030s) will provide the necessary leap forward in spatially-resolved spectroscopy required to disentangle the intricate mechanisms responsible for this chemical enrichment. In this paper, we investigate the future capabilities of the X-IFU in probing the hot gas within galaxy clusters. From a test sample of four clusters extracted from cosmological hydrodynamical simulations, we present comprehensive synthetic observations of these clusters at different redshifts (up to z <= 2) and within the scaled radius R-500 performed using the instrument simulator SIXTE. Through 100 ks exposures, we demonstrate that the X-IFU will provide spatially resolved mapping of the ICM physical properties with little to no biases ((sic)5%) and well within statistical uncertainties. The detailed study of abundance profiles and abundance ratios within R-500 also highlights the power of the X-IFU in providing constraints on the various enrichment models. From synthetic observations out to z = 2, we have also quantified its ability to track the chemical elements across cosmic time with excellent accuracy, and thereby to investigate the evolution of metal production mechanisms as well as the link to the stellar initial mass-function. Our study demonstrates the unprecedented capabilities of the X-IFU of unveiling the properties of the ICM but also stresses the data analysis challenges faced by future high-resolution X-ray missions such as Athena.
Keywords: galaxies: clusters: intracluster medium; galaxies: abundances; galaxies: fundamental parameters; techniques: imaging spectroscopy; methods: numerical; X-rays: galaxies: clusters

Athena X-ray Integral Field Unit on-board Event Processor: Analysis of performance of two triggering algorithms - Cobo, Beatriz; Teresa Ceballos, Mara; Peille, Philippe; Mesnager, Jean-Michel; Wilms, Jörn; Dauser, Thomas; Kirsch, Christian; Pinsard, Frederic; Cara, Christophe; Gros, Michel; Ravera, Laurent; Bandler, Simon; et al. (2018)
In the framework of the ESA Athena mission, the X-ray Integral Field Unit (X-IFU) micro-calorimeter will provide unprecedented spatially resolved high-resolution X-ray spectroscopy. For this purpose, the on-board Event Processor (EP) must initially trigger the current pulses induced by the X-ray photons hitting the detector to proceed with a reconstruction which provides the arrival time, spatial location and energy of each event. The current event triggering design is implemented in two stages: one initial trigger of the low-pass filtered derivative of the raw data to extract records containing pulses and a second stage performing a fine detection to look for all the pulses in the record. In order to establish the current baseline detection technique of the EP in the X-IFU instrument, an assessment of the capabilities of different triggering algorithms is required, both in terms of performance (detection efficiency) and computational load, as processing will take place on-board. We present a comparison of two detection algorithms, the Simplest Threshold Crossing (STC) and the model-dependent Adjusted Derivative (AD). The analysis also evaluates the (possible) negative effect of different instrumental scenarios as a reduced sampling rate. The evaluations point out that the simplest algorithm STC shows worse performance than AD for the smallest pulses separations and the lowest secondary energies. Nevertheless, checking the expected number of such pulses combinations in a typical bright source observation, we conclude that it does not have impact in the science. Moreover, the savings in the computational resources and calibration needs make STC a valuable option.
Keywords: Athena; X-ray Integral Field Unit; X-ray spectroscopy; space telescopes; instrumentation; Event Processor; pulse detection; performance analysis

A variable-density absorption event in NGC 3227 mapped with Suzaku and Swift - Beuchert, Tobias; Markowitz, Alex; Krauß, Felicia; Miniutti, Giovanni; Longinotti, A. L.; Guainazzi, M.; De La Calle Perez, Ignacio; Malkan, M.; Elvis, M.; Miyaji, Takamitsu; Hiriart, David; Lopez, J. M.; et al. (Astronomy & Astrophysics, 2015)
Context. The morphology of the circumnuclear gas accreting onto supermassive black holes in Seyfert galaxies remains a topic of much debate. As the innermost regions of active galactic nuclei (AGN) are spatially unresolved, X-ray spectroscopy, and in particular line-of-sight absorption variability, is a key diagnostic to map out the distribution of gas.Aims. Observations of variable X-ray absorption in multiple Seyferts and over a wide range of timescales indicate the presence of clumps/clouds of gas within the circumnuclear material. Eclipse events by clumps transiting the line of sight allow us to explore the properties of the clumps over a wide range of radial distances from the optical/UV broad line region (BLR) to beyond the dust sublimation radius. Time-resolved absorption events have been extremely rare so far, but suggest a range of density profiles across Seyferts. We resolve a weeks-long absorption event in the Seyfert NGC 3227.Methods. We examine six Suzaku and 12 Swift observations from a 2008 campaign spanning five weeks. We use a model accounting for the complex spectral interplay of three absorbers with different levels of ionization. We perform time-resolved spectroscopy to discern the absorption variability behavior. We also examine the IR to X-ray spectral energy distribution (SED) to test for reddening by dust.Results. The 2008 absorption event is due to moderately-ionized (log xi similar to 1.2-1.4) gas covering 90% of the line of sight. We resolve the density profile to be highly irregular, in contrast to a previous symmetric and centrally-peaked event mapped with RXTE in the same object. The UV data do not show significant reddening, suggesting that the cloud is dust-free.Conclusions. The 2008 campaign has revealed a transit by a filamentary, moderately-ionized cloud of variable density that is likely located in the BLR, and possibly part of a disk wind.
Keywords: galaxies: active; galaxies: Seyfert; galaxies: nuclei

A Variable Ionized Disk Wind in the Black Hole Candidate EXO 1846-031 - Wang, Yanan; Ji, Long; Garcia, Javier A.; Dauser, Thomas; Mendez, Mariano; Mao, Junjie; Tao, Lian; Altamirano, Diego; Maggi, Pierre; Zhang, S. N.; Ge, M. Y.; Zhang, L.; et al. (Astrophysical Journal, 2020)
After 34 yr, the black hole candidate EXO 1846-031 went into outburst again in 2019. We investigate its spectral properties in the hard intermediate and the soft states with NuSTAR and Insight-HXMT. A reflection component has been detected in the two spectral states but possibly originating from different illumination spectra: in the intermediate state, the illuminating source is attributed to a hard coronal component, which has been commonly observed in other X-ray binaries, whereas in the soft state, the reflection is probably produced by disk self-irradiation. Both cases support EXO 1846-031 as a low-inclination system of ∼ 40. An absorption line is clearly detected at ∼7.2 keV in the hard intermediate state, corresponding to a highly ionized disk wind (log, ξ > 6.1) with a velocity of up to 0.06c. Meanwhile, quasi-simultaneous radio emissions have been detected before and after the X-rays, implying the coexistence of disk winds and jets in this system. If only the high-flux segment of the NuSTAR observation is considered, the observed wind appears to be magnetically driven. The absorption line disappeared in the soft state and a narrow emission line appeared at ∼6.7 keV on top of the reflection component, which may be evidence for disk winds, but data with higher spectral resolution are required to examine this.
CRIS-Team Scopus Importer:2021-04-19

A very-high-energy component deep in the γ-ray burst afterglow - Abdalla, H.; Adam, R.; Aharonian, F.; Ait Benkhali, F.; Angüner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Ashkar, H.; Backes, M.; Barbosa Martins, V.; Barnard, M.; et al. (Nature, 2019)
Gamma-ray bursts (GRBs) are brief flashes of γ-rays and are considered to be the most energetic explosive phenomena in the Universe1. The emission from GRBs comprises a short (typically tens of seconds) and bright prompt emission, followed by a much longer afterglow phase. During the afterglow phase, the shocked outflow—produced by the interaction between the ejected matter and the circumburst medium—slows down, and a gradual decrease in brightness is observed2. GRBs typically emit most of their energy via γ-rays with energies in the kiloelectronvolt-to-megaelectronvolt range, but a few photons with energies of tens of gigaelectronvolts have been detected by space-based instruments3. However, the origins of such high-energy (above one gigaelectronvolt) photons and the presence of very-high-energy (more than 100 gigaelectronvolts) emission have remained elusive4. Here we report observations of very-high-energy emission in the bright GRB 180720B deep in the GRB afterglow—ten hours after the end of the prompt emission phase, when the X-ray flux had already decayed by four orders of magnitude. Two possible explanations exist for the observed radiation: inverse Compton emission and synchrotron emission of ultrarelativistic electrons. Our observations show that the energy fluxes in the X-ray and γ-ray range and their photon indices remain comparable to each other throughout the afterglow. This discovery places distinct constraints on the GRB environment for both emission mechanisms, with the inverse Compton explanation alleviating the particle energy requirements for the emission observed at late times. The late timing of this detection has consequences for the future observations of GRBs at the highest energies.
CRIS-Team Scopus Importer:2019-12-03

A VLBI investigation of high-energy neutrino emitter candidates - Nanci, C.; Giroletti, M.; Orienti, M.; Migliori, G.; Moldón, J.; Garrappa, S.; Kadler, M.; Ros, E.; Buson, S.; An, T.; Pérez-Torres, M.; D'Ammando, F.; et al. (Proceedings of Science, 2023)
High angular resolution observations with the very long baseline interferometry (VLBI) provide crucial tests for the association of neutrinos with blazars. The VLBI follow-up observations have led to the unveiling of VLBI-scales properties potentially linked to the neutrino production in the jet of the blazar TXS 0506+056, the first source associated with a neutrino event. In order to collect new pieces of evidence on the connection between radio properties in blazars and neutrino production, we performed a VLBI investigation of gamma-ray blazars observed in spatial coincidence with four neutrino events, detected by the IceCube observatory between 2019 and 2020. We compared our new observations with archival data for selected candidate counterparts with the aim of searching for hints of a possible connection between the neutrino events and those sources. This contribution presents some of the results of the first exploratory VLBI follow-up campaign, with a focus on the results of the most promising targets. A brief summary of the new follow-up observations for IceCube events carried out during 2022 is also given. Among these, there are two events, IC 211208A and IC 220205A, the candidate counterparts of which are flaring at the neutrino detection. They are the blazar PKS 0735+038 and the extremely peculiar source PKS B1413+135, respectively.
CRIS-Team Scopus Importer:2023-09-22

A Wolf-Rayet/black-hole X-ray binary candidate in NGC 300 - Wilms, Jörn; et al. (Astronomy & Astrophysics, 2007)
Context. Wolf Rayet/black hole binaries are believed to exist as a later evolutionary product of high-mass X-ray binaries. Hundreds of such binaries may exist in galaxies, but only a few of them are close enough to be observed as X-ray binaries. Only a couple of candidates have been reported so far.Aims. Based on XMM-Newton observations, we report the positional coincidence of the brightest X-ray source in NGC 300 (NGC 300 X-1) with a Wolf-Rayet candidate. Temporal and spectral analysis of the X-ray source is performed.Methods. We determine an accurate X-ray position of the object, and derive light curves, spectra and flux in four XMM-Newton observations.Results. The positions of the X-ray source and the helium star candidate coincide within 0".11 +/- 0".45. The X-ray light curves show irregular variability. During one XMM-Newton observation, the flux increased by about a factor of ten in 10 h. The spectrum can be modelled by a power-law with Gamma similar to 2.45 with additional relatively weak line emission, notably around 0.95 keV. The mean observed (absorbed) luminosity in the 0.2-10 keV band is similar to 2 x 10(38) erg s(-1).Conclusions. NGC 300 X-1 is a good candidate for a Wolf-Rayet/black-hole X-ray binary: its position coincides with a Wolf-Rayet candidate and the unabsorbed X-ray luminosity reached L0.2-10 keV similar to 1 x 10(39) erg s(-1), suggesting the presence of a black hole.
Keywords: galaxies : individual : NGC 300; X-rays : binaries; stars : Wolf-Rayet

Binaries discovered by the MUCHFUSS project: FBS 0117+396: An sdB+dM binary with a pulsating primary - Ostensen, R. H.; Geier, S.; Schaffenroth, Veronika; Telting, J. H.; Bloemen, S.; Nemeth, Peter; Beck, P. G.; Lombaert, R.; Papics, P. I.; Tillich, A.; Ziegerer, Eva; Fox Machado, L.; et al. (Astronomy & Astrophysics, 2013)
The project Massive Unseen Companions to Hot Faint Underluminous Stars from SDSS (MUCHFUSS) aims to discover subdwarf-B stars with massive compact companions such as overmassive white dwarfs (M > 1.0 M âŠ™), neutron stars or black holes. From the 127 subdwarfs with substantial radial-velocity variations discovered in the initial survey, a number of interesting objects have been selected for extensive follow-up. After an initial photometry run with BUSCA revealed that FBS 0117+396 is photometrically variable both on long and short timescales, we chose it as an auxiliary target during a 6-night multi-color photometry run with Ultracam. Spectroscopy was obtained at a number of observatories in order to determine the binary period and obtain a radial-velocity amplitude. After establishing an orbital period of P = 0.252 d, and removing the signal associated with the irradiated hemisphere of the M-dwarf companion, we were able to detect ten pulsation periods in the Fourier spectrum of the light curve. Two pulsation modes are found to have short periods of 337 and 379 s, and at least eight modes are found with periods between 45 min and 2.5 h. This establishes that FBS 0117+396 is an sdB+dM reflection binary, in which the primary is a hybrid pulsator, and the first one found with this particular mélange of flavours. © ESO, 2013.
CRIS-Team Scopus Importer:2020-12-21
Keywords: Binaries: close; Stars: individual: FBS 0117+396; Stars: oscillations; Subdwarfs; Surveys

Binaries discovered by the MUCHFUSS project: SDSS J08205+0008 - An eclipsing subdwarf B binary with a brown dwarf companion - Geier, Stephan; Schaffenroth, Veronika; Drechsel, Horst; Heber, Ulrich; Kupfer, Thomas; Tillich, A.; Ostensen, R. H.; Smolders, K.; Degroote, P.; Maxted, P. F. L.; Barlow, B. N.; Gaensicke, B. T.; et al. (Astrophysical Journal Letters, 2011)
Hot subdwarf B stars (sdBs) are extreme horizontal branch stars believed to originate from close binary evolution. Indeed about half of the known sdB stars are found in close binaries with periods ranging from a few hours to a few days. The enormous mass loss required to remove the hydrogen envelope of the red-giant progenitor almost entirely can be explained by common envelope ejection. A rare subclass of these binaries are the eclipsing HW Vir binaries where the sdB is orbited by a dwarf M star. Here, we report the discovery of an HW Vir system in the course of the MUCHFUSS project. A most likely substellar object (≃0.068 M⊙) was found to orbit the hot subdwarf J08205+0008 with a period of 0.096 days. Since the eclipses are total, the system parameters are very well constrained. J08205+0008 has the lowest unambiguously measured companion mass yet found in a subdwarf B binary. This implies that the most likely substellar companion has not only survived the engulfment by the red-giant envelope, but also triggered its ejection and enabled the sdB star to form. The system provides evidence that brown dwarfs may indeed be able to significantly affect late stellar evolution. © 2011. The American Astronomical Society. All rights reserved.
CRIS-Team Scopus Importer:2020-12-21
Keywords: binaries: spectroscopic; brown dwarfs; stars: horizontal-branch; stars: individual

Binaries discovered by the MUCHFUSS project: SDSS J162256.66 + 473051.1: An eclipsing subdwarf B binary with a brown dwarf companion - Schaffenroth, Veronika; Geier, Stephan; Heber, Ulrich; Kupfer, Thomas; Ziegerer, Eva; Heuser, Christian; Classen, Lew; Cordes, O. (Astronomy & Astrophysics, 2014)
Hot subdwarf B stars (sdBs) are core helium-burning stars located on the extreme horizontal branch. About half of the known sdB stars are found in close binaries. Their short orbital periods of 1.2 h to a few days suggest that they are post common-envelope systems. Eclipsing hot subdwarf binaries are rare but are important in determining the fundamental stellar parameters. Low-mass companions are identified by the reflection effect. In most cases, the companion is a main sequence star near the stellar mass limit. Here, we report the discovery of an eclipsing hot subdwarf binary SDSS J162256.66+473051.1 (J1622) with very short orbital period (0.0697 d), which has been found in the course of the MUCHFUSS project. The lightcurve shows grazing eclipses and a prominent reflection effect. An analysis of the light-and radial velocity (RV) curves indicated a mass ratio of q = 0.1325, an RV semi-amplitude K = 47.2 km s -1, and an inclination of i = 72.33°. We show that a companion mass of 0.064 MŠ(tm), which is well below the hydrogen-burning limit, is the most plausible solution, which implies a mass close to the canonical mass (0.47 MŠ(tm)) of the sdB star. Therefore, the companion is a brown dwarf, which has not only survived the engulfment by the red-giant envelope but also triggered its ejection and enabled the sdB star to form. The rotation of J1622 is expected to be tidally locked to the orbit. However, J1622 rotates too slowly (vrot = 74.5 ± 7 kmâ‰ s-1) to be synchronized, challenging tidal interaction models. © 2014 ESO.
CRIS-Team Scopus Importer:2020-12-21
Keywords: Binaries: eclipsing; Binaries: spectroscopic; Brown dwarfs; Stars: fundamental parameters; Subdwarfs

Binaries discovered by the SPY project: V. GD687 - A massive double degenerate binary progenitor that will merge within a Hubble time - Geier, Stephan; Heber, Ulrich; Kupfer, Thomas; Napiwotzki, R. (Astronomy & Astrophysics, 2010)
Aims. The ESO SN Ia Progenitor Survey (SPY) aims at finding merging double degenerate binaries as candidates for supernova type Ia (SN Ia) explosions. A white dwarf merger has also been suggested to explain the formation of rare types of stars like R CrB, extreme helium or He sdO stars. Here we present the hot subdwarf B binary GD 687, which will merge in less than a Hubble time. Methods. The orbital parameters of the close binary have been determined from time resolved spectroscopy. Since GD 687 is a single-lined binary, the spectra contain only information about the subdwarf primary and its orbit. From high resolution spectra the projected rotational velocity was derived. Assuming orbital synchronisation, the inclination of the system and the mass of the unseen companion were constrained. Results. The derived inclination is i = 39.3+6.2-5.6 °. The mass M2 = 0.71 -0.21+0.22 M⊙ indicates that the companion must be a white dwarf, most likely of C/O composition. This is only the fourth case that an sdB companion has been proven to be a white dwarf unambiguously. Its mass is somewhat larger than the average white dwarf mass, but may be as high as 0.93 M⊙ in which case the total mass of the system comes close to the Chandrasekhar limit. Conclusions. GD 687 will evolve into a double degenerate system and merge to form a rare supermassive white dwarf with a mass in excess of solar. A death in a sub-Chandrasekhar supernova is also conceivable. © ESO, 2010.
CRIS-Team Scopus Importer:2020-12-21
Keywords: Binaries: spectroscopic; Stars: individual: GD 687; Stars: rotation; Subdwarfs; Supernovae: general

Binaries discovered by the SPY survey: VI. Discovery of a low mass companion to the hot subluminous planetary nebula central star EGB5 - A recently ejected common envelope? - Geier, Stephan; Napiwotzki, R.; Heber, Ulrich; Nelemans, Gijs (Astronomy & Astrophysics, 2011)
Hot subdwarf B stars (sdBs) in close binary systems are assumed to be formed via common envelope ejection. According to theoretical models, the amount of energy and angular momentum deposited in the common envelope scales with the mass of the companion. That low mass companions near or below the core hydrogen-burning limit are able to trigger the ejection of this envelope is well known. The currently known systems have very short periods ≃0.1-0 d. Here we report the discovery of a low mass companion (M2 > 0.14⊙) orbiting the sdB star and central star of a planetary nebula EGB 5 with an orbital period of 16.5 d at a minimum separation of 23⊙. Its long period is only just consistent with the energy balance prescription of the common envelope. The marked difference between the short and long period systems will provide strong constraints on the common envelope phase, in particular if the masses of the sdB stars can be measured accurately. Due to selection effects, the fraction of sdBs with low mass companions and similar or longer periods may be quite high. Low mass stellar and substellar companions may therefore play a significant role for the still unclear formation of hot subdwarf stars. Furthermore, the nebula around EGBâ€‰ 5 may be the remnant of the ejected common envelope making this binary a unique system to study this short und poorly understood phase of binary evolution. © ESO 2011.
CRIS-Team Scopus Importer:2020-12-21
Keywords: binaries: spectroscopic; subdwarfs

Black hole lightning due to particle acceleration at subhorizon scales - Aleksic, J.; Ansoldi, S.; Antonelli, L. A.; Antoranz, Pedro; Babic, A.; Bangale, P.; Barrio, J. A.; Becerra Gonzalez, Josefa; Bednarek, Wlodek; Bernardini, E.; Biasuzzi, B.; Biland, A.; et al. (Science, 2014)
Supermassive black holes with masses of millions to billions of solar masses are commonly found in the centers of galaxies. Astronomers seek to image jet formation using radio interferometry but still suffer from insufficient angular resolution. An alternative method to resolve small structures is to measure the time variability of their emission. Here we report on gamma-ray observations of the radio galaxy IC 310 obtained with the MAGIC (Major Atmospheric Gamma-ray Imaging Cherenkov) telescopes, revealing variability with doubling time scales faster than 4.8 min. Causality constrains the size of the emission region to be smaller than 20% of the gravitational radius of its central black hole. We suggest that the emission is associated with pulsar-like particle acceleration by the electric field across a magnetospheric gap at the base of the radio jet.

Blue extreme disk-runaway stars with Gaia EDR3 - Irrgang, Andreas; Dimpel, Markus; Heber, Ulrich; Raddi, Roberto (Astronomy & Astrophysics, 2021)
Since the discovery of hypervelocity stars in 2005, it has been widely believed that only the disruption of a binary system by a supermassive black hole at the Galactic center (GC), that is, the so-called Hills mechanism, is capable of accelerating stars to beyond the Galactic escape velocity. In the meantime, however, driven by the Gaia space mission, there is mounting evidence that many of the most extreme high-velocity early-type stars at high Galactic latitudes do originate in the Galactic disk and not in the GC. Moreover, the ejection velocities of these extreme disk-runaway stars exceed the predicted limits of the classical scenarios for the production of runaway stars. Based on proper motions from the Gaia early data release 3 and on recent and new spectrophotometric distances, we studied the kinematics of 30 such extreme disk-runaway stars, allowing us to deduce their spatial origins in and their ejection velocities from the Galactic disk with unprecedented precision. Only three stars in the sample have past trajectories that are consistent with an origin in the GC, most notably S5-HVS 1, which is the most extreme object in the sample by far. All other program stars are shown to be disk runaways with ejection velocities that sharply contrast at least with classical ejection scenarios. They include HVS 5 and HVS 6, which are both gravitationally unbound to the Milky Way. While most stars originate from within a galactocentric radius of 15 kpc, which corresponds to the observed extent of the spiral arms, a group of five stars stems from radii of about 21-29 kpc. This indicates a possible link to outer Galactic rings and a potential origin from infalling satellite galaxies.
CRIS-Team Scopus Importer:2021-04-09
Keywords: Stars: distances; Stars: early-type; Stars: fundamental parameters; Stars: kinematics and dynamics

BRIGHT ACTIVE GALACTIC NUCLEI SOURCE LIST FROM THE FIRST THREE MONTHS OF THE FERMI LARGE AREA TELESCOPE ALL-SKY SURVEY - Abdo, A. A.; Ackermann, Markus; Ajello, M.; Atwood, W. B.; Axelsson, Magnus; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Baughman, B. M.; Bechtol, K.; Bellazzini, R.; et al. (Astrophysical Journal, 2009)
The first three months of sky-survey operation with the Large Area Telescope (LAT) onboard the Fermi Gamma-Ray Space Telescope reveal 132 bright sources at |b| > 10 degrees with test statistic greater than 100 ( corresponding to about 10 sigma). Two methods, based on the CGRaBS, CRATES, and BZCat catalogs, indicate high-confidence associations of 106 of these sources with known active galactic nuclei (AGNs). This sample is referred to as the LAT Bright AGN Sample (LBAS). It contains two radio galaxies, namely, Centaurus A and NGC 1275, and 104 blazars consisting of 58 flat spectrum radio quasars (FSRQs), 42 BL Lac objects, and 4 blazars with unknown classification. Four new blazars were discovered on the basis of the LAT detections. Remarkably, the LBAS includes 10 high-energy-peaked BL Lacs (HBLs), sources which were previously difficult to detect in the GeV range. Another 10 lower-confidence associations are found. Only 33 of the sources, plus two at |b| < 10 degrees, were previously detected with Energetic Gamma-Ray Experiment Telescope( EGRET), probably due to variability. The analysis of the gamma-ray properties of the LBAS sources reveals that the average GeV spectra of BL Lac objects are significantly harder than the spectra of FSRQs. No significant correlation between radio and peak gamma-ray fluxes is observed. Blazar log N-log S distributions and luminosity functions are constructed to investigate the evolution of the different blazar classes, with positive evolution indicated for FSRQs but none for BL Lacs. The contribution of LAT blazars to the total extragalactic gamma-ray intensity is estimated.
CRIS-Team WoS Importer:2020-01-15

Broadband maps of eROSITA and their comparison with the ROSAT survey - Zheng, Xueying; Ponti, Gabriele; Freyberg, Michael; Sanders, Jeremy; Locatelli, Nicola; Merloni, Andrea; Strong, Andy; Sasaki, Manami; Comparat, Johan; Becker, Werner; Kerp, Juergen; Maitra, Chandreyee; et al. (Astronomy & Astrophysics, 2024)
By June of 2020, the extended ROentgen Survey with an Imaging Telescope Array (eROSITA) on board the Spectrum Roentgen Gamma observatory had completed its first of the planned eight X-ray all-sky survey (eRASS1). The large effective area of the X-ray telescope makes it ideal for a survey of the faint X-ray diffuse emission over half of the sky with an unprecedented energy resolution and position accuracy. In this work, we produce the X-ray diffuse emission maps of the eRASS1 data with a current calibration, covering the energy range from 0.2 to 8.0 keV. We validated these maps by comparison with X-ray background maps derived from the ROSAT All Sky Survey (RASS). We generated X-ray images with a pixel area of 9 arcmin2 using the observations available to the German eROSITA consortium. The contribution of the particle background to the photons was subtracted from the final maps. We also subtracted all the point sources above a flux threshold dependent on the goal of the subtraction, exploiting the eRASS1 catalog that will soon be available. The accuracy of the eRASS1 maps is shown by a flux match to the RASS X-ray maps, obtained by converting the eROSITA rates into equivalent ROSAT count rates in the standard ROSAT energy bands R4–R7, within 1.25σ. We find small residual deviations in the R4–R6 bands, where eROSITA tends to observe lower flux than ROSAT (∼11%), while a better agreement is achieved in the R7 band (∼1%). The eRASS maps exhibit lower noise levels than RASS maps at the same resolution above 0.3 keV. We report the average surface brightness and total flux of different large sky regions as a reference. The detection of faint emission from diffuse hot gas in the Milky Way is corroborated by the consistency of the eRASS1 and RASS maps shown in this paper and by their comparable flux dynamic range.
CRIS-Team Scopus Importer:2024-02-16
Keywords: Galaxy: halo; plasmas; techniques: image processing; X-rays: diffuse background; X-rays: ISM

BROADBAND SPECTROSCOPY USING TWO SUZAKU OBSERVATIONS OF THE HMXB GX 301-2 - Suchy, Slawomir; Fürst, Felix; Pottschmidt, Katja; Caballero, Isabel; Kreykenbohm, Ingo; Wilms, Jörn; Markowitz, Alex; Rothschild, Richard E. (Astrophysical Journal, 2012)
We present the analysis of two Suzaku observations of GX 301-2 at two orbital phases after the periastron passage. Variations in the column density of the line-of-sight absorber are observed, consistent with accretion from a clumpy wind. In addition to a cyclotron resonance scattering feature (CRSF), multiple fluorescence emission lines were detected in both observations. The variations in the pulse profiles and the CRSF throughout the pulse phase have a signature of a magnetic dipole field. Using a simple dipole model we calculated the expected magnetic field values for different pulse phases and were able to extract a set of geometrical angles, loosely constraining the dipole geometry in the neutron star. From the variation of the CRSF width and energy, we found a geometrical solution for the dipole, making the inclination consistent with previously published values.
Keywords: pulsars: individual (GX 301-2); stars: magnetic field; X-rays: binaries; X-rays: stars

Broadband study and the discovery of pulsations from the Be/X-ray binary eRASSU J052914.9-662446 in the Large Magellanic Cloud - Maitra, C.; Kaltenbrunner, D.; Haberl, F.; Buckley, D. A.H.; Monageng, I. M.; Udalski, A.; Carpano, S.; Coley, J. B.; Doroshenko, V.; Ducci, L.; Malacaria, C.; König, Ole; et al. (Astronomy & Astrophysics, 2023)
Context. The Magellanic Clouds are our nearest star-forming galaxies. While the population of high-mass X-ray binaries (HMXBs) in the Small Magellanic Cloud is relatively well studied, our knowledge about the Large Magellanic Cloud (LMC) is far from complete given its large angular extent and the insufficient coverage with X-ray observations. Aims. We conducted a search for new HMXBs in the LMC using data from eROSITA, the soft X-ray instrument on board the Spektrum-Roentgen-Gamma satellite. Methods. After confirming the nature of eRASSU J052914.9-662446 as a hard X-ray source that is positionally coincident with an early-type star, we followed it up with optical spectroscopic observations from the South African Large Telescope (SALT) and a dedicated NuSTAR observation. Results. We study the broadband timing and spectral behaviour of the newly discovered HMXB eRASSU J052914.9-662446 through eROSITA, Swift, and NuSTAR data in X-rays and the Optical Gravitational Lensing Experiment (OGLE) and SALT RSS data at the optical wavelength. We report the detection of a spin period at 1412 s and suggest that the orbital period of the system is E 151 days. We thereby establish that eRASSU J052914.9-662446 is an accreting pulsar. Furthermore, through optical spectroscopic observations and the detection of Hα emission, the source is identified as a Be X-ray binary pulsar in the LMC. We also investigated the variability of the source in the optical and X-ray regime over the past decades and provide estimates of the possible magnetic field strength of the neutron star.
CRIS-Team Scopus Importer:2023-01-20
Keywords: Be; Magellanic Clouds; Stars: emission-line; Stars: neutron; X-rays: binaries

Broadband X-Ray Spectral and Timing Analyses of the Black Hole Binary Candidate Swift J1658.2-4242: Rapid Flux Variation and the Turn-on of a Transient QPO - Xu, Yanjun; Harrison, Fiona A.; Tomsick, John A.; Barret, Didier; Gandhi, Poshak; Garcia, Javier; Miller, Jon M.; Uttley, Phil; Walton, Dominic J. (Astrophysical Journal, 2019)
We report results from joint Nuclear Spectroscopic Telescope Array, Swift, and XMM-Newton observations of the newly discovered black hole X-ray binary candidate Swift J1658.2-4242 in the intermediate state. We observe a peculiar event in this source, with its X-ray flux rapidly decreasing by similar to 45% in similar to 40 s, accompanied by only subtle changes in the shape of the broadband X-ray spectrum. In addition, we find a sudden turn-on of a transient quasiperiodic oscillation (QPO) with a frequency of 6-7 Hz around the time of the flux change, and the total fractional rms amplitude of the power spectrum increases from similar to 2% to similar to 10%. The X-ray spectral and timing analyses indicate that the flux decrease is driven by intrinsic changes in the accretion flow around the black hole, rather than intervening material along the line of sight. In addition, we do not significantly detect any relativistic disk reflection component, indicating it is much weaker than previously observed while the source was in the bright hard state. We propose accretion disk instabilities triggered at a large disk radius as the origin of the fast transition in spectral and timing properties, and discuss possible causes of the unusual properties observed in Swift J1658.2-4242. The prompt flux variation detected along with the emergence of a QPO makes the event an interesting case for investigating QPO mechanisms in black hole X-ray binaries.
CRIS-Team WoS Importer:2019-07-26

Broad emission lines for a negatively spinning black hole - Dauser, Thomas; Wilms, Jörn; Reynolds, C. S.; Brenneman, L. W. (Monthly Notices of the Royal Astronomical Society, 2010)
We present an extended scheme for the calculation of the profiles of emission lines from accretion discs around rotating black holes. The scheme includes discs with angular momenta which are parallel and antiparallel with respect to the black hole's angular momentum, as both configurations are assumed to be stable. We discuss line shapes for such discs and present a code for modelling observational data with this scheme in X-ray data analysis programs. Based on a Green's function approach, an arbitrary radius dependence of the disc emissivity and arbitrary limb-darkening laws can be easily taken into account, while the amount of pre-computed data is significantly reduced with respect to other available models.
Keywords: accretion; accretion discs; black hole physics; line: profiles; galaxies: active; galaxies: nuclei

Building a testable shear viscosity across the QCD phase diagram - Mclaughlin, Emma; Rose, Jacob; Dore, Travis; Parotto, Paolo; Ratti, Claudia; Noronha-Hostler, Jacquelyn (Physical Review C - Nuclear Physics, 2022)
Current experiments at the Relativistic Heavy Ion Collider (RHIC) are probing finite baryon densities where the shear viscosity to enthalpy ratio ilT /w of the quark gluon plasma remains unknown. We use the hadron resonance gas (HRG) model with the most up-to-date hadron list to calculate ilT /w at low temperatures and at finite baryon densities pB. We then match ilT /w to a quantum-chromodynamics-based shear viscosity calculation within the deconfined phase to create a table across T, mu B for different crossover and critical point scenarios at a specified location. We find that these new ilT /w(T, mu B) values would require initial conditions at significantly larger pB, compared to ideal hydrodynamic trajectories, to reach the same freeze-out point.
CRIS-Team WoS Importer:2022-03-04

Calibration aspects of the JEM-EUSO mission - Adams, J. H.; Ahmad, S.; Albert, J. -N.; Allard, D.; Anchordoqui, L.; Andreev, V.; Anzalone, Anna; Arai, Y.; Asano, K.; Ave Pernas, M.; Baragatti, P.; Barrillon, P.; et al. (Experimental Astronomy, 2015)
The JEM-EUSO telescope will be, after calibration, a very accurate instrument which yields the number of received photons from the number of measured photo-electrons. The project is in phase A (demonstration of the concept) including already operating prototype instruments, i.e. many parts of the instrument have been constructed and tested. Calibration is a crucial part of the instrument and its use. The focal surface (FS) of the JEM-EUSO telescope will consist of about 5000 photo-multiplier tubes (PMTs), which have to be well calibrated to reach the required accuracy in reconstructing the air-shower parameters. The optics system consists of 3 plastic Fresnel (double-sided) lenses of 2.5 m diameter. The aim of the calibration system is to measure the efficiencies (transmittances) of the optics and absolute efficiencies of the entire focal surface detector. The system consists of 3 main components: (i) Pre-flight calibration devices on ground, where the efficiency and gain of the PMTs will be measured absolutely and also the transmittance of the optics will be. (ii) On-board relative calibration system applying two methods: a) operating during the day when the JEM-EUSO lid will be closed with small light sources on board. b) operating during the night, together with data taking: the monitoring of the background rate over identical sites. (iii) Absolute in-flight calibration, again, applying two methods: a) measurement of the moon light, reflected on high altitude, high albedo clouds. b) measurements of calibrated flashes and tracks produced by the Global Light System (GLS). Some details of each calibration method will be described in this paper.
Keywords: Air-Shower fluorescence telescope; JEM-EUSO; Calibration; Space-Based experiment

Calorimetric neutrino expectations from bright blazar flares - Kreter, Michael; Kadler, Matthias; Krauß, Felicia; Buson, Sara; Ojha, Roopesh; Mannheim, Karl; Wilms, Jörn; Böttcher, Markus (Proceedings of Science, 2019)
Blazar jets are extreme environments, in which relativistic proton interactions with an ultraviolet photon field could give rise to photopion production. High-confidence associations of individual high-energy neutrinos with blazar flares could be achieved via spatially and temporally coincident detections. In 2017, the track-like, extremely high-energy neutrino event IC 170922A was found to coincide with increased γ-ray emission from the blazar TXS 0506+056, leading to the identification of the most promising neutrino source candidate so far. We test the chance coincidence of such events by calculating the expected number of neutrinos that can be detected by IceCube, based on a broadband parametrization of bright short-term blazar flares that were observed in the past 8 years by Fermi/LAT. We find that the integrated keV-to-GeV fluence of most individual blazar flares is far too small to yield a substantial Poisson probability for the detection of one or more neutrinos with IceCube. In contrast to such short-term flares that usually last only a few days or less, TXS0506+056 did show a major outburst that lasted several months, giving rise to a much higher fluence than most short blazar flares. We show, based on the calorimetric argumentation presented in this work, that the association of the IC 170922A neutrino with TXS 0506+056 is energetically plausible at a significance level of about 3.5 sigma. We further discuss strategies to search for more significant associations in future data unblindings of IceCube and KM3NeT.
CRIS-Team Scopus Importer:2021-04-20

Candidate hypervelocity stars of spectral type G and K revisited - Ziegerer, Eva; Volkert, Marco; Heber, Ulrich; Irrgang, Andreas; Gaensicke, B. T.; Geier, Stephan (Astronomy & Astrophysics, 2015)
Hypervelocity stars (HVS) move so fast that they are not bound to the Galaxy. When they were first discovered in 2005, dynamical ejection from the supermassive black hole (SMBH) in the Galactic centre (GC) was suggested as their origin. The two dozen HVSs known today are young massive B stars, mostly of 3-4 solar masses. Recently, 20 HVS candidates of low mass were discovered in the Segue G and K dwarf sample, but none of them originates from the GC. We embarked on a kinematic analysis of the Segue HVS candidate sample using the full 6D phase space information based on new proper motion measurements. Their orbital properties can then be derived by tracing back their trajectories in different mass models of our Galaxy. We present the results for 14 candidate HVSs for which proper motion measurements were possible. Significantly lower proper motions than found in the previous study were derived. Considering three different Galactic mass models, we found that all stars are bound to the Galaxy. We confirm that the stars do not originate from the GC. The distribution of their proper motions and radial velocities is consistent with predictions for runaway stars ejected from the Galactic disk by the binary supernova mechanism. However, their kinematics are also consistent with old disk membership. Moreover, most stars have rather low metallicities and strong alpha-element enrichment, as is typical for thick disk and halo stars, whereas the metallicity of the three most metal-rich stars might indicate that they are runaway stars from the thin disk. One start shows halo kinematics.
Keywords: stars: kinematics and dynamics; stars: low-mass; stars: late-type; stars: abundances; stars: Population II

Carbon abundances of sdO stars from SPY - Hirsch, Heiko; Heber, Ulrich (2009)
Stroer et al. (2007) recently suggested a classification of sdOs according to supersolar and subsolar helium abundances, with only the helium-enriched stars showing signes of carbon and/or nitrogen in their optical spectra. We aim to derive reliable carbon and nitrogen abundances by fitting synthetic spectra to data obtained with the UVES spectrograph at ESO. Here we present our first results of the analysis of carbon abundances in hot subdwarf O stars. By constructing a grid of model atmospheres consisting of hydrogen, helium and carbon we were able to derive atmospheric parameters of nine carbon rich sdOs. We find log(N(C)/N(total)) up to ten times higher than the solar value, while the mean value for the effective temperature and the surface gravity is slightly lower than derived by helium-hydrogen models only. Surprisingly, we also find three fast rotators among our program stars.

Chandra ACIS Survey of M33 (ChASeM33): X-ray imaging spectroscopy of M33SNR 21, the brightest X-ray supernova remnant in M33 - Sasaki, Manami; et al. (Astrophysical Journal, 2007)
We present and interpret new X-ray data for M33SNR 21, the brightest X-ray supernova remnant (SNR) in M33. The SNR is in seen projection against ( and appears to be interacting with) the bright H II region NGC 592. Data for this source were obtained as part of the Chandra ACIS Survey of M33 ( ChASeM33) Very Large Project. The nearly on-axis Chandra data resolve the SNR into a similar to 5 '' diameter (20 pc at our assumed M33 distance of 817 +/- 58 kpc) slightly elliptical shell. The shell is brighter in the east, which suggests that it is encountering higher density material in that direction. The optical emission is coextensive with the X-ray shell in the north, but extends well beyond the X-ray rim in the southwest. Modeling the X-ray spectrum with an absorbed sedov model yields a shock temperature of 0.46(-0.02)(+0.01) with an ionization timescale of n(e)t = 2.1(-0.3)(+0.2) cm(-3) s and half-solar abundances (0. 45- (+0.12)(0.09)). Assuming Sedov dynamics gives an average preshock H density of 1.7 +/- 0.3 cm(-3). The dynamical age estimate is 6500 +/- 600 yr, while the best-fit net value and derived ne gives 8200 +/- 1700 yr; the weighted mean of the age estimates is 6700 +/- 600 yr. We estimate an X-ray luminosity (0.25-4.5 keV) of (1. 2 +/- 0.2); 10(37) ergs s(-1) ( absorbed), and (1.7 +/- 0.3) x 10(37) ergs s(-1) ( unabsorbed), in good agreement with the recent XMM- Newton determination. No significant excess hard emission was detected; the luminosity less than or similar to 1.2 x 10(35) ergs s(-1) (2-8 keV) for any hard point source.
Keywords: galaxies : individual (M33); shock waves; supernova remnants

Chandra-HETGS Characterization of an Outflowing Wind in the Accreting Millisecond Pulsar IGR J17591-2342 - Nowak, Michael A.; Paizis, Adamantia; Jaisawal, Gaurava Kumar; Chenevez, Jerome; Chaty, Sylvain; Fortin, Francis; Rodriguez, Jerome; Wilms, Jörn (Astrophysical Journal, 2019)
An accreting millisecond X-ray pulsar, IGR J17591-2342 was discovered in 2018 August in scans of the Galactic bulge and center by the International Gamma-Ray Astrophysics Laboratory X-ray and gamma-ray observatory. It exhibited an unusual outburst profile with multiple peaks in the X-ray, as observed by several X-ray satellites over 3 months. Here we present observations of this source performed in the X-ray / gamma-ray and near-infrared domains and focus on a simultaneous observation performed with the Chandra High Energy Transmission Gratings Spectrometer (HETGS) and the Neutron Star Interior Composition Explorer (NICER). The HETGS provides high-resolution spectra of the Si edge region that yield clues as to the source's distance and reveal evidence (at 99.999% significance) of an outflow with a velocity of 2800 km s(-1). We demonstrate good agreement between the NICER and HETGS continua, provided that one properly accounts for the differing manners in which these instruments view the dust-scattering halo in the source's foreground. Unusually, we find a possible set of Ca lines in the HETGS spectra (with significances ranging from 97.0% to 99.7%). We hypothesize that IGR. J17591-2342 is a neutron star low-mass X-ray binary at the distance of the Galactic bulge or beyond that may have formed from the collapse of a white dwarf system in a rare, calcium-rich Type Ib supernova explosion.
CRIS-Team WoS Importer:2019-04-09

Chandra observation of the Galactic supernova remnant CTB 109 (G109.1-1.0) - Sasaki, Manami; Plucinsky, Paul P.; Gaetz, Terrance J.; Bocchino, Fabrizio (Astronomy & Astrophysics, 2013)
Context. We study the X-ray emission of the Galactic supernova remnant (SNR) CTB 109 (G109.1−1.0), which is well-known for its enigmatic half-shell morphology both in radio and in X-rays and is associated with the anomalous X-ray pulsar (AXP) 1E 2259+586. Aims. We want to understand the origin of the X-ray bright feature inside the SNR called the Lobe and the details of the interaction of the SNR shock wave with the ambient interstellar medium (ISM). Methods. The Lobe and the northeastern part of the SNR were observed with Chandra ACIS-I. We analysed the spectrum of the X-ray emission by dividing the entire observed emission into small regions. The X-ray emission is best reproduced with one-component or two-component non-equilibrium ionisation models depending on the position. In the two-component model, one emission component represents the shocked ISM and the other the shocked ejecta. Results. We detect enhanced element abundances, in particular for Si and Fe, in and around the Lobe. There is one particular region next to the Lobe with a high Si abundance of 3.3 (2.6−4.0) times the solar value. This is the first, unequivocal detection of ejecta in CTB 109. Conclusions. The new Chandra data confirm that the Lobe was created by the interaction of the SNR shock and the supernova ejecta with a dense and inhomogeneous medium in the environment of SNR CTB 109. The newly calculated age of the SNR is t≈ 1.4×104 yr.
Keywords: shock waves; ISM: supernova remnants; X-rays: ISM; X-rays: individuals: SNR CTB 109

Chandra Spectral and Timing Analysis of Sgr A∗'s Brightest X-Ray Flares - Haggard, Daryl; Nynka, Melania; Mon, Brayden; Hernandez, Noelia De La Cruz; Nowak, Michael; Heinke, Craig; Neilsen, Joseph; Dexter, Jason; Fragile, P. Chris; Baganoff, Fred; Bower, Geoffrey C.; Corrales, Lia R.; et al. (Astrophysical Journal, 2019)
We analyze the two brightest Chandra X-ray flares detected from Sagittarius A∗, with peak luminosities more than 600 and 245 greater than the quiescent X-ray emission. The brightest flare has a distinctive double-peaked morphology - it lasts 5.7 ks (∼2 hr), with a rapid rise time of 1500 s and a decay time of 2500 s. The second flare lasts 3.4 ks, with rise and decay times of 1700 and 1400 s. These luminous flares are significantly harder than quiescence: the first has a power-law spectral index Γ = 2.06 0.14 and the second has Γ = 2.03 0.27, compared to Γ = 3.0 0.2 for the quiescent accretion flow. These spectral indices (as well as the flare hardness ratios) are consistent with previously detected Sgr A∗ flares, suggesting that bright and faint flares arise from similar physical processes. Leveraging the brightest flare's long duration and high signal-to-noise, we search for intraflare variability and detect excess X-ray power at a frequency of ν ≈ 3 mHz, but show that it is an instrumental artifact and not of astrophysical origin. We find no other evidence (at the 95% confidence level) for periodic or quasi-periodic variability in either flares' time series. We also search for nonperiodic excess power but do not find compelling evidence in the power spectrum. Bright flares like these remain our most promising avenue for identifying Sgr A∗'s short timescale variability in the X-ray, which may probe the characteristic size scale for the X-ray emission region.
CRIS-Team Scopus Importer:2021-04-20

Chandra X-ray spectroscopy of focused wind in the Cygnus X-1 system. II. The non-dip spectrum in the low/hard state - modulations with orbital phase - Miskovicova, Ivica; Hell, Natalie; Hanke, Manfred; Nowak, Michael A.; Pottschmidt, Katja; Schulz, Norbert S.; Grinberg, Victoria; Duro, Refiz; Madej, Oliwia K.; Lohfink, Anne M.; Rodriguez, Jerome; Bel, Marion Cadolle; et al. (Astronomy & Astrophysics, 2016)
Accretion onto the black hole in the system HDE 226868/Cygnus X-1 is powered by the strong line-driven stellar wind of the O-type donor star. We study the X-ray properties of the stellar wind in the hard state of Cyg X-1, as determined using data from the Chandra High Energy Transmission Gratings. Large density and temperature inhomogeneities are present in the wind, with a fraction of the wind consisting of clumps of matter with higher density and lower temperature embedded in a photoionized gas. Absorption dips observed in the light curve are believed to be caused by these clumps. This work concentrates on the non-dip spectra as a function of orbital phase. The spectra show lines of H-like and He-like ions of S, Si, Na, Mg, Al, and highly ionized Fe (Fe xvii-Fe xxiv). We measure velocity shifts, column densities, and thermal broadening of the line series. The excellent quality of these five observations allows us to investigate the orbital phase-dependence of these parameters. We show that the absorber is located close to the black hole. Doppler shifted lines point at a complex wind structure in this region, while emission lines seen in some observations are from a denser medium than the absorber. The observed line profiles are phase-dependent. Their shapes vary from pure, symmetric absorption at the superior conjunction to P Cygni profiles at the inferior conjunction of the black hole.
Keywords: Accretion; accretion disks; Stars: individual: Cyg X-1; Stars: individual: HDE 226868; Stars: winds; outflows; X-rays: binaries

Chandra X-ray spectroscopy of the focused wind in the Cygnus X-1 system III. Dipping in the low/hard state - Hirsch, Maria; Hell, Natalie; Grinberg, Victoria; Ballhausen, Ralf; Nowak, Michael A.; Pottschmidt, Katja; Schulz, Norbert S.; Dauser, Thomas; Hanke, Manfred; Kallman, Timothy R.; Brown, Gregory; Wilms, Jörn (Astronomy & Astrophysics, 2019)
We present an analysis of three Chandra High Energy Transmission Gratings observations of the black hole binary Cyg X-1/HDE 226868 at different orbital phases. The stellar wind that is powering the accretion in this system is characterized by temperature and density inhomogeneities including structures, or "clumps", of colder, more dense material embedded in the photoionized gas. As these clumps pass our line of sight, absorption dips appear in the light curve. We characterize the properties of the clumps through spectral changes during various dip stages. Comparing the silicon and sulfur absorption line regions (1.6-2.7 keV 7.7-4.6 angstrom) in four levels of varying column depth reveals the presence of lower ionization stages, i.e., colder or denser material, in the deeper dip phases. The Doppler velocities of the lines are roughly consistent within each observation, varying with the respective orbital phase. This is consistent with the picture of a structure that consists of differently ionized material, in which shells of material facing the black hole shield the inner and back shells from the ionizing radiation. The variation of the Doppler velocities compared to a toy model of the stellar wind, however, does not allow us to pin down an exact location of the clump region in the system. This result, as well as the asymmetric shape of the observed lines, point at a picture of a complex wind structure.
CRIS-Team WoS Importer:2019-06-28

CHANDRA X-RAY SPECTROSCOPY OF THE FOCUSED WIND IN THE CYGNUS X-1 SYSTEM. I. THE NONDIP SPECTRUM IN THE LOW/HARD STATE - Hanke, Manfred; Wilms, Jörn; Nowak, Michael A.; Pottschmidt, Katja; Schulz, Norbert S.; Lee, Julia C. (Astrophysical Journal, 2009)
We present analyses of a 50 ks observation of the supergiant X-ray binary system Cygnus X-1 (Cyg X-1)/HDE226868 taken with the Chandra High Energy Transmission Grating Spectrometer (HETGS). Cyg X-1 was in its spectrally hard state and the observation was performed during superior conjunction of the black hole, allowing for the spectroscopic analysis of the accreted stellar wind along the line of sight. A significant part of the observation covers X-ray dips as commonly observed for Cyg X-1 at this orbital phase, however, here we analyze only the high count rate nondip spectrum. The full 0.5-10 keV continuum can be described by a single model consisting of a disk, a narrow and a relativistically broadened Fe K alpha line, and a power-law component, which is consistent with simultaneous Rossi X-Ray Timing Explorer broadband data. We detect absorption edges from overabundant neutral O, Ne, and Fe, and absorption line series from highly ionized ions and infer column densities and Doppler shifts. With emission lines of He-like Mg XI, we detect two plasma components with velocities and densities consistent with the base of the spherical wind and a focused wind. A simple simulation of the photoionization zone suggests that large parts of the spherical wind outside of the focused stream are completely ionized, which is consistent with the low velocities (<200 km s(-1)) observed in the absorption lines, as the position of absorbers in a spherical wind at low projected velocity is well constrained. Our observations provide input for models that couple the wind activity of HDE 226868 to the properties of the accretion flow onto the black hole.
Keywords: accretion; accretion disks; stars: individual (HDE 226868; Cyg X-1); stars: winds; outflows; techniques: spectroscopic; X-rays: binaries

Characterisation of the Hamamatsu photomultipliers for the KM3NeT Neutrino Telescope - Aiello, S.; Akrame, S. E.; Ameli, F.; Anassontzis, E. G.; Andre, M.; Androulakis, G.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aublin, J.; Avgitas, T.; Baars, M.; et al. (Journal of Instrumentation, 2018)
The Hamamatsu R12199-023-inch photomultiplier tube is the photodetector chosen for the first phase of the KM3NeT neutrino telescope. About 7000 photomultipliers have been characterised for dark count rate, timing spread and spurious pulses. The quantum efficiency, the gain and the peak-to-valley ratio have also been measured for a sub-sample in order to determine parameter values needed as input to numerical simulations of the detector.
Keywords: Cherenkov detectors; Large detector systems for particle and astroparticle physics; Neutrino detectors; Photon detectors for UV; visible and IR photons (vacuum)

Characterising the VHE diffuse emission in the central 200 parsecs of our Galaxy with H.E.S.S. - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Andersson, T.; Anguener, E. O.; Arakawa, M.; Arrieta, M.; Aubert, P.; Backes, Michael; Balzer, A.; et al. (Astronomy & Astrophysics, 2018)
The diffuse very high-energy (VHE; > 100 GeV) gamma-ray emission observed in the central 200 pc of the Milky Way by H.E.S.S. was found to follow dense matter distribution in the central molecular zone (CMZ) up to a longitudinal distance of about 130 pc to the Galactic centre (GC), where the flux rapidly decreases. This was initially interpreted as the result of a burst-like injection of energetic particles 104 yr ago, but a recent more sensitive H.E.S.S. analysis revealed that the cosmic-ray (CR) density profile drops with the distance to the centre, making data compatible with a steady cosmic PeVatron at the GC. In this paper, we extend this analysis to obtain, for the first time, a detailed characterisation of the correlation with matter and to search for additional features and individual gamma-ray sources in the inner 200 pc. Taking advantage of 250 h of H.E.S.S. data and improved analysis techniques, we perform a detailed morphology study of the diffuse VHE emission observed from the GC ridge and reconstruct its total spectrum. To test the various contributions to the total gamma-ray emission, we used an iterative 2D maximum-likelihood approach that allows us to build a phenomenological model of the emission by summing a number of different spatial components. We show that the emission correlated with dense matter covers the full CMZ and that its flux is about half the total diffuse emission flux. We also detect some emission at higher latitude that is likely produced by hadronic collisions of CRs in less dense regions of the GC interstellar medium. We detect an additional emission component centred on the GC and extending over about 15 pc that is consistent with the existence of a strong CR density gradient and confirms the presence of a CR accelerator at the very centre of our Galaxy. We show that the spectrum of full ridge diffuse emission is compatible with that previously derived from the central regions, suggesting that a single population of particles fills the entire CMZ. Finally, we report the discovery of a VHE gamma-ray source near the GC radio arc and argue that it is produced by the pulsar wind nebula candidate G0.13-0.11.
Keywords: gamma rays: general; gamma rays: ISM; Galaxy: center; cosmic rays

Characterization of the Particle-induced Background of XMM-Newton EPIC-pn: Short- and Long-term Variability - Bulbul, Esra; Kraft, Ralph; Nulsen, Paul; Freyberg, Michael; Miller, Eric D.; Grant, Catherine; Bautz, Mark W.; Burrows, David N.; Allen, Steven; Eraerds, Tanja; Fioretti, Valentina; Gasteldello, Fabio; et al. (Astrophysical Journal, 2020)
The particle-induced background of X-ray observatories is produced by galactic cosmic ray (GCR) primary protons, electrons, and He ions. Events due to direct interaction with the detector are usually removed by onboard processing. The interactions of these primary particles with the detector environment produce secondary particles that mimic X-ray events from celestial sources, and are much more difficult to identify. The filter-wheel closed data from the XMM-Newton EPIC-pn camera in small window mode (SWM) contains both the X-ray-like background events, and the events due to direct interactions with the primary particles. From this data, we demonstrate that X-ray-like background events are spatially correlated with the primary particle interaction. This result can be used to further characterize and reduce the non-X-ray background in silicon-based X-ray detectors in current and future missions. We also show that spectrum and pattern fractions of secondary particle events are different from those produced by cosmic X-rays.
CRIS-Team WoS Importer:2020-06-19

Characterizing the patchy appearance of the circumgalactic medium and the influence of foreground absorption - Ponti, G.; Sanders, J. S.; Locatelli, N.; Zheng, X.; Zhang, Y.; Yeung, M.; Freyberg, M.; Dennerl, K.; Comparat, J.; Merloni, A.; Di Teodoro, E.; Sasaki, Manami; et al. (Astronomy & Astrophysics, 2023)
Context. Recent studies have demonstrated that the emission from the circumgalactic medium displays a relatively high degree of patchiness on angular scales of a∼10. Aims. Taking advantage of the Spectrum Roentgen Gamma eROSITA Final Equatorial Depth Survey, we aim to constrain any variation in the X-ray surface brightness on scales ranging from sub-degrees to a hundred square degrees. Result. The surface brightness in the soft X-ray band (0.3-0.45 keV) shows modulations of about 60% on scales of several degrees. The amplitude of such variations decreases at higher energies. The observed patchiness is stable over a period of two years, therefore excluding the possiblity that it could have been induced by solar wind charge exchange. We also observe no correlation between such an excess and the density of galaxies in the Local Universe, suggesting no strong contribution from the hot baryons in the filaments of the cosmic web. Instead, the soft X-ray emission is anti-correlated with the column density of absorbing material. Indeed, we can reproduce the spectrum of the bright and dark regions by simply varying the column density of the matter absorbing the emission components located beyond the Local Hot Bubble, while no modulation of the intrinsic emission is required. At high Galactic latitudes, the eROSITA all-sky map shows patchiness of the soft X-ray diffuse emission similar to the one observed in the eFEDS field; it is therefore likely that the same"absorption-modulation" is present over the entire sky. Conclusions. The observed patchiness of soft X-ray diffuse emission within the eFEDS field is primarily a consequence of absorption. Our spectral decomposition of the soft X-ray background appears accurate, predicting that (apart from the Local Hot Bubble) all other spectral components are modulated by clouds beyond ∼200 pc from the Sun. These results highlight the importance of an accurate treatment of the absorption effects in determining the patchiness of the circumgalactic medium.
CRIS-Team Scopus Importer:2023-03-03
Keywords: Galaxy: general; ISM: bubbles; ISM: structure; Local insterstellar matter; Solar wind; X-rays: diffuse background

Chemical fingerprints of He-sdO stars - Schindewolf, Markus; Nemeth, Peter; Heber, Ulrich; Battich, Tiara; Miller Bertolami, Marcelo M.; Latour, Marilyn (Open Astronomy, 2018)
The chemical composition of helium-rich hot subluminous O stars plays an important role to understand and model their formation history. We present a spectroscopic analysis of four He-sdO stars,CD-31° 4800, [CW83] 0904-02, LSS 1274 and LS IV +10° 9. The analysis is based on archival optical and UV high-resolution spectra. We used Tlusty200/Synspec48 to compute line blanketed non-LTE model atmospheres and their corresponding synthetic spectra and derive the atmospheric parameters as well as the abundances of the most prominent elements. All stars have helium-dominated atmospheres with hardly any hydrogen and temperatures between 42000 K and 47000 K while their surface gravity spans between log g = 5.4 and 5.7. CD-31° 4800 shows an enrichment of nitrogen and the characteristic pattern of hydrogen burning via the CNO-cycle, while the rest of the elements have about the solar abundance. This points to the slow merger of two helium white dwarfs as the most likely origin for this system. The other three stars are enriched in carbon, nitrogen and neon while their intermediate mass element's abundance scatters around the solar value. They were possibly formed in the deep mixing late hot flasher scenario.
CRIS-Team Scopus Importer:2020-12-21
Keywords: abundances; atmospheric parameters; He-sdO; hot flasher; slow merger; stellar atmospheres; Subdwarfs

Classification of low-luminosity stellar X-ray sources in the field of the Draco dwarf spheroidal galaxy - Saeedi, Sara; Sasaki, Manami; Stelzer, Beate; Ducci, Lorenzo (Astronomy & Astrophysics, 2019)
Aims. A previous study of the X-ray luminosity function of the X-ray sources in the Draco dwarf spheroidal (dSph) galaxy field indicates the presence of a population of unknown X-ray sources in the soft energy range of 0.5-2 keV. In 2015, there were twenty-six further deep XMM-Newton observations of Draco dSph, providing an opportunity for a new study of the as yet unclassified sources.
CRIS-Team WoS Importer:2019-07-26

Close Binary Progenitors and Ejected Companions of Thermonuclear Supernovae - Geier, S.; Kupfer, T.; Heber, Ulrich; Nemeth, Peter; Ziegerer, Eva; Irrgang, Andreas; Schindewolf, Markus; Marsh, T. R.; Gansicke, B. T.; Barlow, B. N.; Bloemen, S. (2017)
Hot subdwarf stars (sdO/Bs) are evolved core helium-burning stars with very thin hydrogen envelopes, which can be formed by common envelope ejection. Close sdB binaries with massive white dwarf (WD) companions are potential progenitors of thermonuclear supernovae type Ia (SN Ia). We discovered such a progenitor candidate as well as a candidate for a surviving companion star, which escapes from the Galaxy. More candidates for both types of objects have been found by cross-matching known sdB stars with proper motion and light curve catalogues. We found 72 sdO/B candidates with high Galactic restframe velocities, 12 of them might be unbound to our Galaxy. Furthermore, we discovered the second-most compact sdB+WD binary known. However, due to the low mass of the WD companion, it is unlikely to be a SN Ia progenitor.

Coincidence of a high-fluence blazar outburst with a PeV-energy neutrino event - Kadler, Matthias; Krauss, Felicia; Mannheim, K.; Ojha, R.; Mueller, C.; Schulz, R.; Anton, Gisela; Baumgartner, W.; Beuchert, T.; Buson, S.; Carpenter, B.; Eberl, Thomas; et al. (Nature Physics, 2016)
The astrophysical sources of the extraterrestrial, very high-energy neutrinos detected by the IceCube collaboration remain to be identified. Gamma-ray (3-ray) blazars have been predicted to yield a cumulative neutrino signal exceeding the atmospheric background above energies of 100 TeV, assuming that both the neutrinos and the 3-ray photons are produced by accelerated protons in relativistic jets. As the background spectrum falls steeply with increasing energy, the individual events with the clearest signature of being of extraterrestrial origin are those at petaelectronvolt energies. Inside the large positional-uncertainty fields of the first two petaelectronvolt neutrinos detected by IceCube, the integrated emission of the blazar population has a sufficiently high electromagnetic flux to explain the detected IceCube events, but fluences of individual objects are too low to make an unambiguous source association. Here, we report that a major outburst of the blazar PKS B1424-418 occurred in temporal and positional coincidence with a third petaelectronvolt-energy neutrino event (HESE-35) detected by IceCube. On the basis of an analysis of the full sample of 3-ray blazars in the HESE-35 field, we show that the long-term average 3-ray emission of blazars as a class is in agreement with both the measured all-sky flux of petaelectronvolt neutrinos and the spectral slope of the IceCube signal. The outburst of PKS B1424-418 provides an energy output high enough to explain the observed petaelectronvolt event, suggestive of a direct physical association.

Combined search for neutrinos from dark matter self-annihilation in the Galactic Center with ANTARES and IceCube - Albert, A.; Andre, M.; Domi, Alba; Anghinolfi, M.; Ardid, M.; Aubert, J-J; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; Bertin,; Biagi, Simone; et al. (Physical Review D, 2020)
We present the results of the first combined dark matter search targeting the Galactic Center using the ANTARES and IceCube neutrino telescopes. For dark matter particles with masses from 50 to 1000 GeV, the sensitivities on the self-annihilation cross section set by ANTARES and IceCube are comparable, making this mass range particularly interesting for a joint analysis. Dark matter self-annihilation through the tau(+)tau(-) , mu(+)mu(-) , b (b) over bar, and W+W- channels is considered for both the Navarro-Frenk-White and Burkert halo profiles. In the combination of 2101.6 days of ANTARES data and 1007 days of IceCube data, no excess over the expected background is observed. Limits on the thermally averaged dark matter annihilation cross section are set. These limits present an improvement of up to a factor of 2 in the studied dark matter mass range with respect to the individual limits published by both collaborations. When considering dark matter particles with a mass of 200 GeV annihilating through the tau(+)tau(-)channel, the value obtained for the limit is 7.44 x 10(-24) cm(3) s(-1 )for the Navarro-Frenk-White halo profile. For the purpose of this joint analysis, the model parameters and the likelihood are unified, providing a benchmark for forthcoming dark matter searches performed by neutrino telescopes.
CRIS-Team WoS Importer:2020-11-13

Common patterns in pulse profiles of high-mass X-ray binaries - Alonso-Hernandez, J.; Furst, F.; Kretschmar, P.; Caballero,; Joyce, Amy (Astronomy & Astrophysics, 2022)
Context. X-ray pulsars are binary systems which consist of a neutron star in orbit with a mass donor (companion). In these systems the neutron accretes matter from the companion star, which creates accretion columns or hot spots on the neutron star surface and gives rise to pulsations in the X-ray light curve. The pulse profiles carry information about the accretion and magnetic field geometry. Here we present a study and classification of energy-resolved pulse profiles of a sample of X-ray pulsars, focusing on high-mass X-ray binaries. Aims. Our goal is to perform a classification of X-ray pulsars based on their observed pulse profiles and look for correlations between this classification and their principle physical observables. The analysis pipeline is available online. Methods. We analysed the pulse profiles of a sample of X-ray pulsars using data obtained with the X-ray Multi-Mirror Mission (XMM-Newton) and the Nuclear Spectroscopic Telescope Array (NuSTAR). We fitted the energy-resolved pulse profiles with a Fourier series of up to five harmonics. We then used the energy evolution of the different Fourier components to classify the pulse profiles into groups. We investigated relationships between the pulse profile properties and other observables of the systems (e.g. orbital period, magnetic field strength, and luminosity) to study the extreme physics of these systems. Results. The sources were divided into three groups using a classification based on the shape, the dominance of the fitted Fourier harmonics, and their respective evolution with energy. We do not find a conclusive correlation between the pulse profile shapes or groups and other parameters of the systems. However, a weak trend was found when comparing our classification to the sources' locations in the spin period-orbital period diagram. Further studies are required to confirm this trend. Conclusions. Despite the large variety of pulse profiles of the X-ray pulsars, we found that with our approach clear categories emerge which we use to classify their behaviour as a function of energy. As we do not find a clear relationship between our classification scheme and other parameters, like the luminosity, the magnetic field strength, or the orbital and spin periods, we conclude that X-ray pulse profiles are influenced by other hidden variables.
CRIS-Team WoS Importer:2022-09-30

Confirming the thermal Comptonization model for black hole X-ray emission in the low-hard state - Castro, M.; D'Amico, F.; Braga, J.; Maiolino, T.; Pottschmidt, K.; Wilms, Jörn (Astronomy & Astrophysics, 2014)
Hard X-ray spectra of black hole binaries in the low/hard state are well modeled by thermal Comptonization of soft seed photons by a corona-type region with kT similar to 50 keV and optical depth around 1. Previous spectral studies of 1E 1740.7-2942, including both the soft and the hard X-ray bands, were always limited by gaps in the spectra or by a combination of observations with imaging and non-imaging instruments. In this study, we have used three rare nearly-simultaneous observations of 1E 1740.7-1942 by both XMM-Newton and INTEGRAL satellites to combine spectra from four different imaging instruments with no data gaps, and we successfully applied the Comptonization scenario to explain the broadband X-ray spectra of this source in the low/hard state. For two of the three observations, our analysis also shows that, models including Compton reflection can adequately fit the data, in agreement with previous reports. We show that the observations can also be modeled by a more detailed Comptonization scheme. Furthermore, we find the presence of an iron K-edge absorption feature in one occasion, which confirms what had been previously observed by Suzaku. Our broadband analysis of this limited sample shows a rich spectral variability in 1E 1740.7 2942 at the low/hard state, and we address the possible causes of these variations. More simultaneous soft/hard X-ray observations of this system and other black-hole binaries would be very helpful in constraining the Comptonization scenario and shedding more light on the physics of these systems.
Keywords: radiation mechanisms: non-thermal; radiation mechanisms: thermal; X-rays: stars

Constraining jet/disc geometry and radiative processes in stellar black holes XTE J1118+480 and GX 339-4 - Maitra, Dipankar; Markoff, Sera; Brocksopp, Catherine; Noble, Michael; Nowak, Michael; Wilms, Jörn (Monthly Notices of the Royal Astronomical Society, 2009)
We present results from modelling of quasi-simultaneous broad-band (radio through X-ray) observations of the Galactic stellar black hole (BH) transient X-ray binary (XRB) systems XTE J1118+480 and GX 339-4 using an irradiated disc + compact jet model. In addition to quantifying the physical properties of the jet, we have developed a new irradiated disc model which also constrains the geometry and temperature of the outer accretion disc by assuming a disc heated by viscous energy release and X-ray irradiation from the inner regions. For the source XTE J1118+480, which has better spectral coverage of the two in optical and near-infrared (OIR) wavelengths, we show that the entire broad-band continuum can be well described by an outflow-dominated model + an irradiated disc. The best-fitting radius of the outer edge of the disc is consistent with the Roche lobe geometry of the system, and the temperature of the outer edge of the accretion disc is similar to those found for other XRBs. Irradiation of the disc by the jet is found to be negligible for this source. For GX 339-4, the entire continuum is well described by the jet-dominated model only, with no disc component required. For the two XRBs, which have very different physical and orbital parameters and were in different accretion states during the observations, the sizes of the jet base are similar and both seem to prefer a high fraction of non-thermal electrons in the acceleration/shock region and a magnetically dominated plasma in the jet. These results, along with recent similar results from modelling other galactic XRBs and AGNs, may suggest an inherent unity in diversity in the geometric and radiative properties of compact jets from accreting black holes.
Keywords: accretion; accretion discs; black hole physics; radiation mechanisms: general; stars: winds; outflows; X-rays: individual: GX 339-4; X-rays: individual: J1118+480

Constraining the contribution of Gamma-Ray Bursts to the high-energy diffuse neutrino flux with 10 yr of ANTARES data - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J-J; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; Bertin,; Biagi, S.; et al. (Monthly Notices of the Royal Astronomical Society, 2021)
Addressing the origin of the astrophysical neutrino flux observed by IceCube is of paramount importance. Gamma-Ray Bursts (GRBs) are among the few astrophysical sources capable of achieving the required energy to contribute to such neutrino flux through p gamma interactions. In this work, ANTARFS data have been used to search for upward going muon neutrinos in spatial and temporal coincidence with 784 GRBs occurred from 2007 to 2017. For each GRB, the expected neutrino flux has been calculated in the framework of the internal shock model and the impact of the lack of knowledge on the majority of source redshifts and on other intrinsic parameters of the emission mechanism has been quantified. It is found that the model parameters that set the radial distance where shock collisions occur have the largest impact on neutrino flux expectations. In particular, the bulk Lorentz factor of the source ejecta and the minimum variability time-scale are found to contribute significantly to the GRB-neutrino flux uncertainty. For the selected sources, ANTARES data have been analysed by maximizing the discovery probability of the stacking sample through an extended maximum-likelihood strategy. Since no neutrino event passed the quality cuts set by the optimization procedure, 90 per cent confidence level upper limits (with their uncertainty) on the total expected diffuse neutrino flux have been derived, according to the model. The GRB contribution to the observed diffuse astrophysical neutrino flux around 100 TeV is constrained to be less than 10 percent.
CRIS-Team WoS Importer:2021-01-29

Constraining the neutrino emission of gravitationally lensed Flat-Spectrum Radio Quasars with ANTARES data - Adrian-Martinez, S.; Albert, A.; Andre, Michel; Anton, Gisela; Ardid, Miguel; Aubert, J. J.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagii, S.; Bogazzi, C.; et al. (Journal of Cosmology and Astroparticle Physics, 2014)
This paper proposes to exploit gravitational lensing effects to improve the sensitivity of neutrino telescopes to the intrinsic neutrino emission of distant blazar populations. This strategy is illustrated with a search for cosmic neutrinos in the direction of four distant and gravitationally lensed Flat-Spectrum Radio Quasars. The magnification factor is estimated for each system assuming a singular isothermal profile for the lens. Based on data collected from 2007 to 2012 by the ANTARES neutrino telescope, the strongest constraint is obtained from the lensed quasar B0218+357, providing a limit on the total neutrino luminosity of this source of 1.08 x 10(46) erg s(-1) This limit is about one order of magnitude lower than those previously obtained in the ANTARES standard point source searches with non-lensed Flat-Spectrum Radio Quasars.
Keywords: gravitational lensing; neutrino astronomy

Constraining the origin and models of chemical enrichment in galaxy clusters using the Athena X-IFU - Mernier, F.; Cucchetti, E.; Tornatore, L.; Biffi, V.; Pointecouteau, E.; Clerc, N.; Peille, P.; Rasia, Elena; Barret, Didier; Borgani, Stefano; Bulbul, E.; Dauser, Thomas; et al. (Astronomy & Astrophysics, 2020)
Chemical enrichment of the Universe at all scales is related to stellar winds and explosive supernovae phenomena. Metals produced by stars and later spread throughout the intracluster medium (ICM) at the megaparsec scale become a fossil record of the chemical enrichment of the Universe and of the dynamical and feedback mechanisms determining their circulation. As demonstrated by the results of the soft X-ray spectrometer onboard Hitomi, high-resolution X-ray spectroscopy is the path to differentiating among the models that consider different metal-production mechanisms, predict the outcoming yields, and are a function of the nature, mass, and/or initial metallicity of their stellar progenitor. Transformational results shall be achieved through improvements in the energy resolution and effective area of X-ray observatories, allowing them to detect rarer metals (e.g. Na, Al) and constrain yet-uncertain abundances (e.g. C, Ne, Ca, Ni). The X-ray Integral Field Unit (X-IFU) instrument onboard the next-generation European X-ray observatory Athena is expected to deliver such breakthroughs. Starting from 100 ks of synthetic observations of 12 abundance ratios in the ICM of four simulated clusters, we demonstrate that the X-IFU will be capable of recovering the input chemical enrichment models at both low (z = 0.1) and high (z = 1) redshifts, while statistically excluding more than 99.5% of all the other tested combinations of models. By fixing the enrichment models which provide the best fit to the simulated data, we also show that the X-IFU will constrain the slope of the stellar initial mass function within ∼12%. These constraints will be key ingredients in our understanding of the chemical enrichment of the Universe and its evolution.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Galaxies: abundances; Galaxies: clusters: intracluster medium; Galaxies: fundamental parameters; Methods: numerical; Supernovae: general; X-rays: galaxies: clusters

Constraints on the emission region of 3C 279 during strong flares in 2014 and 2015 through VHE γ -ray observations with H.E.S.S. - Abdalla, H.; Adam, R.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Ashkar, H.; Backes, M.; Martins, V. Barbosa; Barnard, M.; et al. (Astronomy & Astrophysics, 2019)
The flat spectrum radio quasar 3C 279 is known to exhibit pronounced variability in the high-energy (100MeV < E < 100 GeV) gamma-ray band, which is continuously monitored with Fermi-LAT. During two periods of high activity in April 2014 and June 2015 target-of-opportunity observations were undertaken with the High Energy Stereoscopic System (H.E.S.S.) in the very-high-energy (VHE, E > 100 GeV) gamma-ray domain. While the observation in 2014 provides an upper limit, the observation in 2015 results in a signal with 8 : 7 sigma significance above an energy threshold of 66 GeV. No VHE variability was detected during the 2015 observations. The VHE photon spectrum is soft and described by a power-law index of 4.2 +/- 0.3. The H.E.S.S. data along with a detailed and contemporaneous multiwavelength data set provide constraints on the physical parameters of the emission region. The minimum distance of the emission region from the central black hole was estimated using two plausible geometries of the broad-line region and three potential intrinsic spectra. The emission region is confidently placed at r greater than or similar to 1 : 7 X 1017 cm from the black hole, that is beyond the assumed distance of the broad-line region. Time-dependent leptonic and lepto-hadronic one-zone models were used to describe the evolution of the 2015 flare. Neither model can fully reproduce the observations, despite testing various parameter sets. Furthermore, the H.E.S.S. data were used to derive constraints on Lorentz invariance violation given the large redshift of 3C 279.
CRIS-Team WoS Importer:2019-07-30
Keywords: Galaxies: active; Quasars: individual: 3C 279; Radiation mechanisms: non-thermal; Relativistic processes

Constraints on the Intergalactic Magnetic Field Using Fermi-LAT and H.E.S.S. Blazar Observations - Aharonian, F.; Aschersleben, J.; Backes, M.; Martins, V. Barbosa; Batzofin, R.; Becherini, Y.; Berge, D.; Bi, B.; Bouyahiaoui, M.; Breuhaus, M.; Brose, R.; Brun, F.; et al. (Astrophysical Journal Letters, 2023)

Constraints on the neutrino emission from the Galactic Ridge with the ANTARES telescope - Adrian-Martinez, S.; Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. -J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; et al. (Physics Letters B, 2016)
A highly significant excess of high-energy astrophysical neutrinos has been reported by the IceCube Collaboration. Some features of the energy and declination distributions of IceCube events hint at a North/South asymmetry of the neutrino flux. This could be due to the presence of the bulk of our Galaxy in the Southern hemisphere. The ANTARES neutrino telescope, located in the Mediterranean Sea, has been taking data since 2007. It offers the best sensitivity to muon neutrinos produced by galactic cosmic ray interactions in this region of the sky. In this letter a search for an extended neutrino flux from the Galactic Ridge region is presented. Different models of neutrino production by cosmic ray propagation are tested. No excess of events is observed and upper limits for different neutrino flux spectral indices Γ are set. For Γ=2.4 the 90% confidence level flux upper limit at 100 TeV for one neutrino flavour corresponds to Φ (100 TeV)=2.0⋅10 GeVcmssr. Under this assumption, at most two events of the IceCube cosmic candidates can originate from the Galactic Ridge. A simple power-law extrapolation of the Fermi-LAT flux to account for IceCube High Energy Starting Events is excluded at 90% confidence level.
Keywords: ANTARES; Diffuse muon neutrino flux; Neutrino telescope

Constraints on the Spacetime Metric around Seven "Bare" AGNs Using X-Ray Reflection Spectroscopy - Tripathi, Ashutosh; Yan, Jinli; Yang, Yuchan; Yan, Yunfeng; Garnham, Marcus; Yao, Yu; Li, Songcheng; Ding, Ziyu; Abdikamalov, Askar B.; Ayzenberg, Dimitry; Bambi, Cosimo; Dauser, Thomas; et al. (Astrophysical Journal, 2019)
We present the study of a sample of seven "bare" active galactic nuclei observed with Suzaku. We interpret the spectrum of these sources with a relativistic reflection component and we employ our model RELXILL_NK to test the Kerr nature of their supermassive black holes. We constrain the Johannsen deformation parameters alpha(13) and alpha(22), in which the Kerr metric is recovered when alpha(13) = alpha(22) = 0. All our measurements are consistent with the hypothesis that the spacetime geometry around these supermassive objects is described by the Kerr solution. For some sources, we obtain quite strong constraints on alpha(13) and alpha(22) when compared to those found in our previous studies. We discuss the systematic uncertainties in our tests and the implications of our results.
CRIS-Team WoS Importer:2019-04-12

Constraints on the winds of hot subdwarf stars from X-ray observations of two sdB binaries with compact companions: CD-30 degrees 11223 and PG 1232-136 - Mereghetti, Sandro; La Palombara, Nicola; Esposito, Paolo; Gastaldello, Fabio; Tiengo, A.; Heber, Ulrich; Geier, Stephan; Wilms, Jörn (Monthly Notices of the Royal Astronomical Society, 2014)
Little observational data are available on the weak stellar winds of hot subdwarf stars of B spectral type (sdB). Close binary systems composed of an sdB star and a compact object (white dwarf, neutron star or black hole) could be detected as accretion-powered X-ray sources. The study of their X-ray emission can probe the properties of line-driven winds of sdB stars that cannot be derived directly from spectroscopy because of the low luminosity of these stars. Here we report on the first sensitive X-ray observations of two sdB binaries with compact companions. CD -30A degrees A 11223 is the sdB binary with the shortest known orbital period (1.2 h) and its companion is certainly a white dwarf. PG 1232-136 is an sdB binary considered the best candidate to host a black hole companion. We observed these stars with XMM-Newton in 2013 August for 50 ks and in 2009 July for 36 ks, respectively. None of them was detected and we derived luminosity upper limits of similar to 1.5 x 10(29) erg s(-1) for CD -30A degrees A 11223 and similar to 5 x 10(29) erg s(-1) for PG 1232-136. The corresponding mass-loss rate for PG 1232-136 is poorly constrained, owing to the unknown efficiency for black hole accretion. On the other hand, in the case of CD -30A degrees A 11223 we could derive, under reasonable assumptions, an upper limit of similar to 3 x 10(-13) M-aS (TM) yr(-1) on the wind mass-loss rate from the sdB star. This is one of the few observational constraints on the weak winds expected in this class of low-mass hot stars. We also report the results on the X-ray emission from a cluster of galaxies serendipitously discovered in the field of CD -30 degrees 11223.
Keywords: stars: individual: CD-30 11223; PG 1232-136; subdwarfs; stars: winds; outflows; X-rays: binaries; X-rays: galaxies: clusters; X-rays: individual: XMMU J141057.7-305132

Continued decay in the cyclotron line energy in Hercules X-1 - Staubert, R.; Klochkov, D.; Vybornov, V.; Wilms, Jörn; Harrison, F. A. (Astronomy & Astrophysics, 2016)
The centroid energy E of the cyclotron line in the spectrum of the binary X-ray pulsar Her X-1 has been found to decrease with time on a time scale of a few tens of years - surprisingly short in astrophysical terms. This was found for the pulse phase-averaged line centroid energy using observational data from various X-ray satellites over the time period 1996 to 2012, establishing a reduction of ∼4 keV. Here we report on the result of a new observation by NuSTAR performed in August 2015. The earlier results are confirmed and strengthened with respect to both the dependence of E on flux (it is still present after 2006) and the dependence on time: the long-term decay continued with the same rate, corresponding to a reduction of ∼5 keV in 20 yr.
Keywords: Accretion; accretion disks; Magnetic fields; Radiation mechanisms: general; Radiation mechanisms: non-thermal; Stars: neutron; X-rays: binaries

Continuum, cyclotron line, and absorption variability in the high-mass X-ray binary Vela X-1 - Diez, C. M.; Grinberg,; Fuerst, F.; Sokolova-Lapa, Ekaterina; Santangelo, A.; Wilms, Jörn; Pottschmidt, K.; Martinez-Nunez, S.; Malacaria, C.; Kretschmar, P. (Astronomy & Astrophysics, 2022)
Because of its complex clumpy wind, prominent cyclotron resonant scattering features, intrinsic variability, and convenient physical parameters (close distance, high inclination, and small orbital separation), which facilitate the observation and analysis of the system, Vela X-1 is one of the key systems for understanding accretion processes in high-mass X-ray binaries on all scales. We revisit Vela X-1 with two new observations taken with NuSTAR at orbital phases similar to 0.68-0.78 and similar to 0.36-0.52, which show a plethora of variability and allow us to study the accretion geometry and stellar wind properties of the system. We follow the evolution of spectral parameters down to the pulse period timescale using a partially covered power law continuum with a Fermi-Dirac cutoff to model the continuum and local absorption. We are able to confirm anti-correlations between the photon index and the luminosity and, for low fluxes, between the folding energy and the luminosity, implying a change of properties in the Comptonising plasma. We were not able to confirm a previously seen correlation between the cyclotron line energy and the luminosity of the source in the overall observation, but we observed a drop in the cyclotron line energy following a strong flare. We see strong variability in absorption between the two observations and within one observation (for the similar to 0.36-0.52 orbital phases) that can be explained by the presence of a large-scale structure, such as accretion and photoionisation wakes in the system, and our variable line of sight through this structure.
CRIS-Team WoS Importer:2022-04-15

CORONA, JET, AND RELATIVISTIC LINE MODELS FOR SUZAKU/RXTE/CHANDRA-HETG OBSERVATIONS OF THE CYGNUS X-1 HARD STATE - Nowak, Michael A.; Hanke, Manfred; Trowbridge, Sarah N.; Markoff, Sera B.; Wilms, Jörn; Pottschmidt, Katja; Coppi, Paolo; Maitra, Dipankar; Davis, John E.; Tramper, Frank (Astrophysical Journal, 2011)
Using Suzaku and the Rossi X-ray Timing Explorer (RXTE), we have conducted a series of four simultaneous observations of the galactic black hole candidate Cyg X-1 in what were historically faint and spectrally hard "low states." Additionally, all of these observations occurred near superior conjunction with our line of sight to the X-ray source passing through the dense phases of the "focused wind" from the mass donating secondary. One of our observations was also simultaneous with observations by the Chandra-High Energy Transmission Grating (HETG). These latter spectra are crucial for revealing the ionized absorption due to the secondary's focused wind. Such absorption is present and must be accounted for in all four spectra. These simultaneous data give an unprecedented view of the 0.8-300 keV spectrum of Cyg X-1, and hence bear upon both corona and X-ray emitting jet models of black hole hard states. Three models fit the spectra well: coronae with thermal or mixed thermal/non-thermal electron populations and jets. All three models require a soft component that we fit with a low temperature disk spectrum with an inner radius of only a few tens of GM/c(2). All three models also agree that the known spectral break at 10 keV is not solely due to the presence of reflection, but each gives a different underlying explanation for the augmentation of this break. Thus, whereas all three models require that there is a relativistically broadened Fe line, the strength and inner radius of such a line is dependent upon the specific model, thus making premature line-based estimates of the black hole spin in the Cyg X-1 system. We look at the relativistic line in detail, accounting for the narrow Fe emission and ionized absorption detected by HETG. Although the specific relativistic parameters of the line are continuum dependent, none of the broad line fits allow for an inner disk radius that is >40 GM/c(2).
Keywords: accretion; accretion disks; black hole physics; radiation mechanisms: non-thermal; X-rays: binaries

Correction to: A new benchmark of soft X-ray transition energies of Ne, CO2, and SF6: paving a pathway towards ppm accuracy (The European Physical Journal D, (2022), 76, 3, (38), 10.1140/epjd/s10053-022-00355-0) - Stierhof, Jakob; Kuehn, S.; Winter, Michael; Micke, Peter; Steinbruegge, R.; Shah, C.; Hell, N.; Bissinger, Matthias; Hirsch, Maria; Ballhausen, Ralf; Lang, Melanie; Gräfe, Christina; et al. (European Physical Journal D, 2022)
CRIS-Team Scopus Importer:2022-11-11

Correction to: The Athena X-IFU Instrument Simulator xifusim (Journal of Low Temperature Physics, (2022), 10.1007/s10909-022-02700-4) - Kirsch, Christian; Lorenz, Maximilian; Peille, P.; Dauser, Thomas; Ceballos, M. T.; Cobo, B.; Merino-Alonso, P. E.; Cucchetti, E.; Smith, S. J.; Gottardi, L.; Den Hartog, R. H.; Miniussi, A.; et al. (Journal of Low Temperature Physics, 2022)
The original version of this article unfortunately contained a mistake. The co-author "R. H. den Hartog" affiliation should read as "SRON Netherlands Institute for Space Reseach, Niels Bohrweg 4, 2333 CA Leiden, Netherlands" instead of "Friedrich- Alexander-Universität Erlangen-Nürnberg, Dr. Karl Remeis-Observatory & ECAP, Sternwartstr. 7, Bamberg 96049, Germany". It is now corrected with this correction.
CRIS-Team Scopus Importer:2022-04-29

Correlated optical, X- ray, and gamma- ray flaring activity seen with INTEGRAL during the 2015 outburst of V404 Cygni - Rodriguez, J.; Bel, M. Cadolle; Alfonso-Garzon, J.; Siegert, T.; Zhang, X. -L.; Grinberg, V.; Savchenko, V.; Tomsick, J. A.; Chenevez, J.; Clavel, M.; Corbel, S.; Diehl, R.; et al. (Astronomy & Astrophysics, 2015)
After 25 years of quiescence, the microquasar V404 Cyg entered a new period of activity in June 2015. This X-ray source is known to undergo extremely bright and variable outbursts seen at all wavelengths. It is therefore an object of prime interest to understand the accretion-ejection connections. These can, however, only be probed through simultaneous observations at several wavelengths. We made use of the INTEGRAL instruments to obtain long, almost uninterrupted observations from 2015 June 20, 15: 50 UTC to June 25, 4: 05 UTC, from the optical V band up to the soft gamma-rays. V404 Cyg was extremely variable in all bands, with the detection of 18 flares with fluxes exceeding 6 Crab (20-40 keV) within three days. The flare recurrence can be as short as similar to 20 min from peak to peak. A model-independent analysis shows that the >6 Crab flares have a hard spectrum. A simple 10-400 keV spectral analysis of the off-flare and flare periods shows that the variation in intensity is likely to be only due to variations of a cut-off power-law component. The optical flares seem to be at least of two different types: one occurring in simultaneity with the X-ray flares, the other showing a delay greater than 10 min. The former could be associated with X-ray reprocessing by either an accretion disk or the companion star. We suggest that the latter are associated with plasma ejections that have also been seen in radio.
Keywords: accretion; accretion disks; X-rays: binaries; radio continuum: stars; stars: black holes; stars: individual: V404 Cygni

Correlated radio-X-ray variability of galactic black holes: A radio-X-ray flare in cygnus X-1 - Wilms, Jörn; et al. (Astrophysical Journal, 2007)
We report on the first detection of a quasi-simultaneous radio-X-ray flare of Cygnus X-1. The detection was made on 2005 April 16 with pointed observations by the RXTE and the Ryle telescope, during a phase where the black hole candidate was close to a transition from its soft state to its hard state. The radio flare lagged the X-rays by similar to 7 minutes, peaking at 3:20 hr barycentric time (TDB 2,453,476.63864). We discuss this lag in the context of models explaining such flaring events as the ejection of electron bubbles emitting synchrotron radiation.
Keywords: accretion; ccretion disks; black hole physics; X-rays : binaries; X-rays : stars

Cosmic ray oriented performance studies for the JEM-EUSO first level trigger - Abdellaoui, Ghouti; Abe, S.; Acheli, A.; Adams, J. H.; Ahmad, S.; Ahriche, A.; Albert, J. -N.; Allard, D.; Alonso, Gustavo; Anchordoqui, L.; Andreev, V.; Anzalone, A.; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2017)
JEM-EUSO is a space mission designed to investigate Ultra-High Energy Cosmic Rays and Neutrinos (E > 5.10(19) eV) from the International Space Station (ISS). Looking down from above its wide angle telescope is able to observe their air showers and collect such data from a very wide area. Highly specific trigger algorithms are needed to drastically reduce the data load in the presence of both atmospheric and human activity related background light, yet retain the rare cosmic ray events recorded in the telescope. We report the performance in offline testing of the first level trigger algorithm on data from JEM-EUSO prototypes and laboratory measurements observing different light sources: data taken during a high altitude balloon flight over Canada, laser pulses observed from the ground traversing the real atmosphere, and model landscapes reproducing realistic aspect ratios and light conditions as would be seen from the ISS itself. The first level trigger logic successfully kept the trigger rate within the permissible bounds when challenged with artificially produced as well as naturally encountered night sky background fluctuations and while retaining events with general air-shower characteristics. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: JEM-EUSO; Trigger system; FPGA; Nightglow background

CRIRES high-resolution near-infrared spectroscopy of diffuse interstellar band profiles Detection of 12 new DIBs in the YJ band and the introduction of a combined ISM sight line and stellar analysis approach - Ebenbichler, A.; Postel, A.; Przybilla, N.; Seifahrt, A.; Wessmayer, D.; Kausch, W.; Firnstein, M.; Butler, K.; Kaufer, A.; Linnartz, H. (Astronomy & Astrophysics, 2022)
Aims. A high spectral resolution investigation of diffuse interstellar bands (DIBs) in the near-infrared (YJ band) is conducted to test new methods, to confirm and improve existing parameters, and to search for new DIBs. Methods. The CRyogenic high-resolution InfraRed Echelle Spectrograph (CRIRES) on the European Southern Observatory's Very Large Telescope was employed to obtain spectra of four reddened background supergiant stars (HD 183143, HD 165784, HD 92207, HD 111613) and an unreddened comparison star (HD 87737) at the highest resolution of R ≈ 100 000 currently achievable at near-infrared wavelengths, more than twice as high as accomplished in previous near-infrared DIB studies. The correction for telluric absorption was performed by a modelling approach. Non-local thermodynamic equilibrium spectral modelling of available optical and the new near-infrared stellar spectra facilitated a comprehensive characterisation of the atmospheric properties of the background stars. As a consequence, a more precise and accurate determination of the reddening and the reddening law along the respective sight lines could be achieved than feasible before by comparison of the observed and model spectral energy distributions. For DIBs that overlap with stellar lines the DIB profile shapes could be recovered. Results. Seventeen known near-infrared DIBs were confirmed, and 12 previously unknown and generally weaker DIBs were identified in the YJ band. Three DIBs that show uniform profiles along all sight lines were identified, possibly connected to transitions from a common lower state of the same carrier. The divergent extinction curve towards the frequently discussed DIB standard star HD 183143 could be reproduced for the first time, requiring extra absorption by 3.5 mag due to polycyclic aromatic hydrocarbons (PAHs) to match the ultraviolet extinction bump. This extra absorption probably stems from a circumstellar bubble lying in front of the star which is intersected tangentially by the line of sight, making this particular sight line more peculiar than standard.
CRIS-Team WoS Importer:2022-07-08
Keywords: dust; extinction; ISM: lines and bands; ISM: molecules; line: profiles; stars: early-type; supergiants

Crosstalk in an FDM Laboratory Setup and the Athena X-IFU End-to-End Simulator - Den Hartog, Roland; Kirsch, Christian; De Vries, C.; Akamatsu, H.; Dauser, Thomas; Peille, P.; Cucchetti, E.; Jackson, B.; Bandler, S.; Smith, Stephen; Wilms, Jörn (SPRINGER/PLENUM PUBLISHERS, 2018)
The impact of various crosstalk mechanisms on the performance of the Athena X-IFU instrument has been assessed with detailed end-to-end simulations. For the crosstalk in the electrical circuit, a detailed model has been developed. In this contribution, we test this model against measurements made with an FDM laboratory setup and discuss the assumption of deterministic crosstalk in the context of the weak link effect in the detectors. We conclude that crosstalk levels predicted by the model are conservative with respect to the observed levels.
Keywords: Athena; X-IFU; TES; FDM; Crosstalk

Cyclotron line energy in Hercules X-1: Stable after the decay - Staubert, R.; Ducci, L.; Ji, L.; Fürst, F.; Wilms, Jörn; Rothschild, R. E.; Pottschmidt, K.; Brumback, M.; Harrison, F. (Astronomy & Astrophysics, 2020)
We summarize the results of a dedicated effort made between 2012 and 2019 to follow the evolution of the cyclotron line in Her X-1 through repeated NuSTAR observations. The previously observed nearly 20-year-long decay of the cyclotron line energy has ended in 2012: from then on, the pulse-phase-averaged flux-corrected cyclotron line energy has remained stable and constant at an average value of Ecyc = (37.44 ± 0.07) keV (normalized to a flux level of 6.8 RXTE/ASM-cts s-1). The flux dependence of Ecyc discovered in 2007 is now measured with high precision, giving a slope of (0.675 ± 0.075) keV/(ASM-cts s-1), corresponding to an increase of 6.5% of Ecyc for an increase in flux by a factor of two. We also find that all line parameters as well as the continuum parameters show a correlation with X-ray flux. While a correlation between Ecyc and X-ray flux (both positive and negative) is now known for several accreting binaries with various suggestions for the underlying physics, the phenomenon of a long-term decay has so far only been seen in Her X-1 and Vela X-1, with far less convincing explanations.
CRIS-Team Scopus Importer:2020-11-13
Keywords: Pulsars: individual: Her X-1; Radiation mechanisms: general; Scattering; Stars: magnetic field; Stars: neutron; X-rays: stars

Cyclotron line features of magnetized accreting neutron stars - Wilms, Jörn; et al. (2007)
Providing the only known direct estimate of the magnetic field strength of an accreting neutron star, the study of 'Cyclotron Resonance Scattering Features' (often abbreviated CRSFs or cyclotron lines) is fundamental to a better understanding of the physics of those powerful X-ray sources. During the last three decades cyclotron lines have been detected as absorption features in many accreting neutron star binaries [1, 2, 3, 4]. The excellent energy resolution of todays' instruments on satellites such as INTEGRAL allows not only for the detection of cyclotron lines but also for a good resolution of their complex line shapes. Using a revised version of the Monte Carlo code by R. Araya [5, 6], we set up a preliminary model for cyclotron line formation and compare its predictions to observational data.
Keywords: X-rays : stars; stars : neutron; magnetic fields; line : formation

Cyclotron lines in highly magnetized neutron stars - Staubert, R.; Truemper, J.; Kendziorra, E.; Klochkov, D.; Postnov, K.; Kretschmar, P.; Pottschmidt, K.; Haberl, F.; Rothschild, R. E.; Santangelo, A.; Wilms, Jörn; Kreykenbohm, Ingo; et al. (Astronomy & Astrophysics, 2019)
Cyclotron lines, also called cyclotron resonant scattering features are spectral features, generally appearing in absorption, in the X-ray spectra of objects containing highly magnetized neutron stars, allowing the direct measurement of the magnetic field strength in these objects. Cyclotron features are thought to be due to resonant scattering of photons by electrons in the strong magnetic fields. The main content of this contribution focusses on electron cyclotron lines as found in accreting X-ray binary pulsars (XRBP) with magnetic fields on the order of several 10(12) Gauss. Also, possible proton cyclotron lines from single neutron stars with even stronger magnetic fields are briefly discussed. With regard to electron cyclotron lines, we present an updated list of XRBPs that show evidence of such absorption lines. The first such line was discovered in a 1976 balloon observation of the accreting binary pulsar Hercules X-1, it is considered to be the first direct measurement of the magnetic field of a neutron star. As of today (end 2018), we list 35 XRBPs showing evidence of one ore more electron cyclotron absorption line(s). A few have been measured only once and must be confirmed (several more objects are listed as candidates). In addition to the Tables of objects, we summarize the evidence of variability of the cyclotron line as a function of various parameters (especially pulse phase, luminosity and time), and add a discussion of the di ff erent observed phenomena and associated attempts of theoretical modeling. We also discuss our understanding of the underlying physics of accretion onto highly magnetized neutron stars. For proton cyclotron lines, we present tables with seven neutron stars and discuss their nature and the physics in these objects.
Keywords: accretion; accretion disks; magnetic fields; radiation mechanisms: non-thermal; binaries: general; X-rays: binaries; stars: neutron

Cyclotron resonant scattering feature simulations II. Description of the CRSF simulation process - Schwarm, Fritz-Walter; Ballhausen, Ralf; Falkner, Sebastian; Schoenherr, G.; Pottschmidt, K.; Wolff, M. T.; Becker, P. A.; Furst, F.; Marcu-Cheatham, D. M.; Hemphill, P. B.; Sokolova-Lapa, E.; Dauser, Thomas; et al. (Astronomy & Astrophysics, 2017)
Context. Cyclotron resonant scattering features (CRSFs) are formed by scattering of X-ray photons off quantized plasma electrons in the strong magnetic field (of the order 10(12) G) close to the surface of an accreting X-ray pulsar. Due to the complex scattering cross-sections, the line profiles of CRSFs cannot be described by an analytic expression. Numerical methods, such as Monte Carlo (MC) simulations of the scattering processes, are required in order to predict precise line shapes for a given physical setup, which can be compared to observations to gain information about the underlying physics in these systems.Aims. A versatile simulation code is needed for the generation of synthetic cyclotron lines. Sophisticated geometries should be investigatable by making their simulation possible for the first time.Methods. The simulation utilizes the mean free path tables described in the first paper of this series for the fast interpolation of propagation lengths. The code is parallelized to make the very time-consuming simulations possible on convenient time scales. Furthermore, it can generate responses to monoenergetic photon injections, producing Green's functions, which can be used later to generate spectra for arbitrary continua.Results. We develop a new simulation code to generate synthetic cyclotron lines for complex scenarios, allowing for unprecedented physical interpretation of the observed data. An associated XSPEC model implementation is used to fit synthetic line profiles to NuSTAR data of Cep X-4. The code has been developed with the main goal of overcoming previous geometrical constraints in MC simulations of CRSFs. By applying this code also to more simple, classic geometries used in previous works, we furthermore address issues of code verification and cross-comparison of various models. The XSPEC model and the Green's function tables are available online (see link in footnote, page 1).
Keywords: X-rays: binaries; stars: neutron; methods: numerical

Cyclotron resonant scattering feature simulations: I. Thermally averaged cyclotron scattering cross sections, mean free photon-path tables, and electron momentum sampling - Schwarm, Fritz-Walter; Schönherr, Gabriele; Falkner, Sebastian; Pottschmidt, Katja; Wolff, Michael; Becker, Peter A.; Sokolova-Lapa, Ekaterina; Klochkov, Dmitry; Ferrigno, Carlo; Fuerst, Felix; Hemphill, Paul F.; Marcu-Cheatham, Diana M.; et al. (Astronomy & Astrophysics, 2017)
Context. Electron cyclotron resonant scattering features (CRSFs) are observed as absorption-like lines in the spectra of X-ray pulsars. A significant fraction of the computing time for Monte Carlo simulations of these quantum mechanical features is spent on the calculation of the mean free path for each individual photon before scattering, since it involves a complex numerical integration over the scattering cross section and the (thermal) velocity distribution of the scattering electrons. Aims. We aim to numerically calculate interpolation tables which can be used in CRSF simulations to sample the mean free path of the scattering photon and the momentum of the scattering electron. The tables also contain all the information required for sampling the scattering electron's final spin. Methods. The tables were calculated using an adaptive Simpson integration scheme. The energy and angle grids were refined until a prescribed accuracy is reached. The tables are used by our simulation code to produce artificial CRSF spectra. The electron momenta sampled during these simulations were analyzed and justified using theoretically determined boundaries. Results. We present a complete set of tables suited for mean free path calculations of Monte Carlo simulations of the cyclotron scattering process for conditions expected in typical X-ray pulsar accretion columns (0:01 ≤ B/B ≤ 0.12, where B = 4.413 × 10 G, and 3 keV ≤ kT ≤ 15 keV). The sampling of the tables is chosen such that the results have an estimated relative error of at most 1=15 for all points in the grid. The tables are available online (see link in footnote, page 1
Keywords: Methods: numerical; Stars: neutron; X-rays: binaries

Cygnus X-1 contains a 21-solar mass black hole-Implications for massive star winds - Miller-Jones, James C.A.; Bahramian, Arash; Orosz, Jerome A.; Mande, Ilya; Gou, Lijun; Maccarone, Thomas J.; Neijsse, Coenraad J.; Zhao, Xueshan; Ziółkowski, Janusz; Reid, Mark J.; Uttley, Phil; Zheng, Xueying; et al. (Science, 2021)
The evolution of massive stars is influenced by the mass lost to stellar winds over their lifetimes. These winds limit the masses of the stellar remnants (such as black holes) that the stars ultimately produce. We used radio astrometry to refine the distance to the black hole X-ray binary Cygnus X-1, which we found to be 2:220:180:17 kiloparsecs. When combined with archival optical data, this implies a black hole mass of 21.2 ± 2.2 solar masses, which is higher than previous measurements. The formation of such a high-mass black hole in a high-metallicity system (within the Milky Way) constrains wind mass loss from massive stars.
CRIS-Team Scopus Importer:2021-03-19

Decomposing blazar spectra into lepto-hadronic emission components - Gokus, A.; Richter, S.; Spanier, Felix; Kreter, M.; Kadler, M.; Mannheim, K.; Wilms, Jörn (Astronomische Nachrichten, 2018)
The recently reported coincidences between high-energy neutrino events and major blazar outbursts reinforce the relevance of lepto-hadronic emission models for blazars. We study the influence of physical parameters on the neutrino output by modeling blazar spectral energy distributions self-consistently assuming a relativistically propagating acceleration zone surrounded by a larger cooling zone. We find that the gross features of the spectral energy distribution can readily be explained with the model. A rigorous test requires time-resolved measurements of blazar spectral energy distributions during an outburst and high-statistics neutrino measurements to discriminate the leptonic and hadronic emission components.
Keywords: acceleration of particles; galaxies: Active; galaxies: Individual (TXS 0506+056)

Deep Chandra Survey of the Small Magellanic Cloud. III. Formation Efficiency of High-mass X-Ray Binaries - Antoniou, Vallia; Zezas, Andreas; Drake, Jeremy J.; Badenes, Carles; Haberl, Frank; Wright, Nicholas J.; Hong, Jaesub; Di Stefano, Rosanne; Gaetz, Terrance J.; Long, Knox S.; Plucinsky, Paul P.; Sasaki, Manami; et al. (Astrophysical Journal, 2019)
We have compiled the most complete census of high-mass X-ray binaries (HMXBs) in the Small Magellanic Cloud with the aim to investigate the formation efficiency of young accreting binaries in its low-metallicity environment. In total, we use 123 X-ray sources with detections in our Chandra X-ray Visionary Program (XVP), supplemented by 14 additional (likely and confirmed) HMXBs identified by Haberl & Sturm that fall within the XVP area, but are neither detected in our survey (nine sources) nor matched with any of the 127 sources identified in the XVP data (five sources). Specifically, we examine the number ratio of the HMXBs [N(HMXBs)] to (a) the number of OB stars, (b) the local star formation rate (SFR), and (c) the stellar mass produced during the specific star formation burst, all as a function of the age of their parent stellar populations. Each of these indicators serves a different role, but in all cases we find that the HMXB formation efficiency increases as a function of time (following a burst of star formation) up to similar to 40-60 Myr, and then gradually decreases. The formation efficiency peaks at similar to 30-40 Myr with average rates of N(HMXB)/SFR = 339(-83)(+78) (M-circle dot/yr)(-1), and N(HMXB)/M-* = (8.74(-0.92)(+1.0)) x 10(-6) M-circle dot(-1,) in good agreement with previous estimates of the average formation efficiency in the broad similar to 20-60 Myr age range.
CRIS-Team WoS Importer:2020-01-21

Deeper HESS observations of Vela Junior (RX J0852.0-4622): Morphology studies and resolved spectroscopy - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Andersson, T.; Anguener, E. O.; Arakawa, M.; Arrieta, M.; Aubert, P.; Backes, Michael; Balzer, A.; et al. (Astronomy & Astrophysics, 2018)
Aims. We study gamma-ray emission from the shell-type supernova remnant (SNR) RXJ0852.0-4622 to better characterize its spectral properties and its distribution over the SNR.Methods. The analysis of an extended High Energy Spectroscopic System (H.E.S.S.) data set at very high energies (E > 100 GeV) permits detailed studies, as well as spatially resolved spectroscopy, of the morphology and spectrum of the whole RXJ0852.0-4622 region. The H.E.S.S. data are combined with archival data from other wavebands and interpreted in the framework of leptonic and hadronic models. The joint Fermi-LAT-H.E.S.S. spectrum allows the direct determination of the spectral characteristics of the parent particle population in leptonic and hadronic scenarios using only GeV-TeV data.Results. An updated analysis of the H.E.S.S. data shows that the spectrum of the entire SNR connects smoothly to the high-energy spectrum measured by Fermi-LAT. The increased data set makes it possible to demonstrate that the H.E.S.S. spectrum deviates significantly from a power law and is well described by both a curved power law and a power law with an exponential cutoff at an energy of E-cut = (6.7 +/- 1.2(stat) +/- 1.2(syst)) TeV. The joint Fermi-LAT-H.E.S.S. spectrum allows the unambiguous identification of the spectral shape as a power law with an exponential cutoff. No significant evidence is found for a variation of the spectral parameters across the SNR, suggesting similar conditions of particle acceleration across the remnant. A simple modeling using one particle population to model the SNR emission demonstrates that both leptonic and hadronic emission scenarios remain plausible. It is also shown that at least a part of the shell emission is likely due to the presence of a pulsar wind nebula around PSR J0855-4644.
Keywords: astroparticle physics; gamma rays: general; acceleration of particles; cosmic rays; ISM: supernova remnants

Deep-Sea Bioluminescence Blooms after Dense Water Formation at the Ocean Surface - Tamburini, Christian; Canals, Miquel; Houpert, Loic; Lefevre, Dominique; Martini, Verine; D'Ortenzio, Fabrizio; Robert, Anne; Testor, Pierre; Aguilar, Juan Antonio; Al Samarai, Imen; Albert, Arnaud; Andre, Michel; et al. (PLoS ONE, 2013)
The deep ocean is the largest and least known ecosystem on Earth. It hosts numerous pelagic organisms, most of which are able to emit light. Here we present a unique data set consisting of a 2.5-year long record of light emission by deep-sea pelagic organisms, measured from December 2007 to June 2010 at the ANTARES underwater neutrino telescope in the deep NW Mediterranean Sea, jointly with synchronous hydrological records. This is the longest continuous time-series of deep-sea bioluminescence ever recorded. Our record reveals several weeks long, seasonal bioluminescence blooms with light intensity up to two orders of magnitude higher than background values, which correlate to changes in the properties of deep waters. Such changes are triggered by the winter cooling and evaporation experienced by the upper ocean layer in the Gulf of Lion that leads to the formation and subsequent sinking of dense water through a process known as "open-sea convection". It episodically renews the deep water of the study area and conveys fresh organic matter that fuels the deep ecosystems. Luminous bacteria most likely are the main contributors to the observed deep-sea bioluminescence blooms. Our observations demonstrate a consistent and rapid connection between deep open-sea convection and bathypelagic biological activity, as expressed by bioluminescence. In a setting where dense water formation events are likely to decline under global warming scenarios enhancing ocean stratification, in situ observatories become essential as environmental sentinels for the monitoring and understanding of deep-sea ecosystem shifts.

Deep-sea deployment of the KM3NeT neutrino telescope detection units by self-unrolling - Aiello, S.; Domi, Alba; Albert, A.; Garre, S. Alves; Aly, Z.; Ameli, F.; Anassontzis, E.; Andre, M.; Androulakis, G.; Anghinolfi, M.; Anguita, M.; Anton, Gisela; et al. (Journal of Instrumentation, 2020)
KM3NeT is a research infrastructure being installed in the deep Mediterranean Sea. It will house a neutrino telescope comprising hundreds of networked moorings - detection units or strings - equipped with optical instrumentation to detect the Cherenkov radiation generated by charged particles from neutrino-induced collisions in its vicinity. In comparison to moorings typically used for oceanography, several key features of the KM3NeT string are different: the instrumentation is contained in transparent and thus unprotected glass spheres; two thin Dyneema (R) ropes are used as strength members; and a thin delicate backbone tube with fibre-optics and copper wires for data and power transmission, respectively, runs along the full length of the mooring. Also, compared to other neutrino telescopes such as ANTARES in the Mediterranean Sea and GVD in Lake Baikal, the KM3NeT strings are more slender to minimise the amount of material used for support of the optical sensors. Moreover, the rate of deploying a large number of strings in a period of a few years is unprecedented. For all these reasons, for the installation of the KM3NeT strings, a custom-made, fast deployment method was designed. Despite the length of several hundreds of metres, the slim design of the string allows it to be compacted into a small, re-usable spherical launching vehicle instead of deploying the mooring weight down from a surface vessel. After being lowered to the seafloor, the string unfurls to its full length with the buoyant launching vehicle rolling along the two ropes. The design of the vehicle, the loading with a string, and its underwater self-unrolling are detailed in this paper.
CRIS-Team WoS Importer:2020-12-18

Deep sea tests of a prototype of the KM3NeT digital optical module - Adrian-Martinez, S.; Ageron, M.; Aharonian, F.; Aiello, S.; Albert, A.; Ameli, F.; Anassontzis, E. G.; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; De Asmundis, R.; et al. (European Physical Journal C, 2014)
The first prototype of a photo-detection unit of the future KM3NeT neutrino telescope has been deployed in the deepwaters of the Mediterranean Sea. This digital optical module has a novel design with a very large photocathode area segmented by the use of 31 three inch photomultiplier tubes. It has been integrated in the ANTARES detector for in-situ testing and validation. This paper reports on the first months of data taking and rate measurements. The analysis results highlight the capabilities of the new module design in terms of background suppression and signal recognition. The directionality of the optical module enables the recognition of multiple Cherenkov photons from the same (40)Kdecay and the localisation of bioluminescent activity in the neighbourhood. The single unit can cleanly identify atmospheric muons and provide sensitivity to the muon arrival directions.

Deep XMM-Newton observations of the northern disc of M31 - Kavanagh, Patrick J.; Sasaki, Manami; Breitschwerdt, Dieter; De Avillez, Miguel A.; Filipovic, Miroslav D.; Galvin, Timothy; Haberl, Frank; Hatzidimitriou, Despina; Henze, Martin; Plucinsky, Paul P.; Saeedi, Sara; Sokolovsky, Kirill; et al. (Astronomy & Astrophysics, 2020)
Aims. We use new deep XMM-Newton observations of the northern disc of M31 to trace the hot interstellar medium (ISM) in unprecedented detail and to characterise the physical properties of the X-ray emitting plasmas.
CRIS-Team WoS Importer:2020-07-24

Dependence of atmospheric muon flux on seawater depth measured with the first KM3NeT detection units: The KM3NeT Collaboration - Ageron, M.; Aiello, S.; Ameli, F.; Andre, M.; Androulakis, G.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aublin, J.; Bagatelas, C.; Barbarino, G.; Baret, B.; et al. (European Physical Journal C: Particles and Fields, 2020)
KM3NeT is a research infrastructure located in the Mediterranean Sea, that will consist of two deep-sea Cherenkov neutrino detectors. With one detector (ARCA), the KM3NeT Collaboration aims at identifying and studying TeV–PeV astrophysical neutrino sources. With the other detector (ORCA), the neutrino mass ordering will be determined by studying GeV-scale atmospheric neutrino oscillations. The first KM3NeT detection units were deployed at the Italian and French sites between 2015 and 2017. In this paper, a description of the detector is presented, together with a summary of the procedures used to calibrate the detector in-situ. Finally, the measurement of the atmospheric muon flux between 2232–3386 m seawater depth is obtained.
CRIS-Team Scopus Importer:2020-02-18

Detecting clusters of galaxies and active galactic nuclei in an eROSITA all-sky survey digital twin - Seppi, R.; Comparat, J.; Bulbul, E.; Nandra, K.; Merloni, A.; Clerc, N.; Liu, T.; Ghirardini,; Liu, A.; Salvato, M.; Sanders, J. S.; Wilms, Jörn; et al. (Astronomy & Astrophysics, 2022)
Context. The extended ROentgen Survey with an Imaging Telescope Array (eROSITA) on board the Spectrum-Roentgen-Gamma (SRG) observatory is revolutionizing X-ray astronomy. The mission provides unprecedented samples of active galactic nuclei (AGN) and clusters of galaxies, with the potential of studying astrophysical properties of X-ray sources and measuring cosmological parameters using X-ray-selected samples with higher precision than ever before.
CRIS-Team WoS Importer:2022-09-30

Detection capabilities of the Athena X-IFU for the warm-hot intergalactic medium using gamma-ray burst X-ray afterglows - Walsh, Sarah; Mcbreen, Sheila; Martin-Carrillo, Antonio; Dauser, Thomas; Wijers, Nastasha; Wilms, Jörn; Schaye, Joop; Barret, Didier (Astronomy & Astrophysics, 2020)
At low redshifts, the observed baryonic density falls far short of the total number of baryons predicted. Cosmological simulations suggest that these baryons reside in filamentary gas structures, known as the warm-hot intergalactic medium (WHIM). As a result of the high temperatures of these filaments, the matter is highly ionised such that it absorbs and emits far-UV and soft X-ray photons. Athena, the proposed European Space Agency X-ray observatory, aims to detect the "missing"baryons in the WHIM up to redshifts of z = 1 through absorption in active galactic nuclei and gamma-ray burst (GRB) afterglow spectra, allowing for the study of the evolution of these large-scale structures of the Universe. This work simulates WHIM filaments in the spectra of GRB X-ray afterglows with Athena using the SImulation of X-ray TElescopes framework. We investigate the feasibility of their detection with the X-IFU instrument, through Oâ€» VII (E = 573 eV) and O VIII (E = 674 eV) absorption features, for a range of equivalent widths imprinted onto GRB afterglow spectra of observed starting fluxes ranging between 10-12 and 10-10 erg cm-2 s-1, in the 0.3-10 keV energy band. The analyses of X-IFU spectra by blind line search show that Athena will be able to detect O VII-O VIII absorption pairs with EWO VII > 0.13 eV and EWO VIII > 0.09 eV for afterglows with F > 2 × 10-11 erg cm-2 s-1. This allows for the detection of ≈ 45-137 O VII-O VIII absorbers during the four-year mission lifetime. The work shows that to obtain an O VII-O VIII detection of high statistical significance, the local hydrogen column density should be limited at NH < 8 × 1020 cm-2.
CRIS-Team Scopus Importer:2020-10-30
Keywords: Gamma-ray burst: general; Instrumentation: detectors; Intergalactic medium; Large-scale structure of Universe; X-rays: general

Detection of a giant flare displaying quasi-periodic pulsations from a pre-main-sequence M star by the Next Generation Transit Survey - Jackman, James A. G.; Wheatley, Peter J.; Pugh, Chloe E.; Kolotkov, Dmitrii Y.; Broomhall, Anne-Marie; Kennedy, Grant M.; Murphy, Simon J.; Raddi, Roberto; Burleigh, Matthew R.; Casewell, Sarah L.; Eigmueller, Philipp; Gillen, Edward; et al. (Monthly Notices of the Royal Astronomical Society, 2019)
We present the detection of an energetic flare on the pre-main-sequence M3 star NGTS J121939.5-355557, which we estimate to be only 2 Myr old. The flare had an energy of 3.2 +/-(0.4)(0.3) x 10(36) erg and a fractional amplitude of 7.2 +/- 0.8, making it one of the most energetic flares seen on an M star. The star is alsoX-ray active, in the saturated regime with log L-X/L-Bol = -3.1. In the flare's peak, we have identified multimode quasi-periodic pulsations formed of two statistically significant periods of approximately 320 and 660 s. This flare is one of the largest amplitude events to exhibit such pulsations. The shorter period mode is observed to start after a short-lived spike in flux lasting around 30 s, which would not have been resolved in Kepler or TESS short-cadence modes. Our data show how the high cadence of the Next Generation Transient Survey (NGTS) can be used to apply solar techniques to stellar flares and to identify potential causes of the observed oscillations. We also discuss the implications of this flare for the habitability of planets around M star hosts and how NGTS can help our understanding of this.
CRIS-Team WoS Importer:2019-04-09

Detection of extended γ -ray emission around the Geminga pulsar with H.E.S.S. - Aharonian, F.; Ait Benkhali, F.; Aschersleben, J.; Ashkar, H.; Backes, M.; Barbosa Martins, V.; Batzofin, R.; Becherini, Y.; Berge, D.; Bernlöhr, K.; Bi, B.; Böttcher, M.; et al. (Astronomy & Astrophysics, 2023)
Geminga is an enigmatic radio-quiet γ-ray pulsar located at a mere 250 pc distance from Earth. Extended very-high-energy γ-ray emission around the pulsar was discovered by Milagro and later confirmed by HAWC, which are both water Cherenkov detector-based experiments. However, evidence for the Geminga pulsar wind nebula in gamma rays has long evaded detection by imaging atmospheric Cherenkov telescopes (IACTs) despite targeted observations. The detection of γ-ray emission on angular scales ≳2° poses a considerable challenge for the background estimation in IACT data analysis. With recent developments in understanding the complementary background estimation techniques of water Cherenkov and atmospheric Cherenkov instruments, the H.E.S.S. IACT array can now confirm the detection of highly extended γ-ray emission around the Geminga pulsar with a radius of at least 3° in the energy range 0.5-40 TeV. We find no indications for statistically significant asymmetries or energy-dependent morphology. A flux normalisation of (2.8 ± 0.7)×10-12 cm-2 s-1 TeV-1 at 1 TeV is obtained within a 1° radius region around the pulsar. To investigate the particle transport within the halo of energetic leptons around the pulsar, we fitted an electron diffusion model to the data. The normalisation of the diffusion coefficient obtained of D0 = 7.6-1.2+1.5×1027 cm2 s-1, at an electron energy of 100 TeV, is compatible with values previously reported for the pulsar halo around Geminga, which is considerably below the Galactic average.
CRIS-Team Scopus Importer:2023-06-16
Keywords: Acceleration of particles; Diffusion; Gamma rays: general; Pulsars: general

Detection of large-scale X-ray bubbles in the Milky Way halo - Predehl, P.; Sunyaev, R. A.; Becker, W.; Brunner, H.; Burenin, R.; Bykov, A.; Cherepashchuk, A.; Chugai, N.; Churazov, E.; Doroshenko, V.; Eismont, N.; Freyberg, M.; et al. (Nature, 2020)
The halo of the Milky Way provides a laboratory to study the properties of the shocked hot gas that is predicted by models of galaxy formation. There is observational evidence of energy injection into the halo from past activity in the nucleus of the Milky Way1–4; however, the origin of this energy (star formation or supermassive-black-hole activity) is uncertain, and the causal connection between nuclear structures and large-scale features has not been established unequivocally. Here we report soft-X-ray-emitting bubbles that extend approximately 14 kiloparsecs above and below the Galactic centre and include a structure in the southern sky analogous to the North Polar Spur. The sharp boundaries of these bubbles trace collisionless and non-radiative shocks, and corroborate the idea that the bubbles are not a remnant of a local supernova5 but part of a vast Galaxy-scale structure closely related to features seen in γ-rays6. Large energy injections from the Galactic centre7 are the most likely cause of both the γ-ray and X-ray bubbles. The latter have an estimated energy of around 1056 erg, which is sufficient to perturb the structure, energy content and chemical enrichment of the circumgalactic medium of the Milky Way.
CRIS-Team Scopus Importer:2020-12-25

Detection of variable VHE gamma-ray emission from the extra-galactic gamma-ray binary LMC P3 - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Armand, C.; Arrieta, M.; Backes, Michael; Balzer, A.; Barnard, M.; Becherini, Y.; et al. (Astronomy & Astrophysics, 2018)
Context. Recently, the high-energy (HE, 0.1-100 GeV) gamma-ray emission from the object LMC P3 in the Large Magellanic Cloud (LMC) has been discovered to be modulated with a 10.3-day period, making it the first extra-galactic gamma-ray binary.
CRIS-Team WoS Importer:2020-01-15
Keywords: Gamma rays: stars; Binaries: general; Stars: massive

Detection potential of the KM3NeT detector for high-energy neutrinos from the Fermi bubbles - Adrian-Martinez, S.; Ageron, M.; Aguilar, J. A.; Aharonian, F.; Aiello, S.; Albert, A.; Alexandri, M.; Ameli, F.; Anassontzis, E. G.; Anghinolfi, M.; Anton, Gisela; Anvar, S.; et al. (Astroparticle Physics, 2013)
A recent analysis of the Fermi Large Area Telescope data provided evidence for a high-intensity emission of high-energy gamma rays with a E-2 spectrum from two large areas, spanning 50 above and below the Galactic centre (the "Fermi bubbles"). A hadronic mechanism was proposed for this gamma-ray emission making the Fermi bubbles promising source candidates of high-energy neutrino emission. In this work Monte Carlo simulations regarding the detectability of high-energy neutrinos from the Fermi bubbles with the future multi-km(3) neutrino telescope KM3NeT in the Mediterranean Sea are presented. Under the hypothesis that the gamma-ray emission is completely due to hadronic processes, the results indicate that neutrinos from the bubbles could be discovered in about one year of operation, for a neutrino spectrum with a cutoff at 100 TeV and a detector with about 6 km(3) of instrumented volume. The effect of a possible lower cutoff is also considered. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Neutrino telescope; Fermi Bubbles; KM3NeT

Development of the Wide Field Imager for Athena - Meidinger, Norbert; Eder, Josef; Fuermetz, Maria; Nandra, Kirpal; Pietschner, Daniel; Plattner, Markus; Rau, Arne; Reiffers, Jonas; Strecker, Rafael; Barbera, Marco; Brand, Thorsten; Wilms, Jörn (2015)
The WFI (Wide Field Imager) instrument is planned to be one of two complementary focal plane cameras on ESA's next X-ray observatory Athena. It combines unprecedented survey power through its large field of view of 40 arcmin x 40 arcmin together with excellent count-rate capability (>= 1 Crab). The energy resolution of the silicon sensor is state-of-the-art in the energy band of interest from 0.2 keV to 15 keV, e.g. the full width at half maximum of a line at 6 keV will be <= 150 eV until the end of the nominal mission phase. This performance is accomplished by using DEPFET active pixel sensors with a pixel size of 130 mu m x 130 mu m well suited to the on-axis angular resolution of 5 arcsec of the mirror system. Each DEPFET pixel is a combined detector-amplifier structure with a MOSFET integrated onto a fully depleted 450 mu m thick silicon bulk. Two different types of DEPFET sensors are planned for the WFI instrument: A set of four large-area sensors to cover the physical size of 14 cm x 14 cm in the focal plane and a single smaller gateable DEPFET sensor matrix optimized for high count-rate observations. Here we present the conceptual design of the instrument with focus on the critical subsystems and describe the instrument performance expectations. An outline of the model philosophy and the project organization completes the presentation.
Keywords: Active pixel sensor; Athena; DEPFET; focal plane camera; Hot and Energetic Universe; WFI; X-ray astronomy; X-ray detector

Developments and results in the context of the JEM-EUSO program obtained with the ESAF simulation and analysis framework - Abe, S.; Adams, J. H.; Allard, D.; Alldredge, P.; Anchordoqui, L.; Anzalone, A.; Arnone, E.; Baret, B.; Barghini, D.; Battisti, M.; Bayer, J.; Bellotti, R.; et al. (European Physical Journal C: Particles and Fields, 2023)
JEM-EUSO is an international program for the development of space-based Ultra-High Energy Cosmic Ray observatories. The program consists of a series of missions which are either under development or in the data analysis phase. All instruments are based on a wide-field-of-view telescope, which operates in the near-UV range, designed to detect the fluorescence light emitted by extensive air showers in the atmosphere. We describe the simulation software ESAF in the framework of the JEM-EUSO program and explain the physical assumptions used. We present here the implementation of the JEM-EUSO, POEMMA, K-EUSO, TUS, Mini-EUSO, EUSO-SPB1 and EUSO-TA configurations in ESAF. For the first time ESAF simulation outputs are compared with experimental data.
CRIS-Team Scopus Importer:2023-11-24

Dipping in Cygnus X-2 in a multi-wavelength campaign due to absorption of extended ADC emission - Balucinska-Church, M.; Schulz, N. S.; Wilms, Jörn; Gibiec, A.; Hanke, Manfred; Spencer, R. E.; Rushton, A.; Church, M. J. (Astronomy & Astrophysics, 2011)
We report results of one-day simultaneous multiwavelength observations of Cygnus X-2 using XMM, Chandra, the European VLBI Network and the XMM Optical Monitor. During the observations, the source did not exhibit Z-track movement, but remained in the vicinity of the soft apex. It was in a radio quiescent/quiet state of <150 mu Jy. Strong dip events were seen as 25% reductions in X-ray intensity. The use of broadband CCD spectra in combination with narrow-band grating spectra has now demonstrated for the first time that these dipping events in Cygnus X-2 are caused by absorption in cool material in quite a unique way. In the band 0.2-10 keV, dipping appears to be due to progressive covering of the Comptonized emission of an extended accretion disk corona, the covering factor rising to 40% in deep dipping with an associated column density of 3 x 10(23) atom cm(-2). Remarkably, the blackbody emission of the neutron star is not affected by these dips, in strong contrast with observations of typical low mass X-ray binary dipping sources. The Chandra and XMM gratings directly measure the optical depths in absorption edges such as Ne K, Fe L, and O K and a comparison of the optical depths in the edges of non-dip and dip data reveals no increase of optical depth during dipping even though the continuum emission sharply decreases. Based on these findings, at orbital phase 0.35, we propose that dipping in this observation is caused by absorption in the outer disk by structures located opposite to the impact bulge of the accretion stream. With an inclination angle >60 degrees these structures can still cover large parts of the extended ADC, without absorbing emission from the central neutral star.
Keywords: accretion; accretion disks; acceleration of particles; stars: neutron; X-rays: binaries; X-rays: individuals: Cyg X-2; radio continuum: general

Discovery and analysis of three magnetic hot subdwarf stars: evidence for merger-induced magnetic fields - Pelisoli, Ingrid; Dorsch, Matti; Heber, Ulrich; Gaensicke, B.; Geier, S.; Kupfer, T.; Nemeth, P.; Scaringi, S.; Schaffenroth, (Monthly Notices of the Royal Astronomical Society, 2022)
Magnetic fields can play an important role in stellar evolution. Among white dwarfs, the most common stellar remnant, the fraction of magnetic systems is more than 20 per cent. The origin of magnetic fields in white dwarfs, which show strengths ranging from 40 kG to hundreds of MG, is still a topic of debate. In contrast, only one magnetic hot subdwarf star has been identified out of thousands of known systems. Hot subdwarfs are formed from binary interaction, a process often associated with the generation of magnetic fields, and will evolve to become white dwarfs, which makes the lack of detected magnetic hot subdwarfs a puzzling phenomenon. Here we report the discovery of three new magnetic hot subdwarfs with field strengths in the range 300-500 kG. Like the only previously known system, they are all helium-rich O-type stars (He-sdOs). We analysed multiple archival spectra of the three systems and derived their stellar properties. We find that they all lack radial velocity variability, suggesting formation via a merger channel. However, we derive higher than typical hydrogen abundances for their spectral type, which are in disagreement with current model predictions. Our findings suggest a lower limit to the magnetic fraction of hot subdwarfs of 0.147(+0.143)(-0.047) per cent, and provide evidence for merger-induced magnetic fields which could explain white dwarfs with field strengths of 50-150 MG, assuming magnetic flux conservation.
CRIS-Team WoS Importer:2022-08-19

DISCOVERY OF A CLOSE SUBSTELLAR COMPANION TO THE HOT SUBDWARF STAR HD 149382-THE DECISIVE INFLUENCE OF SUBSTELLAR OBJECTS ON LATE STELLAR EVOLUTION - Geier, Stephan; Edelmann, Heinz; Heber, Ulrich; Heber, Ulrich; Morales-Rueda, L. (Astrophysical Journal Letters, 2009)
Substellar objects, like planets and brown dwarfs orbiting stars, are by-products of the star formation process. The evolution of their host stars may have an enormous impact on these small companions. Vice versa a planet might also influence stellar evolution as has recently been argued. Here, we report the discovery of an 8-23 Jupiter-mass substellar object orbiting the hot subdwarf HD 149382 in 2.391 d at a distance of only about five solar radii. Obviously, the companion must have survived engulfment in the red giant envelope. Moreover, the substellar companion has triggered envelope ejection and enabled the sdB star to form. Hot subdwarf stars have been identified as the sources of the unexpected ultraviolet (UV) emission in elliptical galaxies, but the formation of these stars is not fully understood. Being the brightest star of its class, HD 149382 offers the best conditions to detect the substellar companion. Hence, undisclosed substellar companions offer a natural solution for the long-standing formation problem of apparently single hot subdwarf stars. Planets and brown dwarfs may therefore alter the evolution of old stellar populations and may also significantly affect the UV emission of elliptical galaxies.
Keywords: binaries: spectroscopic; galaxies: evolution; planetary systems; stars: horizontal-branch; stars: individual (HD 149382); stars: low-mass; brown dwarfs

Discovery of a Double-detonation Thermonuclear Supernova Progenitor - Kupfer, Thomas; Bauer, Evan B.; Van Roestel, Jan; Bellm, Eric C.; Bildsten, Lars; Fuller, Jim; Prince, Thomas A.; Heber, Ulrich; Geier, Stephan; Green, Matthew J.; Kulkarni, Shrinivas R.; Bloemen, Steven; et al. (Astrophysical Journal Letters, 2022)
We present the discovery of a new double-detonation progenitor system consisting of a hot subdwarf B (sdB) binary with a white dwarf companion with a P (orb) = 76.34179(2) minutes orbital period. Spectroscopic observations are consistent with an sdB star during helium core burning residing on the extreme horizontal branch. Chimera light curves are dominated by ellipsoidal deformation of the sdB star and a weak eclipse of the companion white dwarf. Combining spectroscopic and light curve fits, we find a low-mass sdB star, M (sdB) = 0.383 +/- 0.028 M (circle dot) with a massive white dwarf companion, M (WD) = 0.725 +/- 0.026 M (circle dot). From the eclipses we find a blackbody temperature for the white dwarf of 26,800 K resulting in a cooling age of approximate to 25 Myr whereas our MESA model predicts an sdB age of approximate to 170 Myr. We conclude that the sdB formed first through stable mass transfer followed by a common envelope which led to the formation of the white dwarf companion approximate to 25 Myr ago. Using the MESA stellar evolutionary code we find that the sdB star will start mass transfer in approximate to 6 Myr and in approximate to 60 Myr the white dwarf will reach a total mass of 0.92 M (circle dot) with a thick helium layer of 0.17 M (circle dot). This will lead to a detonation that will likely destroy the white dwarf in a peculiar thermonuclear supernova. PTF1 J2238+7430 is only the second confirmed candidate for a double-detonation thermonuclear supernova. Using both systems we estimate that at least approximate to 1% of white dwarf thermonuclear supernovae originate from sdB+WD binaries with thick helium layers, consistent with the small number of observed peculiar thermonuclear explosions.
CRIS-Team WoS Importer:2022-02-04

Discovery of a flux-related change of the cyclotron line energy in Hercules X-1 - Wilms, Jörn; et al. (Astronomy & Astrophysics, 2007)
Aims. We present the results of ten years of repeated measurements of the Cyclotron Resonance Scattering Feature (CRSF) in the spectrum of the binary X-ray pulsar Her X-1 and report the discovery of a positive correlation of the centroid energy of this absorption feature in pulse phase averaged spectra with source luminosity.Methods. Our results are based on a uniform analysis of observations by the RXTE satellite from 1996 to 2005, using suffciently long observations of 12 individual 35-day Main-On states of the source.Results. The mean centroid energy E-c of the CRSF in pulse phase averaged spectra of Her X-1 during this time is around 40 keV, with significant variations from one Main-On state to the next. We find that the centroid energy of the CRSF in Her X-1 changes by similar to 5% in energy for a factor of 2 in luminosity. The correlation is positive, contrary to what is observed in some high luminosity transient pulsars.Conclusions. Our finding is the first significant measurement of a positive correlation between Ec and luminosity in any X-ray pulsar. We suggest that this behaviour is expected in the case of sub-Eddington accretion and present a calculation of a quantitative estimate, which is very consistent with the effect observed in Her X-1. We urge that Her X-1 is regularly monitored further and that other X-ray pulsars are investigated for a similar behaviour.
Keywords: accretion; accretion disks; binaries : eclipsing; stars : neutron; X-rays : binaries; X-rays : stars

Discovery of a highly magnetic He-sdO star from a double-degenerate binary merger - Dorsch, Matti; Reindl, N.; Pelisoli, I.; Heber, Ulrich; Geier, S.; Istrate, A. G.; Justham, S. (Astronomy & Astrophysics, 2022)
Helium-rich hot subdwarf stars of spectral type O (He-sdO) are considered prime candidates for stellar merger remnants. Such events should lead to the generation of strong magnetic fields. However, no magnetic He-sdO has yet been unambiguously discovered despite the high magnetic rate (20%) among white dwarf stars, the progeny of hot subdwarfs. Here we present the discovery of a strong magnetic field (B = 353 ± 10 kG) from Zeeman-split hydrogen, helium, and metal lines in the optical X-shooter spectrum of an He-sdO and present the first spectroscopic analysis of any magnetic hot subdwarf. For this we used line-blanketed TLUSTY non-local thermodynamic equilibrium models and assumed a simple homogeneous magnetic field. The derived atmospheric parameters Teff = 44 900 ± 1000 K and log g = 5.93 ± 0.15 are typical for He-sdO stars, while the star is less hydrogen-poor than most He-sdOs at log n(He)/n(H) = + 0.28 ± 0.10. The star is a slow rotator (vrot sin i < 40 km s-1). Its chemical composition is N-rich and C- and O-poor, and the Si and S abundances are close to solar. Combining the atmospheric parameters with Gaia parallax and photometry, the stellar radius and luminosity are found to be typical for He-sdOs and place the star on the helium main sequence in the Hertzsprung-Russell diagram. Its mass of 0.93-0.30+0.44 M⊙, although uncertain, appears to be remarkably high. The strong magnetic field along with the atmospheric parameters and metal abundances provide overwhelming evidence for the double-degenerate merger scenario.
CRIS-Team Scopus Importer:2022-02-25
Keywords: Stars: early-type; Stars: magnetic field; Subdwarfs

Discovery of a pulsar-powered bow shock nebula in the Small Magellanic Cloud supernova remnant DEMS5 - Alsaberi, Rami Z.E.; Maitra, C.; Filipović, M. D.; Bozzetto, L. M.; Haberl, F.; Maggi, P.; Sasaki, Manami; Manjolović, P.; Velović, V.; Kavanagh, P.; Maxted, N. I.; Urošević, D.; et al. (Monthly Notices of the Royal Astronomical Society, 2019)
We report the discovery of a new Small Magellanic Cloud pulsar wind nebula (PWN) at the edge of the supernova remnant (SNR) DEMS5. The pulsar powered object has a cometary morphology similar to the Galactic PWN analogues PSR B1951+32 and 'the mouse'. It is travelling supersonically through the interstellar medium.We estimate the pulsar kick velocity to be in the range of 700-2000 km s-1 for an age between 28 and 10 kyr. The radio spectral index for this SNR-PWN-pulsar system is flat (-0.29 ± 0.01) consistent with other similar objects. We infer that the putative pulsar has a radio spectral index of -1.8, which is typical for Galactic pulsars. We searched for dispersion measures up to 1000 cm-3 pc but found no convincing candidates with an S/N greater than 8. We produce a polarization map for this PWN at 5500 MHz and find a mean fractional polarization of P ∼ 23 per cent. The X-ray power-law spectrum (τ ∼ 2) is indicative of non-thermal synchrotron emission as is expected from PWN-pulsar system. Finally, we detect DEMS5 in infrared (IR) bands. Our IR photometric measurements strongly indicate the presence of shocked gas that is expected for SNRs. However, it is unusual to detect such IR emission in an SNR with a supersonic bow shock PWN.We also find a low-velocity HI cloud of ∼107 km s-1 that is possibly interacting with DEMS5. SNR DEMS5 is the first confirmed detection of a pulsar-powered bow shock nebula found outside the Galaxy.
CRIS-Team Scopus Importer:2019-07-09
Keywords: ISM: individual objects: DEMS5; ISM: supernova remnants; Magellanic Clouds; radiation mechanisms: general; radio continuum: ISM.

Discovery of a stripped red giant core in a bright eclipsing binary system - Maxted, P. F. L.; Anderson, D. R.; Burleigh, M. R.; Cameron, A. Collier; Heber, Ulrich; Gaensicke, B. T.; Geier, Stephan; Kupfer, Thomas; Marsh, T. R.; Nelemans, Gijs; O'Toole, S. J.; Ostensen, R. H.; et al. (Monthly Notices of the Royal Astronomical Society, 2011)
We have identified a star in the Wide Angle Search for Planets (WASP) archive photometry with an unusual light curve due to the total eclipse of a small, hot star by an apparently normal A-type star and with an orbital period of only 0.668d. From an analysis of the WASP light curve together with V-band and IC-band photometry of the eclipse and a spectroscopic orbit for the A-type star we estimate that the companion star has a mass of 0.23 ± 0.03M⊙ and a radius of 0.33 ± 0.01R⊙, assuming that the A-type star is a main-sequence star with the metallicity appropriate for a thick-disc star. The effective temperature of the companion is 13400 ± 1200K from which we infer a luminosity of 3 ± 1L⊙. From a comparison of these parameters to various models we conclude that the companion is most likely to be the remnant of a red giant star that has been very recently stripped of its outer layers by mass transfer on to the A-type star. In this scenario, the companion is currently in a shell hydrogen-burning phase of its evolution, evolving at nearly constant luminosity to hotter effective temperatures prior to ceasing hydrogen burning and fading to become a low-mass white dwarf composed of helium (He-WD). The system will then resemble the pre-He-WD/He-WD companions to A- and B-type stars recently identified from their Kepler satellite light curves (KOI-74, KOI-81 and KIC10657664). This newly discovered binary offers the opportunity to study the evolution of a stripped red giant star through the pre-He-WD stage in great detail. © 2011 The Authors Monthly Notices of the Royal Astronomical Society © 2011 RAS.
CRIS-Team Scopus Importer:2020-12-21
Keywords: Binaries: close; Binaries: eclipsing; Binaries: spectroscopic; Stars: individual: 1SWASPJ024743.37-251549.2; Stars: peculiar

Discovery of a very young high-mass X-ray binary associated with the supernova remnant MCSNRJ0513-6724 in the LMC - Maitra, C.; Haberl, F.; Filipovic, M. D.; Udalski, A.; Kavanagh, P. J.; Carpano, S.; Maggi, P.; Sasaki, Manami; Norris, R. P.; O'Brien, A.; Hotan, A.; Lenc, E.; et al. (Monthly Notices of the Royal Astronomical Society, 2019)
We report the discovery of a very young high-mass X-ray binary (HMXB) system associated with the supernova remnant (SNR) MCSNR J0513-6724 in the Large Magellanic Cloud (LMC), using XMM-Newton X-ray observations. The HMXB is located at the geometrical centre of extended soft X-ray emission, which we confirm as an SNR. The HMXB spectrum is consistent with an absorbed power law with spectral index similar to 1.6 and a luminosity of 7 x 10(33) erg s(-1) (0.2-12 keV). Tentative X-ray pulsations are observed with a periodicity of 4.4 s and the OGLE I-band light curve of the optical counterpart from more than 17.5 yr reveals a period of 2.2324 +/- 0.0003 d, which we interpret as the orbital period of the binary system. The X-ray spectrum of the SNR is consistent with non-equilibrium shock models as expected for young/less evolved SNRs. From the derived ionization time-scale we estimate the age of the SNR to be <6 kyr. The association of the HMXB with the SNR makes it the youngest HMXB, in the earliest evolutionary stage known to date. An HMXB as young as this can switch on as an accreting pulsar only when the spin period has reached a critical value. Under this assumption, we obtain an upper limit to the magnetic field of <5 x 10(11) G. This implies several interesting possibilities including magnetic field burial, possibly by an episode of post-supernova hyper-critical accretion. Since these fields are expected to diffuse out on a time-scale of 10(3)-10(4) yr, the discovery of a very young HMXB can provide us the unique opportunity to observe the evolution of the observable magnetic field for the first time in X-ray binaries.
CRIS-Team WoS Importer:2020-01-10

Discovery of eRASSt J192932.9-560346: A bright, two-pole accreting, eclipsing polar - Schwope, Axel; Buckley, David A. H.; Malyali, Adam; Potter, Stephen; König, Ole; Arcodia, Riccardo; Gromadzki, Mariusz; Rau, Arne (Astronomy & Astrophysics, 2022)
We report the discovery of a bright (V similar to 15), eclipsing, two-pole accreting magnetic cataclysmic variable (CV), a polar, as counterpart of the SRG/eROSITA and Gaia transients eRASStJ192932.9-560346 and Gaia21bxo. Frequent large-amplitude changes of its brightness at X-ray and optical wavelengths by more than four magnitudes are indicative of a CV nature of the source. Identification spectra obtained with the 10m SALT telescope revealed the typical features of a magnetic CV: strong, broad HeI, HeII, and hydrogen Balmer emission lines superposed on a blue continuum. Time-resolved photoelectric polarimetry revealed that the circular polarization varies from -20 to +20% and the linear polarization varies from 0 to 10%, confirming the system to be a magnetic CV of the polar subclass. High-cadence photometry revealed deep, structured eclipses, indicating that the system is a two-pole accretor. The orbital period determined from the eclipse times is 92.5094 +/- 0.0002 min. The X-ray spectrum is thermal only, and the implied luminosity is L-X = 2.2 x 10(31) erg s(-1) at the Gaia-determined distance of 376 pc.
CRIS-Team WoS Importer:2022-06-17

Discovery of Pulsation Dropout and Turn-on during the High State of the Accreting X-Ray Pulsar LMC X-4 - Brumback, Mckinley C.; Hickox, Ryan C.; Bachetti, Matteo; Ballhausen, Ralf; Furst, Felix S.; Pike, Sean; Pottschmidt, Katja; Tomsick, John A.; Wilms, Jörn (Astrophysical Journal Letters, 2018)
Two Nuclear Spectroscopic Telescope Array (NuSTAR) observations of the luminous X-ray pulsar LMC X-4 in 2015 October and November captured several bright accretion flares from this source, which has a long history of stable pulse and superorbital behavior. We present a timing analysis of these data in which we detect a rapid pulse "turn-on" in association with the accretion flares, during which the source reaches super-Eddington luminosities. Pulsations, which are normally seen from this source, are found to only occur for approximately one hour before and during the bright flares. Beyond one hour before and after the flares, we find pulsations to be weak or nonexistent, with fractional rms amplitudes of less than 0.05. At the onset of the flare, the pulse profiles exhibit a phase shift of 0.25 cycles that could be associated with a change in the emission geometry. This increase in pulse strength occurring well before the flare cannot be explained by the propeller effect, and potentially offers a connection between the magnetic properties of pulsars that accrete close to their Eddington limits and ultraluminous X-ray pulsars.
Keywords: pulsars: individual (LMC X-4); stars: neutron; X-rays: binaries

Discovery of pulsations from the Be/X-ray binary RX j0101.3-7211 in the SMC by XMM-Newton - Sasaki, Manami; Haberl, Frank; Keller, Stefan; Pietsch, Wolfgang (Astronomy and Astrophysics, 2001)
We report pulsations in the X-ray flux of RX J0101.3-7211 in the Small Magellanic Cloud (SMC)! with a period of (455 +/- 2) s in XMM-Newton EPIC-PN data. The X-ray spectrum can be described by a power-law with a photon index of 0.6 +/- 0.1. Timing analysis of ROSAT PSPC and HRI archival data confirms the pulsations and indicates a period increase of similar to5 s since 1993. RX J0101.3-7211 varied in brightness during the ROSAT observations with timescales of years with a maximum unabsorbed flux of 6 10(-13) erg cm(-2) s(-1) (0.1-2.4 keV). The flux during the XMM-Newton observation in the ROSAT band was lower than during the faintest ROSAT detection. The unabsorbed luminosity derived from the EPIC-PN spectrum is 2 10(35) erg s(-1) (0.2-10.0 keV) assuming a distance of 60 kpc. Optical spectra of the proposed counterpart taken at the 2.3 rn telescope of MSSSO in Australia in August 2000 show strong H alpha emission and indicate a Be star. The X-ray and optical data confirm RX J0101.3-7211 as a Be/X-ray binary pulsar in the SMC.
Keywords: stars : binaries : general; stars : emission-line; Be galaxies : Magellanic Clouds; X-rays : stars

DISCOVERY OF RADIAL VELOCITY VARIABLE POST-AGB STARS FROM THE MUCHFUSS PROJECT - Reindl, N.; Geier, S.; Kupfer, Thomas; Schaffenroth, Veronika; Heber, Ulrich; Barlow, B. N.; Ostensen, R. H. (2015)
In the course of the MUCHFUSS project we have discovered five radial velocity (RV) post-AGB stars. Among them, we found the first known RV variable 0(He) star, the only second known RV variable PG 1159 close binary candidate and three RV variable, H-rich post-AGB stars of O(H)-type.

Discovery of Shocked Molecular Clouds Associated with the Shell-type Supernova Remnant RX J0046.5-7308 in the Small Magellanic Cloud - Sano, H.; Matsumura, H.; Yamane, Y.; Maggi, P.; Fujii, K.; Tsuge, K.; Tokuda, K.; Alsaberi, R. Z. E.; Filipovic, M. D.; Maxted, N.; Rowell, G.; Uchida, H.; et al. (Astrophysical Journal, 2019)
RX J0046.5-7308 is a shell-type supernova remnant (SNR) in the Small Magellanic Cloud (SMC). We carried out new (CO)-C-12(J = 1-0, 3-2) observations toward the SNR using Mopra and the Atacama Submillimeter Telescope Experiment. We found eight molecular clouds (A-H) along the X-ray shell of the SNR. The typical cloud size and mass are similar to 10-15. pc and similar to 1000-3000. M-circle dot, respectively. The X-ray shell is slightly deformed and has the brightest peak in the southwestern shell where two molecular clouds A and B are located. The four molecular clouds A, B, F, and G have high intensity ratios of (CO)-C-12(J = 3-2)/(CO)-C-12(J = 1-0) > 1.2, which are not attributable to any identified internal infrared sources or high-mass stars. The H I cavity and its expanding motion are found toward the SNR, which are likely created by strong stellar winds from a massive progenitor. We suggest that the molecular clouds A-D, F, and G and H I clouds within the wind-blown cavity at V-LSR = 117.1-122.5 km s(-1) are associated with the SNR. The X-ray spectroscopy reveals the dynamical age of 26000(-2000)(+1000) yr and the progenitor mass of greater than or similar to 30M(circle dot), which is also consistent with the proposed scenario. We determine physical conditions of the giant molecular cloud LIRS 36A using the large velocity gradient analysis with archival data sets of the Atacama Large Millimeter/submillimeter Array; the kinematic temperature is 72(-37)(+50) K and the number density of molecular hydrogen is 1500(-300)(+600) cm(-3). The next generation of gamma-ray observations will allow us to study the pion-decay.-rays from the molecular clouds in the SMC SNR.
CRIS-Team WoS Importer:2019-09-06

Discovery of slow X-ray pulsations in the high-mass X-ray binary 4U 2206+54 - Reig, Pablo; Torrejon, J. M.; Negueruela, Ignacio; Blay, P.; Ribo, Marc; Wilms, Jörn (Astronomy & Astrophysics, 2009)
Context. The source 4U 2206+54 is one of the most enigmatic high-mass X-ray binaries. In spite of intensive searches, X-ray pulsations have not been detected in the time range 10(-3)-10(3) s. A cyclotron line at similar to 30 keV has been suggested by various authors but never detected with significance. The stellar wind of the optical companion is abnormally slow. The orbital period, initially reported to be 9.6 days, disappeared and a new periodicity of 19.25 days emerged.Aims. The main objective of our RXTE monitoring of 4U 2206+54 is to study the X-ray orbital variability of the spectral and timing parameters. The new long and uninterrupted RXTE observations allow us to search for long (similar to 1 h) pulsations for the first time.Methods. We divided the similar to 7-day observation into five intervals and obtained time-averaged energy spectra and power spectral density for each observation interval. We also searched for pulsations using various algorithms.Results. We have discovered 5560-s pulsations in the light curve of 4U2206+54. Initially detected in RXTE data, these pulsations are also present in INTEGRAL and EXOSAT observations. The average X-ray luminosity in the energy range 2-10 keV is 1.5 x 10(35) erg s(-1) with a ratio F-max/F-min similar to 5. This ratio implies an eccentricity of similar to 0.4, somewhat higher than previously suggested. The power spectrum is dominated by red noise that can be fitted with a single power law whose index and strength decrease with X-ray flux. The source also shows a soft excess at low energies. If the soft excess is modelled with a blackbody component, then the size and temperature of the emitting region agrees with its interpretation in terms of a hot spot on the neutron star surface.Conclusions. The discovery of X-ray pulsations in 4U 2206+54 confirms the neutron star nature of the compact companion and definitively rules out the presence of a black hole. The source displays variability on time scales of days, presumably due to changes in the mass accretion rate as the neutron star moves around the optical companion in a moderately eccentric orbit. If current models for the spin evolution in X-ray pulsars are correct, then the magnetic field of 4U 2206+54 at birth must have been B >= 10(14) G.
Keywords: stars: early-type; stars: emission-line; Be; stars: binaries: close; X-rays: binaries; stars: pulsars: general

Discovery of variable VHE gamma-ray emission from the binary system 1FGL J1018.6-5856 - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E. O.; Backes, Michael; Balzer, A.; Becherini, Y.; Tjus, J. Becker; Berge, D.; Bernhard, S.; Bernloehr, K.; et al. (Astronomy & Astrophysics, 2015)
Re-observations with the HESS telescope array of the very high-energy (VHE) source HESS J1018-589A that is coincident with the Fermi-LAT gamma-ray binary 1FGL J1018.6-5856 have resulted in a source detection significance of more than 9 sigma and the detection of variability (chi(2)/nu of 238.3/155) in the emitted gamma-ray flux. This variability confirms the association of HESS J1018-589A with the high-energy gamma-ray binary detected Fermi-LAT and also confirms the point-like source as a new VHE binary system. The spectrum of HESS J1018-589A is best fit with a power-law function with photon index Gamma = 2.20 +/- 0.14(stat) +/- 0.2(sys). Emission is detected up to similar to 20 TeV. The mean differential flux level is (2.9 +/- 0.4) x 10(-13) TeV-1 cm(-2) s(-1) at 1 TeV, equivalent to similar to 1% of the flux from the Crab Nebula at the same energy. Variability is clearly detected the night-by-night light curve. When folded on the orbital period of 16.58 days, the rebinned light curve peaks in phase with the observed X-ray high-energy phaseograms. The fit of the HESS phaseogram to a constant flux provides evidence of periodicity at the level of N-sigma > 3 sigma. The of the VHE phaseogram and measured spectrum suggest a low-inclination, low-eccentricity system with a modest impact from VHE gamma-ray due to pair production (tau less than or similar to 1 at 300 GeV).
Keywords: Acceleration of particles; Gamma rays: stars; Radiation mechanisms: non-thermal; Stars: individual: 1FGL J1018.6-5856; X-rays: binaries

Disk, Corona, Jet Connection in the Intermediate State of MAXI J1820+070 Revealed by NICER Spectral-timing Analysis - Wang, Jingyi; Mastroserio, Guglielmo; Kara, Erin; Garcia, Javier A.; Ingram, Adam; Connors, Riley; Van Der Klis, Michiel; Dauser, Thomas; Steiner, James F.; Buisson, Douglas J. K.; Homan, Jeroen; Lucchini, Matteo; et al. (Astrophysical Journal Letters, 2021)
We analyze five epochs of Neutron star Interior Composition Explorer (NICER) data of the black hole X-ray binary MAXI J1820+070 during the bright hard-to-soft state transition in its 2018 outburst with both reflection spectroscopy and Fourier-resolved timing analysis. We confirm the previous discovery of reverberation lags in the hard state, and find that the frequency range where the (soft) reverberation lag dominates decreases with the reverberation lag amplitude increasing during the transition, suggesting an increasing X-ray emitting region, possibly due to an expanding corona. By jointly fitting the lag-energy spectra in a number of broad frequency ranges with the reverberation model reltrans, we find the increase in reverberation lag is best described by an increase in the X-ray coronal height. This result, along with the finding that the corona contracts in the hard state, suggests a close relationship between spatial extent of the X-ray corona and the radio jet. We find the corona expansion (as probed by reverberation) precedes a radio flare by similar to 5 days, which may suggest that the hard-to-soft transition is marked by the corona expanding vertically and launching a jet knot that propagates along the jet stream at relativistic velocities.
CRIS-Team WoS Importer:2021-03-26

DISK-DOMINATED STATES OF 4U 1957+11: CHANDRA, XMM-NEWTON, AND RXTE OBSERVATIONS OF OSTENSIBLY THE MOST RAPIDLY SPINNING GALACTIC BLACK HOLE - Nowak, Michael A.; Juett, Adrienne; Homan, Jeroen; Yao, Yangsen; Wilms, Jörn; Schulz, Norbert S.; Canizares, Claude R. (Astrophysical Journal, 2008)
We present simultaneous Chandra High-Energy Transmission Gratings (HETG) and Rossi X-ray Timing Explorer (RXTE) observations of a "soft state'' of the black hole candidate 4U 1957+11. These spectra, having limited hard X-ray excess, are an excellent test of disk atmosphere models that include effects of black hole spin. The HETG data show, by modeling the broadband continuum and direct fitting of absorption edges, that the disk spectrum is only very mildly absorbed, with N-H = (1-2) x 10(21) cm(-2). These data additionally reveal lambda lambda 13.449 Ne IX absorption consistent with the warm/ hot phase of the interstellar medium. The fitted disk model implies an inclined disk around a low-mass black hole rotating with normalized spin a* approximate to 1. We show, however, that pure Schwarzschild models describe the data extremely well, albeit with large disk atmosphere "color-correction'' factors. Standard correction factors can be attained if one incorporates mild Comptonization. We find that the Chandra observations do not uniquely determine spin, even with this otherwise extremely well-measured, nearly pure disk spectrum. XMM-Newton RXTE observations, taken only six weeks later, are equally unconstraining. This lack of constraint is partly driven by the unknown mass and distance of 4U 1957+ 11; however, it is also driven by the limited Chandra and XMM-Newton bandpasses. We therefore present a series of 48 RXTE observations taken at different brightness/ hardness levels. These data prefer a spin of a* approximate to 1, even when including a mild Comptonization component; however, they also show evolution of the color-correction factors. If the rapid-spin models with standard correction factors are to be believed, then the RXTE observations predict that 4U 1957+ 11 can range from a 3 M-circle dot black hole at 10 kpc with a* approximate to 0: 83 to a 16 M-circle dot black hole at 22 kpc with
Keywords: accretion; accretion disks; black hole physics; radiation mechanisms: thermal; X-rays: binaries

DISTORTED CYCLOTRON LINE PROFILE IN CEP X-4 AS OBSERVED BY NuSTAR - Fuerst, F.; Pottschmidt, K.; Miyasaka, H.; Bhalerao, V.; Bachetti, M.; Boggs, S. E.; Christensen, F. E.; Craig, W. W.; Grinberg, V.; Hailey, C. J.; Harrison, F. A.; Kennea, J. A.; et al. (Astrophysical Journal Letters, 2015)
We present spectral analysis of Nuclear Spectroscopic Telescope Array and Swift observations of Cep X-4 during its outburst in 2014. We observed the source once during the peak of the outburst and once during the decay, finding good agreement in the spectral shape between the observations. We describe the continuum using a power law with a Fermi-Dirac cutoff at high energies. Cep X-4 has a very strong cyclotron resonant scattering feature (CRSF) around 30 keV. A simple absorption-like line with a Gaussian optical depth or a pseudo-Lorentzian profile both fail to describe the shape of the CRSF accurately, leaving significant deviations at the red side of the line. We characterize this asymmetry with a second absorption feature around 19 keV. The line energy of the CRSF, which is not influenced by the addition of this feature, shows a small but significant positive luminosity dependence. With luminosities between (1-6) x 10(36) erg s(-1), Cep X-4 is below the theoretical limit where such a correlation is expected. This behavior is similar to Vela X-1 and we discuss parallels between the two systems.
Keywords: accretion; accretion disks; radiation: dynamics; stars: neutron; X-rays: binaries; X-rays: individual (Cep X-4)

Doubling the number of Be/X-ray binaries in the SMC - Haberl, Frank; Sasaki, Manami (Astronomy & Astrophysics, 2000)
A correlation of X-ray source and H-alpha emission-line object catalogues in the Small Magellanic Cloud (SMC) shows that more than two thirds of the optically identified Be stars in Be/X-ray binaries an found as emission-line objects in the catalogues. On the basis of this result we propose up to 25 X-ray sources mainly from recent ROSAT catalogues as new Be/X-ray binaries and give their likely optical counterparts. Also for the five yet unidentified X-ray pulsars in the SMC we propose emission-line stars as counterparts. This more than doubles the number of known high mass X-ray binary systems in this nearby galaxy. The spatial distribution of the new candidates is similar to that of the already identified Be/X-ray binaries with a strong concentration along the SMC main body and some systems in the eastern wing. The new candidates contribute mainly to the low-luminosity end of the X-ray luminosity distribution of Be/X-ray binaries. A comparison with the luminosity distribution in the Milky Way reveals no significant differences at the high-luminosity end and the large number of low-luminosity systems in the SMC suggests that many such systems may still be undetected in the Galaxy. The overall ratio of known Be to OB supergiant X-ray binaries in the SMC is an order of magnitude larger than in the Galaxy, however, might show spatial variations. While in the eastern wing the ratio is comparable to that in the Galaxy no supergiant X-ray binary is currently known in the main body of the SMC. Possible explanations include a different star formation history over the last similar to 15 My.
Keywords: galaxies : Magellanic Clouds; galaxies : stellar content; stars : variables : general; X-rays : stars

Dual-frequency VLBI study of Centaurus A on sub-parsec scales The highest-resolution view of an extragalactic jet - Müller, Cornelia; Kadler, Matthias; Roopesh, Ojha; Wilms, Jörn; Böck, Moritz; Edwards, P. G.; Fromm, C. M.; Hase, H.; Horiuchi, S.; Katz, Uli; Lovell, J. E. J.; Ploetz, C.; et al. (Astronomy & Astrophysics, 2011)
Context. Centaurus A is the closest active galactic nucleus. High resolution imaging using Very Long Baseline Interferometry (VLBI) enables us to study the spectral and kinematic behavior of the radio jet-counterjet system on sub-parsec scales, providing essential information for jet emission and formation models.Aims. Our aim is to study the structure and spectral shape of the emission from the central-parsec region of Cen A.Methods. As a target of the Southern Hemisphere VLBI monitoring program TANAMI (Tracking Active Galactic Nuclei with Austral Milliarcsecond Interferometry), VLBI observations of Cen A are made regularly at 8.4 and 22.3 GHz with the Australian Long Baseline Array (LBA) and associated telescopes in Antarctica, Chile, and South Africa.Results. The first dual-frequency images of this source are presented along with the resulting spectral index map. An angular resolution of 0.4 mas x 0.7 mas is achieved at 8.4 GHz, corresponding to a linear scale of less than 0.013 pc. Hence, we obtain the highest resolution VLBI image of CenA, comparable to previous space-VLBI observations. By combining with the 22.3 GHz image, which has been taken without contributing transoceanic baselines at somewhat lower resolution, we present the corresponding dual-frequency spectral index distribution along the sub-parsec scale jet revealing the putative emission regions for recently detected gamma-rays from the core region by Fermi/LAT.Conclusions. We resolve the innermost structure of the milliarcsecond scale jet and counterjet system of CenA into discrete components. The simultaneous observations at two frequencies provide the highest resolved spectral index map of an AGN jet allowing us to identify multiple possible sites as the origin of the high energy emission.
Keywords: techniques: high angular resolution; galaxies: individual: Centaurus A; black hole physics; galaxies: active; galaxies: individual: NGC 5128; galaxies: jets

Dust and gas absorption in the high mass X-ray binary IGR J16318-4848 - Ballhausen, Ralf; Lorenz, Maximilian; Fuerst, Felix; Pottschmidt, Katja; Corrales, Lia; Tomsick, John A.; Kühnel, Matthias; Kretschmar, Peter; Kallman, Timothy R.; Grinberg, Victoria; Hell, Natalie; Psadaraki, Ioanna; et al. (Astronomy & Astrophysics, 2020)
Context. With an absorption column density on the order of 1024 cm-2, IGR J16318-4848 is one of the most extreme cases of a highly obscured high mass X-ray binary. In addition to the overall continuum absorption, the source spectrum exhibits a strong iron and nickel fluorescence line complex at 6.4 keV. Previous empirical modeling of these features and comparison with radiative transfer simulations raised questions about the structure and covering fraction of the absorber and the profile of the fluorescence lines. Aims. We aim at a self-consistent description of the continuum absorption, the absorption edges, and the fluorescence lines to constrain the properties of the absorbing material, such as ionization structure and geometry. We further investigate the effects of dust absorption on the observed spectra and the possibility of fluorescence emission from dust grains. Methods. We used XMM-Newton and NuSTAR spectra to first empirically constrain the incident continuum and fluorescence lines. Next we used XSTAR to construct a customized photoionization model where we vary the ionization parameter, column density, and covering fraction. In the third step we modeled the absorption and fluorescence in a dusty olivine absorber and employed both a simple analytical model for the fluorescence line emission and a Monte Carlo simulation of radiative transfer that generates line fluxes, which are very close to the observational data. Results. Our empirical spectral modeling is in agreement with previous works. Our second model, the single gas absorber does not describe the observational data. In particular, irrespective of the ionization state or column density of the absorber, a much higher covering fraction than previously estimated is needed to produce the strong fluorescence lines and the large continuum absorption. A dusty, spherical absorber (modeled as consisting of olivine dust, although the nature of dust cannot be constrained) is able to produce the observed continuum absorption and edges. Conclusions. A dense, dusty absorber in the direct vicinity of the source consisting of dust offers a consistent description of both the strong continuum absorption and the strong emission features in the X-ray spectrum of IGR J16318-4848. In particular, for low optical depth of individual grains, which is the case for typical volume densities and grain size distribution models, the dust will contribute significantly to the fluorescence emission.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Circumstellar matter; Dust; extinction; X-rays: binaries; X-rays: individuals: IGR J16318-4848

EC 22536-5304: a lead-rich and metal-poor long-period binary - Dorsch, Matti; Jeffery, C. S.; Irrgang, Andreas; Woolf, V.; Heber, Ulrich (Astronomy & Astrophysics, 2021)
Helium-burning hot subdwarf stars of spectral types O and B (sdO/B) are thought to be produced through various types of binary interactions. The helium-rich hot subdwarf star EC 22536-5304 was recently found to be extremely enriched in lead. Here, we show that EC 22536-5304 is a binary star with a metal-poor subdwarf F-type (sdF) companion. We performed a detailed analysis of high-resolution SALT/HRS and VLT/UVES spectra, deriving metal abundances for the hot subdwarf, as well as atmospheric parameters for both components. Because we consider the contribution of the sdF star, the derived lead abundance for the sdOB, + 6.3 +/- 0.3 dex relative to solar, is even higher than previously thought. We derive T-eff = 6210 +/- 70 K, log g = 4.64 +/- 0.10, [FE/H] = - 1.95 +/- 0.04, and [alpha/Fe] = + 0.40 +/- 0.04 for the sdF component. Radial velocity variations, although poorly sampled at present, indicate that the binary system has a long orbital period of about 457 days. This suggests that the system was likely formed through stable Roche lobe overflow (RLOF). A kinematic analysis shows that EC 22536-5304 is on an eccentric orbit around the Galactic centre. This, as well as the low metallicity and strong alpha enhancement of the sdF-type companion, indicate that EC 22536-5304 is part of the Galactic halo or metal-weak thick disc. As the first long-period hot subdwarf binary at [FE/H] less than or similar to- 1, EC 22536-5304 may help to constrain the RLOF mechanism for mass transfer from low-mass, low-metallicity red giant branch (RGB) stars to main-sequence companions.
CRIS-Team WoS Importer:2021-10-01

Eclipsing Binaries Found by the EREBOS Project: Gaia DR2 6097540197980557440-a Deeply Eclipsing sdB plus dM System - Corcoran, Kyle A.; Barlow, Brad N.; Schaffenroth, Veronika; Heber, Ulrich; Walser, Stephen; Irgang, Andreas (Astrophysical Journal, 2021)
We present time-series spectroscopy and photometry of Gaia DR2 6097540197980557440, a new deeply eclipsing hot subdwarf B (sdB) + M dwarf (dM) binary. We discovered this object during the course of the Eclipsing Reflection Effect Binaries from Optical Surveys (EREBOS) project, which aims to find new eclipsing sdB+dM binaries (HW Vir systems) and increase the small sample of studied systems. In addition to the primary eclipse, which is in excess of similar to 5 mag in the optical, the light curve also shows features typical for other HW Vir binaries such as a secondary eclipse and strong reflection effect from the irradiated, cool companion. The orbital period is 0.127037 days (similar to 3 hr), falling right at the peak of the orbital period distribution of known HW Vir systems. Analysis of our time-series spectroscopy yields a radial velocity semiamplitude of K (sdB) = 100.0 +/- 2.0 km s(-1), which is among the fastest line-of-sight velocities found to date for an HW Vir binary. State-of-the-art atmospheric models that account for deviations from local thermodynamic equilibrium are used to determine the atmospheric parameters of the sdB. Although we cannot claim a unique light-curve modeling solution, the best-fitting model has an sdB mass of M (sdB) = 0.47 +/- 0.03 M (circle dot) and a companion mass of M (dM) = 0.18 +/- 0.01 M (circle dot). The radius of the companion appears to be inflated relative to theoretical mass-radius relationships, consistent with other known HW Vir binaries. Additionally, the M dwarf is one of the most massive found to date among this type of binary.
CRIS-Team WoS Importer:2021-09-10

Editorial: Plasma, particles, and photons: ISM physics revisited - Sasaki, Manami; Dettmar, Ralf-Juergen; Tjus, Julia Becker (Astrophysics and Space Science, 2022)
CRIS-Team WoS Importer:2022-08-19

Effects of multiphase gas and projection on X-ray observables in simulated galaxy clusters as seen by eROSITA - Zuhone, J.; Bahar, Y. E.; Biffi, V.; Dolag, K.; Sanders, J.; Bulbul, E.; Liu, T.; Dauser, Thomas; König, Ole; Zhang, X.; Ghirardini, V. (Astronomy & Astrophysics, 2023)
Context. Galaxy clusters are the most massive bound objects in the recent history of the universe; the number density of galaxy clusters as a function of mass and redshift is a sensitive function of the cosmological parameters. To use clusters for cosmological parameter studies, it is necessary to determine their masses as accurately as possible, which is typically done via scaling relations between mass and observables. Aims. X-ray observables can be biased by a number of effects, including multiphase gas and projection effects, especially in the case where cluster temperatures and luminosities are estimated from single-model fits to all of the emission with an overdensity radius such as r500c. Using simulated galaxy clusters from a realistic cosmological simulation, our aim is to determine the importance of these biases in the context of Spectrum-Roentgen-Gamma/eROSITA observations of clusters. Methods. We extracted clusters from the Box2_hr simulation from the Magneticum suite, and simulated synthetic eROSITA observations of these clusters using PHOX to generate the photons and the end-to-end simulator SIXTE to trace them through the optics and simulate the detection process. We fitted the spectra from these observations and compared the fitted temperatures and luminosities to the quantities derived from the simulations. We fitted an intrinsically scattered LX - T scaling relation to these measurements following a Bayesian approach with which we fully took into account the selection effects and the mass function. Results. The largest biases on the estimated temperature and luminosities of the clusters come from the inadequacy of single-temperature model fits to represent emission from multiphase gas, and from a bias arising from cluster emission within the projected r500c along the line of sight but outside of the spherical r500c. We find that the biases on temperature and luminosity due to the projection of emission from other clusters within r500c is comparatively small. We find eROSITA-like measurements of Magneticum clusters following a LX - T scaling relation that has a broadly consistent but slightly shallower slope compared to the literature values. We also find that the intrinsic scatter of LX at given T is lower compared to the recent observational results where the selection effects are fully considered.
CRIS-Team Scopus Importer:2023-08-11
Keywords: Galaxies: clusters: intracluster medium; Methods: numerical; X-rays: galaxies: clusters

Einleitung: Unendlichkeit: Versuch einer asymptotischen Annäherung - Freiburg, Rudolf; Lubkoll, Christine; Schoberth, Wolfgang; Weth, Thomas; Wilms, Jörn; Leven, Karl-Heinz (Unendlichkeit: Erlanger Universitätstage Ansbach 2015, 2016)
Keywords: Unendlichkeit; Literatur; Alexander Pope; Edward Young; Thodizee; Gott; Ewigkeit; Zeit; Raum

EL CVn-type binaries - discovery of 17 helium white dwarf precursors in bright eclipsing binary star systems - Maxted, P. F. L.; Bloemen, S.; Heber, Ulrich; Geier, Stephan; Wheatley, P. J.; Marsh, T. R.; Breedt, E.; Sebastian, D.; Faillace, G.; Owen, Christopher; Pulley, D.; Smith, D.; et al. (Monthly Notices of the Royal Astronomical Society, 2013)
The star 1SWASP J024743.37-251549.2 was recently discovered to be a binary star in which an A-type dwarf star eclipses the remnant of a disrupted red giant star (WASP 0247-25 B). The remnant is in a rarely observed state evolving to higher effective temperatures at nearly constant luminosity prior to becoming a very low mass white dwarf composed almost entirely of helium, i.e. it is a pre-helium white dwarf (pre-He-WD). We have used the photometric database from theWide Angle Search for Planets (WASP) to find 17 eclipsing binary stars with orbital periods P = 0.7-2.2 d with similar light curves to 1SWASP J024743.37-251549.2. The only star in this group previously identified as a variable star is the brightest one, EL CVn, which we adopt as the prototype for this class of eclipsing binary star. The characteristic light curves of EL CVn-type stars show a total eclipse by an A-type dwarf star of a smaller, hotter star and a secondary eclipse of comparable depth to the primary eclipse. We have used new spectroscopic observations for six of these systems to confirm that the companions to the A-type stars in these binaries have very low masses (≈0.2M⊙). This includes the companion to EL CVn which was not previously known to be a pre-He-WD. EL CVn-type binary star systems will enable us to study the formation of very low mass white dwarfs in great detail, particularly in those cases where the pre-He-WD star shows non-radial pulsations similar to those recently discovered in WASP0247-25 B. © 2013 The Authors Published by Oxford University Press on behalf of the Royal Astronomical Society.
CRIS-Team Scopus Importer:2020-12-21
Keywords: Binaries: close; Binaries: eclipsing; Binaries: spectroscopic; Stars: individual: 1SWASP J024743.37-251549.2; Stars: individual: EL CVn.

EMU Detection of a Large and Low Surface Brightness Galactic SNR G288.8-6.3 - Filipović, Miroslav D.; Dai, Shi; Arbutina, Bojan; Hurley-Walker, Natasha; Brose, Robert; Becker, Werner; Sano, Hidetoshi; Urošević, Dejan; Jarrett, T. H.; Hopkins, Andrew M.; Alsaberi, Rami Z.E.; Alsulami, R.; et al. (Astronomical Journal, 2023)
We present the serendipitous detection of a new Galactic supernova remnant (SNR), G288.8-6.3, using data from the Australian Square Kilometre Array Pathfinder (ASKAP) Evolutionary Map of the Universe (EMU) survey. Using multifrequency analysis, we confirm this object as an evolved Galactic SNR at high Galactic latitude with low radio surface brightness and typical SNR spectral index of α = − 0.41 ± 0.12. To determine the magnetic field strength in SNR G288.8-6.3, we present the first derivation of the equipartition formulae for SNRs with spectral indices α > − 0.5. The angular size is 1.°8 × 1.°6 (107.′6 × 98.′4), and we estimate that its intrinsic size is ∼40 pc, which implies a distance of ∼1.3 kpc and a position of ∼140 pc above the Galactic plane. This is one of the largest in angular size and closest Galactic SNRs. Given its low radio surface brightness, we suggest that it is about 13,000 yr old.
CRIS-Team Scopus Importer:2023-09-22

EPIC 216747137: A new HW Vir eclipsing binary with a massive sdOB primary and a low-mass M-dwarf companion - Silvotti, R.; Schaffenroth,; Heber, Ulrich; Ostensen, R. H.; Telting, J. H.; Vos, J.; Kilkenny, D.; Mancini, L.; Ciceri, S.; Irrgang, Andreas; Drechsel, Horst (Monthly Notices of the Royal Astronomical Society, 2021)
EPIC 216747137 is a new HW Virginis system discovered by the Kepler spacecraft during its K2 'second life'. Like the other HW Vir systems, EPIC 216747137 is a post-common-envelope eclipsing binary consisting of a hot subluminous star and a cool low-mass companion. The short orbital period of 3.87 h produces a strong reflection effect from the secondary (∼9 per cent in the R band). Together with AA Dor and V1828 Aql, EPIC 216747137 belongs to a small subgroup of HW Vir systems with a hot evolved sdOB primary. We find the following atmospheric parameters for the hot component: Teff = 40400 ± 1000 K, log g = 5.56 ± 0.06, and log(N(He)/N(H)) =-2.59 ± 0.05. The sdOB rotational velocity v sin i = 51 ± 10 km s-1 implies that the stellar rotation is slower than the orbital revolution and the system is not synchronized. When we combine photometric and spectroscopic results with the Gaia parallax, the best solution for the system corresponds to a primary with a mass of about 0.62 M close to, and likely beyond, the central helium exhaustion, while the cool M-dwarf companion has a mass of about 0.11 M.
CRIS-Team Scopus Importer:2021-02-05
Keywords: binaries: eclipsing; stars: horizontal branch; stars: individual: EPIC 216747137

ERASSt J040515.6-745202, an X-ray burster in the Magellanic Bridge - Haberl, F.; Vasilopoulos, G.; Maitra, C.; Valdes, F.; Lang, D.; Doroshenko, V.; Ducci, L.; Kreykenbohm, Ingo; Rau, A.; Weber, Philipp; Wilms, Jörn; Maggi, P.; et al. (Astronomy & Astrophysics, 2023)
Context. During the third all-sky survey (eRASS3), eROSITA, the soft X-ray instrument aboard Spectrum-Roentgen-Gamma, detected a new hard X-ray transient, eRASSt J040515.6-745202, in the direction of the Magellanic Bridge. Aims. We arranged follow-up observations and searched for archival data to reveal the nature of the transient. Methods. Using X-ray observations with XMM-Newton, NICER, and Swift, we investigated the temporal and spectral behaviour of the source for over about 10 days. Results. The X-ray light curve obtained from the XMM-Newton observation with an ∼28 ks exposure revealed a type-I X-ray burst with a peak bolometric luminosity of at least 1.4×1037 erg s-1. The burst energetics are consistent with a location of the burster at the distance of the Magellanic Bridge. The relatively long exponential decay time of the burst of ∼70 s indicates that it ignited in a H-rich environment. The non-detection of the source during the other eROSITA surveys, twelve and six months before and six months after eRASS3, suggests that the burst was discovered during a moderate outburst which reached 2.6×1036 erg s-1 in persistent emission. During the NICER observations, the source showed alternating flux states with the high level at a similar brightness as during the XMM-Newton observation. This behaviour is likely caused by dips as also seen during the last hour of the XMM-Newton observation. Evidence for a recurrence of the dips with a period of ∼21.8 h suggests eRASSt J040515.6-745202 is a low-mass X-ray binary (LMXB) system with an accretion disk seen nearly edge on.We identify a multi-wavelength counterpart to the X-ray source in UVW1 and g; r; i, and z images obtained by the optical/UV monitor on XMM-Newton and the Dark Energy Camera at the Cerro Tololo Inter-American Observatory. The spectral energy distribution is consistent with radiation from an accretion disk which dominates the UV and from a cool late-type star detected in the optical to infrared wavelengths. Conclusions. After the discovery of X-ray bursts inM31, the Magellanic Bridge is only the second location outside of the MilkyWay where an X-ray burster was found. The burst uniquely identifies eRASSt J040515.6-745202 as an LMXB system with a neutron star. Its location in the Magellanic Bridge confirms the existence of an older stellar population which is expected if the bridge was formed by tidal interactions between the Magellanic Clouds, which stripped gas and stars from the clouds.
CRIS-Team Scopus Importer:2023-01-27
Keywords: Magellanic Clouds; Stars: mass-loss; Stars: neutron; X-rays: binaries; X-rays: bursts; X-rays: individuals: eRASSt J040515.6-745202

eROSITA calibration and performance verification phase: High-mass X-ray binaries in the Magellanic Clouds - Haberl, F.; Maitra, C.; Carpano, S.; Dai, X.; Doroshenko,; Dennerl, K.; Freyberg, M. J.; Sasaki, Manami; Udalski, A.; Postnov, K. A.; Shakura, N. (Astronomy & Astrophysics, 2022)
Context. During its performance verification phase, the soft X-ray instrument eROSITA on board the Spektrum-Roentgen-Gamma (SRG) spacecraft observed large regions in the Magellanic Clouds in which almost 40 known high-mass X-ray binaries (HMXBs, including candidates) are located.
CRIS-Team WoS Importer:2022-06-17

eROSITA detection of flares from the Be/X-ray binary A0538-66 - Ducci, L.; Mereghetti, S.; Santangelo, A.; Ji, L.; Carpano, S.; Covino, S.; Doroshenko,; Haberl, F.; Maitra, C.; Kreykenbohm, Ingo; Udalski, A. (Astronomy & Astrophysics, 2022)
In 2018, XMM-Newton observed the awakening in X-rays of the Be/X-ray binary (Be/XRB) A0538-66. It showed bright and fast flares close to periastron with properties that had never been observed in other Be/XRBs before. We report the results from the observations of A0538-66 collected during the first all-sky survey of eROSITA, an X-ray telescope (0.2-10 keV) on board the Spektrum-RoentgenGamma satellite. eROSITA caught two flares within one orbital cycle at orbital phases phi = 0.29 and phi = 0.93 (where phi = 0 corresponds to periastron), with peak luminosities of similar to 2-4 x 10(36) erg s(-1) (0.2-10 keV) and durations of 42 <= Delta t(fl) <= 5.7 x 10(4) s. The flare observed at phi approximate to 0.29 shows that the neutron star can accrete considerably far from periastron, although it is expected to be outside of the circumstellar disk, thus providing important new information about the plasma environment surrounding the binary system. We also report the results from the photometric monitoring of A0538-66 carried out with the REM, OGLE, and MACHO telescopes from January 1993 until March 2020. We found that the two sharp peaks that characterize the orbital modulation in the optical occur asymmetrically in the orbit, relative to the position of the donor star.
CRIS-Team WoS Importer:2022-06-17
Keywords: accretion; accretion disks; stars: neutron; X-rays: binaries; X-rays: individuals: 1A 0538-66

eROSITA ground operations - Brunner, H.; Boller, T.; Coutinho, D.; Dauser, Thomas; Dennerl, K.; Dwelly, T.; Freyberg, M.; Fuermetz, M.; Georgakakis, A.; Grossberger, C.; Kreykenbohm, Ingo; Lamer, G.; et al. (2018)
eROSITA (extended ROentgen Survey with an Imaging Telescope Array) is the primary instrument on-board the Russian/German "Spectrum-Roentgen-Gamma"(SRG) mission. It will perform the first all-sky imaging X-ray survey in the medium X-ray energy band. eROSITA is currently awaiting its launch from Baikonur in early 2019 into an L2 halo orbit. Preparations for eROSITA ground operations have been under way in parallel with the hardware development of the eROSITA telescope, comprising the areas mission planning, telescope operation and data reception, the operation of a data processing pipeline, and the creation of tools for data access and interactive data analysis. eROSITA mission: After a brief calibration and performance verification phase eROSITA will perform a four-year all-sky survey fully covering the sky eight times, which will be followed by several years of dedicated observations of interesting objects. Two ground antennas in Russia (near Moscow and in Siberia) will be available to provide several hours of daily ground contact for commanding and for data reception. eROSITA data rights will be equally divided between the Russian and German partners. Operation and data centers will exist at Max-Planck-Institut fur extraterrestrische Physics (MPE) in Garching, Germany and at the Russian Space Research Institute (IKI) in Moscow. Interfaces and procedures for mission planning, telescope operation and data exchange are closely coordinated between both sites. Mission planning and operation: Based on orbit simulations provided by the Russian side, a software environment for optimizing the desired sky coverage and observing efficiency while fulfilling visibility and solar constraints was set up. Agreed upon observing timelines will be converted to eROSITA and SRG command sequences fed to the Russian ground station for up-linking. MPE personnel will be on site either in Moscow or at MPE in Garching during each ground contact to conduct on-demand commanding and to assess instrument health and data quality. Data analysis pipeline and interactive data analysis: The eROSITA data processing pipeline consists of modules for data ingestion, event calibration, exposure calculation, source detection, and the creation of high-level source specific data products. It will be operated at MPE on a daily basis after each ground contact. A subset of the software tasks comprising the data analysis pipeline also functions as interactive data analysis tools. These can be grouped into tasks for X-ray event calibration, selection and binning, exposure, background and sensitivity map creation and for source detection. Data products are provided in a standards compliant FITS format for use with well-known high-level X-ray data analysis tools. A Web based graphical source catalog and data products viewer will allow easy data browsing. Since mid-2014 the interactive eROSITA data analysis package is available to the eROSITA user community, permitting the analysis of simulated eROSITA datasets, created by a sophisticated X-ray modeling and simulation tool.
Keywords: eROSITA; SRG; Spectrum-Roentgen-Gamma; X-ray telescope; space telescope; all-sky survey; astrophysics; ground segment

EROSITA on SRG - Predehl, Peter; Andritschke, Robert; Babyshkin, Vladimir; Becker, Werner; Bornemann, Walter; Bräuninger, Heinrich; Brunner, Hermann; Boller, Thomas; Burwitz, Vadim; Burkert, Wolfgang; Clerc, Nicolas; Churazov, Eugene; et al. (Space Telescopes and Instrumentation 2016: Ultraviolet to Gamma Ray, 2016)
eROSITA (extended ROentgen Survey with an Imaging Telescope Array) is the core instrument on the Russian/German Spektrum-Roentgen-Gamma (SRG) mission which is now officially scheduled for launch on September 2017, eROSITA will perform a deep survey of the entire X-ray sky. Within the first 4 years of the mission the sky will be scanned 8 times. In the soft band (0.5-2 keV), it will be about 30 times more sensitive than ROSAT, while in the hard band (2-8 keV) it will provide the first ever true imaging survey of the sky. eROSITA is currently (June 2016) in its final integration and test phase. All seven FM Mirror Assemblies and Camera Assemblies (+ 1 spare) have been tested and calibrated. All subsystems and components are well within their expected performances.
Keywords: eROSITA; X-ray astronomy; X-ray optics; X-ray telescopes; X-ray testing

EROSITA study of the globular cluster 47 Tucanae - Saeedi, Sara; Liu, Teng; Knies, Jonathan; Sasaki, Manami; Becker, Werner; Bulbul, Esra; Dennerl, Konrad; Freyberg, Michael; Laktionov, Roman; Merloni, Andrea (Astronomy & Astrophysics, 2022)
Aims. We present the results of the analysis of five observations of the globular clutser 47 Tucanae (47 Tuc) with the extended Roentgen Survey with an Imaging Telescope Array (eROSITA) on board the Spektrum-Roentgen-Gamma (Spektr-RG, SRG). We study the X-ray population in the field of one of the most massive globular clusters in our Milky Way. We focused on the classification of point-like sources in the field of 47 Tuc. The unresolved dense core of 47 Tuc (1.7 radius) and also sources that show extended emission are excluded from this study. Methods. We applied different methods of X-ray spectral and timing analysis together with multi-wavelength studies to classify the X-rays sources in the field of 47 Tuc. Results. We detected 888 point-like sources in the energy range of 0.2a-5.0 keV. We identified 126 background active galactic nuclei and 25 foreground stars. One of the foreground stars is classified as a variable M dwarf. We also classified 14 X-ray sources as members of 47 Tuc, including one symbiotic star, two quiescent low-mass X-ray binaries, and four cataclysmic variables. There are also five X-ray sources that can either be a cataclysmic variable or a contact binary, and also one X-ray source can be an active binary (type RS CVn). We identified one X-ray binary that belongs to the Small Magellanic Cloud. Moreover, we calculated the X-ray luminosity function of 47 Tuc. No significant population that seems to belong to the globular cluster is observed in the energy range of 0.5-2.0 keV using eROSITA observations.
CRIS-Team Scopus Importer:2022-06-10
Keywords: Binaries: Symbiotic; Globular clusters: General; Novae; cataclysmic variables; X-rays: Binaries

Erratum: The impact of precession on the observed population of ULXs (MNRAS (2023) 522 (5654) DOI: 10.1093/mnras/stab3049) - Khan, Norman; Middleton, Matthew J.; Wiktorowicz, Grzegorz; Dauser, Thomas; Roberts, Timothy P.; Wilms, Jörn (Monthly Notices of the Royal Astronomical Society, 2023)
This is a correction to the paper 'The impact of precession on the observed population of ULXs', published in MNRAS, 509 (2), 2493-2506 (2022). In our paper, we incorrectly reported the neutron star spin to have a value of a∗ = 0.01 when in fact we used a value of a∗ = 0.0005, in accordance with the known spin period of ULX pulsars (P = 1 s) and canonical values for the NS systems (M = 1.4 × 2 × 1033 g and I = 1045 g cm−2). This does not affect any results in the paper.
CRIS-Team Scopus Importer:2023-06-23

Erratum to “Results from the search for dark matter in the Milky Way with 9 years of data of the ANTARES neutrino telescope” [Phys. Lett. B 769 (2017)249–254](S037026931730254X)(10.1016/j.physletb.2017.03.063) - Albert, A.; André, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. J.; Avgitas, T.; Baret, B.; Barrios-Martí, J.; Basa, S.; Bertin, V.; Biagi, S.; et al. (Physics Letters B, 2019)
Limits on the neutrino flux for a given mass [Formula presented] and annihilation channel are calculated as in Eq. (7)(page 252), with the integrated acceptances defined in Eq. (8)(page 252)as the effective area averaged over the neutrino energy. A numerical approximation of WIMP annihilation spectra, adapted from [1]with a too coarse binning, led to an overestimation of the integrated acceptances for dark-matter induced neutrino events. The spectra were replaced with a fine-binned version both in the likelihood and in the acceptances. The main change is a weaker limit for WIMP masses larger than 1 TeV/ [Formula presented]. Updated versions of Figs. 3–6 are provided.
CRIS-Team Scopus Importer:2019-06-04

Establishing the X-ray source detection strategy for eROSITA with simulations - Liu, Teng; Merloni, Andrea; Comparat, Johan; Nandra, Kirpal; Sanders, Jeremy; Lamer, Georg; Buchner, Johannes; Dwelly, Tom; Freyberg, Michael; Malyali, Adam; Georgakakis, Antonis; Salvato, Mara; et al. (Astronomy & Astrophysics, 2022)
Context. The eROSITA X-ray telescope on board the Spectrum-Roentgen-Gamma satellite has started to detect new X-ray sources over the full sky at an unprecedented rate. Understanding the performance and selection function of the source detection is important for the subsequent scientific analysis of the eROSITA catalogs. Aims. Through simulations, we test and optimize the eROSITA source detection procedures, and we characterize the detected catalog quantitatively. Methods. Taking the eROSITA Final Equatorial-Depth Survey (eFEDS) as an example, we ran extensive photon-event simulations based on our best knowledge of the instrument characteristics, the background spectrum, and the population of astronomical X-ray sources. We introduce a method of analyzing source detection completeness, purity, and efficiency based on the origin of each photon. Results. According to the source detection efficiency measured in the simulation, we chose a two-pronged strategy to build eROSITA X-ray catalogs, creating a main catalog using only the most sensitive band (0.2-2.3 keV) and an independent hard-band-selected catalog using multiband detection in a range up to 5 keV. Because our mock data are highly representative of the real eFEDS data, we used the mock catalogs to measure the completeness and purity of the eFEDS catalogs as a function of multiple parameters, such as detection likelihood, flux, and luminosity. These measurements provide a basis for choosing the eFEDS catalog selection thresholds. The mock catalogs (available with this paper) can be used to construct the selection function of active galactic nuclei and galaxy clusters. A direct comparison of the output and input mock catalogs also gives rise to a correction curve that converts the raw point-source flux distribution into the intrinsic number counts distribution.
CRIS-Team WoS Importer:2022-06-17

EUSO-SPB1 mission and science - Abdellaoui, G.; Abe, S.; Adams, J. H.; Allard, D.; Alonso, G.; Anchordoqui, L.; Anzalone, A.; Arnone, E.; Asano, K.; Attallah, R.; Attoui, H.; Pernas, M. Ave; et al. (Astroparticle Physics, 2024)
The Extreme Universe Space Observatory on a Super Pressure Balloon 1 (EUSO-SPB1) was launched in 2017 April from Wanaka, New Zealand. The plan of this mission of opportunity on a NASA super pressure balloon test flight was to circle the southern hemisphere. The primary scientific goal was to make the first observations of ultra-high-energy cosmic-ray extensive air showers (EASs) by looking down on the atmosphere with an ultraviolet (UV) fluorescence telescope from suborbital altitude (33 km). After 12 days and 4 h aloft, the flight was terminated prematurely in the Pacific Ocean. Before the flight, the instrument was tested extensively in the West Desert of Utah, USA, with UV point sources and lasers. The test results indicated that the instrument had sensitivity to EASs of ⪆3 EeV. Simulations of the telescope system, telescope on time, and realized flight trajectory predicted an observation of about 1 event assuming clear sky conditions. The effects of high clouds were estimated to reduce this value by approximately a factor of 2. A manual search and a machine-learning-based search did not find any EAS signals in these data. Here we review the EUSO-SPB1 instrument and flight and the EAS search.
CRIS-Team Scopus Importer:2023-09-22
Keywords: Air fluorescence; Cosmic rays (329); Extensive air showers; High-altitude balloons (738); JEM-EUSO

EUSO-TA - First results from a ground-based EUSO telescope - Abdellaoui, G.; Abe, S.; Adams, J. H.; Ahriche, A.; Allard, D.; Allen, L.; Alonso, G.; Anchordoqui, L.; Anzalone, A.; Arai, Y.; Asano, K.; Attallah, R.; et al. (Astroparticle Physics, 2018)
EUSO-TA is a ground-based telescope, installed at the Telescope Array (TA) site in Black Rock Mesa, Utah, USA. This is the first detector to successfully use a Fresnel lens based optical system and multi-anode photomultipliers (64 channels per tube, 2304 channels encompassing a 10.6 degrees x 10.6 degrees field of view) for detection of Ultra High Energy Cosmic Rays (UHECR). The telescope is located in front of one of the fluorescence detectors of the TA experiment. Since its installation in 2013, the detector has observed several ultra-high energy cosmic ray events and, in addition, meteors. The limiting magnitude of 5.5 on summed frames (similar to 3 ms) has been established. Measurements of the UV night sky emission in different conditions and moon phases and positions have been completed. The performed observations serve as a proof of concept for the future application of this detector technology. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: UHECR; EAS; JEM-EUSO; cosmic rays; Fresnel lens

Event reconstruction for KM3NeT/ORCA using convolutional neural networks - Aiello, S.; Albert, A.; Garre, S. Alves; Aly, Z.; Ameli, F.; Andre, M.; Androulakis, G.; Anghinolfi, M.; Anguita, M.; Anton, Gisela; Ardid, M.; Aublin, J.; et al. (Journal of Instrumentation, 2020)
The KM3NeT research infrastructure is currently under construction at two locations in the Mediterranean Sea. The KM3NeT/ORCA water-Cherenkov neutrino detector off the French coast will instrument several megatons of seawater with photosensors. Its main objective is the determination of the neutrino mass ordering. This work aims at demonstrating the general applicability of deep convolutional neural networks to neutrino telescopes, using simulated datasets for the KM3NeT/ORCA detector as an example. To this end, the networks are employed to achieve reconstruction and classification tasks that constitute an alternative to the analysis pipeline presented for KM3NeT/ORCA in the KM3NeT Letter of Intent. They are used to infer event reconstruction estimates for the energy, the direction, and the interaction point of incident neutrinos. The spatial distribution of Cherenkov light generated by charged particles induced in neutrino interactions is classified as shower- or track-like, and the main background processes associated with the detection of atmospheric neutrinos are recognized. Performance comparisons to machine-learning classification and maximum-likelihood reconstruction algorithms previously developed for KM3NeT/ORCA are provided. It is shown that this application of deep convolutional neural networks to simulated datasets for a large-volume neutrino telescope yields competitive reconstruction results and performance improvements with respect to classical approaches.
CRIS-Team WoS Importer:2020-10-30

Evidence for an evolving cyclotron line energy in 4U 1538-522 - Hemphill, Paul B.; Rothschild, Richard E.; Furst, Felix; Grinberg, Victoria; Klochkov, Dmitry; Kretschmar, Peter; Pottschmidt, Katja; Staubert, Ruediger; Wilms, Jörn (Monthly Notices of the Royal Astronomical Society, 2016)
We have performed a full time and luminosity-resolved spectral analysis of the high-mass X-ray binary 4U 1538-522 using the available RXTE, INTEGRAL, and Suzaku data, examining both phase-averaged and pulse-phase-constrained data sets and focusing on the behaviour of the cyclotron resonance scattering feature (CRSF). No statistically significant trend between the energy of the CRSF and luminosity is observed in the combined data set. However, the CRSF energy appears to have increased by 1.5 keV in the 8.5 yr between the RXTE and Suzaku measurements, with Monte Carlo simulations finding the Suzaku measurement 4.6σ above the RXTE points. Interestingly, the increased Suzaku CRSF energy is much more significant and robust in the pulse-phase-constrained spectra from the peak of the main pulse, suggesting a change that is limited to a single magnetic pole. The seven years of RXTE measurements do not show any strongly significant evolution with time on their own. We discuss the significance of the CRSF's behaviour with respect to luminosity and time in the context of historical observations of this source as well as recent observational and theoretical work concerning the neutron star accretion column, and suggest some mechanisms by which the observed change over time could occur.
Keywords: Accretion; accretion discs; Pulsars: Individual: 4U 1538-522; Stars: Magnetic field; X-rays: Binaries; X-rays: Stars

Evidence for different accretion regimes in GRO J1008-57 - Kühnel, Matthias; Furst, Felix; Pottschmidt, Katja; Kreykenbohm, Ingo; Ballhausen, Ralf; Falkner, Sebastian; Rothschild, Richard E.; Klochkov, Dmitry; Wilms, Jörn (Astronomy & Astrophysics, 2017)
We present a comprehensive spectral analysis of the BeXRB GRO J1008-57 over a luminosity range of three orders of magnitude using NuSTAR, Suzaku, and RXTE data. We find significant evolution of the spectral parameters with luminosity. In particular, the photon index hardens with increasing luminosity at intermediate luminosities in the range 10(36)-10(37) erg s(-1). This evolution is stable and repeatedly observed over different outbursts. However, at the extreme ends of the observed luminosity range, we find that the correlation breaks down, with a significance level of at least 3.7 sigma. We conclude that these changes indicate transitions to different accretion regimes, which are characterized by different deceleration processes, such as Coulomb or radiation breaking. We compare our observed luminosity levels of these transitions to theoretical predications and discuss the variation of those theoretical luminosity values with fundamental neutron star parameters. Finally, we present detailed spectroscopy of the unique "triple peaked" outburst in 2014/15 which does not fit in the general parameter evolution with luminosity. The pulse profile on the other hand is consistent with what is expected at this luminosity level, arguing against a change in accretion geometry. In summary, GRO J1008-57 is an ideal target to study different accretion regimes due to the well-constrained evolution of its broad-band spectral continuum over several orders of magnitude in luminosity.
Keywords: X-rays: binaries; stars: neutron; stars: emission-line; Be; pulsars: individual: GRO J1008-57

Evidence for shocked molecular gas in the Galactic supernova remnant CTB 109 (G109.1-1.0) - Sasaki, Manami; Kothes, Roland; Plucinsky, Paul P.; Gaetz, Terrance J.; Brunt, Christopher (Astrophysical Journal, 2006)
We report the detection of molecular clouds around the X-ray-bright interior feature in the Galactic supernova remnant (SNR) CTB 109 (G109.1-1.0). This feature, called the "lobe," has been previously suggested to be the result of an interaction of the SNR shock wave with a molecular cloud complex. We present new high-resolution X-ray data from the Chandra X-Ray Observatory and new high-resolution CO data from the Five College Radio Astronomy Observatory that show the region of interaction with the cloud complex in greater detail. The CO data reveal three clouds around the lobe in the velocity interval. The velocity -57 km s(-1) < v < -52 km s(-1) profiles of (CO)-C-12 in various parts of the east cloud are well fit with a Gaussian; however, at the position at which the CO cloud and the lobe overlap, the velocity profile has an additional component toward higher negative velocities. The molecular hydrogen density in this part of the cloud is relatively high (N-H2 approximate to 1.9 x 10(20) cm(-2)), whereas the foreground absorption in X-rays (NH approximate to 4.5 x 10(21) cm(-2)), obtained from Chandra data, is lower than in other parts of the cloud and in the north and south clouds. These results indicate that the east cloud has been hit by the SNR blast wave on the western side, forming the bright X- ray lobe.
Keywords: ISM : clouds; shock waves; supernova remnants; X-rays : individual (CTB 109)

Evidence for γ-ray emission from the remnant of Kepleras supernova based on deep H.E.S.S. observations - Aharonian, F.; Benkhali, F. Ait; Angüner, E. O.; Ashkar, H.; Backes, M.; Martins, V. Barbosa; Batzofin, R.; Becherini, Y.; Berge, D.; Bernlöhr, K.; Böttcher, M.; Boisson, C.; et al. (Astronomy & Astrophysics, 2022)
Observations with imaging atmospheric Cherenkov telescopes (IACTs) have enhanced our knowledge of nearby supernova (SN) remnants with ages younger than 500 yr by establishing Cassiopeia A and the remnant of Tychoas SN as very-high-energy (VHE) ?-ray sources. The remnant of Kepleras SN, which is the product of the most recent naked-eye SN in our Galaxy, is comparable in age to the other two, but is significantly more distant. If the ?-ray luminosities of the remnants of Tychoas and Kepleras SNe are similar, then the latter is expected to be one of the faintest ?-ray sources within reach of the current generation IACT arrays. Here we report evidence at a statistical level of 4.6? for a VHE signal from the remnant of Kepleras SN based on deep observations by the High Energy Stereoscopic System (H.E.S.S.) with an exposure of 152 h. The measured integral flux above an energy of 226 GeV is ?0.3% of the flux of the Crab Nebula. The spectral energy distribution (SED) reveals a ?-ray emitting component connecting the VHE emission observed with H.E.S.S.To the emission observed at GeV energies with Fermi-LAT. The overall SED is similar to that of the remnant of Tychoas SN, possibly indicating the same nonthermal emission processes acting in both these young remnants of thermonuclear SNe.
CRIS-Team Scopus Importer:2022-07-15
Keywords: Gamma rays: General; Ism: Supernova remnants; Radiation mechanisms: Non-Thermal; Supernovae: Individual: Kepler

Evolution of a Relativistic Outflow and X-Ray Corona in the Extreme Changing-look AGN 1ES 1927+654 - Masterson, Megan; Kara, Erin; Ricci, Claudio; Garcia, Javier; Fabian, Andrew C.; Pinto, Ciro; Kosec, Peter; Remillard, Ronald A.; Loewenstein, Michael; Trakhtenbrot, Benny; Arcavi, Iair (Astrophysical Journal, 2022)
1ES 1927+654 is a paradigm-defying active galactic nucleus (AGN) and one of the most peculiar X-ray nuclear transients. In early 2018, this well-known AGN underwent a changing-look event, in which broad optical emission lines appeared and the optical flux increased. Yet, by 2018 July, the X-ray flux had dropped by over two orders of magnitude, indicating a dramatic change in the inner accretion flow. With three years of observations with NICER, XMM-Newton, and NuSTAR, we present the X-ray evolution of 1ES 1927+654, which can be broken down into three phases: (1) an early super-Eddington phase with rapid variability in X-ray luminosity and spectral parameters, (2) a stable super-Eddington phase at the peak X-ray luminosity, and (3) a steady decline back to the pre-outburst luminosity and spectral parameters. For the first time, we witnessed the formation of the X-ray corona, as the X-ray spectrum transitioned from thermally dominated to primarily Comptonized. We also track the evolution of the prominent, broad 1 keV feature in the early X-ray spectra and show that this feature can be modeled with blueshifted reflection (z = -0.33) from a single-temperature blackbody irradiating spectrum using xillverTDE, a new flavor of the xillver models. Thus, we propose that the 1 keV feature could arise from reflected emission off the base of an optically thick outflow from a geometrically thick, super-Eddington inner accretion flow, connecting the inner accretion flow with outflows launched during extreme accretion events (e.g., tidal disruption events). Lastly, we compare 1ES 1927+654 to other nuclear transients and discuss applications of xillverTDE to super-Eddington accretors.
CRIS-Team WoS Importer:2022-08-05

Evolution of the Accretion Disk-Corona during the Bright Hard-to-soft State Transition: A Reflection Spectroscopic Study with GX 339-4 - Sridhar, Navin; Garcia, Javier; Steiner, James F.; Connors, Riley M. T.; Grinberg, Victoria; Harrison, Fiona A. (Astrophysical Journal, 2020)
We present the analysis of several observations of the black hole binary GX 339-4 during its bright intermediate states from two different outbursts (2002 and 2004), as observed by the RXTE/Proportional Counter Array. We perform a consistent study of its reflection spectrum by employing the relxill family of relativistic reflection models to probe the evolutionary properties of the accretion disk including the inner disk radius (R in), ionization parameter (ξ), temperatures of the inner disk (T in), corona (kT e), and its optical depth (τ). Our analysis indicates that the disk inner edge approaches the innermost stable circular orbit during the early onset of the bright hard state, and that the truncation radius of the disk remains low (<9 R g) throughout the transition from hard to soft state. This suggests that the changes observed in the accretion disk properties during the state transition are driven by variation in accretion rate, and not necessarily due to changes in the inner disk's radius. We compare the aforementioned disk properties in two different outbursts with state transitions occurring at dissimilar luminosities and find identical evolutionary trends in the disk properties, with differences only seen in the corona's kT e and τ. We also perform an analysis by employing a self-consistent Comptonized accretion disk model accounting for the scatter of disk photons by the corona, and measure the low inner disk truncation radius across the bright intermediate states, using the temperature-dependent values of the spectral hardening factor, thereby independently confirming our results from the reflection analysis.
CRIS-Team Scopus Importer:2021-04-19

EVR-CB-004: An Inflated Hot Subdwarf O Star plus Unseen WD Companion in a Compact Binary Discovered with the Evryscope - Ratzloff, Jeffrey K.; Kupfer, Thomas; Barlow, Brad N.; Schneider, David; Marsh, Thomas R.; Heber, Ulrich; Corcoran, Kyle A.; Bauer, Evan; Hämmerich, Steven; Corbett, Henry T.; Glazier, Amy; Howard, Ward S.; et al. (Astrophysical Journal, 2020)
We present the discovery of EVR-CB-004, a close binary with a remnant stellar core and an unseen white dwarf (WD) companion. The analysis in this work reveals that the primary is potentially an inflated hot subdwarf (sdO) and more likely is a rarer post-blue horizontal branch (post-BHB) star. Post-BHBs are the short-lived shell-burning final stage of a blue horizontal star or hot subdwarf before transitioning to a WD. This object was discovered using Evryscope photometric data in a southern all-sky hot subdwarf variability survey. The photometric light curve for EVR-CB-004 shows multicomponent variability from ellipsoidal deformation of the primary and Doppler boosting, as well as gravitational limb darkening. The binary EVR-CB-004 is one of just a handful of known systems and has a long period (6.08426 hr) and large-amplitude ellipsoidal modulation (16.0% change in brightness from maximum to minimum) for these extremely close binary systems, while the properties of the primary make it a truly unique system. It also shows a peculiar low-amplitude (less than 1%) sinusoidal light-curve variation with a period that is a 1/3 resonance of the binary period. We tentatively identify this additional variation source as a tidally induced resonant pulsation, and we suggest follow-up observations that could verify this interpretation. From the evolutionary state of the system, its components, and its mass fraction, EVR-CB-004 is a strong merger candidate to form a single high-mass (1.2M) WD. It offers a glimpse into a brief phase of remnant core evolution and secondary variation not seen before in a compact binary.
CRIS-Team WoS Importer:2020-10-30

Expansion cone for the 3-inch PMTs of the KM3NeT optical modules - Adrian-Martinez, S.; Ageron, M.; Aguilar, J. A.; Aharonian, F.; Aiello, S.; Albert, A.; Alexandri, M.; Ameli, F.; Anassontzis, E. G.; Anghinolfi, M.; Anton, Gisela; Anvar, S.; et al. (Journal of Instrumentation, 2013)
Detection of high-energy neutrinos from distant astrophysical sources will open a new window on the Universe. The detection principle exploits the measurement of Cherenkov light emitted by charged particles resulting from neutrino interactions in the matter containing the telescope. A novel multi-PMT digital optical module (DOM) was developed to contain 31 3-inch photomultiplier tubes (PMTs). In order to maximize the detector sensitivity, each PMT will be surrounded by an expansion cone which collects photons that would otherwise miss the photocathode. Results for various angles of incidence with respect to the PMT surface indicate an increase in collection efficiency by 30% on average for angles up to 45 degrees with respect to the perpendicular. Ray-tracing calculations could reproduce the measurements, allowing to estimate an increase in the overall photocathode sensitivity, integrated over all angles of incidence, by 27% (for a single PMT). Prototype DOMs, being built by the KM3NeT consortium, will be equipped with these expansion cones.
Keywords: Optical detector readout concepts; Instrument optimisation; Cherenkov detectors; Large detector systems for particle and astroparticle physics

Explaining the asymmetric line profile in Cepheus X-4 with spectral variation across pulse phase - Bhargava, Yash; Bhalerao, Varun; Ballhausen, Ralf; Furst, Felix; Pottschmidt, Katja; Tomsick, John A.; Wilms, Jörn (Monthly Notices of the Royal Astronomical Society, 2019)
The high mass X-ray binary Cepheus X-4, during its 2014 outburst, showed evidence for an asymmetric cyclotron line in its hard X-ray spectrum. The 2014 spectrum provides one of the clearest cases of an asymmetric line profile among all studied sources with Cyclotron Resonance Scattering Features (CRSF). We present a phase-resolved analysis of NuSTAR and Suzaku data taken at the peak and during the decline phases of this outburst. We find that the pulse-phased resolved spectra are well-fit by a single, symmetric cyclotron feature. The fit parameters vary strongly with pulse phase: most notably the central energy and depth of the cyclotron feature, the slope of the power-law component, and the absorbing column density. We synthesise a 'phase averaged' spectrum using the best-fitting parameters for these individual pulse phases, and find that this combined model spectrum has a similar asymmetry in the cyclotron features as discovered in phase-averaged data. We conclude that the pulse phase resolved analysis with simple symmetric line profiles when combined can explain the asymmetry detected in the phase-averaged data.
Keywords: accretion; accretion discs; stars: neutron; X-rays: binaries; X-rays: individual (Cep X-4)

Extended VHE gamma-ray emission towards SGR1806-20, LBV 1806-20, and stellar cluster Cl*1806-20 - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E. O.; Arrieta, M.; Aubert, P.; Backes, M.; Balzer, A.; Barnard, M.; Becherini, Y.; et al. (Astronomy & Astrophysics, 2018)
Using the High Energy Spectroscopic System (H.E.S.S.) telescopes we have discovered a steady and extended very high-energy (VHE) gamma-ray source towards the luminous blue variable candidate LBV 1806-20, massive stellar cluster Cl* 1806-20, and magnetar SGR 1806-20. The new VHE source, HESS J1808-204, was detected at a statistical significance of >6 sigma (post-trial) with a photon flux normalisation (2.9 +/- 0.4(stat) +/- 0.5(sys)) x 10(-13) ph cm(-2) s(-1) TeV-1 at 1 TeV and a power-law photon index of 2.3 +/- 0.2(stat) +/- 0.3(sys). The luminosity of this source (0.2 to 10 TeV; scaled to distance d = 8 : 7 kpc) is L-VHE similar to 1.6 x 10(34)(d = 8.7 kpc)(2) erg s(-1). The VHE gamma-ray emission is extended and is well fit by a single Gaussian with statistical standard deviation of 0.095 degrees +/- 0.015 degrees. This extension is similar to that of the synchrotron radio nebula G10.0-0.3, which is thought to be powered by LBV 1806-20. The VHE gamma-ray luminosity could be provided by the stellar wind luminosity of LBV 1806-20 by itself and/or the massive star members of Cl* 1806-20. Alternatively, magnetic dissipation (e.g. via reconnection) from SGR 1806-20 can potentially account for the VHE luminosity. The origin and hadronic and/or leptonic nature of the accelerated particles responsible for HESS J1808-204 is not yet clear. If associated with SGR 1806 20, the potentially young age of the magnetar (650 yr) can be used to infer the transport limits of these particles to match the VHE source size. This discovery provides new interest in the potential for high-energy particle acceleration from magnetars, massive stars, and/or stellar clusters.
Keywords: gamma rays: general; stars: magnetars; stars: massive

Extended X-ray emission in PKS 1718-649 - Beuchert, T.; Rodriguez-Ardila, A.; Moss, V. A.; Schulz, R.; Kadler, M.; Wilms, Jörn; Angioni, Roberto; Callingham, J. R.; Gräfe, Christina; Krauss, F.; Kreikenbohm, A.; Langejahn, M.; et al. (Astronomy & Astrophysics, 2018)
PKS 1718 649 is one of the closest and most comprehensively studied candidates of a young active galactic nucleus (AGN) that is still embedded in its optical host galaxy. The compact radio structure, with a maximal extent of a few parsecs, makes it a member of the group of compact symmetric objects (CSO). Its environment imposes a turnover of the radio synchrotron spectrum towards lower frequencies, also classifying PKS 1718-649 as gigahertz-peaked radio spectrum (GPS) source. Its close proximity has allowed the first detection of extended X-ray emission in a GPS/CSO source with Chandra that is for the most part unrelated to nuclear feedback. However, not much is known about the nature of this emission. By co-adding all archival Chandra data and complementing these datasets with the large effective area of XMM-Newton, we are able to study the detailed physics of the environment of PKS 1718-649. Not only can we confirm that the bulk of the less than or similar to kiloparsec-scale environment emits in the soft X-rays, but we also identify the emitting gas to form a hot, collisionally ionized medium. While the feedback of the central AGN still seems to be constrained to the inner few parsecs, we argue that supernovae are capable of producing the observed large-scale X-ray emission at a rate inferred from its estimated star formation rate.
Keywords: galaxies: active; galaxies: nuclei; galaxies: individual: PKS 1718-649; galaxies: ISM; galaxies: star formation; X-rays: galaxies

EXTP: Enhanced X-ray Timing and Polarization mission - Zhang, S. N.; Feroci, M.; Santangelo, A.; Dong, Y. W.; Feng, H.; Lu, F. J.; Nandra, K.; Wang, Z. S.; Zhang, S.; Bozzo, E.; Brandt, S.; De Rosa, A.; et al. (Space Telescopes and Instrumentation 2016: Ultraviolet to Gamma Ray, 2016)
EXTP is a science mission designed to study the state of matter under extreme conditions of density, gravity and magnetism. Primary goals are the determination of the equation of state of matter at supra-nuclear density, the measurement of QED effects in highly magnetized star, and the study of accretion in the strong-field regime of gravity. Primary targets include isolated and binary neutron stars, strong magnetic field systems like magnetars, and stellar-mass and supermassive black holes. The mission carries a unique and unprecedented suite of state-of-the-art scientific instruments enabling for the first time ever the simultaneous spectral-timing-polarimetry studies of cosmic sources in the energy range from 0.5-30 keV (and beyond). Key elements of the payload are: the Spectroscopic Focusing Array (SFA) - a set of 11 X-ray optics for a total effective area of ∼0.9 m and 0.6 m at 2 keV and 6 keV respectively, equipped with Silicon Drift Detectors offering <180 eV spectral resolution; the Large Area Detector (LAD) - a deployable set of 640 Silicon Drift Detectors, for a total effective area of ∼3.4 m, between 6 and 10 keV, and spectral resolution better than 250 eV; the Polarimetry Focusing Array (PFA) - a set of 2 X-ray telescope, for a total effective area of 250 cm at 2 keV, equipped with imaging gas pixel photoelectric polarimeters; the Wide Field Monitor (WFM) - a set of 3 coded mask wide field units, equipped with position-sensitive Silicon Drift Detectors, each covering a 90 degrees × 90 degrees field of view. The eXTP international consortium includes major institutions of the Chinese Academy of Sciences and Universities in China, as well as major institutions in several European countries and the United States. The predecessor of eXTP, the XTP mission concept, has been selected and funded as one of the so-called background missions in the Strategic Priority Space Science Program of the Chinese Academy of Sciences since 2011. The strong European participation has significantly enhanced the scientific capabilities of eXTP. The planned launch date of the mission is earlier than 2025.
Keywords: Neutron Star EOS; spectroscopy; Strong Gravity; Strong Magnetism; X-ray astronomy; X-ray timing

Extragalactic Wolf-Rayet/black-hole X-ray binary candidates NGC 300 X-1 and IC 10 X-1 - Carpano, S.; Pollock, A. M. T.; Prestwich, A.; Kilgard, R.; Crowther, P.; Wilms, Jörn; Yungelson, L.; Ehle, Matthias (2008)
NGC 300 X-1 and IC 10 X-1 have recently been identified in nearby galaxies as extragalactic examples of the rare class of Wolf-Rayet/compact object X-ray binary system uniquely exemplified in the Galaxy by Cyg X-3. Using Swift TOO observations of NGC 300 X-1 and IC 10 X-1, we recently discovered very similar periods of 32.8 +/- 0.4 and 34.8 +/- 0.9 hours, respectively. We believe that these are likely to be orbital periods. It seems surprising that these are so similar and large compared to the short 4.8 hour period of Cyg X-3, suggesting different evolutionary paths. For both extragalactic candidates we show the allowed ranges of component masses and Wolf-Rayet star wind velocities for which accretion disks could form around the black holes.

EXTraS discovery of an 1.2-s X-ray pulsar in M 31 - Esposito, Paolo; Israel, G. L.; Belfiore, Andrea; Novara, G.; Sidoli, Lara; Castillo, G. A. Rodriguez; De Luca, Andrea; Tiengo, A.; Haberl, Frank; Salvaterra, Ruben; Read, A. M.; Salvetti, D.; et al. (Monthly Notices of the Royal Astronomical Society: Letters, 2016)
During a search for coherent signals in the X-ray archival data of XMM-Newton, we discovered a modulation at 1.2 s in 3XMMJ004301.4+413017 (3X J0043), a source lying in the direction of an external arm ofM31. This short period indicates a neutron star (NS). Between 2000 and 2013, the position of 3X J0043 was imaged by public XMM-Newton observations 35 times. The analysis of these data allowed us to detect an orbital modulation at 1.27 d and study the long-term properties of the source. The emission of the pulsar was rather hard (most spectra are described by a power law withΓ <1) and, assuming the distance to M 31, the 0.3-10 keV luminosity was variable, from 3 × 10 to 2 × 10 erg s. The analysis of optical data shows that, while 3X J0043 is likely associated to a globular cluster in M 31, a counterpart with V ≥ 22 outside the cluster cannot be excluded. Considering our findings, there are two main viable scenarios for 3X J0043: a peculiar low-mass X-ray binary, similar to 4U 1822-37 or 4U 1626-67, or an intermediate-mass X-ray binary resembling Her X-1. Regardless of the exact nature of the system, 3X J0043 is the first accreting NS in M 31 in which the spin period has been detected.
Keywords: Galaxies: individual: M 31; X-rays: binaries; X-rays: individual: 3XMM J004301.4+413017

Extreme relativistic reflection in the active galaxy ESO 033-G002 - Walton, D. J.; Balokovic, Mislav; Fabian, A. C.; Gallo, Luigi C.; Koss, M.; Nardini, E.; Reynolds, C. S.; Ricci, C.; Stern, Daniel; Alston, W. N.; Dauser, Thomas; Garcia, Javier; et al. (Monthly Notices of the Royal Astronomical Society, 2021)
We present the first high signal-to-noise broad-band X-ray spectrum of the radio-quiet type-2 Seyfert ESO 033-G002, combining data from XMM-Newton and NuSTAR. The nuclear X-ray spectrum is complex, showing evidence for both neutral and ionized absorption, as well as reflection from both the accretion disc and more distant material, but our broad-band coverage allows us to disentangle all of these different components. The total neutral column during this epoch is NH ∼(5-6) × 1022 cm-2, consistent with the optical classification of ESO 033-G002 as a type-2 Seyfert but not so large as to prevent us from robustly determining the properties of the innermost accretion flow. The ionized absorption - dominated by lines from Fe xxv and Fe xxvi - reveals a moderately rapid outflow (vout ∼5400 km s-1) which has a column comparable to the neutral absorption. We find the disc reflection from the innermost regions to be extreme, with a reflection fraction of Rfrac ∼5. This requires strong gravitational lightbending and, in turn, both an extremely compact corona (within ∼2 RG of the black hole) and a rapidly rotating black hole (a∗ > 0.96). Despite this tight size constraint, with a temperature of kTe = 40-70 keV the X-ray corona in ESO 033-G002 appears similar to other active galactic nucle in terms of its placement in the compactness-temperature plane, consistent with sitting close to the limit determined by runaway pair production. Finally, combining X-ray spectroscopy, timing, and updated optical spectroscopy, we also estimate the mass of the black hole to be log[MBH/M⊙] ∼7.0-7.5.
CRIS-Team Scopus Importer:2021-08-20
Keywords: Black hole physics; Galaxies: active; X-rays: individual: ESO 033-G002

Extreme ultra-soft X-ray variability in an eROSITA observation of the narrow-line Seyfert 1 galaxy 1H 0707-495 - Boller, Th; Liu, T.; Weber, Philipp; Arcodia, R.; Dauser, Thomas; Wilms, Jörn; Nandra, K.; Buchner, J.; Merloni, A.; Freyberg, M. J.; Krumpe, M.; Waddell, S. G.H. (Astronomy & Astrophysics, 2021)
The ultra-soft narrow-line Seyfert 1 galaxy 1H 0707-495 is a well-known and highly variable active galactic nucleus (AGN), with a complex, steep X-ray spectrum, and has been studied extensively with XMM-Newton. 1H 0707-495 was observed with the extended ROentgen Survey with an Imaging Telescope Array (eROSITA) aboard the Spectrum-Roentgen-Gamma (SRG) mission on October 11, 2019, for about 60 000 s as one of the first calibration and pointed verification phase (CalPV) observations. The eROSITA light curves show significant variability in the form of a flux decrease by a factor of 58 with a 1 σ error confidence interval between 31 and 235. This variability is primarily in the soft band, and is much less extreme in the hard band. No strong ultraviolet variability has been detected in simultaneous XMM-Newton Optical Monitor observations. The UV emission is LUV ≈ 1044 erg s-1, close to the Eddington limit. 1H 0707-495 entered the lowest hard flux state seen in 20 yr of XMM-Newton observations. In the eROSITA All-Sky Survey (eRASS) observations taken in April 2020, the X-ray light curve is still more variable in the ultra-soft band, but with increased soft and hard band count rates more similar to previously observed flux states. A model including relativistic reflection and a variable partial covering absorber is able to fit the spectra and provides a possible explanation for the extreme light-curve behaviour. The absorber is probably ionised and therefore more transparent to soft X-rays. This leaks soft X-rays in varying amounts, leading to large-Amplitude soft-X-ray variability.
CRIS-Team Scopus Importer:2021-03-19
Keywords: Accretion; accretion disks; Galaxies: Seyfert; X-rays: general

Far-Ultraviolet and X-ray observations of the reverse shock in the Small Magellanic Cloud supernova remnant 1E 0102.2-7219 - Sasaki, Manami; Gaetz, Terrance J.; Blair, William; Edgar, Richard; Morse, Jon; Plucinsky, Paul P.; Smith, Randall (Astrophysical Journal, 2006)
We present Far Ultraviolet Spectroscopic Explorer (FUSE) and X-Ray Multi-Mirror Mission (XMM-Newton) data for the reverse shock of the O-rich supernova remnant (SNR) 1E 0102.2-7219 in the Small Magellanic Cloud (SMC). The FUSE observations cover three regions with significantly different optical [O (III)] intensities, all associated with the relatively bright part of the X-ray ring. Emission lines of O (VI) lambda lambda 1032, 1038 are clearly detected in the FUSE spectra. The XMM-Newton EPIC MOS 1/2 spectra are dominated by strong emission lines of O, Ne, and Mg. By combining the O (VI) doublet emission with the O (VII) triplet and O (VIII) Ly alpha fluxes from the X-ray spectra and assuming a nonequilibrium ionization (NEI) model with a single ionization timescale for the spectra, we find an increase of the ionization timescale tau from north (tau approximate to 0.6 x 10(11) s cm(-3)) to southeast (tau approximate to 2 x 10(11) s cm(-3)). This is indicative of increasing density in the X-ray-bright ring, in good agreement with the optical [O (III)] emission, which is strongest in the southeast. However, if we assume a plane-parallel shock model with a distribution of ionization timescales, the O (VI) emission appears to be inconsistent with O (VII) and O (VIII) in X-rays. The analysis of the total X-ray spectra shows that there is no consistent set of values for the temperature and ionization timescale that can explain the observed line ratios for O, Ne, and Mg. This would be consistent with a structured distribution of the ejecta, as the O, Ne, and Mg would have interacted with the reverse shock at different times.
Keywords: shock waves; supernova remnants; ultraviolet : ISM; X-rays : individual (1E 0102.2-7219)

Fast as Potoroo: Radio Continuum Detection of a Bow-Shock Pulsar Wind Nebula Powered by Pulsar J1638-4713 - Lazarević, Sanja; Filipović, Miroslav D.; Dai, Shi; Kothes, Roland; Ahmad, Adeel; Alsaberi, Rami Z.E.; Balzan, Joel C.F.; Barnes, Luke A.; Cotton, William D.; Edwards, Philip G.; Gordon, Yjan A.; Haberl, Frank; et al. (Publications of the Astronomical Society of Australia, 2024)
We report the discovery of a bow-shock pulsar wind nebula (PWN), named Potoroo, and the detection of a young pulsar J1638-4713 that powers the nebula. We present a radio continuum study of the PWN based on 20-cm observations obtained from the Australian Square Kilometre Array Pathfinder (ASKAP) and MeerKAT. PSR J1638-4713 was identified using Parkes radio telescope observations at frequencies above 3 GHz. The pulsar has the second-highest dispersion measure of all known radio pulsars (1553 pc cm-3), a spin period of 65.74 ms and a spin-down luminosity of E = 6.1 × 1036 erg s-1. The PWN has a cometary morphology and one of the greatest projected lengths among all the observed pulsar radio tails, measuring over 21 pc for an assumed distance of 10 kpc. The remarkably long tail and atypically steep radio spectral index are attributed to the interplay of a supernova reverse shock and the PWN. The originating supernova remnant is not known so far. We estimated the pulsar kick velocity to be in the range of 1000 - 2000 km s -1 for ages between 23 and 10 kyr. The X-ray counterpart found in Chandra data, CXOU J163802.6-471358, shows the same tail morphology as the radio source but is shorter by a factor of 10. The peak of the X-ray emission is offset from the peak of the radio total intensity (Stokes I) emission by approximately 4.7", but coincides well with circularly polarised (Stokes V) emission. No infrared counterpart was found.
CRIS-Team Scopus Importer:2024-04-19
Keywords: ISM: individual (Potoroo); pulsars: individual (PSR J1638-4713); radiation mechanism: non-thermal; radio continuum: ISM; stars: winds; outflows; X-rays: individual (CXOU J163802.6-471358)

FERMI DISCOVERY OF GAMMA-RAY EMISSION FROM NGC 1275 - Abdo, A. A.; Ackermann, Markus; Ajello, M.; Asano, K.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Baughman, B. M.; Bechtol, K.; Bellazzini, R.; Blandford, R. D.; et al. (Astrophysical Journal, 2009)
We report the discovery of high-energy (E > 100 MeV) gamma-ray emission from NGC 1275, a giant elliptical galaxy lying at the center of the Perseus cluster of galaxies, based on observations made with the Large Area Telescope (LAT) of the Fermi Gamma-ray Space Telescope. The positional center of the gamma-ray source is only approximate to 3' away from the NGC 1275 nucleus, well within the 95% LAT error circle of approximate to 5'. The spatial distribution of gamma-ay photons is consistent with a point source. The average flux and power-law photon index measured with the LAT from 2008 August 4 to 2008 December 5 are F-gamma = (2.10 +/- 0.23) x 10(-7) ph (>100 MeV) cm(-2) s(-1) and Gamma = 2.17 +/- 0.05, respectively. The measurements are statistically consistent with constant flux during the four-month LAT observing period. Previous EGRET observations gave an upper limit of F-gamma < 3.72 x 10(-8) ph (>100 MeV) cm(-2) s(-1) to the gamma-ray flux from NGC 1275. This indicates that the source is variable on timescales of years to decades, and therefore restricts the fraction of emission that can be produced in extended regions of the galaxy cluster. Contemporaneous and historical radio observations are also reported. The broadband spectrum of NGC 1275 is modeled with a simple one-zone synchrotron/synchrotron self-Compton model and a model with a decelerating jet flow.
CRIS-Team WoS Importer:2020-01-15

FERMI LARGE AREA TELESCOPE VIEW OF THE CORE OF THE RADIO GALAXY CENTAURUS A - Abdo, A. A.; Ackermann, Markus; Ajello, M.; Atwood, W. B.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Baughman, B. M.; Bechtol, K.; Bellazzini, R.; Berenji, Bijan; et al. (Astrophysical Journal, 2010)
We present gamma-ray observations with the Large Area Telescope (LAT) on board the Fermi Gamma-Ray Space Telescope of the nearby radio galaxy Centaurus A (Cen A). The previous EGRET detection is confirmed, and the localization is improved using data from the first 10 months of Fermi science operation. In previous work, we presented the detection of the lobes by the LAT; in this work, we concentrate on the gamma-ray core of Cen A. Flux levels as seen by the LAT are not significantly different from that found by EGRET, nor is the extremely soft LAT spectrum (Gamma = 2.67 +/- 0.10(stat) +/- 0.08(sys) where the photon flux is Phi alpha E-Gamma). The LAT core spectrum, extrapolated to higher energies, is marginally consistent with the non-simultaneous HESS spectrum of the source. The LAT observations are complemented by simultaneous observations from Suzaku, the Swift Burst Alert Telescope and X-ray Telescope, and radio observations with the Tracking Active Galactic Nuclei with Austral Milliarcsecond Interferometry program, along with a variety of non-simultaneous archival data from a variety of instruments and wavelengths to produce a spectral energy distribution (SED). We fit this broadband data set with a single-zone synchrotron/synchrotron self-Compton model, which describes the radio through GeV emission well, but fails to account for the non-simultaneous higher energy TeV emission observed by HESS from 2004 to 2008. The fit requires a low Doppler factor, in contrast to BL Lac objects which generally require larger values to fit their broadband SEDs. This indicates that the gamma-ray emission originates from a slower region than that from BL Lac objects, consistent with previous modeling results from Cen A. This slower region could be a slower moving layer around a fast spine, or a slower region farther out from the black hole in a decelerating flow. The fit parameters are also consistent with Cen A being able to accelerate ultra-high energy cosmic-rays, as hinted at by results from the Auger observatory.
CRIS-Team WoS Importer:2020-01-15

Fermi/LAT counterparts of IceCube neutrinos above 100 TeV - Krauss, F.; Deoskar, K.; Baxter, Claire; Kadler, M.; Kreter, M.; Langejahn, M.; Mannheim, K.; Polko, P.; Wang, B.; Wilms, Jörn (Astronomy & Astrophysics, 2018)
The IceCube Collaboration has published four years of data and the observed neutrino flux is significantly in excess of the expected atmospheric background. Due to the steeply falling atmospheric background spectrum, events at the highest energies are most likely extraterrestrial. In our previous approach we have studied blazars as the possible origin of the High-Energy Starting Events (HESE) neutrino events at PeV energies. In this work we extend our study to include all HESE neutrinos (which does not include IC 170922A) at or above a reconstructed energy of 100 TeV, but below 1 PeV. We study the X-ray and gamma-ray data of all (similar to 200) 3LAC blazars that are positionally consistent with the neutrino events above 100 TeV to determine the maximum neutrino flux from these sources. This larger sample allows us to better constrain the scaling factor between the observed and maximum number of neutrino events. We find that when we consider a realistic neutrino spectrum and other factors, the number of neutrinos is in good agreement with the detected number of IceCube HESE events. We also show that there is no direct correlation between Fermi/LAT gamma-ray flux and the IceCube neutrino flux and that the expected number of neutrinos is consistent with the non-detection of individual bright blazars.
Keywords: neutrinos; galaxies: active; quasars: general; BL Lacertae objects: general

Finding a 24-day orbital period for the X-ray binary 1A 1118-616 - Staubert, R.; Pottschmidt, K.; Doroshenko, Victor; Wilms, Jörn; Suchy, S.; Rothschild, R.; Santangelo, A. (Astronomy & Astrophysics, 2011)
We report the first determination of the binary period and orbital ephemeris of the Be X-ray binary containing the pulsar 1A 1118-616 (35 years after the discovery of the source). The orbital period is found to be P(orb) = 24.0 +/- 0.4 days. The source was observed by RXTE during its last large X-ray outburst in January 2009, which peaked at MJD 54845.4, by taking short observations every few days, covering an elapsed time comparable to the orbital period. Using the phase connection technique, pulse arrival time delays could be measured and an orbital solution determined. The data are consistent with a circular orbit and the time of 90 degrees longitude was found to be T(pi/2) = MJD 54845.37(10), which is coincident with that of the peak X-ray flux.
Keywords: binaries: general; stars: neutron; X-rays: general; X-rays: binaries; X-rays: individuals: 1A 1118-616; ephemerides

First all-flavor neutrino pointlike source search with the ANTARES neutrino telescope - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. -J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Belhorma, B.; Bertin, V.; et al. (Physical Review D - Particles, Fields, Gravitation and Cosmology, 2017)
A search for cosmic neutrino sources using the data collected with the ANTARES neutrino telescope between early 2007 and the end of 2015 is performed. For the first time, all neutrino interactions-charged and neutral-current interactions of all flavors-are considered in a search for point-like sources with the ANTARES detector. In previous analyses, only muon neutrino charged-current interactions were used. This is achieved by using a novel reconstruction algorithm for shower-like events in addition to the standard muon track reconstruction. The shower channel contributes about 23% of all signal events for an E-2 energy spectrum. No significant excess over background is found. The most signal-like cluster of events is located at (alpha, delta) = (343.8 degrees, 23.5 degrees) with a significance of 1.9 sigma. The neutrino flux sensitivity of the search is about E(2)d Phi/dE = 6 x 10(-9) GeV cm(-2) s(-1) for declinations from -90 degrees up to -42 degrees, and below 10(-8) GeV cm(-2) s(-1) for declinations up to 5 degrees. The directions of 106 source candidates and 13 muon track events from the IceCube high-energy sample events are investigated for a possible neutrino signal and upper limits on the signal flux are determined.

First ground-based measurement of sub-20 GeV to 100 GeV gamma-Rays from the Vela pulsar with HESS II - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Arrieta, M.; Backes, Michael; Barnard, M.; Becherini, Y.; Tjus, J. Becker; et al. (Astronomy & Astrophysics, 2018)
Aims. We report on the measurement and investigation of pulsed high-energy y-ray emission from the Vela pulsar, PSR B0833-45, based on observations with the largest telescope of H.E.S.S., CT5, in monoscopic mode, and on data obtained with the Fermi-LAT.
CRIS-Team WoS Importer:2020-01-15
Keywords: Gamma rays: stars; Pulsars: individual: PSR B0833-45; Radiation mechanisms: non-Thermal

First multi-wavelength campaign on the gamma-ray-loud active galaxy IC 310 - Ahnen, M. L.; Ansoldi, S.; Antonelli, L. A.; Arcaro, C.; Babic, A.; Banerjee, B.; Bangale, P.; De Almeida, U. Barres; Barrio, J. A.; Becerra Gonzalez, Josefa; Bednarek, Wlodek; Bernardini, E.; et al. (Astronomy & Astrophysics, 2017)
Context. The extragalactic very-high-energy gamma-ray sky is rich in blazars. These are jetted active galactic nuclei that are viewed at a small angle to the line-of-sight. Only a handful of objects viewed at a larger angle are so far known to emit above 100 GeV. Multi-wavelength studies of such objects up to the highest energies provide new insights into the particle and radiation processes of active galactic nuclei.Aims. We aim to report the results from the first multi-wavelength campaign observing the TeV detected nucleus of the active galaxy IC 310, whose jet is observed at a moderate viewing angle of 10 degrees-20 degrees.Methods. The multi-instrument campaign was conducted between 2012 November and 2013 January, and involved observations with MAGIC, Fermi, INTEGRAL, Swift, OVRO, MOJAVE and EVN. These observations were complemented with archival data from the AllWISE and 2MASS catalogs. A one-zone synchrotron self-Compton model was applied to describe the broadband spectral energy distribution.Results. IC 310 showed an extraordinary TeV flare at the beginning of the campaign, followed by a low, but still detectable TeV flux. Compared to previous measurements in this energy range, the spectral shape was found to be steeper during the low emission state. Simultaneous observations in the soft X-ray band showed an enhanced energy flux state and a harder-when-brighter spectral shape behavior. No strong correlated flux variability was found in other frequency regimes. The broadband spectral energy distribution obtained from these observations supports the hypothesis of a double-hump structure.Conclusions. The harder-when-brighter trend in the X-ray and VHE emission, observed for the first time during this campaign, is consistent with the behavior expected from a synchrotron self-Compton scenario. The contemporaneous broadband spectral energy distribution is well described with a one-zone synchrotron self-Compton model using parameters that are comparable to those found for other gamma-ray-emitting misaligned blazars.
Keywords: galaxies: active; galaxies: individual: IC 310; gamma rays: galaxies

First observations of speed of light tracks by a fluorescence detector looking down on the atmosphere - Abdellaoui, G.; Abe, S.; Adams, J. H.; Ahriche, A.; Allard, D.; Allen, L.; Alonso, G.; Anchordoqui, L.; Anzalone, A.; Arai, Y.; Asano, K.; Attallah, R.; et al. (Journal of Instrumentation, 2018)
EUSO-Balloon is a pathfinder mission for the Extreme Universe Space Observatory onboard the Japanese Experiment Module (JEM-EUSO). It was launched on the moonless night of the 25(th) of August 2014 from Timmins, Canada. The flight ended successfully after maintaining the target altitude of 38 km for five hours. One part of the mission was a 2.5 hour underflight using a helicopter equipped with three UV light sources (LED, xenon flasher and laser) to perform an inflight calibration and examine the detectors capability to measure tracks moving at the speed of light. We describe the helicopter laser system and details of the underflight as well as how the laser tracks were recorded and found in the data. These are the first recorded laser tracks measured from a fluorescence detector looking down on the atmosphere. Finally, we present a first reconstruction of the direction of the laser tracks relative to the detector.
Keywords: Detectors for UV; visible and IR photons; Lasers; Balloon instrumentation; Space instrumentation

First results on dark matter annihilation in the Sun using the ANTARES neutrino telescope - Adrian-Martinez, S.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anton, L.; Anvar, S.; Ardid, Miguel; Astraatmadja, T.; Aubert, J-J.; Baret, B.; et al. (Journal of Cosmology and Astroparticle Physics, 2013)
A search for high-energy neutrinos coming from the direction of the Sun has been performed using the data recorded by the ANTARES neutrino telescope during 2007 and 2008. The neutrino selection criteria have been chosen to maximize the selection of possible signals produced by the self-annihilation of weakly interacting massive particles accumulated in the centre of the Sun with respect to the atmospheric background. After data unblinding, the number of neutrinos observed towards the Sun was found to be compatible with background expectations. The 90% CL upper limits in terms of spin-dependent and spin-independent WIMP-proton cross-sections are derived and compared to predictions of two supersymmetric models, CMSSM and MSSM-7. The ANTARES limits are comparable with those obtained by other neutrino observatories and are more stringent than those obtained by direct search experiments for the spin-dependent WIMP-proton cross-section in the case of hard self-annihilation channels (W+W-, tau(+)tau(-)).
Keywords: neutrino experiments; dark matter detectors; supersymmetry and cosmology; particle physics - cosmology connection

First search for neutrinos in correlation with gamma-ray bursts with the ANTARES neutrino telescope - Adrian-Martinez, S.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Jesus, A. C. Assis; Astraatmadja, T.; Aubert, J-J.; Baret, B.; et al. (Journal of Cosmology and Astroparticle Physics, 2013)
A search for neutrino-induced muons in correlation with a selection of 40 gamma-ray bursts that occurred in 2007 has been performed with the ANTARES neutrino telescope. During that period, the detector consisted of 5 detection lines. The ANTARES neutrino telescope is sensitive to TeV-PeV neutrinos that are predicted from gamma-ray bursts. No events were found in correlation with the prompt photon emission of the gamma-ray bursts and upper limits have been placed on the flux and fluence of neutrinos for different models.
Keywords: neutrino experiments; neutrino astronomy; gamma ray bursts theory

FIRST SEARCH FOR POINT SOURCES OF HIGH-ENERGY COSMIC NEUTRINOS WITH THE ANTARES NEUTRINO TELESCOPE - Adrian-Martinez, S.; Aguilar, J. A.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Jesus, A. C. Assis; Astraatmadja, T.; Aubert, J. -J.; et al. (Astrophysical Journal Letters, 2011)
Results are presented of a search for cosmic sources of high-energy neutrinos with the ANTARES neutrino telescope. The data were collected during 2007 and 2008 using detector configurations containing between 5 and 12 detection lines. The integrated live time of the analyzed data is 304 days. Muon tracks are reconstructed using a likelihood-based algorithm. Studies of the detector timing indicate a median angular resolution of 0.5 +/- 0.1 deg. The neutrino flux sensitivity is 7.5 x 10(-8)(E(v)/GeV)(-2) GeV(-1) s(-1) cm(-2) for the part of the sky that is always visible (delta < -48 deg), which is better than limits obtained by previous experiments. No cosmic neutrino sources have been observed.
Keywords: astroparticle physics; cosmic rays; neutrinos

First studies of the diffuse X-ray emission in the Large Magellanic Cloud with eROSITA - Sasaki, Manami; Knies, Jonathan; Haberl, Frank; Maitra, Chandreyee; Kerp, Juergen; Bykov, Andrei M.; Dennerl, Konrad; Filipovic, Miroslav D.; Freyberg, Michael; Koribalski, Barbel S.; Points, Sean; Staveley-Smith, Lister (Astronomy & Astrophysics, 2022)
Context. In the first months after its launch in July 2019, the extended Roentgen Survey with an Imaging Telescope Array (eROSITA) on board Spektrum-Roentgen-Gamma performed long-exposure observations in the regions around supernova (SN) 1987A and super-nova remnant (SNR) N132D in the Large Magellanic Cloud (LMC). Aims. We analysed the distribution and the spectrum of the diffuse X-ray emission in the observed fields to determine the physical properties of the hot phase of the interstellar medium (ISM). Methods. Spectral extraction regions were defined using the Voronoi tessellation method. The spectra were fit with a combination of thermal and non-thermal emission models. The eROSITA data are complemented by newly derived column density maps for the Milky Way and the LMC, 888 MHz radio continuum map from the Australian Square Kilometer Array Pathfinder, and optical images of the Magellanic Cloud Emission Line Survey. Results. We detect significant emission from thermal plasma with kT = 0.2 keV in all the regions. There is also an additional higher- temperature emission component from a plasma with kT approximate to 0.7 keV. The surface brightness of this component is one order of magnitude lower than that of the lower-temperature component. In addition, non-thermal X-ray emission is significantly detected in the superbubble 30 Dor C. The absorbing column density N-H in the LMC derived from the analysis of the X-ray spectra taken with eROSITA is consistent with the N-H obtained from the emission of the cold medium over the entire area. Neon abundance is enhanced in the regions in and around 30 Dor and SN 1987A, indicating that the ISM has been chemically enriched by the young stellar population. In the centre of 30 Dor, there are two bright extended X-ray sources, which coincide with the stellar cluster RMC 136 and the Wolf-Rayet stars RMC 139 and RMC 140. For both regions the emission is best modelled with a high-temperature (kT > 1 keV) non-equilibrium ionisation plasma emission and a non-thermal component with a photon index of Gamma = 1.3. In addition, we detect an extended X-ray source at the position of the optical SNR candidate J0529-7004 with thermal emission, and thus confirm its classification as an SNR. Conclusions. Using data from the early observations of the regions around SN 1987A and SNR N132D with eROSITA we confirm that there is thermal interstellar plasma in the entire observed field. eROSITA with its large field of view and high sensitivity at lower X-ray energies allows us for the first time to carry out a detailed study of the ISM at high energies consistently over a large region in the LMC. We thus measure the properties of the interstellar plasma and the distribution of non-thermal particles and derive the column density of the cold matter on the line of sight.
CRIS-Team WoS Importer:2022-06-17

Fitting strategies of accretion column models and application to the broadband spectrum of Cen X-3 - Thalhammer, Philipp; Bissinger, Matthias; Ballhausen, Ralf; Pottschmidt, Katja; Wolff, Michael T.; Stierhof, Jakob; Sokolova-Lapa, Ekaterina; Furst, Felix; Malacaria, Christian; Gottlieb, Amy; Marcu-Cheatham, Diana M.; Becker, Peter A.; et al. (Astronomy & Astrophysics, 2021)
Due to the complexity of modeling the radiative transfer inside the accretion columns of neutron star binaries, their X-ray spectra are still commonly described with phenomenological models, for example, a cutoff power law. While the behavior of these models is well understood and they allow for a comparison of different sources and studying source behavior, the extent to which the underlying physics can be derived from the model parameters is very limited. During recent years, several physically motivated spectral models have been developed to overcome these limitations. Their application, however, is generally computationally much more expensive and they require a high number of parameters which are difficult to constrain. Previous works have presented an analytical solution to the radiative transfer equation inside the accretion column assuming a velocity profile that is linear in the optical depth. An implementation of this solution that is both fast and accurate enough to be fitted to observed spectra is available as a model in XSPEC. The main difficulty of this implementation is that some solutions violate energy conservation and therefore have to be rejected by the user. We propose a novel fitting strategy that ensures energy conservation during the chi(2)-minimization which simplifies the application of the model considerably. We demonstrate this approach as well as a study of possible parameter degeneracies with a comprehensive Markov-chain Monte Carlo analysis of the complete parameter space for a combined NuSTAR and Swift/XRT dataset of Cen X-3. The derived accretion-flow structure features a small column radius of similar to 63 m and a spectrum dominated by bulk-Comptonization of bremsstrahlung seed photons, in agreement with previous studies.
CRIS-Team WoS Importer:2021-12-17

Four new X-ray-selected supernova remnants in the Large Magellanic Cloud - Maggi, P.; Haberl, Frank; Kavanagh, P. J.; Points, S. D.; Dickel, J.; Bozzetto, L. M.; Sasaki, Manami; Chu, Y. -H.; Gruendl, R. A.; Filipovic, M. D.; Pietsch, W. (Astronomy & Astrophysics, 2014)
Aims: We present a detailed multi-wavelength study of four new supernova remnants (SNRs) in the Large Magellanic Cloud (LMC). The objects were identified as SNR candidates in X-ray observations performed during the survey of the LMC with XMM-Newton. Methods: Data obained with XMM-Newton are used to investigate the morphological and spectral features of the remnants in X-rays. We measure the plasma conditions, look for supernova (SN) ejecta emission, and constrain some of the SNR properties (e.g. age and ambient density). We supplement the X-ray data with optical, infrared, and radio-continuum archival observations, which allow us to understand the conditions resulting in the current appearance of the remnants. Based on the spatially-resolved star formation history (SFH) of the LMC together with the X-ray spectra, we attempt to type the supernovae that created the remnants. Results: We confirm all four objects as SNRs, to which we assign the names MCSNR J0508-6830, MCSNR J0511-6759, MCSNR J0514-6840, and MCSNR J0517-6759. In the first two remnants, an X-ray bright plasma is surrounded by very faint [S ii] emission. The emission from the central plasma is dominated by Fe L-shell lines, and the derived iron abundance is greatly in excess of solar. This establishes their type Ia (i.e. thermonuclear) SN origin. They appear to be more evolved versions of other Magellanic Cloud iron-rich SNRs which are centrally-peaked in X-rays. From the two other remnants (MCSNR J0514-6840 and MCSNR J0517-6759), we do not see ejecta emission. At all wavelengths at which they are detected, the local environment plays a key role in their observational appearance. We present evidence that MCSNR J0517-6759 is close to and interacting with a molecular cloud, suggesting a massive progenitor.
Keywords: ISM: supernova remnants; Magellanic Clouds; X-rays: ISM

gamma-ray emission from the Perseus cluster of galaxies observed with the MAGIC telescopes - Colin, P.; Eisenacher, D.; Hildebrand, D.; Lombardi, S.; Lindorfs, E.; Paneque, D.; Partini, S.; Prada, F.; Sitarek, Julian; Zandanel, F.; Dauser, Thomas; Kadler, M.; et al. (2012)
The Perseus cluster of galaxies is a nearby cool-core cluster with an intra-cluster medium (ICM) characterized by very high central densities. The observation of the Perseus cluster with the MAGIC telescopes, during 85 h from 2009 to 2011, resulted in the discovery of 2 point-like sources at very high energy (>100GeV, VHE) coinciding with the central radio galaxy NGC1275 and the radio galaxy IC 310. The gamma-ray properties of these 2 sources are presented, taking into account contemporaneous Fermi-LAT as well as multi-wavelength data. Flux variability and spectral energy distribution shapes indicate that the VHE gamma-rays do not originate from large-scale interaction of the radio galaxies with ICM but more likely from the active nuclei of these two galaxies. They could be both misaligned version of BL Lac objects, the most common TeV AGN. Our results provide vital clues to understand emission mechanisms of such misaligned objects, and how they may be related to the beamed emission seen in BL Lacs. No evidence of large-scale VHE gamma-ray emission from hadronic cosmic ray (CR) interactions with the ICM has been found. The flux upper limit above 1 TeV reaches the signal expected by some theoretical models, constraining the cluster CR physics. In the framework of the hadronic model of the radiomini-halos, this limit implies a minimal magnetic field ranging from 4-9 mu G for the central cluster region.
Keywords: gamma-ray astronomy; Galaxy Cluster; Radio galaxy; NGC 1275; IC 310; Cosmic rays

Gamma-ray emission in radio galaxies under the VLBI scope: I. Parsec-scale jet kinematics and high-energy properties of γ -ray-detected TANAMI radio galaxies - Angioni, Roberto; Ros, E.; Kadler, M.; Ojha, R.; Mueller, C.; Edwards, P. G.; Burd, P. R.; Carpenter, B.; Dutka, M. S.; Gulyaev, S.; Hase, H.; Horiuchi, S.; et al. (Astronomy & Astrophysics, 2019)
Aims. In the framework of the multi-wavelength and very long baseline interferometry (VLBI) monitoring program TANAMI (Tracking Active Nuclei with Austral Milliarcsecond Interferometry), we study the evolution of the parsec-scale radio emission in radio galaxies in the southern hemisphere and their relationship to the γ-ray properties of the sources. Our study investigates systematically, for the first time, the relationship between the two energy regimes in radio galaxies. In this first paper, we focus on Fermi-LAT-detected sources. Methods. The TANAMI program monitors a large sample of radio-loud AGN at 8.4 GHz and 22.3 GHz with the Australian long baseline array (LBA) and associated telescopes in Antarctica, Chile, New Zealand and South Africa. We performed a kinematic analysis for five γ-ray detected radio galaxies using multi-epoch 8.4 GHz VLBI images, deriving limits on intrinsic jet parameters such as speed and viewing angle. We analyzed 103 months of Fermi-LAT data in order to study possible connections between the γ-ray properties and the pc-scale jets of Fermi-LAT-detected radio galaxies, both in terms of variability and average properties. We discuss the individual source results and draw preliminary conclusions on sample properties including published VLBI results from the MOJAVE (Monitoring Of Jets in Active galactic nuclei with VLBA Experiments) survey, with a total of fifteen sources. Results. We find that the first γ-ray detection of Pictor A might be associated with the passage of a new VLBI component through the radio core, which appears to be a defining feature of high-energy emitting Fanaroff-Riley type II radio galaxies. We detect subluminal parsec-scale jet motions in the peculiar AGN PKS 0521-36, and we confirm the presence of fast γ-ray variability in the source down to timescales of six hours, which is not accompanied by variations in the VLBI jet. We robustly confirm the presence of significant superluminal motion, up to βapp ∼ 3, in the jet of the TeV radio galaxy PKS 0625-35. Our VLBI results constrain the jet viewing angle to be θ < 53°, allowing for the possibility of a closely aligned jet. Finally, by analyzing the first pc-scale multi-epoch images of the prototypical compact symmetric object (CSO) PKS 1718-649, we place an upper limit on the separation speed between the two mini-lobes. This in turn allows us to derive a lower limit on the age of the source. Conclusions. We can draw some preliminary conclusions on the relationship between pc-scale jets and γ-ray emission in radio galaxies, based on Fermi-LAT-detected sources with available multi-epoch VLBI measurements. We find that the VLBI core flux density correlates with the γ-ray flux, as seen in blazars. On the other hand, the γ-ray luminosity does not show any dependence on the core brightness temperature and core dominance, which are two common indicators of jet Doppler boosting. This seems to indicate that γ-ray emission in radio galaxies is not driven by orientation-dependent effects, as in blazars, in accordance with the unified model of jetted AGN.
CRIS-Team Scopus Importer:2019-08-02
Keywords: Galaxies: active; Galaxies: jets; Galaxies: nuclei; γrays: galaxies

GAMMA-RAY OBSERVATIONS OF THE MICROQUASARS CYGNUS X-1, CYGNUS X-3, GRS 1915+105, AND GX 339-4 WITH THE FERMI LARGE AREA TELESCOPE - Bodaghee, Arash; Tomsick, John A.; Pottschmidt, Katja; Rodriguez, Jerome; Wilms, Jörn; Pooley, Guy G. (Astrophysical Journal, 2013)
Detecting gamma-rays from microquasars is a challenging but worthwhile endeavor for understanding particle acceleration and the jet mechanism and for constraining leptonic/hadronic emission models. We present results from a likelihood analysis on timescales of 1 day and 10 days of similar to 4 yr worth of gamma-ray observations (0.1-10 GeV) by Fermi-LAT of Cyg X-1, Cyg X-3, GRS 1915 + 105, and GX 339-4. Our analysis reproduced all but one of the previous gamma-ray outbursts of Cyg X-3 as reported with Fermi or AGILE, plus five new days on which Cyg X-3 is detected at a significance of similar to 5 sigma that are not reported in the literature. In addition, Cyg X-3 is significantly detected on 10 day timescales outside of known gamma-ray flaring epochs, which suggests that persistent gamma-ray emission from Cyg X-3 has been detected for the first time. For Cyg X-1 we find three low-significance excesses (similar to 3-4 sigma) on daily timescales that are contemporaneous with gamma-ray flares reported (also at low significance) by AGILE. Two other microquasars, GRS 1915+105 and GX 339-4, are not detected, and we derive 3 sigma upper limits of 2.3 x 10(-8) photons cm(-2) s(-1) and 1.6 x 10-8 photons cm(-2) s(-1), respectively, on the persistent flux in the 0.1-10 GeV range. These results enable us to define a list of the general conditions that are necessary for the detection of gamma-rays from microquasars.
Keywords: black hole physics; gamma rays: stars; stars: neutron; X-rays: binaries; X-rays: individual (Cygnus X-3; Cygnus X-1; GRS 1915+105; GX 339-4)

Geant4 simulation for the responses to X-rays and charged particles through the eXTP focusing mirrors - Qi, L. Q.; Li, G.; Xu, Y. P.; Zhang, J.; Yang, Y. J.; Sheng, L. Z.; Basso, S.; Campana, R.; Chen, Y.; De Rosa, A.; Pareschi, G.; Qiang, P. F.; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2020)
A geometrical and physical model of Wolter-I type mirrors has been implemented in Geant4 for the design of the enhanced X-ray Timing and Polarimetry observatory (eXTP). It can simultaneously simulate the mirror responses to X-rays and charged particles. A new geometry class G4Hyperboloid is created and verified, which allows an exact surface profile description of Wolter-I optics. A physics model for the interaction of X-rays and matter is implemented to effectively estimate the focusing performances with reasonable accuracy, including the effective area and the point spread function. Scattering models of charged particles at grazing incidence are discussed. The multiple scattering model provided by the latest Geant4 release can be used instead of the single scattering model with reasonable accuracy and CPU cost when the step size is properly constrained.
CRIS-Team Scopus Importer:2020-03-17
Keywords: eXTP; Geant4; X-ray telescope

GPU Supported Simulation of Transition-Edge Sensor Arrays - Lorenz, Maximilian; Kirsch, Christian; Merino-Alonso, P. E.; Peille, P.; Dauser, Thomas; Cucchetti, E.; Smith, S. J.; Wilms, Jörn (Journal of Low Temperature Physics, 2020)
We present numerical simulations of full transition-edge sensor (TES) arrays utilizing graphical processing units (GPUs). With the support of GPUs, it is possible to perform simulations of large pixel arrays to assist detector development. Comparisons with TES small-signal and noise theory confirm the representativity of the simulated data. In order to demonstrate the capabilities of this approach, we present its implementation in xifusim, a simulator for the X-ray Integral Field Unit, a cryogenic X-ray spectrometer on board the future Athena X-ray observatory.
CRIS-Team WoS Importer:2020-04-24

GRO J1008-57: an (almost) predictable transient X-ray binary - Kühnel, Matthias; Müller, Sebastian; Kreykenbohm, Ingo; Fuerst, F.; Pottschmidt, K.; Rothschild, R. E.; Caballero, I.; Grinberg, Victoria; Schoenherr, G.; Shrader, C.; Klochkov, D.; Staubert, R.; et al. (Astronomy & Astrophysics, 2013)
A study of archival RXTE, Swift, and Suzaku pointed observations of the transient high-mass X-ray binary GRO J1008-57 is presented. A new orbital ephemeris based on pulse arrival-timing shows the times of maximum luminosities during outbursts of GRO J1008-57 to be close to periastron at orbital phase -0.03. This makes the source one of a few for which outburst dates can be predicted with very high precision. Spectra of the source in 2005, 2007, and 2011 can be well described by a simple power law with high-energy cutoff and an additional black body at lower energies. The photon index of the power law and the black-body flux only depend on the 15-50 keV source flux. No apparent hysteresis effects are seen. These correlations allow us to predict the evolution of the pulsar's X-ray spectral shape over all outbursts as a function of just one parameter, the source's flux. If modified by an additional soft component, this prediction even holds during GRO J1008-57's 2012 type II outburst.
Keywords: X-rays: binaries; pulsars: individual: GRO J1008-57; accretion; accretion disks; ephemerides

GRS 1739-278 Observed at Very Low Luminosity with XMM-Newton and NuSTAR - Furst, F.; Tomsick, J. A.; Yamaoka, K.; Dauser, Thomas; Miller, J. M.; Clavel, Maica; Corbel, S.; Fabian, A.; Garcia, Javier; Harrison, F. A.; Loh, A.; Kaaret, P.; et al. (Astrophysical Journal, 2016)
Keywords: accretion; accretion disks; stars: black holes; X-rays: binaries; X-rays: individual: GRS 1739-278

Hard X-ray properties of radio-selected blazars - Langejahn, M.; Kadler, M.; Wilms, Jörn; Litzinger, E.; Kreter, M.; Gehrels, N.; Baumgartner, W. H.; Markwardt, C. B.; Tueller, J. (Astronomy & Astrophysics, 2020)
Context. Hard X-ray properties of beamed active galactic nuclei have been published in the 105-month Swift/BAT catalog, but there have not been any studies carried out so far on a well-defined, radio-selected sample of low-peaked blazars in the hard X-ray band.
CRIS-Team WoS Importer:2020-06-16

HD188112: Supernova Ia Progenitor? - Latour, Marilyn; Irrgang, Andreas; Heber, Ulrich; Schaffenroth, Veronika (ASTRONOMICAL SOC PACIFIC, 390 ASHTON AVE, SAN FRANCISCO, CA 94112 USA, 2015)
HD188112 is an extremely low mass white dwarf in a close binary system. According to a previous study, the mass of HD188112 is similar to 0.24 M-circle dot and a lower limit of 0.73 M-circle dot could be put for the mass of its unseen companion, a compact degenarate object. We used HST STIS spectra to measure the rotational broadening of UV metallic lines in HD188112, in order to put tighter constraints on the mass of its companion. By assuming that the system in is synchronous rotation, we derive a companion mass between 1.05 and 1.25 M-circle dot. We also measure abundances for magnesium, silicon, and iron, respectively log N(X)/N(H) = -6.40, -7.25, and -5.81. The radial velocities measured from the UV spectra are found to be in very good agreement with the prediction based on the orbital parameters derived in the previous study made a decade ago.

Heavy metal enrichment in the intermediate He-sdOB pulsator Feige 46 - Latour, Marilyn; Dorsch, Matti; Heber, Ulrich (Astronomy & Astrophysics, 2019)
The intermediate He-enriched hot subdwarf star Feige 46 was recently reported as the second member of the V366 Aqr (or He-sdOBV) pulsating class. Feige 46 is very similar to the prototype of the class, LS IV-14 degrees 116, not only in terms of pulsational properties, but also in terms of atmospheric parameters and kinematic properties. LS IV-14 degrees 116 is additionally characterized by a very peculiar chemical composition, with extreme overabundances of the trans-iron elements Ge, Sr, Y, and Zr. We investigate the possibility that the similarity between the two pulsators extends to their chemical composition. We retrieved archived optical and UV spectroscopic observations of Feige 46 and performed an abundance analysis using model atmospheres and synthetic spectra computed with TLUSTY and SYNSPEC. In total, we derived abundances for 16 elements and provide upper limits for four additional elements. Using absorption lines in the optical spectrum of the star we measure an enrichment of more than 10 000x solar for yttrium and zirconium. The UV spectrum revealed that strontium is equally enriched. Our results confirm that Feige 46 is not only a member of the now growing group of heavy metal subdwarfs, but also has an abundance pattern that is remarkably similar to that of LS IV-14 degrees 116.
Keywords: stars: abundances; subdwarfs; stars: individual: Feige 46

Heavy metal enrichment in the intermediate He-sdOB pulsator Feige 46 - Latour, M.; Dorsch, M.; Heber, Ulrich (Astronomy & Astrophysics, 2019)
The intermediate He-enriched hot subdwarf star Feige 46 was recently reported as the second member of the V366 Aqr (or He-sdOBV) pulsating class. Feige 46 is very similar to the prototype of the class, LS IV-14 degrees 116, not only in terms of pulsational properties, but also in terms of atmospheric parameters and kinematic properties. LS IV-14 degrees 116 is additionally characterized by a very peculiar chemical composition, with extreme overabundances of the trans-iron elements Ge, Sr, Y, and Zr. We investigate the possibility that the similarity between the two pulsators extends to their chemical composition. We retrieved archived optical and UV spectroscopic observations of Feige 46 and performed an abundance analysis using model atmospheres and synthetic spectra computed with TLUSTY and SYNSPEC. In total, we derived abundances for 16 elements and provide upper limits for four additional elements. Using absorption lines in the optical spectrum of the star we measure an enrichment of more than 10 000x solar for yttrium and zirconium. The UV spectrum revealed that strontium is equally enriched. Our results confirm that Feige 46 is not only a member of the now growing group of heavy metal subdwarfs, but also has an abundance pattern that is remarkably similar to that of LS IV-14 degrees 116.
CRIS-Team WoS Importer:2019-10-04
Keywords: stars: abundances; subdwarfs; stars: individual: Feige 46

Heavy-metal enrichment of intermediate He-sdOB stars: The pulsators Feige 46 and LS IV-14°116 revisited - Dorsch, M.; Latour, M.; Heber, Ulrich; Irrgang, Andreas; Charpinet, S.; Jeffery, C. S. (Astronomy & Astrophysics, 2020)
Hot subdwarf stars of spectral types O and B represent a poorly understood phase in the evolution of low-mass stars, in particular of close compact binaries. A variety of phenomena are observed, which make them important tools for several astronomical disciplines. For instance, the richness of oscillations of many subdwarfs are important for asteroseismology. Furthermore, hot subdwarfs are among the most chemically peculiar stars known. Two intermediate He-rich hot subdwarf stars, LS IV-14 degrees 116 and Feige 46, are particularly interesting, because they show extreme enrichments of heavy elements such as Ge, Sr, Y, and Zr, which are strikingly similar in both stars. In addition, both stars show light oscillations at periods incompatible with standard pulsation theory and form the class of V366 Aqr variables. We investigated whether the similar chemical compositions extend to more complete abundance patterns in both stars and validate the pulsations in Feige 46 using its recent TESS light curve. High-resolution optical and near-ultraviolet spectroscopy are combined with non-local thermodynamical-equilibrium model atmospheres and synthetic spectra calculated withTLUSTY andSYNSPEC to consistently determine detailed metal abundance patterns in both stars. Many previously unidentified lines were identified for the first time with transitions originating from GaIII, GeIII-IV, SeIII, KrIII, SrII-III, YIII, ZrIII-IV, and SnIV, most of which have not yet been observed in any star. The abundance patterns of 19 metals in both stars are almost identical, light metals being only slightly more abundant in Feige 46, while Zr, Sn, and Pb are slightly less enhanced compared to LS IV-14 degrees 116. Both abundance patterns are distinctively different from those of normal He-poor hot subdwarfs of a similar temperature. The extreme enrichment in heavy metals of more than 4 dex compared to the Sun is likely the result of strong atmospheric diffusion processes that operate similarly in both stars while their similar patterns of C, N, O, and Ne abundances might provide clues to their as yet unclear evolutionary history. Finally, we find that the periods of the pulsation modes in Feige 46 are stable to better than P less than or similar to 10(-8) s s(-1). This is not compatible with P predicted for pulsations driven by the -mechanism and excited by helium-shell flashes in a star that is evolving, for example, onto the extended horizontal branch.
CRIS-Team Scopus Importer:2020-11-13
Keywords: Stars: abundances; Stars: chemically peculiar; Stars: individual: Feige 46; Stars: individual: LS IV-14°116; Stars: oscillations; Subdwarfs

Heavy-metal enrichment of intermediate He-sdOB stars: the pulsators Feige 46 and LSIV-14 degrees 116 revisited - Dorsch, M.; Latour, M.; Heber, Ulrich; Irrgang, Andreas; Charpinet, S.; Jeffery, C. S. (Astronomy & Astrophysics, 2020)
Hot subdwarf stars of spectral types O and B represent a poorly understood phase in the evolution of low-mass stars, in particular of close compact binaries. A variety of phenomena are observed, which make them important tools for several astronomical disciplines. For instance, the richness of oscillations of many subdwarfs are important for asteroseismology. Furthermore, hot subdwarfs are among the most chemically peculiar stars known. Two intermediate He-rich hot subdwarf stars, LS IV-14 degrees 116 and Feige 46, are particularly interesting, because they show extreme enrichments of heavy elements such as Ge, Sr, Y, and Zr, which are strikingly similar in both stars. In addition, both stars show light oscillations at periods incompatible with standard pulsation theory and form the class of V366 Aqr variables. We investigated whether the similar chemical compositions extend to more complete abundance patterns in both stars and validate the pulsations in Feige 46 using its recent TESS light curve. High-resolution optical and near-ultraviolet spectroscopy are combined with non-local thermodynamical-equilibrium model atmospheres and synthetic spectra calculated withTLUSTY andSYNSPEC to consistently determine detailed metal abundance patterns in both stars. Many previously unidentified lines were identified for the first time with transitions originating from GaIII, GeIII-IV, SeIII, KrIII, SrII-III, YIII, ZrIII-IV, and SnIV, most of which have not yet been observed in any star. The abundance patterns of 19 metals in both stars are almost identical, light metals being only slightly more abundant in Feige 46, while Zr, Sn, and Pb are slightly less enhanced compared to LS IV-14 degrees 116. Both abundance patterns are distinctively different from those of normal He-poor hot subdwarfs of a similar temperature. The extreme enrichment in heavy metals of more than 4 dex compared to the Sun is likely the result of strong atmospheric diffusion processes that operate similarly in both stars while their similar patterns of C, N, O, and Ne abundances might provide clues to their as yet unclear evolutionary history. Finally, we find that the periods of the pulsation modes in Feige 46 are stable to better than P less than or similar to 10(-8) s s(-1). This is not compatible with P predicted for pulsations driven by the -mechanism and excited by helium-shell flashes in a star that is evolving, for example, onto the extended horizontal branch.
Keywords: stars: abundances; stars: chemically peculiar; stars: oscillations; subdwarfs; stars: individual: LS IV-14 degrees 116; stars: individual: Feige 46

Heavy metals in intermediate He-rich hot subdwarfs: the chemical composition of HZ44 and HD127493 - Dorsch, Matti; Latour, Marilyn; Heber, Ulrich (Astronomy & Astrophysics, 2019)
Context. Hot subluminous stars can be spectroscopically classified as subdwarf B (sdB) and O (sdO) stars. While the latter are predominantly hydrogen deficient, the former are mostly helium deficient. The atmospheres of most sdOs are almost devoid of hydrogen, whereas a small group of hot subdwarf stars of mixed H/He composition exists, showing extreme metal abundance anomalies. Whether such intermediate helium-rich (iHe) subdwarf stars provide an evolutionary link between the dominant classes is an open question.Aims. The presence of strong Ge, Sn, and Pb lines in the UV spectrum of HZ44 suggests a strong enrichment of heavy elements in this iHe-sdO star and calls for a detailed quantitative spectral analysis focusing on trans-iron elements.Methods. Non-local thermodynamical equilibrium model atmospheres and synthetic spectra calculated with TLUSTY/SYNSPEC were combined with high-quality optical, ultraviolet (UV), and far-UV (FUV) spectra of HZ44 and its hotter sibling HD127493 to determine their atmospheric parameters and metal abundance patterns.Results. By collecting atomic data from the literature we succeeded in determining the abundances of 29 metals in HZ44, including the trans-iron elements Ga, Ge, As, Se, Zr, Sn, and Pb and providing upper limits for ten other metals. This makes it the best-described hot subdwarf in terms of chemical composition. For HD127493 the abundance of 15 metals, including Ga, Ge, and Pb and upper limits for another 16 metals were derived. Heavy elements turn out to be overabundant by one to four orders of magnitude with respect to the Sun. Zr and Pb are among the most enriched elements.Conclusions. The C, N, and O abundance for both stars can be explained by the nucleosynthesis of hydrogen burning in the CNO cycle along with the stars' helium enrichment. On the other hand, the heavy-element anomalies are unlikely to be caused by nucleosynthesis. Instead diffusion processes are evoked, with radiative levitation overcoming gravitational settlement of the heavy elements.
Keywords: stars: abundances; stars: atmospheres; stars: individual: HZ 44; stars: individual: HD 127493; stars: evolution; subdwarfs

Heavy metals in intermediate He-rich hot subdwarfs: The chemical composition of HZ 44 and HD 127493 - Dorsch, Matti; Latour, M.; Heber, Ulrich (Astronomy & Astrophysics, 2019)
Context. Hot subluminous stars can be spectroscopically classified as subdwarf B (sdB) and O (sdO) stars. While the latter are predominantly hydrogen deficient, the former are mostly helium deficient. The atmospheres of most sdOs are almost devoid of hydrogen, whereas a small group of hot subdwarf stars of mixed H/He composition exists, showing extreme metal abundance anomalies. Whether such intermediate helium-rich (iHe) subdwarf stars provide an evolutionary link between the dominant classes is an open question. Aims. The presence of strong Ge, Sn, and Pb lines in the UV spectrum of HZ 44 suggests a strong enrichment of heavy elements in this iHe-sdO star and calls for a detailed quantitative spectral analysis focusing on trans-iron elements. Methods. Non-local thermodynamical equilibrium model atmospheres and synthetic spectra calculated with TLUSTY/SYNSPEC were combined with high-quality optical, ultraviolet (UV), and far-UV (FUV) spectra of HZ 44 and its hotter sibling HD 127493 to determine their atmospheric parameters and metal abundance patterns. Results. By collecting atomic data from the literature we succeeded in determining the abundances of 29 metals in HZ 44, including the trans-iron elements Ga, Ge, As, Se, Zr, Sn, and Pb and providing upper limits for ten other metals. This makes it the best-described hot subdwarf in terms of chemical composition. For HD 127493 the abundance of 15 metals, including Ga, Ge, and Pb and upper limits for another 16 metals were derived. Heavy elements turn out to be overabundant by one to four orders of magnitude with respect to the Sun. Zr and Pb are among the most enriched elements. Conclusions. The C, N, and O abundance for both stars can be explained by the nucleosynthesis of hydrogen burning in the CNO cycle along with the stars' helium enrichment. On the other hand, the heavy-element anomalies are unlikely to be caused by nucleosynthesis. Instead diffusion processes are evoked, with radiative levitation overcoming gravitational settlement of the heavy elements.
CRIS-Team Scopus Importer:2019-10-22
Keywords: Stars: abundances; Stars: atmospheres; Stars: evolution; Stars: individual: HD 127493; Stars: individual: HZ 44; Subdwarfs

HESS and Fermi-LAT observations of PSR B1259-63/LS 2883 during its 2014 and 2017 periastron passages - Abdalla, H.; Adam, R.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Ashkar, H.; Backes, M.; Martins, V. Barbosa; Barnard, M.; et al. (Astronomy & Astrophysics, 2020)
Context. PSR B1259-63/LS 2883 is a gamma-ray binary system consisting of a pulsar in an eccentric orbit around a bright Oe stellar-type companion star that features a dense circumstellar disc. The bright broad-band emission observed at phases close to periastron offers a unique opportunity to study particle acceleration and radiation processes in binary systems. Observations at gamma-ray energies constrain these processes through variability and spectral characterisation studies.
CRIS-Team WoS Importer:2020-01-31
Keywords: Pulsars: general; Radiation mechanisms: non-thermal; Shock waves; γ-rays: general; Binaries: general; Astroparticle physics

HESS and Suzaku observations of the Vela X pulsar wind nebula - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Backes, M.; Barnard, M.; Becherini, Y.; Berge, D.; Bernloehr, K.; et al. (Astronomy & Astrophysics, 2019)
Context. Pulsar wind nebulae (PWNe) represent the most prominent population of Galactic very-high-energy gamma-ray sources and are thought to be an efficient source of leptonic cosmic rays. Vela X is a nearby middle-aged PWN, which shows bright X-ray and TeV gamma-ray emission towards an elongated structure called the cocoon.
CRIS-Team WoS Importer:2019-07-23
Keywords: Gamma rays: stars; Pulsars: individual: PSR B0833-45; Radiation mechanisms: non-thermal; Stars: winds; outflows; Acceleration of particles

HESS detection of very high-energy gamma-ray emission from the quasar PKS 0736+017 - Abdalla, H.; Adam, R.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Ashkar, H.; Backes, M.; Martins, V. Barbosa; Barnard, M.; et al. (Astronomy & Astrophysics, 2020)
Context. Flat-spectrum radio-quasars (FSRQs) are rarely detected at very high energies (E& x2004;>=& x2004;100 GeV) due to their low-frequency-peaked spectral energy distributions. At present, only six FSRQs are known to emit very high-energy (VHE) photons, representing only 7% of the VHE extragalactic catalog, which is largely dominated by high-frequency-peaked BL Lacertae objects. Aims. Following the detection of MeV-GeV gamma-ray flaring activity from the FSRQ PKS 0736+017 (z& x2004;=& x2004;0.189) with Fermi-LAT, the H.E.S.S. array of Cherenkov telescopes triggered target-of-opportunity (ToO) observations on February 18, 2015, with the goal of studying the gamma-ray emission in the VHE band. Methods. H.E.S.S. ToO observations were carried out during the nights of February 18, 19, 21, and 24, 2015. Together with Fermi-LAT, the multi-wavelength coverage of the flare includes Swift observations in soft X-ray and optical-UV bands, and optical monitoring (photometry and spectro-polarimetry) by the Steward Observatory, and the ATOM, the KAIT, and the ASAS-SN telescopes. Results. VHE emission from PKS 0736+017 was detected with H.E.S.S. only during the night of February 19, 2015. Fermi-LAT data indicate the presence of a gamma-ray flare, peaking at the time of the H.E.S.S. detection, with a flux doubling timescale of around six hours. The gamma-ray flare was accompanied by at least a 1 mag brightening of the non-thermal optical continuum. No simultaneous observations at longer wavelengths are available for the night of the H.E.S.S. detection. The gamma-ray observations with H.E.S.S. and Fermi-LAT are used to put constraints on the location of the gamma-ray emitting region during the flare: it is constrained to be just outside the radius of the broad-line region r(BLR) with a bulk Lorentz factor Gamma& x2004;similar or equal to& x2004;20, or at the level of the radius of the dusty torus r(torus) with Gamma& x2004;similar or equal to& x2004;60. Conclusions. PKS 0736+017 is the seventh FSRQ known to emit VHE photons, and at z& x2004;=& x2004;0.189 is the nearest so far. The location of the gamma-ray emitting region during the flare can be tightly constrained thanks to opacity, variability, and collimation arguments.
CRIS-Team WoS Importer:2020-02-18
Keywords: Astroparticle physics; Gamma rays: general; Quasars: individual: PKS 0736+017; Relativistic processes

HESS discovery of very high energy gamma-ray emission from PKS 0625-354 - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Andersson, T.; Anguner, E. O.; Arrieta, M.; Aubert, P.; Backes, M.; Balzer, A.; Barnard, M.; et al. (Monthly Notices of the Royal Astronomical Society, 2018)
PKS 0625-354 (z = 0.055) was observed with the four High Energy Stereoscopic System (H.E.S.S.) telescopes in 2012 during 5.5 h. The source was detected above an energy threshold of 200 GeV at a significance level of 6.1 sigma. No significant variability is found in these observations. The source is well described with a power-law spectrum with photon index Gamma = 2.84 +/- 0.50(stat) +/- 0.10(syst) and normalization (at E-0 = 1.0 TeV) N-0(E-0)=(0.58 +/- 0.22(stat) +/- 0.12(syst)) x 10(-12) TeV-1 cm(-2) s(-1). Multiwavelength data collected with Fermi-LAT, Swift-XRT, Swift-UVOT, ATOM and WISE are also analysed. Significant variability is observed only in the Fermi-LAT gamma-ray and Swift-XRT X-ray energy bands. Having a good multiwavelength coverage from radio to very high energy, we performed a broad-band modelling from two types of emission scenarios. The results from a one zone lepto-hadronic and a multizone leptonic models are compared and discussed. On the grounds of energetics, our analysis favours a leptonic multizone model. Models associated to the X-ray variability constraint support previous results, suggesting a BL Lac nature of PKS 0625-354 with, however, a large-scale jet structure typical of a radio galaxy.
Keywords: radiation mechanisms: non-thermal; galaxies: active; galaxies: individual: PKS 0625-354; galaxies: jets; gamma-rays: galaxies

HESS Follow-up Observations of Binary Black Hole Coalescence Events during the Second and Third Gravitational-wave Observing Runs of Advanced LIGO and Advanced Virgo - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Ashkar, H.; Backes, M.; Baghmanyan,; Martins, V. Barbosa; Batzofin, R.; Becherini, Y.; Berge, D.; Bernlohr, K.; et al. (Astrophysical Journal, 2021)
We report on the observations of four well-localized binary black hole (BBH) mergers by the High Energy Stereoscopic System (H.E.S.S.) during the second and third observing runs of Advanced LIGO and Advanced Virgo, O2 and O3. H.E.S.S. can observe 20 deg(2) of the sky at a time and follows up gravitational-wave (GW) events by "tiling" localization regions to maximize the covered localization probability. During O2 and O3, H.E.S.S. observed large portions of the localization regions, between 35% and 75%, for four BBH mergers (GW170814, GW190512_180714, GW190728_064510, and S200224ca). For these four GW events, we find no significant signal from a pointlike source in any of the observations, and we set upper limits on the very high energy (>100 GeV) gamma-ray emission. The 1-10 TeV isotropic luminosity of these GW events is below 10(45) erg s(-1) at the times of the H.E.S.S. observations, around the level of the low-luminosity GRB 190829A. Assuming no changes are made to how follow-up observations are conducted, H.E.S.S. can expect to observe over 60 GW events per year in the fourth GW observing run, O4, of which eight would be observable with minimal latency.
CRIS-Team WoS Importer:2021-12-24

HESS J1741-302: a hidden accelerator in the Galactic plane - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Angüner, E. O.; Arakawa, M.; Armand, C.; Arrieta, M.; Backes, M.; Balzer, A.; Barnard, M.; Becherini, Y.; et al. (Astronomy & Astrophysics, 2018)
The H.E.S.S. Collaboration has discovered a new very high energy (VHE, E > 0.1 TeV) gamma-ray source, HESS J1741-302, located in the Galactic plane. Despite several attempts to constrain its nature, no plausible counterpart has been found so far at X-ray and MeV/GeV gamma-ray energies, and the source remains unidentified. An analysis of 145-h of observations of HESS J1741-302 at VHEs has revealed a steady and relatively weak TeV source (similar to 1% of the Crab Nebula flux), with a spectral index of Gamma = 2.3 +/- 0.2(stat) +/- 0.2(sys), extending to energies up to 10 TeV without any clear signature of a cut-off. In a hadronic scenario, such a spectrum implies an object with particle acceleration up to energies of several hundred TeV. Contrary to most H.E.S.S. unidentified sources, the angular size of HESS J1741-302 is compatible with the H.E.S.S. point spread function at VHEs, with an extension constrained to be below 0.068 degrees at a 99% confidence level. The gamma-ray emission detected by H.E.S.S. can be explained both within a hadronic scenario, due to collisions of protons with energies of hundreds of TeV with dense molecular clouds, and in a leptonic scenario, as a relic pulsar wind nebula, possibly powered by the middle-aged (20 kyr) pulsar PSR B1737-30. A binary scenario, related to the compact radio source 1LC 358.266+0.038 found to be spatially coincident with the best fit position of HESS J1741-302, is also envisaged.
Keywords: gamma rays: ISM; gamma rays: general; cosmic rays; ISM: clouds

HESS J1809-193: A halo of escaped electrons around a pulsar wind nebula? - Aharonian, F.; Ait Benkhali, F.; Aschersleben, J.; Ashkar, H.; Backes, M.; Barbosa Martins, V.; Batzofin, R.; Becherini, Y.; Berge, D.; Boettcher, M.; Boisson, C.; Bolmont, J.; et al. (Astronomy & Astrophysics, 2023)
Context. HESS J1809-193 is an unassociated very-high-energy gamma-ray source located on the Galactic plane. While it has been connected to the nebula of the energetic pulsar PSR J1809-1917, supernova remnants and molecular clouds present in the vicinity also constitute possible associations. Recently, the detection of gamma-ray emission up to energies of similar to 100 TeV with the HAWC observatory has led to renewed interest in HESS J1809-193.Aims. We aim to understand the origin of the gamma-ray emission of HESS J1809-193.Methods. We analysed 93.2 h of data taken on HESS J1809-193 above 0.27 TeV with the High Energy Stereoscopic System (H.E.S.S.), using a multi-component, three-dimensional likelihood analysis. In addition, we provide a new analysis of 12.5 yr of Fermi-LAT data above 1 GeV within the region of HESS J1809-193. The obtained results are interpreted in a time-dependent modelling framework.Results. For the first time, we were able to resolve the emission detected with H.E.S.S. into two components: an extended component (modelled as an elongated Gaussian with a 1-sigma semi-major and semi-minor axis of similar to 0.62 degrees and similar to 0.35 degrees, respectively) that exhibits a spectral cutoff at similar to 13 TeV, and a compact component (modelled as a symmetric Gaussian with a 1-sigma radius of similar to 0.1 degrees) that is located close to PSR J1809-1917 and shows no clear spectral cutoff. The Fermi-LAT analysis also revealed extended gamma-ray emission, on scales similar to that of the extended H.E.S.S. component.Conclusions. Our modelling indicates that based on its spectrum and spatial extent, the extended H.E.S.S. component is likely caused by inverse Compton emission from old electrons that form a halo around the pulsar wind nebula. The compact component could be connected to either the pulsar wind nebula or the supernova remnant and molecular clouds. Due to its comparatively steep spectrum, modelling the Fermi-LAT emission together with the H.E.S.S. components is not straightforward.
CRIS-Team WoS Importer:2023-05-05

H.E.S.S. Limits on Linelike Dark Matter Signatures in the 100 GeV to 2 TeV Energy Range Close to the Galactic Center - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Andersson, T.; Anguener, E. O.; Arrieta, M.; Aubert, P.; Backes, M.; Balzer, A.; Barnard, M.; et al. (Physical Review Letters, 2016)
A search for dark matter linelike signals iss performed in the vicinity of the Galactic Center by the H.E.S.S. experiment on observational data taken in 2014. An unbinned likelihood analysis iss developed to improve the sensitivity to linelike signals. The upgraded analysis along with newer data extend the energy coverage of the previous measurement down to 100 GeV. The 18 h of data collected with the H.E.S.S. array allow one to rule out at 95% C.L. the presence of a 130 GeV line (at l=-1.5°, b=0° and for a dark matter profile centered at this location) previously reported in Fermi-LAT data. This new analysis overlaps significantly in energy with previous Fermi-LAT and H.E.S.S. results. No significant excess associated with dark matter annihilations was found in the energy range of 100 GeV to 2 TeV and upper limits on the gamma-ray flux and the velocity weighted annihilation cross section are derived adopting an Einasto dark matter halo profile. Expected limits for present and future large statistics H.E.S.S. observations are also given.

HESS observations of the flaring gravitationally lensed galaxy PKS 1830-211 - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Arrieta, M.; Backes, M.; Barnard, M.; Becherini, Y.; Tjus, J. Becker; et al. (Monthly Notices of the Royal Astronomical Society, 2019)
PKS 1830-211 is a known macrolensed quasar located at a redshift of z = 2.5. Its highenergy gamma-ray emission has been detected with the Fermi-Large Area Telescope (LAT) instrument and evidence for lensing was obtained by several authors from its high-energy data. Observations of PKS 1830-211 were taken with the High Energy Stereoscopic System (H.E.S.S.) array of Imaging Atmospheric Cherenkov Telescopes in 2014 August, following a flare alert by the Fermi-LAT Collaboration. The H.E.S.S observations were aimed at detecting a gamma-ray flare delayed by 20-27 d from the alert flare, as expected from observations at other wavelengths. More than 12 h of good-quality data were taken with an analysis threshold of similar to 67 GeV. The significance of a potential signal is computed as a function of the date and the average significance over the whole period. Data are compared to simultaneous observations by Fermi-LAT. No photon excess or significant signal is detected. An upper limit on PKS 1830-211 flux above 67 GeV is computed and compared to the extrapolation of the Fermi-LAT flare spectrum.
CRIS-Team WoS Importer:2019-07-26
Keywords: gamma-rays: galaxies; gravitational lensing: strong; diffuse radiation

High-degree gravity modes in the single sdB star HD 4539 - Silvotti, R.; Uzundag, M.; Baran, A. S.; Ostensen, R. H.; Telting, J. H.; Heber, Ulrich; Reed, M. D.; Vuckovic, M. (Monthly Notices of the Royal Astronomical Society, 2019)
HD4539 (alias PG0044 + 097 or EPIC 220641886) is a bright (V = 10.2) long-period V1093 Her-type subdwarf B (sdB) pulsating star that was observed by the Kepler spacecraft in its secondary (K2) mission. We use the K2 light curve (78.7 d) to extract 169 pulsation frequencies, 124 with a robust detection. Most of these frequencies are found in the low-frequency region typical of gravity (g-)modes, but some higher frequencies corresponding to pressure (p-)modes are also detected. Therefore HD4539 is a hybrid pulsator and both the deep and surface layers of the star can potentially be probed through asteroseismology. The lack of any frequency splitting in its amplitude spectrum suggests that HD 4539 has a rotation period longer than the K2 run and/or that it is seen pole-on. From asymptotic period spacing we see many high-degree modes, up to l = 12, in the spectrum of HD 4539, with amplitudes as low as a few ppm. A large fraction of these modes can be identified and for similar to 29 per cent of them we obtain a unique and robust identification corresponding to l <= 8. Our study includes also a new determination of the atmospheric parameters of the star. From low-resolution spectroscopy we obtain T-eff = 22 800 +/- 160 K, log g = 5.20 +/- 0.02, and log(N(He)/N(H)) = -2.34 +/- 0.05. By fitting the SED we obtain T-eff = 23 470(-210)(+650) K, R-star = 0.26 +/- 0.01 R-circle dot, and M-star = 0.40 +/- 0.08 M-circle dot. Moreover, from 11 high-resolution spectra we see the radial velocity variations caused by the stellar pulsations, with amplitudes of approximate to 150 m s(-1) for the main modes, and we can exclude the presence of a companion with a minimum mass higher than a few Jupiter masses for orbital periods below similar to 300 d.
CRIS-Team WoS Importer:2019-10-25

High-density disc reflection spectroscopy of low-mass active galactic nuclei - Mallick, Labani; Fabian, A. C.; Garcia, J. A.; Tomsick, J. A.; Parker, M. L.; Dauser, Thomas; Wilkins, D. R.; De Marco, B.; Steiner, J. F.; Connors, R. M. T.; Mastroserio, G.; Markowitz, A. G.; et al. (Monthly Notices of the Royal Astronomical Society, 2022)
The standard alpha-disc model predicts an anticorrelation between the density of the inner accretion disc and the black hole mass times square of the accretion rate, as seen in higher mass (M-BH > 10(6) M-circle dot) active galactic nuclei (AGNs). In this work, we test the predictions of the alpha-disc model and study the properties of the inner accretion flow for the low-mass end (M-BH approximate to 10(5-6) M-circle dot) of AGNs. We utilize a new high-density disc reflection model where the density parameter varies from n(e) = 10(15) to 10(20) cm(-3) and apply it to the broad-band X-ray (0.3-10 keV) spectra of the low-mass AGN sample. The sources span a wide range of Eddington fractions and are consistent with being sub-Eddington or near-Eddington. The X-ray spectra reveal a soft X-ray excess below similar to 1.5 keV which is well modelled by high-density reflection from an ionized accretion disc of density n(e) similar to 10(18) cm(-3) on average. The results suggest a radiation pressure-dominated disc with an average of 70 per cent fraction of the disc power transferred to the corona, consistent with that observed in higher mass AGNs. We show that the disc density higher than 10(15) cm(-3) can result from the radiation pressure compression when the disc surface does not hold a strong magnetic pressure gradient. We find tentative evidence for a drop in black hole spin at low-mass regimes.
CRIS-Team WoS Importer:2022-06-10

High-density reflection spectroscopy: I. A case study of GX 339-4 - Jiang, Jiachen; Fabian, Andrew C.; Wang, Jingyi; Walton, Dominic J.; Garcia, Javier; Parker, Michael L.; Steiner, James F.; Tomsick, John A. (Monthly Notices of the Royal Astronomical Society, 2019)
We present a broad-band spectral analysis of the black hole binary GX 339-4 with NuSTAR and Swift using high-density reflection model. The observations were taken when the source was in low-flux (LF) hard states during the outbursts in 2013 and 2015, and in a very high-flux (HF) soft state in 2015. The high-density reflection model can explain its LF spectra with no requirement for an additional low temperature thermal component. This model enables us to constrain the density in the disc surface of GX 339-4 in different flux states. The disc density in the LF state is log (ne/ cm−3) ≈ 21, 100 times higher than the density in the HF state (log (ne/ cm−3) = 18.93+−001216). A close-to-solar iron abundance is obtained by modelling the LF and HF broad-band spectra with variable density reflection model (ZFe = 1.50+−001204Z and ZFe = 1.05+−001715Z, respectively).
CRIS-Team Scopus Importer:2021-04-20
Keywords: Accretion; Accretion discs; X-rays: binaries; X-rays: individual (GX 339-4)

High Density Reflection Spectroscopy - II. The density of the inner black hole accretion disc in AGN - Jiang, Jiachen; Fabian, Andrew C.; Dauser, Thomas; Gallo, Luigi; Garcia, Javier; Kara, Erin; Parker, Michael L.; Tomsick, John A.; Walton, Dominic J.; Reynolds, Christopher S. (Monthly Notices of the Royal Astronomical Society, 2019)
We present a high density disc reflection spectral analysis of a sample of 17 Seyfert 1 galaxies to study the inner disc densities at different black hole mass scales and accretion rates. All the available XMM-Newton observations in the archive are used. OM observations in the optical/UV band are used to estimate their accretion rates. We find that 65 per cent of sources in our sample show a disc density significantly higher than ne = 1015 cm-3, which was assumed in previous reflection-based spectral analyses. The best-fitting disc densities show an anticorrelation with black hole mass and mass accretion rate. High density disc reflection model can successfully explain the soft excess emission and significantly reduce inferred iron abundances. We also compare our black hole spin and disc inclination angle measurements with previous analyses.
CRIS-Team Scopus Importer:2021-04-20
Keywords: Accretion; accretion discs; Black hole physics; Galaxies: Seyfert; X-rays: Galaxies

High-energy neutrino follow-up search of gravitational wave event GW150914 with ANTARES and IceCube - Adrian-Martinez, S.; Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J-J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; et al. (Physical Review D - Particles, Fields, Gravitation and Cosmology, 2016)
We present the high-energy-neutrino follow-up observations of the first gravitational wave transient GW150914 observed by the Advanced LIGO detectors on September 14, 2015. We search for coincident neutrino candidates within the data recorded by the IceCube and Antares neutrino detectors. A possible joint detection could be used in targeted electromagnetic follow-up observations, given the significantly better angular resolution of neutrino events compared to gravitational waves. We find no neutrino candidates in both temporal and spatial coincidence with the gravitational wave event. Within ±500 s of the gravitational wave event, the number of neutrino candidates detected by IceCube and Antares were three and zero, respectively. This is consistent with the expected atmospheric background, and none of the neutrino candidates were directionally coincident with GW150914. We use this nondetection to constrain neutrino emission from the gravitational-wave event.

Highly charged ions in a new era of high resolution X-ray astrophysics - Hell, Natalie; Beiersdorfer, Peter; Brown, Gregory V.; Eckart, Megan E.; Kelley, Richard L.; Kilbourne, Caroline A.; Leutenegger, Maurice A.; Lockard, Thomas E.; Porter, F. Scott; Wilms, Jörn (X-Ray Spectrometry, 2019)
X-ray astronomy and ground-based atomic physics have a long history of fruitful collaboration: Sound understanding of the underlying atomic physics is the key to reliable interpretation of the spectra from celestial sources; conversely, astronomical spectra have been used to benchmark and advance atomic physics. This interplay is about to become even more important as we enter a new era of high-resolution X-ray astrophysics with large effective collection area. Although high-resolution observations with the gratings on the Chandra and XMM-Newton observatories continue to drive new science, upcoming planned and proposed missions will open up new discovery space in the near future that is currently challenging to access: high-resolution spectroscopy on extended sources, in the Fe K band, and on short time scales. This review summarizes open questions in these areas and the design parameters for the Hitomi, XRISM, Athena, and Arcus observatories. The expected high quality of spectra taken with these observatories puts new constraints on the accuracy of atomic reference data required to take full advantage of the diagnostic potential of these spectra.
CRIS-Team Scopus Importer:2019-11-19

High-Precision Determination of Oxygen Kα Transition Energy Excludes Incongruent Motion of Interstellar Oxygen - Leutenegger, M. A.; Kühn, S.; Micke, P.; Steinbrügge, R.; Stierhof, Jakob; Shah, C.; Hell, N.; Bissinger, Matthias; Hirsch, Maria; Ballhausen, Ralf; Lang, Melanie; Gräfe, Christina; et al. (Physical Review Letters, 2020)
We demonstrate a widely applicable technique to absolutely calibrate the energy scale of x-ray spectra with experimentally well-known and accurately calculable transitions of highly charged ions, allowing us to measure the K-shell Rydberg spectrum of molecular O2 with 8 meV uncertainty. We reveal a systematic ∼450 meV shift from previous literature values, and settle an extraordinary discrepancy between astrophysical and laboratory measurements of neutral atomic oxygen, the latter being calibrated against the aforementioned O2 literature values. Because of the widespread use of such, now deprecated, references, our method impacts on many branches of x-ray absorption spectroscopy. Moreover, it potentially reduces absolute uncertainties there to below the meV level.
CRIS-Team Scopus Importer:2020-12-25

High Resolution Photoexcitation Measurements Exacerbate the Long-Standing Fe XVII Oscillator Strength Problem - Kuehn, Steffen; Shah, Chintan; Lopez-Urrutia, Jose R. Crespo; Fujii, Keisuke; Steinbruegge, Rene; Stierhof, Jakob; Togawa, Moto; Harman, Zoltan; Oreshkina, Natalia S.; Cheung, Charles; Kozlov, Mikhail G.; Porsev, Sergey G.; et al. (Physical Review Letters, 2020)
For more than 40 years, most astrophysical observations and laboratory studies of two key soft x-ray diagnostic 2p-3d transitions, 3C and 3D, in Fe XVII ions found oscillator strength ratios f(3C)/f(3D) disagreeing with theory, but uncertainties had precluded definitive statements on this much studied conundrum. Here, we resonantly excite these lines using synchrotron radiation at PETRA III, and reach, at a millionfold lower photon intensities, a 10 times higher spectral resolution, and 3 times smaller uncertainty than earlier work. Our final result of f(3C)/f(3D)=3.09(8)(6) supports many of the earlier clean astrophysical and laboratory observations, while departing by five sigmas from our own newest large-scale ab initio calculations, and excluding all proposed explanations, including those invoking nonlinear effects and population transfers.
CRIS-Team Scopus Importer:2021-04-19

High variability in Vela X-1: giant flares and off states - Kreykenbohm, Ingo; Wilms, Jörn; Kretschmar, Peter; Torrejon, J. M.; Pottschmidt, K.; Hanke, Manfred; Santangelo, A.; Ferrigno, Carlo; Staubert, R. (Astronomy & Astrophysics, 2008)
Aims. We investigate the spectral and temporal behavior of the high mass X-ray binary Vela X-1 during a phase of high activity, with special focus on the observed giant flares and off states.Methods. INTEGRAL observed Vela X-1 in a long almost uninterrupted observation for two weeks in 2003 Nov/Dec. The data were analyzed with OSA 7.0 and FTOOLS 6.2. We derive the pulse period, light curves, spectra, hardness ratios, and hardness intensity diagrams, and study the eclipse.Results. In addition to an already high activity level, Vela X-1 exhibited several intense flares, the brightest ones reaching a maximum intensity of more than 5 Crab in the 20-40 keV band and several off states where the source was no longer detected by INTEGRAL. We determine the pulse period to be 283.5320 +/- 0.0002 s, which is stable throughout the entire observation. Analyzing the eclipses provided an improvement in the ephemeris. Spectral analysis of the flares indicates that there appear to be two types of flares: relatively brief flares, which can be extremely intense and show spectral softening, in contrast to high intensity states, which are longer and show no softening.Conclusions. Both flares and off states are interpreted as being due to a strongly structured wind of the optical companion. When Vela X-1 encounters a cavity with strongly reduced density, the flux will drop triggering the onset of the propeller effect, which inhibits further accretion, giving rise to off states. The sudden decrease in the density of the material required to trigger the propeller effect in Vela X-1 is of the same order as predicted by theoretical papers about the densities in OB star winds. A similarly structured wind can produce giant flares when Vela X-1 encounters a dense blob in the wind.
Keywords: X-rays: stars; stars: flare; stars: pulsars: individual: Vela X-1; stars: magnetic fields

HILIGT, Upper Limit Servers II — Implementing the data servers - König, Ole; Saxton, R. D.; Kretschmar, P.; Angelini, L.; Belanger, G.; Evans, P. A.; Freyberg, M. J.; Savchenko, V.; Traulsen, I.; Wilms, Jörn (Astronomy and Computing, 2022)
The High-Energy Lightcurve Generator (HILIGT) is a new web-based tool which allows the user to generate long-term lightcurves of X-ray sources. It provides historical data and calculates upper limits from image data in real-time. HILIGT utilizes data from twelve satellites, both modern missions such as XMM-Newton and Swift, and earlier facilities such as ROSAT, EXOSAT, Einstein or Ariel V. Together, this enables the user to query 50 years of X-ray data and, for instance, study outburst behavior of transient sources. In this paper we focus on the individual back-end servers for each satellite, detailing the software layout, database design, catalog calls, and image footprints. We compile all relevant calibration information of these missions and provide an in-depth summary of the details of X-ray astronomical instrumentation and data.
CRIS-Team Scopus Importer:2021-12-24
Keywords: Aperture photometry; Catalogs; Instrumentation; Surveys; Upper limit; X-rays

HILIGT, upper limit servers I — Overview - Saxton, R. D.; König, Ole; Descalzo, M.; Belanger, G.; Kretschmar, P.; Gabriel, C.; Evans, P. A.; Ibarra, A.; Colomo, E.; Sarmiento, M.; Salgado, J.; Agrafojo, A.; et al. (Astronomy and Computing, 2022)
The advent of all-sky facilities, such as the Neil Gehrels Swift observatory, the All Sky Automated Search for Supernovae (ASAS-SN), eROSITA and Gaia has led to a new appreciation of the importance of transient sources in solving outstanding astrophysical questions. Identification and catalogue cross-matching of transients has been eased over the last two decades by the Virtual Observatory but we still lack a client capable of providing a seamless, self-consistent, analysis of all observations made of a particular object by current and historical facilities. HILIGT is a web-based interface which polls individual servers written for XMM-Newton, INTEGRAL and other missions, to find the fluxes, or upper limits, from all observations made of a given target. These measurements are displayed as a table or a time series plot, which may be downloaded in a variety of formats. HILIGT currently works with data from X-ray and Gamma-ray observatories.
CRIS-Team Scopus Importer:2021-12-24
Keywords: Aperture photometry; Catalogs; Instrumentation: detectors; Surveys; Upper limit; X-rays: general

HIP 60350: A supernova ejected hyper-runaway star? - Irrgang, Andreas; Przybilla, Norbert; Heber, Ulrich; Nieva, M. Fernanda; Schuh, Sonja (Proceedings of Science, 2010)
Halo runaway stars, i.e., young, massive, high-velocity stars in the halo of our Galaxy, are widely supposed to be the result of an ejection event from the Galactic disk. The three most likely ejection scenarios are tidal disruptions of binary systems by the supermassive black hole at the Galactic center, dynamical interactions in star clusters, e.g., binary-binary encounters, or a supernova explosion disrupting a binary system. Here, we present a detailed spectroscopic and kinematic analysis of the runaway B star HIP 60350 to discuss the three competing mechanisms. Using spectrum synthesis techniques that allow for deviations from local thermal equilibrium, we derived chemical elemental abundances from high resolution spectra. The analysis of HIP 60350 revealed an outstanding high Galactic rest-frame velocity of 530±35kms-1 slightly exceeding the local Galactic escape velocity and thus qualifying the star as a hyper-runaway candidate, i.e., an unbound runaway star. The kinematically predicted birthplace within the disk is located ∼ 6kpc away from the Galactic center excluding this region as the star's spatial origin and in this way the involvement of the central supermassive black hole. Instead, the obtained chemical abundance pattern shows hints of α-element enhancement being characteristic of supernova debris. HIP 60350 might be the surviving secondary of a massive, close binary system disrupted by the primary's supernova explosion. © Copyright owned by the author(s).
CRIS-Team Scopus Importer:2020-12-21

Hot subdwarf binaries from the MUCHFUSS project Analysis of 12 new systems and a study of the short-period binary population - Kupfer, Thomas; Geier, S.; Heber, Ulrich; Ostensen, R. H.; Barlow, B. N.; Maxted, P. F. L.; Heuser, Christian; Schaffenroth, Veronika; Gaensicke, B. T. (Astronomy & Astrophysics, 2015)
The project Massive Unseen Companions to Hot Faint Underluminous Stars from SDSS (MUCHFUSS) aims at finding hot subdwarf stars with massive compact companions like massive white dwarfs (M > 1.0 M-circle dot), neutron stars, or stellar-mass black holes. The existence of such systems is predicted by binary evolution theory, and recent discoveries indicate that they exist in our Galaxy. We present orbital and atmospheric parameters and put constraints on the nature of the companions of 12 close hot subdwarf B star (sdB) binaries found in the course of the MUCHFUSS project. The systems show periods between 0.14 and 7.4 days. In nine cases the nature of the companions cannot be constrained unambiguously whereas three systems most likely have white dwarf companions. We find that the companion to SDSS J083006.17+475150.3 is likely to be a rare example of a low-mass helium-core white dwarf. SDSS J095101.28+034757.0 shows an excess in the infrared that probably originates from a third companion in a wide orbit, which makes this system the second candidate hierarchical triple system containing an sdB star. SDSS J113241.58-063652.8 is the first helium deficient sdO star with a confirmed close companion. This study brings to 142 the number of sdB binaries with orbital periods of less than 30 days and with measured mass functions. We present an analysis of the minimum companion mass distribution and show that it is bimodal. One peak around 0.1 M-circle dot corresponds to the low-mass main sequence (dM) and substellar companions. The other peak around 0.4 M-circle dot corresponds to the white dwarf companions. The derived masses for the white dwarf companions are significantly lower than the average mass for single carbon-oxygen white dwarfs. In a T-eff - log g diagram of sdB+dM companions, we find signs that the sdB components are more massive than the rest of the sample. The full sample was compared to the known population of extremely low-mass white dwarf binaries as well as short-period white dwarfs with main sequence companions. Both samples show a significantly different companion mass distribution indicating either different selection effects or different evolutionary paths. We identified 16 systems where the dM companion will fill its Roche Lobe within a Hubble time and will evolve into a cataclysmic variable; two of them will have a brown dwarf as donor star. Twelve systems with confirmed white dwarf companions will merge within a Hubble time, two of them having a mass ratio to evolve into a stable AMCVn-type binary and another two which are potential supernova Ia progenitor systems. The remaining eight systems will most likely merge and form RCrB stars or massive C/O white dwarfs depending on the structure of the white dwarf companion.
Keywords: subdwarfs; binaries: close

Hot subdwarf binaries - Masses and nature of their heavy compact companions - Geier, Stephan; Heber, Ulrich; Edelmann, Heinz; Kupfer, Thomas; Napiwotzki, Ralf; Podsiadlowski, Philipp (2009)
Neutron stars and stellar-mass black holes are the remnants of massive stars, which ended their lives in supernova explosions. These exotic objects can only be studied in relatively rare cases. If they axe interacting with close companions they become bright X-ray sources. If they are neutron stars, they may be detected as pulsars. Only a few hundred such systems are presently known in the Galaxy. However, there should be many more binaries with basically invisible compact objects in non-interacting binaries.Here we report the discovery of unseen compact companions to hot subdwarfs in close binary systems. Hot subdwarfs are evolved helium-core-burning stars that have lost most of their hydrogen envelopes, often due to binary interactions. Using high-resolution spectra and assuming tidal synchronisation of the subdwarfs, we were able to constrain the companion masses of 31 binaries. While most hot subdwarf binaries have white-dwarf or late-type main sequence companions, as predicted by binaxy evolution models, at least 5% of the observed subdwarfs must have very massive companions: unusually heavy white dwarfs, neutron stars and, in some cases, even black holes. We present evolutionary models which show that such binaries can indeed form if the system has evolved through two common-envelope phases. This new connection between hot subdwarfs, which are numerous in the Galaxy, and massive compact objects may lead to a tremendous increase in the number of known neutron stars and black holes and shed some light on this dark population and its evolutionary link to the X-ray binaxy population.

Hot subdwarfs in binary systems and the nature of their unseen companions - Geier, Stephan; Heber, Ulrich; Tillich, A.; Hirsch, H.; Edelmann, Heinz; Schaffenroth, Veronika; Kupfer, Thomas; Mueller, S.; Maxted, P. F. L.; Ostensen, R.; Podsiadlowski, P.; Marsh, T.; et al. (Astrophysics and Space Science, 2010)
A large fraction of the sdB stars reside in short period binaries. It is therefore clear that binary evolution plays an important role in the still unsolved problem of hot subdwarf formation. Here we present new results from different projects devoted to the analysis of sdBs in close binaries. The nature and masses of the unseen companions of 31 sdBs have been constrained by an analysis of high resolution spectra. In the course of this study candidate systems with massive compact companions have been discovered. The HYPERMUCHFUSS project aims at finding such systems making use of the huge spectral database of SDSS. A multi-site follow-up campaign of promising radial velocity variable sdBs started in 2009 and preliminary results are shown here. The most recent discovery of a substellar companion to the bright sdB HD 149382 may provide new evidence for the decisive role of low mass companions for sdB formation in general. A mysterious IR-excess has been detected, which may be caused by this otherwise invisible companion. Another low mass companion has been found to orbit the sdB star EGB 5 within 16.5 days. The space mission CoRoT is performing wide field and high precision photometry. First preliminary results from a spectroscopic survey of the COROT fields are also reported.
Keywords: Stars: horizontal branch; Stars: binaries

Hot subdwarf stars and their connection to thermonuclear supernovae - Geier, S.; Kupfer, Thomas; Ziegerer, Eva; Heber, Ulrich; Nemeth, Peter; Irrgang, Andreas (Journal of Physics: Conference Series, 2016)
Hot subdwarf stars (sdO/Bs) are evolved core helium-burning stars with very thin hydrogen envelopes, which can be formed by common envelope ejection. Close sdB binaries with massive white dwarf (WD) companions are potential progenitors of thermonuclear supernovae type Ia (SN Ia). We discovered such a progenitor candidate as well as a candidate for a surviving companion star, which escapes from the Galaxy. More candidates for both types of objects have been found by crossmatching known sdB stars with proper motion and light curve catalogues. The Gaia mission will provide accurate astrometry and light curves of all the stars in our hot subdwarf sample and will allow us to compile a much larger all-sky catalogue of those stars. In this way we expect to find hundreds of progenitor binaries and ejected companions.
CRIS-Team Scopus Importer:2020-12-21

Hot subdwarf stars in close-up view: II. Rotational properties of single and wide binary subdwarf B stars - Geier, Stephan; Heber, Ulrich (Astronomy & Astrophysics, 2012)
Subluminous B stars (sdBs) form the extremely hot end of the horizontal branch and are therefore related to the blue horizontal branch (BHB) stars. While the rotational properties of BHB stars have been investigated extensively, studies of sdB stars have concentrated on close binaries that are influenced by tidal interactions between their components. Here we present a study of 105 sdB stars, which are either single stars or in wide binaries where tidal effects become negligible. The projected rotational velocities have been determined by measuring the broadening of metal lines using high-resolution optical spectra. All stars in our sample are slow rotators (v rotsini < 10< kms -1). Furthermore, the v rotsini-distributions of single sdBs are similar to those of hot subdwarfs in wide binaries with main-sequence companions as well as close binary systems with unseen companions and periods exceeding ≈ 1.2< d. We show that blue horizontal and extreme horizontal branch stars are also related in terms of surface rotation and angular momentum. Hot BHB stars (T eff > 11 500< K) with diffusion-dominated atmospheres are slow rotators like the hot subdwarf stars located on the extreme horizontal branch, which lost more envelope and therefore angular momentum in the red-giant phase. The uniform rotation distributions of single and wide binary sdBs pose a challenge to our understanding of hot subdwarf formation. Especially the high fraction of helium white dwarf mergers predicted by theory seems to be inconsistent with the results presented here. © 2012 ESO.
CRIS-Team Scopus Importer:2020-12-21
Keywords: Binaries: spectroscopic; Stars: rotation; Subdwarfs

Hot subdwarf stars in close-up view: I. Rotational properties of subdwarf B stars in close binary systems and nature of their unseen companions - Geier, Stephan; Heber, Ulrich; Podsiadlowski, Ph.; Edelmann, Heinz; Napiwotzki, R.; Kupfer, Thomas; Müller, Sebastian (Astronomy & Astrophysics, 2010)
The origin of hot subdwarf B stars (sdBs) is still unclear. About half of the known sdBs are in close binary systems for which common envelope ejection is the most likely formation channel. Little is known about this dynamic phase of binary evolution. Since most of the known sdB systems are single-lined spectroscopic binaries, it is difficult to derive masses and unravel the companions' nature, which is the aim of this paper. Due to the tidal influence of the companion in close binary systems, the rotation of the primary becomes synchronised to its orbital motion. In this case it is possible to constrain the mass of the companion, if the primary mass, its projected rotational velocity as well as its surface gravity are known. For the first time we measured the projected rotational velocities of a large sdB binary sample from high resolution spectra. We analysed a sample of 51 sdB stars in close binaries, 40 of which have known orbital parameters comprising half of all such systems known today. Synchronisation in sdB binaries is discussed both from the theoretical and the observational point of view. The masses and the nature of the unseen companions could be constrained in 31 cases. We found orbital synchronisation most likely to be established in binaries with orbital periods shorter than 1.2 d. Only in five cases it was impossible to decide whether the sdB's companion is a white dwarf or an M dwarf. The companions to seven sdBs could be clearly identified as late M stars. One binary may have a brown dwarf companion. The unseen companions of nine sdBs are white dwarfs with typical masses. The mass of one white dwarf companion is very low. In eight cases (including the well known system KPD1930+2752) the companion mass exceeds 0.9∼M-, four of which even exceed the Chandrasekhar limit indicating that they may be neutron stars. Even stellar mass black holes are possible for the most massive companions. The distribution of the inclinations of the systems with low mass companions appears to be consistent with expectations, whereas a lack of high inclinations becomes obvious for the massive systems. We show that the formation of such systems can be explained with common envelope evolution and present an appropriate formation channel including two phases of unstable mass transfer and one supernova explosion. The sample also contains a candidate post-RGB star, which rotates fast despite its long orbital period. The post-RGB stars are expected to spin-up caused by their ongoing contraction. The age of the sdB is another important factor. If the EHB star is too young, the synchronisation process might not be finished yet. Estimating the ages of the target stars from their positions on the EHB band, we found PG 2345+318, which is known not to be synchronised, to lie near the zero-age extreme horizontal branch as are the massive candidates PG 1232-136, PG 1432+159 and PG 1101+249. These star may possibly be too young to have reached synchronisation. The derived large fraction of putative massive sdB binary systems in low inclination orbits is inconsistent with theoretical predictions. Even if we dismiss three candidates because they may be too young and assume that the other sdB primaries are of low mass, PG 1743+477 and, in particular, HE 0532-4503 remain as candidates whose companions may have masses close to or above the Chandrasekhar limit. X-ray observations and accurate photometry are suggested to clarify their nature. As high inclination systems must also exist, an appropriate survey has already been launched to find such binaries. © 2010 ESO.
CRIS-Team Scopus Importer:2020-12-21
Keywords: Binaries: spectroscopic; stars: rotation; subdwarfs

Hot subdwarf stars in close-up view: IV. Helium abundances and the 3he isotopic anomaly of subdwarf b stars - Geier, Stephan; Heber, Ulrich; Edelmann, Heinz; Morales-Rueda, L.; Kilkenny, D.; O'Donoghue, D.; Marsh, T. R.; Copperwheat, Christopher (Astronomy & Astrophysics, 2013)
Atmospheric parameters and helium abundances of 44 bright subdwarf B stars have been determined. More than half of our sample consists of newly discovered stars from the Edinburgh Cape survey. We showed that effective temperatures and surface gravities can be derived from high resolution echelle spectra with sufficient accuracy. Systematic uncertainties have been determined by comparing the parameters derived from the high resolution data with the ones derived from medium resolution spectra. Helium abundances have been measured with high accuracy. Besides the known correlation of helium abundance with temperature, two distinct sequences in helium abundance have been confirmed. Significant isotopic shifts of helium lines due to an enrichment in 3He have been found in the spectra of 8 subluminous B stars (sdBs). Most of these stars cluster in a small temperature range between 27 000 K and 31 000 K very similar to the known 3He-rich main sequence B stars, which also cluster in such a small strip, but at different temperatures. Both the helium sequences and the isotopic anomaly are discussed. © 2013 ESO.
CRIS-Team Scopus Importer:2020-12-21
Keywords: Stars: abundances; Stars: atmospheres; Stars: fundamental parameters; Subdwarfs

Hot subdwarf stars in the Galactic halo Tracers of prominent events in late stellar evolution - Geier, Stephan; Kupfer, Thomas; Schaffenroth, Veronika; Heber, Ulrich (2016)
Hot subdwarf stars (sdO/Bs) are the stripped cores of red giants located at the bluest extension of the horizontal branch. They constitute the dominant population of UV-bright stars in old stellar environments and are most likely formed by binary interactions. We perform the first systematic, spectroscopic analysis of a sample of those stars in the Galactic halo based on data from SDSS. In the course of this project we discovered 177 close binary candidates. A significant fraction of the sdB binaries turned out to have close substellar companions, which shows that brown dwarfs and planets can significantly influence late stellar evolution. Close hot subdwarf binaries with massive white dwarf companions on the other hand are good candidates for the progenitors of type Ia supernovae. We discovered a hypervelocity star, which not only turned out to be the fastest unbound star known in our Galaxy, but also the surviving companion of such a supernova explosion.
Keywords: binaries: spectroscopic; binaries: eclipsing; stars: subdwarfs; stars: brown dwarfs

Hot Subluminous Stars - Heber, Ulrich; Heber, Ulrich (Publications of the Astronomical Society of the Pacific, 2016)
Hot subluminous stars of spectral type B and O are core helium-burning stars at the blue end of the horizontal branch or have evolved even beyond that stage. Most hot subdwarf stars are chemically highly peculiar and provide a laboratory to study diffusion processes that cause these anomalies. The most obvious anomaly lies with helium, which may be a trace element in the atmosphere of some stars (sdB, sdO) while it may be the dominant species in others (He-sdB, He-sdO). Strikingly, the distribution in the Hertzsprung-Russell diagram of He-rich versus He-poor hot subdwarf stars of the globular clusters omega Cen and NGC. 2808 differ from that of their field counterparts. The metal-abundance patterns of hot subdwarfs are typically characterized by strong deficiencies of some lighter elements as well as large enrichments of heavy elements. A large fraction of sdB stars are found in close binaries with white dwarf or very low-mass main sequence companions, which must have gone through a common-envelope (CE) phase of evolution. Because the binaries are detached they provide a clean-cut laboratory to study this important but yet poorly understood phase of stellar evolution. Hot subdwarf binaries with sufficiently massive white dwarf companions are viable candidate progenitors of type Ia supernovae both in the double degenerate as well as in the single degenerate scenario as helium donors for double detonation supernovae. The hyper-velocity He-sdO star US. 708 may be the surviving donor of such a double detonation supernova. Substellar companions to sdB stars have also been found. For HW. Vir systems the companion mass distribution extends from the stellar into the brown dwarf regime. A giant planet to the acoustic-mode pulsator V391 Peg was the first discovery of a planet that survived the red giant evolution of its host star. Evidence for Earth-size planets to two pulsating sdB stars have been reported and circumbinary giant planets or brown dwarfs have been found around HW. Vir systems from eclipse timings. The high incidence of circumbinary substellar objects suggests that most of the planets are formed from the remaining CE material (second generation planets). Several types of pulsating star have been discovered among hot subdwarf stars, the most common are the gravity-mode sdB pulsators (V1093 Her) and their hotter siblings, the p-mode pulsating V361 Hya stars. Another class of multi-periodic pulsating hot subdwarfs has been found in the globular cluster omega Cen that is unmatched by any field star. Asteroseismology has advanced enormously thanks to the high-precision Kepler photometry and allowed stellar rotation rates to be determined, the interior structure of gravity-mode pulsators to be probed and stellar ages to be estimated. Rotation rates turned out to be unexpectedly slow calling for very efficient angular momentum loss on the red giant branch or during the helium core flash. The convective cores were found to be larger than predicted by standard stellar evolution models requiring very efficient angular momentum transport on the red giant branch. The masses of hot subdwarf stars, both single or in binaries, are the key to understand the stars' evolution. A few pulsating sdB stars in eclipsing binaries have been found that allow both techniques to be applied for mass determination. The results, though few, are in good agreement with predictions from binary population synthesis calculations. New classes of binaries, hosting so-called extremely low mass (ELM) white dwarfs (M < 0.3 M-circle dot), have recently been discovered, filling a gap in the mosaic of binary stellar evolution. Like most sdB stars the ELM white dwarfs are the stripped cores of red giants, the known companions are either white dwarfs, neutron stars (pulsars) or F-or A-type main sequence stars ("EL CVn" stars). In the near future, the Gaia mission will provide high-precision astrometry for a large sample of subdwarf stars to disentangle the different stellar populations in the field and to compare the field subdwarf population with the globular clusters' hot subdwarfs. New fast-moving subdwarfs will allow the mass of the Galactic dark matter halo to be constrained and additional unbound hyper-velocity stars may be discovered.
Keywords: binaries: close; stars: abundances; stars: evolution; stars: oscillations; subdwarfs; white dwarfs

Hot subluminous stars: Highlights from the MUCHFUSS and Kepler missions - Heber, Ulrich; Geier, Stephan; Gaensicke, Boris T (EPJ Web of Conferences, 2013)
Research into hot subdwarf stars is progressing rapidly. We present recent important discoveries. First we review the knowledge about magnetic fields in hot subdwarfs and highlight the first detection of a highly-magnetic, helium-rich sdO star. We briefly summarize recent discoveries based on Kepler light curves and finally introduce the closest known sdB+WD binary discovered by the MUCHFUSS project and discuss its relevance as a progenitor of a double-detonation type Ia supernova. © 2013 Owned by the authors, published by EDP Sciences.
CRIS-Team Scopus Importer:2020-12-21

Hubble spectroscopy of LB-1: Comparison with B+black-hole and Be+stripped-star models - Lennon, D. J.; Maíz Apellániz, J.; Irrgang, Andreas; Bohlin, R.; Deustua, S.; Dufton, P. L.; Simón-DÍaz, S.; Herrero, A.; Casares, J.; Muñoz-Darias, T.; Smartt, S. J.; González Hernández, J. I.; et al. (Astronomy & Astrophysics, 2021)
Context. LB-1 (alias ALS 8775) has been proposed as either an X-ray dim B-type star plus black hole (B+BH) binary or a Be star plus an inflated stripped star (Be+Bstr) binary. The latter hypothesis contingent upon the detection and characterization of the hidden broad-lined star in a composite optical spectrum. Aims. Our study is aimed at testing the published B+BH (single star) and Be+Bstr (binary star) models using a flux-calibrated UV-optical-IR spectrum. Methods. The Space Telescope Imaging Spectrograph (STIS) on board the Hubble Space Telescope (HST) was used to obtain a flux-calibrated spectrum with an accuracy of ∼1%. We compared these data with non-local thermal equilibrium (non-LTE) spectral energy distributions (SED) and line profiles for the proposed models. The Hubble data, together with the Gaia EDR3 parallax and a well-determined extinction, were used to provide tight constraints on the properties and stellar luminosities of the LB-1 system. In the case of the Be+Bstr model we adopted the published flux ratio for the Be and Bstr stars, re-determined the Teff of the Bstr using the silicon ionization balance, and inferred Teff for the Be star from the fit to the SED. Results. The UV data strongly constrain the microturbulence velocity to ≲ 2 km s-1 for the stellar components of both models. We also find stellar parameters consistent with previous results, but with greater precision enabled by the Hubble SED. For the B+BH single-star model, we find the parameters (Teff, log(L/L⊙ ), Mspec/M⊙ ) of the B-type star to be (15 300 ± 300 K, 3.23-0.10+0.09, 5.2-1.4+1.8). For the Bstr star we obtain (12 500 ± 100 K, 2.70-0.09+0.09, 0.8-0.3+0.5), and for the Be star (18 900 ± 200 K, 3.04-0.09+0.09, 3.4-1.8+3.5). While the Be+Bstr model is a better fit to the He » I lines and cores of the Balmer lines in the optical, the B+BH model provides a better fit to the Si » IV resonance lines in the UV. The analysis also implies that the Bstr star has roughly twice the solar silicon abundance, which is difficult to reconcile with a stripped star origin. The Be star, on the other hand, has a rather low luminosity and a spectroscopic mass that is inconsistent with its possible dynamical mass. Conclusions. We provide tight constraints on the stellar luminosities of the Be+Bstr and B+BH models. For the former, the Bstr star appears to be silicon-rich, while the notional Be star appears to be sub-luminous for a classical Be star of its temperature and the predicted UV spectrum is inconsistent with the data. This latter issue can be significantly improved by reducing the Teff and radius of the Be star, at the cost, however, of a different mass ratio as a result. In the B+BH model, the single B-type spectrum is a good match to the UV spectrum. Adopting a mass ratio of 5.1 ± 0.1, from the literature, implies a BH mass of ∼21-8+9 M⊙ .
CRIS-Team Scopus Importer:2021-06-18
Keywords: Binaries: spectroscopic; Stars: black holes; Stars: early-type; Stars: evolution; Stars: fundamental parameters; Techniques: spectroscopic

Hunting for the nature of the enigmatic narrow-line Seyfert 1 galaxy PKS 2004-447 - Berton, Marco; Peluso, G.; Marziani, Paola; Komossa, S.; Foschini, L.; Ciroi, S.; Chen, S.; Congiu, E.; Gallo, L. C.; Bjorklund, I.; Crepaldi, L.; Di Mille, F.; et al. (Astronomy & Astrophysics, 2021)
Narrow-line Seyfert 1 (NLS1) galaxies are a class of active galactic nuclei (AGN) that, in some cases, can harbor powerful relativistic jets. One of them, PKS 2004-447, shows γ-ray emission, and underwent its first recorded multifrequency flare in 2019. However, past studies revealed that in radio this source can be classified as a compact steep-spectrum source (CSS), suggesting that, unlike other γ-ray sources, the relativistic jets of PKS 2004-447 have a large inclination with respect to the line of sight. We present here a set of spectroscopic observations of this object, aimed at carefully measuring its black hole mass and Eddington ratio, determining the properties of its emission lines, and characterizing its long term variability. We find that the black hole mass is (1.5 ± 0.2)×107 M⊙, and the Eddington ratio is 0.08. Both values are within the typical range of NLS1s. The spectra also suggest that the 2019 flare was caused mainly by the relativistic jet, while the accretion disk played a minor role during the event. In conclusion, we confirm that PKS 2004-447 is one of the rare examples of γ-ray emitting CSS/NLS1s hybrid, and that these two classes of objects are likely connected in the framework of AGN evolution.
CRIS-Team Scopus Importer:2021-11-05
Keywords: Galaxies: active; Galaxies: jets; Quasars: supermassive black holes

Hypervelocity stars in the Gaia era Revisiting the most extreme stars from the MMT HVS survey - Kreuzer, Simon; Irrgang, Andreas; Heber, Ulrich (Astronomy & Astrophysics, 2020)
The hypervelocity star (HVS) survey conducted at the Multiple Mirror Telescope (MMT) identified 42 B-type stars in the Galactic halo whose radial velocity in the Galactic rest-frame exceeds +275 km s 1. In order to unravel the nature and origin of those highvelocity outliers, their complete six-dimensional phase space information is needed. To this end, we complemented positions and proper motions from the second data release of Gaia with revised radial velocities and spectrophotometric distances that are based on a reanalysis of the available MMT spectra of 40 objects using state-of-the-art model spectra and a tailored analysis strategy. The resulting position and velocity vectors for 37 stars were then used as input for a subsequent kinematic investigation to obtain as complete a picture as possible. The combination of projected rotational velocity, position in the Kiel diagram, and kinematic properties suggests that all objects in the sample except two (B576, B598) are very likely to be main sequence stars. While the available data are still not precise enough to constrain the place of origin for 19 program stars, we identified eight objects that either come from the outer rim of the Galactic disk or not from the disk at all, along with ten that presumably stem from the Galactic disk. For almost all of those 18 targets with more or less well-constrained spatial origin, the Galactic center (GC) is disqualified as a possible place of origin. The most notable exception is B576, the origin of which coincides extremely well with the GC when assuming a blue horizontal branch nature for it. HVS 22 is by far the most extreme object in the sample. Although its origin is completely unconstrained, an ejection from the GC by the Hills mechanism is the most plausible explanation for its current Galactic rest-frame velocity of 1530(-560)(+690) km s(-1).
Keywords: stars: distances; stars: early-type; stars: fundamental parameters; stars: kinematics and dynamics

Hypervelocity stars in the Gaia era Runaway B stars beyond the velocity limit of classical ejection mechanisms - Irrgang, Andreas; Kreuzer, Simon; Heber, Ulrich (Astronomy & Astrophysics, 2018)
Context. Young massive stars in the halo are assumed to be runaway stars from the Galactic disk. Possible ejection scenarios are binary supernova ejections (BSE) or dynamical ejections from star clusters (DE). Hypervelocity stars (HVSs) are extreme runaway stars that are potentially unbound from the Galaxy. Powerful acceleration mechanisms such as the tidal disruption of a binary system by a supermassive black hole (SMBH) are required to produce them. Therefore, HVSs are believed to originate in the Galactic center (GC), the only place known to host an SMBH.Aims. The second Gaia data release (DR2) offers the opportunity of studying HVSs in an unprecedented manner. We revisit some of the most interesting high-velocity stars, that is, 15 stars (11 candidate HVSs and 4 radial velocity outliers) for which proper motions with the Hubble Space Telescope. were obtained in the pre-Gaia era, to unravel their origin.Methods. By carrying out kinematic analyses based on revised spectrophotometric distances and proper motions from Gaia DR2, kinematic properties were obtained that help constrain the spatial origins of these stars.Results. Stars that were previously considered (un)bound remain (un)bound in Galactic potentials favored by Gaia DR2 astrometry. For nine stars (five candidate HVSs plus all four radial velocity outliers), the GC can be ruled out as spatial origin at least at 2 sigma confidence level, suggesting that a large portion of the known HVSs are disk runaway stars launched close to or beyond Galactic escape velocities. The fastest star in the sample, HVS 3, is confirmed to originate in the Large Magellanic Cloud.Conclusions. Because the ejection velocities of five of our non-GC stars are close to or above the upper limits predicted for BSE and DE, another powerful dynamical ejection mechanism (e.g., involving massive perturbers such as intermediate-mass black holes) is likely to operate in addition to the three classical scenarios mentioned above.
Keywords: stars: early-type; stars: kinematics and dynamics

Identification of SRGt 062340.2-265751 as a bright, strongly variable, novalike cataclysmic variable - Schwope, Axel; Buckley, David A. H.; Kawka, Adela; König, Ole; Lutovinov, Alexander; Maitra, Chandreyee; Mereminskiy, Ilya; Miller-Jones, James; Marcano, Manuel Pichardo; Rau, Arne; Semena, Andrei; Townsend, Lee J.; et al. (Astronomy & Astrophysics, 2022)
We report the identification and follow-up of the transient SRGt 062340.2-265751 detected with both instruments on board the Spektrum-Roentgen-Gamma mission. Optical spectroscopy of the G = 12.5 counterpart firmly classifies the object as a novalike cataclysmic variable (CV) at a distance of 495 pc. A highly significant TESS period of 3.941 h, tentatively identified with the orbital period of the binary, could not be found when the object was reobserved with TESS two years later. The newer high-cadence TESS data revealed quasi-periodic oscillations around 25 min, while ground-based photometry indicated periodic variability at 32 min. Located in very sparsely populated regions of color-magnitude diagrams involving X-ray and optical magnitudes and colors, the new object could be an X-ray underluminous magnetic CV, an intermediate polar, or an overluminous nonmagnetic CV. The lack of uniquely identified spin and orbital periods prevents a final classification. The site of X-ray production in the system, L-X,L-bol = 4.8 x 10(32) erg s(-1), remains to be understood given its high variability on long and short timescales.
CRIS-Team WoS Importer:2022-06-17

IGAPS: the merged IPHAS and UVEX optical surveys of the northern Galactic plane* - Monguio, M.; Greimel, R.; Drew, J. E.; Barentsen, G.; Groot, P. J.; Irwin, M. J.; Casares, J.; Gaensicke, B. T.; Carter, P. J.; Corral-Santana, J. M.; Gentile-Fusillo, N. P.; Greiss, S.; et al. (Astronomy & Astrophysics, 2020)
The INT Galactic Plane Survey (IGAPS) is the merger of the optical photometric surveys, IPHAS and UVEX, based on data from the Isaac Newton Telescope (INT) obtained between 2003 and 2018. Here, we present the IGAPS point source catalogue. It contains 295.4 million rows providing photometry in the filters, i, r, narrow-band H alpha, g, and U-RGO. The IGAPS footprint fills the Galactic coordinate range, |b| < 5 degrees and 30 degrees< l < 215 degrees. A uniform calibration, referred to as the Pan-STARRS system, is applied to g, r, and i, while the H alpha calibration is linked to r and then is reconciled via field overlaps. The astrometry in all five bands has been recalculated in the reference frame of Gaia Data Release 2. Down to i similar to 20 mag (Vega system), most stars are also detected in g, r, and H alpha. As exposures in the r band were obtained in both the IPHAS and UVEX surveys, typically a few years apart, the catalogue includes two distinct r measures, r(I) and r(U). The r 10 sigma limiting magnitude is approximately 21, with median seeing of 1.1 arcsec. Between approximately 13th and 19th mag in all bands, the photometry is internally reproducible to within 0.02 mag. Stars brighter than r=19.5 mag are tested for narrow-band H alpha excess signalling line emission, and for variation exceeding |r(I)-r(U)| = 0.2 mag. We find and flag 8292 candidate emission line stars and over 53 000 variables (both at > 5 sigma confidence).
CRIS-Team WoS Importer:2020-07-03

Implications of the Warm Corona and Relativistic Reflection Models for the Soft Excess in Mrk 509 - Garcia, Javier A.; Kara, Erin; Walton, Dominic; Beuchert, Tobias; Dauser, Thomas; Gatuzz, Efrain; Balokovic, Mislav; Steiner, James F.; Tombesi, Francesco; Connors, Riley M. T.; Kallman, Timothy R.; Harrison, Fiona A.; et al. (Astrophysical Journal, 2019)
We present the analysis of the first Nuclear Spectroscopic Telescope Array observations (similar to 220 ks), simultaneous with the last Suzaku observations (similar to 50 ks), of the active galactic nucleus of the bright Seyfert 1 galaxy Mrk 509. The time-averaged spectrum in the 1-79 keV X-ray band is dominated by a power-law continuum (Gamma similar to 1.8-1.9), a strong soft excess around 1 keV, and signatures of X-ray reflection in the form of Fe K emission (similar to 6.4 keV), an Fe K absorption edge (similar to 7.1 keV), and a Compton hump due to electron scattering (similar to 20-30 keV). We show that these data can be described by two very different prescriptions for the soft excess: a warm (kT similar to 0.5-1 keV) and optically thick (tau similar to 10-20) Comptonizing corona or a relativistically blurred ionized reflection spectrum from the inner regions of the accretion disk. While these two scenarios cannot be distinguished based on their fit statistics, we argue that the parameters required by the warm corona model are physically incompatible with the conditions of standard coronae. Detailed photoionization calculations show that even in the most favorable conditions, the warm corona should produce strong absorption in the observed spectrum. On the other hand, while the relativistic reflection model provides a satisfactory description of the data, it also requires extreme parameters, such as maximum black hole spin, a very low and compact hot corona, and a very high density for the inner accretion disk. Deeper observations of this source are thus necessary to confirm the presence of relativistic reflection and further understand the nature of its soft excess.
Keywords: accretion; accretion disks; black hole physics; galaxies: active; galaxies: individual (Mrk 509); galaxies: nuclei

Improved physical properties of the quadruple sub-system with the eclipsing binary QZ Carinae - Mayer, P.; Harmanec, P.; Zasche, P.; Catalan-Hurtado, R.; Barlow, B. N.; Fremat, Y.; Wolf, M.; Drechsel, Horst; Chini, R.; Nasseri, A.; Christie, G. W.; Walker, W. S. G.; et al. (Contributions of the Astronomical Observatory Skalnate Pleso, 2020)
Using a collection of 79 spectra of the quadruple system QZ Car, we were able - for the first time in the optical region - to measure radial velocities of both components of the eclipsing subsystem Ac, and in combination with the photometric solution to obtain masses and radii of both bodies. We confirm that the Ac binary is a semi-detached system with a brighter primary Ac1 and a more massive secondary Ac2. Variations due to the light-time effect and secular changes in the systemic velocities of both binaries, Aa and Ac, allowed us to estimate the period of mutual orbit of binaries Aa and Ac to be about 11700 d. Preliminary improved basic properties of the system and its components are provided.
CRIS-Team WoS Importer:2020-04-21

IMPROVED REFLECTION MODELS OF BLACK HOLE ACCRETION DISKS: TREATING THE ANGULAR DISTRIBUTION OF X-RAYS - Garcia, Javier; Dauser, Thomas; Lohfink, Anne; Kallman, T. R.; Steiner, J. F.; Mcclintock, J. E.; Brenneman, L.; Wilms, Jörn; Eikmann, Wiebke; Reynolds, C. S.; Tombesi, F. (Astrophysical Journal, 2014)
X-ray reflection models are used to constrain the properties of the accretion disk, such as the degree of ionization of the gas and the elemental abundances. In combination with general relativistic ray tracing codes, additional parameters like the spin of the black hole and the inclination to the system can be determined. However, current reflection models used for such studies only provide angle-averaged solutions for the flux reflected at the surface of the disk. Moreover, the emission angle of the photons changes over the disk due to relativistic light bending. To overcome this simplification, we have constructed an angle-dependent reflection model with the xillver code and self-consistently connected it with the relativistic blurring code RELLINE. The new model, relxill, calculates the proper emission angle of the radiation at each point on the accretion disk and then takes the corresponding reflection spectrum into account. We show that the reflected spectra from illuminated disks follow a limb-brightening law highly dependent on the ionization of disk and yet different from the commonly assumed form I alpha ln(1 + 1/mu). A detailed comparison with the angle-averaged model is carried out in order to determine the bias in the parameters obtained by fitting a typical relativistic reflection spectrum. These simulations reveal that although the spin and inclination are mildly affected, the Fe abundance can be overestimated by up to a factor of two when derived from angle-averaged models. The fit of the new model to the Suzaku observation of the Seyfert galaxy Ark 120 clearly shows a significant improvement in the constraint of the physical parameters, in particular by enhancing the accuracy in the inclination angle and the spin determinations.
Keywords: accretion; accretion disks; black hole physics; galaxies: individual (Ark 120); line: formation; radiative transfer; X-rays: general

In-flight polarization angle calibration for LiteBIRD: Blind challenge and cosmological implications - Krachmalnicoff, N.; Matsumura, T.; De La Hoz, E.; Basak, S.; Gruppuso, A.; Minami, Y.; Baccigalupi, C.; Komatsu, E.; Martínez-González, E.; Vielva, P.; Aumont, J.; Aurlien, R.; et al. (Journal of Cosmology and Astroparticle Physics, 2022)
We present a demonstration of the in-flight polarization angle calibration for the JAXA/ISAS second strategic large class mission, LiteBIRD, and estimate its impact on the measurement of the tensor-to-scalar ratio parameter, r, using simulated data. We generate a set of simulated sky maps with CMB and polarized foreground emission, and inject instrumental noise and polarization angle offsets to the 22 (partially overlapping) LiteBIRD frequency channels. Our in-flight angle calibration relies on nulling the EB cross correlation of the polarized signal in each channel. This calibration step has been carried out by two independent groups with a blind analysis, allowing an accuracy of the order of a few arc-minutes to be reached on the estimate of the angle offsets. Both the corrected and uncorrected multi-frequency maps are propagated through the foreground cleaning step, with the goal of computing clean CMB maps. We employ two component separation algorithms, the Bayesian-Separation of Components and Residuals Estimate Tool (B-SeCRET), and the Needlet Internal Linear Combination (NILC). We find that the recovered CMB maps obtained with algorithms that do not make any assumptions about the foreground properties, such as NILC, are only mildly affected by the angle miscalibration. However, polarization angle offsets strongly bias results obtained with the parametric fitting method. Once the miscalibration angles are corrected by EB nulling prior to the component separation, both component separation algorithms result in an unbiased estimation of the r parameter. While this work is motivated by the conceptual design study for LiteBIRD, its framework can be broadly applied to any CMB polarization experiment. In particular, the combination of simulation plus blind analysis provides a robust forecast by taking into account not only detector sensitivity but also systematic effects.
CRIS-Team Scopus Importer:2022-02-11
Keywords: CMBR experiments; gravitational waves and CMBR polarization

INTEGRAL and Swift observations of EXO 2030+375 during a giant outburst - Wilms, Jörn; et al. (Astronomy & Astrophysics, 2007)
Aims. We investigate the X- ray spectral and timing properties of the high mass X- ray binary EXO 2030+ 375 observed during its June - September 2006 giant ( type II) outburst.Methods. The data analyzed in this work are from partly simultaneous observations with INTEGRAL and Swift. The pulse period P and its temporal derivative. P are measured. X- ray pulse profiles in different energy ranges and time intervals are constructed. Pulse averaged X- ray spectra for different time intervals are studied.Results. We report a strong spin-up of the source during the outburst, comparable to that observed in 1985 during the previous giant outburst when the source was discovered. The value of. P is found to be linearly related to the X- ray luminosity of the source during the outburst. For the first time the hard X- ray (> 25 keV) characteristics of the source during a type II outburst are studied. The X- ray pulse profiles apparently change with luminosity. The X- ray spectral continuum in the 3 - 120 keV energy range is modeled with an absorbed power law with an exponential cutoff around E similar to 26 keV. An iron emission line at similar to 6 - 7 keV is observed. The spectrum reveals some features between 10 and 20 keV which can be modeled either by a broad emission line at similar to 13 - 15 keV ( a " bump") or by two absorption lines at similar to 10 and similar to 20 keV.
Keywords: X-ray binaries; stars : neutron; accretion; accretion disks

INTEGRAL deep observations of the Small Magellanic Cloud - Coe, M. J.; Bird, A. J.; Buckley, D. A. H.; Corbet, R. H. D.; Dean, A. J.; Finger, M.; Galache, J. L.; Haberl, Frank; Mcbride, V. A.; Negueruela, Ignacio; Schurch, Matthew; Townsend, L. J.; et al. (Monthly Notices of the Royal Astronomical Society, 2010)
Deep observations of the Small Magellanic Cloud (SMC) and region were carried out in the hard X-ray band by the INTEGRAL observatory in 2008-2009. The field of view of the instrument permitted simultaneous coverage of the entire SMC and the eastern end of the Magellanic Bridge. In total, INTEGRAL detected seven sources in the SMC and five in the Magellanic Bridge; the majority of the sources were previously unknown systems. Several of the new sources were detected undergoing bright X-ray outbursts and all the sources exhibited transient behaviour except the supergiant system SMC X-1. They are all thought to be high-mass X-ray binary systems in which the compact object is a neutron star.
Keywords: stars: neutron; X-rays: binaries

INTEGRAL discovery of a high-energy tail in the microquasar Cygnus X-3 - Cangemi, F.; Rodriguez, J.; Grinberg, V.; Belmont, R.; Laurent, P.; Wilms, Jörn (Astronomy & Astrophysics, 2021)
Context. The X-ray spectra of X-ray binaries are dominated by emission of either soft or hard X-rays which defines their soft and hard spectral states. While the generic picture is relatively well understood, little is known about the interplay of the various media at work, or about the reasons why some sources do not follow common behavior. Cygnus X-3 is amongst the list of X-ray binaries that show quite complex behavior, with various distinct spectral states not seen in other sources. These states have been characterized in many studies. Because of its softness and intrinsic low flux above typically 50 keV, very little is known about the hard X/soft gamma-ray (100-1000 keV) emission in Cygnus X-3.Aims. Using the whole INTEGRAL data base, we aim to explore the 3-1000 keV spectra of Cygnus X-3. This allows to probe this region with the highest sensitivity ever, and search for the potential signature of a high-energy non-thermal component as sometimes seen in other sources.Methods. Our work is based on state classification carried out in previous studies with data from the Rossi X-Ray Timing Explorer. We extend this classification to the whole INTEGRAL data set in order to perform a long-term state-resolved spectral analysis. Six stacked spectra were obtained using 16 years of data from JEM-X (3-25 keV), ISGRI (25-300 keV), and SPI (20-400 keV).Results. We extract stacked images in three different energy bands, and detect the source up to 200 keV. In the hardest states, our purely phenomenological approach clearly reveals the presence of an additonnal component > 50 keV in addition to the component usually interpreted as thermal Comptonization. We apply a more physical model of hybrid thermal/nonthermal corona (EQPAIR) to characterize this nonthermal component and compare our results with those of previous studies and analyses. Our modeling indicates a more efficient acceleration of electrons in states where major ejections are observed. We also evaluate and find a dependence of the photon index of the power law as a function of the strong orbital modulation of the source in the Flaring InterMediate state. This dependence could be due to a higher absorption when Cygnus X-3 is behind its companion. However, the uncertainties on the density column prevent us from drawing any firm conclusions.
CRIS-Team WoS Importer:2021-02-12

INTEGRAL observation of the accreting pulsar GX 1+4 - Wilms, Jörn; et al. (Astronomy & Astrophysics, 2007)
Aims: We present the results of the INTEGRAL monitoring campaign on the accreting low mass X-ray binary pulsar GX1+4 performed during the Galactic plane scan of the INTEGRAL Core Programme.Methods. The source was observed in different luminosity states ranging from L20-40 keV = 1.7 x 10(-10) erg cm(-2) s(-1), to L20-40 keV = 10.5 x 10(-10) erg cm(-2) s(-1) for about 779 ks from March 2003 until October 2004.Results. Our observations confirm the secular spin down of GX 1+4 with the spin period (P-s) varying from 139.63 s to 141.56 s. In the highest luminosity state, a spin-up phase is observed. The phase-averaged spectrum of the source was modelled either with an absorbed cut-off power law or with a Comptonization model with significantly different parameters in the two brightest luminosity states. No evidence of any absorption-like feature is observed in the phase averaged spectrum up to 110 keV. At highest luminosity, the source is found to pulsate up to 130 keV. Phase resolved spectroscopy reveals a phase-dependent continuum and marginal evidence for an absorption feature at 34 +/- 2 keV in the descending part of the pulse. If interpreted as due to electron resonant cyclotron scattering, the magnetic field in the emitting region would be (2.9 +/- 0.2) x 10(12) (1+z) G where z is the gravitational red shift of the emitting region. We also observed a very low luminosity state, typical of this source, which lasted for about two days during which the source spectrum was modelled by a simple power law, and a pulsed signal was still detectable in the 15-100 keV energy range.
Keywords: X-rays : stars; stars : pulsars : individual : GX 1+4

INTEGRAL observations of Hercules X-1 - Klochkov, D.; Staubert, R.; Postnov, Konstantin; Shakura, N.; Santangelo, A.; Tsygankov, S.; Lutovinov, A.; Kreykenbohm, Ingo; Wilms, Jörn (Astronomy & Astrophysics, 2008)
Aims. We investigate the X-ray spectral and timing properties of the accreting X-ray pulsar Her X-1 observed with the INTEGRAL satellite in July-August 2005.Methods. The data analyzed in this work cover a substantial part of one main-on state of the source. The short time scale pulse period development is measured. X-ray pulse profiles for different energy ranges and time intervals are constructed. Pulse-averaged and pulse-phase resolved broad band X-ray spectra are studied. Spectral changes during X-ray dips are explored.Results. The X-ray pulse profiles are found to change significantly during the period of observations. For the first time a strong spin-up is measured within one 35 d cycle. Spectral characteristics observed during the X-ray dips are consistent with their interpretation as being due to partial covering as has been reported by several authors. The fundamental cyclotron absorption line is firmly observed in both pulse-averaged and pulse-phase resolved X-ray spectra. The energy, width, and the depth of the line are found to vary significantly with pulse phase.
Keywords: X-rays : binaries; accretion; accretion disks; stars : neutron

INTEGRAL observations of the variability of OAO1657-415 - Barnstedt, J.; Staubert, R.; Santangelo, A.; Ferrigno, Carlo; Horns, Dieter; Klochkov, D.; Kretschmar, Peter; Kreykenbohm, Ingo; Segreto, Alberto; Wilms, Jörn (Astronomy & Astrophysics, 2008)
Context. The Galactic Plane Scan (GPS) was one of the core observation programmes of the INTEGRAL satellite. The highly variable accreting pulsar OAO1657-415 was frequently observed within the GPS.Aims. We investigate the spectral and timing properties of OAO1657-415 and their variability on short and long time scales in the energy range 6-160 keV.Methods. Using standard extraction tools and custom software for extracting INTEGRAL data we analysed energy-resolved light curves with a time resolution of one second-mainly data of the ISGRI instrument. We also analysed phase-averaged broad band spectra -including JEM-X spectra -and pulse-phase resolved spectra of ISGRI.Results. During the time covered by the INTEGRAL observations, the pulse period evolution shows an initial spin-down, which is followed by an equally strong spin-up. In combining our results with historical pulse period measurements (correcting them for orbital variation) and with stretches of continuous observations by BATSE, we find that the long-term period evolution is characterised by a long-term spin-up overlayed by sets of relative spin-down/spin-up episodes, which appear to repeat quasi-periodically on a 4.8 yr time scale. We measure an updated local ephemeris and confirm the previously determined orbital period with an improved accuracy. The spectra clearly change with pulse phase. The spectrum measured during the main peak of the pulse profile is particularly hard. We do not find any evidence of a cyclotron line, wether in the phase-averaged spectrum or in phase-resolved spectra.
Keywords: x-rays : binaries; pulsars : individual : OAO1657-415

INTEGRAL study of MAXI J1535-571, MAXI J1820+070, and MAXI J1348-630 outbursts - Cangemi, F.; Rodriguez, J.; Belloni, T.; Gouiffès, C.; Grinberg, V.; Laurent, P.; Petrucci, P. O.; Wilms, Jörn (Astronomy & Astrophysics, 2023)
In black hole X-ray binaries, a nonthermal high-energy component is sometimes detected at energies above 200 keV. The origin of this high-energy component is debated and distinct spectral modelizations can lead to di_erent interpretations. High-energy polarimetry measurements with the INTErnational Gamma-Ray Astrophysics Laboratory (INTEGRAL) enable new diagnostics on the physics responsible for the MeV spectral component in black hole X-ray binaries. In this work, we aim to investigate the high-energy behavior of three bright sources discovered by the Monitor of All-sky X-ray Image: MAXI J1535-571, MAXI J1820+070, and MAXI J1348-630. We took advantage of their brightness to investigate their soft -ray (0.1-2 MeV) properties with INTEGRAL. We used both spectral and polarimetric approaches to probe their high-energy emission with the aim of bringing new constraints on the MeV emission in black hole X-ray binaries. We first studied the spectral characteristics of the sources in the 3-2000 keV range using JEM-X, IBIS, and SPI, with a semi-phenomenological description of the data. We then used IBIS as a Compton telescope in order to evaluate the polarization properties of the sources above 300 keV. A high-energy component was detected during the hardintermediate state and soft-intermediate state of MAXI J1535-571, the low-hard state of MAXI J1820+070, and the low-hard state of MAXI J1348-630. The components detected in MAXI J1820+070 and MAXI J1348-630 were polarized with a polarization fraction of 26±9° and >56% in the 300-1000 keV range, respectively.With no polarization information for MAXI J1535-571, the component detected could either come from the jets or the corona. In the case of MAXI J1820+070, the extrapolation of the synchrotron spectrum measured in the infrared indicates that the component is likely due to a nonthermal distribution of electrons from a hybrid corona. For MAXI J1348-630, the high fraction of polarization points toward a jets origin; however, we cannot formally conclude this without any infrared data giving information on the optically thin part of the synchrotron spectrum.
CRIS-Team Scopus Importer:2023-01-27
Keywords: Acceleration of particles; Black hole physics; Polarization; Radiation mechanisms: non-thermal; X-rays: binaries

Intrinsic limits on resolutions in muon- and electron-neutrino charged-current events in the KM3NeT/ORCA detector - Adrian-Martinez, S.; Ageron, M.; Aiello, S.; Albert, A.; Ameli, F.; Anassontzis, E. G.; Andre, Michel; Androulakis, G.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Avgitas, T.; et al. (Journal of High Energy Physics, 2017)
Studying atmospheric neutrino oscillations in the few-GeV range with a multimegaton detector promises to determine the neutrino mass hierarchy. This is the main science goal pursued by the future KM3NeT/ORCA water Cherenkov detector in the Mediterranean Sea. In this paper, the processes that limit the obtainable resolution in both energy and direction in charged-current neutrino events in the ORCA detector are investigated. These processes include the composition of the hadronic fragmentation products, the subsequent particle propagation and the photon-sampling fraction of the detector. GEANT simulations of neutrino interactions in seawater produced by GENIE are used to study the effects in the 1-20 GeV range. It is found that fluctuations in the hadronic cascade in conjunction with the variation of the inelasticity y are most detrimental to the resolutions. The effect of limited photon sampling in the detector is of significantly less importance. These results will therefore also be applicable to similar detectors/media, such as those in ic
Keywords: Neutrino Detectors and Telescopes (experiments)

Inversion of the decay of the cyclotron line energy in Hercules X-1 - Staubert, R.; Klochkov, D.; Fuerst, F.; Wilms, Jörn; Rothschild, R. E.; Harrison, F. (Astronomy & Astrophysics, 2017)
Recent observations of Her X-1 with NuSTAR and INTEGRAL in 2016 have provided evidence that the 20-year decay of the cyclotron line energy found between 1996 and 2015 has ended and that an inversion with a new increase, possibly similar to the one observed around 1990-1993, has started. We consider this a strong motivation for further observations and for enhanced efforts to significantly improve our theoretical understanding of the accretion process in binary X-ray pulsars. We speculate about the physics behind the long-term decay and its inversion, a possible cyclic behavior, and correlations with other variable observables.
Keywords: magnetic fields; binaries: eclipsing; stars: neutron; radiation mechanisms: non-thermal; line: formation; X-rays: general

Investigating source confusion in PMN J1603-4904 - Krauss, F.; Kreter, M.; Mueller, C.; Markowitz, A.; Böck, Moritz; Burnett, T.; Dauser, Thomas; Kadler, M.; Kreikenbohm, A.; Ojha, R.; Wilms, Jörn (Astronomy & Astrophysics, 2018)
PMN J1603-4904 is a likely member of the rare class of gamma-ray emitting young radio galaxies. Only one other source, PKS 1718-649, has been confirmed so far. These objects, which may transition into larger radio galaxies, are a stepping stone to understanding AGN evolution. It is not completely clear how these young galaxies, seen edge-on, can produce high-energy gamma rays. PMN J1603-4904 has been detected by TANAMI Very Long Baseline Interferometry (VLBI) observations and has been followed-up with multiwavelength observations. A Fermi Gamma-ray Space Telescope Large Area Telescope (Fermi-LAT) gamma-ray source has been associated with this young galaxy in the LAT catalogs. We have obtained Chandra observations of the source to consider the possibility of source confusion due to the relatively large positional uncertainty of Fermi-LAT. The goal was to investigate the possibility of other X-ray bright sources in the vicinity of PMN J1603-4904 that could be counterparts to the gamma-ray emission. With Chandra/ACIS, we find no other sources in the uncertainty ellipse of Fermi-LAT data, which includes an improved localization analysis of eight years of data. We further study the X-ray fluxes and spectra. We conclude that PMN J1603-4904 is indeed the second confirmed gamma-ray bright young radio galaxy.
Keywords: galaxies: active; galaxies: jets; Galaxy: abundances; galaxies: individual: PMN J1603-4904

Investigating the effect of source contamination on eXTP/SFA - Zhang, Juan; Li, Gang; Ge, Mingyu; Kirsch, Christian; Lorenz, Maximilian; Wilms, Jörn; Qi, Liqiang; Sheng, Lizhi; Yang, Yi Jung; Dauser, Thomas; Xu, Yupeng; Lu, Fangju; et al. (Proceedings of SPIE - The International Society for Optical Engineering, 2020)
The Spectroscopy Focusing Array (SFA) onboard the enhanced X-ray Timing and Polarimetry (eXTP) observatory consists of 9 modules, each comprising a Wolter type I telescope with a field of view (FOV) around 16 arcminutes and a focal plane silicon drift detector (SDD) with 19 hexagonal pixels. Due to the large size of each individual SDD pixel (each pixel corresponds to an area of ∼ 3.6 arcminutes in diameter) and the limited pixel number, SFA can not obtain a real image of the observed region like many other X-ray imaging telescopes. Thus, contamination from nearby bright sources needs to be considered when we study the properties of the target source. We simulate such contaminations using the SIXTE simulator. In this paper we present the results by taking observations of the millisecond pulsar PSR J0437-4715 as an example, and discuss the cases for contamination on background or target source respectively.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Contamination; EXTP/SFA; Nearby source

Investigating the Impact of Vertically Extended Coronae on X-Ray Reverberation Mapping - Lucchini, Matteo; Mastroserio, Guglielmo; Wang, Jingyi; Kara, Erin; Ingram, Adam; Garcia, Javier; Dauser, Thomas; van der Klis, Michiel; König, Ole; Lewin, Collin; Nathan, Edward; Panagiotou, Christos (Astrophysical Journal, 2023)
Accreting black holes commonly exhibit hard X-ray emission, originating from a region of hot plasma near the central engine referred to as the corona. The origin and geometry of the corona are poorly understood, and models invoking either inflowing or outflowing material (or both) can successfully explain only parts of the observed phenomenology. In particular, recent works indicate that the time-averaged and variability property might originate in different regions of the corona. In this paper we present a model designed to move beyond the lamppost paradigm, with the goal of accounting for the vertical extent of the corona. In particular, we highlight the impact of including self-consistently a second lamppost, mimicking, for example, an extended jet base. We fully include the effect that the second source has on the time-dependent disk ionization, reflection spectrum, and reverberation lags. We also present an application of this new model to NICER observations of the X-ray binary MAXI J1820+070 near its hard-to-soft state transition. We demonstrate that in these observations, a vertically extended corona can capture both spectral and timing properties, while a single-lamppost model can not. In this scenario, the illumination responsible for the time-averaged spectrum originates close to the black hole, while the variability is likely associated with the ballistic jet.
CRIS-Team Scopus Importer:2023-09-29

Investigating the Mini and Giant Radio Flare Episodes of Cygnus X-3 - Egron, Elise; Pellizzoni, Alberto; Righini, Simona; Giroletti, Marcello; Koljonen, Karri; Pottschmidt, Katja; Trushkin, Sergei; Lobina, Jessica; Pilia, Maura; Wilms, Jörn; Corbel, Stephane; Grinberg, Victoria; et al. (Astrophysical Journal, 2021)
The microquasar Cygnus X-3 underwent a giant radio flare in 2017 April, reaching a maximum flux of similar to 16.5 Jy at 8.5 GHz. We present results from a long monitoring campaign carried out with Medicina at 8.5, 18.6, and 24.1 GHz, parallel to the Metsahovi radio telescope at 37 GHz, from 2017 April 4 to 11. We observe a spectral steepening from alpha = 0.2 to 0.5 (with S-nu proportional to nu(-alpha)) within 6 hr of the epoch of the flare's peak maximum, and rapid changes in the spectral slope in the following days during brief enhanced emission episodes while the general trend of the radio flux density indicated the decay of the giant flare. We further study the radio orbital modulation of Cyg X-3 emission associated with the 2017 giant flare and with six mini-flares observed in 1983, 1985, 1994, 1995, 2002, and 2016. The enhanced emission episodes observed during the decline of the giant flare at 8.5 GHz coincide with the orbital phase phi similar to 0.5 (orbital inferior conjunction). On the other hand, the light curves of the mini-flares observed at 15-22 GHz peak at phi similar to 0, except for the 2016 light curve, which is shifted 0.5 w.r.t. the other ones. We attribute the apparent phase shift to the variable location of the emitting region along the bent jet. This might be explained by the different accretion states of the flaring episodes (the 2016 mini-flare occurred in the hypersoft X-ray state).
CRIS-Team WoS Importer:2021-01-15

Irradiation of an accretion disc by a jet: general properties and implications for spin measurements of black holes - Dauser, Thomas; Garcia, Javier; Wilms, Jörn; Böck, Moritz; Brenneman, L. W.; Falanga, M.; Fukumura, K.; Reynolds, C. S. (Monthly Notices of the Royal Astronomical Society, 2013)
X-ray irradiation of the accretion disc leads to strong reflection features, which are then broadened and distorted by relativistic effects. We present a detailed, general relativistic approach to model this irradiation for different geometries of the primary X-ray source. These geometries include the standard point source on the rotational axis as well as more jet-like sources, which are radially elongated and accelerating. Incorporating this code in the RELLINE model for relativistic line emission, the line shape for any configuration can be predicted. We study how different irradiation geometries affect the determination of the spin of the black hole. Broad emission lines are produced only for compact irradiating sources situated close to the black hole. This is the only case where the black hole spin can be unambiguously determined. In all other cases the line shape is narrower, which could either be explained by a low spin or an elongated source. We conclude that in those cases and independent of the quality of the data no unique solution for the spin exists and therefore only a lower limit of the spin value can be given.
Keywords: accretion; accretion discs; black hole physics; lines: profiles; galaxies: active; galaxies: nuclei

Is the plateau state in GRS 1915+105 equivalent to canonical hard states? - Van Oers, Pieter; Markoff, Sera; Rahoui, Farid; Maitra, Dipankar; Nowak, Michael; Wilms, Jörn; Castro-Tirado, Alberto J.; Rodriguez, Jerome; Dhawan, Vivek; Harlaftis, Emilios (Monthly Notices of the Royal Astronomical Society, 2010)
GRS 1915+105 is a very peculiar black hole binary that exhibits accretion-related states that are not observed in any other stellar-mass black hole system. One of these states, however referred to as the plateau state - may be related to the canonical hard state of black hole X-ray binaries. Both the plateau and hard state are associated with steady, relatively lower X-ray emission and flat/inverted radio emission, that is sometimes resolved into compact, self-absorbed jets. However, while generally black hole binaries quench their jets when the luminosity becomes too high, GRS 1915+105 seems to sustain them despite the fact that it accretes at near- or super-Eddington rates. In order to investigate the relationship between the plateau and the hard state, we fit two multiwavelength observations using a steady-state outflow-dominated model, developed for hard-state black hole binaries. The data sets consist of quasi-simultaneous observations in radio, near- infrared and X-ray bands. Interestingly, we find both significant differences between the two plateau states, as well as between the best-fitting model parameters and those representative of the hard state. We discuss our interpretation of these results, and the possible implications for GRS 1915+105's relationship to canonical black hole candidates.
Keywords: accretion; accretion discs; black hole physics; radiation mechanisms: general; galaxies: active; galaxies: jets; X-rays: binaries

Joint Constraints on Galactic Diffuse Neutrino Emission from the ANTARES and IceCube Neutrino Telescopes - Albert, A.; Grasso, D.; Andre, M.; Anghinolfi, M.; Ardid, M.; Aubert, J. -J.; Aublin, J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Belhorma, B.; et al. (Astrophysical Journal Letters, 2018)
The existence of diffuse Galactic neutrino production is expected from cosmic-ray interactions with Galactic gas and radiation fields. Thus, neutrinos are a unique messenger offering the opportunity to test the products of Galactic cosmic-ray interactions up to energies of hundreds of TeV. Here we present a search for this production using ten years of Astronomy with a Neutrino Telescope and Abyss environmental RESearch (ANTARES) track and shower data, as well as seven years of IceCube track data. The data are combined into a joint likelihood test for neutrino emission according to the KRA(gamma) model assuming a 5 PeV per nucleon Galactic cosmic-ray cutoff. No significant excess is found. As a consequence, the limits presented in this Letter start constraining the model parameter space for Galactic cosmic-ray production and transport.
Keywords: cosmic rays; diffusion; Galaxy: disk; gamma rays: diffuse background; neutrinos

Joint spectral-timing modelling of the hard lags in GX 339-4: constraints on reflection models - Cassatella, P.; Uttley, P.; Wilms, Jörn; Poutanen, Juri (Monthly Notices of the Royal Astronomical Society, 2012)
The X-ray variations of hard state black hole X-ray binaries above 2 keV show hard lags, in that the variations at harder energies follow variations at softer energies, with a time lag t depending on frequency ? approximately as t??-0.7. Several models have so far been proposed to explain this time delay, including fluctuations propagating through an accretion flow, spectral variations during coronal flares, Comptonization in the extended hot corona or a jet, or time delays due to large-scale reflection from the accretion disc. In principle, these models can be used to predict the shape of the energy spectrum as well as the frequency dependence of the time lags, through the construction of energy-dependent response functions which map the emission as a function of time delay in the system. Here we use this approach to test a simple reflection model for the frequency-dependent lags seen in the hard state of GX 339-4, by simultaneously fitting the model to the frequency-dependent lags and energy spectrum measured by XMMNewton in 2004 and 2009. Our model cannot simultaneously fit both the lag and spectral data, since the relatively large lags require an extremely flared disc which subtends a large solid angle to the continuum at large radii, in disagreement with the observed Fe Ka emission. Therefore, we consider it more likely that the lags >2 keV are caused by propagation effects in the accretion flow, possibly related to the accretion disc fluctuations which have been observed previously.
Keywords: accretion; accretion discs; black hole physics; stars: individual: GX 339-4; X-rays: binaries

Kinematic properties of white dwarfs Galactic orbital parameters and age-velocity dispersion relation - Raddi, Roberto; Torres, Santiago; Rebassa-Mansergas, Alberto; Maldonado, Jesus; Camisassa, Maria E.; Koester, Detlev; Fusillo, Nicola Pietro Gentile; Tremblay, Pier-Emmanuel; Dimpel, Markus; Heber, Ulrich; Cunningham, Tim; Ren, Juan-Juan (Astronomy & Astrophysics, 2022)
Context. Kinematic and chemical tagging of stellar populations have both revealed much information on the past and recent history of the Milky Way, including its formation history, merger events, and mixing of populations across the Galactic disk and halo.
CRIS-Team WoS Importer:2022-02-11

KM3NeT front-end and readout electronics system: hardware, firmware, and software - Aiello, Sebastiano; Amllei, Fabrizio; Andre, Michel; Androulakis, Giorgos; Anghinolfi, Marco; Anton, Gisela; Ardid, Miquel; Aublin, Julien; Bagatelas, Christos; Barbarino, Giancarlo; Baret, Bruny; Du Pree, Suzan Basegmez; et al. (Journal of Astronomical Telescopes, Instruments, and Systems, 2019)
The KM3NeT research infrastructure being built at the bottom of the Mediterranean Sea will host water-Cherenkov telescopes for the detection of cosmic neutrinos. The neutrino telescopes will consist of large volume three-dimensional grids of optical modules to detect the Cherenkov light from charged particles produced by neutrino-induced interactions. Each optical module houses 31 3-in. photomultiplier tubes, instrumentation for calibration of the photomultiplier signal and positioning of the optical module, and all associated electronics boards. By design, the total electrical power consumption of an optical module has been capped at seven Watts. We present an overview of the front-end and readout electronics system inside the optical module, which has been designed for a 1-ns synchronization between the clocks of all optical modules in the grid during a life time of at least 20 years. (C) 2019 Society of Photo-Optical Instrumentation Engineers (SPIE)
CRIS-Team WoS Importer:2020-02-28

LABORATORY MEASUREMENTS of the K-SHELL TRANSITION ENERGIES in L-SHELL IONS of SI and S - Hell, Natalie; Brown, G. V.; Wilms, Jörn; Grinberg, Victoria; Clementson, J.; Liedahl, D.; Porter, F. S.; Kelley, R. L.; Kilbourne, C. A.; Beiersdorfer, P. (Astrophysical Journal, 2016)
We have measured the energies of the strongest 1s-2 ℓ (ℓ = s, p) transitions in He- through Ne-like silicon and sulfur ions to an accuracy of <1 eV using the Lawrence Livermore National Laboratorys electron beam ion traps, EBIT-I and SuperEBIT, and the NASA/GSFC EBIT Calorimeter Spectrometer (ECS). We identify and measure the energies of 18 and 21 X-ray features from silicon and sulfur, respectively. The results are compared to new Flexible Atomic Code calculations and to semi-relativistic Hartree-Fock calculations by Palmeri et al. (2008). These results will be especially useful for wind diagnostics in high-mass X-ray binaries, such as Vela X-1 and Cygnus X-1, where high-resolution spectral measurements using Chandras high-energy transmission grating has made it possible to measure Doppler shifts of 100 km s. The accuracy of our measurements is consistent with that needed to analyze Chandra observations, exceeding Chandras 100 km s limit. Hence, the results presented here not only provide benchmarks for theory, but also accurate rest energies that can be used to determine the bulk motion of material in astrophysical sources. We show the usefulness of our results by applying them to redetermine Doppler shifts from Chandra observations of Vela X-1.
Keywords: atomic data; methods: laboratory: atomic; X-rays: binaries; X-rays: general

Letter of intent for KM3NeT 2.0 - Adrian-Martinez, S.; Ageron, M.; Aharonian, F.; Aiello, S.; Albert, A.; Ameli, F.; Anassontzis, E.; Andre, Michel; Androulakis, G.; Anghinolfi, M.; Anton, Gisela; Ardid, Miguel; et al. (Journal of Physics G: Nuclear and Particle Physics, 2016)
The main objectives of the KM3NeT Collaboration are (i) the discovery and subsequent observation of high-energy neutrino sources in the Universe and (ii) the determination of the mass hierarchy of neutrinos. These objectives are strongly motivated by two recent important discoveries, namely: (1) the high-energy astrophysical neutrino signal reported by IceCube and (2) the sizable contribution of electron neutrinos to the third neutrino mass eigenstate as reported by Daya Bay, Reno and others. To meet these objectives, the KM3NeT Collaboration plans to build a new Research Infrastructure consisting of a network of deep-sea neutrino telescopes in the Mediterranean Sea. A phased and distributed implementation is pursued which maximises the access to regional funds, the availability of human resources and the synergistic opportunities for the Earth and sea sciences community. Three suitable deep-sea sites are selected, namely off-shore Toulon (France), Capo Passero (Sicily, Italy) and Pylos (Peloponnese, Greece). The infrastructure will consist of three so-called building blocks. A building block comprises 115 strings, each string comprises 18 optical modules and each optical module comprises 31 photo-multiplier tubes. Each building block thus constitutes a three-dimensional array of photo sensors that can be used to detect the Cherenkov light produced by relativistic particles emerging from neutrino interactions. Two building blocks will be sparsely configured to fully explore the IceCube signal with similar instrumented volume, different methodology, improved resolution and complementary field of view, including the galactic plane. One building block will be densely configured to precisely measure atmospheric neutrino oscillations.
Keywords: deep sea neutrino telescope; neutrino astronomy; neutrino mass hierarchy; neutrino physics

Limits on dark matter annihilation in the sun using the ANTARES neutrino telescope - Adrian-Martineza, S.; Albert, A.; Andre, M.; Anton, Gisela; Ardid, M.; Aubert, J. -J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; et al. (Physics Letters B, 2016)
A search for muon neutrinos originating from dark matter annihilations in the Sun is performed using the data recorded by the ANTARES neutrino telescope from 2007 to 2012. In order to obtain the best possible sensitivities to dark matter signals, an optimisation of the event selection criteria is performed taking into account the background of atmospheric muons, atmospheric neutrinos and the energy spectra of the expected neutrino signals. No significant excess over the background is observed and 90% C.L. upper limits on the neutrino flux, the spin-dependent and spin-independent WIMP-nucleon cross-sections are derived for WIMP masses ranging from 50 GeV to 5 TeV for the annihilation channels WIMP+WIMP→bb-,WW and ττ.
Keywords: Dark matter; Indirect detection; Neutralino; Neutrino telescope; Sun; WIMP

Long-Term Activity of a Little Known Dwarf Nova DT Octantis - Simon, V.; Edelmann, Heinz (Astrophysical Bulletin, 2019)
We analyze the long-term activity of a little known dwarf nova (DN) DT Oct. We use photographic observations from the Bamberg Observatory (Southern Patrol Photographic Sky Survey), CCD data from ASAS-3 survey, and AAVSO data (both CCD and visual). We determined the recurrence times of the superoutbursts, T-Cso, and of the normal outbursts, T-Cno, to be approximately 311 d and about 30 d, respectively. Although the length of T-Cso evolves gradually and undergoes only small variations (increases and decreases) of the nearby or neighbouring events (on the timescale of a few epochs), the evolution of T-Cso displays considerably larger changes on the longer timescales. They suggest a dominant trend of a decrease of T-Cso on the timescale of tens of years. The possibly magnetized white dwarf does not prevent DT Oct to show the long-term activity of the SUUMa systems. We place the time evolution of the superoutbursts of DT Oct in the context of DNe of various sub-types.
CRIS-Team WoS Importer:2020-02-25

Long-term change in the cyclotron line energy in Hercules X-1 - Staubert, R.; Klochkov, D.; Wilms, Jörn; Postnov, Konstantin; Shakura, N. I.; Rothschild, R. E.; Fuerst, F.; Harrison, F. A. (Astronomy & Astrophysics, 2014)
Aims. We investigate the long-term evolution of the cyclotron resonance scattering feature (CRSF) in the spectrum of the binary X-ray pulsar Her X-1 and present evidence of a true long-term decrease in the centroid energy E-cyc of the cyclotron line in the pulse phase averaged spectra from 1996 to 2012.Methods. Our results are based on repeated observations of Her X-1 by those X-ray observatories capable of measuring clearly beyond the cyclotron line energy of similar to 40 keV; these are RXTE, INTEGRAL, Suzaku, and NuSTAR. We consider results based on our own successful observing proposals as well as results from the literature.Results. The historical evolution of the pulse phase averaged CRSF centroid energy Ecyc since its discovery in 1976 is characterized by an initial value around 35 keV, an abrupt jump upwards to beyond similar to 40 keV between 1990 and 1994, and an apparent decay thereafter. Much of this decay, however, was found to be due to an artifact, namely a correlation between Ecyc and the X-ray luminosity L-x discovered in 2007. In observations after 2006, however, we now find a statistically significant true decrease in the cyclotron line energy. At the same time, the dependence of Ecyc on X-ray luminosity is still valid with an increase of similar to 5% in energy for a factor of two increase in luminosity. We also report on the first evidence of a weak dependence of Ecyc on phase of the 35 d precessional period, which manifests itself not only in the modulation of the X-ray flux, but also in the systematic variation in the shape of the 1.24 s pulse profile. One of our motivations for repeatedly observing Her X-1, namely the suspicion that the cyclotron line energy may be gradually decreasing after its strong upward jump in the early 1990s, is finally confirmed. A decrease in Ecyc by 4.2 keV over the 16 years from 1996 to 2012 can either be modeled by a linear decay, or by a slow decay until 2006 followed by a more abrupt decrease thereafter.Conclusions. The observed timescale for the decrease in Ecyc of a few decades is too short for a decay of the global magnetic field. We speculate that the physical reason could be connected to a geometric displacement of the cyclotron resonant scattering region in the polar field or to a true physical change in the magnetic field configuration at the polar cap by the continued accretion. In the second scenario, the upward jump in Ecyc observed around 1991 may have been due to a relatively fast event in which the polar magnetic field rearranged itself after releasing part of the accumulated material to larger areas of the neutron star surface.
Keywords: radiation mechanisms: non-thermal; binaries: eclipsing; pulsars: individual: Her X-1; accretion; accretion disks; magnetic fields; X-rays: binaries

Long-term monitoring of the ANTARES optical module efficiencies using K-40 decays in sea water - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J-J; Aublin, J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Belhorma, B.; et al. (European Physical Journal C, 2018)
Cherenkov light induced by radioactive decay products is one of the major sources of background light for deep-sea neutrino telescopes such as ANTARES. These decays are at the same time a powerful calibration source. Using data collected by the ANTARES neutrino telescope from mid 2008 to 2017, the time evolution of the photon detection efficiency of optical modules is studied. A modest loss of only 20% in 9 years is observed. The relative time calibration between adjacent modules is derived as well.

Long-term pulse period evolution of the ultra-luminous X-ray pulsar NGC 7793 P13 - Furst, F.; Walton, D. J.; Heida, M.; Bachetti, M.; Pinto, C.; Middleton, M. J.; Brightman, M.; Earnshaw, H. P.; Barret, D.; Fabian, A. C.; Kretschmar, P.; Pottschmidt, K.; et al. (Astronomy & Astrophysics, 2021)
Ultra-luminous X-ray pulsars (ULXPs) provide a unique opportunity to study persistent super-Eddington accretion. Here we present the results of a long-term monitoring campaign of ULXP NGC7793 P13, focusing on the pulse period evolution and the determination of the orbital ephemeris. Over our four year monitoring campaign with Swift, XMM-Newton, and NuSTAR, we measured a continuous spin-up with an average value of. P- 3:8 x 10 11 s s 1. We find that the strength of the spin-up is independent of the observed X-ray flux, indicating that despite a drop in observed flux in 2019, accretion onto the source has continued at largely similar rates. The source entered an apparent o ff-state in early 2020, which might have resulted in a change in the accretion geometry as no pulsations were found in observations in July and August 2020. We used the long-term monitoring to update the orbital ephemeris, as well as the periodicities seen in both the observed optical and UV magnitudes and the X-ray fluxes. We find that the optical and UV period is very stable over the years, with PUV = 63:75+0:17 0:12 d. The best-fit orbital period determined from our X-ray timing results is 64:86 +/- 0:19 d, which is almost a day longer than previously implied, and the X-ray flux period is 65 :21 +/- 0 :15 d, which is slightly shorter than previously measured. The physical origin of these di fferent flux periods is currently unknown. We study the hardness ratio of the XMM-Newton and NuSTAR data between 2013 2020 to search for indications of spectral changes. We find that the hardness ratios at high energies are very stable and not directly correlated with the observed flux. At lower energies we observe a small hardening with increased flux, which might indicate increased obscuration through outflows at higher luminosities. Comparing the changes in flux with the observed pulsed fraction, we find that the pulsed fraction is significantly higher at low fluxes. This seems to imply that the accretion geometry already changed before the source entered the deep o ff-state. We discuss possible scenarios to explain this behavior, which is likely driven by a precessing accretion disk.
CRIS-Team WoS Importer:2021-08-06

Long term variability of Cygnus X-1 VI. Energy-resolved X-ray variability 1999-2011 - Grinberg, Victoria; Pottschmidt, K.; Boeck, M.; Schmid, Christian; Nowak, M. A.; Uttley, P.; Tomsick, J. A.; Rodriguez, Jerome; Hell, Natalie; Markowitz, Alex; Bodaghee, A.; Bel, M. Cadolle; et al. (Astronomy & Astrophysics, 2014)
We present the most extensive analysis of Fourier-based X-ray timing properties of the black hole binary Cygnus X-1 to date, based on 12 years of bi-weekly monitoring with RXTE from 1999 to 2011. Our aim is a comprehensive study of timing behavior across all spectral states, including the elusive transitions and extreme hard and soft states. We discuss the dependence of the timing properties on spectral shape and photon energy, and study correlations between Fourier-frequency dependent coherence and time lags with features in the power spectra. Our main results are: (a) The fractional rms in the 0.125-256 Hz range in different spectral states shows complex behavior that depends on the energy range considered. It reaches its maximum not in the hard state, but in the soft state in the Comptonized tail above 10 keV. (b) The shape of power spectra in hard and intermediate states and the normalization in the soft state are strongly energy dependent in the 2.1-15 keV range. This emphasizes the need for an energy-dependent treatment of power spectra and a careful consideration of energy- and mass-scaling when comparing the variability of different source types, e.g., black hole binaries and AGN. PSDs during extremely hard and extremely soft states can be easily confused for energies above similar to 5 keV in the 0.125-256 Hz range. (c) The coherence between energy bands drops during transitions from the intermediate into the soft state but recovers in the soft state. (d) The time lag spectra in soft and intermediate states show distinct features at frequencies related to the frequencies of the main variability components seen in the power spectra and show the same shift to higher frequencies as the source softens. Our results constitute a template for other sources and for physical models for the origin of the X-ray variability. In particular, we discuss how the timing properties of Cyg X-1 can be used to assess the evolution of variability with spectral shape in other black hole binaries. Our results suggest that none of the available theoretical models can explain the full complexity of X-ray timing behavior of Cyg X-1, although several ansatzes with different physical assumptions are promising.
Keywords: X-rays: binaries; stars: individual: Cygnus X-1; binaries: close

Long term variability of Cygnus X-1 VII. Orbital variability of the focussed wind in Cyg X-1/HDE 226868 system - Grinberg, V.; Leutenegger, M. A.; Hell, Natalie; Pottschmidt, K.; Böck, Moritz; Garcia, J. A.; Hanke, Manfred; Nowak, M. A.; Sundqvist, J. O.; Townsend, R. H. D.; Wilms, Jörn (Astronomy & Astrophysics, 2015)
Binary systems with an accreting compact object off er a unique opportunity to investigate the strong, clumpy, line-driven winds of early-type supergiants by using the compact object's X-rays to probe the wind structure. We analyze the two-component wind of HDE 226868, the O9.7Iab giant companion of the black hole Cyg X-1, using 4.77 Ms Rossi X-ray Timing Explorer (RXTE) observations of the system taken over the course of 16 years. Absorption changes strongly over the 5.6 d binary orbit, but also shows a large scatter at a given orbital phase, especially at superior conjunction. The orbital variability is most prominent when the black hole is in the hard X-ray state. Our data are poorer for the intermediate and soft state, but show signs for orbital variability of the absorption column in the intermediate state. We quantitatively compare the data in the hard state to a toy model of a focussed Castor-Abbott-Klein wind: as it does not incorporate clumping, the model does not describe the observations well. A qualitative comparison to a simplified simulation of clumpy winds with spherical clumps shows good agreement in the distribution of the equivalent hydrogen column density for models with a porosity length on the order of the stellar radius at inferior conjunction; we conjecture that the deviations between data and model at superior conjunction could either be due to lack of a focussed wind component in the model or to a more complicated clump structure.
Keywords: stars: individual: Cyg X-1; X-rays: binaries; binaries : close; stars: winds; outflows

Long term variability of Cygnus X-1 V. State definitions with all sky monitors - Grinberg, Victoria; Hell, Natalie; Pottschmidt, K.; Boeck, M.; Nowak, M. A.; Rodriguez, Jerome; Bodaghee, A.; Bel, M. Cadolle; Case, G. L.; Hanke, Manfred; Kühnel, Matthias; Markoff, S. B.; et al. (Astronomy & Astrophysics, 2013)
We present a scheme for determining the spectral state of the canonical black hole Cyg X-1 using data from previous and current X-ray all sky monitors (RXTE-ASM, Swift-BAT, MAXI, and Fermi-GBM). Determinations of the hard/intermediate and soft state agree to better than 10% between different monitors, facilitating the determination of the state and its context for any observation of the source, potentially over the lifetimes of different individual monitors. A separation of the hard and the intermediate states, which strongly differ in their spectral shape and short-term timing behavior, is only possible when data in the soft X-rays (<5 keV) are available. A statistical analysis of the states confirms the different activity patterns of the source (e.g., month- to year-long hard-state periods or phases during which numerous transitions occur). It also shows that the hard and soft states are stable, with the probability of Cyg X-1 remaining in a given state for at least one week to be larger than 85% in the hard state and larger than 75% in the soft state. Intermediate states are short lived, with a 50% probability that the source leaves the intermediate state within three days. Reliable detection of these potentially short-lived events is only possible with monitor data that have a time resolution better than 1 d.
Keywords: X-rays: binaries; stars: individual: Cygnus X-1; binaries: close

Long-term variability of Vela X-1 - Kretschmar, Peter; Keating, J.; Kreykenbohm, Ingo; Wilms, Jörn; Staubert, R. (2010)
The archetypical wind-accreting X-ray pulsar Vela X-1 is known to be variable on a large range of timescales. Relatively tranquil phases exist as well as extended phases of high variability and flaring. We present results from a systematic study of variations with orbital phase and other timescales based on RXTE/ASM and Swift/BAT data.
Keywords: X-rays: binaries; Stars: neutron; Stars: winds; outflows

Looking at A 0535+26 at low luminosities with NuSTAR - Ballhausen, Ralf; Pottschmidt, Katja; Furst, Felix; Wilms, Jörn; Tomsick, John A.; Schwarm, Fritz-Walter; Stern, Daniel; Kretschmar, Peter; Caballero, Isabel; Harrison, Fiona A.; Boggs, Steven E.; Christensen, Finn E.; et al. (Astronomy & Astrophysics, 2017)
We report on two NuSTAR observations of the high-mass X-ray binary A 0535 + 26 taken toward the end of its normal 2015 outburst at very low 3-50 keV luminosities of similar to 1.4 x 10(36) erg s(-1) and similar to 5 x 10(35) erg s(-1), which are complemented by nine Swift observations. The data clearly confirm indications seen in earlier data that the source's spectral shape softens as it becomes fainter. The smooth exponential rollover at high energies seen in the first observation evolves to a much more abrupt steepening of the spectrum at 20-30 keV. The continuum evolution can be nicely described with emission from a magnetized accretion column, modeled using the compmag model modified by an additional Gaussian emission component for the fainter observation. Between the two observations, the optical depth changes from 0.75 +/- 0.04 to 0.56(-0.04)(+0.01), the electron temperature remains constant, and there is an indication that the column decreases in radius. Since the energy-resolved pulse profiles remain virtually unchanged in shape between the two observations, the emission properties of the accretion column reflect the same accretion regime. This conclusion is also confirmed by our result that the energy of the cyclotron resonant scattering feature (CRSF) at similar to 45 keV is independent of the luminosity, implying that the magnetic field in the region in which the observed radiation is produced is the same in both observations. Finally, we also constrain the evolution of the continuum parameters with the rotational phase of the neutron star. The width of the CRSF could only be constrained for the brighter observation. Based on Monte Carlo simulations of CRSF formation in single accretion columns, its pulse phase dependence supports a simplified fan beam emission pattern. The evolution of the CRSF width is very similar to that of the CRSF depth, which is, however, in disagreement with expectations.
Keywords: X-rays: binaries; pulsars: individual: A 0535+26; stars: neutron; accretion; accretion disks; stars: magnetic field

Low charge states of Si and S in Cygnus X-1 - Hell, Natalie; Miskovicova, I.; Brown, G. V.; Wilms, Jörn; Clementson, J.; Hanke, Manfred; Beiersdorfer, P.; Liedahl, D.; Pottschmidt, K.; Porter, F. S.; Kilbourne, C. A.; Kelley, R. L.; et al. (IOP PUBLISHING LTD, 2013)
Strong, relatively short, absorption dips have been observed in the x-ray light curves measured from the high mass x-ray binary system Cygnus X-1. With increasing strength of the dips, which are believed to be caused by 'clumps' of cold material present in the stellar wind of Cyg X-1's companion star, K-shell absorption lines in L-shell ions of Si and S develop. To determine the bulk motion of the clumps via the Doppler shifts of these lines with high accuracy, we measured their reference energies using the Lawrence Livermore National Laboratory electron beam ion trap EBIT-I and EBIT Calorimeter Spectrometer. Our findings-shifts consistent with zero velocity of the absorber throughout all ionization states at orbital phase zero-provide evidence for an onion-like ion structure of the clumps.

Luminosity dependent accretion state change in GRO J1008-57 - Kühnel, Matthias; Müller, Sebastian; Kreykenbohm, Ingo; Fuerst, Felix; Pottschmidt, Katja; Rothschild, Richard E.; Caballero, Isabel; Grinberg, Victoria; Schoenherr, Gabriele; Shrader, Chris; Klochkov, Dmitry; Staubert, Ruediger; et al. (2014)
In a former publication, we have analyzed the transient neutron star X-ray binary GRO J1008-57 using all available RXTE-, Swift-, and Suzaku-data. As we have found, the source's spectral components, i.e., a power-law with high exponential cutoff and a black-body, are strongly correlated with the hard X-ray flux (15-50 keV). We update the analytical description of these dependence, including a change in the photon index behaviour from a flat to a logarithmic function. The flux, where the change occurs, is consistent with the onset of the black-body emission. Thus, a change of the accretion state always occurs in GRO J1008-57 at a particular flux level.

M33 X-7: ChASeM33 reveals the first eclipsing black hole X-ray binary - Pietsch, Wolfgang; Haberl, Frank; Sasaki, Manami; Gaetz, Terrance J.; Plucinsky, Paul P.; Ghavamian, Parviz; Long, Knox S.; Pannuti, Thomas (Astrophysical Journal, 2006)
The first observations conducted as part of the Chandra ACIS survey of M33 (ChASeM33) sampled the eclipsing X-ray binary M33 X-7 over a large part of the 3.45 day orbital period and have resolved eclipse ingress and egress for the first time. The occurrence of the X-ray eclipse allows us to determine an improved ephemeris of mid-eclipse and binary period as HJD (2; 453; 639.119 +/- 0.005) +/- N(3.453014 +/- 0.000020) and constrain the eclipse half-angle to 26 degrees.5 +/- 1 degrees.1. There are indications for a shortening of the orbital period. The X-ray spectrum is best described by a disk blackbody spectrum typical for black hole X-ray binaries in the Galaxy. We find a flat power density spectrum, and no significant regular pulsations were found in the frequency range of 10(-4) to 0.15 Hz. HST WFPC2 images resolve the optical counterpart, which can be identified as an O6 III star with the help of extinction and color corrections derived from the X-ray absorption. Based on the optical light curve, the mass of the compact object in the system most likely exceeds 9 M-circle dot. This mass, the shape of the X-ray spectrum, and the short-term X-ray time variability identify M33 X-7 as the first eclipsing black hole high-mass X-ray binary.
Keywords: binaries : eclipsing; galaxies : individual (M33); X-rays : binaries; X-rays : individual (M33 X-7)

Magnetic field estimates from the X-ray synchrotron emitting rims of the 30 Dor C superbubble and the implications for the nature of 30 Dor C's TeV emission - Kavanagh, Patrick J.; Vink, Jacco; Sasaki, Manami; Chu, You-Hua; Filipovic, Miroslav D.; Ohm, Stefan; Haberl, Frank; Manojlovic, Perica; Maggi, Pierre (Astronomy & Astrophysics, 2019)
Context. The 30 Dor C superbubble is unique for its synchrotron X-ray shell, as well as being the first superbubble to be detected in TeV γ-rays, though which is the dominant TeV emission mechanism, leptonic or hadronic, is still unclear. Aims. We aim to use new Chandra observations of 30 Dor C to resolve the synchrotron shell in unprecedented detail and to estimate the magnetic (B) field in the postshock region, a key discriminator between TeV γ-ray emission mechanisms. Methods. We extracted radial profiles in the 1.5-8 keV range from various sectors around the synchrotron shell and fitted these with a projected and point spread function convolved postshock volumetric emissivity model to determine the filament widths. We then calculated the postshock magnetic field strength from these widths. Results. We find that most of the sectors were well fitted with our postshock model and the determined B-field values were low, all with best fits ≤20 μG. Upper limits on the confidence intervals of three sectors reached z 30 μG though these were poorly constrained. The generally low B-field values suggests a leptonic-dominated origin for the TeV γ-rays. Our postshock model did not provide adequate fits to two sectors. We find that one sector simply did not provide a clean enough radial profile, while the other could be fitted with a modified postshock model where the projected profile falls off abruptly below ∼0.8 times the shell radius, yielding a postshock B-field of 4.8 (3.7-11.8) μG which is again consistent with the leptonic TeV γ-ray mechanism. Alternatively, the observed profiles in these sectors could result from synchrotron enhancements around a shock-cloud interaction as suggested in previous works. Conclusions. The average postshock B-field determined around the X-ray synchrotron shell of 30 Dor C suggests the leptonic scenario as the dominant emission mechanism for the TeV γ-rays.
CRIS-Team Scopus Importer:2019-05-02
Keywords: ISM: Bubbles; ISM: Magnetic fields; ISM: Supernova remnants; Magellanic Clouds; X-rays: ISM

Massive star formation in the Carina nebula complex and Gum 31. II. A cloud–cloud collision in Gum 31 - Fujita, Shinji; Sano, Hidetoshi; Enokiya, Rei; Hayashi, Katsuhiro; Kohno, Mikito; Tsuge, Kisetsu; Tachihara, Kengo; Nishimura, Atsushi; Ohama, Akio; Yamane, Yumiko; Ohno, Takahiro; Yamada, Rin; et al. (Publications of the Astronomical Society of Japan, 2021)
We present the results of analyses of the 12CO (J = 1–0), 13CO (J = 1–0), and 12CO (J = 2–1) emission data toward Gum 31. Three molecular clouds separated in velocity were detected at -25, -20, and -10 km s-1. The velocity structure of the molecular clouds in Gum 31 cannot be interpreted as an expanding motion. Two of them, the -25 km s-1 cloud and the -20 km s-1 cloud, are likely to be associated with Gum 31, because their 12CO (J = 2–1)/12CO (J = 1–0) intensity ratios are high. We found that these two clouds show the observational signatures of cloud–cloud collisions (CCCs): a complementary spatial distribution and a V-shaped structure (bridge features) in the position–velocity diagram. In addition, their morphology and velocity structures are very similar to the numerical simulations conducted by the previous studies. We propose a scenario that the -25 km s-1 cloud and the -20 km s-1 cloud collided and triggered the formation of the massive star system HD 92206 in Gum 31. This scenario can explain the offset of the stars from the center and the morphology of Gum 31 simultaneously. The timescale of the collision was estimated to be ∼1 Myr by using the ratio between the path length of the collision and the assumed velocity separation. This is consistent with that of the CCCs in the Carina Nebula Complex in our previous study.
CRIS-Team Scopus Importer:2021-10-29
Keywords: ISM: clouds; ISM: individual (Carina); Radio lines: ISM

Massive unseen companions to hot faint underluminous stars from SDSS (MUCHFUSS): Analysis of seven close subdwarf B binaries - Geier, Stephan; Maxted, P. F. L.; Napiwotzki, R.; Ostensen, R. H.; Heber, Ulrich; Hirsch, H.; Kupfer, Thomas; Mueller, S.; Tillich, A.; Barlow, B. N.; Oreiro, R.; Ottosen, T. A.; et al. (Astronomy & Astrophysics, 2011)
The project Massive Unseen Companions to Hot Faint Underluminous Stars from SDSS (MUCHFUSS) aims at finding hot subdwarf stars with massive compact companions like massive white dwarfs (M > 1.0 M⊙), neutron stars or stellar mass black holes. The existence of such systems is predicted by binary evolution theory and recent discoveries indicate that they exist in our Galaxy. First results are presented for seven close binary sdBs with short orbital periods ranging from ≃ 0.21 d to 1.5 d. The atmospheric parameters of all objects are compatible with core helium-burning stars. The companions are most likely white dwarfs. In one case the companion could be shown to be a white dwarf by the absence of light-curve variations. However, in most cases late type main sequence stars cannot be firmly excluded. Comparing our small sample with the known population of close sdB binaries we show that our target selection method aiming at massive companions is efficient. The minimum companion masses of all binaries in our sample are high compared to the reference sample of known sdB binaries. © 2010 ESO.
CRIS-Team Scopus Importer:2020-12-21
Keywords: binaries: close; binaries: spectroscopic; subdwarfs; white dwarfs

Maxi J1820+070 with Nustar I. An increase in variability frequency but a stable reflection spectrum: Coronal properties and implications for the inner disc in black hole binaries - Buisson, D. J. K.; Fabian, A. C.; Barret, Didier; Furst, F.; Gandhi, P.; Garcia, Javier; Kara, E.; Madsen, K. K.; Miller, J. M.; Parker, M. L.; Shaw, A. W.; Tomsick, J. A.; et al. (Monthly Notices of the Royal Astronomical Society, 2019)
MAXI J1820+070 (optical counterpart ASASSN-18ey) is a black hole candidate discovered through its recent very bright outburst. The low extinction column and long duration at high flux allow detailed measurements of the accretion process to be made. In this work, we compare the evolution of X-ray spectral and timing properties through the initial hard state of the outburst. We show that the inner accretion disc, as measured by relativistic reflection, remains steady throughout this period of the outburst. Nevertheless, subtle spectral variability is observed, which is well explained by a change in coronal geometry. However, characteristic features of the temporal variability – low-frequency roll-over and quasi-periodic oscillation frequency – increase drastically in frequency, as the outburst proceeds. This suggests that the variability time-scales are governed by coronal conditions rather than solely by the inner disc radius. We also find a strong correlation between X-ray luminosity and coronal temperature. This can be explained by electron pair production with a changing effective radius and a non-thermal electron fraction of ∼ 20 per cent.
CRIS-Team Scopus Importer:2021-04-20
Keywords: Accretion accretion discs; Black hole physics; X-rays: binaries

Measurement of atmospheric neutrino oscillations with the ANTARES neutrino telescope ANTARES Collaboration - Adrian-Martinez, S.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Astraatmadja, T.; Aubert, J. -J.; Baret, B.; Basa, S.; et al. (Physics Letters B, 2012)
The data taken with the ANTARES neutrino telescope from 2007 to 2010, a total live time of 863 days, are used to measure the oscillation parameters of atmospheric neutrinos. Muon tracks are reconstructed with energies as low as 20 GeV. Neutrino oscillations will cause a suppression of vertical upgoing muon neutrinos of such energies crossing the Earth. The parameters determining the oscillation of atmospheric neutrinos are extracted by fitting the event rate as a function of the ratio of the estimated neutrino energy and reconstructed flight path through the Earth. Measurement contours of the oscillation parameters in a two-flavour approximation are derived. Assuming maximal mixing, a mass difference of Delta m(32)(2) = (3.1 +/- 0.9) . 10(-3) eV(2) is obtained, in good agreement with the world average value. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Neutrino oscillations; Neutrino telescope; ANTARES

Measurement of the atmospheric nu (mu) energy spectrum from 100 GeV to 200 TeV with the ANTARES telescope - Adrian-Martinez, S.; Albert, A.; Al Samarai, I.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Astraatmadja, T.; Aubert, J. -J.; Baret, B.; Barrios-Marti, J.; et al. (European Physical Journal C, 2013)
Atmospheric neutrinos are produced during cascades initiated by the interaction of primary cosmic rays with air nuclei. In this paper, a measurement of the atmospheric energy spectrum in the energy range 0.1-200 TeV is presented, using data collected by the ANTARES underwater neutrino telescope from 2008 to 2011. Overall, the measured flux is similar to 25 % higher than predicted by the conventional neutrino flux, and compatible with the measurements reported in ice. The flux is compatible with a single power-law dependence with spectral index gamma (meas)=3.58 +/- 0.12. With the present statistics the contribution of prompt neutrinos cannot be established.

Measurement of the atmospheric νe and νμ energy spectra with the ANTARES neutrino telescope - Albert, A.; Alves, S.; André, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. J.; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; Bendahman, M.; et al. (Physics Letters B, 2021)
This letter presents a combined measurement of the energy spectra of atmospheric νe and νμ in the energy range between ∼100 GeV and ∼50 TeV with the ANTARES neutrino telescope. The analysis uses 3012 days of detector livetime in the period 2007–2017, and selects 1016 neutrinos interacting in (or close to) the instrumented volume of the detector, yielding shower-like events (mainly from νe+ν‾e charged current plus all neutrino neutral current interactions) and starting track events (mainly from νμ+ν‾μ charged current interactions). The contamination by atmospheric muons in the final sample is suppressed at the level of a few per mill by different steps in the selection analysis, including a Boosted Decision Tree classifier. The distribution of reconstructed events is unfolded in terms of electron and muon neutrino fluxes. The derived energy spectra are compared with previous measurements that, above 100 GeV, are limited to experiments in polar ice and, for νμ, to Super-Kamiokande.
CRIS-Team Scopus Importer:2021-04-02
Keywords: ANTARES; Atmospheric neutrinos; Neutrino telescope

Measurement of the EBL spectral energy distribution using the VHE gamma-ray spectra of HESS blazars - Abdalla, H.; Abramowski, A.; Aharonian, F.; Ait Benkhali, F.; Akhperjanian, A. G.; Andersson, T.; Angüner, E. O.; Arakawa, M.; Arrieta, M.; Aubert, P.; Backes, M.; Balzer, A.; et al. (Astronomy & Astrophysics, 2017)
Very high-energy gamma rays (VHE, E greater than or similar to 100 GeV) propagating over cosmological distances can interact with the low-energy photons of the extragalactic background light (EBL) and produce electron-positron pairs. The transparency of the Universe to VHE gamma rays is then directly related to the spectral energy distribution (SED) of the EBL. The observation of features in the VHE energy spectra of extragalactic sources allows the EBL to be measured, which otherwise is very difficult. An EBL model-independent measurement of the EBL SED with the H.E.S.S. array of Cherenkov telescopes is presented. It was obtained by extracting the EBL absorption signal from the reanalysis of high-quality spectra of blazars. From H.E.S.S. data alone the EBL signature is detected at a significance of 9.5 sigma, and the intensity of the EBL obtained in different spectral bands is presented together with the associated gamma-ray horizon.
CRIS-Team WoS Importer:2020-01-15
Keywords: Infrared: diffuse background; Cosmic background radiation; Gamma rays: galaxies; BL Lacertae objects: general

Measurement of the group velocity of light in sea water at the ANTARES site - Adrian-Martinez, S.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Jesus, A. C. Assis; Astraatmadja, T.; Aubert, J-J.; Baret, B.; et al. (Astroparticle Physics, 2012)
The group velocity of light has been measured at eight different wavelengths between 385 nm and 532 nm in the Mediterranean Sea at a depth of about 2.2 km with the ANTARES optical beacon systems. A parametrisation of the dependence of the refractive index on wavelength based on the salinity, pressure and temperature of the sea water at the ANTARES site is in good agreement with these measurements. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: ANTARES; Neutrino telescope; Optical beacon system; Velocity of light; Refractive index

MEASUREMENTS OF CYCLOTRON FEATURES AND PULSE PERIODS IN THE HIGH-MASS X-RAY BINARIES 4U 1538-522 AND 4U 1907+09 WITH THE INTERNATIONAL GAMMA-RAY ASTROPHYSICS LABORATORY - Hemphill, Paul B.; Rothschild, Richard E.; Caballero, Isabel; Pottschmidt, Katja; Kühnel, Matthias; Fuerst, Felix; Wilms, Jörn (Astrophysical Journal, 2013)
We present a spectral and timing analysis of International Gamma-Ray Astrophysics Laboratory (INTEGRAL) observations of two high-mass X-ray binaries, 4U 1538-522 and 4U 1907+09. Our timing measurements for 4U 1538-522 find the pulse period to have exhibited a spin-up trend until approximately 2009, after which there is evidence for a torque reversal, with the source beginning to spin down to the most recently measured period of 525.407 +/- 0.001 s. The most recent INTEGRAL observations of 4U 1907+09 are not found to yield statistically significant pulse periods due to the significantly lower flux from the source compared with 4U 1538-522. A spectral model consisting of a power-law continuum with an exponential cutoff and modified by two cyclotron resonance scattering features is found to fit both sources well, with the cyclotron scattering features detected at similar to 22 and similar to 49 keV for 4U 1538-522 and at similar to 18 and similar to 36 keV for 4U 1907+09. The spectral parameters of 4U 1538-522 are generally not found to vary significantly with flux and there is little to no variation across the torque reversal. Examining our results in conjunction with previous work, we find no evidence for a correlation between cyclotron line energy and luminosity for 4U 1538-522. 4U 1907+09 shows evidence for a positive correlation between cyclotron line energy and luminosity, which would make it the fourth, and lowest luminosity, cyclotron line source to exhibit this relationship.
Keywords: pulsars: individual (4U 1538-522; 4U 1907+09); stars: magnetic field; stars: oscillations; X-rays: binaries; X-rays: stars

Measuring the atmospheric neutrino oscillation parameters and constraining the 3+1 neutrino model with ten years of ANTARES data - Albert, A.; André, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. J.; Aublin, J.; Avgitas, T.; Baret, B.; Barrios-Martí, J.; Basa, S.; Belhorma, B.; et al. (Journal of High Energy Physics, 2019)
The ANTARES neutrino telescope has an energy threshold of a few tens of GeV. This allows to study the phenomenon of atmospheric muon neutrino disappearance due to neutrino oscillations. In a similar way, constraints on the 3+1 neutrino model, which foresees the existence of one sterile neutrino, can be inferred. Using data collected by the ANTARES neutrino telescope from 2007 to 2016, a new measurement of Δm322 and θ23 has been performed — which is consistent with world best-fit values — and constraints on the 3+1 neutrino model have been derived.[Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2019-07-02
Keywords: Neutrino Detectors and Telescopes (experiments); Oscillation

Meet the family - the catalog of known hot subdwarf stars - Geier, Stephan; Ostensen, R. H.; Nemeth, Peter; Heber, Ulrich; Fusillo, Nicola Pietro Gentile; Gänsicke, Boris T.; Telting, John; Green, E. M.; Schaffenroth, Johannes (DE GRUYTER POLAND SP ZOO, 2017)
In preparation for the upcoming all-sky data releases of the Gaia mission, we compiled a catalog of known hot subdwarf stars and candidates drawn from the literature and yet unpublished databases. The catalog contains 5613 unique sources and provides multi-band photometry from the ultraviolet to the far infrared, ground based proper motions, classifications based on spectroscopy and colors, published atmospheric parameters, radial velocities and light curve variability information. Using several different techniques, we removed outliers and misclassified objects. By matching this catalog with astrometric and photometric data from the Gaia mission, we will develop selection criteria to construct a homogeneous, magnitude-limited all-sky catalog of hot subdwarf stars based on Gaia data. As first application of the catalog data, we present the quantitative spectral analysis of 280 sdB and sdOB stars from the Sloan Digital Sky Survey Data Release 7. Combining our derived parameters with state-of-the-art proper motions, we performed a full kinematic analysis of our sample. This allowed us to separate the first significantly large sample of 78 sdBs and sdOBs belonging to the Galactic halo. Comparing the properties of hot subdwarfs from the disk and the halo with hot subdwarf samples from the globular clusters omega Cen and NGC 2808, we found the fraction of intermediate He-sdOBs in the field halo population to be significantly smaller than in the globular clusters.
Keywords: stars: subdwarfs; stars: horizontal branch; catalogs

Metal abundances of subdwarf B stars-the extended sample - Geier, Stephan; Heber, Ulrich; Heber, Ulrich; Edelmann, Heinz; Morales-Rueda, L.; Napiwotzki, R. (Astrophysics and Space Science, 2010)
The formation of sdBs as well as the chemical composition of their atmospheres is still puzzling. While helium and other light elements are depleted relative to solar values, heavy elements are highly enriched. Diffusion processes in the hot, radiative atmosphere of these stars are the most likely explanation. Although several attempts have been made, it has not yet been possible to model all the observed features of sdB atmospheres. A drawback of most prior studies was the small sample size. We present a detailed abundance analysis of 139 sdBs. A general trend of enrichment was found with increasing temperature for most of the heavier elements. The lighter elements like carbon, oxygen and nitrogen are depleted and less affected by temperature. Although there is considerable scatter from one star to the other, the general abundance patterns in most sdBs are similar. An interplay between gravitational settling, radiative levitation and weak winds is most likely responsible. About 3% of the analysed stars show an enrichment in carbon and helium, which cannot be explained in the framework of diffusion alone. Nuclear processed material must have been transported to the surface somehow.
Keywords: Stars: horizontal branch; Stars: abundances; Stars: chemically peculiar; Stars: atmospheres

Meteor studies in the framework of the JEM-EUSO program - Abdellaoui, Ghouti; Abe, S.; Acheli, A.; Adams, J. H. J. H.; Ahmad, S.; Ahriche, A.; Albert, J. -N.; Allard, D.; Alonso, Gustavo; Anchordoqui, L.; Andreev, V.; Anzalone, A.; et al. (PERGAMON-ELSEVIER SCIENCE LTD, 2017)
We summarize the state of the art of a program of UV observations from space of meteor phenomena, a secondary objective of the JEM-EUSO international collaboration. Our preliminary analysis indicates that JEM-EUSO, taking advantage of its large FOV and good sensitivity, should be able to detect meteors down to absolute magnitude close to 7. This means that JEM-EUSO should be able to record a statistically significant flux of meteors, including both sporadic ones, and events produced by different meteor streams. Being unaffected by adverse weather conditions, JEM-EUSO can also be a very important facility for the detection of bright meteors and fireballs, as these events can be detected even in conditions of very high sky background. In the case of bright events, moreover, exhibiting some persistence of the meteor train, preliminary simulations show that it should be possible to exploit the motion of the ISS itself and derive at least a rough 3D reconstruction of the meteor trajectory. Moreover, the observing strategy developed to detect meteors may also be applied to the detection of nuclearites, exotic particles whose existence has been suggested by some theoretical investigations. Nuclearites are expected to move at higher velocities than meteoroids, and to exhibit a wider range of possible trajectories, including particles moving upward after crossing the Earth. Some pilot studies, including the approved Mini-EUSO mission, a precursor of JEM-EUSO, are currently operational or in preparation. We are doing simulations to assess the performance of Mini-EUSO for meteor studies, while a few meteor events have been already detected using the ground-based facility EUSO-TA.
Keywords: Meteors; Nuclearites; JEM-EUSO; Mini-EUSO; EUSO-TA

Millimeter VLBI of NGC 1052: Dynamics - Baczko, Anne-Kathrin; Schulz, Robert; Ros, Eduardo; Kadler, Matthias; Perucho, Manel; Wilms, Jörn (Galaxies, 2016)

Mock catalogs for the extragalactic X-ray sky: Simulating AGN surveys with ATHENA and with the AXIS probe - Marchesi, Stefano; Gilli, Roberto; Lanzuisi, G.; Dauser, Thomas; Ettori, Stefano; Vito, F.; Cappelluti, N.; Comastri, Andrea; Mushotzky, R.; Ptak, A.; Norman, C. (Astronomy & Astrophysics, 2020)
We present a series of new, publicly available mock catalogs of X-ray selected active galactic nuclei (AGNs), nonactive galaxies, and clusters of galaxies. These mocks are based on up-to-date observational results on the demographic of extragalactic X-ray sources and their extrapolations. They reach fluxes below 10-20 erg cm-2 s-1 in the 0.5-2 keV band, that is, more than an order of magnitude below the predicted limits of future deep fields, and they therefore represent an important tool for simulating extragalactic X-ray surveys with both current and future telescopes. We used our mocks to perform a set of end-to-end simulations of X-ray surveys with the forthcoming ATHENA mission and with the AXIS probe, a subarcsecond resolution X-ray mission concept proposed to the Astro 2020 Decadal Survey. We find that these proposed, next generation surveys may transform our knowledge of the deep X-ray Universe. As an example, in a total observing time of 15 Ms, AXIS would detect ∼225 000 AGNs and ∼50 000 nonactive galaxies, reaching a flux limit of f0.5-2 ∼5 × 10-19 erg cm-2 s-1 in the 0.5-2 keV band, with an improvement of over an order of magnitude with respect to surveys with current X-ray facilities. Consequently, 90% of these sources would be detected for the first time in the X-rays. Furthermore, we show that deep and wide X-ray surveys with instruments such as AXIS and ATHENA are expected to detect ∼20 000 z > 3 AGNs and ∼250 sources at redshift z > 6, thus opening a new window of knowledge on the evolution of AGNs over cosmic time and putting strong constraints on the predictions of theoretical models of black hole seed accretion in the early universe.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Galaxies: active; Surveys; Telescopes; X-rays: galaxies

Mode identification in three pulsating hot subdwarfs observed with TESS satellite - Sahoo, S. K.; Baran, A. S.; Heber, Ulrich; Ostrowski, J.; Sanjayan, S.; Silvotti, R.; Irrgang, Andreas; Uzundag, M.; Reed, M. D.; Shoaf, K. A.; Raddi, Roberto; Vuckovic, M.; et al. (Monthly Notices of the Royal Astronomical Society, 2020)
We report on the detectirm of pulsations of three pulsating subdwarf B stars observed by the Transiting Exoplanet Survey Satellite (TESS) satellite and our results of mode iderttification in these stars based on an asymptotic period relation. SI3 459 (TIC 067584818), SI3 815 (TIC 169285097), and PG0342 + 026 (TIC 457168745) have been monitored during single sectors resulting in 27 d coverage. These data sets allowed for detecting, m each star, a fey): tens of frequencies that we interpreted as stellar oscillations. We found no multiplets, though we partially constrained mode geometry by means of period spacing. which recently became a key tool in analyses of pulsating subdwarf B stars. Standard routine that we have used allowed us to select candidates for trapped triodes that surely bear signatures of non-uniform chemical profile inside the stars. We have also done statistical analysis using collected spectroscopic and asteroseismic data of previously known subdwarf 13 stars along with our three stars. Making use of high precision trigonometric parallaxes from the Gaia mission and spectral energy distributions we converted atmospheric parameters to stellar ones. Radii, masses, and lunfinosities are close to their canonical values for extreme horizontal branch stars. In particular, the stellar masses are close to the canonical one of 0.47 M-circle dot for all three stars but uncertainties on the mass are large. The results of the analyses presented here will provide important constrains for asteroseismic modelling.
CRIS-Team WoS Importer:2020-07-17

Model-independent search for neutrino sources with the ANTARES neutrino telescope - Albert, A.; André, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. J.; Avgitas, T.; Baret, B.; Barrios-Martí, J.; Basa, S.; Bertin, V.; Biagi, S.; et al. (Astroparticle Physics, 2020)
A novel method to analyse the spatial distribution of neutrino candidates recorded with the ANTARES neutrino telescope is introduced, searching for an excess of neutrinos in a region of arbitrary size and shape from any direction in the sky. Techniques originating from the domains of machine learning, pattern recognition and image processing are used to purify the sample of neutrino candidates and for the analysis of the obtained skymap. In contrast to a dedicated search for a specific neutrino emission model, this approach is sensitive to a wide range of possible morphologies of potential sources of high-energy neutrino emission. The application of these methods to ANTARES data yields a large-scale excess with a post-trial significance of 2.5σ. Applied to public data from IceCube in its IC40 configuration, an excess consistent with the results from ANTARES is observed with a post-trial significance of 2.1σ.
CRIS-Team Scopus Importer:2019-07-02
Keywords: Anisotropy; Astroparticle physics; Neutrino astronomy; Pattern recognition

Modelling correlated variability in accreting black holes: The effect of high density and variable ionization on reverberation lags - Mastroserio, Guglielmo; Ingram, Adam; Wang, Jingyi; García, Javier A.; Van Der Klis, Michiel; Cavecchi, Yuri; Connors, Riley; Dauser, Thomas; Harrison, Fiona; Kara, Erin; König, Ole; Lucchini, Matteo (Monthly Notices of the Royal Astronomical Society, 2021)
We present a new release of the reltrans model to fit the complex cross-spectrum of accreting black holes as a function of energy. The model accounts for continuum lags and reverberation lags self-consistently in order to consider the widest possible range of X-ray variability time-scales. We introduce a more self-consistent treatment of the reverberation lags, accounting for how the time variations of the illuminating flux change the ionization level of the accretion disc. This process varies the shape of the reflection spectrum in time causing an additional source of lags besides the light crossing delay. We also consider electron densities in the accretion disc up to 1020 cm-3, which are found in most of the stellar mass black holes and in some active galactic nuclei. These high densities increase the amplitude of the reverberation lags below 1 keV since the reflection flux enhances in the same energy range. In addition, we investigate the properties of hard lags produced by variations in the power-law index of the continuum spectrum, which can be interpreted as due to roughly 3 per cent variability in the corona's optical depth and temperature. As a test case, we simultaneously fit the lag-energy spectra in a wide range of Fourier frequency for the black hole candidate MAXI J1820+0701820 observed with NICER. The best fit shows how the reverberation lags contribute even at the longer time-scales where the hard lags are important. This proves the importance of modelling these two lags together and self-consistently in order to constrain the parameters of the system.
CRIS-Team Scopus Importer:2021-09-24
Keywords: accretion; accretion discs; black hole physics; relativistic processes; X-rays: binaries; X-rays: galaxies

Modelling of 35-d superorbital cycle of B and V light curves of IMXB HZ Her/Her X-1 - Kolesnikov, D. A.; Shakura, N.; Postnov, K. A.; Volkov, I. M.; Bikmaev, I. F.; Irsmambetova, T. R.; Staubert, R.; Wilms, Jörn; Irtuganov, E.; Golysheva, P. Yu; Shugarov, S. Yu; Nikolenko, I.; et al. (Monthly Notices of the Royal Astronomical Society, 2020)
The X-ray binary Her X-1 consists of an accreting neutron star and the optical component HZ Her. The 35-d X-ray superorbital variability of this system is known, since its discovery in 1972 by the Uhuru satellite and is believed to be caused by forced precession of a warped accretion disc tilted to the orbital plane. We argue that the observed features of the 35-d optical variability of HZ Her can be explained by free precession of the neutron star with a period close to that of the forced disc. The model parameters include (a) the X-ray luminosity of the neutron star; (b) the optical flux from the accretion disc; and (c) the tilt of the inner and outer edges of the accretion disc. A possible synchronization mechanism based on the coupling between the neutron star free precession and the dynamical action of non-stationary gas streams is discussed.
CRIS-Team WoS Importer:2020-12-04

Modelling the light curves of ultraluminous X-ray sources as precession - Dauser, Thomas; Middleton, M.; Wilms, Jörn (Monthly Notices of the Royal Astronomical Society, 2017)
We present a freely available XSPEC model for the modulations seen in the long-term light curves of multiple ultraluminous X-ray sources (ULXs). By incorporating the physics of multiple electron scatterings (ray traced with a Monte Carlo routine), we go beyond analytical predictions and show that the geometrical beaming of radiation in the conical outflow can be more than a factor of 100 for opening angles smaller than 10 degrees. We apply our new model to the long-term, well-sampled Swift light curve of the recently confirmed ULX pulsar NGC 5907 X-1 with an established period of 78 d. Our results suggest that geometrical beaming together with a slight precession of the conical wind can describe the light curve with a consistent set of parameters for the wind. The small opening angle of roughly 10 degrees-13 degrees implies a highly supercritical flow and boosting factors of the order of B = 60-90 that would yield a fairly low surface magnetic field strength of 2 x 10(10) G.
Keywords: accretion; accretion discs; black hole physics; pulsars: individual: NGC 5907 ULX-1; X-rays: binaries

Modelling X-ray RMS spectra II: the ultrafast outflow of PDS 456 - Härer, Lucia; Parker, M. L.; Joyce, A.; Igo, Z.; Alston, W. N.; Furst, F.; Lobban, A. P.; Matzeu, G. A.; Reeves, J. N. (Monthly Notices of the Royal Astronomical Society, 2021)
We present an improved model for excess variance spectra describing ultrafast outflows and successfully apply it to the luminous (L-bol similar to 10(47)erg s(-1)) low-redshift (z = 0.184) quasar Pico del Dias Survey (PDS) 456. The model is able to account well for the broadening of the spike-like features of these outflows in the excess variance spectrum of PDS 456, by considering two effects: a correlation between the outflow' velocity and the logarithmic X-ray flux and intrinsic Doppler broadening with v(int) = 10(4) km s(-1). Die models were generated by calculating the fractional excess variance of count spectra from a Monte Carlo simulation. We find evidence that the outflow in PDS 456 is structured, i.e. there exist two or more layers with outflow velocities 0.27-0.30 c, 0.41-0.49 c, and 0.15-0.20 c for a possible third layer, which agrees well with the literature. We discuss the prospects of generally applicable models for excess variance spectra for detecting ultrafast outflow's and investigating their structure. We provide an estimate for the strength of the correlation between the outflow' velocity and the logarithmic X-ray flux and investigate its validity.
CRIS-Team WoS Importer:2021-01-29

Modulated High-Energy Gamma-Ray Emission from the Microquasar Cygnus X-3 - Abdo, A. A.; Ackermann, Markus; Ajello, M.; Axelsson, M.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Baughman, B. M.; Bechtol, K.; Bellazzini, R.; Berenji, B.; et al. (Science, 2009)
Microquasars are accreting black holes or neutron stars in binary systems with associated relativistic jets. Despite their frequent outburst activity, they have never been unambiguously detected emitting high-energy gamma rays. The Fermi Large Area Telescope (LAT) has detected a variable high-energy source coinciding with the position of the x-ray binary and microquasar Cygnus X-3. Its identification with Cygnus X-3 is secured by the detection of its orbital period in gamma rays, as well as the correlation of the LAT flux with radio emission from the relativistic jets of Cygnus X-3. The gamma-ray emission probably originates from within the binary system, opening new areas in which to study the formation of relativistic jets.

Monte Carlo simulations for the ANTARES underwater neutrino telescope - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. J.; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; Bertin, V.; Biagi, S.; et al. (Journal of Cosmology and Astroparticle Physics, 2021)
Monte Carlo simulations are a unique tool to check the response of a detector and to monitor its performance. For a deep-sea neutrino telescope, the variability of the environmental conditions that can affect the behaviour of the data acquisition system must be considered, in addition to a reliable description of the active parts of the detector and of the features of physics events, in order to produce a realistic set of simulated events. In this paper, the software tools used to produce neutrino and cosmic ray signatures in the telescope and the strategy developed to represent the time evolution of the natural environment and of the detector efficiency are described.
CRIS-Team Scopus Importer:2021-02-12
Keywords: Cosmic ray experiments; Neutrino astronomy; Neutrino detectors; Neutrino experiments

MUCHFUSS - Massive Unseen Companions to Hot Faint Underluminous Stars from SDSS - Geier, Stephan; Schaffenroth, Veronika; Hirsch, H.; Tillich, A.; Heber, Ulrich; Maxted, P. F. L.; Ostensen, R. H.; Barlow, B. N.; O'Toole, S. J.; Kupfer, Thomas; Marsh, T.; Gaensicke, Boris T; et al. (Astronomische Nachrichten, 2012)
The project Massive Unseen Companions to Hot Faint Underluminous Stars from SDSS (MUCHFUSS) aims at finding hot subdwarf stars with massive compact companions (white dwarfs with masses M > 1.0 M ⊙, neutron stars or black holes). The existence of such systems is predicted by binary evolution calculations and some candidate systems have been found. We identified ≃1100 hot subdwarf stars from the Sloan Digital Sky Survey (SDSS). Stars with high velocities have been reobserved and individual SDSS spectra have been analysed. About 70 radial velocity variable subdwarfs have been selected as good candidates for follow-up time resolved spectroscopy to derive orbital parameters and photometric follow-up to search for features like eclipses in the light curves. Up to now we found nine close binary sdBs with short orbital periods ranging from ≃0.07 d to 1.5 d. Two of them are eclipsing binaries with companions that are most likely of substellar nature © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2020-12-21
Keywords: Binaries: spectroscopic; Subdwarfs

Multi-frequency observations of SNR J0453-6829 in the LMC: A composite supernova remnant with a pulsar wind nebula - Haberl, Frank; Filipovic, M. D.; Bozzetto, L. M.; Crawford, E. J.; Points, S. D.; Pietsch, W.; De Horta, A. Y.; Tothill, Nicholas; Payne, J. L.; Sasaki, Manami (Astronomy & Astrophysics, 2012)
Context. The Large Magellanic Cloud (LMC) is rich in supernova remnants (SNRs), which can be investigated in detail with radio, optical, and X-ray observations. SNR J0453–6829 is an X-ray and radio-bright remnant in the LMC, within which previous studies revealed the presence of a pulsar wind nebula (PWN), making it one of the most interesting SNRs in the Local Group of galaxies. Aims. We study the emission of SNR J0453–6829 to improve our understanding of its morphology, spectrum, and thus the emission mechanisms in the shell and the PWN of the remnant. Methods. We obtained new radio data with the Australia Telescope Compact Array and analysed archival XMM-Newton observations of SNR J0453–6829. We studied the morphology of SNR J0453–6829 from radio, optical, and X-ray images and investigated the energy spectra in the different parts of the remnant. Results. Our radio results confirm that this LMC SNR hosts a typical PWN. The prominent central core of the PWN exhibits a radio spectral index αCore of −0.04 ± 0.04, while in the rest of the SNR shell the spectral slope is somewhat steeper with αShell = −0.43 ± 0.01. We detect regions with a mean polarisation of P = (12 ± 4)% at 6 cm and (9 ± 2)% at 3 cm. The full remnant is of roughly circular shape with dimensions of (31 ± 1) pc × (29 ± 1) pc. The spectral analysis of the XMM-Newton EPIC and RGS spectra allowed us to derive physical parameters for the SNR. Somewhat depending on the spectral model, we obtain for the remnant a shock temperature of around 0.2 keV and estimate the dynamical age to 12 000–15 000 years. Using a Sedov model we further derive an electron density in the X-ray emitting material of 1.56cm−3, typical for LMC remnants, a large swept-up mass of 830 M⊙, and an explosion energy of 7.6 × 1050 erg. These parameters indicate a well evolved SNR with an X-ray spectrum dominated by emission from the swept-up material.
Keywords: ISM: supernova remnants; ISM: individual objects: SNR J0453-6829; Magellanic Clouds

Multi-frequency study of DEM L299 in the Large Magellanic Cloud - Gabriele, Warth; Sasaki, Manami; Kavanagh, Patrick J.; Filipovic, M. D.; Points, Sean; Bozzetto, L. M. (Astronomy & Astrophysics, 2014)
Aims. We have studied the H ii region DEM L299 in the Large Magellanic Cloud (LMC) to understand its physical characteristics and morphology in different wavelengths. Methods. We performed a spectral analysis of archived XMM-Newton EPIC data and studied the morphology of DEM L299 in X-ray, optical, and radio wavelengths. We used Hα, [S ii], and [O iii] data from the Magellanic Cloud Emission Line Survey (MCELS) and radio 21 cm line data from the Australia Telescope Compact Array (ATCA) and the Parkes Telescope as well as radio continuum data (3 cm, 6 cm, 20 cm, 36 cm) from ATCA and from the Molonglo Synthesis Telescope (MOST). Results. Our morphological studies imply that, in addition to the supernova remnant SNR B0543-68.9 reported in previous studies, a superbubble also overlaps the SNR in projection. The position of the SNR is clearly defined through the [S ii]/Hα flux ratio image. Moreover, the optical images show a shell-like structure that is located farther to the north and is filled with diffuse X-ray emission, which again indicates the superbubble. Radio 21 cm line data show a shell around both objects. Radio continuum data show diffuse emission at the position of DEM L299, which appears clearly distinguished from the H ii region LHA 120-N 164 that lies south-west of it. We determined the spectral index of SNR B0543-68.9 to be α = −0.34, which indicates the dominance of thermal emission and therefore a rather mature remnant. We determined the basic properties of the diffuse X-ray emission for the SNR, the superbubble, and a possible blowout region of the bubble, as suggested by the optical and X-ray data. We obtained an age of (8.9+9.2) kyr for the −5.4 SNR and a temperature of (0.64+0.73) keV for the hot gas inside the SNR, as well as a thermal energy content and temperature of the −0.20 hot gas inside the superbubble of (4.3+8.1 ) × 1050 φ0.5 erg and (0.74+0.36 ) keV, with φ being the gas-filling factor. −2.6 −0.30 Conclusions. We conclude that DEM L299 consists of a superposition of SNR B0543-68.9 and a superbubble, which we identified based on optical data.
Keywords: Magellanic Clouds; ISM: supernova remnants; ISM: bubbles; HII regions; X-rays: ISM

Multifrequency study of SNR J0533-7202, a new supernova remnant in the LMC - Bozzetto, L. M.; Filipovic, M. D.; Crawford, E. J.; Sasaki, Manami; Maggi, P.; Haberl, Frank; Urosevic, D.; Payne, J. L.; De Horta, A. Y.; Stupar, M.; Gruendl, R.; Dickel, J. (Monthly Notices of the Royal Astronomical Society, 2013)
We present a detailed study of Australia Telescope Compact Array observations of a newly discovered Large Magellanic Cloud supernova remnant (SNR), SNR J0533-7202. This object follows a horseshoe morphology, with a size of 37 pc x 28 pc (1 pc uncertainty in each direction). It exhibits a radio spectrum with the intrinsic synchrotron spectral index of alpha = -0.47 +/- 0.06 between 73 and 6 cm. We report detections of regions showing moderately high fractional polarization at 6 cm, with a peak value of 36 +/- 6 per cent and a mean fractional polarization of 12 +/- 7 per cent. We also estimate an average rotation measure across the remnant of -591 rad m(-2). The current lack of deep X-ray observation precludes any conclusion about high-energy emission from the remnant. The association with an old stellar population favours a thermonuclear supernova origin of the remnant.
Keywords: polarization; ISM: supernova remnants; Magellanic Clouds; radio continuum: ISM; X-rays: ISM

Multi-frequency study of supernova remnants in the Large Magellanic Cloud Confirmation of the supernova remnant status of DEM L205 - Maggi, Pierre; Haberl, Frank; Filipovic, Miroslav D.; Bozzetto, L. M.; Points, Sean; Chu, You-Hua; Sasaki, Manami; Pietsch, Wolfgang; Gruendl, R. A.; Dickel, John; Smith, R. C.; Sturm, Richard; et al. (Astronomy & Astrophysics, 2012)
Context. The Large Magellanic Cloud (LMC) is an ideal target for the study of an unbiased and complete sample of supernova remnants (SNRs). We started an X-ray survey of the LMC with XMM-Newton, which, in combination with observations at other wavelengths, will allow us to discover and study remnants that are either even fainter or more evolved (or both) than previously known. Aims. We present new X-ray and radio data of the LMC SNR candidate DEM L205, obtained by XMM-Newton and ATCA, along with archival optical and infrared observations. Methods. We use data at various wavelengths to study this object and its complex neighbourhood, in particular in the context of the star formation activity, past and present, around the source. We analyse the X-ray spectrum to derive some remnant’s properties, such as age and explosion energy. Results. Supernova remnant features are detected at all observed wavelengths : soft and extended X-ray emission is observed, arising from a thermal plasma with a temperature kT between 0.2 keV and 0.3 keV. Optical line emission is characterised by an enhanced [S ii]-to-Hα ratio and a shell-like morphology, correlating with the X-ray emission. The source is not or only tentatively detected at near-infrared wavelengths (shorter than 10 μm), but there is a detection of arc-like emission at mid and far-infrared wavelengths (24 and 70 μm) that can be unambiguously associated with the remnant. We suggest that thermal emission from dust heated by stellar radiation and shock waves is the main contributor to the infrared emission. Finally, an extended and faint non-thermal radio emission correlates with the remnant at other wavelengths and we find a radio spectral index between −0.7 and −0.9, within the range for SNRs. The size of the remnant is ∼79 × 64 pc and we estimate a dynamical age of about 35 000 years. Conclusions. We definitely confirm DEM L205 as a new SNR. This object ranks amongst the largest remnants known in the LMC. The numerous massive stars and the recent outburst in star formation around the source strongly suggest that a core-collapse supernova is the progenitor of this remnant.
Keywords: Magellanic Clouds; ISM: supernova remnants; ISM: individual objects: MCSNR J0528-6727; X-rays: ISM

Multi-frequency study of supernova remnants in the Large Magellanic Cloud: The case of LMC SNR J0530–7007 - De Horta, A. Y.; Filipovic, M. D.; Bozzetto, L. M.; Maggi, P.; Haberl, F.; Crawford, E. J.; Sasaki, Manami; Urosevic, D.; Pietsch, W.; Gruendl, R.; Dickel, J.; Tothill, N. F. H.; et al. (Astronomy & Astrophysics, 2012)
Context. The supernova remnants (SNRs) known in the Large Magellanic Cloud (LMC) show a variety of morphological structures in the different wavelength bands. This variety is the product of the conditions in the surrounding medium with which the remnant interacts and the inherent circumstances of the supernova event itself. Aims. This paper performs a multi-frequency study of the LMC SNR J0530–7007 by combining Australia Telescope Compact Array (ATCA), Molonglo Observatory Synthesis Telescope (MOST), Röntgensatellit (ROSAT) and Magellanic Clouds Emission Line Survey (MCELS) observations. Methods. We analysed radio-continuum, X-ray and optical data and present a multi-wavelength morphological study of LMC SNR J0530–7007. Results. We find that this object has a shell-type morphology with a size of 215′′ × 180′′ (52 pc × 44 pc); a radio spectral index (α = −0.85 ± 0.13); with [S ii]/Hα > 0.4 in the optical; and the presence of non-thermal radio and X-ray emission. Conclusions. We confirmed this object as a bona-fide shell-type SNR which is probably a result of a Type Ia supernova.
Keywords: ISM: supernova remnants; Magellanic Clouds; radio continuum: ISM; ISM: individual objects: SNR J0530-7007

Multi-messenger Observations of a Binary Neutron Star Merger - Abbott, B. P.; Abbott, R.; Abbott, T. D.; Acernese, F.; Ackley, K.; Adams, C.; Adams, T.; Addesso, Paolo; Adhikari, R. X.; Adya, V. B.; Affeldt, C.; Afrough, M.; et al. (Astrophysical Journal Letters, 2017)
On 2017 August 17 a binary neutron star coalescence candidate (later designated GW170817) with merger time 12:41:04 UTC was observed through gravitational waves by the Advanced LIGO and Advanced Virgo detectors. The Fermi Gamma-ray Burst Monitor independently detected a gamma-ray burst (GRB 170817A) with a time delay of similar to 1.7 s with respect to the merger time. From the gravitational-wave signal, the source was initially localized to a sky region of 31 deg(2) at a luminosity distance of 40(-8)(+8) Mpc and with component masses consistent with neutron stars. The component masses were later measured to be in the range 0.86 to 2.26 M-circle dot. An extensive observing campaign was launched across the electromagnetic spectrum leading to the discovery of a bright optical transient (SSS17a, now with the IAU identification of AT 2017gfo) in NGC 4993 (at similar to 40 Mpc) less than 11 hours after the merger by the One-Meter, Two Hemisphere (1M2H) team using the 1 m Swope Telescope. The optical transient was independently detected by multiple teams within an hour. Subsequent observations targeted the object and its environment. Early ultraviolet observations revealed a blue transient that faded within 48 hours. Optical and infrared observations showed a redward evolution over similar to 10 days. Following early non-detections, X-ray and radio emission were discovered at the transient's position similar to 9 and similar to 16 days, respectively, after the merger. Both the X-ray and radio emission likely arise from a physical process that is distinct from the one that generates the UV/optical/near-infrared emission. No ultra-high-energy gamma-rays and no neutrino candidates consistent with the source were found in follow-up searches. These observations support the hypothesis that GW170817 was produced by the merger of two neutron stars in NGC4993 followed by a short gamma-ray burst (GRB 170817A) and a kilonova/macronova powered by the radioactive decay of r-process nuclei synthesized in the ejecta.
Keywords: gravitational waves; stars: neutron

Multi-object spectroscopy of stars in the CoRoT fields: I. Early-type stars in the CoRoT-fields IRa01, LRa01, LRa02 - Sebastian, Daniel; Guenther, E. W.; Schaffenroth, Veronika; Gandolfi, Davide; Geier, Stephan; Heber, Ulrich; Deleuil, Magali; Moutou, C. (Astronomy & Astrophysics, 2012)
Context. Observations of giant stars indicate that the frequency of giant planets is much higher for intermediate-mass stars than for solar-like stars. Up to now all known planets of giant stars orbit at relatively far distances from their host stars. It is not known whether intermediate-mass stars also had many close-in planets when they were on the main sequence, which were then engulfed when the star became a giant star. To understand the formation and evolution of planets it is therefore important to find out whether main-sequence stars of intermediate-mass have close-in planets or not. Aims. A survey for transiting planets of intermediate-mass stars would be ideal to solve this question, because the detection of transiting planets is not affected by the rapid rotation of these stars. With CoRoT it is possible to detect transiting planets around stars up to a spectral type B4V. As a first step for an efficient survey we need to identify intermediate-mass stars in the CoRoT-fields, which can then be used as an input list. Methods. To compile the input list we derived the spectral types of essentially all O, B and A stars down to 14.5 mag in the CoRoT fields IRa01, LRa01, LRa02 taken with the multi-object spectrograph AAOmega. We determined the spectral types by comparing the spectra with template spectra from a library. Results. In total we identify 1856 A and B stars that have been observed with CoRoT. Using multiple spectra of these stars, we find that the accuracy of the resulting spectral classification is 1.61 ± 0.14 sub-classes for A and B stars. Conclusions. Given the number of planets that have been detected in these fields amongst late-type stars, we estimate that there are one to four transiting planets of intermediate-mass stars waiting to be discovered. Our survey not only allows us to carry out a dedicated planet search programme but is also essential for any types of studies of the light curves of early-type stars in the CoRoT database. We also show that it would be possible to extend the survey to all fields that CoRoT has observed using photometrically determined spectral types. © 2012 ESO.
CRIS-Team Scopus Importer:2020-12-21
Keywords: Planets and satellites: detection; Planets and satellites: formation; Stars: early-type; Surveys; Techniques: spectroscopic

Multi-periodic pulsations of a stripped red-giant star in an eclipsing binary system - Maxted, Pierre F. L.; Serenelli, Aldo M.; Miglio, Andrea; Marsh, Thomas R.; Heber, Ulrich; Dhillon, Vikram S.; Littlefair, Stuart; Copperwheat, Chris; Smalley, Barry; Breedt, Elme; Schaffenroth, Veronika (Nature, 2013)
Low-mass white-dwarf stars are the remnants of disrupted red-giant stars in binary millisecond pulsars and other exotic binary star systems. Some low-mass white dwarfs cool rapidly, whereas others stay bright for millions of years because of stable fusion in thick surface hydrogen layers. This dichotomy is not well understood, so the potential use of low-mass white dwarfs as independent clocks with which to test the spin-down ages of pulsars or as probes of the extreme environments in which low-mass white dwarfs form cannot fully be exploited. Here we report precise mass and radius measurements for the precursor to a low-mass white dwarf. We find that only models in which this disrupted red-giant star has a thick hydrogen envelope can match the strong constraints provided by our data. Very cool low-mass white dwarfs must therefore have lost their thick hydrogen envelopes by irradiation from pulsar companions or by episodes of unstable hydrogen fusion (shell flashes). We also find that this low-mass white-dwarf precursor is a type of pulsating star not hitherto seen. The observed pulsation frequencies are sensitive to internal processes that determine whether this star will undergo shell flashes. © 2013 Macmillan Publishers Limited. All rights reserved.
CRIS-Team Scopus Importer:2020-12-21

Multiwavelength analysis of the X-ray spur and southeast of the Large Magellanic Cloud - Knies, Jonathan; Sasaki, Manami; Fukui, Y.; Tsuge, K.; Haberl, F.; Points, S.; Kavanagh, P. J.; Filipović, M. D. (Astronomy & Astrophysics, 2021)
Aims. The giant H II region 30 Doradus (30 Dor) located in the eastern part of the Large Magellanic Cloud is one of the most active star-forming regions in the Local Group. Studies of H I data have revealed two large gas structures which must have collided with each other in the region around 30 Dor. In X-rays there is extended emission (∼1 kpc) south of 30 Dor called the X-ray spur, which appears to be anticorrelated with the H I gas. We study the properties of the hot interstellar medium (ISM) in the X-ray spur and investigate its origin including related interactions in the ISM. Methods. We analyzed new and archival XMM-Newton data of the X-ray spur and its surroundings to determine the properties of the hot diffuse plasma. We created detailed plasma property maps by utilizing the Voronoi tessellation algorithm. We also studied H I and CO data, as well as optical line emission data of Hα and [S II], and compared them to the results of the X-ray spectral analysis. Results. We find evidence of two hot plasma components with temperatures of kT1 ∼ 0.2 keV and kT2 ∼ 0.5-0.9 keV, with the hotter component being much more pronounced near 30 Dor and the X-ray spur. In 30 Dor, the plasma has most likely been heated by massive stellar winds and supernova remnants. In the X-ray spur, we find no evidence of heating by stars. Instead, the X-ray spur must have been compressed and heated by the collision of the H I gas.
CRIS-Team Scopus Importer:2021-04-30
Keywords: Galaxies: ISM; ISM: general; ISM: structure; Magellanic Clouds; Radio lines: ISM; X-rays: ISM

Multiwavelength Characterization of the High-mass X-Ray Binary Population of M31 - Lazzarini, Margaret; Williams, Benjamin F.; Durbin, Meredith; Dalcanton, Julianne; Antoniou, Vallia; Binder, Breanna A.; Eracleous, Michael; Plucinsky, Paul P.; Sasaki, Manami; Vulic, Neven (Astrophysical Journal, 2021)
We present our analysis of high-quality high-mass X-ray binary (HMXB) candidates in M31 selected from point-source optical counterpart candidates from the Chandra-PHAT survey catalog. We fit the spectral energy distributions of optical counterpart candidates using the Bayesian Extinction and Stellar Tool. We used the best-fit luminosity, effective temperature, radius, and dust reddening for the companion stars in combination with the local star formation history, dust maps of M31, published X-ray spectral fits from XMM-Newton observations, IR colors, and Chandra X-ray hardness ratios to determine our best sample of HMXB candidates. The age distribution of the HMXB sample appears peaked between 10 and 50 Myr, consistent with findings in other nearby galaxies. Using the age distribution and mean star formation rate (SFR), we find that 80-136 HMXBs were produced per unit of SFR over the last 50 Myr and 89-163 HMXBs were produced per unit of SFR over the last 80 Myr, if we expand the assumed age limit beyond the lifetimes of single massive stars. We also calculate the HMXB production rate (HMXBs/M) over time, which ranges from 7 x 10(-7) to 4 x 10(-6) HMXBs/M over the last 80 Myr, in agreement with both theoretical predictions and measured production rates in other galaxies.
CRIS-Team WoS Importer:2021-02-05

Multiwavelength observations of the black hole transient Swift J1745-26 during the outburst decay - Kalemci, E.; Arabaci, M. Ozbey; Guver, Tolga; Russell, D. M.; Tomsick, J. A.; Wilms, Jörn; Weidenspointner, G.; Kuulkers, E.; Falanga, M.; Dincer, Tolga; Drave, S.; Belloni, T.; et al. (Monthly Notices of the Royal Astronomical Society, 2014)
We characterized the broad-band X-ray spectra of Swift J1745-26 during the decay of the 2013 outburst using INTEGRAL ISGRI, JEM-X and Swift XRT. The X-ray evolution is compared to the evolution in optical and radio. We fit the X-ray spectra with phenomenological and Comptonization models. We discuss possible scenarios for the physical origin of an similar to 50 d flare observed both in optical and X-rays similar to 170 d after the peak of the outburst. We conclude that it is a result of enhanced mass accretion in response to an earlier heating event. We characterized the evolution in the hard-X-ray band and showed that for the joint ISGRI-XRT fits, the e-folding energy decreased from 350 to 130 keV, while the energy where the exponential cut-off starts increased from 75 to 112 keV as the decay progressed. We investigated the claim that high-energy cut-offs disappear with the compact jet turning on during outburst decays, and showed that spectra taken with HEXTE on RXTE provide insufficient quality to characterize cut-offs during the decay for typical hard-X-ray fluxes. Long INTEGRAL monitoring observations are required to understand the relation between the compact jet formation and hard-X-ray behaviour. We found that for the entire decay (including the flare), the X-ray spectra are consistent with thermal Comptonization, but a jet synchrotron origin cannot be ruled out.
Keywords: stars: black holes; stars: individual: Swift J174510.8-2624; X-rays: binaries

Multi-wavelength study of Mrk 421 during a TeV flare - Gokus, Andrea; Kreikenbohm, A.; Leiter, K.; Bretz, T.; Dauser, Thomas; Dorner, D.; Elsaesser, D.; Eppel, F.; Heßdörfer, J.; Kadler, M.; Kraus, A.; Kreter, M.; et al. (Proceedings of Science, 2022)
The blazar Mrk 421 shows frequent, short flares in the TeV energy regime. Due to the fast nature of such episodes, we often fail to obtain sufficient simultaneous information about flux variations in several energy bands. To overcome this lack of multi-wavelength (MWL) coverage, especially for the pre- and post-flare periods, we have set up a monitoring program with the FACT telescope (TeV energies) and the Neil Gehrels Swift Observatory (X-rays). On 2019 June 9, Mrk 421 showed a TeV outburst reaching a flux level of more than two times the flux of the Crab Nebula at TeV energies. We acquired simultaneous data in the X-rays with additional observations by XMM-Newton and INTEGRAL. For the first time, we can study a TeV blazar in outburst taking advantage of highly sensitive X-ray data from XMM-Newton and INTEGRAL combined. Our dataset is complemented by pointed radio observations by Effelsberg at GHz frequencies. We present our first results, including the γ-ray and X-ray light curves, a timing analysis of the X-ray data obtained with XMM-Newton , as well as the radio spectra before, during and after the flare.
CRIS-Team Scopus Importer:2022-12-23

MURCHISON WIDEFIELD ARRAY LIMITS on RADIO EMISSION from ANTARES NEUTRINO EVENTS - Croft, Steve; Kaplan, D. L.; Tingay, S. J.; Murphy, Tara; Bell, M. E.; Rowlinson, Antonia; Adrian-Martinez, S.; Ageron, M.; Albert, A.; Andre, Michel; Anton, Gisela; Ardid, Miguel; et al. (Astrophysical Journal Letters, 2016)
We present a search, using the Murchison Widefield Array (MWA), for electromagnetic (EM) counterparts to two candidate high-energy neutrino events detected by the ANTARES neutrino telescope in 2013 November and 2014 March. These events were selected by ANTARES because they are consistent, within 0°.4, with the locations of galaxies within 20 Mpc of Earth. Using MWA archival data at frequencies between 118 and 182 MHz, taken ∼20 days prior to, at the same time as, and up to a year after the neutrino triggers, we look for transient or strongly variable radio sources that are consistent with the neutrino positions. No such counterparts are detected, and we set a 5σ upper limit for low-frequency radio emission of ∼10 erg s for progenitors at 20 Mpc. If the neutrino sources are instead not in nearby galaxies, but originate in binary neutron star coalescences, our limits place the progenitors at z 0.2. While it is possible, due to the high background from atmospheric neutrinos, that neither event is astrophysical, the MWA observations are nevertheless among the first to follow up neutrino candidates in the radio, and illustrate the promise of wide-field instruments like MWA for detecting EM counterparts to such events.
Keywords: neutrinos; radio continuum: general

Mysterious odd radio circle near the large magellanic cloud - an intergalactic supernova remnant? - Filipovic, Miroslav D.; Payne, J. L.; Alsaberi, R. Z. E.; Norris, R. P.; Macgregor, P. J.; Rudnick, Lawrence; Koribalski, B. S.; Leahy, D.; Ducci, L.; Kothes, R.; Andernach, H.; Barnes, L.; et al. (Monthly Notices of the Royal Astronomical Society, 2022)
We report the discovery of J0624-6948, a low-surface brightness radio ring, lying between the Galactic Plane and the large magellanic cloud (LMC). It was first detected at 888 MHz with the Australian Square Kilometre Array Pathfinder (ASKAP), and with a diameter of similar to 196 arcsec. This source has phenomenological similarities to odd radio circles (ORCs). Significant differences to the known ORCs - a flatter radio spectral index, the lack of a prominent central galaxy as a possible host, and larger apparent size - suggest that J0624-6948 may be a different type of object. We argue that the most plausible explanation for J0624-6948 is an intergalactic supernova remnant due to a star that resided in the LMC outskirts that had undergone a single-degenerate type Ia supernova, and we are seeing its remnant expand into a rarefied, intergalactic environment. We also examine if a massive star or a white dwarf binary ejected from either galaxy could be the supernova progenitor. Finally, we consider several other hypotheses for the nature of the object, including the jets of an active galactic nucleus (30Dor) or the remnant of a nearby stellar super-flare.
CRIS-Team WoS Importer:2022-04-01

New ASKAP radio supernova remnants and candidates in the Large Magellanic Cloud - Bozzetto, Luke M.; Filipovic, Miroslav D.; Sano, Hidetoshi; Alsaberi, R. Z. E.; Barnes, L. A.; Bojicic, I. S.; Brose, R.; Chomiuk, L.; Crawford, E. J.; Dai, Shi; Ghavam, M.; Haberl, F.; et al. (Monthly Notices of the Royal Astronomical Society, 2023)
We present a new Australian Square Kilometre Array Pathfinder (ASKAP) sample of 14 radio supernova remnants (SNR) candidates in the Large Magellanic Cloud (LMC). This new sample is a significant increase to the known number of older, larger, and low surface brightness LMC SNRs. We employ a multi frequency search for each object and found possible traces of optical and occasionally X-ray emission in several of these 14 SNR candidates. One of these 14 SNR candidates (MCSNR J0522 - 6543) has multifrequency properties that strongly indicate a bona fide SNR. We also investigate a sample of 20 previously suggested LMC SNR candidates and confirm the SNR nature of MCSNR J0506 - 6815. We detect lower surface brightness SNR candidates which were likely formed by a combination of shock waves and strong stellar winds from massive progenitors (and possibly surrounding OB stars). Some of our new SNR candidates are also found in lower density environments in which SNe type Ia explode inside a previously excavated interstellar medium.
CRIS-Team WoS Importer:2023-01-27

New constraints on all flavor Galactic diffuse neutrino emission with the ANTARES telescope - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. -J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Belhorma, B.; Bertin, V.; et al. (Physical Review D - Particles, Fields, Gravitation and Cosmology, 2017)
The flux of very high-energy neutrinos produced in our Galaxy by the interaction of accelerated cosmic rays with the interstellar medium is not yet determined. The characterization of this flux will shed light on Galactic accelerator features, gas distribution morphology and Galactic cosmic ray transport. The central Galactic plane can be the site of an enhanced neutrino production, thus leading to anisotropies in the extraterrestrial neutrino signal as measured by the IceCube Collaboration. The ANTARES neutrino telescope, located in the Mediterranean Sea, offers a favorable view of this part of the sky, thereby allowing for a contribution to the determination of this flux. The expected diffuse Galactic neutrino emission can be obtained, linking a model of generation and propagation of cosmic rays with the morphology of the gas distribution in the Milky Way. In this paper, the so-called "gamma model" introduced recently to explain the high-energy gamma-ray diffuse Galactic emission is assumed as reference. The neutrino flux predicted by the "gamma model" depends on the assumed primary cosmic ray spectrum cutoff. Considering a radially dependent diffusion coefficient, this proposed scenario is able to account for the local cosmic ray measurements, as well as for the Galactic gamma-ray observations. Nine years of ANTARES data are used in this work to search for a possible Galactic contribution according to this scenario. All flavor neutrino interactions are considered. No excess of events is observed, and an upper limit is set on the neutrino flux of 1.1 (1.2) times the prediction of the "gamma model," assuming the primary cosmic ray spectrum cutoff at 5 (50) PeV. This limit excludes the diffuse Galactic neutrino emission as the major cause of the "spectral anomaly" between the two hemispheres measured by IceCube.

New optically identified supernova remnants in the Large Magellanic Cloud - Yew, Miranda; Filipovic, Miroslav D.; Stupar, Milorad; Points, Sean D.; Sasaki, Manami; Maggi, Pierre; Haberl, Frank; Kavanagh, Patrick J.; Parker, Quentin A.; Crawford, Evan J.; Vukotic, Branislav; Urosevic, Dejan; et al. (Monthly Notices of the Royal Astronomical Society, 2021)
We present a new optical sample of three Supernova Remnants (SNRs) and 16 Supernova Remnant (SNR) candidates in the Large Magellanic Cloud (LMC). These objects were originally selected using deep H α, [S ii], and [O iii] narrow-band imaging. Most of the newly found objects are located in less dense regions, near or around the edges of the LMC's main body. Together with previously suggested MCSNR J0541-6659, we confirm the SNR nature for two additional new objects: MCSNR J0522-6740 and MCSNR J0542-7104. Spectroscopic follow-up observations for 12 of the LMC objects confirm high [S ii]/H α emission-line ratios ranging from 0.5 to 1.1. We consider the candidate J0509-6402 to be a special example of the remnant of a possible type Ia Supernova (SN) which is situated some 2° (∼1.75 kpc) north from the main body of the LMC. We also find that the SNR candidates in our sample are significantly larger in size than the currently known LMC SNRs by a factor of ∼2. This could potentially imply that we are discovering a previously unknown but predicted, older class of large LMC SNRs that are only visible optically. Finally, we suggest that most of these LMC SNRs are residing in a very rarefied environment towards the end of their evolutionary span where they become less visible to radio and X-ray telescopes.
CRIS-Team Scopus Importer:2021-02-05
Keywords: ISM: supernova remnants; Magellanic Clouds; techniques: spectroscopic

New XMM-Newton observations of faint, evolved supernova remnants in the Large Magellanic Cloud - Kavanagh, P. J.; Sasaki, Manami; Filipovic, M. D.; Points, S. D.; Bozzetto, L. M.; Haberl, F.; Maggi, P.; Maitra, C. (Monthly Notices of the Royal Astronomical Society, 2022)
The Large Magellanic Cloud (LMC) hosts a rich population of supernova remnants (SNRs), our knowledge of which is the most complete of any galaxy. However, there remain many candidate SNRs, identified through optical and radio observations where additional X-ray data can confirm their SNR nature and provide details on their physical properties. In this paper, we present XMM-Newton observations that provide the first deep X-ray coverage of ten objects, comprising eight candidates and two previously confirmed SNRs. We perform multifrequency studies using additional data from the Magellanic Cloud Emission Line Survey (MCELS) to investigate their broad-band emission and used Spitzer data to understand the environment in which the objects are evolving. We confirm seven of the eight candidates as bona-fide SNRs. We used a multifrequency morphological study to determine the position and size of the remnants. We identify two new members of the class of evolved Fe-rich remnants in the Magellanic Clouds (MCs), several SNRs well into their Sedov-phase, one SNR likely projected towards a H ii region, and a faint, evolved SNR with a hard X-ray core which could indicate a pulsar wind nebula. Overall, the seven newly confirmed SNRs represent a similar to 10-per cent increase in the number of LMC remnants, bringing the total number to 71, and provide further insight into the fainter population of X-ray SNRs.
CRIS-Team WoS Importer:2022-08-26

NICER/NuSTAR Characterization of 4U 1957+11: A Near Maximally Spinning Black Hole Potentially in the Mass Gap - Barillier, Erin; Grinberg, Victoria; Horn, David; Nowak, Michael A. A.; Remillard, Ronald A. A.; Steiner, James F. F.; Walton, Dominic J. J.; Wilms, Jörn (Astrophysical Journal, 2023)
4U 1957+11 is a black hole candidate system that has been in a soft X-ray spectral state since its discovery. We present analyses of recent joint NICER and NuSTAR spectra, which are extremely well described by a highly inclined disk accreting into a near maximally spinning black hole. Owing to the broad X-ray coverage of NuSTAR, the fitted spin and inclination are strongly constrained for our hypothesized disk models. The faintest spectra are observed out to 20 keV, even though their hard tail components are almost absent when described with a simple corona. The hard tail increases with luminosity, but shows clear two-track behavior with one track having appreciably stronger tails. The disk spectrum color-correction factor is anticorrelated with the strength of the hard tail (e.g., as measured by the Compton y parameter). Although the spin and inclination parameters are strongly constrained for our chosen model, the mass and distance are degenerate parameters. We use our spectral fits, along with a theoretical prior on color-correction, an observational prior on likely fractional Eddington luminosity, and an observational prior on distance obtained from Gaia studies, to present mass and distance contours for this system. The most likely parameters, given our presumed disk model, suggest a 4.6 M ⊙ black hole at 7.8 kpc observed at luminosities ranging from ≈1.7% to 9% of Eddington. This would place 4U 1957+11 as one of the few actively accreting sources within the mass gap of ≈2-5 M ⊙ where there are few known massive neutron stars or low-mass black holes. Higher mass and distance, however, remain viable.
CRIS-Team Scopus Importer:2023-03-10

NICER-NuSTAR Observations of the Neutron Star Low-mass X-Ray Binary 4U 1735-44 - Ludlam, R. M.; Cackett, E. M.; Garcia, Javier; Miller, J. M.; Bult, P. M.; Strohmayer, T. E.; Guillot, S.; Jaisawal, G. K.; Malacaria, C.; Fabian, A. C.; Markwardt, C. B. (Astrophysical Journal, 2020)
We report on the first simultaneous Neutron Star Interior Composition Explore (NICER) and Nuclear Spectroscopic Telescope Array (NuSTAR) observations of the neutron star (NS) low-mass X-ray binary 4U 1735-44, obtained in 2018 August. The source was at a luminosity of similar to 1.8 (D/5.6 kpc)(2) x 10(37) erg s(-1) in the 0.4-30 keV band. We account for the continuum emission with two different continuum descriptions that have been used to model the source previously. Despite the choice in continuum model, the combined passband reveals a broad Fe K line indicative of reflection in the spectrum. In order to account for the reflection spectrum we utilize a modified version of the reflection model relxill that is tailored for thermal emission from accreting NSs. Alternatively, we also use the reflection convolution model of rfxconv to model the reflected emission that would arise from a Comptonized thermal component for comparison. We determine that the innermost region of the accretion disk extends close to the innermost stable circular orbit (R-ISCO) at the 90% confidence level regardless of reflection model. Moreover, the current flux calibration of NICER is within 5% of the NuSTAR/FPMA(B).
CRIS-Team WoS Importer:2020-06-16

Nitrogen X-ray absorption in the local ISM - Gatuzz, Efrain; Garcia, Javier; Kallman, Timothy R. (Monthly Notices of the Royal Astronomical Society, 2021)
Nitrogen is one of the most abundant metals in the interstellar medium (ISM), and thus it constitutes an excellent test to study a variety of astrophysical environments, ranging from nova to active galactic nuclei. We present a detailed analysis of the gaseous component of the N K-edge using high-resolution XMM-Newton spectra of 12 Galactic and 40 extragalactic sources. For each source, we have estimated column densities for N i, N ii, N iii, N v, N vi, and N vii ionic species, which trace the cold, warm, and hot phases of the local Galactic ISM. We have found that the cold-warm component column densities decrease with the Galactic latitude, while the hot component does not. Moreover, the cold column density distribution is in good agreement with UV measurements. This is the first detailed analysis of the nitrogen K-edge absorption due to ISM using high-resolution X-ray spectra.
CRIS-Team Scopus Importer:2021-07-09
Keywords: Galaxy: structure; ISM: Abundances; ISM: Atoms; ISM: structure; X-rays: ISM

NLTE spectroscopic analysis of the He-3 anomaly in subluminous B-type stars - Schneider, David; Irrgang, Andreas; Heber, Ulrich; Heber, Ulrich; Nieva, M. F.; Przybilla, N. (Astronomy & Astrophysics, 2018)
Several B-type main-sequence stars show chemical peculiarities. A particularly striking class are the He-3 stars, which exhibit a remarkable enrichment of He-3 with respect to He-4. This isotopic anomaly has also been found in blue horizontal branch (BHB) and subdwarf B (sdB) stars, which are helium-core burning stars of the extreme horizontal branch. Recent surveys uncovered 11 He-3 sdBs. The He-3 anomaly is not due to thermonuclear processes, but caused by atomic diffusion in the stellar atmosphere. Using a hybrid local/non-local thermodynamic equilibrium (LTE/NLTE) approach for B-type stars, we analyzed high-quality spectra of two known He-3 BHBs and nine known He-3 sdBs to determine their isotopic helium abundances and He-4/He-3 abundance ratios. We redetermined their atmospheric parameters and analyzed selected He I lines, including lambda 4922 angstrom and lambda 6678 angstrom, which are very sensitive to He-4/He-3. Most of the He-3 sdBs cluster in a narrow temperature strip between 26 000K and 30 000K and are helium deficient in accordance with previous LTE analyses. BD + 48 degrees 2721 is reclassified as a BHB star because of its low temperature (T-eff = 20 700 K). Whereas He-4 is almost absent (He-4/He-3 < 0.25) in most of the known He-3 stars, other sample stars show abundance ratios up to He-4/He-3 similar to 2.51. A search for He-3 stars among 26 candidate sdBs from the ESO SPY survey led to the discovery of two new He-3 sdB stars (HE 0929-0424 and HE 1047-0436). The observed helium line profiles of all BHBs and of three sdBs are not matched by chemically homogeneous atmospheres, but hint at vertical helium stratification. This phenomenon has been seen in other peculiar B-type stars, but is found for the first time for sdBs. We estimate helium to increase from the outer to the inner atmosphere by factors ranging from 1.4 (SB 290) up to 8.0 (BD + 48 degrees 2721).
Keywords: stars: chemically peculiar; stars: atmospheres; stars: fundamental parameters; stars: abundances; subdwarfs; stars: horizontal-branch

No anticorrelation between cyclotron line energy and X-ray flux in 4U 0115+634 - Müller, Sebastian; Ferrigno, C.; Kühnel, Matthias; Schoenherr, G.; Becker, P. A.; Wolff, M. T.; Hertel, Dominik; Schwarm, Fritz-Walter; Grinberg, Victoria; Obst, M.; Caballero, I.; Pottschmidt, K.; et al. (Astronomy & Astrophysics, 2013)
We report on an outburst of the high mass X-ray binary 4U 0115+634 with a pulse period of 3.6 s in 2008 March/April as observed with RXTE and INTEGRAL. During the outburst the neutron star's luminosity varied by a factor of 10 in the 3-50 keV band. In agreement with earlier work we find evidence of five cyclotron resonance scattering features at similar to 10.7, 21.8, 35.5, 46.7, and 59.7 keV. Previous work had found an anticorrelation between the fundamental cyclotron line energy and the X-ray flux. We show that this apparent anticorrelation is probably due to the unphysical interplay of parameters of the cyclotron line with the continuum models used previously, e. g., the negative and positive exponent power law (NPEX). For this model, we show that cyclotron line modeling erroneously leads to describing part of the exponential cutoff and the continuum variability, and not the cyclotron lines. When the X-ray continuum is modeled with a simple exponentially cutoff power law modified by a Gaussian emission feature around 10 keV, the correlation between the line energy and the flux vanishes, and the line parameters remain virtually constant over the outburst. We therefore conclude that the previously reported anticorrelation is an artifact of the assumptions adopted in the modeling of the continuum.
Keywords: X-rays: binaries; pulsars: individual 4U 0115+634; magnetic fields

NON-LOCAL THERMAL EQUILIBRIUM MODEL ATMOSPHERES FOR THE HOTTEST WHITE DWARFS: SPECTRAL ANALYSIS OF THE COMPACT COMPONENT IN NOVA V4743 Sgr - Rauch, T.; Orio, M.; Gonzales-Riestra, R.; Nelson, T.; Still, M.; Werner, Klaus; Wilms, Jörn (Astrophysical Journal, 2010)
Half a year after its outburst in 2002 September, nova V4743 Sgr evolved into the brightest supersoft X-ray source in the sky with a flux maximum around 30 angstrom. We calculated grids of synthetic energy distributions based on non-local thermal equilibrium model atmospheres for the analysis of the hottest white dwarfs (WDs) and present the result of fits to Chandra and XMM-Newton grating X-ray spectra of V4743 Sgr of outstanding quality, exhibiting prominent resonance lines of C v, C VI, N VI, N VII, and O VII in absorption. The nova reached its highest effective temperature (T(eff) = 740 +/- 70 kK) around 2003 April and remained at that temperature at least until 2003 September. We conclude that the WD is massive, approximate to 1.1-1.2M(circle dot). The nuclear-burning phase lasted for 2-2.5 years after the outburst, probably the average duration for a classical nova. The photosphere of V4743 Sgr was strongly carbon deficient (approximate to 0.01 times solar) and enriched in nitrogen and oxygen (>5 times solar). Especially the very low C/N ratio indicates that the material at the WD's surface underwent thermonuclear burning. Thus, this nova retained some of the accreted material and did not eject all of it in outburst. From 2003 March to September, the nitrogen abundance is strongly decreasing; new material is probably already being accreted at this stage.
Keywords: novae; cataclysmic variables; stars: abundances; stars: AGB and post-AGB; stars: atmospheres; stars: individual (V4743 Sgr); white dwarfs

Non-local thermodynamic equilibrium spectral analysis of five hot, hydrogen-deficient pre-white dwarfs - Werner, Klaus; Reindl, Nicole; Dorsch, Matti; Geier, Stephan; Munari, Ulisse; Raddi, Roberto (Astronomy & Astrophysics, 2022)
Hot, compact, hydrogen-deficient pre-white dwarfs (pre-WDs) with effective temperatures of T-eff > 70 000 K and a surface gravity of 5.0 < log g < 7.0 are rather rare objects despite recent and ongoing surveys. It is believed that they are the outcome of either single star evolution (late helium-shell flash or late helium-core flash) or binary star evolution (double WD merger). Their study is interesting because the surface elemental abundances reflect the physics of thermonuclear flashes and merger events. Spectroscopically they are divided in three different classes, namely PG1159, O(He), or He-sdO. We present a spectroscopic analysis of five such stars that turned out to have atmospheric parameters in the range T-eff = 70 000-80 000 K and log g = 5.2-6.3. The three investigated He-sdOs have a relatively high hydrogen mass fraction (10%) that is unexplained by both single (He core flash) and binary evolution (He-WD merger) scenarios. The O(He) star JL 9 is probably a binary helium-WD merger, but its hydrogen content (6%) is also at odds with merger models. We found that RL 104 is the 'coolest' (T-eff = 80 000 K) member of the PG1159 class in a pre-WD stage. Its optical spectrum is remarkable because it exhibits C iv lines involving Rydberg states with principal quantum numbers up to n = 22. Its rather low mass (0.48(-0.02)(+0.03)M(circle dot)) is difficult to reconcile with the common evolutionary scenario for PG1159 stars due to it being the outcome of a (very) late He-shell flash. The same mass-problem faces a merger model of a close He-sdO plus CO WD binary that predicts PG1159-like abundances. Perhaps RL 104 originates from a very late He-shell flash in a CO/He WD formed by a merger of two low-mass He-WDs.
CRIS-Team WoS Importer:2022-02-11

Normalizing a relativistic model of X-ray reflection. Definition of the reflection fraction and its implementation in relxill - Dauser, Thomas; Garcia, J.; Walton, D. J.; Eikmann, Wiebke; Kallman, T.; Mcclintock, J.; Wilms, Jörn (Astronomy & Astrophysics, 2016)
The only relativistic reflection model that implements a parameter relating the intensity incident on an accretion disk to the observed intensity is relxill. The parameter used in earlier versions of this model, referred to as the reflection strength, is unsatisfactory; it has been superseded by a parameter that provides insight into the accretion geometry, namely the reflection fraction. The reflection fraction is defined as the ratio of the coronal intensity illuminating the disk to the coronal intensity that reaches the observer. Methods. The relxill model combines a general relativistic ray-tracing code and a photoionization code to compute the component of radiation reflected from an accretion that is illuminated by an external source. The reflection fraction is a particularly important parameter for relativistic models with well-defined geometry, such as the lamp post model, which is a focus of this paper. Results. Relativistic spectra are compared for three inclinations and for four values of the key parameter of the lamp post model, namely the height above the black hole of the illuminating, on-axis point source. In all cases, the strongest reflection is produced for low source heights and high spin. A low-spin black hole is shown to be incapable of producing enhanced relativistic reflection. Results for the relxill model are compared to those obtained with other models and a Monte Carlo simulation. Conclusions. Fitting data by using the relxill model and the recently implemented reflection fraction, the geometry of a system can be constrained. The reflection fraction is independent of system parameters such as inclination and black hole spin. The reflection-fraction parameter was implemented with the name refl-frac in all flavours of the relxill model, and the non-relativistic reflection model xillver, in v0.4a (18 January 2016).
Keywords: accretion; accretion disks; galaxies: active; line: profiles; X-rays: galaxies

NO TIME FOR DEAD TIME: TIMING ANALYSIS OF BRIGHT BLACK HOLE BINARIES WITH NuSTAR - Bachetti, Matteo; Harrison, Fiona A.; Cook, Rick; Tomsick, John; Schmid, Christian; Grefenstette, Brian W.; Barret, Didier; Boggs, Steven E.; Christensen, Finn E.; Craig, William W.; Fabian, Andrew C.; Fuerst, Felix; et al. (Astrophysical Journal, 2015)
Timing of high-count-rate sources with the NuSTAR Small Explorer Mission requires specialized analysis techniques. NuSTAR was primarily designed for spectroscopic observations of sources with relatively low count rates rather than for timing analysis of bright objects. The instrumental dead time per event is relatively long (similar to 2.5msec) and varies event-to-event by a few percent. The most obvious effect is a distortion of the white noise level in the power density spectrum (PDS) that cannot be easily modeled with standard techniques due to the variable nature of the dead time. In this paper, we show that it is possible to exploit the presence of two completely independent focal planes and use the cospectrum, the real part of the cross PDS, to obtain a good proxy of the white-noise-subtracted PDS. Thereafter, one can use a Monte Carlo approach to estimate the remaining effects of dead time, namely, a frequency-dependent modulation of the variance and a frequency-independent drop of the sensitivity to variability. In this way, most of the standard timing analysis can be performed, albeit with a sacrifice in signal-to-noise ratio relative to what would be achieved using more standard techniques. We apply this technique to NuSTAR observations of the black hole binaries GX 339-4, Cyg X-1, and GRS 1915+105.
Keywords: accretion; accretion disks; black hole physics; methods: data analysis; methods: statistical; X-rays: stars

Nuclear spallation in active galaxies - Gallo, L. C.; Randhawa, J. S.; Waddell, S. G. H.; Hani, M. H.; Garcia, Javier; Reynolds, C. S. (Monthly Notices of the Royal Astronomical Society, 2019)
A number of works point to the presence of narrow emission features at unusual energies in the X-ray spectra of active galactic nuclei or to potentially low iron abundances as possible evidence for the spallation of iron. With the imminence of high-resolution calorimeter spectroscopy, the potential to test spallation models in astrophysical sources will soon be possible. Previously determined nuclear spallation reactions of Fe are recalculated making use of improved total inelastic and partial reaction cross-sections that result in different absolute and relative abundances of the main spallation elements Mn, Cr, V, and Ti. The effects of ionization and dynamics near the black hole are examined in simulated spectra with CCD and calorimeter (i.e. Hitomi) resolution. With high resolution, differences in relative abundances and ionization should be detectable if spallation is originating at large distances from the black hole (e.g. torus or disc wind), where blurring is not significant. If spallation were occurring in the inner accretion disc, it would likely be undetected as blurring effects would cause significant blending of spectral features.
CRIS-Team Scopus Importer:2021-04-20
Keywords: accretion; accretion discs; galaxies: active; galaxies: nuclei; nuclear reactions; nucleosynthesis; abundances; X-rays: galaxies

NuSTAR AND SUZAKU OBSERVATIONS OF THE HARD STATE IN CYGNUS X-1: LOCATING THE INNER ACCRETION DISK - Parker, M. L.; Tomsick, J. A.; Miller, J. M.; Yamaoka, K.; Lohfink, A.; Nowak, M.; Fabian, A. C.; Alston, W. N.; Boggs, S. E.; Christensen, F. E.; Craig, W. W.; Fuerst, F.; et al. (Astrophysical Journal, 2015)
We present simultaneous Nuclear Spectroscopic Telescope Array (NuSTAR) and Suzaku. observations of the X-ray binary Cygnus X-1 in the hard state. This is the first time this state has been observed in Cyg X-1 with NuSTAR, which enables us to study the reflection and broadband spectra in unprecedented detail. We confirm that the iron line cannot be fit with a combination of narrow lines and absorption features, instead requiring. a relativistically blurred profile in combination with a narrow line and absorption from the companion wind. We use the reflection models of Garcia et al. to simultaneously measure the black hole spin, disk inner radius, and coronal height in a self-consistent manner. Detailed fits to the iron line profile indicate a high level of relativistic blurring, indicative of reflection from the inner accretion disk. We find a high spin, a small inner disk radius, and a low source height. and rule out truncation to greater than three gravitational radii at the 3 sigma confidence level. In addition, we find that the line profile has not changed greatly in the switch from soft to hard states, and that the differences are consistent with changes in the underlying reflection spectrum rather than the relativistic blurring. We find that the blurring parameters are consistent when fitting either just the iron line or the entire broadband spectrum, which is well modeled with a Comptonized continuum plus reflection model.
Keywords: accretion; accretion disks; black hole physics; X-rays: binaries; X-rays: individual (Cygnus X-1)

NuSTAR and XMM-Newton Observations of the Hard X-Ray Spectrum of Centaurus A - Fuerst, F.; Mueller, C.; Madsen, K. K.; Lanz, L.; Rivers, E.; Brightman, M.; Arevalo, P.; Balokovic, M.; Beuchert, T.; Boggs, S. E.; Christensen, F. E.; Craig, W. W.; et al. (Astrophysical Journal, 2016)
Keywords: galaxies: active; galaxies: individual: Centaurus A; X-rays: galaxies

NuSTAR observation of GRO J1744–28 at low mass accretion rate - König, Ole; Fuerst, Felix; Kretschmar, Peter; Ballhausen, Ralf; Sokolova-Lapa, Ekaterina; Dauser, Thomas; Sánchez-Fernández, Celia; Hemphill, Paul B.; Wolff, Michael T.; Pottschmidt, Katja; Wilms, Jörn (Astronomy & Astrophysics, 2020)
Context. Neutron stars in low-mass X-ray binaries are important systems for studying the physics of accretion onto compact objects. The system GRO J1744–28 is particularly interesting as it usually shows clear pulsations as well as X-ray bursts. Additionally, there are claims for a magnetic field of 5 × 1011 G through the detection of a cyclotron resonant scattering feature (CRSF). Aims. We present the spectral analysis of GRO J1744–28 using ∼29 ks of NuSTAR data taken in 2017 February at a low luminosity of 3.2 × 1036 erg s−1 (3−50 keV). Our goal is to study the variability of the source spectrum with pulse phase and to search for the claimed CRSF. Methods. The continuum spectrum was modeled with an absorbed power law with exponential cutoff, and an additional iron line component. We found no obvious indications for a CRSF, and therefore performed a detailed cyclotron line search using statistical methods. We performed this search on pulse phase-averaged spectra and on phase-resolved spectra. Results. GRO J1744–28 was observed in a low-luminosity state. The previously detected Type II X-ray bursts are absent. Clear pulsations at a period of 2.141124(9) Hz are detected. The pulse profile shows an indication of a secondary peak that was not seen at higher flux. The upper limit for the strength of a CRSF in the 3−20 keV band is 0.07 keV (90% CL), lower than the strength of the line found at higher luminosity. Conclusions. The detection of pulsations shows that the source did not enter the “propeller” regime, even though the source flux of 4.15 × 10−10 erg cm−2 s−1 was almost one order of magnitude below the threshold for the propeller regime claimed in previous studies on this source. The transition into the propeller regime in GRO J1744–28 must therefore be below a luminosity of 3.2 × 1036 erg s−1 (3−50 keV), which implies a surface magnetic field ≲2.9 × 1011 G and mass accretion rate ≲1.7 × 1016 g s−1. A change of the CRSF depth as function of luminosity is not unexpected and has been observed in other sources. This result possibly implies a change in emission geometry as function of mass accretion rate to reduce the depth of the line below our detection limi
Keywords: pulsars: individual: GRO J1744–28; X-rays: binaries; stars: neutron; accretion; accretion disks; magnetic fields

NuSTAR Observations of AGNs with Low Observed X-Ray to [O iii] Luminosity Ratios: Heavily Obscured AGNs or Turned-off AGNs? - Saade, M. Lynne; Brightman, Murray; Stern, Daniel; Malkan, Matthew A.; Garcia, Javier (Astrophysical Journal, 2022)
Type 2 active galactic nuclei (AGNs) show signatures of accretion onto a supermassive black hole through strong, high-ionization, narrow emission lines extended on scales of hundreds to thousands of parsecs, but they lack the broad emission lines from close in to the black hole that characterize type 1 AGNs. The lack of broad emission could indicate obscuration of the innermost nuclear regions, or could indicate that the black hole is no longer strongly accreting. Since high-energy X-rays can penetrate thick obscuring columns, they have the power to distinguish these two scenarios. We present high-energy NuSTAR observations of nine Seyfert 2 AGNs from the Infrared Astronomical Satellite 12 mu m survey, supplemented with low-energy X-ray observations from Chandra, XMM-Newton, and Swift. The galaxies were selected to have anomalously low observed 2-10 keV luminosities compared to their [O iii] optical luminosities, a traditional diagnostic of heavily obscured AGNs, reaching into the Compton-thick regime for the highest hydrogen column densities (N (H) > 1.5 x 10(24) cm(-2)). Based on updated [O iii] luminosities and intrinsic X-ray luminosities based on physical modeling of the hard X-ray spectra, we find that one galaxy was misclassified as type 2 (NGC 5005) and most of the remaining AGNs are obscured, including three confirmed as Compton thick (IC 3639, NGC 1386, and NGC 3982). One galaxy, NGC 3627, appears to have recently deactivated. Compared to the original sample that the nine AGNs were selected from, this is a rate of approximately 1%. We also find a new X-ray changing-look AGN in NGC 6890.
CRIS-Team WoS Importer:2022-09-23

NuSTAR Observations of the Accreting Atolls GX 3+1, 4U 1702-429, 4U 0614+091, and 4U 1746-371 - Ludlam, R. M.; Miller, J. M.; Barret, D.; Cackett, E. M.; Coughenour, B. M.; Dauser, Thomas; Degenaar, N.; Garcia, Javier; Harrison, F. A.; Paerels, F. (Astrophysical Journal, 2019)
Atoll sources are accreting neutron star (NS) low-mass X-ray binaries. We present a spectral analysis of four persistent atoll sources (GX 3+1, 4U 1702-429, 4U 0614+091, and 4U 1746-371) observed for similar to 20 ks each with NuSTAR to determine the extent of the inner accretion disk. These sources range from an apparent luminosity of 0.006-0.11 of the Eddington limit (assuming the empirical limit of 3.8 x 10(38) erg s(-1)). Broad Fe emission features shaped by Doppler and relativistic effects close to the NS were firmly detected in three of these sources. The position of the disk appears to be close to the innermost stable circular orbit (ISCO) in each case. For GX 3+1, we determine = R-in = 1.8(-0.6)(+0.2) R-ISCO (90% confidence level) and an inclination of 27 degrees-31 degrees. For 4U 1702-429, we find a = R-in = 1.5(-0.4)(+1.6) R-ISCO and inclination of 53 degrees-64 degrees. For 4U 0614+ 091, the disk has a position of R-in = 1.3(-0.2)(+5.4) ISCO and inclination of 50 degrees-62 degrees. If the disk does not extend to the innermost stable circular orbit, we can place conservative limits on the magnetic field strength in these systems in the event that the disk is truncated at the Alfven radius. This provides the limit at the poles of B <= 6.7 x 10(8) G, 3.3. x. 10(8) G, and 14.5. x. 10(8) G for GX 3+1, 4U. 1702-429, and 4U 0614+091, respectively. For 4U 1746-371, we argue that the most plausible explanation for the lack of reflection features is a combination of source geometry and strong Comptonization. We place these sources among the larger sample of NSs that have been observed with NuSTAR.
CRIS-Team WoS Importer:2019-03-22

NuSTAR Observations of the Transient Galactic Black Hole Binary Candidate Swift J1858.6-0814: A New Sibling of V404 Cyg and V4641 Sgr? - Hare, Jeremy; Tomsick, John A.; Buisson, Douglas J. K.; Clavel, Maica; Gandhi, Poshak; Garcia, Javier; Grefenstette, Brian W.; Walton, Dominic J.; Xu, Yanjun (Astrophysical Journal, 2020)
Swift J1858.6-0814 was discovered by the Burst Alert Telescope on Swift on 2018 October 25. Here we report on the first follow-up Nuclear Spectroscopic Telescope Array (NuSTAR) observation of the source, which shows variability spanning two orders of magnitude in count rate on timescales of ∼10-100 s. The power spectrum of the source does not show any quasi-periodic oscillations or periodicity, but has a large fractional rms amplitude of 147% ± 3%, exhibiting a number of large flares throughout the observation. The hardness ratio (defined as R 10-79keV/R 3-10keV) of the flares tends to be soft, while the source spans a range of hardness ratios during nonflaring periods. The X-ray spectrum of the source shows strong reflection features, which become more narrow and peaked during the nonflaring intervals. We fit an absorbed relativistic reflection model to the source spectra to place physical constraints on the system. Most notably, we find that the source exhibits a large and varying intrinsic absorbing column density (N H = (1.4-4.2) × 1023 cm-2). This large intrinsic absorption is further supported by the energy spectra extracted from two flares observed simultaneously by NuSTAR and the Neutron Star Interior Composition Explorer. We find that the inner accretion disk of the source has a low inclination, i < 29° (3σ upper limit), while the iron abundance in the disk is close to solar, A Fe = 1.0 ± 0.3. We set a 90% confidence upper limit on the inner radius of the accretion disk of r in < 8r ISCO and, by fixing r in to be at r ISCO, a 90% confidence lower limit on the spin of the black hole of a∗ > 0.0. Finally, we compare the properties of Swift J1858.6-0814 to those of V404 Cygni and V4641 Sgr, which both show rapid flaring and a strong and variable absorption.
CRIS-Team Scopus Importer:2021-04-19

NuSTAR reveals the hidden nature of SS433 - Middleton, M. J.; Walton, D. J.; Alston, W.; Dauser, Thomas; Eikenberry, S.; Jiang, Y-F; Fabian, A. C.; Fuerst, F.; Brightman, M.; Marshall, H.; Parker, Michael; Pinto, Ciro; et al. (Monthly Notices of the Royal Astronomical Society, 2021)
SS433 is the only Galactic binary system known to persistently accrete at highly super-critical (or hyper-critical) rates, similar to those in tidal disruption events, and likely needed to explain the rapid growth of those very high redshift quasars containing massive SMBHs. Probing the inner regions of SS433 in the X-rays is crucial to understanding this system, and super-critical accretion in general, but is highly challenging due to obscuration by the surrounding wind, driven from the accretion flow. NuSTAR observed SS433 in the hard X-ray band across multiple phases of its 162 d superorbital precession period. Spectral-timing tools allow us to infer that the hard X-ray emission from the inner regions is likely being scattered towards us by the walls of the wind-cone. By comparing to numerical models, we determine an intrinsic X-ray luminosity of >= 2 x 10(37) erg s(-1) and that, if viewed face on, we would infer an apparent luminosity of >1 x 10(39) erg s(-1), confirming SS433's long-suspected nature as an ultraluminous X-ray source (ULX). We present the discovery of a narrow, similar to 100 s lag due to atomic processes occurring in outflowing material travelling at least 0.14-0.29c, which matches absorption lines seen in ULXs and - in the future - will allow us to map a super-critical outflow for the first time.
CRIS-Team WoS Importer:2021-10-22

NuSTAR Spectral Analysis beyond 79 keV with Stray Light - Mastroserio, G.; Grefenstette, B. W.; Thalhammer, Philipp; Buisson, D. J. K.; Brumback, M. C.; Ludlam, R. M.; Connors, R. M. T.; Garcia, J. A.; Grinberg, Victoria; Madsen, K. K.; Miyasaka, H.; Tomsick, J. A.; et al. (Astrophysical Journal, 2022)
Due to the structure of the NuSTAR telescope, photons at a large off axis (>1 degrees) can reach the detectors directly (stray light), without passing through the instrument optics. At these off-axis angles NuSTAR essentially turns into a collimated instrument and the spectrum can extend to energies above the Pt K edge (79 keV) of the multilayers, which limits the effective area bandpass of the optics. We present the first scientific spectral analysis beyond 79 keV using a Cygnus X-1 observation in StrayCats: the catalog of stray light observations. This serendipitous stray light observation occurred simultaneously with an INTEGRAL observation. When the spectra are modeled together in the 30-120 keV energy band, we find that the NuSTAR stray light flux is well calibrated and constrained to be consistent with the INTEGRAL flux at the 90% confidence level. Furthermore, we explain how to treat the background of the stray light spectral analysis, which is especially important at high energies.
CRIS-Team WoS Importer:2023-02-03

Observation of strong two-electron-one-photon transitions in few-electron ions - Togawa, Moto; Kuehn, S.; Shah, Chintan; Amaro, Pedro; Steinbruegge, R.; Stierhof, Jakob; Hell, N.; Rosner, M.; Fujii, Keisuke; Bissinger, Matthias; Ballhausen, Ralf; Hoesch, M.; et al. (Physical Review A, 2020)
We resonantly excite the K series of O5+ and O6+ up to principal quantum number n=11 with monochromatic x rays, producing K-shell holes, and observe their relaxation by soft-x-ray emission. Some photoabsorption resonances of O5+ reveal strong two-electron-one-photon (TEOP) transitions. We find that for the [(1s2s)15p3/2]3/2;1/2 states, TEOP relaxation is by far stronger than the radiative decay and competes with the usually much faster Auger decay path. This enhanced TEOP decay arises from a strong correlation with the near-degenerate upper states [(1s2p3/2)14s]3/2;1/2 of a Li-like satellite blend of the He-like Kα transition. Even in three-electron systems, TEOP transitions can play a dominant role, and the present results should guide further research on the ubiquitous and abundant many-electron ions where electronic energy degeneracies are far more common and configuration mixing is stronger.
CRIS-Team Scopus Importer:2021-04-19

Observation of the cosmic ray shadow of the Sun with the ANTARES neutrino telescope - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J-J; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; Bertin,; Biagi, S.; et al. (Physical Review D, 2020)
The ANTARES detector is an undersea neutrino telescope in the Mediterranean Sea. The search for pointlike neutrino sources is one of the main goals of the ANTARES telescope, requiring a reliable method to evaluate the detector angular resolution and pointing accuracy. This work describes the study of the Sun "shadow" effect with the ANTARES detector. The shadow is the deficit in the atmospheric muon flux in the direction of the Sun caused by the absorption of the primary cosmic rays. This analysis is based on the data collected between 2008 and 2017 by the ANTARES telescope. The observed statistical significance of the Sun shadow detection is 3.7 sigma, with an estimated angular resolution of 0.59 degrees +/- 0.10 degrees for downward-going muons. The pointing accuracy is found to be consistent with the expectations and no evidence of systematic pointing shifts is observed.
CRIS-Team WoS Importer:2021-01-15

Observations of the extreme runaway HD271791: Nucleosynthesis in a core-collapse supernova - Schaffenroth, Veronika; Przybilla, Norbert; Butler, Keith; Irrgang, Andreas; Heber, Ulrich (Proceedings of Science, 2014)
Some young, massive stars can be found in the Galactic halo. As star formation is unlikely to occur in the halo, they must have been formed in the disk and been ejected shortly afterwards. One explanation is a supernova in a tight binary system. The companion is ejected and becomes a runaway star. HD271791 is the kinematically most extreme runaway star known (Galactic restframe velocity 725±195km s-1, which is even larger than the Galactic escape velocity). Moreover, an analysis of the optical spectrum showed an enhancement of the α-process elements. This indicates the capture of supernova ejecta, and therefore an origin in a core-collapse supernova. As such high space velocities are not reached by the runaway stars in classical binary supernova ejection scenarios, a very massive but compact primary, probably of Wolf-Rayet type is required. HD271791 is therefore a perfect candidate for studying nucleosynthesis in a supernova of probably type Ibc. The goal of this project is to determine the abundances of a large number of elements from the α-process, the iron group, and heavier elements by a quantitative analysis of the optical and UV spectral range. Detailed line-formation calculations are employed that account for deviations from local thermodynamic equilibrium (non-LTE). We intend to verify whether corecollapse supernova are a site of r-process element production. Here, we state the current status of the project.
CRIS-Team Scopus Importer:2020-12-21

Observations of the post-shock break-out emission of SN 2011dh with XMM-Newton - Sasaki, Manami; Ducci, Lorenzo (Astronomy & Astrophysics, 2012)
Context. After the occurrence of the type cIIb SN 2011dh in the nearby spiral galaxy M 51 numerous observations were performed with different telescopes in various bands ranging from radio to γ-rays. Aims: We analysed the XMM-Newton and Swift observations taken 3 to 30 days after the SN explosion to study the X-ray spectrum of SN 2011dh. Methods: We extracted spectra from the XMM-Newton observations, which took place 7 and 11 days after the SN. In addition, we created integrated Swift/XRT spectra of 3 to 10 days and 11 to 30 days. Results: The spectra can be well-fitted with a power-law spectrum absorbed with Galactic foreground absorption. In addition, we find a harder spectral component in the first XMM-Newton spectrum taken at t ≈ 7 d. This component is also detected in the first Swift spectrum of t = 3-10 d. Conclusions: While the persistent component can be explained as inverse Compton emission from radio synchrotron emitting electrons or emission of the reverse shock, the harder component is most likely bremsstrahlung emission from the shocked stellar wind. Therefore, the harder X-ray emission that fades away after t ≈ 10 d can be interpreted as emission from the shocked circumstellar wind of SN 2011dh.
Keywords: shock waves; circumstellar matter; supernovae: individual: SN2011dh

Observations of the Ultra-compact X-Ray Binary 4U 1543-624 in Outburst with NICER, INTEGRAL, Swift, and ATCA - Ludlam, R. M.; Shishkovsky, L.; Bult, P. M.; Miller, J. M.; Zoghbi, Abderahmen; Strohmayer, T. E.; Reynolds, M.; Natalucci, L.; Miller-Jones, J. C. A.; Jaisawal, G. K.; Guillot, S.; Gendreau, K. C.; et al. (Astrophysical Journal, 2019)
We report on X-ray and radio observations of the ultra-compact X-ray binary 4U 1543-624 taken in August 2017 during an enhanced accretion episode. We obtained Neutron Star Interior Composition Explorer (NICER) monitoring of the source over a similar to 10 day period during which target-of-opportunity observations were also conducted with Swift, INTErnational Gamma-Ray Astrophysics Laboratory (INTEGRAL), and the Australia Telescope Compact Array. Emission lines were measured in the NICER X-ray spectrum at similar to 0.64 keV and similar to 6.4 keV that correspond to O and Fe, respectively. By modeling these line components, we are able to track changes in the accretion disk throughout this period. The innermost accretion flow appears to move inwards from hundreds of gravitational radii (R-g = GM/c(2)) at the beginning of the outburst to <8.7 R-g at peak intensity. We do not detect the source in radio, but are able to place a 3 sigma upper limit on the flux density at 27 mu Jy beam(-1). Comparing the radio and X-ray luminosities, we find that the source lies significantly away from the range typical of black holes in the L-r-L-x plane, suggesting a neutron star primary. This adds to the evidence that neutron stars (NSs) do not follow a single track in the L-r-L-x plane, limiting its use in distinguishing between different classes of NSs based on radio and X-ray observations alone.
CRIS-Team WoS Importer:2019-10-11

Observatory science with eXTP - In'T Zand, Jean J. M.; Bozzo, Enrico; Qu, Jinlu; Li, Xiang-Dong; Amati, Lorenzo; Chen, Yang; Donnarumma, Immacolata; Doroshenko, Victor; Drake, Stephen A.; Hernanz, Margarita; Jenke, Peter A.; Maccarone, Thomas J.; et al. (Science China-Physics Mechanics & Astronomy, 2019)
In this White Paper we present the potential of the enhanced X-ray Timing and Polarimetry (eXTP) mission for studies related to Observatory Science targets. These include flaring stars, supernova remnants, accreting white dwarfs, low and high mass X-ray binaries, radio quiet and radio loud active galactic nuclei, tidal disruption events, and gamma-ray bursts. eXTP will be excellently suited to study one common aspect of these objects: their often transient nature. Developed by an international Consortium led by the Institute of High Energy Physics of the Chinese Academy of Science, the eXTP mission is expected to be launched in the mid 2020s.
Keywords: space research instruments; nuclear astrophysics; flare stars; accretion and accretion disks; mass loss and stellar winds; cataclysmic binaries; X-ray binaries; supernova remnants; active galactic nuclei; X-ray bursts; gamma-ray bursts; gravitational waves

Observing the Transient Pulsations of SMC X-1 with NuSTAR - Pike, Sean N.; Harrison, Fiona A.; Bachetti, Matteo; Brumback, Mckinley C.; Furst, Felix S.; Madsen, Kristin K.; Pottschmidt, Katja; Tomsick, John A.; Wilms, Jörn (Astrophysical Journal, 2019)
We report on Nuclear Spectroscopic Telescope Array observations of transient pulsations in the neutron star X-ray binary SMC X-1. The transition from nonpulsing to pulsing states was not accompanied by a large change in flux. Instead, both pulsing and nonpulsing states were observed in a single observation during the low-flux super-orbital state. During the high state, we measure a pulse period of P = 0.70117(9) s at T-ref = 56145 MJD. Spectral analysis during nonpulsing and pulsing states reveals that the observations can be consistently modeled by an absorbed power law with a phenomenological cutoff resembling a Fermi-Dirac distribution, or by a partially obscured cutoff power law. The shapes of the underlying continua show little variability between epochs, while the covering fraction and column density vary between super-orbital states. The strength of pulsations also varies, leading us to infer that the absence and reemergence of pulsations are related to changing obscuration, such as by a warped accretion disk. SMC X-1 is accreting near or above its Eddington limit, reaching an unabsorbed X-ray luminosity of L-x (2-10 keV) approximate to 5 x 10(38) erg s(-1). This suggests that SMC X-1 may be a useful local analog to ultraluminous X-ray pulsars (ULXPs), which likewise exhibit strong variability in their pulsed fractions, as well as flux variability on similar timescales. In particular, the gradual pulse turn-on, which has been observed in M82 X-2, is similar to the behavior we observe in SMC X-1. Thus we propose that pulse fraction variability of ULXPs may also be due to variable obscuration.
Keywords: accretion; accretion disks; stars: neutron; X-rays: binaries; X-rays: individual (SMC X-1)

Observing the WHIM with Athena - Brand, Thorsten; Wilms, Jörn; Dauser, Thomas; Peille, P.; Cobo, B.; Ceballos, M.; Den Hartog, R. A.; Kaastra, J. S.; O'Brien, P.; Barcons, X.; Piro, L.; Den Herder, J. W A; et al. (Space Telescopes and Instrumentation 2016: Ultraviolet to Gamma Ray, 2016)
We present simulations of the detection probability for absorption lines from ions in the warm and hot ionized medium (WHIM) with Athena in the spectra of Gamma-ray burst afterglows. The simulations are based on Swift XRT lightcurves of these afterglows and are performed using the end-to-end simulation framework SIXTE. We simulate both the case of single and multiple absorption lines, as well as results for line searches in absorption structures from a more complex medium. We show that the Athena X-IFU can detect WHIM lines with strong Ovii lines (equivalent widths larger than 0.14 eV) in spectra containing 3 x 10 counts.
Keywords: Athena; GRB; Simulation; SIXTE; WHIM; X-IFU

OGLE-BLAP-009 – a case study for the properties and evolution of blue large-amplitude pulsators - Bradshaw, Corey W.; Dorsch, Matti; Kupfer, Thomas; Barlow, Brad N.; Heber, Ulrich; Bauer, Evan B.; Bildsten, Lars; van Roestel, Jan (Monthly Notices of the Royal Astronomical Society, 2024)
Blue large-amplitude pulsators (BLAPs) make up a rare class of hot pulsating stars with effective temperatures of ≈30 000 K and surface gravities of 4.0–5.0 dex (cgs). The evolutionary origin and current status of BLAPs is not well understood, largely based on a lack of spectroscopic observations and no available mass constraints. However, several theoretical models have been proposed that reproduce their observed properties, including studies that identify them as pulsating helium-core pre-white dwarfs (He-core pre-WDs). We present here follow-up high-speed photometry and phase-resolved spectroscopy of one of the original 14 BLAPs, OGLE-BLAP-009, discovered during the Optical Gravitational Lensing Experiment. We aim to explore its pulsation characteristics and determine stellar properties such as mass and radius in order to test the consistency of these results with He-core pre-WD models. Using the mean atmospheric parameters found using spectroscopy, we fit a spectral energy distribution to obtain a preliminary estimate of the radius, luminosity, and mass by making use of the Gaia parallax. We then compare the consistency of these results to He-core pre-WD models generated using Modules for Experiments in Stellar Astrophysics, with predicted pulsation periods implemented using GYRE. We find that our mass constraints are in agreement with a low-mass He-core pre-WD of ≈0.30 M◦
CRIS-Team Scopus Importer:2024-02-02
Keywords: asteroseismology; stars: evolution; stars: individual: OGLE-BLAP-009; stars: oscillations (including pulsations)

ON ESTIMATING THE HIGH-ENERGY CUTOFF IN THE X-RAY SPECTRA OF BLACK HOLES VIA REFLECTION SPECTROSCOPY - Garcia, Javier A.; Dauser, Thomas; Steiner, James F.; McClintock, Jeffrey E.; Keck, Mason L.; Wilms, Jörn (Astrophysical Journal Letters, 2015)
The fundamental parameters describing the coronal spectrum of an accreting black hole are the slope Gamma of the power-law continuum and the energy E-cut at which it rolls over. Remarkably, this latter parameter can be accurately measured for values as high as 1 MeV by modeling the spectrum of X-rays reflected from a black hole accretion disk at energies below 100 keV. This is possible because the details in the reflection spectrum, rich in fluorescent lines and other atomic features, are very sensitive to the spectral shape of the hardest coronal radiation illuminating the disk. We show that by fitting simultaneous NuSTAR (3-79 keV) and low-energy (e.g., Suzaku) data with the most recent version of our reflection model relxill one can obtain reasonable constraints on E-cut at energies from tens of keV up to 1 MeV, for a source as faint as 1 mCrab in a 100 ks observation.
Keywords: accretion; accretion disks; atomic processes; black hole physics

On measuring the Hubble constant with X-ray reverberation mapping of active galactic nuclei - Ingram, Adam; Mastroserio, Guglielmo; Van Der Klis, Michiel; Nathan, Edward; Connors, Riley; Dauser, Thomas; García, Javier A.; Kara, Erin; König, Ole; Lucchini, Matteo; Wang, Jingyi (Monthly Notices of the Royal Astronomical Society, 2022)
We show that X-ray reverberation mapping can be used to measure the distance to type 1 active galactic nuclei (AGNs). This is because X-ray photons originally emitted from the 'corona' close to the black hole irradiate the accretion disc and are reemitted with a characteristic 'reflection' spectrum that includes a prominent 6.4 keV iron emission line. The shape of the reflection spectrum depends on the irradiating flux, and the light-crossing delay between continuum photons observed directly from the corona and the reflected photons constrain the size of the disc. Siltaneously modelling the X-ray spectrum and the time delays between photons of different energies therefore constrains the intrinsic reflected luminosity, and the distance follows from the observed reflected flux. Alternatively, the distance can be measured from the X-ray spectrum alone if the black hole mass is known. We develop a new model of our reltrans X-ray reverberation mapping package, called rtdist, that has distance as a model parameter. We silate a synthetic observation that we fit with our new model, and find that this technique applied to a sample of 25 AGNs can be used to measure the Hubble constant with a 3σ statistical uncertainty of sim 6,km,s-1, Mpc-1. Since the technique is completely independent of the traditional distance ladder and the cosmic microwave background radiation, it has the potential to address the current tension between them. We discuss sources of modelling uncertainty, and how they can be addressed in the near future.
CRIS-Team Scopus Importer:2021-12-24
Keywords: active; black hole physics; cosmological parameters; data analysis; galaxies; methods

On some Bamberg wide-field plate catalogues recently incorporated into WFPDB - Tsvetkova, K.; Tsvetkov, M.; Kirov, N.; Kalaglarsky, D.; Edelmann, Heinz; Heber, Ulrich (Astronomical and Astrophysical Transactions, 2018)
The Dr. Remeis-Sternwarte (Bamberg Observatory) hosts about 40000 astronomical photographic plates taken from the early 20th century to the mid 1970s. In an ongoing long-term project the Bamberg wide-field plate catalogues are being incorporated into the Wide-Field Plate Database (WFPDB). Here, we describe the recent integration of seven Bamberg catalogues in the framework of a project to digitize and preserve the plates, funded by the German Science Foundation. These catalogues include information about 8400 plates obtained in the period 1931-1963 with three Tessar cameras (WFPDB identifiers BAM003A, BAM003B and BAM009A), a Xenon camera (BAM006), a Vierlinser camera (BAM008), an Ernostar camera (BAM009B), and a Dogmar camera (BAM011). The plate observations aimed at investigations of variable stars in the Northern sky. Some of the cameras were first mounted on an astrograph in Bamberg in preparation for, and testing of the Bamberg large-scale project for variable star research in the Southern sky in the period 1963-1976. Currently information on 31 Bamberg plate archives containing 34200 plates from the Bamberg Northern and Southern Sky Survey can be found in the WFPDB.
CRIS-Team Scopus Importer:2020-12-21
Keywords: Astroinformatics; Databases; Plate catalogues

On the cyclotron line in cepheus X-4 - Wilms, Jörn; et al. (Astronomy & Astrophysics, 2007)
Context. Accreting X-ray pulsars provide us with laboratories for the study of extreme gravitational and magnetic fields, hence accurate descriptions of their observational properties contribute to our understanding of this group of objects.Aims. We aim to detect a cyclotron resonance scattering feature in the Be Be/X-ray binary Cep X-4 and to investigate pulse profile and spectral changes through the outburst.Methods. Spectral fitting and timing analysis are employed to probe th the properties of Cep X-4 during during an outburst in 2002 June.Results. A previously announced cyclotron feature at 30.7 keV is confirmed, while the source shows spectral behaviour and luminosity related changes similar to those observed in previous outbursts. The long-term X-ray lightcurve shows a periodicity at 20.85 d, which could be attributed to the orbit in this Be system.
Keywords: X-rays; binaries - stars; magnetic fields - stars; pulsars; individual; Cep X-4-stars; pulsars; individual; GS 2138+56

On the Detection Potential of Blazar Flares for Current Neutrino Telescopes - Kreter, M.; Kadler, M.; Krauss, F.; Mannheim, K.; Buson, S.; Ojha, R.; Wilms, Jörn; Bottcher, M. (Astrophysical Journal, 2020)
Blazar jets are extreme environments, in which relativistic proton interactions with an ultraviolet photon field could give rise to photopion production. High-confidence associations of individual high-energy neutrinos with blazar flares could be achieved via spatially and temporally coincident detections. In 2017, the track-like, extremely high-energy neutrino event IC 170922A was found to coincide with increased gamma-ray emission from the blazar TXS 0506+056, leading to the identification of the most promising neutrino point-source candidate so far. We calculate the expected number of neutrino events that can be detected with IceCube, based on a broadband parameterization of bright short-term blazar flares that were observed in the first 6.5 yr of Fermi/Large Area Telescope observations. We find that the integrated keV-to-GeV fluence of most individual blazar flares is far too small to yield a substantial Poisson probability for the detection of one or more neutrinos with IceCube. We show that the sample of potentially detectable high-energy neutrinos from individual blazar flares is rather small. We further show that the blazars 3C 279 and PKS 1510-089 dominate the all-sky neutrino prediction from bright and short-term blazar flares. In the end, we discuss strategies to search for more significant associations in future data unblindings of IceCube and KM3NeT.
CRIS-Team WoS Importer:2020-11-06

On the determination of the spin of the black hole in Cyg X-1 from X-ray reflection spectra - Fabian, A. C.; Wilkins, D. R.; Miller, J. M.; Reis, R. C.; Reynolds, C. S.; Cackett, E. M.; Nowak, M. A.; Pooley, G. G.; Pottschmidt, K.; Sanders, J. S.; Ross, R. R.; Wilms, Jörn (Monthly Notices of the Royal Astronomical Society, 2012)
The spin of Cygnus X-1 is measured by fitting reflection models to Suzaku data covering the energy band 0.9400 keV. The inner radius of the accretion disc is found to lie within 2 gravitational radii (rg=GM/c2), and a value of is obtained for the dimensionless black hole spin. This agrees with recent measurements using the continuum fitting method by Gou et al. and of the broad iron line by Duro et al. The disc inclination is measured at , which is consistent with the recent optical measurement of the binary system inclination by Orosz et al. of 27 degrees +/- 08. We pay special attention to the emissivity profile caused by irradiation of the inner disc by the hard power-law source. The X-ray observations and simulations show that the index q of that profile deviates from the commonly used, Newtonian, value of 3 within 3rg, steepening considerably within 2rg, as expected in the strong gravity regime.
Keywords: accretion; accretion discs; black hole physics; line: profiles; X-rays: general

On the discrepancy between the X-ray and UV absorption measurements of O VI in the local ISM - Gatuzz, Efrain; Garcia, Javier; Kallman, Timothy R. (Monthly Notices of the Royal Astronomical Society, 2019)
The total amount of OVI present in the interstellar medium ( ISM) obtained via absorption measurements in UV and X-ray spectra is currently in disagreement, with the latter being significantly larger ( by a factor of 10 or more) than the former. Previous works have proposed that the blend of the OVI K alpha line ( 22.032 angstrom) with the OII K beta-L12 line ( 22.04 angstrom) could account for the stronger absorption observed in the X-ray spectra. Here, we present a detailed study of the oxygen absorption in the local ISM, implementing our new model IGMabs which includes photoabsorption cross-sections of highly ionized species of abundant elements as well as turbulence broadening. By analysing high-resolution Chandra spectra of 13 low-mass X-ray binaries ( LMXBs) and 29 extragalactic sources, we have estimated the column densities of OI - OIII and from OVI - OVIII along multiple line-of-sights. We find that in most cases the OII K beta-L12 line accounts for <30 per cent of the total OVI K alpha + OII K beta. We conclude that the amount of OII predicted by our model is still insufficient to explain the discrepancy between X-ray and UV measurements of OVI column densities.
CRIS-Team WoS Importer:2019-09-03

On the He-3 anomaly in hot subdwarf B stars - Schneider, David; Irrgang, Andreas; Heber, Ulrich; Nieva, M. F.; Przybilla, Norbert (SCIENDO, 2017)
Decades ago, He-3 isotope enrichment in helium-weak B-type main-sequence, in blue horizontal branch and in hot subdwarf B (sdB) stars, i.e., helium-core burning stars of the extreme horizontal branch, were discovered. Diffusion processes in the atmosphere of these stars lead to the observed abundance anomalies. Quantitative spectral analyses of high-resolution spectra to derive photospheric isotopic helium abundance ratios for known He-3 sdBs have not been performed yet. We present preliminary results of high-resolution and high S/N spectra to determine the He-3 and He-4 abundances of nine known He-3 sdBs. We used a hybrid local/non-local thermodynamic equilibrium (LTE/NLTE) approach for B-type stars investigating multiple He I lines, including lambda 4922 angstrom and lambda 6678 angstrom, which show the strongest isotopic shifts in the optical spectral range. We also report the discovery of four new He-3 sdBs from the ESO Supernova Progenitor survey. Most of the He-3 sdBs cluster in a narrow temperature strip between similar to 26000 K and similar to 30000 K and have almost no atmospheric He-4 at all. Interestingly, three He-3 sdBs show evidence for vertical helium stratification.
Keywords: Stars: chemically peculiar; Stars: atmospheres; Stars: fundamental parameters; Stars: abundances; subdwarfs; Stars: horizontal-branch

On the nature of the 35-day cycle in the X-ray binary Her X-1/HZ Her - Shakura, N.; Kolesnikov, D.; Postnov, K.; Volkov, I.; Bikmaev, I.; Irsmambetova, T.; Staubert, R.; Wilms, Jörn; Irtuganov, E.; Shurygin, P.; Golysheva, P.; Shugarov, S.; et al. (High-mass X-ray Binaries: Illuminating the Passagefrom Massive Binaries to Merging Compact Objects, 2019)
The X-ray binary Her X-1 consists of an accreting neutron star and the optical companion HZ Her. The 35-day X-ray variability of this system is known since its discovery in 1972 by the UHURU satellite and is believed to be caused by forced precession of the warped accretion disk tilted to the orbital plane. We argue that the observed features of the optical variability of HZ Her can be explained by free precession of the neutron star with a period close to that of the forced disk precession. The model parameters include a) the intensity (power) of the stream of matter flowing out of the optical star; b) the X-ray luminosity of the neutron star; c) the optical flux of the accretion disk; d) the X-ray irradiation pattern on the donor star; e) the tilt of the inner and outer edge of the accretion disk. A possible synchronization mechanism based on the coupling between the neutron star free precession and the dynamical action of non-stationary gas streams is discussed shortly.
CRIS-Team Scopus Importer:2020-02-21
Keywords: stars: binaries: close; stars: neutron; X-rays: binaries

ON THE RADIAL ONSET OF CLUMPING IN THE WIND OF THE B0I MASSIVE STAR QV NOR - Torrejon, J. M.; Schulz, N. S.; Nowak, M. A.; Oskinova, L.; Rodes-Roca, J. J.; Shenar, T.; Wilms, Jörn (Astrophysical Journal, 2015)
We present an analysis of a 78 ks Chandra high-energy transmission gratings observation of the B0I star QV Nor, the massive donor of the wind-accreting pulsar 4U1538-52. The neutron star (NS) orbits its companion in a very close orbit (r < 1.4R(*), in units of the stellar radii), thereby allowing probing of the innermost wind regions. The flux of the Fe K alpha line during eclipse reduces to only similar to 30% of the flux measured out of eclipse. This indicates that the majority of Fe fluorescence must be produced in regions close to the NS, at distances smaller than 1R(*) from its surface. The fact that the flux of the continuum decreases to only similar to 3% during eclipse allows for a high contrast of the Fe Ka line fluorescence during eclipse. The line is not resolved and centered at lambda = 1.9368(-0.0018)(+0.0032) angstrom. From the inferred plasma speed limit of v < c Delta lambda/lambda < 800 km s(-1) and range of ionization parameters of log xi =[-1, 2], together with the stellar density profile, we constrain the location of the cold, dense material in the stellar wind of QV Nor using simple geometrical considerations. We then use the Fe K alpha line fluorescence as a tracer of wind clumps and determine that these clumps in the stellar wind of QV Nor (B0I) must already be present at radii r < 1.25R(*), close to the photosphere of the star.
Keywords: stars: individual (QV Nor; 4U1538+52); stars: winds; outflows; X-rays: binaries

ON THE ROLE OF THE ACCRETION DISK IN BLACK HOLE DISK-JET CONNECTIONS - Miller, J. M.; Pooley, G. G.; Fabian, A. C.; Nowak, M. A.; Reis, R. C.; Cackett, E. M.; Pottschmidt, K.; Wilms, Jörn (Astrophysical Journal, 2012)
Models of jet production in black hole systems suggest that the properties of the accretion disk-such as its mass accretion rate, inner radius, and emergent magnetic field-should drive and modulate the production of relativistic jets. Stellar-mass black holes in the "low/hard" state are an excellent laboratory in which to study disk-jet connections, but few coordinated observations are made using spectrometers that can incisively probe the inner disk. We report on a series of 20 Suzaku observations of Cygnus X-1 made in the jet-producing low/hard state. Contemporaneous radio monitoring was done using the Arcminute MicroKelvin Array radio telescope. Two important and simple results are obtained: (1) the jet (as traced by radio flux) does not appear to be modulated by changes in the inner radius of the accretion disk and (2) the jet is sensitive to disk properties, including its flux, temperature, and ionization. Some more complex results may reveal aspects of a coupled disk-corona-jet system. A positive correlation between the reflected X-ray flux and radio flux may represent specific support for a plasma ejection model of the corona, wherein the base of a jet produces hard X-ray emission. Within the framework of the plasma ejection model, the spectra suggest a jet base with v/c similar or equal to 0.3 or the escape velocity for a vertical height of z similar or equal to 20 GM/c(2) above the black hole. The detailed results of X-ray disk continuum and reflection modeling also suggest a height of z similar or equal to 20 GM/c(2) for hard X-ray production above a black hole, with a spin in the range 0.6 <= a <= 0.99. This height agrees with X-ray time lags recently found in Cygnus X-1. The overall picture that emerges from this study is broadly consistent with some jet-focused models for black hole spectral energy distributions in which a relativistic plasma is accelerated at z = 10-100 GM/c(2). We discuss these results in the context of disk-jet connections across the black hole mass scale.
Keywords: accretion; accretion disks; black hole physics; relativistic processes; X-rays: binaries

Optical and near-infrared photometric monitoring of the transient X-ray binary A0538-66 with REM - Ducci, L.; Covino, S.; Doroshenko, V.; Mereghetti, S.; Santangelo, A.; Sasaki, Manami (Astronomy & Astrophysics, 2016)
The transient Be/X-ray binary A0538-66 shows peculiar X-ray and optical variability. Despite numerous studies, the intrinsic properties underlying its anomalous behaviour remain poorly understood. Since September 2014 we have conducted the first quasi-simultaneous, optical and near-infrared photometric monitoring of A0538-66 in seven filters with the Rapid Eye Mount ( REM) telescope to understand the properties of this binary system. We found that the REM light curves show fast flares lasting one or two days that repeat almost regularly every similar to 16.6 d, which is the orbital period of the neutron star. If the optical flares are powered by X-ray outbursts through photon reprocessing, the REM light curves indicate that A0538-66 is still active in X-rays; bright X-ray flares (L-x greater than or similar to 10(37) erg s(-1)) could be observable during the periastron passages. The REM light curves show a long-term variability that is especially pronounced in the g-band and decreases with increasing wavelength until it no longer appears in the near-infrared light curves. In addition, A0538- 66 is fainter with respect to previous optical observations, and this is likely because of the higher absorption of the stellar radiation of a denser circumstellar disc. On the basis of the current models, we interpret these observational results with a circumstellar disc around the Be star observed nearly edge-on during a partial depletion phase. The REM light curves also show short-term variability on timescales of similar to 1 day, which is possibly indicative of perturbations in the density distribution of the circumstellar disc caused by the tidal interaction with the neutron star.
Keywords: accretion; accretion disks; X-rays: binaries; (stars:) pulsars: individual: A0538-66

Optical and X-ray early follow-up of ANTARES neutrino alerts - Adrian-Martinez, S.; Ageron, M.; Albert, A.; Al Samarai, I.; Andre, Michel; Anton, Gisela; Ardid, Miguel; Aubert, J. -J.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; et al. (Journal of Cosmology and Astroparticle Physics, 2016)
High-energy neutrinos could be produced in the interaction of charged cosmic rays with matter or radiation surrounding astrophysical sources. Even with the recent detection of extraterrestrial high-energy neutrinos by the IceCube experiment, no astrophysical neutrino source has yet been discovered. Transient sources, such as gamma-ray bursts, core-collapse supernovae, or active galactic nuclei are promising candidates. Multi-messenger programs offer a unique opportunity to detect these transient sources. By combining the information provided by the ANTARES neutrino telescope with information coming from other observatories, the probability of detecting a source is enhanced, allowing the possibility of identifying a neutrino progenitor from a single detected event. A method based on optical and X-ray follow-ups of high-energy neutrino alerts has been developed within the ANTARES collaboration. This method does not require any assumptions on the relation between neutrino and photon spectra other than time-correlation. This program, denoted as TAToO, triggers a network of robotic optical telescopes (TAROT and ROTSE) and the Swift-XRT with a delay of only a few seconds after a neutrino detection, and is therefore well-suited to search for fast transient sources. To identify an optical or X-ray counterpart to a neutrino signal, the images provided by the follow-up observations are analysed with dedicated pipelines. A total of 42 alerts with optical and 7 alerts with X-ray images taken with a maximum delay of 24 hours after the neutrino trigger have been analysed. No optical or X-ray counterparts associated to the neutrino triggers have been found, and upper limits on transient source magnitudes have been derived. The probability to reject the gamma-ray burst origin hypothesis has been computed for each alert.

Orbital Decay in M82 X-2 - Bachetti, Matteo; Heida, Marianne; Maccarone, Thomas; Huppenkothen, Daniela; Israel, Gian Luca; Barret, Didier; Brightman, Murray; Brumback, Mckinley; Earnshaw, Hannah P.; Forster, Karl; Furst, Felix; Grefenstette, Brian W.; et al. (Astrophysical Journal, 2022)
M82 X-2 is the first pulsating ultraluminous X-ray source discovered. The luminosity of these extreme pulsars, if isotropic, implies an extreme mass transfer rate. An alternative is to assume a much lower mass transfer rate, but with an apparent luminosity boosted by geometrical beaming. Only an independent measurement of the mass transfer rate can help discriminate between these two scenarios. In this paper, we follow the orbit of the neutron star for 7 yr, measure the decay of the orbit ( P ̇ orb / P orb ≈ − 8 · 10 − 6 yr − 1 ), and argue that this orbital decay is driven by extreme mass transfer of more than 150 times the mass transfer limit set by the Eddington luminosity. If this is true, the mass available to the accretor is more than enough to justify its luminosity, with no need for beaming. This also strongly favors models where the accretor is a highly magnetized neutron star.
CRIS-Team Scopus Importer:2022-10-21

Orbital solutions of eight close sdB binaries and constraints on the nature of the unseen companions - Geier, S.; Ostensen, R. H.; Heber, Ulrich; Kupfer, Thomas; Maxted, P. F. L.; Barlow, B. N.; Vuckovic, Maja; Tillich, A.; Mueller, S.; Edelmann, Heinz; Classen, Lew; Mcleod, A. F. (Astronomy & Astrophysics, 2014)
The project Massive Unseen Companions to Hot Faint Underluminous Stars from SDSS (MUCHFUSS) aims at finding hot subdwarf stars (sdBs) with massive compact companions such as white dwarfs, neutron stars, or stellar-mass black holes. In a supplementary programme we obtained time-resolved spectroscopy of known hot subdwarf binary candidates. Here we present orbital solutions of eight close sdB binaries with orbital periods ranging from 0.1 d to, which allow us to derive lower limits on the masses of their companions. Additionally, a dedicated photometric follow-up campaign was conducted to obtain light curves of the reflection-effect binary HS 2043+0615. We are able to constrain the most likely nature of the companions in all cases but one, making use of information derived from photometry and spectroscopy. Four sdBs have white dwarf companions, while another three are orbited by low-mass main sequence stars of spectral type M. © 2014 ESO.
CRIS-Team Scopus Importer:2020-12-21
Keywords: Binaries: spectroscopic; Subdwarfs

Outburst of GX 304-1 monitored with INTEGRAL: positive correlation between the cyclotron line energy and flux - Klochkov, D.; Doroshenko, Victor; Santangelo, A.; Staubert, R.; Ferrigno, Carlo; Kretschmar, Peter; Caballero, I.; Wilms, Jörn; Kreykenbohm, Ingo; Pottschmidt, K.; Rothschild, R. E.; Wilson-Hodge, C. A.; et al. (Astronomy & Astrophysics, 2012)
Context. X-ray spectra of many accreting pulsars exhibit significant variations as a function of flux and thus of mass accretion rate. In some of these pulsars, the centroid energy of the cyclotron line(s), which characterizes the magnetic field strength at the site of the X-ray emission, has been found to vary systematically with flux.Aims. GX304-1 is a recently established cyclotron line source with a line energy around 50 keV. Since 2009, the pulsar shows regular outbursts with the peak flux exceeding one Crab. We analyze the INTEGRAL observations of the source during its outburst in January-February 2012.Methods. The observations covered almost the entire outburst, allowing us to measure the source's broad-band X-ray spectrum at different flux levels. We report on the variations in the spectral parameters with luminosity and focus on the variations in the cyclotron line.Results. The centroid energy of the line is found to be positively correlated with the luminosity. We interpret this result as a manifestation of the local sub-Eddington (sub-critical) accretion regime operating in the source.
Keywords: X-rays: binaries; stars: neutron; accretion; accretion disks

Overview of the Advanced X-ray Imaging Satellite (AXIS) - Reynolds, Christopher S.; Kara, Erin A.; Mushotzky, Richard F.; Ptak, Andrew; Koss, Michael J.; Williams, Brian J.; Allen, Steven W.; Bauer, Franz E.; Bautz, Marshall; Bodaghee, Arash; Burdge, Kevin B.; Cappelluti, Nico; et al. (Proceedings of SPIE - The International Society for Optical Engineering, 2023)
The Advanced X-ray Imaging Satellite (AXIS) is a Probe-class concept that will build on the legacy of the Chandra X-ray Observatory by providing low-background, arcsecond-resolution imaging in the 0.3-10 keV band across a 450 arcminute2 field of view, with an order of magnitude improvement in sensitivity. AXIS utilizes breakthroughs in the construction of lightweight segmented X-ray optics using single-crystal silicon, and developments in the fabrication of large-format, small-pixel, high readout rate CCD detectors with good spectral resolution, allowing a robust and cost-effective design. Further, AXIS will be responsive to target-of-opportunity alerts and, with onboard transient detection, will be a powerful facility for studying the time-varying X-ray universe, following on from the legacy of the Neil Gehrels (Swift) X-ray observatory that revolutionized studies of the transient X-ray Universe. In this paper, we present an overview of AXIS, highlighting the prime science objectives driving the AXIS concept and how the observatory design will achieve these objectives.
CRIS-Team Scopus Importer:2023-11-24
Keywords: APEX Probe missions; X-ray astronomy; X-ray detectors; X-ray optics

Particle transport within the pulsar wind nebula HESS J1825-137 - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Arrieta, M.; Backes, M.; Barnard, Monica; Becherini, Y.; Tjus, J. Becker; et al. (Astronomy & Astrophysics, 2019)
Context. We present a detailed view of the pulsar wind nebula (PWN) HESS J1825-137. We aim to constrain the mechanisms dominating the particle transport within the nebula, accounting for its anomalously large size and spectral characteristics. Aims. The nebula was studied using a deep exposure from over 12 years of H.E.S.S. I operation, together with data from H.E.S.S. II that improve the low-energy sensitivity. Enhanced energy-dependent morphological and spatially resolved spectral analyses probe the very high energy (VHE, E > 0.1 TeV) γ-ray properties of the nebula. Methods. The nebula emission is revealed to extend out to 1.5° from the pulsar, ∼1.5 times farther than previously seen, making HESS J1825-137, with an intrinsic diameter of ∼100 pc, potentially the largest γ-ray PWN currently known. Characterising the strongly energy-dependent morphology of the nebula enables us to constrain the particle transport mechanisms. A dependence of the nebula extent with energy of RE α with α = -0.29 ± 0.04 stat ± 0.05 sys disfavours a pure diffusion scenario for particle transport within the nebula. The total γ-ray flux of the nebula above 1 TeV is found to be (1.12 ± 0.03 stat ± 0.25 sys ) × 10 -11 cm -2 s -1 , corresponding to ∼64% of the flux of the Crab nebula. Results. HESS J1825-137 is a PWN with clearly energy-dependent morphology at VHE γ-ray energies. This source is used as a laboratory to investigate particle transport within intermediate-age PWNe. Based on deep observations of this highly spatially extended PWN, we produce a spectral map of the region that provides insights into the spectral variation within the nebula.
CRIS-Team Scopus Importer:2019-05-02
Keywords: gamma rays: general; acceleration of particles; convection; diffusion; pulsars: general

Partly burned white dwarf survivors from peculiar thermonuclear supernovae - Raddi, Roberto (Proceedings of Science, 2021)
LP 40−365 is the prototype of a new class of runaway stars, thus far consisting of four members. The atmospheres of the known “LP 40−365 stars” are dominated by oxygen, neon, and magnesium, and are sprinkled with the ashes of partial oxygen and silicon burning. Possessing masses and radii in the range of 0.2-0.3 M☉ and 0.16-0.6 R☉, respectively, the LP 40−365 stars are suggested to be the former accreting white dwarfs that have survived disruption in near-Chandrasekhar-mass thermonuclear supernova explosions. Due to remarkable mass loss, the LP 40−365 stars were violently unbound from their companions. Detailed spectroscopic and kinematic analysis is crucial to assess their physical properties, which can be used as boundary conditions for population synthesis modelling aiming to characterise the formation and evolution mechanisms.
CRIS-Team Scopus Importer:2021-03-19

Partly burnt runaway stellar remnants from peculiar thermonuclear supernovae - Raddi, Roberto; Hollands, M. A.; Koester, D.; Hermes, J. J.; Gansicke, B. T.; Heber, Ulrich; Shen, K. J.; Townsley, D. M.; Pala, A. F.; Reding, J. S.; Toloza, O. F.; Pelisoli, I.; et al. (Monthly Notices of the Royal Astronomical Society, 2019)
We report the discovery of three stars that, along with the prototype LP 40-365, form a distinct class of chemically peculiar runaway stars that are the survivors of thermonuclear explosions. Spectroscopy of the four confirmed LP 40-365 stars finds ONe-dominated atmospheres enriched with remarkably similar amounts of nuclear ashes of partial O- and Si-burning. Kinematic evidence is consistent with ejection from a binary supernova progenitor; at least two stars have rest-frame velocities indicating they are unbound to the Galaxy. With masses and radii ranging between 0.20 and 0.28Mθ and between 0.16 and 0.60 Rθ, respectively, we speculate these inflated white dwarfs are the partly burnt remnants of either peculiar Type Iax or electron-capture supernovae. Adopting supernova rates from the literature, we estimate that ∼20 LP 40-365 stars brighter than 19 mag should be detectable within 2 kpc from the Sun at the end of the Gaia mission. We suggest that as they cool, these stars will evolve in their spectroscopic appearance, and eventually become peculiar O-rich white dwarfs. Finally, we stress that the discovery of new LP 40-365 stars will be useful to further constrain their evolution, supplying key boundary conditions to the modelling of explosion mechanisms, supernova rates, and nucleosynthetic yields of peculiar thermonuclear explosions.
CRIS-Team Scopus Importer:2019-11-29
Keywords: Galaxy: Kinematics and dynamics; Stars: Individual: LP 40-365; Subdwarfs; Supernovae: General-white dwarfs

Performance assessment of different pulse reconstruction algorithms for the ATHENA X-ray Integral Field Unit - Peille, Philippe; Ceballos, Maria Teresa; Cobo, Beatriz; Wilms, Jörn; Bandler, Simon; Smith, Stephen J.; Dauser, Thomas; Brand, Thorsten; Den Hartog, Roland; De Plaa, Jelle; Barret, Didier; Den Herder, Jan Willem; et al. (Space Telescopes and Instrumentation 2016: Ultraviolet to Gamma Ray, 2016)
The X-ray Integral Field Unit (X-IFU) microcalorimeter, on-board Athena, with its focal plane comprising 3840 Transition Edge Sensors (TESs) operating at 90 mK, will provide unprecedented spectral-imaging capability in the 0.2-12 keV energy range. It will rely on the on-board digital processing of current pulses induced by the heat deposited in the TES absorber, as to recover the energy of each individual events. Assessing the capabilities of the pulse reconstruction is required to understand the overall scientific performance of the X-IFU, notably in terms of energy resolution degradation with both increasing energies and count rates. Using synthetic data streams generated by the X-IFU End-to-End simulator, we present here a comprehensive benchmark of various pulse reconstruction techniques, ranging from standard optimal filtering to more advanced algorithms based on noise covariance matrices. Beside deriving the spectral resolution achieved by the different algorithms, a first assessment of the computing power and ground calibration needs is presented. Overall, all methods show similar performances, with the reconstruction based on noise covariance matrices showing the best improvement with respect to the standard optimal filtering technique. Due to prohibitive calibration needs, this method might however not be applicable to the X-IFU and the best compromise currently appears to be the so-called resistance space analysis which also features very promising high count rate capabilities.
Keywords: Athena; microcalorimeters; performance analysis; pulse reconstruction; X-IFU; X-rays

Performances of JEM-EUSO: angular reconstruction (vol 30, pg 153, 2015) - Adams, J. H.; Ahmad, S.; Albert, J. -N.; Allard, D.; Anchordoqui, L.; Andreev, V.; Anzalone, A.; Arai, Y.; Asano, K.; Ave Pernas, M.; Baragatti, P.; Barrillon, P.; et al. (Experimental Astronomy, 2015)

Performances of JEM-EUSO: energy and X (max) reconstruction - Adams, J. H.; Ahmad, S.; Albert, J. -N.; Allard, D.; Anchordoqui, L.; Andreev, V.; Anzalone, A.; Arai, Y.; Asano, K.; Ave Pernas, M.; Baragatti, P.; Barrillon, P.; et al. (Experimental Astronomy, 2015)
The Extreme Universe Space Observatory (EUSO) on-board the Japanese Experimental Module (JEM) of the International Space Station aims at the detection of ultra high energy cosmic rays from space. The mission consists of a UV telescope which will detect the fluorescence light emitted by cosmic ray showers in the atmosphere. The mission, currently developed by a large international collaboration, is designed to be launched within this decade. In this article, we present the reconstruction of the energy of the observed events and we also address the X (max) reconstruction. After discussing the algorithms developed for the energy and X (max) reconstruction, we present several estimates of the energy resolution, as a function of the incident angle, and energy of the event. Similarly, estimates of the X (max) resolution for various conditions are presented.
Keywords: JEM-EUSO; Energy reconstruction; X-max reconstruction

PG 1610+062: a runaway B star challenging classical ejection mechanisms - Irrgang, Andreas; Geier, Stephan; Heber, Ulrich; Kupfer, Thomas; Furst, F. S. (Astronomy & Astrophysics, 2019)
Hypervelocity stars are rare objects, mostly main-sequence (MS) B stars, traveling so fast that they will eventually escape from the Milky Way. Recently, it has been shown that the popular Hills mechanism, in which a binary system is disrupted via a close encounter with the supermassive black hole at the Galactic center, may not be their only ejection mechanism. The analyses of Gaia data ruled out a Galactic center origin for some of them, and instead indicated that they are extreme disk runaway stars ejected at velocities exceeding the predicted limits of classical scenarios (dynamical ejection from star clusters or binary supernova ejection). We present the discovery of a new extreme disk runaway star, PG 1610+062, which is a slowly pulsating B star bright enough to be studied in detail. A quantitative analysis of spectra taken with ESI at the Keck Observatory revealed that PG 1610+062 is a late B-type MS star of 4-5 M-circle dot with low projected rotational velocity. Abundances (C, N, O, Ne, Mg, Al, Si, S, Ar, and Fe) were derived differentially with respect to the normal B star HD 137366 and indicate that PG 1610+062 is somewhat metal rich. A kinematic analysis, based on our spectrophotometric distance (17.3 kpc) and on proper motions from Gaia's second data release, shows that PG 1610+062 was probably ejected from the Carina-Sagittarius spiral arm at a velocity of 550 +/- 40 km s(-1), which is beyond the classical limits. Accordingly, the star is in the top five of the most extreme MS disk runaway stars and is only the second among the five for which the chemical composition is known.
Keywords: stars: abundances; stars: individual: HD 137366; stars: kinematics and dynamics; stars: individual: PG 1610+062; stars: early-type

PheniX: a new vision for the hard X-ray sky - Roques, Jean-Pierre; Jourdain, Elisabeth; Bassani, Loredana; Bazzano, Angela; Belmont, Renaud; Bird, A. J.; Caroli, Ezio; Chauvin, Maxime; Clark, D.; Gehrels, N.; Goerlach, U.; Harrisson, F.; et al. (Experimental Astronomy, 2012)
We are proposing a mission devoted to high energy X-ray astronomy that is based on a focusing telescope operating in the 1-200 keV energy range but optimized for the hard X-ray range. The main scientific topics concern: Physics of compact objects: The proximity of compact objects provides a unique laboratory to study matter and radiation in extreme conditions of temperature and density in strong gravitational environment. The emission of high energy photons from these objects is far from being understood. The unprecedented sensitivity in the high energy domain will allow a precise determination of the non-thermal processes at work in the vicinity of compact objects. The full 1-200 keV energy coverage will be ideal to disentangle the emission processes produced in the spacetime regions most affected by strong-gravity, as well as the physical links: disk-thermal emission-iron line-comptonisation-reflection-non-thermal emission-jets. Neutron stars-magnetic field-cyclotron lines: Time resolved spectroscopy (and polarimetry) at ultra-high sensitivity of AXP, milliseconds pulsars and magnetars will give new tools to study the role of the synchrotron processes at work in these objects. Cyclotron lines-direct measurement of magnetic filed-equation of state constraints-short bursts-giant flares could all be studied with great details. AGN: The large sensitivity improvement will provide detailed spectral properties of the high energy emission of AGN's. This will give a fresh look to the connection between accretion and jet emission and will provide a new understanding of the physical processes at work. Detection of high-redshift active nuclei in this energy range will allow to introduce an evolutionary aspect to high-energy studies of AGN, probing directly the origin of the Cosmic X-ray Background also in the non-thermal range (> 20 keV). Element formation-Supernovae: The energy resolution achievable for this mission (< 0.5 keV) and a large high energy effective area are ideally suited for the 44Ti line study (68 and 78 keV). This radioactive nuclei emission will give an estimate of their quantities and speed in their environment. In addition the study of the spatial structure and spectral emission of SNR will advance our knowledge of the dynamics of supernovae explosions, of particles acceleration mechanisms and how the elements are released in the interstellar medium. Instrumental design: The progress of X-ray focusing optics techniques allows a major step in the instrumental design: the collecting area becomes independent of the detection area. This drastically reduces the instrumental background and will open a new era. The optics will be based on depth-graded multi-layer mirrors in a Wolter I configuration. To obtain a significant effective area in the hundred of keV range a focal length in the 40-50 meters range (attainable with a deployable mast) is needed. In addition such a mission could benefit from recent progress made on mirror coating. We propose to cover the 1-200 keV energy range with a single detector, a double-sided Germanium strip detector operating at 80 K. The main features will be: (a) good energy resolution (.150 keV at 5 keV and <.5 keV at 100 keV), (b) 3 dimensional event localization with a low number of electronic chains, (c) background rejection by the 3D localization, (d) polarisation capabilities in the Compton regime.
Keywords: Hard X-rays; Germanium; Grazing incidence optics; Space instrument

Photoionization Models for High-density Gas - Kallman, T.; Bautista, M.; Deprince, J.; Garcia, Javier; Mendoza, Claudio; Ogorzalek, Anna; Palmeri, P.; Quinet, P. (Astrophysical Journal, 2021)
Relativistically broadened and redshifted 6.4-6.9 keV iron K lines are observed from many accretion powered objects, including X-ray binaries and active galactic nuclei. The existence of gas close to the central engine implies large radiation intensities and correspondingly large gas densities if the gas is to remain partially ionized. Simple estimates indicate that high gas densities are needed to allow for the survival of iron against ionization. These are high enough that rates for many atomic processes are affected by mechanisms related to interactions with nearby ions and electrons. Radiation intensities are high enough that stimulated processes can be important. Most models currently in use for interpreting relativistic lines use atomic rate coefficients designed for use at low densities and neglect stimulated processes. In our work so far we have presented atomic structure calculations with the goal of providing physically appropriate models at densities consistent with line-emitting gas near compact objects. In this paper we apply these rates to photoionization calculations, and produce ionization balance curves and X-ray emissivities and opacities that are appropriate for high densities and high radiation intensities. The final step in our program will be presented in a subsequent paper in which model atmosphere calculations will incorporate these rates into synthetic spectra.
CRIS-Team Scopus Importer:2021-04-09

Plasma environment effects on K lines of astrophysical interest: I. Atomic structure, radiative rates, and Auger widths of oxygen ions - Deprince, Jerome; Bautista, M. A.; Fritzsche, S.; Garcia, Javier; Kallman, T. R.; Mendoza, Claudio; Palmeri, P.; Quinet, P. (Astronomy & Astrophysics, 2019)
Aims. In the context of black-hole accretion disks, the main goal of the present study is to estimate the plasma environment effects on the atomic structure and radiative parameters associated with the K-vacancy states in ions of the oxygen isonuclear sequence. Methods. We used a time-averaged Debye-Hückel potential for both the electron-nucleus and the electron-electron interactions implemented in the fully relativistic multiconfiguration Dirac-Fock (MCDF) method. Results. Modified ionization potentials, K thresholds, Auger widths, and radiative transition wavelengths and rates are reported for O I-O VII in plasma environments with electron temperature and density ranges 105-107 K and 1018-1022 cm-3.
CRIS-Team Scopus Importer:2021-04-20
Keywords: Atomic data; Black hole physics; Plasmas; X-rays: general

Plasma environment effects on K lines of astrophysical interest: II. Ionization potentials, K thresholds, radiative rates, and Auger widths in Ne-Through He-like iron ions (Feâ XVII-Feâ XXV) - Deprince, Jerome; Bautista, M. A.; Fritzsche, S.; Garcia, Javier; Kallman, T.; Mendoza, Claudio; Palmeri, P.; Quinet, P. (Astronomy & Astrophysics, 2019)
Aims. In the context of accretion disks around black holes, we estimate plasma-environment effects on the atomic parameters associated with the decay of K-vacancy states in highly charged iron ions, namely Feâ XVII-Feâ XXV. Methods. Within the relativistic multiconfiguration Dirac-Fock (MCDF) framework, the electron-nucleus and electron-electron plasma screenings were approximated with a time-Averaged Debye-Hückel potential. Results. Modified ionization potentials, K thresholds, wavelengths, radiative emission rates, and Auger widths are reported for astrophysical plasmas characterized by electron temperatures and densities in the ranges 105â-Â 107 K and 1018â-Â 1022 cm-3, respectively. Conclusions. We conclude that the high-resolution microcalorimeters on board future X-ray missions such as XRISM and ATHENA are expected to be sensitive to the lowering of the iron K edge due to the extreme plasma conditions occurring in accretion disks around compact objects.
CRIS-Team Scopus Importer:2021-04-20
Keywords: Atomic data; Black hole physics; Plasmas; X-rays: general

Plasma environment effects on K lines of astrophysical interest: IV. IPs, K thresholds, radiative rates, and Auger widths in Fe II-Fe VIII - Deprince, Jerome; Bautista, M. A.; Fritzsche, S.; Garcia, Javier; Kallman, T. R.; Mendoza, C.; Palmeri, P.; Quinet, P. (Astronomy & Astrophysics, 2020)
Aims. Within the framework of compact-object accretion disks, we calculate plasma environment effects on the atomic structure and decay parameters used in the modeling of K lines in lowly charged iron ions, namely Fe II-Fe VIII. Methods. For this study, we used the fully relativistic multiconfiguration Dirac-Fock method approximating the plasma electron-nucleus and electron-electron screenings with a time-averaged Debye-Hückel potential. Results. We report modified ionization potentials, K-threshold energies, wavelengths, radiative emission rates, and Auger widths for plasmas characterized by electron temperatures and densities in the ranges 105â€ -â€ 107 K and 1018â€ -â€ 1022 cm-3. In addition, we propose two universal fitting formulae to predict the IP and K-threshold lowerings in any elemental ion. Conclusions. We conclude that the high-resolution X-ray spectrometers onboard the future XRISM and ATHENA space missions will be able to detect the lowering of the K edges of these Fe ions due to the extreme plasma conditions occurring in the accretion disks around compact objects.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Atomic data; Black hole physics; Plasmas; X-rays: general

Plasma environment effects on K lines of astrophysical interest: V. Universal formulae for ionization potential and K-threshold shifts - Palmeri, P.; Deprince, J.; Bautista, M. A.; Fritzsche, S.; Garcia, Javier; Kallman, T. R.; Mendoza, C.; Quinet, P. (Astronomy & Astrophysics, 2022)
Aims. We calculate the plasma environment effects on the ionization potentials (IPs) and K-thresholds used in the modeling of K lines for all the ions belonging to the isonuclear sequences of abundant elements apart from oxygen and iron, namely: carbon, silicon, calcium, chromium, and nickel. These calculations are used to extend the data points for the fits of the universal formulae, first proposed in our fourth paper of this series, to predict the IP and K-threshold lowerings in any elemental ion. Methods. We used the fully relativistic multi-configuration Dirac-Fock method and approximated the plasma electron-nucleus and electron-electron screenings with a time-averaged Debye-Hückel potential. Results. We report the modified ionization potentials and K-threshold energies for plasmas characterized by electron temperatures and densities in the ranges of 105-107 K and 1018-1022 cm-3. In addition, the improved universal fitting formulae are obtained. Conclusions. We conclude that since explicit calculations of the atomic structures for each ion of each element under different plasma conditions is impractical, the use of these universal formulae for predicting the IP and K-threshold lowerings in plasma modeling codes is still recommended. However, their comparatively moderate to low accuracies may affect the predicted opacities with regard to certain cases under extreme plasma conditions that are characterized by a plasma screening parameter of μ > 0.2 a.u., especially for the K-thresholds.
CRIS-Team Scopus Importer:2022-01-28
Keywords: Atomic data; Black hole physics; Plasmas; X-rays: general

Polarized Gamma-Ray Emission from the Galactic Black Hole Cygnus X-1 - Laurent, P.; Rodriguez, Jerome; Wilms, Jörn; Bel, M. Cadolle; Pottschmidt, K.; Grinberg, Victoria (Science, 2011)
Because of their inherently high flux allowing the detection of clear signals, black hole x-ray binaries are interesting candidates for polarization studies, even if no polarization signals have been observed from them before. Such measurements would provide further detailed insight into these sources' emission mechanisms. We measured the polarization of the gamma-ray emission from the black hole binary system Cygnus X-1 with the International Gamma-Ray Astrophysics Laboratory Imager on Board the Integral Satellite (INTEGRAL/IBIS) telescope. Spectral modeling of the data reveals two emission mechanisms: The 250- to 400-keV ( kilo-electron volt) data are consistent with emission dominated by Compton scattering on thermal electrons and are weakly polarized. The second spectral component seen in the 400-keV to 2-MeV band is by contrast strongly polarized, revealing that the MeV emission is probably related to the jet first detected in the radio band.

Polarized x-rays constrain the disk-jet geometry in the black hole x-ray binary Cygnus X-1 - Krawczynski, Henric; Muleri, Fabio; Dovčiak, Michal; Veledina, Alexandra; Rodriguez Cavero, Nicole; Svoboda, Jiri; Ingram, Adam; Matt, Giorgio; Garcia, Javier A.; Loktev, Vladislav; Negro, Michela; Poutanen, Juri; et al. (Science, 2022)
A black hole x-ray binary (XRB) system forms when gas is stripped from a normal star and accretes onto a black hole, which heats the gas sufficiently to emit x-rays. We report a polarimetric observation of the XRB Cygnus X-1 using the Imaging X-ray Polarimetry Explorer. The electric field position angle aligns with the outflowing jet, indicating that the jet is launched from the inner x-ray-emitting region. The polarization degree is 4.01 ± 0.20% at 2 to 8 kiloelectronvolts, implying that the accretion disk is viewed closer to edge-on than the binary orbit. These observations reveal that hot x-ray-emitting plasma is spatially extended in a plane perpendicular to, not parallel to, the jet axis.
CRIS-Team Scopus Importer:2022-11-25

Population of the Galactic X-ray binaries and eRosita (Research Note) - Doroshenko, V.; Ducci, L.; Santangelo, A.; Sasaki, Manami (Astronomy & Astrophysics, 2014)
The population of the Galactic X-ray binaries has been mostly probed with moderately sensitive hard X-ray surveys so far. The eRosita mission will provide for the first time a sensitive all sky X-ray survey in the 2-10 keV energy range, where the X-ray binaries emit most of the flux and discover the still unobserved low luminosity population of these objects. In this paper, we briefly review the current constraints for the X-ray luminosity functions of high- and low-mass X-ray binaries and present our own analysis based the INTEGRAL 9-year Galactic survey, which yields improved constraints. Based on these results, we estimate the number of new XRBs to be detected in the eRosita all sky survey.
Keywords: X-rays: binaries; Galaxy: structure; stars: luminosity function; mass function; surveys

Population study of Galactic supernova remnants at very high gamma-ray energies with HESS - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Anguener, E. O.; Arakawa, M.; Arrieta, M.; Aubert, P.; Backes, M.; Balzer, A.; Barnard, M.; Becherini, Y.; et al. (Astronomy & Astrophysics, 2018)
Shell-type supernova remnants (SNRs) are considered prime candidates for the acceleration of Galactic cosmic rays (CRs) up to the knee of the CR spectrum at E approximate to 3 x 10(15) eV. Our MilkyWay galaxy hosts more than 350 SNRs discovered at radio wavelengths and at high energies, of which 220 fall into the H.E.S.S. Galactic Plane Survey (HGPS) region. Of those, only 50 SNRs are coincident with a H.E.S.S source and in 8 cases the very high-energy (VHE) emission is firmly identified as an SNR. The H.E.S.S. GPS provides us with a legacy for SNR population study in VHE gamma-rays and we use this rich data set to extract VHE flux upper limits from all undetected SNRs. Overall, the derived flux upper limits are not in contradiction with the canonical CR paradigm. Assuming this paradigm holds true, we can constrain typical ambient density values around shell-type SNRs to n <= 7 cm(-3) and electron-to-proton energy fractions above 10 TeV to epsilon(ep) <= 5 x 10(-3). Furthermore, comparisons of VHE with radio luminosities in non-interacting SNRs reveal a behaviour that is in agreement with the theory of magnetic field amplification at shell-type SNRs.
Keywords: gamma rays: general; ISM: supernova remnants

Potential origin of the state-dependent high-energy tail in the black hole microquasar Cygnus X-1 as seen with INTEGRAL - Cangemi, F.; Beuchert, T.; Siegert, T.; Rodriguez, J.; Grinberg, V.; Belmont, R.; Gouiffès, C.; Kreykenbohm, Ingo; Laurent, P.; Pottschmidt, K.; Wilms, Jörn (Astronomy & Astrophysics, 2021)
Context. 0.1-10 MeV observations of the black hole microquasar Cygnus X-1 have shown the presence of a spectral feature in the form of a power law in addition to the standard black body (0.1-10 keV) and Comptonization (10-200 keV) components observed by INTEGRAL in several black-hole X-ray binaries. This so-called "high-energy tail"was recently shown to be strong in the hard spectral state of Cygnus X-1, and, in this system, has been interpreted as the high-energy part of the emission from a compact jet. Aims. This result was nevertheless obtained from a data set largely dominated by hard state observations. In the soft state, only upper limits on the presence and hence the potential parameters of a high-energy tail could be derived. Using an extended data set, we aim to obtain better constraints on the properties of this spectral component in both states. Methods. We make use of data obtained from about 15 years of observations with the INTEGRAL satellite. The data set is separated into the different states and we analyze stacked state-resolved spectra obtained from the X-ray monitors, the gamma-ray imager, and the gamma-ray spectrometer (SPI) onboard. Results. A high-energy component is detected in both states, confirming its earlier detection in the hard state and its suspected presence in the soft state with INTEGRAL, as seen in a much smaller SPI data set. We first characterize the high-energy tail components in the two states through a model-independent, phenomenological analysis. We then apply physical models based on hybrid Comptonization (eqpair and belm). The spectra are well modeled in all cases, with a similar goodness of the fits. While in the semi-phenomenological approach the high-energy tail has similar indices in both states, the fits with the physical models seem to indicate slightly different properties. Based on this approach, we discuss the potential origins of the high-energy components in both the soft and hard states, and favor an interpretation where the high-energy component is due to a compact jet in the hard state and hybrid Comptonization in either a magnetized or nonmagnetized corona in the soft state.
CRIS-Team Scopus Importer:2021-06-25
Keywords: Accretion; accretion disks; Black hole physics; Radiation mechanisms: non-thermal; X-rays: binaries; X-rays: individuals: Cyg X-1

Probing cosmic inflation with the LiteBIRD cosmic microwave background polarization survey - Allys, E.; Arnold, K.; Aumont, J.; Aurlien, R.; Azzoni, S.; Baccigalupi, C.; Banday, A. J.; Banerji, R.; Barreiro, R. B.; Bartolo, N.; Bautista, L.; Beck, D.; et al. (Progress of Theoretical and Experimental Physics, 2023)
LiteBIRD, the Lite (Light) satellite for the study of B-mode polarization and Inflation from cosmic background Radiation Detection, is a space mission for primordial cosmology and fundamental physics. The Japan Aerospace Exploration Agency (JAXA) selected LiteBIRD in May 2019 as a strategic large-class (L-class) mission, with an expected launch in the late 2020s using JAXA’s H3 rocket. LiteBIRD is planned to orbit the Sun–Earth Lagrangian point L2, where it will map the cosmic microwave background polarization over the entire sky for three years, with three telescopes in 15 frequency bands between 34 and 448 GHz, to achieve an unprecedented total sensitivity of 2.2 μK-arcmin, with a typical angular resolution of 0.5◦ at 100 GHz. The primary scientific objective of LiteBIRD is to search for the signal from cosmic inflation, either making a discovery or ruling out well-motivated inflationary models. The measurements of LiteBIRD will also provide us with insight into the quantum nature of gravity and other new physics beyond the standard models of particle physics and cosmology. We provide an overview of the LiteBIRD project, including scientific objectives, mission and system requirements, operation concept, spacecraft and payload module design, expected scientific outcomes, potential design extensions, and synergies with other projects.
CRIS-Team Scopus Importer:2023-06-09

PROBING THE ACCRETION DISK AND CENTRAL ENGINE STRUCTURE OF NGC 4258 WITH SUZAKU AND XMM-NEWTON OBSERVATIONS - Reynolds, Christopher S.; Nowak, Michael A.; Markoff, Sera; Tueller, Jack; Wilms, Jörn; Young, Andrew J. (Astrophysical Journal, 2009)
We present an X-ray study of the low-luminosity active galactic nucleus (AGN) in NGC 4258 using data from Suzaku, XMM-Newton, and the Swift/Burst Alert Telescope survey. We find that signatures of X-ray reprocessing by cold gas are very weak in the spectrum of this Seyfert-2 galaxy; a weak, narrow fluorescent K alpha emission line of cold iron is robustly detected in both the Suzaku and XMM-Newton spectra but at a level much below that of most other Seyfert-2 galaxies. We conclude that the circumnuclear environment of this AGN is very "clean" and lacks the Compton-thick obscuring torus of unified Seyfert schemes. From the narrowness of the iron line, together with evidence of line flux variability between the Suzaku and XMM-Newton observations, we constrain the line emitting region to be between 3 x 10(3)r(g) and 4 x 10(4)r(g) from the black hole. We show that the observed properties of the iron line can be explained if the line originates from the surface layers of a warped accretion disk. In particular, we present explicit calculations of the expected iron line from a disk warped by Lens-Thirring precession from a misaligned central black hole. Finally, the Suzaku data reveal clear evidence of large amplitude 2-10 keV variability on timescales of 50 ksec and smaller amplitude flares on timescales as short as 5-10 ksec. If associated with accretion disk processes, such rapid variability requires an origin in the innermost regions of the disk (r approximate to 10r(g) or less). Analysis of the difference spectrum between a high-and low-flux states suggests that the variable component of the X-ray emission is steeper and more absorbed than the average AGN emission, suggesting that the primary X-ray source and absorbing screen have a spatial structure on comparable scales. We note the remarkable similarity between the circumnuclear environment of NGC 4258 and another well studied low-luminosity AGN, M81*.
Keywords: black hole physics; galaxies: individual (NGC 4258); galaxies: Seyfert; X-rays: galaxies

Probing the physical properties of the intergalactic medium using SRG/eROSITA spectra from blazars - Gatuzz, E.; Wilms, Jörn; Hämmerich, Steven; Arcodia, R. (Astronomy & Astrophysics, 2024)
Most baryonic matter resides in the intergalactic medium (IGM). This diffuse gas is primarily composed of ionized hydrogen and helium and fills the space between galaxies. Observations of this environment are crucial for better understanding the physical processes in it. We present an analysis of the IGM absorption using blazar spectra from the first eROSITA all-sky survey (eRASS1) performed onboard of the Spectrum-Roentgen-Gamma mission (SRG) and XMM-Newton X-ray observations. First, we fit the continuum spectra using a log-parabolic spectrum model and fixed the Galactic absorption. Then, we included a collisional ionization equilibrium model, namely IONeq, to account for the IGM absorption. The column density N(H) and metallicity (Z) were set as free parameters. At the same time, the redshift of the absorber was fixed to half the blazar redshift as an approximation of the full line-of-sight absorber. We measured IGM-N(H) for 147 sources for SRG and 10 sources for XMM-Newton. We found a clear trend between IGM-N(H) and the blazar redshifts that scales as (1 + z)1.63 ± 0.12. The mean hydrogen density at z = 0 is n0 = (2.75 ± 0.63)×10-7 cm-3. The mean temperature over the redshift range is log(T/K) = 5.6 ± 0.6, and the mean metallicity is Z = 0.16 ± 0.09. We found no acceptable fit using a power-law model for the temperatures or metallicities as a function of the redshift. These results indicate that the IGM contributes substantially to the total absorption seen in the blazar spectra.
CRIS-Team Scopus Importer:2024-03-29
Keywords: Galaxies: high-redshift; Intergalactic medium; X-rays: galaxies; X-rays: general

PSR J1024-0719: A MILLISECOND PULSAR IN AN UNUSUAL LONG-PERIOD ORBIT - Kaplan, D. L.; Kupfer, Thomas; Nice, David J.; Irrgang, Andreas; Heber, Ulrich; Arzoumanian, Zaven; Beklen, Elif; Crowter, Kathryn; Decesar, Megan E.; Demorest, Paul B.; Dolch, Timothy; Ellis, Justin A.; et al. (Astrophysical Journal, 2016)
PSR J1024-0719 is a millisecond pulsar that was long thought to be isolated. However, puzzling results concerning its velocity, distance, and low rotational period derivative have led to a reexamination of its properties. We present updated radio timing observations along with new and archival optical data which show that PSR J1024-0719 is most likely in a long-period (2-20 kyr) binary system with a low-mass (approximate to 0.4 M-circle dot), low-metallicity (Z approximate to -0.9 dex) main-sequence star. Such a system can explain most of the anomalous properties of this pulsar. We suggest that this system formed through a dynamical exchange in a globular cluster that ejected it into a halo orbit, which is consistent with the low observed metallicity for the stellar companion. Further astrometric and radio timing observations such as measurement of the third period derivative could strongly constrain the range of orbital parameters.
Keywords: binaries: general; pulsars: individual (PSR J1024-0719); stars: distances

PTF1 J082340.04+081936.5: A Hot Subdwarf B Star with a Low-mass White Dwarf Companion in an 87-minute Orbit - Kupfer, Thomas; van Roestel, Jan; Brooks, Jared; Geier, Stephan; Marsh, Tom R.; Groot, Paul J.; Bloemen, Steven; Prince, Thomas A; Bellm, Eric; Heber, Ulrich; Bildsten, Lars; Miller, Adam A.; et al. (Astrophysical Journal, 2017)
We present the discovery of the hot subdwarf B star (sdB) binary PTF1 J082340.04+081936.5. The system has an orbital period of P-orb = 87.49668(1) minutes (0.060761584(10) days), making it the second-most compact sdB binary known. The light. curve shows ellipsoidal variations. Under the assumption that the sdB primary is synchronized with the orbit, we find a mass of = M-sdB =0.45(-0.07)(+0.009) M-circle dot, a companion white dwarf mass of M-WD = 0.46(-0.09)(+0.12)M(circle dot), and a mass ratio of q =M-WD/M(sdB)1.03+(+0.10)(0.08). The future evolution was calculated using the MESA stellar evolution code. Adopting a canonical sdB mass of M-sdB = 0.47 M-circle dot, we find that the sdB still burns helium at the time it will fill its Roche lobe if the orbital period was less than 106 minutes at the exit from the last common envelope (CE) phase. For longer CE exit periods, the sdB will have stopped burning helium and turned into a C/O white dwarf at the time of contact. Comparing the spectroscopically derived log g and T-eff with our MESA models, we find that an sdB model with a hydrogen envelope mass of 5 x 10(-4) M-circle dot matches the measurements at a post-CE age of 94 Myr, corresponding to a post-CE orbital period of 109 minutes, which is close to the limit to start accretion while the sdB is still burning helium.
Keywords: binaries: close; stars: individual (PTF1 J082340.04+081936.5); subdwarfs; white dwarfs

Public Release of RELXILL_NK: A Relativistic Reflection Model for Testing Einstein's Gravity - Abdikamalov, Askar B.; Ayzenberg, Dimitry; Bambi, Cosimo; Dauser, Thomas; Garcia, Javier; Nampalliwar, Sourabh (Astrophysical Journal, 2019)
We present the public release version of RELXILL_NK, an X-ray reflection model for testing the Kerr hypothesis and general relativity. This model extends the RELXILL model that assumes the black hole (BH) spacetime is described by the Kerr metric. We also present RELXILLLP_NK, the first non-Kerr X-ray reflection model with a lamppost corona configuration, as well as all other models available in the full RELXILL_NK package. In all models the relevant relativistic effects are calculated through a general relativistic ray-tracing code that can be applied to any well-behaved, stationary, axisymmetric, and asymptotically flat BH spacetime. We show that the numerical error introduced by using a ray-tracing code is not significant compared with the observational error present in current X-ray reflection spectrum observations. In addition, we present the reflection spectrum for the Johannsen metric as calculated by RELXILL_NK.
CRIS-Team WoS Importer:2019-07-09

Quantifying the Effect of Cosmic Ray Showers on the X-IFU Energy Resolution - Peille, P.; Den Hartog, R.; Miniussi, A.; Stever, S.; Bandler, S.; Kirsch, Christian; Lorenz, Maximilian; Dauser, Thomas; Wilms, Jörn; Lotti, S.; Gatti, F.; Macculi, C.; et al. (Journal of Low Temperature Physics, 2020)
The X-ray Integral Field Unit (X-IFU) will operate an array of more than 3000 Transition Edge Sensor pixels at 90 mK with an unprecedented energy resolution of 2.5 eV at 7 keV. In space, primary cosmic rays and secondary particles produced in the instrument structure will continuously deposit energy on the detector wafer and induce fluctuations on the pixels’ thermal bath. We have investigated through simulations of the X-IFU readout chain how these fluctuations eventually influence the energy measurement of X-ray photons. Realistic timelines of thermal bath fluctuations at different positions in the array are generated as a function of a thermal model and the expected distribution of the deposited energy of the charged particles. These are then used to model the TES response to these thermal perturbations and their influence on the onboard energy reconstruction process. Overall, we show that with adequate heatsinking, the main energy resolution degradation effect remains minimal and within the associated resolution allocation of 0.2 eV. We further study how a dedicated triggering algorithm could be put in place to flag the rarer large thermal events.
CRIS-Team Scopus Importer:2020-02-14
Keywords: Cosmic rays; Energy resolution; TES; X-IFU; X-ray microcalorimeters

quantitative spectral analysis of 14 hypervelocity stars from the MMT survey - Irrgang, Andreas; Kreuzer, Simon; Heber, Ulrich; Brown, W. (Astronomy & Astrophysics, 2018)
Context. Hypervelocity stars (HVSs) travel so fast that they may leave the Galaxy. The tidal disruption of a binary system by the supermassive black hole in the Galactic center is widely assumed to be their ejection mechanism.Aims. To test the hypothesis of an origin in the Galactic center using kinematic investigations, the current space velocities of the HVSs need to be determined. With the advent of Gaia's second data release, accurate radial velocities from spectroscopy are complemented by proper motion measurements of unprecedented quality. Based on a new spectroscopic analysis method, we provide revised distances and stellar ages, both of which are crucial to unravel the nature of the HVSs.Methods. We reanalyzed low-resolution optical spectra of 14 HVSs from the MMT HVS survey using a new grid of synthetic spectra, which account for deviations from local thermodynamic equilibrium, to derive effective temperatures, surface gravities, radial velocities, and projected rotational velocities. Stellar masses, radii, and ages were then determined by comparison with stellar evolutionary models that account for rotation. Finally, these results were combined with photometric measurements to obtain spectroscopic distances.Results. The resulting atmospheric parameters are consistent with those of main sequence stars with masses in the range 2.5-5.0 M-circle dot. The majority of the stars rotate at fast speeds, providing further evidence for their main sequence nature. Stellar ages range from 90 to 400 Myr and distances (with typical 1 sigma-uncertainties of about 10-15%) from 30 to 100 kpc. Except for one object (B 711), which we reclassify as A-type star, all stars are of spectral type B.Conclusions. The spectroscopic distances and stellar ages derived here are key ingredients for upcoming kinematic studies of HVSs based on Gaia proper motions.
Keywords: stars: distances; stars: early-type; stars: fundamental parameters

Quantitative spectral analysis of the sdB star HD188112: A helium-core white dwarf progenitor - Latour, Marilyn; Heber, Ulrich; Irrgang, Andreas; Schaffenroth, Veronika; Geier, Stephan; Hillebrandt, W.; Roepke, F. K.; Taubenberger, S.; Kromer, Markus; Fink, M. (Astronomy & Astrophysics, 2016)
Context. HD 188112 is a bright (V = 10 : 2 mag) hot subdwarf B (sdB) star with a mass too low to ignite core helium burning and is therefore considered a pre-extremely low-mass (ELM) white dwarf (WD). ELM WDs (M less than or similar to 0.3 M-circle dot) are He-core objects produced by the evolution of compact binary systems.Aims. We present in this paper a detailed abundance analysis of HD188112 based on high-resolution Hubble Space Telescope (HST) near-and far-ultraviolet spectroscopy. We also constrain the mass of the star's companion.Methods. We use hybrid non-LTE model atmospheres to fit the observed spectral lines, and to derive the abundances of more than a dozen elements and the rotational broadening of metallic lines.Results. We confirm the previous binary system parameters by combining radial velocities measured in our UV spectra with the previously published values. The system has a period of 0.60658584 days and a WD companion with M >= 0.70 M-circle dot. By assuming a tidally locked rotation combined with the projected rotational velocity (v sin i = 7.9 +/- 0.3 km s(-1)), we constrain the companion mass to be between 0.9 and 1.3 M-circle dot. We further discuss the future evolution of the system as a potential progenitor of an underluminous type Ia supernova. We measure abundances for Mg, Al, Si, P, S, Ca, Ti, Cr, Mn, Fe, Ni, and Zn, and for the trans-iron elements Ga, Sn, and Pb. In addition, we derive upper limits for the C, N, O elements and find HD188112 to be strongly depleted in carbon. We find evidence of non-LTE e ff ects on the line strength of some ionic species such as Si II and Ni II. The metallic abundances indicate that the star is metal-poor, with an abundance pattern most likely produced by diffusion effects.
Keywords: stars: abundances; stars: atmospheres; stars: individual: HD 188112; subdwarfs; white dwarfs; binaries: general

Quantitative spectroscopy of extreme helium stars Model atmospheres and a non-LTE abundance analysis of BD+10 degrees 2179 - Kupfer, Thomas; Przybilla, N.; Heber, Ulrich; Heber, Ulrich; Jeffery, C. S.; Behara, N. T.; Butler, K. (Monthly Notices of the Royal Astronomical Society, 2017)
Extreme helium stars (EHe stars) are hydrogen-deficient supergiants of spectral type A and B. They are believed to result from mergers in double degenerate systems. In this paper, we present a detailed quantitative non-LTE spectral analysis for BD+10. 2179, a prototype of this rare class of stars, using UV-Visual Echelle Spectrograph and Fiber-fed Extended Range Optical Spectrograph spectra covering the range from similar to 3100 to 10 000 angstrom. Atmosphere model computations were improved in two ways. First, since the UV metal line blanketing has a strong impact on the temperature-density stratification, we used the ATLAS12 code. Additionally, We tested ATLAS12 against the benchmark code STERNE3, and found only small differences in the temperature and density stratifications, and good agreement with the spectral energy distributions. Secondly, 12 chemical species were treated in non-LTE. Pronounced nonLTE effects occur in individual spectral lines but, for the majority, the effects are moderate to small. The spectroscopic parameters give T-eff = 17 300 +/- 300 K and log g = 2.80 +/- 0.10, and an evolutionary mass of 0.55 +/- 0.05 M circle dot. The star is thus slightly hotter, more compact and less massive than found in previous studies. The kinematic properties imply a thick-disc membership, which is consistent with the metallicity [Fe/H] approximate to -1 and alpha-enhancement. The refined light-element abundances are consistent with the white dwarf merger scenario. We further discuss the observed helium spectrum in an appendix, detecting dipole-allowed transitions from about 150 multiplets plus the most comprehensive set of known/predicted isolated forbidden components to date. Moreover, a so far unreported series of pronounced forbidden He I components is detected in the optical-UV.
Keywords: line: formation; stars: abundances; stars: atmospheres; stars: fundamental parameters; stars: individual: BD+10 degrees 2179

Radial velocity measurements of Subdwarf B stars (vol 415, pg 1381, 2011) - Copperwheat, C. M.; Morales-Rueda, L.; Marsh, Thomas R.; Maxted, P. F. L.; Heber, Ulrich (Monthly Notices of the Royal Astronomical Society, 2015)
Keywords: errata; addenda; binaries: close; binaries: spectroscopic; subdwarfs

Radial velocity search for substellar companions to sdB stars - O'Toole, Simon; Heber, Ulrich; Geier, Stephan; Classen, Lew; De Marco, Orsola (AIP Conference Proceedings, 2011)
After the discovery of a substellar companion to the hot subdwarf HD 149382, we have started a radial velocity search for similar objects around other bright sdB stars using the Anglo-Australian Telescope. Our aim is to test the hypothesis that close substellar companions can significantly affect the post-main sequence evolution of solar-type stars. It has previously been proposed that binary interactions in this scenario could lead to the formation of hot subdwarfs. The detection of such objects will provide strong evidence that Jupiter-mass planets can survive the interaction with a solar-type star as it evolves up the Red Giant Branch. We present the first results of our search here. © 2011 American Institute of Physics.
CRIS-Team Scopus Importer:2020-12-21
Keywords: stars: binaries; stars: brown dwarfs

Radial velocity survey of low-mass companions to sdB stars - Classen, Lew; Geier, Stephan; Heber, Ulrich; O'Toole, Simon J. (AIP Conference Proceedings, 2011)
The origin of subdwarf B (sdB) stars is not fully understood yet since it requires high mass loss at the red giant stage. SdBs in close binary systems are formed via common envelope ejection, but the origin of apparently single sdB stars remains unclear. Substellar companions may be able to trigger common envelope ejection and help forming sdBs that appear to be single. Using a sample of high resolution spectra we aim at detecting small radial velocity (RV) shifts caused by such low mass (sub-)stellar companions. The RVs are measured with high accuracy using sharp metal lines. Our goal is to test the theoretical predictions and put constraints on the population of the lowest mass companions to sdB stars. © 2011 American Institute of Physics.
CRIS-Team Scopus Importer:2020-12-21
Keywords: low-mass companions; spectroscopic binaries; subdwarf B stars

Radial velocity variability and the evolution of hot subdwarf stars - Geier, S.; Dorsch, Matti; Pelisoli, I.; Reindl, N.; Heber, Ulrich; Irrgang, Andreas (Astronomy & Astrophysics, 2022)
Hot subdwarf stars represent a late and peculiar stage in the evolution of low-mass stars, since they are likely formed by close binary interactions. In this work, we perform a radial velocity (RV) variability study of a sample of 646 hot subdwarfs with multi-epoch radial velocities based on spectra from Sloan Digital Sky Survey (SDSS) and Large Sky Area Multi-Object Fibre Spectroscopic Telescope (LAMOST). The atmospheric parameters and RVs were taken from the literature. For stars with archival spectra but without literature values, we determined the parameters by fitting model atmospheres. In addition, we redetermined the atmospheric parameters and RVs for all the He-enriched sdO/Bs. This broad sample allowed us to study RV-variability as a function of the location in the T-eff - log g- and T-eff - log n(He)/n(H) diagrams in a statistically significant way. We used the fraction of RV-variable stars and the distribution of the maximum RV variations Delta RVmax as diagnostics. Both indicators turned out to be quite inhomogeneous across the studied parameter ranges. A striking feature is the completely dissimilar behaviour of He-poor and He-rich hot subdwarfs. While the former have a high fraction of close binaries, almost no significant RV variations could be detected for the latter. This has led us to the conclusion that there is likely no evolutionary connection between these subtypes. On the other hand, intermediate He-rich- and extreme He-rich sdOB/Os are more likely to be related. Furthermore, we conclude that the vast majority of this population is formed via one or several binary merger channels. Hot subdwarfs with temperatures cooler than similar to 24 000 K tend to show fewer and smaller RV-variations. These objects might constitute a new subpopulation of binaries with longer periods and late-type or compact companions. The RV-variability properties of the extreme horizontal branch (EHB) and corresponding post-EHB populations of the He-poor hot subdwarfs match and confirm the predicted evolutionary connection between them. Stars found below the canonical EHB at somewhat higher surface gravities show large RV variations and a high RV variability fraction. These properties are consistent with most of them being low-mass EHB stars or progenitors of low-mass helium white dwarfs in close binaries.
CRIS-Team WoS Importer:2022-06-03

Radial velocity variable, hot post-AGB stars from the MUCHFUSS project Classification, atmospheric parameters, formation scenarios - Reindl, N.; Geier, Stephan; Kupfer, Thomas; Bloemen, S.; Schaffenroth, Veronika; Heber, Ulrich; Barlow, Brad N.; Ostensen, R. H. (Astronomy & Astrophysics, 2016)
In the course of the MUCHFUSS project we recently discovered four radial velocity (RV) variable, hot (T-eff approximate to 80 000-110 000 K) post-asymptotic giant branch (AGB) stars. Among them, we found the first known RV variable O(He) star, the only second known RV variable PG1159 close binary candidate, as well as the first two naked (i.e., without planetary nebula (PN)) H-rich post-AGB stars of spectral type O(H) that show significant RV variations. We present a non-LTE spectral analysis of these stars along with one further O(H)-type star whose RV variations were found to be not significant. We also report the discovery of a far-infrared excess in the case of the PG1159 star. None of the stars in our sample displays nebular emission lines, which can be explained well in terms of a very late thermal pulse evolution in the case of the PG1159 star. The "missing" PNe around the O(H)-type stars seems strange, since we find that several central stars of PNe have much longer post-AGB times. Besides the non-ejection of a PN, the occurrence of a late thermal pulse, or the re-accretion of the PN in the previous post-AGB evolution offer possible explanations for those stars not harbouring a PN (anymore). In the case of the O(He) star J0757, we speculate that it might have been previously part of a compact He transferring binary system. In this scenario, the mass transfer must have stopped after a certain time, leaving behind a low-mass close companion that may be responsible for the extreme RV shift of 107.0 +/- 22.0 km s(-1) that was measured within only 31min.
Keywords: binaries: spectroscopic; stars: AGB and post-AGB; stars: evolution; stars: atmospheres

Radio and gamma-ray properties of extragalactic jets from the TANAMI sample - Boeck, M.; Kadler, Matthias; Müller, Cornelia; Tosti, G.; Ojha, R.; Wilms, Jörn; Bastieri, D.; Burnett, T.; Carpenter, B.; Cavazzuti, E.; Dutka, M.; Blanchard, J.; et al. (Astronomy & Astrophysics, 2016)
The TANAMI program has been observing parsec-scale radio jets of southern (declination south of - 30°) γ-ray bright AGN, simultaneously with Fermi/LAT monitoring of their γ-ray emission, via high-resolution radio imaging with Very Long Baseline Interferometry techniques. We present the radio and γ-rayproperties of the TANAMI sources based on one year of contemporaneous TANAMI and Fermi/LAT data. A large fraction (72%) of the TANAMI sample can be associated with bright γ-ray sources for this time range. Association rates differ for different optical classes with all BL Lacs, 76% of quasars, and just 17% of galaxies detected by the LAT. Upper limits were established on the γ-ray flux from TANAMI sources not detected by LAT. This analysis led to the identification of three new Fermi sources whose detection was later confirmed. The γ-ray and radio luminosities are related by L ∞ L . The brightness temperatures of the radio cores increase with the average γ-ray luminosity and the presence of brightness temperatures above the inverse Compton limit implies strong Doppler boosting in those sources. The undetected sources have lower γ/radio luminosity ratios and lower contemporaneous brightness temperatures. Unless the Fermi/LAT-undetected blazars are much γ-ray-fainter than the Fermi/LAT-detected sources, their γ-ray luminosity should not be significantly lower than the upper limits calculated here.
Keywords: Galaxies: active; Galaxies: jets; Galaxies: nuclei; Gamma rays: galaxies; Radio continuum: galaxies

Radio and X-ray observations of jet ejection in Cygnus X-2 - Spencer, R. E.; Rushton, A. P.; Balucinska-Church, M.; Paragi, Zsolt; Schulz, N. S.; Wilms, Jörn; Pooley, G. G.; Church, M. J. (Monthly Notices of the Royal Astronomical Society, 2013)
The ejection of a relativistic jet has been observed in the luminous Galactic low-mass X-ray binary Cygnus X-2. Using high-resolution radio observations, a directly resolved ejection event has been discovered while the source was on the horizontal branch of the Z-track. Contemporaneous radio and X-ray observations were made with the European VLBI Network at 6 cm and the Swift X-ray observatory in the 0.3-10 keV band. This has been difficult to achieve because of the previous inability to predict jet formation. Two sets of similar to 10 h observations were spaced 12 h apart, the jet apparently switching on during Day 1. The radio results show an unresolved core evolving into an extended jet. A preliminary value of jet velocity v/c of 0.33 +/- 0.12 was obtained, consistent with previous determinations in Galactic sources. Simultaneous radio and X-ray lightcurves are presented and the X-ray hardness ratio shows the source to be on the horizontal branch where jets are expected. The observations support our proposal that jet formation can in future be predicted based on X-ray intensity increases beyond a critical value.
Keywords: acceleration of particles; accretion: accretion discs; stars: neutron; X-rays: binaries; X-rays: individual: Cygnus X-2

Radio and X-ray study of SNRs in the Magellanic Clouds - Sasaki, Manami; et al. (1999)
We present our high-resolution radio-continuum and X-ray study of supernova remnants (SNRs) in the Magellanic Clouds (MCs). These investigations are based on Australia Telescope Compact Array (ATCA) radio-continuum and ROSAT X-ray observations. Our main aim is to study a complete sample of the MC SNRs and H II regions.

Radio continuum sources behind the Large Magellanic Cloud - Filipovic, M. D.; Bojicic, I. S.; Grieve, K. R.; Norris, R. P.; Tothill, N. F. H.; Shobhana, D.; Rudnick, L.; Prandoni, I.; Andernach, H.; Hurley-Walker, N.; Alsaberi, R. Z. E.; Anderson, C. S.; et al. (Monthly Notices of the Royal Astronomical Society, 2021)
We present a comprehensive multifrequency catalogue of radio sources behind the Large Magellanic Cloud (LMC) between 0.2 and 20 GHz, gathered from a combination of new and legacy radio continuum surveys. This catalogue covers an area of similar to 144 deg(2) at angular resolutions from 45 arcsec to similar to 3 arcmin. We find 6434 discrete radio sources in total, of which 3789 are detected at two or more radio frequencies. We estimate the median spectral index (alpha; where S-v similar to nu(alpha)) of alpha = -0.89 and mean of -0.88 +/- 0.48 for 3636 sources detected exclusively at two frequencies (0.843 and 1.384 GHz) with similar resolution [full width at half-maximum (FWHM) similar to 40-45 arcsec]. The large frequency range of the surveys makes it an effective tool to investigate Gigahertz Peak Spectrum (GPS), Compact Steep Spectrum (CSS), and Infrared Faint Radio Source (IFRS) populations within our sample. We find 10 GPS candidates with peak frequencies near 5 GHz, from which we estimate their linear size. 1866 sources from our catalogue are CSS candidates with alpha < -0.8. We found six candidates for High Frequency Peaker (HFP) sources, whose radio fluxes peak above 5 GHz and no sources with unconstrained peaks and alpha > 0.5. We found optical counterparts for 343 of the radio continuum sources, of which 128 have a redshift measurement. Finally, we investigate the population of 123 IFRSs found in this study.
CRIS-Team WoS Importer:2021-10-15

Radio emission from interstellar shocks: Young type Ia supernova remnants and the case of N 103B in the Large Magellanic Cloud - Alsaberi, R. Z.E.; Barnes, L. A.; Filipović, M. D.; Maxted, N. I.; Sano, H.; Rowell, G.; Bozzetto, L. M.; Gurovich, S.; Urošević, D.; Onić, D.; For, B. Q.; Manojlović, P.; et al. (Astrophysics and Space Science, 2019)
We investigate young type Ia supernova remnants (SNRs) in our Galaxy and neighbouring galaxies in order to understand their properties and early stage of their evolution. Here we present a radio continuum study based on new and archival data from the Australia Telescope Compact Array (ATCA) towards N 103B, a young (≤1000 yrs) spectroscopically confirmed type Ia SNR in the Large Magellanic Cloud (LMC) and proposed to have originated from a single degenerate (SD) progenitor. The radio morphology of this SNR is asymmetrical with two bright regions towards the north-west and south-west of the central location as defined by radio emission. N 103B identified features include: a radio spectral index of − 0.75 ± 0.01 (consistent with other young type Ia SNRs in the Galaxy); a bulk SNR expansion rate as in X-rays; morphology and polarised electrical field vector measurements where we note radial polarisation peak towards the north-west of the remnant at both 5500 and 9000 MHz. The spectrum is concave-up and the most likely reason is the non-linear diffusive shock acceleration (NLDSA) effects or presence of two different populations of ultra-relativistic electrons. We also note unpolarised clumps near the south-west region which is in agreement with this above scenario. We derive a typical magnetic field strength for N 103B of 16.4 μG for an average rotation measurement of 200radm−2. However, we estimate the equipartition field to be of the order of ∼235 μG with an estimated minimum energy of Emin=6.3×1048erg. The close (∼ 0.5 ∘) proximity of N 103B to the LMC mid-plane indicates that an early encounter with dense interstellar medium may have set an important constrain on SNR evolution. Finally, we compare features of N 103B to six other young type Ia SNRs in the LMC and Galaxy, with a range of proposed degeneracy scenarios to highlight potential differences due to a different models. We suggest that the single degenerate scenario might point to morphologically asymmetric type Ia supernova explosions.
CRIS-Team Scopus Importer:2019-11-29
Keywords: ISM: individual objects: N 103B; ISM: supernova remnants; Radio continuum: ISM; Supernovae: general

Rapid and multiband variability of the TeV bright active nucleus of the galaxy IC 310 - Aleksie, J.; Antonelli, L. A.; Antoranz, Pedro; Babic, Ana; De Almeida, U. Barres; Barrio, J. A.; Becerra Gonzalez, Josefa; Bednarek, Wlodek; Berger, K.; Bernardini, E.; Biland, A.; Blanch, O.; et al. (Astronomy & Astrophysics, 2014)
Context. The radio galaxy IC 310 has recently been identified as a gamma-ray emitter based on observations at GeV energies with Fermi-LAT and at very high energies (VHE, E > 100 GeV) with the MAGIC telescopes. Originally classified as a head-tail radio galaxy, the nature of this object is subject of controversy since its nucleus shows blazar-like behavior.Aims. To understand the nature of IC310 and the origin of the VHE emission, we studied the spectral and flux variability of IC 310 from the X-ray band to the VHE gamma-ray regime.Methods. The light curve of IC310 above 300GeV has been measured with the MAGIC telescopes from 2009 October to 2010 February. Contemporaneous Fermi-LAT data (2008-2011) in the 10-500 GeV energy range were also analyzed. In the X-ray regime, archival observations from 2003 to 2007 with XMM-Newton, Chandra, and Swift-XRT in the 0.5-10 keV band were studied.Results. The VHE light curve reveals several high-amplitude and short-duration flares. Day-to-day flux variability is clearly present (>5 sigma). The photon index between 120 GeV and 8 TeV remains at the value Gamma similar to 2.0 during both low and high flux states. The VHE spectral shape does not show significant variability, whereas the flux at 1 TeV changes by a factor of similar to 7. Fermi-LAT detected only eight gamma-ray events in the energy range 10 GeV-500 GeV in three years of observation. The measured photon index of Gamma = 1.3 +/- 0.5 in the Fermi-LAT range is very hard. The X-ray measurements show strong variability in both flux and photon index. The latter varied from 1.76 +/- 0.07 to 2.55 +/- 0.07.Conclusions. The rapid variability measured in gamma-rays and X-rays confirms the blazar-like behavior of IC310. The multi-TeV gamma-ray emission seems to originate from scales of less than 80 Schwarzschild radii (for a black hole mass of 2 x 10(8) M-circle dot) within the compact core of its FR I radio jet with orientation angle 10 degrees-38 degrees. The spectral energy distribution resembles that of an extreme blazar, albeit the luminosity is more than two orders of magnitude lower.
Keywords: galaxies: active; galaxies: individual: IC 310; gamma rays: galaxies; X-rays: galaxies

Rapid variability of Markarian 421 during extreme flaring as seen through the eyes of XMM-Newton - Gokus, A.; Wilms, Jörn; Kadler, M.; Dorner, D.; Nowak, M. A.; Kreikenbohm, A.; Leiter, K.; Bretz, T.; Schleicher, B.; Markowitz, A. G.; Pottschmidt, K.; Mannheim, K.; et al. (Monthly Notices of the Royal Astronomical Society, 2024)
By studying the variability of blazars across the electromagnetic spectrum, it is possible to resolve the underlying processes responsible for rapid flux increases, so-called flares. We report on an extremely bright X-ray flare in the high-peaked BL Lacertae object Markarian 421 (Mrk 421) that occurred simultaneously with enhanced γ-ray activity detected at very high energies by First G-APD Cherenkov Telescope on 2019 June 9. We triggered an observation with XMM-Newton, which observed the source quasi-continuously for 25 h. We find that the source was in the brightest state ever observed using XMM-Newton, reaching a flux of 2.8 × 10-9 over an energy range of 0.3-10 keV. We perform a spectral and timing analysis to reveal the mechanisms of particle acceleration and to search for the shortest source-intrinsic time-scales. Mrk 421 exhibits the typical harder-when-brighter behaviour throughout the observation and shows a clock-wise hysteresis pattern, which indicates that the cooling dominates over the acceleration process. While the X-ray emission in different sub-bands is highly correlated, we can exclude large time lags as the computed z-transformed discrete correlation functions are consistent with a zero lag. We find rapid variability on time-scales of 1 ks for the 0.3-10 keV band and down to 300 s in the hard X-ray band (4-10 keV). Taking these time-scales into account, we discuss different models to explain the observed X-ray flare, and find that a plasmoid-dominated magnetic reconnection process is able to describe our observation best.
CRIS-Team Scopus Importer:2024-03-29
Keywords: acceleration of particles; BL Lacertae objects: individual: Markarian 421; galaxies: active; relativistic processes; X-rays: galaxies

Ray-tracing Arcus in Phase A - Günther, Hans Moritz; DeRoo, Casey; Heilmann, Ralf K.; Hertz, Edward N.; Smith, Randall; Wilms, Jörn (2018)
Spectroscopy of soft X-rays is an extremely powerful tool to understand the physics of hot plasmas in the universe, but in many cases, such as kinematic properties of stellar emission lines or weak absorption features, we have reached the limits of current instrumentation. Critical-angle transmission (CAT) gratings blaze the dispersed spectra into high orders and also offer high throughput.We present detailed ray-traces for the Arcus mission, which promises an effective area > 300 cm(2) in the soft X-ray band. It uses four petals of Athena-like silicon pore optics. Each petal spans an azimuth of about 30 degrees and thus offers a point-spread function that is significantly narrower in one dimension than a full mirror would provide. Each of these channels has its own optical axis. For each channel, CAT gratings are arranged on a tilted Rowland torus, and the four separate tori are positioned to overlap in such a way that the dispersed spectra from both pairs can be imaged onto a common set of CCD detectors, while at the same time keeping the requirement of the spectroscopic focus.Our ray-traces show that a set of 16 CCDs is sufficient to cover both zeroth orders and most of the dispersed signal. We study the impact of misalignment, finite size of components, and spacecraft jitter on the spectral resolution and effective area and prove that the design achieves R > 3000 even in the presence of these non-ideal effects.In 2017, we presented the ray-traces for the initial Arcus proposal. Since then, Arcus was accepted for a phase A study and we have spent a lot of additional effort to tweak the optical design (for example, we originally intended to have two petals each share an optical axis, but decided against it to avoid alignment constraints) and to link it back to practical mechanical engineering tolerances. In the process, parameters that were only roughly known in the initial proposal have been set to much better than a millimeter, and effects that seemed not important initially have now been studied in much more detail. This contribution presents those detailed studies and tells the story how we used ray-traces to make a better instrument with a more robust design.
Keywords: ray-tracing; X-ray optics; critical angle transmission grating; ARCUS; Rowland design

Re-awakening of GRS 1716-249 after 23 yr, observed by Swift/XRT and NuSTAR - Bharali, Priya; Chandra, Sunil; Chauhan, Jaiverdhan; Garcia, Javier; Roy, Jayashree; Boettcher, Markus; Boruah, Kalyanee (Monthly Notices of the Royal Astronomical Society, 2019)
In this work, we present a spectral and temporal analysis of Swift/XRT and NuSTAR observations of GRS 1716-249 during its recent 2016-2017 outburst. This low-mass X-ray binary underwent an extraordinary outburst after a long quiescence of 23 yr, since its last major outburst in 1993. The source was observed over two different epochs during 2017 April 7 and 10. The best-fitting joint spectral fitting in the energy range 0.5-79.0 keV indicates that the spectrum is best described by relatively cold, weak disc blackbody emission, dominant thermal Comptonization emission, and a relativistically broadened fluorescent iron K alpha emission line. We observed a clear indication of a Compton hump around 30 keV, We also detected an excess feature of 1.3 keV. Assuming a lamp-post geometry of the corona, we constrained the inner disc radius for both observations to 11.92(-11.92)(+8.62) R-ISCO (i.e. an upper limit) and 10.39(-3.02)(+9.51) R-ISCO (where R-ISCO = radius of the innermost stable circular orbit) for the first epoch (El) and second epoch (E2), respectively. A significant (5 sigma) type C quasi-periodic oscillation (QPO) at 1.20 +/- 0.04 Hz is detected for the first time for GRS 1716-249, which drifts to 1.55 +/- 0.04 Hz (6 sigma) at the end of the second observation. The derived spectral and temporal properties show a positive correlation between the QPO frequency and the photon index.
CRIS-Team WoS Importer:2019-08-16

Redshifted Fe K alpha line from the unusual gamma-ray source PMN J1603-4904 - Mueller, C.; Krauss, F.; Dauser, Thomas; Kreikenbohm, A.; Beuchert, T.; Kadler, M.; Ojha, R.; Wilms, Jörn; Boeck, M.; Carpenter, B.; Dutka, M.; Markowitz, Alex; et al. (Astronomy & Astrophysics, 2015)
Conclusions. The detection of a redshiftecl X-ray emission line further challenges the original BL Lac classification of PMN J1603-4904. This result suggests that the source is observed at a larger angle to the line of sight than expected for blazars. and thus the source would add to the elusive class of gamma-ray loud misaligned jet objects, possibly a gamma-ray bright young radio galaxy.
Keywords: galaxies: active; galaxies: jets; galaxies: individual: PMN J1603-4904; X-rays: galaxies; gamma rays: galaxies

Reflection Modeling of the Black Hole Binary 4U 1630-47: The Disk Density and Returning Radiation - Connors, Riley M. T.; Garcia, Javier A.; Tomsick, John; Hare, Jeremy; Dauser, Thomas; Grinberg, Victoria; Steiner, James F.; Mastroserio, Guglielmo; Sridhar, Navin; Fabian, Andrew C.; Jiang, Jiachen; Parker, Michael L.; et al. (Astrophysical Journal, 2021)
We present the analysis of X-ray observations of the black hole binary 4U 1630-47 using relativistic reflection spectroscopy. We use archival data from the Rossi X-ray Timing Explorer, Neil Gehrels Swift Observatory, and Nuclear Spectroscopic Telescope Array observatories, taken during different outbursts of the source between 1998 and 2015. Our modeling includes two relatively new advances in modern reflection codes: high-density disks, and returning thermal disk radiation. Accretion disks around stellar-mass black holes are expected to have densities well above the standard value assumed in traditional reflection models (i.e., n e ∼ 1015 cm-3). New high-density reflection models have important implications in the determination of disk truncation (i.e., the disk inner radius). This is because one must retain self-consistency in the irradiating flux and corresponding disk ionization state, which is a function of disk density and system geometry. We find that the disk density is n e ≥ 1020 cm-3 across all spectral states. This density, combined with our constraints on the ionization state of the material, implies an irradiating flux impinging on the disk that is consistent with the expected theoretical estimates. Returning thermal disk radiation - the fraction of disk photons that bend back to the disk producing additional reflection components - is expected predominantly in the soft state. We show that returning radiation models indeed provide a better fit to the soft-state data, reinforcing previous results that show that in the soft state, the irradiating continuum may be blackbody emission from the disk itself.
CRIS-Team Scopus Importer:2021-04-09

Reflection Spectroscopy of the Black Hole Binary XTE J1752-223 in Its Long-stable Hard State - Garcia, Javier A.; Steiner, James F.; Grinberg, Victoria; Dauser, Thomas; Connors, Riley M. T.; Mcclintock, Jeffrey E.; Remillard, Ronald A.; Wilms, Jörn; Harrison, Fiona A.; Tomsick, John A. (Astrophysical Journal, 2018)
We present a detailed spectral analysis of the black hole binary XTE J1752-223. in the hard state of its 2009 outburst. Regular monitoring of this source by the Rossi X-ray Timing Explorer mission provided high signal-to-noise spectra along the outburst rise and decay. During one full month this source stalled at similar to 30% of its peak count rate at a constant hardness and intensity. By combining all the data in this exceptionally stable hard state, we obtained an aggregate proportional counter array spectrum (3-45 keV) with 100. million counts, and a corresponding high energy X-ray timing experiment spectrum (20-140 keV) with 5.8. million counts. Implementing a version of our reflection code with a physical model for Comptonization, we obtain tight constraints on important physical parameters for this system. In particular, the inner accretion disk is measured very close in, at R-in =1.7 +/- 0.4 R-g. Assuming R-in = R-ISCO, we find a relatively high black hole spin (a* = 0.92 +/- 0.06). Imposing a lamppost geometry, we obtain a low inclination (i = 35 degrees +/- 4 degrees), which agrees with the upper limit found in the radio (i < 49 degrees). However, we note that this model cannot be statistically distinguished from a non-lamppost model with a free emissivity index, for which the inclination is markedly higher. Additionally, we find a relatively cool corona (57-70 keV) and large iron abundance (3.3-3.7 solar). We further find that properly accounting for Comptonization of the reflection emission improves the fit significantly and causes an otherwise low reflection fraction (similar to 0.2-0.3) to increase by an order of magnitude, in line with geometrical expectations for a lamppost corona. We compare these results with similar investigations reported for GX 339-4. in its bright hard state.
Keywords: accretion; accretion disks; atomic processes; black hole physics; line: formation; X-rays: individual (XTE J1752-223)

Relativistic Reflection and Reverberation in GX 339-4 with NICER and NuSTAR - Wang, Jingyi; Kara, Erin; Steiner, James F.; Garcia, Javier; Homan, Jeroen; Neilsen, Joseph; Marcel, Gregoire; Ludlam, Renee M.; Tombesi, Francesco; Cackett, Edward M.; Remillard, Ron A. (Astrophysical Journal, 2020)
We analyze seven Neutron Star Interior Composition Interior Explorer (NICER) and Nuclear Spectroscopic Telescope Array epochs of the black hole X-ray binary GX 339-4 in the hard state during its two most recent hard-only outbursts in 2017 and 2019. These observations cover the 1-100 keV unabsorbed luminosities between 0.3% and 2.1% of the Eddington limit. With NICER's negligible pileup, high count rate, and unprecedented time resolution, we perform a spectral-timing analysis and spectral modeling using relativistic and distant reflection models. Our spectral fitting shows that as the inner disk radius moves inward, the thermal disk emission increases in flux and temperature, the disk becomes more highly ionized, and the reflection fraction increases. This coincides with the inner disk increasing its radiative efficiency around ∼1% Eddington. We see a hint of the hysteresis effect at ∼0.3% of Eddington; the inner radius is significantly truncated during the rise (>49R g ), while only a mild truncation (∼5R g ) is found during the decay. At higher frequencies (2-7 Hz) in the highest-luminosity epoch, a soft lag is present whose energy dependence reveals a thermal reverberation lag with an amplitude similar to previous findings for this source. We also discuss the plausibility of the hysteresis effect and the debate of the disk truncation problem in the hard state.
CRIS-Team Scopus Importer:2020-09-11

Relativistic reflection: Review and recent developments in modeling - Dauser, Thomas; Garcia, Javier; Wilms, Jörn (Astronomische Nachrichten, 2016)
Measuring relativistic reflection is an important tool to study the innermost regions of the an accreting black hole system. In the following we present a brief review on the different aspects contributing to the relativistic reflection. The combined approach is for the first time incorporated in the new "relxill" model. The advantages of this more self-consistent approach are briefly summarized. A special focus is put on the new definition of the intrinsic reflection fraction in the lamp post geometry, which allows to draw conclusions about the primary source of radiation in these system. Additionally the influence of the high energy cutoff of the primary source on the reflection spectrum is motivated, revealing the remarkable capabilities of constraining E by measuring relativistic reflection spectra from NuSTAR, preferably with lower energy coverage.
Keywords: Accretion; accretion disks; Black hole physics; Line: profiles; X-rays: galaxies

Relativistic X-Ray Reflection Models for Accreting Neutron Stars - Garcia, Javier A.; Dauser, Thomas; Ludlam, Renee; Parker, Michael; Fabian, Andrew; Harrison, Fiona A.; Wilms, Jörn (Astrophysical Journal, 2022)
We present new reflection models specifically tailored to model the X-ray radiation reprocessed in accretion disks around neutron stars, in which the primary continuum is characterized by a single-temperature blackbody spectrum, emitted either at the surface of the star or at the boundary layer. These models differ significantly from those with a standard power-law continuum, typically observed in most accreting black holes. We show comparisons with earlier reflection models and test their performance in the NuSTAR observation of the neutron star 4U 1705-44. Simulations of upcoming missions such as XRISM-Resolve and Athena X-IFU are shown to highlight the diagnostic potential of these models for high-resolution X-ray reflection spectroscopy. These new reflection models xillverNS, and their relativistic counterpart relxillNS, are made publicly available to the community as an additional flavor in the relxill suite of reflection models.
CRIS-Team WoS Importer:2022-02-18

Resolving the Crab pulsar wind nebula at teraelectronvolt energies - Abdalla, H.; Aharonian, F.; Ait Benkhali, F.; Angüner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Backes, M.; Barnard, M.; Becherini, Y.; Becker Tjus, J.; Berge, D.; et al. (Nature Astronomy, 2019)
The Crab nebula is one of the most-studied cosmic particle accelerators, shining brightly across the entire electromagnetic spectrum up to very-high-energy gamma rays1,2. It is known from observations in the radio to gamma-ray part of the spectrum that the nebula is powered by a pulsar, which converts most of its rotational energy losses into a highly relativistic outflow. This outflow powers a pulsar wind nebula, a region of up to ten light-years across, filled with relativistic electrons and positrons. These particles emit synchrotron photons in the ambient magnetic field and produce very-high-energy gamma rays by Compton up-scattering of ambient low-energy photons. Although the synchrotron morphology of the nebula is well established, it has not been known from which region the very-high-energy gamma rays are emitted3–8. Here we report that the Crab nebula has an angular extension at gamma-ray energies of 52 arcseconds (assuming a Gaussian source width), much larger than at X-ray energies. This result closes a gap in the multi-wavelength coverage of the nebula, revealing the emission region of the highest-energy gamma rays. These gamma rays enable us to probe a previously inaccessible electron and positron energy range. We find that simulations of the electromagnetic emission reproduce our measurement, providing a non-trivial test of our understanding of particle acceleration in the Crab nebula.
CRIS-Team Scopus Importer:2019-11-15

Results from DROXO: IV. EXTraS discovery of an X-ray flare from the Class i protostar candidate ISO-Oph 85 - Pizzocaro, D.; Stelzer, B.; Paladini, R.; Tiengo, A.; Lisini, G.; Novara, G.; Vianello, G.; Belfiore, A.; Marelli, M.; Salvetti, D.; Pillitteri, Ignazio; Sciortino, S.; et al. (Astronomy & Astrophysics, 2016)
X-ray emission from young stellar objects (YSOs) is a key ingredient in understanding star formation. For the early, protostellar (Class I) phase, a very limited (and controversial) quantity of X-ray results is available to date. Within the EXTraS (Exploring the X-ray Transient and variable Sky) project, we have discovered transient X-ray emission from a source whose counterpart is ISO-Oph 85, a strongly embedded YSO in the ρ Ophiuchi star-forming region. We extract an X-ray light curve for the flaring state, and determine the spectral parameters for the flare from XMM-Newton/EPIC data with a method based upon quantile analysis. We combine photometry from infrared to millimeter wavelengths from the literature with mid-IR Spitzer and unpublished submm Herschel photometry that we analysed for this work, and we describe the resulting spectral energy distribution (SED) with a set of precomputed models. The X-ray flare of ISO-Oph 85 lasted 2500 s and is consistent with a highly-absorbed one-component thermal model (N = 1.0 × 10 cm NH=1.0-0.5+1.2×1023cm-2 and kT= 1.15 keVkT=1.15-0.65+2.35 keV). The X-ray luminosity during the flare is log L [erg/s] = 31.1logLX [erg/s]=31.1-1.2+2.0; during quiescence we set an upper limit of log L [erg/s] < 29.5. We do not detect other flares from this source. The submillimeter fluxes suggest that the object is a Class I protostar. We caution, however, that the offset between the Herschel and optical/infrared position is larger than that for other YSOs in the region, leaving some doubt on this association. To the best of our knowledge, this is the first X-ray flare from a YSO that has been recognised as a candidate Class I protostar via the analysis of its complete SED, including the submm bands that are crucial for detecting the protostellar envelope. This work shows how the analysis of the whole SED is fundamental to the classification of YSOs, and how the X-ray source detection techniques we have developed can open a new era in time-resolved analysis of the X-ray emission from stars.
Keywords: Stars: activity; Stars: coronae; Stars: flare; Stars: protostars; X-rays: stars

Results from the search for dark matter in the Milky Way with 9 years of data of the ANTARES neutrino telescope - Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Ardid, Miguel; Aubert, J. J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; et al. (Physics Letters B, 2017)
Using data recorded with the ANTARES telescope from 2007 to 2015, a new search for dark matter annihilation in the Milky Way has been performed. Three halo models and five annihilation channels, WIMP + WIMP -> b (b) over bar, W+W-, tau(+)tau(-), mu(+)mu(-) and v (v) over bar, with WIMP masses ranging from 50 2 GeV/C-2 to 100 Tev/C-2, were considered. No excess over the expected background was found, and limits on the thermally averaged annihilation cross-section were set. (C) 2017 The Authors. Published by Elsevier B.V. This is an open access article under the CC BY license.
Keywords: Dark matter; WIMP; Indirect detection; Neutrino telescope; Galactic Centre; ANTARES

Returning radiation in strong gravity around black holes: Reverberation from the accretion disc - Wilkins, D. R.; Garcia, J. A.; Dauser, Thomas; Fabian, A. C. (Monthly Notices of the Royal Astronomical Society, 2020)
We study reflected X-ray emission that returns to the accretion disc in the strong gravitational fields around black holes using General Relativistic ray-tracing and radiative transfer calculations. Reflected X-rays that are produced when the inner regions of the disc are illuminated by the corona are subject to strong gravitational light bending, causing up to 47 per cent of the reflected emission to be returned to the disc around a rapidly spinning black hole, depending upon the scale height of the corona. The iron Kα line is enhanced relative to the continuum by 25 per cent, and the Compton hump by up to a factor of 3. Additional light traveltime between primary and secondary reflections increases the reverberation time lag measured in the iron K band by 49 per cent, while the soft X-ray lag is increased by 25 per cent and the Compton hump response time is increased by 60 per cent. Measured samples of X-ray reverberation lags are shown to be consistent with X-rays returning to the accretion disc in strong gravity. Understanding the effects of returning radiation is important in interpreting reverberation observations to probe black holes. Reflected X-rays returning to the disc can be uniquely identified by blueshifted returning iron K line photons that are Compton scattered from the inner disc, producing excess, delayed emission in the 3.5-4.5 keV energy range that will be detectable with forthcoming X-ray observatories, representing a unique test of General Relativity in the strong field limit.
CRIS-Team Scopus Importer:2021-04-19
Keywords: accretion; accretion discs; black hole physics; galaxies: active; relativistic processes; X-rays: binaries; X-rays: galaxies

Revealing the broad iron Kα line in Cygnus X-1 through simultaneous XMM-Newton, RXTE, and INTEGRAL observations - Duro, Refiz; Dauser, Thomas; Grinberg, Victoria; Miskovicova, Ivica; Rodriguez, Jerome; Tomsick, John; Hanke, Manfred; Pottschmidt, Katja; Nowak, Michael A.; Kreykenbohm, Sonja Sophie; Bel, Marion Cadolle; Bodaghee, Arash; et al. (Astronomy & Astrophysics, 2016)
We report on the analysis of the broad Fe Kα line feature of Cyg X-1 in the spectra of four simultaneous hard intermediate state observations made with the X-ray Multiple Mirror mission (XMM-Newton), the Rossi X-ray Timing Explorer (RXTE), and the International Gamma-Ray Astrophysics Laboratory (INTEGRAL). The high quality of the XMM-Newton data taken in the Modified Timing Mode of the EPIC-pn camera provides a great opportunity to investigate the broadened Fe Kα reflection line at 6.4 keV with a very high signal to noise ratio. The 4-500 keV energy range is used to constrain the underlying continuum and the reflection at higher energies. We first investigate the data by applying a phenomenological model that consists of the sum of an exponentially cutoff power law and relativistically smeared reflection. Additionally, we apply a more physical approach and model the irradiation of the accretion disk directly from the lamp post geometry. All four observations show consistent values for the black hole parameters with a spin of a 0.9, in agreement with recent measurements from reflection and disk continuum fitting. The inclination is found to be i 30°, consistent with the orbital inclination and different from inclination measurements made during the soft state, which show a higher inclination. We speculate that the difference between the inclination measurements is due to changes in the inner region of the accretion disk.
Keywords: black hole physics; gravitation; X-rays: binaries

Revealing the supernova remnant population of M33 with Chandra - Sasaki, Manami; et al. (Astronomical Journal, 2005)
We present results of a search for supernova remnants (SNRs) in archival Chandra images of M33. We have identified X-ray SNRs by comparing the list of Chandra X-ray sources in M33 with tabulations of SNR candidates identified from ( 1) elevated [S II]/H alpha ratios in the optical and ( 2) radio spectral indices. In addition, we have searched for optical counterparts to soft sources in the Chandra images and X-ray SNR candidates identified in the XMM-Newton survey of M33. Of the 98 optically known SNRs in M33, 22 have been detected at > 3 sigma level in the soft band (0.35 - 1.1 keV). At least four of these SNR candidates are spatially extended based on a comparison of the data to simulated images of point sources. Aside from the optically matching SNRs, we have found one soft X-ray source in M33 that exhibits no optical emission and is coincident with a known radio source. The radio spectral index of this source is consistent with particle acceleration in shocks, leading us to suggest that it is a nonradiative SNR. We have also found new optical counterparts to two soft X-ray SNRs in M33. These counterparts exhibit enhanced [S II]/H alpha ratios characteristic of radiative shocks. Pending confirmation from optical spectroscopy, the identification of these two optical counterparts increases the total number of known optically emitting SNRs in M33 to 100. This brings the total number of identified SNRs with X-ray counterparts, including those exclusively detected by the XMM-Newton survey of M33, to 37 SNRs. We find that while there are a similar number of confirmed X-ray SNRs in M33 and the LMC with X-ray luminosities in excess of 10(35) ergs s(-1), nearly 40% of the LMC SNRs are brighter than 10(36) ergs s(-1), while only 13% of the M33 sample exceed this luminosity. Including X-ray SNR candidates from the XMM-Newton survey ( objects lacking optical counterparts) increases the fraction of M33 SNRs brighter than 10(36) ergs s(-1) to 22%, still only half the LMC fraction. The differences in luminosity distributions cannot be fully explained by uncertainty in spectral model parameters and are not fully accounted for by abundance differences between the galaxies.
Keywords: galaxies : individual (M33); galaxies : ISM; shock waves; supernova remnants

Revealing x-ray and gamma ray temporal and spectral similarities in the GRB 190829A afterglow - Taylor, Andrew M.; Aharonian, Felix; Romoli, Carlo; Khangulyan, Dmitry; Ruiz-Velasco, Edna; Schüssler, Fabian; Zhu, Sylvia J.; Büchele, Matthias; Eichhorn, Florian; Funk, Stefan; Glawion, Dorit; Jankowsky, David; et al. (Science, 2021)
Gamma-ray bursts (GRBs), which are bright flashes of gamma rays from extragalactic sources followed by fading afterglow emission, are associated with stellar core collapse events. We report the detection of very-high-energy (VHE) gamma rays from the afterglow of GRB 190829A, between 4 and 56 hours after the trigger, using the High Energy Stereoscopic System (H.E.S.S.). The low luminosity and redshift of GRB 190829A reduce both internal and external absorption, allowing determination of its intrinsic energy spectrum. Between energies of 0.18 and 3.3 tera-electron volts, this spectrum is described by a power law with photon index of 2.07 ± 0.09, similar to the x-ray spectrum. The x-ray and VHE gamma-ray light curves also show similar decay profiles. These similar characteristics in the x-ray and gamma-ray bands challenge GRB afterglow emission scenarios.
CRIS-Team Scopus Importer:2021-06-18

ROSAT HRI catalogue of X-ray sources in the LMC region - Sasaki, Manami; Haberl, Frank; Pietsch, Wolfgang (Astronomy and Astrophysics Supplement Series, 2000)
All 543 pointed observations of the ROSAT High Resolution Imager (HRI) with exposure times higher than 50 s and performed between 1990 and 1998 in a field of 10 degrees x 10 degrees covering the Large Magellanic Cloud (LMC) were analyzed. A catalogue was produced containing 397 X-ray sources with their properties measured by the HRI. The list was cross-correlated with the ROSAT Position Sensitive Propotional Counter (PSPC) source catalogue presented by Haberl & Pietsch (1999) in order to obtain the hardness ratios for the X-ray sources detected by both instruments. 138 HRI sources are contained in the PSPC catalogue, 259 sources are new detections. The spatial resolution of the HRI was higher than that of the PSPC and the source position could be determined with errors mostly smaller than 15 " which are dominated by systematic attitude errors. After cross-correlating the source catalogue with the SIMBAD data base and the TYCHO catalogue 94 HRI sources were identified with known objects based on their positional coincidence and X-ray properties. Whenever more accurate coordinates were given in catalogues or literature for identified sources, the X-ray coordinates were corrected and the systematic error of the X-ray position was reduced. For other sources observed simultaneously with an identified source the coordinates were improved as well. In total the X-ray position of 254 sources could be newly determined. The catalogue contains 39 foreground stars, 24 supernova remnants (SNRs), five supersoft sources (SSSs), nine X-ray binaries (XBs), and nine AGN well known from literature. Another eight sources were identified with known candidates for these source classes. Additional 21 HRI sources are suggested in the present work as candidates for SNR, X-ray binary in the LMC, or background AGN because of their extent, hardness ratios, Y-ray to optical flux ratio, or flux variability.
Keywords: catalogues; galaxies : Magellanic Clouds; galaxies : stellar content; X-rays : galaxies; X-rays : stars

ROSAT HRI catalogue of X-ray sources in the SMC region - Sasaki, Manami; Haberl, Frank; Pietsch, Wolfgang (Astronomy and Astrophysics Supplement Series, 2000)
During the operational phase of the ROSAT satellite between 1990 and 1998 the X-ray telescope pointed 71 times to the Small Magellanic Cloud (SMC) for observations with the High Resolution Imager (HRI), covering a field of 5 degrees x 5 degrees. From these data a catalogue of 121 discrete X-ray sources was derived. By cross-correlating the source catalogue with the SIMBAD data base and the TYCHO catalogue, the systematic positional error of the HRI source positions could be reduced. In total the X-ray position for 99 HRI sources was corrected yielding positional errors between 1 " and 16 ". The HRI catalogue was also cross-correlated with the catalogues derived from the ROSAT Position Sensitive Propotional Counter (PSPC) pointings (Kahabka et al. 1999; Haberl et al. 2000). For 75 HRI sources PSPC counterparts were found and thus hardness ratios are given. With the help of the information obtained from the cross-correlations 56 HRI sources were identified with objects of known or proposed nature. Four foreground stars, six supernova remnants, four supersoft sources, 12 X-ray binaries, and one AGN were detected by the HRI. Based on the existence of a likely optical counterpart or properties like hardness ratio and X-ray to optical flux ratio, further 15 HRI sources were classified into different source types.
Keywords: catalogs; galaxies : magellanic clouds; galaxies : stellar content; X-rays : galaxies; X-rays : stars

ROSAT PSPC view of the hot interstellar medium of the Magellanic Clouds - Sasaki, Manami; Haberl, Frank; Pietsch, Wolfgang (Astronomy & Astrophysics, 2002)
Diffuse X-ray emission from the Magellanic Clouds (MCs) is studied by using all the archival data of pointed ROSAT Position Sensitive Proportional Counter (PSPC) observations. For this purpose, contributions from the point and point-like sources in the ROSAT High Resolution Imager (HRI) and PSPC source catalogues are eliminated and periods of high solar activity are excluded. The spectral analysis yielded characteristic temperatures of 10(6)-10(7) K for the hot thin plasma of the ISM which extends over the whole Large Magellanic Cloud (LMC) and the Small Magellanic Cloud (SMC). The total unabsorbed luminosity in the 0.1-2.4 keV band within the observed area amounts to 3.2 x 10(38) erg s(-1) in the LMC and 1.1 x 10(37) erg s(-1) in the SMC, each with an uncertainty of similar to -40%, +100%. The X-ray luminosity of the LMC is comparable to that of other nearby galaxies with pronounced star formation. In the LMC, hot regions were found especially around the supergiant shell (SGS) LMC4 and in the field covering SGS LMC2 and LMC3. Highest temperatures for the SMC were derived in the southwestern part of the galaxy. The diffuse X-ray emission is most likely a superposition of the emission from the hot gas in the interior of shells and supershells as well as from the halo of these galaxies.
Keywords: shock waves; ISM : supernova remnants; galaxies : magellanic clouds; X-rays : ISM

Runaway blue main-sequence stars at high Galactic latitudes: Target selection with Gaia and spectroscopic identification - Raddi, Roberto; Irrgang, Andreas; Heber, Ulrich; Schneider, David; Kreuzer, Simon (Astronomy & Astrophysics, 2021)
Context. The ESA Gaia mission is a remarkable tool for stellar population analysis through its accurate Hertzsprung-Russell diagram. Its precise astrometry has propelled detailed kinematic studies of the Milky Way and the identification of high-velocity outliers. Aims. Motivated by the historical identification of runaway main-sequence (MS) stars of an early spectral type at high Galactic latitudes, we test the capability of Gaia at identifying new such stars. Methods. We selected ≃2300 sources with Gaia magnitudes of GBP-GRP ≤ 0.05, which are compatible with the colors of lowextinction MS stars that are earlier than a mid-A spectral type, and obtained low-resolution optical spectroscopy for 48 such stars. By performing detailed photometric and spectroscopic analyses, we derived their atmospheric and physical parameters (effective temperature, surface gravity, radial velocity, interstellar reddening, spectrophotometric distance, mass, radius, luminosity, and age). The comparison between spectrophotometric and parallax-based distances enabled us to disentangle the MS candidates from older blue horizontal branch (BHB) candidates. Results.We identify 12 runaway MS candidates, with masses between 2 and 6 M⊙. Their trajectories were traced back to the Galactic disk in order to identify their most recent Galactic plane crossings and the corresponding flight times. All 12 candidates are ejected from the Galactic disk within 2 to 16.5 kpc from the Galactic center and possess flight times that are shorter than their evolutionary ages, which is compatible with a runaway hypothesis. Three MS candidates have ejection velocities exceeding 450 km s-1, thus, they appear to challenge the canonical ejection scenarios for late B-type stars. The fastest star of our sample also has a non-negligible Galactic escape probability if its MS nature can be confirmed.We identify 27 BHB candidates, and the two hottest stars in our sample are rare low-mass stars of late O- A nd early B-types, evolving towards the white dwarf cooling sequence. Conclusions. The combination of Gaia parallaxes and proper motions can lead to the efficient selection of runaway blue MS candidates up to 10 kpc away from the Sun. High resolution spectra are needed to confirm the MS status, via precise measurements of projected rotational velocities and chemical compositions.
CRIS-Team Scopus Importer:2021-04-09
Keywords: Stars: Early-type; Stars: Fundamental parameters; Stars: Horizontal-branch; Stars: Kinematics and dynamics

RX J0529.8-6556: A BeXRB pulsar with an evolving optical period and out of phase X-ray outbursts - Treiber, Helena; Vasilopoulos, Georgios; Bailyn, C. D.; Haberl, F.; Gendreau, K. C.; Ray, P. S.; Maitra, Chandreyee; Maggi, Pierre; Jaisawal, G. K.; Udalski, Andrzej; Wilms, Jörn; Monageng, I. M.; et al. (Monthly Notices of the Royal Astronomical Society, 2021)
We report the results of eROSITA and NICER observations of the 2020 June outburst of the Be/X-ray binary pulsar RX J0529.8-6556 in the Large Magellanic Cloud, along with the analysis of archival X-ray and optical data from this source. We find two anomalous features in the system's behaviour. First, the pulse profile observed by NICER during maximum luminosity is similar to that observed by XMM-Newton in 2000, despite the fact that the X-ray luminosity was different by two orders of magnitude. In contrast, a modest decrease in luminosity in the 2020 observations generated a significant change in pulse profile. Secondly, we find that the historical optical outbursts are not strictly periodic, as would be expected if the outbursts were triggered by periastron passage, as is generally assumed. The optical peaks are also not coincident with the X-ray outbursts. We suggest that this behaviour may result from a misalignment of the Be star disc and the orbital plane, which might cause changes in the timing of the passage of the neutron star through the disc as it precesses. We conclude that the orbital period of the source remains unclear.
CRIS-Team Scopus Importer:2021-12-24
Keywords: Magellanic Clouds; pulsars: individual: RX J0209.6-7427; stars: neutron; X-rays: binaries

RXTE observations of the 1A 1118-61 in an outburst, and the discovery of a cyclotron line - Doroshenko, Victor; Suchy, S.; Santangelo, A.; Staubert, R.; Kreykenbohm, Ingo; Rothschild, R.; Pottschmidt, K.; Wilms, Jörn (Astronomy & Astrophysics, 2010)
We present the analysis of RXTE monitoring data obtained during the 2009 January outburst of the hard X-ray transient 1A 1118-61. Using these observations the broadband (3.5-120 keV) spectrum of the source was measured for the first time ever. We have found that the broadband continuum spectrum of the source is similar to other accreting pulsars and is well described by several conventionally used phenomenological models. We have discovered that regardless of the applied continuum model, a prominent broad absorption feature at similar to 55 keV is observed. We interpret this feature as a cyclotron resonance scattering feature (CRSF). The observed CRSF energy is one of the highest known and corresponds to a magnetic field of B similar to 4.8 x 10(12) G in the scattering region. Our data also indicate the presence of an iron emission line presence that has not been previously reported for 1A 1118-61. Timing properties of the source, including a strong spin-up, were found to be similar to those observed by CGRO/BATSE during the previous outburst, but the broadband capabilities of RXTE reveal a more complicated energy dependency of the pulse-profile.
Keywords: stars: neutron; pulsars: individual: 1A 1118-61; binaries: general

S 308 and other X-ray emitting bubbles around Wolf-Rayet stars - Camilloni, Francesco; Becker, Werner; Sasaki, Manami (Astronomy & Astrophysics, 2024)
Context. S 308 is an X-ray emitting bubble that surrounds the Wolf-Rayet star WR6. The structure shines in the optical as well and is thus known as the Dolphin Nebula. Due to its large angular extent, it has been covered at only 90% with past XMM-Newton observations. Aims. Thanks to the unique dataset provided by the all-sky survey performed in X-rays by SRG/eROSITA, we can show for the first time the image of the bubble in its entire extent in this band, together with its spectral characterization. Moreover, we have tried to apply the same procedure for other wind-blown bubbles detected in the optical/IR and we searched for X-ray extended emission around them. Methods. We first analyzed the diffuse emission of S308, providing a detailed spectral analysis. We then considered a sample of 22 optical/IR selected wind-blown bubbles from a previous study based on WISE data, providing an estimate of the X-ray flux for the first time. Results. We obtained the best fit for S308 with a two-temperature non-equilibrium plasma model (kT1 = 0.8-0.3+0.8 keV and kT2 = 2-1+3 keV) showing super-solar N abundance and low absorption. We did not detect any of the 22 optical/IR emitting bubbles in X-rays, but using our best fit model, we estimated the 3σ flux upper limits for each bubble. Conclusions. We demonstrate the new possibility offered by SRG/eROSITA to study known wind-blown bubbles and look for other ones. A two-temperature plasma description seems to fit the data quite well for S308. Since all of the 22 bubbles studied still remain undetected by SRG/eROSITA, it is very likely that absorption effects and spatial compactness are responsible for the challenges standing in the way of detecting these bubbles in soft X-rays.
CRIS-Team Scopus Importer:2024-02-16
Keywords: ISM: bubbles; stars: Wolf-Rayet; X-rays: general; X-rays: ISM

Science of atmospheric phenomena with JEM-EUSO - Adams, J. H.; Ahmad, S.; Albert, J. -N.; Allard, D.; Anchordoqui, L.; Andreev, V.; Anzalone, Anna; Arai, Y.; Asano, K.; Ave Pernas, M.; Baragatti, P.; Barrillon, P.; et al. (Experimental Astronomy, 2015)
The main goal of the JEM-EUSO experiment is the study of Ultra High Energy Cosmic Rays (UHECR, 10(19)-10(21) e V), but the method which will be used (detection of the secondary light emissions induced by cosmic rays in the atmosphere) allows to study other luminous phenomena. The UHECRs will be detected through the measurement of the emission in the range between 290 and 430 m, where some part of Transient Luminous Events (TLEs) emission also appears. This work discusses the possibility of using the JEM-EUSO Telescope to get new scientific results on TLEs. The high time resolution of this instrument allows to observe the evolution of TLEs with great precision just at the moment of their origin. The paper consists of four parts: review of the present knowledge on the TLE, presentation of the results of the simulations of the TLE images in the JEM-EUSO telescope, results of the Russian experiment Tatiana-2 and discussion of the possible progress achievable in this field with JEM-EUSO as well as possible cooperation with other space projects devoted to the study of TLE - TARANIS and ASIM. In atmospheric physics, the study of TLEs became one of the main physical subjects of interest after their discovery in 1989. In the years 1992 - 1994 detection was performed from satellite, aircraft and space shuttle and recently from the International Space Station. These events have short duration (milliseconds) and small scales (km to tens of km) and appear at altitudes 50 - 100 km. Their nature is still not clear and each new experimental data can be useful for a better understanding of these mysterious phenomena.
Keywords: Transient Luminous Events; Elves; Sprites; Jets - Atmospheric phenomena

Science with the EXTraS Project: Exploring the X-Ray Transient and Variable Sky - De Luca, A.; Salvaterra, R.; Tiengo, A.; D'Agostino, D.; Watson, M. G.; Haberl, F.; Wilms, Jörn (The Universe of Digital Sky Surveys, 2016)
Keywords: Physics

Science with the XEUS High Time Resolution Spectrometer - Barret, D.; Belloni, T.; Bhattacharyya, S.; Gilfanov, Marat; Gogus, E.; Homan, J.; Mendez, M.; Miller, J. M.; Miller, M. C.; Mereghetti, Sandro; Paltani, S.; Poutanen, Juri; et al. (2008)
XEUS has been recently selected by ESA for an assessment study. XEUS is a large mission candidate for the Cosmic Vision program, aiming for a launch date as early as 2018. XEUS is a follow-on to ESA's Cornerstone X-Ray Spectroscopy Mission (XMM-Newton). It will be placed in a halo orbit at L2, by a single Ariane 5 ECA, and comprises two spacecrafts. The Silicon pore optics assembly of XEUS is contained in the mirror spacecraft while the focal plane instruments are contained in the detector spacecraft, which is maintained at the focus of the mirror by formation flying. The main requirements for XEUS are to provide a focused beam of X-rays with ail effective aperture of 5 m(2) at 1 keV, 2 m(2) at 7 keV, a spatial resolution better than 5 aresec, a spectral resolution ranging from 2 to 6 eV in the 0.1-8 keV energy band, a total energy bandpass of 0.1-40 keV, ultra-fast timing, and finally polarimetric capabilities. The High Time Resolution Spectrometer (HTRS) is one of the five focal plane instruments, which comprises also a wide field imager, a, hard X-ray imager, a cryogenic spectrometer, and a polarmeter. The HTRS is unique in its ability to cope with extremely high count rates (up to 2 Mcts/s), while providing sub-millisecond time resolution and good (CCD like) energy resolution. In this paper, we focus on the specific scientific objectives to be pursued with the HTRS: they are all centered around the key theme "Matter under extreme conditions" of the Cosmic Vision science program. We demonstrate the potential of the HTRS observations to probe strong gravity and matter at supra-nuclear densities. We conclude this paper by describing the current implementation of the HTRS in the XEUS focal plane.
Keywords: strong gravity; dense matter; X-ray instrumentation; black holes; neutron stars; accretion

SDSS J013655.91+242546.0-an A-type hyper-velocity star from the outskirts of the Galaxy - Tillich, A.; Przybilla, N.; Scholz, R. -D.; Heber, Ulrich; Heber, Ulrich (Astronomy & Astrophysics, 2009)
Context. Hyper-velocity stars (HVS) are moving so fast that they are unbound to the Galaxy. Dynamical ejection by a supermassive black hole is favoured to explain their origin.Aims. Locating the place of birth of an individual HVS is of utmost importance to understanding the ejection mechanism.Methods. SDSS J013655.91+242546.0 (J0136+2425 for short) was found amongst three high-velocity stars (drawn from a sample of more than 10 000 blue stars), for which proper motions were measured. A kinematical as well as a quantitative NLTE spectral analysis was performed. When combined with the radial velocity (RV) and the spectroscopic distance, the trajectory of the star in the Galactic potential was reconstructed.Results. J0136+2425 is found to be an A-type main-sequence star travelling at approximate to 590 km s(-1), possibly unbound to the Galaxy and originating in the outer Galactic rim nowhere near the Galactic centre.Conclusions. J0136+2425 is the second HVS candidate with measured proper motion, besides the massive B star HD 271791, and also the second for which its proper motion excludes a Galactic centre origin and, hence, the SMBH slingshot mechanism. Most known HVS are late B-type stars of about 3 M(circle dot). With a mass of 2.45 M(circle dot), J0136+2425 resembles a typical HVS far more than HD 271791 does. Hence, this is the first time that a typical HVS is found not to originate in the Galactic centre. Its ejection velocity from the disk is so high (550 km s(-1)) that the extreme supernova binary scenario proposed for HD 271791 is very unlikely.
Keywords: stars: kinematics; stars: individual: SDSSJ013655.91+242546.0; stars: atmospheres; line profiles

SDSS J124043.01+671034.68: the partially burned remnant of a low-mass white dwarf that underwent thermonuclear ignition? - Gansicke, Boris T.; Koester, Detlev; Raddi, Roberto; Toloza, Odette; Kepler, S. O. (Monthly Notices of the Royal Astronomical Society, 2020)
The white dwarf SDSS J124043.01+671034.68 (SDSS J1240+6710) was previously found to have an oxygen-dominated atmosphere with significant traces of neon, magnesium, and silicon. A possible origin via a violent late thermal pulse or binary interactions has been suggested to explain this very unusual photospheric composition. We report the additional detection of carbon, sodium, and aluminium in far-ultraviolet and optical follow-up spectroscopy. No iron-group elements are detected, with tight upper limits on titanium, iron, cobalt, and nickel, suggesting that the star underwent partial oxygen burning, but failed to ignite silicon burning. Modelling the spectral energy distribution and adopting the distance based on the Gaia parallax, we infer a low white dwarf mass, M-wd = 0.41 +/- 0.05 M-circle dot. The large space velocity of SDSS J1240+6710, computed from the Gaia proper motion and its radial velocity, is compatible with a Galactic rest-frame velocity of similar or equal to 250 km s(-1) in the opposite direction with respect to the Galactic rotation, strongly supporting a binary origin of this star. We discuss the properties of SDSS J1240+6710 in the context of the recently identified survivors of thermonuclear supernovae, the D-6 and LP 40-365 stars, and conclude that it is unlikely related to either of those two groups. We tentatively suggest that SDSS J1240+6710 is the partially burned remnant of a low-mass white dwarf that underwent a thermonuclear event.
CRIS-Team WoS Importer:2020-10-23

Searches for clustering in the time integrated skymap of the ANTARES neutrino telescope - Adrian-Martinez, S.; Albert, A.; Andre, Michel; Anton, Gisela; Ardid, Miguel; Aubert, J. -J.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; Bogazzi, C.; et al. (Journal of Cosmology and Astroparticle Physics, 2014)
This paper reports a search for spatial clustering of the arrival directions of high energy muon neutrinos detected by the ANTARES neutrino telescope. An improved two-point correlation method is used to study the autocorrelation of 3058 neutrino candidate events as well as cross-correlations with other classes of astrophysical objects: sources of high energy gamma rays, massive black holes and nearby galaxies. No significant deviations from the isotropic distribution of arrival directions expected from atmospheric backgrounds are observed.
Keywords: neutrino astronomy; neutrino detectors

Searches for gamma-ray lines and 'pure WIMP' spectra from Dark Matter annihilations in dwarf galaxies with HESS - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Arrieta, M.; Backes, Michael; Barnard, Monica; Becherini, Y.; Tjus, J. Becker; et al. (Journal of Cosmology and Astroparticle Physics, 2018)
Dwarf spheroidal galaxies are among the most promising targets for detecting signals of Dark Matter (DM) annihilations. The H.E.S.S. experiment has observed five of these systems for a total of about 130 hours. The data are re-analyzed here, and, in the absence of any detected signals, are interpreted in terms of limits on the DM annihilation cross section. Two scenarios are considered: i) DM annihilation into mono-energetic gamma-rays and ii) DM in the form of pure WIMP multiplets that, annihilating into all electroweak bosons, produce a distinctive gamma-ray spectral shape with a high-energy peak at the DM mass and a lower-energy continuum. For case i), upper limits at 95% confidence level of about less than or similar to 3 x 10(-25) cm(3) s(-1) are obtained in the mass range of 400 GeV to 1TeV. For case ii), the full spectral shape of the models is used and several excluded regions are identified, but the thermal masses of the candidates are not robustly ruled out.
CRIS-Team WoS Importer:2020-01-15

SEARCHES FOR POINT-LIKE AND EXTENDED NEUTRINO SOURCES CLOSE TO THE GALACTIC CENTER USING THE ANTARES NEUTRINO TELESCOPE - Adrian-Martinez, S.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Ardid, Miguel; Aubert, J-J.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; et al. (Astrophysical Journal Letters, 2014)
A search for cosmic neutrino sources using six years of data collected by the ANTARES neutrino telescope has been performed. Clusters of muon neutrinos over the expected atmospheric background have been looked for. No clear signal has been found. The most signal-like accumulation of events is located at equatorial coordinates R.A. = -46 degrees.8 and decl. = -64 degrees.9 and corresponds to a 2.2 sigma background fluctuation. In addition, upper limits on the flux normalization of an E-2 muon neutrino energy spectrum have been set for 50 pre-selected astrophysical objects. Finally, motivated by an accumulation of seven events relatively close to the Galactic Center in the recently reported neutrino sample of the IceCube telescope, a search for point sources in a broad region around this accumulation has been carried out. No indication of a neutrino signal has been found in the ANTARES data and upper limits on the flux normalization of an E-2 energy spectrum of neutrinos from point sources in that region have been set. The 90% confidence level upper limits on the muon neutrino flux normalization vary between 3.5 and 5.1 x 10(-8) GeV cm(-2) s(-1), depending on the exact location of the source.
Keywords: astroparticle physics; Galaxy: center; neutrinos

SEARCH FOR A CORRELATION BETWEEN ANTARES NEUTRINOS AND PIERRE AUGER OBSERVATORY UHECRs ARRIVAL DIRECTIONS - Adrian-Martinez, S.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Astraatmadja, T.; Aubert, J-J.; Baret, B.; Basa, S.; et al. (Astrophysical Journal, 2013)
A multimessenger analysis optimized for a correlation of arrival directions of ultra-high energy cosmic rays (UHECRs) and neutrinos is presented and applied to 2190 neutrino candidate events detected in 2007-2008 by the ANTARES telescope and 69 UHECRs observed by the Pierre Auger Observatory between 2004 January 1 and 2009 December 31. No significant correlation is observed. Assuming an equal neutrino flux (E-2 energy spectrum) from all UHECR directions, a 90% CL upper limit on the neutrino flux of 5.0 x 10(-8) GeV cm(-2) s(-1) per source is derived.
Keywords: astroparticle physics; cosmic rays; neutrinos

SEARCH FOR COSMIC NEUTRINO POINT SOURCES WITH FOUR YEARS OF DATA FROM THE ANTARES TELESCOPE - Adrian-Martinez, S.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Astraatmadja, T.; Aubert, J-J; Baret, B.; Basa, S.; et al. (Astrophysical Journal, 2012)
In this paper, a time-integrated search for point sources of cosmic neutrinos is presented using the data collected from 2007 to 2010 by the ANTARES neutrino telescope. No statistically significant signal has been found and upper limits on the neutrino flux have been obtained. Assuming an E-nu(-2). spectrum, these flux limits are at 1-10x10(-8) GeV cm(-2) s(-1) for declinations ranging from -90 degrees to 40 degrees. Limits for specific models of RX J1713.7-3946 and Vela X, which include information on the source morphology and spectrum, are also given.
Keywords: astroparticle physics; cosmic rays; neutrinos

Search for dark matter annihilation in the earth using the ANTARES neutrino telescope - Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Ardid, Miguel; Aubert, J. -J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; et al. (Physics of the Dark Universe, 2017)
A search for a neutrino signal from WIMP pair annihilations in the centre of the Earth has been performed with the data collected with the ANTARES neutrino telescope from 2007 to 2012. The event selection criteria have been developed and tuned to maximise the sensitivity of the experiment to such a neutrino signal. No significant excess of neutrinos over the expected background has been observed. Upper limits at 90% C.L. on the WIMP annihilation rate in the Earth and the spin independent scattering cross-section of WIMPs to nucleons sigma(SI)(p) were calculated for WIMP pair annihilations into either iota(+) iota(-), W+W-, b (b) over bar or the non-SUSY v mu(v) over bar as a function of the WIMP mass (between 25 GeV/c(2) and 1000 GeV/c(2)) and as a function of the thermally averaged annihilation cross section times velocity (Earth) of the WIMPs in the centre of the Earth. For masses of the WIMP close to the mass of iron nuclei (50 GeV/c(2)), the obtained limits on sigma(SI)(p) are more stringent than those obtained by other indirect searches. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Dark matter; Neutrino telescope; ANTARES; Indirect detection; WIMP

Search for Dark Matter Annihilation Signals from Unidentified Fermi-LAT Objects with HESS - Abdalla, H.; Spencer, Samuel; Aharonian, Felix; Ait Benkhali, F.; Anguner, E. O.; Arcaro, C.; Armand, C.; Armstrong, T.; Ashkar, H.; Backes, M.; Baghmanyan, V.; Barbosa-Martins, V.; et al. (Astrophysical Journal, 2021)
Cosmological N-body simulations show that Milky Way-sized galaxies harbor a population of unmerged dark matter (DM) subhalos. These subhalos could shine in gamma-rays and eventually be detected in gamma-ray surveys as unidentified sources. We performed a thorough selection among unidentified Fermi-Large Area Telescope Objects (UFOs) to identify them as possible tera-electron-volt-scale DM subhalo candidates. We search for very-high-energy (E greater than or similar to 100 GeV) gamma-ray emissions using H.E.S.S. observations toward four selected UFOs. Since no significant very-high-energy gamma-ray emission is detected in any data set of the four observed UFOs or in the combined UFO data set, strong constraints are derived on the product of the velocity-weighted annihilation cross section sigma v by the J factor for the DM models. The 95% confidence level observed upper limits derived from combined H.E.S.S. observations reach sigma vJ values of 3.7 x 10(-5) and 8.1 x 10(-6) GeV(2 )cm(-2 )s(-1) in the W (+) W (-) and tau (+) tau (-) channels, respectively, for a 1 TeV DM mass. Focusing on thermal weakly interacting massive particles, the H.E.S.S. constraints restrict the J factors to lie in the range 6.1 x 10(19)-2.0 x 10(21) GeV(2 )cm(-5) and the masses to lie between 0.2 and 6 TeV in the W (+) W (-) channel. For the tau (+) tau (-) channel, the J factors lie in the range 7.0 x 10(19)-7.1 x 10(20) GeV(2 )cm(-5) and the masses lie between 0.2 and 0.5 TeV. Assuming model-dependent predictions from cosmological N-body simulations on the J-factor distribution for Milky Way-sized galaxies, the DM models with masses >0.3 TeV for the UFO emissions can be ruled out at high confidence level.
CRIS-Team WoS Importer:2021-09-10

Search for Dark Matter Annihilation Signals in the H.E.S.S. Inner Galaxy Survey - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Angüner, E. O.; Armand, C.; Ashkar, H.; Backes, M.; Baghmanyan, V.; Martins, V. Barbosa; Batzofin, R.; Becherini, Y.; Berge, D.; et al. (Physical Review Letters, 2022)
The central region of the Milky Way is one of the foremost locations to look for dark matter (DM) signatures. We report the first results on a search for DM particle annihilation signals using new observations from an unprecedented γ-ray survey of the Galactic Center (GC) region, i.e., the Inner Galaxy Survey, at very high energies (?100 GeV) performed with the H.E.S.S. array of five ground-based Cherenkov telescopes. No significant γ-ray excess is found in the search region of the 2014-2020 dataset and a profile likelihood ratio analysis is carried out to set exclusion limits on the annihilation cross section ?σv?
CRIS-Team Scopus Importer:2022-09-30

Search for Dark Matter Annihilations towards the Inner Galactic Halo from 10 Years of Observations with HESS - Abdallah, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E.; Arrieta, M.; Aubert, P.; Backes, M.; Balzer, A.; Barnard, M.; Becherini, Y.; et al. (Physical Review Letters, 2016)
The inner region of the Milky Way halo harbors a large amount of dark matter (DM). Given its proximity, it is one of the most promising targets to look for DM. We report on a search for the annihilations of DM particles using gamma-ray observations towards the inner 300 pc of the Milky Way, with the H.E.S.S. array of ground-based Cherenkov telescopes. The analysis is based on a 2D maximum likelihood method using Galactic Center (GC) data accumulated by H.E.S.S. over the last 10 years (2004-2014), and does not show any significant gamma-ray signal above background. Assuming Einasto and Navarro-Frenk-White DM density profiles at the GC, we derive upper limits on the annihilation cross section <sigma nu="">. These constraints are the strongest obtained so far in the TeV DM mass range and improve upon previous limits by a factor 5. For the Einasto profile, the constraints reach <sigma nu=""> values of 6 x 10(-26) cm(3) s(-1) in the W+W- channel for a DM particle mass of 1.5 TeV, and 2 x 10(-26) cm(3) s(-1) in the tau(+)tau(-) channel for a 1 TeV mass. For the first time, ground-based gamma-ray observations have reached sufficient sensitivity to probe <sigma nu=""> values expected from the thermal relic density for TeV DM particles.</sigma></sigma></sigma>

Search for dark matter towards the Galactic Centre with 11 years of ANTARES data - Albert, A.; André, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. J.; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; Bertin, V.; Biagi, S.; et al. (Physics Letters B, 2020)
Neutrino detectors participate in the indirect search for the fundamental constituents of dark matter (DM) in form of weakly interacting massive particles (WIMPs). In WIMP scenarios, candidate DM particles can pair-annihilate into Standard Model products, yielding considerable fluxes of high-energy neutrinos. A detector like ANTARES, located in the Northern Hemisphere, is able to perform a complementary search looking towards the Galactic Centre, where a high density of dark matter is thought to accumulate. Both this directional information and the spectral features of annihilating DM pairs are entered into an unbinned likelihood method to scan the data set in search for DM-like signals in ANTARES data. Results obtained upon unblinding 3170 days of data reconstructed with updated methods are presented, which provides a larger, and more accurate, data set than a previously published result using 2101 days. A non-observation of dark matter is converted into limits on the velocity-averaged cross section for WIMP pair annihilation.
CRIS-Team Scopus Importer:2020-05-12
Keywords: ANTARES; Dark matter indirect detection; Galactic Centre; Neutrino telescope

Search for gamma-Ray Line Signals from Dark Matter Annihilations in the Inner Galactic Halo from 10 Years of Observations with HESS - Abdallah, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arrieta, M.; Aubert, P.; Backes, M.; Balzer, A.; Barnard, M.; Becherini, Y.; et al. (Physical Review Letters, 2018)
Spectral lines are among the most powerful signatures for dark matter (DM) annihilation searches in very-high-energy gamma rays. The central region of the Milky Way halo is one of the most promising targets given its large amount of DM and proximity to Earth. We report on a search for a monoenergetic spectral line from self-annihilations of DM particles in the energy range from 300 GeV to 70 TeV using a two-dimensional maximum likelihood method taking advantage of both the spectral and spatial features of the signal versus background. The analysis makes use of Galactic center observations accumulated over ten years (2004-2014) with the H.E.S.S. array of ground-based Cherenkov telescopes. No significant gamma-ray excess above the background is found. We derive upper limits on the annihilation cross section (sigma v) for monoenergetic DM lines at the level of 4 x 10(-28) cm(3) s(-1) at 1 TeV, assuming an Einasto DM profile for the Milky Way halo. For a DM mass of 1 TeV, they improve over the previous ones by a factor of 6. The present constraints are the strongest obtained so far for DM particles in the mass range 300 GeV-70 TeV. Ground-based gamma-ray observations have reached sufficient sensitivity to explore relevant velocity-averaged cross sections for DM annihilation into two gamma-ray photons at the level expected from the thermal relic density for TeV DM particles.

Search for High-energy Neutrinos from Binary Neutron Star Merger GW170817 with ANTARES, IceCube, and the Pierre Auger Observatory - Albert, A.; Andre, M.; Anghinolfi, M.; Ardid, M.; Aubert, J. -J.; Aublin, J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Belhorma, B.; Bertin, V.; et al. (Astrophysical Journal Letters, 2017)
The Advanced LIGO and Advanced Virgo observatories recently discovered gravitational waves from a binary neutron star inspiral. A short gamma-ray burst (GRB) that followed the merger of this binary was also recorded by the Fermi Gamma-ray Burst Monitor (Fermi-GBM), and the Anti-Coincidence Shield for the Spectrometer for the International Gamma-Ray Astrophysics Laboratory (INTEGRAL), indicating particle acceleration by the source. The precise location of the event was determined by optical detections of emission following the merger. We searched for high-energy neutrinos from the merger in the GeV-EeV energy range using the ANTARES, IceCube, and Pierre Auger Observatories. No neutrinos directionally coincident with the source were detected within +/- 500 s around the merger time. Additionally, no MeV neutrino burst signal was detected coincident with the merger. We further carried out an extended search in the direction of the source for high-energy neutrinos within the 14 day period following the merger, but found no evidence of emission. We used these results to probe dissipation mechanisms in relativistic outflows driven by the binary neutron star merger. The non-detection is consistent with model predictions of short GRBs observed at a large off-axis angle.
Keywords: gamma-ray burst: general; gravitational waves; neutrinos

Search for high-energy neutrinos from bright GRBs with ANTARES - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J-J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; et al. (Monthly Notices of the Royal Astronomical Society, 2017)
Gamma-ray bursts are thought to be sites of hadronic acceleration, thus neutrinos are expected from the decay of charged particles, produced in p gamma interactions. The methods and results of a search for muon neutrinos in the data of the ANTARES neutrino telescope from four bright GRBs (GRB 080916C, GRB 110918A, GRB 130427A and GRB 130505A) observed between 2008 and 2013 are presented. Two scenarios of the fireball model have been investigated: the internal shock scenario, leading to the production of neutrinos with energies mainly above 100 TeV, and the photospheric scenario, characterized by a low-energy component in neutrino spectra due to the assumption of neutrino production closer to the central engine. Since no neutrino events have been detected in temporal and spatial coincidence with these bursts, upper limits at 90 per cent confidence level on the expected neutrino fluxes are derived. The non-detection allows for directly constraining the bulk Lorentz factor of the jet Gamma and the baryon loading f(p).
Keywords: acceleration of particles; neutrinos; gamma-ray burst: individual: GRB 080916C; gamma-ray burst: individual: GRB 110918A; gamma-ray burst: individual: GRB 130427A; gamma-ray burst: individual: GRB 130505A

Search for high-energy neutrinos from gravitational wave event GW151226 and candidate LVT151012 with ANTARES and IceCube - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, Miguel; Aubert, J. -J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; et al. (Physical Review D - Particles, Fields, Gravitation and Cosmology, 2017)
The Advanced LIGO observatories detected gravitational waves from two binary black hole mergers during their first observation run (O1). We present a high-energy neutrino follow-up search for the second gravitational wave event, GW151226, as well as for gravitational wave candidate LVT151012. We find two and four neutrino candidates detected by IceCube, and one and zero detected by ANTARES, within +/- 500 s around the respective gravitational wave signals, consistent with the expected background rate. None of these neutrino candidates are found to be directionally coincident with GW151226 or LVT151012. We use nondetection to constrain isotropic-equivalent high-energy neutrino emission from GW151226, adopting the GW event's 3D localization, to less than 2 x 10(51)-2 x 10(54) erg.

Search for high-redshift blazars with Fermi/LAT - Kreter, Michael; Gokus, Andrea; Kadler, Matthias; Krauß, Felicia; Buson, Sara; Ojha, Roopesh; Wilms, Jörn; Böttcher, Markus (Proceedings of Science, 2019)
High-redshift blazars (z ≥ 2.5) are the most powerful class of persistent γ-ray sources in the Universe. These objects possess the highest jet powers and luminosities and have black hole masses often in excess of 109 solar masses. In addition, high-z blazars are important cosmological probes and serve as test objects for blazar evolution models. Due to their large distance and the resulting electron/positron cascading on the extragalactic background light, their high-energy emission typically peaks below the GeV range. This makes these blazars difficult to study with Fermi/LAT and only the very brightest objects are detectable. Hence, only a small number of high-z blazars could be detected with Fermi/LAT so far. In this work, we present a strategy to increase the detection statistics at redshift z ≥ 2.5 via a search for flaring events in high-z γ-ray blazars whose long-term averaged flux is just below the sensitivity limit of Fermi/LAT. Seven previously GeV undetected high-z blazars have been identified with a test statistic of TS ≥ 25 from their bright monthly outburst periods, while more detections are expected in the future.
CRIS-Team Scopus Importer:2021-04-19

Search for High-redshift Blazars with Fermi/LAT - Kreter, M.; Gokus, A.; Krauss, F.; Kadler, M.; Ojha, R.; Buson, S.; Wilms, Jörn; Bottcher, M. (Astrophysical Journal, 2020)
High-z blazars (z 2.5) are the most powerful class of persistent γ-ray sources in the universe. These objects possess the highest jet powers and luminosities and have black hole masses often in excess of 109 solar masses. In addition, high-z blazars are important cosmological probes and serve as test objects for blazar evolution models. Due to their large distance, their high-energy emission typically peaks below the GeV range, which makes them difficult to study with Fermi/Large Area Telescope (LAT). Therefore, only the very brightest objects are detectable and, to date, only a small number of high-z blazars have been detected with Fermi/LAT. In this work, we studied the monthly binned long-term γ-ray emission of a sample of 176 radio and optically detected blazars that have not been reported as known γ-ray sources in the 3FGL catalog. To account for false-positive detections, we calculated monthly Fermi/LAT light curves for a large sample of blank sky positions and derived the number of random fluctuations that we expect at various test statistic (TS) levels. For a given blazar, a detection of TS > 9 in at least one month is expected ∼15% of the time. Although this rate is too high to secure detection of an individual source, half of our sample shows such single-month γ-ray activity, indicating a population of high-energy blazars at distances of up to z = 5.2. Multiple TS > 9 monthly detections are unlikely to happen by chance, and we have detected several individual new sources in this way, including the most distant γ-ray blazar, BZQ J1430+4204 (z = 4.72). Finally, two new γ-ray blazars at redshifts of z = 3.63 and z = 3.11 are unambiguously detected via very significant (TS > 25) flares in individual monthly time bins.
CRIS-Team Scopus Importer:2020-11-27
Keywords: Blazars (164); Gamma-ray astronomy (628); High-redshift galaxies (734)

Search for magnetic monopoles with ten years of the ANTARES neutrino telescope - Albert, A.; Alves, S.; André, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Ardid, S.; Aubert, J. J.; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; et al. (Journal of High Energy Astrophysics, 2022)
This work presents a new search for magnetic monopoles using data taken with the ANTARES neutrino telescope over a period of 10 years (January 2008 to December 2017). Compared to previous ANTARES searches, this analysis uses a run-by-run simulation strategy, with a larger exposure as well as a new simulation of magnetic monopoles taking into account the Kasama, Yang and Goldhaber model for their interaction cross-section with matter. No signal compatible with the passage of relativistic magnetic monopoles is observed, and upper limits on the flux of magnetic monopoles with β=v/c≥0.55, are presented. For ultra-relativistic magnetic monopoles the flux limit is ∼7×10−18 cm−2s−1sr−1.
CRIS-Team Scopus Importer:2022-03-25
Keywords: ANTARES telescope; Magnetic monopoles; Neutrino

Search for Multimessenger Sources of Gravitational Waves and High-energy Neutrinos with Advanced LIGO during Its First Observing Run, ANTARES, and IceCube - Albert, A.; Andre, M.; Anghinolfi, M.; Ardid, M.; Aubert, J-J; Aublin, J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Belhorma, B.; Bertin,; et al. (Astrophysical Journal, 2019)
Astrophysical sources of gravitational waves, such as binary neutron star and black hole mergers or core-collapse supernovae, can drive relativistic outflows, giving rise to non-thermal high-energy emission. High-energy neutrinos are signatures of such outflows. The detection of gravitational waves and high-energy neutrinos from common sources could help establish the connection between the dynamics of the progenitor and the properties of the outflow. We searched for associated emission of gravitational waves and high-energy neutrinos from astrophysical transients with minimal assumptions using data from Advanced LIGO from its first observing run O1, and data from the ANTARES and IceCube neutrino observatories from the same time period. We focused on candidate events whose astrophysical origins could not be determined from a single messenger. We found no significant coincident candidate, which we used to constrain the rate density of astrophysical sources dependent on their gravitational-wave and neutrino emission processes.
Keywords: gravitational waves; neutrinos

Search for muon-neutrino emission from GeV and TeV gamma-ray flaring blazars using five years of data of the ANTARES telescope - Adrian-Martinez, S.; Albert, A.; Andre, Michel; Anton, Gisela; Ardid, Miguel; Aubert, J. J.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; Bogazzi, C.; et al. (Journal of Cosmology and Astroparticle Physics, 2015)
The ANTARES telescope is well-suited for detecting astrophysical transient neutrino sources as it can observe a full hemisphere of the sky at all times with a high duty cycle. The background due to atmospheric particles can be drastically reduced, and the point-source sensitivity improved, by selecting a narrow time window around possible neutrino production periods. Blazars, being radio-loud active galactic nuclei with their jets pointing almost directly towards the observer, are particularly attractive potential neutrino point sources, since they are among the most likely sources of the very high-energy cosmic rays. Neutrinos and gamma rays may be produced in hadronic interactions with the surrounding medium. Moreover, blazars generally show high time variability in their light curves at different wavelengths and on various time scales. This paper presents a time-dependent analysis applied to a selection of flaring gamma-ray blazars observed by the FERMI/LAT experiment and by TeV Cherenkov telescopes using five years of ANTARES data taken from 2008 to 2012. The results are compatible with fluctuations of the background. Upper limits on the neutrino fluence have been produced and compared to the measured gamma-ray spectral energy distribution.
Keywords: X-ray binaries; neutrino astronomy

Search for muon neutrinos from gamma-ray bursts with the ANTARES neutrino telescope using 2008 to 2011 data - Adrian-Martinez, S.; Albert, A.; Al Samarai, I.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Astraatmadja, T.; Aubert, J. -J.; Baret, B.; Barrios-Marti, J.; et al. (Astronomy & Astrophysics, 2013)
Aims. We search for muon neutrinos in coincidence with GRBs with the ANTARES neutrino detector using data from the end of 2007 to 2011.Methods. Expected neutrino fluxes were calculated for each burst individually. The most recent numerical calculations of the spectra using the NeuCosmA code were employed, which include Monte Carlo simulations of the full underlying photohadronic interaction processes. The discovery probability for a selection of 296 GRBs in the given period was optimised using an extended maximum-likelihood strategy.Results. No significant excess over background is found in the data, and 90% confidence level upper limits are placed on the total expected flux according to the model.
Keywords: neutrinos; gamma-ray burst: general; methods: numerical

Search for neutrino counterparts of gravitational-wave events detected by LIGO and Virgo during run O2 with the ANTARES telescope - Albert, A.; André, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. J.; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; Bertin, V.; Biagi, S.; et al. (European Physical Journal C: Particles and Fields, 2020)
An offline search for a neutrino counterpart to gravitational-wave (GW) events detected during the second observation run (O2) of Advanced-LIGO and Advanced-Virgo performed with ANTARES data is presented. In addition to the search for long tracks induced by νμ (ν¯ μ) charged current interactions, a search for showering events induced by interactions of neutrinos of any flavour is conducted. The severe spatial and time coincidence provided by the gravitational-wave alert allows regions above the detector horizon to be probed, extending the ANTARES sensitivity over the entire sky. The results of this all-neutrino-flavour and all-sky time dependent analysis are presented. The search for prompt neutrino emission within ±500 s around the time of six GW events yields no neutrino counterparts. Upper limits on the neutrino spectral fluence and constraints on the isotropic energy radiated via high-energy neutrinos (from a few TeV to a few tens of PeV) are set for each GW event analysed.
CRIS-Team Scopus Importer:2020-06-16

Search for neutrino emission from gamma-ray flaring blazars with the ANTARES telescope - Adrian-Martinez, S.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Astraatmadja, T.; Aubert, J-J.; Baret, B.; Basa, S.; et al. (Astroparticle Physics, 2012)
The ANTARES telescope is well-suited to detect neutrinos produced in astrophysical transient sources as it can observe a full hemisphere of the sky at all times with a high duty cycle. Radio-loud active galactic nuclei with jets pointing almost directly towards the observer, the so-called blazars, are particularly attractive potential neutrino point sources. The all-sky monitor LAT on board the Fermi satellite probes the variability of any given gamma-ray bright blazar in the sky on time scales of hours to months. Assuming hadronic models, a strong correlation between the gamma-ray and the neutrino fluxes is expected. Selecting a narrow time window on the assumed neutrino production period can significantly reduce the background.An unbinned method based on the minimization of a likelihood ratio was applied to a subsample of data collected in 2008 (61 days live time). By searching for neutrinos during the high state periods of the AGN light curve, the sensitivity to these sources was improved by about a factor of two with respect to a standard time-integrated point source search. First results on the search for neutrinos associated with ten bright and variable Fermi sources are presented. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: ANTARES; Neutrino astronomy; Fermi LAT transient sources; Time-dependent search; Blazars

Search for Neutrinos from the Tidal Disruption Events AT2019dsg and AT2019fdr with the ANTARES Telescope - Albert, A.; Alves, S.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J-J; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; Bendahman, M.; et al. (Astrophysical Journal, 2021)
On 2019 October 1, the IceCube Collaboration detected a muon track neutrino with a high probability of being of astrophysical origin, IC191001A. After a few hours, the tidal disruption event (TDE) AT2019dsg, observed by the Zwicky Transient Facility (ZTF), was indicated as the most likely counterpart of the IceCube track. More recently, the follow-up campaign of the IceCube alerts by ZTF suggested a second TDE, AT2019fdr, as a promising counterpart of another IceCube muon track candidate, IC200530A, detected on 2020 May 30. Here, these intriguing associations are followed-up by searching for neutrinos in the ANTARES detector from the directions of AT2019dsg and AT2019fdr using a time-integrated approach. As no significant evidence for space clustering is found in the ANTARES data, upper limits on the one-flavor neutrino flux and fluence are set.
CRIS-Team WoS Importer:2021-10-29

Search for non-standard neutrino interactions with 10 years of ANTARES data - Albert, A.; Alves, S.; André, M.; Anghinolfi, M.; Anton, G.; Ardid, M.; Ardid, S.; Aubert, J. J.; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; et al. (Journal of High Energy Physics, 2022)
Non-standard interactions of neutrinos arising in many theories beyond the Standard Model can significantly alter matter effects in atmospheric neutrino propagation through the Earth. In this paper, a search for deviations from the prediction of the standard 3-flavour atmospheric neutrino oscillations using the data taken by the ANTARES neutrino telescope is presented. Ten years of atmospheric neutrino data collected from 2007 to 2016, with reconstructed energies in the range from ∼16 GeV to 100 GeV, have been analysed. A log-likelihood ratio test of the dimensionless coefficients εμτ and εττ − εμμ does not provide clear evidence of deviations from standard interactions. For normal neutrino mass ordering, the combined fit of both coefficients yields a value 1.7σ away from the null result. However, the 68% and 95% confidence level intervals for εμτ and εττ − εμμ, respectively, contain the null value. Best fit values, one standard deviation errors and bounds at the 90% confidence level for these coefficients are given for both normal and inverted mass orderings. The constraint on εμτ is among the most stringent to date and it further restrains the strength of possible non-standard interactions in the μ − τ sector. [Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2022-07-22
Keywords: Neutrino Detectors and Telescopes (experiments)

Search for nuclearites with the ANTARES detector - Albert, A.; Alves, S.; André, M.; Anghinolfi, M.; Anton, G.; Ardid, M.; Ardid, S.; Aubert, J. J.; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; et al. (Proceedings of Science, 2022)
ANTARES is a Cherenkov underwater neutrino telescope operating in the Mediterranean. Its construction was completed in 2008. Even though optimised for the search of cosmic neutrinos, this telescope is also sensitive to nuclearites (massive nuggets of strange quark matter [1]) trough the black body radiation emitted along their path [2]. We discuss here the possible detection of non-relativistic down-going nuclearites with the ANTARES telescope and present the results of an analysis using data collected from 2009 till 2017.
CRIS-Team Scopus Importer:2022-12-23

Search for Pre-Burst Emission from Binary Neutron Star Mergers with Spectrum–Roentgen–Gamma - Mereminskiy, I. A.; Lutovinov, A. A.; Postnov, K. A.; Arefiev, V. A.; Lapshov, I. Yu; Molkov, S.; Sazonov, S. Yu; Semena, A. N.; Tkachenko, A. Yu; Shtykovsky, A. E.; Liu, Z.; Wilms, Jörn; et al. (Astronomy Letters-A Journal of Astronomy and Space Astrophysics, 2022)
Abstract: Close binary systems consisting of two neutron stars (BNS) emit gravitational waves, that allow them to merge on timescales shorter than Hubble time. It is widely believed, that NS–NS mergers in such systems power short gamma-ray bursts (GRB). Several mechanisms which could lead to electromagnetic energy release prior to a merger have been proposed. We estimate the ability to observe the possible pre-burst emission with telescopes of Spectrum–Roentgen–Gamma. We also investigate first such event, GRB210919A, which fell into the field of view of the SRG telescopes less than two days before the burst.
CRIS-Team Scopus Importer:2022-11-18
Keywords: gamma-ray burst; surveys; X-ray sources

Search for relativistic magnetic monopoles with five years of the ANTARES detector data - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, Miguel; Aubert, J. -J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; et al. (Journal of High Energy Physics, 2017)
A search for magnetic monopoles using five years of data recorded with the ANTARES neutrino telescope from January 2008 to December 2012 with a total live time of 1121 days is presented. The analysis is carried out in the range beta > 0.6 of magnetic monopole velocities using a strategy based on run-by-run Monte Carlo simulations. No signal above the background expectation from atmospheric muons and atmospheric neutrinos is observed, and upper limits are set on the magnetic monopole flux ranging from 5.7 x 10(-16) to 1.5 x 10(-18) cm(-2).s(-1).sr(-1).
Keywords: Exotics; Neutrino Detectors and Telescopes (experiments)

Search for relativistic magnetic monopoles with the ANTARES neutrino telescope - Adrian-Martinez, S.; Aguilar, J. A.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Jesus, A. C. Assis; Astraatmadja, T.; Aubert, J-J.; et al. (Astroparticle Physics, 2012)
Magnetic monopoles are predicted in various unified gauge models and could be produced at intermediate mass scales. Their detection in a neutrino telescope is facilitated by the large amount of light emitted compared to that from muons. This paper reports on a search for upgoing relativistic magnetic monopoles with the ANTARES neutrino telescope using a data set of 116 days of live time taken from December 2007 to December 2008. The one observed event is consistent with the expected atmospheric neutrino and muon background, leading to a 90% C.L. upper limit on the monopole flux between 1.3 x 10-(17) and 8.9 x 10(-17) CM-2 s(-1) sr(-1) for monopoles with velocity beta >= 0.625. (c) 2012 Elsevier B.V. All rights reserved.
Keywords: Magnetic monopole; Neutrino telescopes; ANTARES

Search for Spatial Correlations of Neutrinos with Ultra-high-energy Cosmic Rays - Albert, A.; Domi, Alba; Alves, S.; Andre, M.; Anghinolfi, M.; Ardid, S.; Aubert, J-J; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; Bendahman, M.; et al. (Astrophysical Journal, 2022)
For several decades, the origin of ultra-high-energy cosmic rays (UHECRs) has been an unsolved question of high-energy astrophysics. One approach for solving this puzzle is to correlate UHECRs with high-energy neutrinos, since neutrinos are a direct probe of hadronic interactions of cosmic rays and are not deflected by magnetic fields. In this paper, we present three different approaches for correlating the arrival directions of neutrinos with the arrival directions of UHECRs. The neutrino data are provided by the IceCube Neutrino Observatory and ANTARES, while the UHECR data with energies above similar to 50 EeV are provided by the Pierre Auger Observatory and the Telescope Array. All experiments provide increased statistics and improved reconstructions with respect to our previous results reported in 2015. The first analysis uses a high-statistics neutrino sample optimized for point-source searches to search for excesses of neutrino clustering in the vicinity of UHECR directions. The second analysis searches for an excess of UHECRs in the direction of the highest-energy neutrinos. The third analysis searches for an excess of pairs of UHECRs and highest-energy neutrinos on different angular scales. None of the analyses have found a significant excess, and previously reported overfluctuations are reduced in significance. Based on these results, we further constrain the neutrino flux spatially correlated with UHECRs.
CRIS-Team WoS Importer:2022-08-26

Searching for TeV Gamma-Ray Emission from SGR 1935+2154 during Its 2020 X-Ray and Radio Bursting Phase - Abdalla, H.; Aharonian, F.; Mitchell, Alison; Spencer, Samuel; Benkhali, F. Ait; Anguner, E. O.; Arcaro, C.; Armand, C.; Armstrong, T.; Ashkar, H.; Backes, M.; Baghmanyan,; et al. (Astrophysical Journal, 2021)
Magnetar hyperflares are the most plausible explanation for fast radio bursts (FRBs)-enigmatic powerful radio pulses with durations of several milliseconds and high brightness temperatures. The first observational evidence for this scenario was obtained in 2020 April when an FRB was detected from the direction of the Galactic magnetar and soft gamma-ray repeater SGR 1935+2154. The FRB was preceded by two gamma-ray outburst alerts by the BAT instrument aboard the Swift satellite, which triggered follow-up observations by the High Energy Stereoscopic System (H.E.S.S.). H.E.S.S. observed SGR 1935+2154 for 2 hr on 2020 April 28. The observations are coincident with X-ray bursts from the magnetar detected by INTEGRAL and Fermi-GBM, thus providing the first very high energy gamma-ray observations of a magnetar in a flaring state. High-quality data acquired during these follow-up observations allow us to perform a search for short-time transients. No significant signal at energies E > 0.6 TeV is found, and upper limits on the persistent and transient emission are derived. We here present the analysis of these observations and discuss the obtained results and prospects of the H.E.S.S. follow-up program for soft gamma-ray repeaters.
CRIS-Team WoS Importer:2021-10-08

Searching for X-ray counterparts of degree-wide TeV halos around middle-aged pulsars with SRG/eROSITA - Khokhriakova, A.; Becker, W.; Ponti, G.; Sasaki, Manami; Li, B.; Liu, R. Y. (Astronomy & Astrophysics, 2024)
Context. Extended gamma-ray TeV emission (TeV halos) has been detected around middle-aged pulsars. A proposed model to explain these TeV halos is that electrons from a degree-wide pulsar wind nebula (PWN) get up-scattered by cosmic microwave background photons through inverse Compton processes. However, no X-ray degree-wide faint diffuse PWNe have been found around these middle-aged pulsars in previous X-ray observations. Aims. We performed a search for degree-wide PWNe around Geminga, PSR B0656+14, B0540+23, J0633+0632, and J0631+1036 using data from the first four consecutive Spectrum Roentgen Gamma/eROSITA all-sky surveys. In order to better understand the mechanisms underlying the formation of TeV halos, we investigated the magnetic field strength within an area of 1 in radius centred on those pulsars. Methods. To achieve our goals, we selected a list of suitable candidate pulsars in the eROSITA-DE part of the sky and applied data reduction techniques to process the eROSITA data. We then performed a spatial analysis of the regions around selected pulsars. Results. We do not detect any degree-wide diffuse emission driven by rotation-powered pulsars around Geminga, PSR B0656+14, B0540+23, J0633+0632, or J0631+1036. Indeed, close inspection of the data shows that the pulsars of interest are all embedded in diffuse emission from supernova remnants such as the Monogem Ring or the Rosetta Nebula, while PSR B0540+23 is located 2.5 away from the Crab pulsar, which is exceptionally bright, causing its X-ray emission to spread over a significant area up to the position of PSR B0540+23 and therefore strongly diminishes our capacity to search for degree-wide bright diffuse X-ray emission. Conclusions. Despite the non-detection of any degree-wide PWN surrounding the analysed pulsars, we set flux upper limits to provide useful information on magnetic field strength and its spatial distribution around those pulsars, providing additional constraints on the proposed theory for the formation of TeV halos around pulsars.
CRIS-Team Scopus Importer:2024-03-29
Keywords: ISM: magnetic fields; Pulsars: general; X-rays: ISM

Search of dark matter annihilation in the galactic centre using the ANTARES neutrino telescope - Adrian-Martinez, S.; Albert, A.; Andre, Michel; Anton, Gisela; Ardid, Miguel; Aubert, J. -J.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; Bogazzi, C.; et al. (Journal of Cosmology and Astroparticle Physics, 2015)
A search for high-energy neutrinos coming from the direction of the Galactic Centre is performed using the data recorded by the ANTARES neutrino telescope from 2007 to 2012. The event selection criteria are chosen to maximise the sensitivity to possible signals produced by the self-annihilation of weakly interacting massive particles accumulated around the centre of the Milky Way with respect to the atmospheric background. After data unblinding, the number of neutrinos observed in the line of sight of the Galactic Centre is found to be compatible with background expectations. The 90% C.L. upper limits in terms of the neutrino+anti-neutrino flux, Phi(nu mu + (nu) over bar mu), and the velocity averaged annihilation cross-section, , are derived for the WIMP self-annihilation channels into b (b) over bar; W+W-; tau(+)tau(-); mu(+)mu(-); nu(nu) over bar. The ANTARES limits for are shown to be the most stringent for a neutrino telescope over the WIMP masses 25 GeV < M-WIMP < 10TeV.
Keywords: neutrino experiments; dark matter experiments; neutrino astronomy

Sensitivity Modeling for LiteBIRD - Hasebe, T.; Ade, P. A.R.; Adler, A.; Allys, E.; Alonso, D.; Arnold, K.; Auguste, D.; Aumont, J.; Aurlien, R.; Austermann, J.; Azzoni, S.; Baccigalupi, C.; et al. (Journal of Low Temperature Physics, 2022)
LiteBIRD is a future satellite mission designed to observe the polarization of the cosmic microwave background radiation in order to probe the inflationary universe. LiteBIRD is set to observe the sky using three telescopes with transition-edge sensor bolometers. In this work we estimated the LiteBIRD instrumental sensitivity using its current design. We estimated the detector noise due to the optical loadings using physical optics and ray-tracing simulations. The noise terms associated with thermal carrier and readout noise were modeled in the detector noise calculation. We calculated the observational sensitivities over fifteen bands designed for the LiteBIRD telescopes using assumed observation time efficiency.
CRIS-Team Scopus Importer:2022-12-23
Keywords: Astronomy; CMB; Cosmology; Detector noise; Satellite; Sensitivity

Sensitivity of the KM3NeT/ARCA neutrino telescope to point-like neutrino sources - Aiello, S.; Akrame, S. E.; Ameli, F.; G. Anassontzis, E.; Andre, M.; Androulakis, G.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aublin, J.; Avgitas, T.; Bagatelas, C.; et al. (Astroparticle Physics, 2019)
KM3NeT will be a network of deep-sea neutrino telescopes in the Mediterranean Sea. The KM3NeT/ARCA detector, to be installed at the Capo Passero site (Italy), is optimised for the detection of high-energy neutrinos of cosmic origin. Thanks to its geographical location on the Northern hemisphere, KM3NeT/ARCA can observe upgoing neutrinos from most of the Galactic Plane, including the Galactic Centre. Given its effective area and excellent pointing resolution, KM3NeT/ARCA will measure or significantly constrain the neutrino flux from potential astrophysical neutrino sources. At the same time, it will test flux predictions based on gamma-ray measurements and the assumption that the gamma-ray flux is of hadronic origin. Assuming this scenario, discovery potentials and sensitivities for a selected list of Galactic sources and to generic point sources with an E −2 spectrum are presented. These spectra are assumed to be time independent. The results indicate that an observation with 3σ significance is possible in about six years of operation for the most intense sources, such as Supernovae Remnants RX J1713.7-3946 and Vela Jr. If no signal will be found during this time, the fraction of the gamma-ray flux coming from hadronic processes can be constrained to be below 50% for these two objects.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Astrophysical neutrino sources; Cherenkov underwater neutrino telescope; KM3NeT

Sensitivity to light sterile neutrino mixing parameters with KM3NeT/ORCA - Aiello, S.; Albert, A.; Alshamsi, M.; Garre, S. Alves; Aly, Z.; Ambrosone, Antonio; Ameli, F.; Andre, M.; Androulakis, G.; Anghinolfi, M.; Anguita, M.; Anton, Gisela; et al. (Journal of High Energy Physics, 2021)
KM3NeT/ORCA is a next-generation neutrino telescope optimised for atmospheric neutrino oscillations studies. In this paper, the sensitivity of ORCA to the presence of a light sterile neutrino in a 3+1 model is presented. After three years of data taking, ORCA will be able to probe the active-sterile mixing angles theta(14), theta(24), theta(34) and the effective angle theta(mu e), over a broad range of mass squared difference Delta m(41)(2) similar to [10(-5), 10] eV(2), allowing to test the eV-mass sterile neutrino hypothesis as the origin of short baseline anomalies, as well as probing the hypothesis of a very light sterile neutrino, not yet constrained by cosmology. ORCA will be able to explore a relevant fraction of the parameter space not yet reached by present measurements.
CRIS-Team WoS Importer:2021-11-12

Short-period X-ray oscillations in super-soft novae and persistent super-soft sources - Ness, J-U; Beardmore, A. P.; Osborne, J. P.; Kuulkers, E.; Henze, M.; Piro, A. L.; Drake, J. J.; Dobrotka, A.; Schwarz, G.; Starrfield, S.; Kretschmar, P.; Hirsch, Maria; et al. (Astronomy & Astrophysics, 2015)
Conclusions. Since fast rotation periods of the white dwarfs as origin of these transient oscillations are speculative, we concentrate on pulsation mechanisms. We present initial considerations predicting the oscillation period to scale linearly with the white dwarf radius (and thus mass), weakly with the pressure at the base, and luminosity. Estimates of the size of the white dwarf could be useful for determining whether these systems are more massive than typical white dwarfs, and thus whether they are growing from accretion over time. Signs of such mass growth may have implications for whether some of these systems are attractive as Type Ia supernova progenitors.
Keywords: novae; cataclysmic variables; stars: oscillations; white dwarfs; X-rays: stars

Short term and multi-band variability of the active nucleus of IC 310 - Eisenacher, Dorit; Colin, Pierre; Lombardi, Saverio; Sitarek, Julian; Zandanel, Fabio; Paneque, David; Dauser, Thomas; Krauß, Felicia; Wilbert, Sven; Kadler, Matthias; Schulz, Robert; Wilms, Jörn; et al. (2012)
The MAGIC Telescopes detected the active galaxy IC 310 at very high energies (VHE, > 100 GeV) during observations of the Perseus cluster in 2009 and 2010. This source had originally been classified as a head-tail radio galaxy. By contrast, recent high-resolution radio images obtained with the VLBA reveal the blazar-like structure of IC 310 on parsec scales. This object is also investigated in terms of its variability at X-ray and gamma-ray energies. Studies of the multi-band flux variability at different time periods are presented. The spectral evolution seems to be different in the VHE gamma-ray and X-ray bands.
Keywords: Active Galactic Nuclei: individual (IC 310); gamma-rays: observations; gamma-ray telescopes; Radio galaxies

SHOTGLAS: II. MUSE spectroscopy of blue horizontal branch stars in the core of ω Centauri and NGC6752 - Latour, M.; Hämmerich, Steven; Dorsch, Matti; Heber, Ulrich; Husser, T. O.; Kamman, S.; Dreizler, S.; Brinchmann, J. (Astronomy & Astrophysics, 2023)
Aims. We want to study the population of blue horizontal branch (HB) stars in the centres of globular clusters (GC) for the first time by exploiting the unique combination of MUSE spectroscopy and HST photometry. In this work, we characterize their properties in the GCs ω Cen and NGC 6752. Methods. We use dedicated model atmospheres and grids of synthetic spectra computed using a hybrid LTE/NLTE modeling approach to fit the MUSE spectra of HB stars hotter than 8000 K in both clusters. The spectral fits provide estimates of the effective temperature (Teff), surface gravity (log É¡), and helium abundance of the stars. The model grids are further used to fit the HST magnitudes of the stars, that is, their spectral energy distributions (SEDs). From the SED fits, we derive the average reddening, radius, luminosity, and mass of the stars in our sample. Results. The atmospheric and stellar properties that we derive for the stars in our sample are in good agreement with theoretical expectations. In particular, the stars cooler than 15 000 K closely follow the theoretical predictions on radius, log É¡, and luminosity for helium-normal (Y = 0.25) models. In ω Cen, we show that the majority of these cooler HB stars cannot originate from a helium-enriched population with Y > 0.35. The properties of the hotter stars (radii and luminosities) are still in reasonable agreement with theoretical expectations, but the individual measurements show a large scatter. For these hot stars, we find a mismatch between the effective temperatures indicated from the MUSE spectral fits and the photometric fits, with the latter returning Teff lower by 3000 K. We use three different diagnostics, namely the position of the G-jump and changes in metallicity and helium abundances, to place the onset of diffusion in the stellar atmospheres at Teff between 11 000 and 11 500 K. Our sample includes two stars known as photometric variables; we confirm one to be a bona fide extreme HB object but the other is a blue straggler star. Finally, unlike what has been reported in the literature, we do not find significant differences between the properties (e.g., log É¡, radius, and luminosity) of the stars in the two clusters. Conclusions. We show that our analysis method - combining MUSE spectra and HST photometry of HB stars in GCs - is a powerful tool for characterising their stellar properties. With the availability of MUSE and HST observations of additional GCs, we have a unique opportunity to combine homogeneous spectroscopic and photometric data to study and compare the properties of blue HB stars in different GCs.
CRIS-Team Scopus Importer:2023-09-22
Keywords: Globular clusters: individual: NGC 5139; Globular clusters: individual: NGC 6752; Stars: fundamental parameters; Stars: horizontal-branch

Simulating X-ray observations of galaxy clusters with the X-ray Integral Field Unit onboard the Athena mission - Cucchetti, Edoardo; Pointecouteau, Etienne; Peille, Philippe; Clerc, Nicolas; Rasia, Elena; Biffi, Veronica; Borgani, Stefano; Dolag, Klaus; Wilms, Jörn; Pajot, Francois; Barret, Didier (2018)
The X-ray Integral Field Unit (X-IFU) is the cryogenic imaging spectrometer onboard the ESA L2 mission Athena. With its array of almost 3840 superconducting Transition Edge Sensors micro-calorimeters, the X-IFU will provide spatially resolved (5" over the field of view) high-resolution spectroscopy (2.5 eV FWHM up to 7 keV) in the 0.2-12 keV energy band. These transformational capabilities will allow the X-IFU to probe the Hot and Energetic Universe, and notably measure the physical properties of large-scale structures with unprecedented accuracy. Starting from numerically-simulated massive (1014 Mo) galaxy clusters at different steps of their evolution, we investigate the capabilities of the X-IFU in recovering chemical abundances, redshift and gas temperature spatial distributions across time, making use of full field-of-view End-To-End simulations of X-IFU observations. This work serve as feasibility study for the Chemical Enrichment of the Universe science objective. We show that using 100 ks observations, the X-IFU will provide an unprecedented spatially-accurate knowledge of the physics of the ICM (abundances, temperature, bulk-motion). We also demonstrate that challenges related to the data analysis of extended sources with very high-resolution spectrometers (e.g. binning, line of sight mixing, particle background) need to be thoroughly addressed to maximise the science of the instrument.
Keywords: Athena; X-IFU; End-To-End simulations; galaxy clusters; chemical enrichment

Simulation of cyclotron resonant scattering features The effect of bulk velocity - Schwarm, Fritz-Walter; Schoenherr, G.; Kühnel, Matthias; Wilms, Jörn (2014)
X-ray binary systems consisting of a mass donating optical star and a highly magnetized neutron star, under the right circumstances, show quantum mechanical absorption features in the observed spectra called cyclotron resonant scattering features (CRSFs). We have developed a simulation to model CRSFs using Monte Carlo methods. We calculate Green's tables which can be used to imprint CRSFs to arbitrary X-ray continua. Our simulation keeps track of scattering parameters of individual photons, extends the number of variable parameters of previous works, and allows for more flexible geometries. Here we focus on the influence of bulk velocity of the accreted matter on the CRSF line shapes and positions.

Simulation of Radiative Transfer Within X-ray Microcalorimeter Absorbers - Lorenz, Maximilian; Kirsch, Christian; Peille, P.; Ballhausen, R.; Fioretti,; Lotti, S.; Dauser, Thomas; Wilms, Jörn (Journal of Low Temperature Physics, 2022)
We present Monte Carlo simulations of radiative transfer within the absorbers of X-ray microcalorimeters, utilizing a numerical model for the photon propagation and photon absorption process within the absorber structure. In our model, we include effects of Compton scattering off bound electrons and fluorescence. Scattered or fluorescence photons as well as Auger and photoelectrons escaping the absorber can result in partial energy depositions. By implementing a simplified description of the physical processes compared to existing comprehensive particle transport software frameworks, our model aims to provide representative results at a small computational effort. This approach makes it possible to use our model for quick assessments, parametric studies, and application in other Monte Carlo-based instrument simulators like SIXTE, a software package for X-ray astronomical instrumentation. To study the impact of the energy loss effects on the spectral response of a microcalorimeter, we apply our model to the sensors of the cryogenic X-ray spectrometer X-IFU onboard the future Athena X-ray observatory.
CRIS-Team WoS Importer:2022-06-17

Simultaneous NICER and NuSTAR observations of the ultracompact x-ray binary 4u 1543-624 - Ludlam, R. M.; Jaodand, A. D.; Garcia, Javier; Degenaar, N.; Tomsick, J. A.; Cackett, E. M.; Fabian, A. C.; Gandhi, P.; Buisson, D. J. K.; Shaw, A. W.; Chakrabarty, D. (Astrophysical Journal, 2021)
We present the first joint NuSTAR and NICER observations of the ultracompact X-ray binary (UCXB) 4U 1543 -624 obtained in 2020 April. The source was at a luminosity of L0.5-50 keV = 4.9(D/7 kpc)2 × 1036 erg s-1 and showed evidence of reflected emission in the form of an O VIII line, Fe K line, and Compton hump within the spectrum. We used a full reflection model, known as XILLVERCO, that is tailored for the atypical abundances found in UCXBs, to account for the reflected emission. We tested the emission radii of the O and Fe line components and conclude that they originate from a common disk radius in the innermost region of the accretion disk (Rin . 1.07 RISCO). Assuming that the compact accretor is a neutron star (NS) and the position of the inner disk is the Alfvén radius, we placed an upper limit on the magnetic field strength to be B . 0.7(D/7 kpc) × 108 G at the poles. Given the lack of pulsations detected and position of Rin, it was likely that a boundary layer region had formed between the NS surface and inner edge of the accretion disk with an extent of 1.2 km. This implies a maximum radius of the neutron star accretor of RNS . 12.1 km when assuming a canonical NS mass of 1.4Me.
CRIS-Team Scopus Importer:2021-05-21

Single-dish and VLBI observations of Cygnus X-3 during the 2016 giant flare episode - Egron, Elise; Pellizzoni, A.; Giroletti, M.; Righini, Simona; Stagni, M.; Orlati, Andrea; Migoni, C.; Melis, A.; Concu, R.; Barbas, L.; Buttaccio, S.; Cassaro, Pietro; et al. (Monthly Notices of the Royal Astronomical Society, 2017)
In 2016 September, the microquasar Cygnus X-3 underwent a giant radio flare, which was monitored for 6 d with the Medicina Radio Astronomical Station and the Sardinia Radio Telescope. Long observations were performed in order to follow the evolution of the flare on an hourly scale, covering six frequency ranges from 1.5 to 25.6 GHz. The radio emission reached a maximum of 13.2 +/- 0.7 Jy at 7.2 GHz and 10 +/- 1 Jy at 18.6 GHz. Rapid flux variations were observed at high radio frequencies at the peak of the flare, together with rapid evolution of the spectral index: a steepened from 0.3 to 0.6 (with S-nu alpha nu(-alpha)) within 5 h. This is the first time that such fast variations are observed, giving support to the evolution from optically thick to optically thin plasmons in expansion moving outward from the core. Based on the Italian network (Noto, Medicina and SRT) and extended to the European antennas (Torun, Yebes, Onsala), very long baseline interferometry (VLBI) observations were triggered at 22 GHz on five different occasions, four times prior to the giant flare, and once during its decay phase. Flux variations of 2 h duration were recorded during the first session. They correspond to a mini-flare that occurred close to the core 10 d before the onset of the giant flare. From the latest VLBI observation we infer that 4 d after the flare peak the jet emission was extended over 30 mas.
Keywords: stars: flare; stars: individual: Cyg X-3; radio continuum: stars; X-rays: binaries

SIRENA: Software for Athena X-IFU Event Reconstruction - Ceballos, M. T.; Cobo, B.; Peille, P.; Wilms, Jörn; Brand, Thorsten; Dauser, Thomas; Bandler, S.; Smith, S. (ASTRONOMICAL DATA ANALYSIS SOFTWARE AND SYSTEMS XXVI, 2019)
CRIS-Team WoS Importer:2019-11-29

SIXTE: a generic X-ray instrument simulation toolkit - Dauser, Thomas; Falkner, Sebastian; Lorenz, Maximilian; Kirsch, Christian; Peille, Philippe; Cucchetti, Edoardo; Schmid, Christian; Brand, Thorsten; Oertel, Mirjam; Smith, Randall; Wilms, Jörn (Astronomy & Astrophysics, 2019)
We give an overview of the SImulation of X-ray TElescopes (SIXTE) software package, a generic, mission-independent Monte Carlo simulation toolkit for X-ray astronomical instrumentation. The package is based on a modular approach for the source definition, the description of the optics, and the detector type such that new missions can be easily implemented. The targets to be simulated are stored in a flexible input format called SIMPUT. Based on this source definition, a sample of photons is produced and then propagated through the optics. In order to model the detection process, the software toolkit contains modules for various detector types, ranging from proportional counter and Si-based detectors, to more complex descriptions like transition edge sensor (TES) devices. The implementation of characteristic detector effects and a detailed modeling of the read-out process allow for representative simulations and therefore enable the analysis of characteristic features, such as for example pile-up, and their impact on observations. We present an overview of the implementation of SIXTE from the input source, the imaging, and the detection process, highlighting the modular approach taken by the SIXTE software package. In order to demonstrate the capabilities of the simulation software, we present a selection of representative applications, including the all-sky survey of eROSITA and a study of pile-up effects comparing the currently operating XMM-Newton with the planned Athena-WFI instrument. A simulation of a galaxy cluster with the AthenaX-IFU shows the capability of SIXTE to predict the expected performance of an observation for a complex source with a spatially varying spectrum and our current knowledge of the future instrument.
CRIS-Team WoS Importer:2019-10-11

SN 1987A: Tracing the flux decline and spectral evolution through a comparison of SRG/eROSITA and XMM-Newton observations - Maitra, C.; Haberl, F.; Sasaki, Manami; Maggi, P.; Dennerl, K.; Freyberg, M. J. (Astronomy & Astrophysics, 2022)
Context. SN 1987A is the supernova closest to us observed in the past four centuries. It provides the unique opportunity of witnessing the birth and evolution of a supernova remnant. Monitoring the source in X-rays provides insights into the physics of the shock, the X-ray emitting plasma, and the interaction of the shock with the structures in the circumstellar medium. The source has been monitored by XMM-Newton EPIC-pn from 2007 to 2020. SRG/eROSITA also observed the source during its commissioning phase and first light in September and October 2019. Aims. We investigated the spectral and flux evolution of SN 1987A in X-rays in the last 14 yr up to November 2020 using XMM-Newton and eROSITA observations. Methods. We performed a detailed spectral analysis using a three-component plane-parallel shock model and analysed and modelled the EPIC-pn monitoring and eROSITA observations in a consistent manner. Results. This paper reports a complete and the most recent flux evolution of SN 1987A in the soft (0.5-2 keV) and hard (3-10 keV) X-ray band. The flux in the soft band flattened around 9424 days and then displayed a turnover between 10 142 and 10 493 days, after which it showed a continued decline. At about the same time, a break in the hard-band flux time evolution slope was detected. This implies that the blast wave has now passed beyond the dense structures of the equatorial ring and is expanding farther into more tenuous circumstellar medium. The temporal evolution of the normalisations of the three shock components match the results of hydrodynamical simulations well, which predict a blue supergiant progenitor scenario. The trend in recent epochs indicates that the emission caused by the forward shock after leaving the equatorial ring and by the reverse shock in the ejecta is now becoming more dominant. The elemental abundances in the hot plasma component are significantly higher than those in the cooler component, indicating an origin in the reverse shock that propagates into the ejecta.
CRIS-Team WoS Importer:2022-06-17

SNR surface density distribution in nearby galaxies - Sasaki, Manami; Breitschwerdt, Dieter; Supper, Rodrigo (Astrophysics and Space Science, 2004)
Since supernova remnants (SNRs) are believed to be the primary sources of Galactic cosmic rays (CRs), their distribution in galaxies is an important basis for modelling and understanding the distribution of the CRs and their gamma-ray spectrum. We analysed the radial surface density of X-ray and radio selected SNRs in the Large Magellanic Cloud (LMC) and M 33. Both in X-rays and in radio, the surface densities of the SNRs are in excellent agreement in both galaxies, showing an exponential decay in radius. The results were compared to the SNR distribution in the spiral galaxies M 31 and NGC 6946 as well. The radial scale length of the distribution is 1/4 - 1/3 of the radius of the galaxies, fully consistent with values derived for the Milky Way, the LMC, and M33. Therefore, not only the radio SNRs, but also the X-ray detected SNR sample can be interpreted to be representative for the CR sources within a galaxy.
Keywords: X-rays : galaxies; ISM : supernova remnants; cosmic rays

Space experiment TUS on board the Lomonosov satellite as pathfinder of JEM-EUSO - Adams, J. H.; Ahmad, S.; Albert, J. -N.; Allard, D.; Anchordoqui, L.; Andreev, V.; Anzalone, A.; Arai, Y.; Asano, K.; Ave Pernas, M.; Baragatti, P.; Barrillon, P.; et al. (Experimental Astronomy, 2015)
Space-based detectors for the study of extreme energy cosmic rays (EECR) are being prepared as a promising new method for detecting highest energy cosmic rays. A pioneering space device - the "tracking ultraviolet set-up" (TUS) - is in the last stage of its construction and testing. The TUS detector will collect preliminary data on EECR in the conditions of a space environment, which will be extremely useful for planning the major JEM-EUSO detector operation.
Keywords: Air-shower fluorescence telescope; JEM-EUSO; Pathfinder

Space observations of AA Doradus provide consistent mass determinations. New HW-Vir systems observed with TESS - Baran, A. S.; Ostensen, R. H.; Heber, Ulrich; Irrgang, Andreas; Sanjayan, Sachu; Telting, J. H.; Reed, M. D.; Ostrowski, J. (Monthly Notices of the Royal Astronomical Society, 2021)
We present an overview of eclipsing systems of the HW-Virginis (HW-Vir) type, based on space observations from the Transiting Exoplanet Survey Satellite (TESS) mission. We perform a detailed analysis of the properties of AA Doradus (AA Dor), which was monitored for almost a full year. This excellent time series data set permitted us to search for both stellar pulsations and eclipse timing variations. In addition, we used the high-precision trigonometric parallax from Gaia Early Data Release 3 to make an independent determination of the fundamental stellar parameters. No convincing pulsations were detected down to a limit of 76 parts per million; however, we detected one peak with false alarm probability of 0.2 per cent. 20 s cadences being collected during Year 3 should confirm or reject our detection. From eclipse timing measurements we were able to confirm that the orbital period is stable, with an upper limit to any period change of 5.75 × 10−13 s s−1. The apparent offset of the secondary eclipse is consistent with the predicted Rømer delay when the primary mass is that of a canonical extended horizontal branch star. Using parallax and a spectral energy distribution corroborates that the mass of the primary in AA Dor is canonical, and its radius and luminosity are consistent with an evolutionary state beyond core helium burning. The mass of the secondary is found to be at the limit of hydrogen burning.
CRIS-Team Scopus Importer:2021-10-22
Keywords: Binaries: eclipsing; Binaries: general; Stars: individual: AA Dor; Stars: oscillations; Subdwarfs

Spectral analysis of 1H 0707-495 with XMM-Newton - Dauser, Thomas; Svoboda, Jiri; Schartel, N.; Wilms, Jörn; Dovciak, Michal; Ehle, Matthias; Karas, Vladimir; Santos-Lleo, Maria; Marshall, H. L. (Monthly Notices of the Royal Astronomical Society, 2012)
We present the results of a 500 ks long XMMNewton observation and a 120 ks long quasi-simultaneous Chandra observation of the Narrow-Line Seyfert 1 galaxy 1H 0707-495 performed in 2010 September. Consistent with earlier results by Fabian et al. and Zoghbi et al., the spectrum is found to be dominated by relativistically broadened reflection features from an ionized accretion disc around a maximally rotating black hole. Even though the spectra changed between this observation and earlier XMMNewton observations, the physical parameters of the black hole and accretion disc (i.e. spin and inclination) are consistent between both observations. We show that this reflection spectrum is slightly modified by absorption in a mildly relativistic, highly ionized outflow which changed velocity from around 0.11 c to 0.18 c between 2008 January and 2010 September. Alternative models, in which the spectral shape is dominated by absorption, lead to spectral fits of similar quality, however, the parameters inferred for the putative absorber are unphysical.
Keywords: galaxies: active; galaxies: individual: 1H 0707-495; galaxies: nuclei; X-rays: galaxies

Spectral analysis of the He-enriched sdO-star HD 127493 - Dorsch, Matti; Latour, Marilyn; Heber, Ulrich (DE GRUYTER POLAND SP ZOO, 2018)
The bright sdO star HD127493 is known to be of mixed H/He composition and excellent archival spectra covering both optical and ultraviolet ranges are available. UV spectra play a key role as they give access to many chemical species that do not show spectral lines in the optical, such as iron and nickel. This encouraged the quantitative spectral analysis of this prototypical mixed H/He composition sdO star.We determined atmospheric parameters for HD127493 in addition to the abundance of C, N, O, Si, S, Fe, and Ni in the atmosphere using non-LTE model atmospheres calculated with TLUSTY/SYNSPEC. A comparison between the parallax distance measured by Hipparcos and the derived spectroscopic distance indicate that the derived atmospheric parameters are realistic. From our metal abundance analysis, we find a strong CNO signature and enrichment in iron and nickel.
Keywords: HD127493; hot subdwarf; atmospheric abundances

Spectral and Timing Analysis of NuSTAR and Swift/XRT Observations of the X-Ray Transient MAXI J0637-430 - Lazar, Hadar; Tomsick, John A.; Pike, Sean N.; Bachetti, Matteo; Buisson, Douglas J. K.; Connors, Riley M. T.; Fabian, Andrew C.; Fuerst, Felix; Garcia, Javier; Hare, Jeremy; Jiang, Jiachen; Shaw, Aarran W.; et al. (Astrophysical Journal, 2021)
We present results for the first observed outburst from the transient X-ray binary source MAXI J0637-430. This study is based on eight observations from the Nuclear Spectroscopic Telescope Array (NuSTAR) and six observations from the Neil Gehrels Swift Observatory X-Ray Telescope (Swift/XRT) collected from 2019 November 19 to 2020 April 26 as the 3-79 keV source flux declined from 8.2 x 10(-10) to 1.4 x 10(-12) erg cm(-2) s(-1). We see the source transition from a soft state with a strong disk-blackbody component to a hard state dominated by a power-law or thermal Comptonization component. NuSTAR provides the first reported coverage of MAXI J0637-430 above 10 keV, and these broadband spectra show that a two-component model does not provide an adequate description of the soft-state spectrum. As such, we test whether blackbody emission from the plunging region could explain the excess emission. As an alternative, we test a reflection model that includes a physical Comptonization continuum. Finally, we also test a spectral component based on reflection of a blackbody illumination spectrum, which can be interpreted as a simple approximation to the reflection produced by returning disk radiation due to the bending of light by the strong gravity of the black hole. We discuss the physical implications of each scenario and demonstrate the value of constraining the source distance.
CRIS-Team WoS Importer:2021-11-19

Spectral and Timing Analysis of the Accretion-powered Pulsar 4U 1626-67 Observed with Suzaku and NuSTAR - Iwakiri, Wataru B.; Pottschmidt, Katja; Falkner, Sebastian; Hemphill, Paul B.; Furst, Felix; Nishimura, Osamu; Schwarm, Fritz-Walter; Wolff, Michael T.; Marcu-Cheatham, Diana M.; Chakrabarty, Deepto; Tomsick, John A.; Wilson-Hodge, Colleen A.; et al. (Astrophysical Journal, 2019)
We present an analysis of the spectral shape and pulse profile of the accretion-powered pulsar 4U 1626-67 observed with Suzaku and Nuclear Spectroscopic Telescope Array (NuSTAR) during a spin-up state. The pulsar, which experienced a torque reversal to spin-up in 2008, has a spin period of similar to 7.7 s. Comparing the phase-averaged spectra obtained with Suzaku in 2010 and with NuSTAR in 2015, we find that the spectral shape changed between the two observations: the 3-10 keV flux increased by similar to 5%, while the 30-60 keV flux decreased significantly by similar to 35%. Phase-averaged and phase-resolved spectral analysis shows that the continuum spectrum observed by NuSTAR is well described by an empirical negative and positive power law times exponential continuum with an added broad Gaussian emission component around the spectral peak at similar to 20 keV. Taken together with the observed P. value obtained from the Fermi/gamma-ray burst monitor data, we conclude that the spectral change between the Suzaku and NuSTAR observations was likely caused by an increase in the accretion rate. We also report the possible detection of asymmetry in the profile of the fundamental cyclotron line. Furthermore, we present a study of the energy-resolved pulse profiles using a new relativistic ray tracing code, where we perform a simultaneous fit to the pulse profiles assuming a two-column geometry with a mixed pencil- and fan-beam emission pattern. The resulting pulse profile decompositions enable us to obtain geometrical parameters of accretion columns (inclination, azimuthal and polar angles) and a fiducial set of beam patterns. This information is important to validate the theoretical predictions from radiation transfer in a strong magnetic field.
CRIS-Team WoS Importer:2021-10-18

Spectral and timing evolution of the bright failed outburst of the transient black hole Swift J174510.8-262411 - Del Santo, Melania; Belloni, T. M.; Tomsick, J. A.; Sbarufatti, Boris; Bel, M. Cadolle; Casella, Piergiorgio; Castro-Tirado, A.; Corbel, S.; Grinberg, Victoria; Homan, J.; Kalemci, E.; Motta, Sara Elisa; et al. (Monthly Notices of the Royal Astronomical Society, 2016)
We studied time variability and spectral evolution of the Galactic black hole transient Swift J174510.8-262411 during the first phase of its outburst. INTEGRAL and Swift observations collected from 2012 September 16 until October 30 have been used. The total squared fractional rms values did not drop below 5 per cent and quasi-periodic oscillations (QPOs), when present, were type-C, indicating that the source never made the transition to the soft-intermediate state. Even though the source was very bright (up to 1 Crab in hard X-rays), it showed a so called failed outburst as it never reached the soft state. XRT and IBIS broad-band spectra, well represented by a hybrid thermal/non-thermal Comptonization model, showed physical parameters characteristic of the hard and intermediate states. In particular, the derived temperature of the geometrically thin disc blackbody was about 0.6 keV at maximum. We found a clear decline of the optical depth of the corona electrons (close to values of 0.1), as well as of the total compactness ratio l/l. The hard-to-hard/intermediate state spectral transition is mainly driven by the increase in the soft photon flux in the corona, rather than small variations of the electron heating. This, associated with the increasing of the disc temperature, is consistent with a disc moving towards the compact object scenario, i.e. the truncated-disc model. Moreover, this scenario is consistent with the decreasing fractional squared rms and increasing of the noise and QPO frequency. In our final group of observations, we found that the contribution from the non-thermal Comptonization to the total power supplied to the plasma is 0.59 and that the thermal electrons cool to kT < 26 keV.
Keywords: Accretion; accretion discs; Black hole physics; Gamma-rays: general; Radiation mechanisms: non-thermalI; Stars: individual: Swift J174510.8-262411; X-rays: binaries

SPECTRAL AND TIMING NATURE OF THE SYMBIOTIC X-RAY BINARY 4U 1954+319: THE SLOWEST ROTATING NEUTRON STAR IN AN X-RAY BINARY SYSTEM - Enoto, Teruaki; Sasano, Makoto; Yamada, Shin'Ya; Tamagawa, Toru; Makishima, Kazuo; Pottschmidt, Katja; Marcu, Diana; Corbet, Robin H. D.; Fuerst, Felix; Wilms, Jörn (Astrophysical Journal, 2014)
The symbiotic X-ray binary (SyXB) 4U 1954+ 319 is a rare system hosting a peculiar neutron star (NS) and an M-type optical companion. Its similar to 5.4 hr NS spin period is the longest among all known accretion-powered pulsars and exhibited large (similar to 7%) fluctuations over 8 yr. A spin trend transition was detected with Swift/BAT around an X-ray brightening in 2012. The source was in quiescent and bright states before and after this outburst based on 60 ks Suzaku observations in 2011 and 2012. The observed continuum is well described by a Comptonized model with the addition of a narrow 6.4 keV Fe-K alpha line during the outburst. Spectral similarities to slowly rotating pulsars in high-mass X-ray binaries, its high pulsed fraction (similar to 60%-80%), and the location in the Corbet diagram favor high B-field (greater than or similar to 10(12) G) over a weak field as in low-mass X-ray binaries. The observed low X-ray luminosity (10(33)-10(35) erg s(-1)), probable wide orbit, and a slow stellar wind of this SyXB make quasi-spherical accretion in the subsonic settling regime a plausible model. Assuming a similar to 10(13) G NS, this scheme can explain the similar to 5.4 hr equilibrium rotation without employing the magnetar-like field (similar to 10(16) G) required in the disk accretion case. The timescales of multiple irregular flares (similar to 50 s) can also be attributed to the free-fall time from the Alfven shell for a similar to 10(13) G field. A physical interpretation of SyXBs beyond the canonical binary classifications is discussed.
Keywords: accretion; accretion disks; binaries: symbiotic; magnetic fields; stars: individual (3A 1954+319; 4U 1954+319); stars: neutron; X-rays : binaries

Spectral energy distributions and colours of hot subluminous stars - Heber, Ulrich; Irrgang, Andreas; Schaffenroth, Johannes (DE GRUYTER POLAND SP ZOO, 2018)
Photometric surveys at optical, ultraviolet, and infrared wavelengths provide ever-growing datasets as major surveys proceed. Colour-colour diagrams are useful tools to identify classes of star and provide large samples. However, combining all photometric measurements of a star into a spectral energy distribution will allow quantitative analyses to be carried out. We demonstrate how to construct and exploit spectral energy distributions and colours for sublumious B (sdB) stars. The aim is to identify cool companions to hot subdwarfs and to determine atmospheric parameters of apparently single sdB stars as well as composite spectrum sdB binaries. We analyse two sdB stars with high-quality photometric data which serve as our benchmarks, the apparently single sdB HD205805 and the sdB + K5 binary PG 0749+658, briefly present preliminary results for the sample of 142 sdB binaries with known orbits, and discuss future prospects from ongoing all-sky optical space-(Gaia) and ground-based (e.g. SkyMapper) as well as NIR surveys.
Keywords: stars: early type; subdwarfs; Techniques: potometric

Spectral formation in accreting X-ray pulsars: bimodal variation of the cyclotron energy with luminosity - Becker, P. A.; Klochkov, D.; Schoenherr, G.; Nishimura, O.; Ferrigno, C.; Caballero, I.; Kretschmar, Peter; Wolff, M. T.; Wilms, Jörn; Staubert, R. (Astronomy & Astrophysics, 2012)
Context. Accretion-powered X-ray pulsars exhibit significant variability of the cyclotron resonance scattering feature (CRSF) centroid energy on pulse-to-pulse timescales, and also on much longer timescales. Two types of spectral variability are observed. For sources in group 1, the CRSF energy is negatively correlated with the variable source luminosity, and for sources in group 2, the opposite behavior is observed. The physical basis for this bimodal behavior is currently not well understood.Aims. We explore the hypothesis that the accretion dynamics in the group 1 sources is dominated by radiation pressure near the stellar surface, and that Coulomb interactions decelerate the gas to rest in the group 2 sources.Methods. We derive a new expression for the critical luminosity, L-crit, such that radiation pressure decelerates the matter to rest in sources with X-ray luminosity L-X > L-crit. The formula for L-crit is based on a simple physical model for the structure of the accretion column in luminous X-ray pulsars that takes into account radiative deceleration, the energy dependence of the cyclotron cross section, the thermodynamics of the accreting gas, the dipole structure of the pulsar magnetosphere, and the diffusive escape of radiation through the column walls. We show that for typical neutron star parameters, L-crit = 1.5 x 10(37)B(12)(16/15) erg s(-1), where B-12 is the surface magnetic field strength in units of 10(12) G.Results. The formula for the critical luminosity is evaluated for five sources, using the maximum value of the CRSF centroid energy to estimate the surface magnetic field strength B-12. The results confirm that the group 1 sources are supercritical (L-X > L-crit) and the group 2 sources are subcritical (L-X < L-crit), although the situation is less clear for those highly variable sources that cross over the line L-X = L-crit. We also explain the variation of the CRSF energy with luminosity as a consequence of the variation of the characteristic emission height. The sign of this dependence is opposite in the supercritical and subcritical cases, hence creating the observed bimodal behavior.Conclusions. We have developed a new model for the critical luminosity in accretion-powered X-ray pulsars that explains the bimodal dependence of the CRSF centroid energy on the X-ray luminosity L-X. Our model provides a physical basis for the observed variation of the CRSF energy as a function of L-X for both the group 1 (supercritical) and the group 2 (subcritical) sources as a result of the variation of the emission height in the column.
Keywords: stars: neutron; pulsars: general; radiative transfer; accretion; accretion disks

SPECTRAL STATE DEPENDENCE OF THE 0.4-2 MEV POLARIZED EMISSION IN CYGNUS X-1 SEEN WITH INTEGRAL/IBIS, AND LINKS WITH THE AMI RADIO DATA - Rodriguez, Jerome; Grinberg, Victoria; Laurent, Philippe; Bel, Marion Cadolle; Pottschmidt, Katja; Pooley, Guy; Bodaghee, Arash; Wilms, Jörn; Gouiffes, Christian (Astrophysical Journal, 2015)
Polarization of the greater than or similar to 400 keV hard tail of the microquasar Cygnus X-1 has been independently reported by INTEGRAL/Imager on Board the INTEGRAL Satellite (IBIS), and INTEGRAL/SPectrometer on INTEGRAL and interpreted as emission from a compact jet. These conclusions were, however, based on the accumulation of all INTEGRAL data regardless of the spectral state. We utilize additional INTEGRAL exposure accumulated until 2012 December, and include the AMI/Ryle (15 GHz) radio data in our study. We separate the observations into hard, soft, and intermediate/transitional states and detect radio emission from a compact jet in hard and intermediate states (IS), but not in the soft. The 10-400 keV INTEGRAL (JEM-X and IBIS) state resolved spectra are well modeled with thermal Comptonization and reflection components. We detect a hard tail in the 0.4-2 MeV range for the hard state only. We extract the state dependent polarigrams of Cyg X-1, which are all compatible with no or an undetectable level of polarization except in the 400-2000 keV range in the hard state where the polarization fraction is 75% +/- 32% and the polarization angle 40.degrees 0 +/- 14.degrees 3. An upper limit on the 0.4-2 MeV soft state polarization fraction is 70%. Due to the short exposure, we obtain no meaningful constraint for the IS. The likely detection of a >400 keV polarized tail in the hard state, together with the simultaneous presence of a radio jet, reinforce the notion of a compact jet origin of the >400 keV emission.
Keywords: accretion; accretion disks; black hole physics; stars: individual (Cyg X-1); X-rays: stars

Spectroscopic and photometric analysis of the HW Vir star PTF1 J011339.09+225739.1 - Woltz, Maximilian; Kupfer, Thomas; Drechsel, Horst; Heber, Ulrich; Irrgang, Andreas; Hermes, J. J.; Bloemen, Steven; Levitan, D.; Dhillon, Vik S.; Marsh, Thomas (DE GRUYTER POLAND SP ZOO, 2018)
HW Vir systems are rare eclipsing binary systems including a subdwarf B star (sdB) with a faint companion, mostly M-dwarfs. Up to now, 19 HW Vir systems have been published, three of them with substellar companions. We report the spectroscopic as well as photometric observation of the eclipsing sdB binary PTF1 J011339.09+225739.1 (PTF1 J0113) in a close (a=0.722 +/- 0.023 R-circle dot), short period (P = 0.0933731(3)d) orbit. A quantitative spectral analysis of the sdB yields T-eff =29280 +/- 720 K, log(g)=5.77 +/- 0.09 dex, and log(y)=-2.32 +/- 0.12. The circular orbital velocity of the sdB of K-1 =74.2 +/- 1.7 km s(-1) is derived from the radial velocity curve. Except for the strong reflection effect, no other light contribution of the companion could be detected. The light curves - recorded with ULTRACAM - were analyzed using the Wilson-Devinney code. We find an inclination angle of i=79.88 +/- 0.18 degrees. Because our first attempts to determine q failed, we calculated large grids of synthetic lightcurves for several mass ratios. Because of degeneracy, good solutions for different mass ratios were found - the one at q = 0.24 is consistent with the sdB's canonical mass (M-sdB = 0.47 M-circle dot). Accordingly, the mass of the companion is M-2=0.112 +/- 0.003 M-circle dot. The radii of the two components were also derived: R-sdB=0.178 +/- 0.006 R-circle dot and R-2 = 0.158 +/- 0.009 R-circle dot. Thus, the results for the secondary are consistent with an M-dwarf as secondary.
Keywords: subdwarfs; binaries: eclipsing; stars: early-type; stars: evolution; stars: fundamental parameters; stars: horizontal-branch

Spectroscopic twin to the hypervelocity sdO star US 708 and three fast sdB stars from the Hyper-MUCHFUSS project - Ziegerer, Eva; Heber, Ulrich; Geier, Stephan; Irrgang, Andreas; Kupfer, Thomas; Fuerst, F.; Schaffenroth, Johannes (Astronomy & Astrophysics, 2017)
Important tracers for the dark matter halo of the Galaxy are hypervelocity stars (HVSs), which are faster than the local escape velocity of the Galaxy and their slower counterparts, the high-velocity stars in the Galactic halo. Such HVSs are believed to be ejected from the Galactic centre (GC) through tidal disruption of a binary by the super-massive black hole (Hills mechanism). The Hyper-MUCHFUSS survey aims at finding high-velocity potentially unbound hot subdwarf stars. We present the spectroscopic and kinematical analyses of a He-sdO as well as three candidates among the sdB stars using optical Keck/ESI and VLT (X-shooter, FORS) spectroscopy. Proper motions are determined by combining positions from early-epoch photographic plates with those derived from modern digital sky surveys. The Galactic rest frame velocities range from 203 km s(-1) to 660 km s(-1), indicating that most likely all four stars are gravitationally bound to the Galaxy. With T-eff = 47 000 K and a surface gravity of log g = 5 : 7, SDSS J205030.39-061957.8 (J2050) is a spectroscopic twin of the hypervelocity He-sdO US 708. As for the latter, the GC is excluded as a place of origin based on the kinematic analysis. Hence, the Hills mechanism can be excluded for J2050. The ejection velocity is much more moderate (385 +/- 79 km s(-1)) than that of US 708 (998 +/- 68 km s(-1)). The binary thermonuclear supernova scenario suggested for US 708 would explain the observed properties of J2050 very well without pushing the model parameters to their extreme limits, as required for US 708. Accordingly, the star would be the surviving donor of a type Ia supernova. Three sdB stars also showed extreme kinematics; one could be a HVS ejected from the GC, whereas the other two could be ejected from the Galactic disk through the binary supernova mechanism. Alternatively, they might be extreme halo stars.
Keywords: stars: kinematics and dynamics; subdwarfs; stars: atmospheres; Galaxy: halo

Spectroscopy of hot subdwarf binaries - Kreuzer, Simon; Irrgang, Andreas; Heber, Ulrich (DE GRUYTER POLAND SP ZOO, 2018)
We present a status report of our spectroscopic analysis of subdwarf binaries consisting of a subdwarf and a F/G/K-type main-sequence companion. These systems selected from SDSS photometry show significant excess in the (infra-)red which can not be explained by interstellar reddening. Inspection of SDSS spectra revealed that most of them are composite spectrum sdB binaries. Once their spectra are disentangled, a detailed spectral analysis can be carried out. It reveals T-eff, log g and the metal abundance of each individual star. The cool companion is of particular interest, because its spectrum reveals the original chemical composition of the binary.

Spectro-timing analysis of Cygnus X-1 during a fast state transition - Böck, Moritz; Grinberg, Victoria; Pottschmidt, K.; Hanke, Manfred; Nowak, M. A.; Markoff, S. B.; Uttley, P.; Rodriguez, Jerome; Pooley, G. G.; Suchy, S.; Rothschild, R. E.; Wilms, Jörn (Astronomy & Astrophysics, 2011)
We present the analysis of two long, quasi-uninterrupted RXTE observations of Cygnus X-1 that span several days within a 10 d interval. The spectral characteristics during this observation cover the region where previous observations have shown the source to be most dynamic. Despite that the source behavior on time scales of hours and days is remarkably similar to that on year time scales. This includes a variety of spectral/temporal correlations that previously had only been observed over CygX-1's long-term evolution. Furthermore, we observe a full transition from a hard to a soft spectral state that occurs within less than 2.5 h - shorter than previously reported for any other similar CygX-1 transition. We describe the spectra with a phenomenological model dominated by a broken power law, and we fit the X-ray variability power spectra with a combination of a cutoff power law and Lorentzian components. The spectral and timing properties are correlated: the power spectrum Lorentzian components have an energy-dependent amplitude, and their peak frequencies increase with photon spectral index. Averaged over 3.2-10 Hz, the time lag between the variability in the 4.5-5.7 keV and 9.5-15 keV bands increases with decreasing hardness when the variability is dominated by the Lorentzian components during the hard state. The lag is small when there is a large power law noise contribution, shortly after the transition to the soft state. Interestingly, the soft state not only shows the shortest lags, but also the longest lags when the spectrum is at its softest and faintest. We discuss our results in terms of emission models for black hole binaries.
Keywords: X-rays: binaries; X-rays: individuals: CygX-1

SPECTRO-TIMING STUDY of GX 339-4 in A HARD INTERMEDIATE STATE - Furst, F.; Grinberg, Victoria; Tomsick, J. A.; Bachetti, Matteo; Boggs, S. E.; Brightman, M.; Christensen, F. E.; Craig, W. W.; Gandhi, P.; Grefenstette, B.; Hailey, C. J.; Harrison, F. A.; et al. (Astrophysical Journal, 2016)
We present an analysis of Nuclear Spectroscopic Telescope Array observations of a hard intermediate state of the transient black hole GX 339-4 taken in 2015 January. With the source softening significantly over the course of the 1.3 day long observation we split the data into 21 sub-sets and find that the spectrum of all of them can be well described by a power-law continuum with an additional relativistically blurred reflection component. The photon index increases from ∼1.69 to ∼1.77 over the course of the observation. The accretion disk is truncated at around nine gravitational radii in all spectra. We also perform timing analysis on the same 21 individual data sets, and find a strong type-C quasi-periodic oscillation (QPO), which increases in frequency from ∼0.68 to ∼1.05 Hz with time. The frequency change is well correlated with the softening of the spectrum. We discuss possible scenarios for the production of the QPO and calculate predicted inner radii in the relativistic precession model as well as the global disk mode oscillations model. We find discrepancies with respect to the observed values in both models unless we allow for a black hole mass of ∼100 , which is highly unlikely. We discuss possible systematic uncertainties, in particular with the measurement of the inner accretion disk radius in the relativistic reflection model. We conclude that the combination of observed QPO frequencies and inner accretion disk radii, as obtained from spectral fitting, is difficult to reconcile with current models.

Spectrum-RG astrophysical project - Pavlinsky, M.; Sunyaev, R.; Churazov, Eugene; Vikhlinin, A.; Sazonov, Sergey; Revnivtsev, M.; Arefiev, V.; Lapshov, I.; Akimov, V.; Levin, V.; Buntov, M.; Semena, N.; et al. (2009)
The Spectrum-Roentgen-Gamma mission will be launched in the 2012 year into a L2 orbit with Soyuz launcher and Fregat buster from Baikonur. The mission will conduct all-sky survey with X-ray mirror telescopes eROSITA and ART-XC up to 11 keV. It will allow detection of about 100 thousand clusters of galaxies and discovery large scale Universe structure. It will also discover all obscured accreting Black Holes in nearby galaxies and many (about 3 millions) new distant AGN. Then it is planned to observe dedicated sky regions with high sensitivity and thereafter to perform follow-up pointed observations of selected sources.
Keywords: X-ray astrophysical mission; X-ray telescope; all-sky X-ray survey

Sperm whale long-range echolocation sounds revealed by ANTARES, a deep-sea neutrino telescope - Andre, Michel; Caballe, A.; Van Der Schaar, M.; Solsona, A.; Houegnigan, L.; Zaugg, S.; Sanchez, A. M.; Castell, J. V.; Sole, Marta; Vila, F.; Djokic, D.; Adrian-Martinez, S.; et al. (Scientific Reports, 2017)
Despite dedicated research has been carried out to adequately map the distribution of the sperm whale in the Mediterranean Sea, unlike other regions of the world, the species population status is still presently uncertain. The analysis of two years of continuous acoustic data provided by the ANTARES neutrino telescope revealed the year-round presence of sperm whales in the Ligurian Sea, probably associated with the availability of cephalopods in the region. The presence of the Ligurian Sea sperm whales was demonstrated through the real-time analysis of audio data streamed from a cabled-to-shore deep-sea observatory that allowed the hourly tracking of their long-range echolocation behaviour on the Internet. Interestingly, the same acoustic analysis indicated that the occurrence of surface shipping noise would apparently not condition the foraging behaviour of the sperm whale in the area, since shipping noise was almost always present when sperm whales were acoustically detected. The continuous presence of the sperm whale in the region confirms the ecological value of the Ligurian sea and the importance of ANTARES to help monitoring its ecosystems.

SRGA J124404.1-632232/SRGU J124403.8-632231: New X-ray pulsar discovered in the all-sky survey by the SRG - Doroshenko, V.; Staubert, R.; Maitra, C.; Rau, A.; Haberl, F.; Santangelo, A.; Schwope, A.; Wilms, Jörn; Buckley, D. A. H.; Semena, A.; Mereminskiy, I.; Lutovinov, A.; et al. (Astronomy & Astrophysics, 2022)
Ongoing all-sky surveys by the eROSITA and the Mikhail Pavlinsky ART-XC telescopes on board the Spectrum-RoentgenGamma (SRG) mission have already revealed over a million of X-ray sources. One of them, SRGA J124404.1-632232/ SRGU J124403.8-632231, was detected as a new source in the third (of the planned eight) consecutive X-ray surveys by ART-XC. Based on the properties of the identified optical counterpart, it was classified as a candidate X-ray binary. We report on the follow-up observations of this source with the Nuclear Spectroscopic Telescope Array, the Neil Gehrels Swift Observatory, and the Southern African Large Telescope, which allowed us to unambiguously confirm the initial identification and establish SRGU J124403.8-632231 as a new X-ray pulsar with a spin period of -538 s and a Be-star companion, making it one of the first Galactic X-ray pulsars discovered by the SRG.
CRIS-Team WoS Importer:2022-06-17

SRG/ART-XC, Swift, NICER, and NuSTAR study of different states of the transient X-ray pulsar MAXI J0903-531 - Tsygankov, Sergey S.; Molkov, Sergey; Doroshenko, Victor; Mushtukov, Alexander A.; Mereminskiy, Ilya A.; Semena, Andrei N.; Thalhammer, Philipp; Wilms, Jörn; Lutovinov, Alexander A. (Astronomy & Astrophysics, 2022)
The results of the broadband spectral and timing study of the recently discovered transient X-ray pulsar MAXI J0903-531 in a wide range of luminosities that differ by a factor of similar to 30 are reported. The observed X-ray spectrum in both states can be described as a classical pulsar-like spectrum consisting of a power law with a high-energy cutoff. We argue that the absence of the spectrum transformation to the two-hump structure that is expected at low fluxes indicates that the magnetic field of the neutron star is relatively weak below (2-3) x 10(12) G. This estimate is consistent with other indirect constraints and non-detection of any absorption features that might be interpreted as a cyclotron absorption line. The timing analysis of the NuSTAR data revealed only slight variations of a single-peaked pulse profile of the source as a function of the energy band and mass accretion rate. In both intensity states, the pulsed fraction increases from 40% to roughly 80% with the energy. Finally, we were also able to obtain the orbital solution for the binary system using data from the Fermi/GBM, NICER, and NuSTAR instruments.
CRIS-Team WoS Importer:2022-06-17

SRG/eROSITA and XMM-Newton observations of Vela Jr - Camilloni, Francesco; Becker, Werner; Predehl, Peter; Dennerl, Konrad; Freyberg, Michael; Mayer, Martin G.F.; Sasaki, Manami (Astronomy & Astrophysics, 2023)
Context. The Vela supernova remnant (SNR) complex is a region containing at least three SNRs: Vela, Puppis A, and Vela Jr. With the launch of the spectro-imaging X-ray telescope eROSITA on board the Spectrum-Röntgen-Gamma (SRG) mission, it became possible to observe the one degree wide Vela Jr in its entirety. Although several previous pointed Chandra and XMM-Newton observations are available, it is only the second time after the ROSAT all-sky survey that the whole remnant was observed in X-rays with homogeneous sensitivity. Aims. Vela Jr is one of the few remnants emitting in the TeV band, making it an important object in shock acceleration studies. However, the age and distance determination using X-ray emission is largely hampered by the presence of the Vela SNR along the same line. With the eROSITA data set our aim is to characterize the emission of Vela Jr and distinguish it from Vela emission, and also to characterize the spectral emission of the inner remnant. Methods. We processed the eROSITA data dividing the whole remnant into seven different regions. In addition, images of the whole remnant were employed to pinpoint the position of the geometric center and constrain the proper motion of the CCO. We also employed archival XMM-Newton pointed observations of the NW rim to determine the cutoff energy of the electrons and the expansion velocity. Results. We find the magnetic field can vary between 2 µG and 16 µG in the NW rim. We also find that the remnant spectrum is uniformly featureless in most regions, except for two inner regions where an extra thermal model component improves the fit. We obtain new coordinates for the geometric remnant center, resulting in a separation of only 35.2 ± 15.8′′ from the position of the CCO. As a result, we reinforce the association between the CCO and a proposed faint optical–IR counterpart.
CRIS-Team Scopus Importer:2023-05-26
Keywords: ISM: supernova remnants; shock waves; X-rays: general; X-rays: ISM

SRG/eROSITA status and operations during the first four all-sky surveys - Coutinho, D.; Ramos-Ceja, M. E.; Dennerl, K.; Haberl, F.; Meidinger, N.; Merloni, A.; Predehl, P.; Stewart, I.; Freyberg, M.; Bornemann, W.; Brunner, H.; Burwitz, V.; et al. (Proceedings of SPIE - The International Society for Optical Engineering, 2022)
eROSITA (extended ROentgen Survey with an Imaging Telescope Array) is the soft X-ray scientific payload on board the SRG (Spektrum-Roentgen-Gamma) mission. It was successfully launched from Baikonur in July 2019. Following a 101 days cruise phase, SRG reached its final orbit around the Sun-Earth Lagrangian point L2, from where it has carried out already four full-sky surveys. eROSITA is a complex instrument composed of seven identical co-aligned X-ray telescopes with a focal length of 1600mm and an aperture of 350mm. Each telescope is equipped with an independent CCD camera. The cold redundant ITC (Interface and Thermal Controller) manages all seven cameras as well as the thermal control of the telescope and the interface to the spacecraft. The cruise phase of SRG was used to verify that all systems had survived launch and no degradation in the functionality was present. Following that, the main science mission, comprised of an early Calibration and Performance Verification Phase, followed by the all-sky survey. This paper presents the performance of the eROSITA telescope during the first four complete all-sky surveys. It presents the challenges encountered during the telescope operations as well as the operations and mitigation strategies put in place to understand or minimize the effects of the space environment in L2, such as micrometeoroid hits and radiation damage of the detectors.
CRIS-Team Scopus Importer:2022-11-04
Keywords: all-sky survey; eROSITA; L2; operations; space telescope; Spectrum-Roentgen-Gamma; SRG; X-ray telescope

SRG/eROSITA-triggered XMM-Newton observations of three Be/X-ray binaries in the LMC: Discovery of X-ray pulsations - Haberl, F.; Maitra, C.; Kaltenbrunner, D.; Buckley, D. A.H.; Monageng, I. M.; Udalski, A.; Doroshenko, V.; Ducci, L.; Kreykenbohm, Ingo; Maggi, P.; Rau, A.; Vasilopoulos, G.; et al. (Astronomy & Astrophysics, 2023)
Context. Using data from eROSITA, the soft X-ray instrument aboard Spectrum-Roentgen-Gamma (SRG), we report the discovery of two new hard transients, eRASSU J050810.4-660653 and eRASSt J044811.1-691318, in the Large Magellanic Cloud. We also report the detection of the Be/X-ray binary RX J0501.6-7034 in a bright state. Aims. We initiated follow-up observations to investigate the nature of the new transients and to search for X-ray pulsations coming from RX J0501.6-7034. Methods. We analysed the X-ray spectra and light curves from our XMM-Newton observations, obtained optical spectra using the South African Large Telescope to look for Balmer emission lines and utilised the archival data from the Optical Gravitational Lensing Experiment (OGLE) for the long-term monitoring of the optical counterparts. Results. We find X-ray pulsations for eRASSU J050810.4-660653, RX J0501.6-7034, and eRASSt J044811.1-691318 of 40.6 s, 17.3 s, and 784 s, respectively. The Hα emission lines with equivalent widths of -10.4 Å (eRASSU J050810.4-660653) and -43.9 Å (eRASSt J044811.1-691318) were measured, characteristic for a circumstellar disc around Be stars. The OGLE I- and V-band light curves of all three systems exhibit strong variability. A regular pattern of deep dips in the light curves of RX J0501.6-7034 suggests an orbital period of ∼451 days. Conclusions. We identify the two new hard eROSITA transients eRASSU J050810.4-660653 and eRASSt J044811.1-691318 and the known Be/X-ray binary RX J0501.6-7034 as Be/X-ray binary pulsars.
CRIS-Team Scopus Importer:2023-03-24
Keywords: Be; Galaxies: individual: LMC; Stars: emission-line; Stars: neutron; X-rays: binaries

SRG/eROSITA X-ray shadowing study of giant molecular clouds - Yeung, M. C.H.; Freyberg, M. J.; Ponti, G.; Dennerl, K.; Sasaki, Manami; Strong, A. (Astronomy & Astrophysics, 2023)
Context. SRG/eROSITA is situated in a halo orbit around L2 where the highly variable solar wind charge exchange (SWCX) emission from Earth's magnetosheath is expected to be negligible. The soft X-ray foreground emissions from the local hot bubble (LHB) and the remaining heliospheric SWCX emissions could be studied in unprecedented detail with eROSITA All-Sky Survey (eRASS) data in a 6-month cadence and better spectral resolution than ROSAT. Aims. We aim to use eRASS data of the sight lines towards three giant molecular clouds away from the Galactic plane to isolate and study the soft X-ray diffuse foreground emission. These X-ray shadows will serve as calibration baselines for the future three-dimensional structural study of the LHB. Methods. We conducted spectral analysis on the diffuse X-ray spectra of these clouds from the first four eRASSs to estimate and separate the heliospheric SWCX contribution from the LHB emission. Results. We find the density of the LHB to be independent of the sight line with ne 4×10-3 cm-3, but not the temperature. We report a lower temperature of kTLHB = 0.084 ± 0.004 keV towards Chamaeleon II & III (Cha II & III) than Ophiuchus (Oph) and Corona Australis (CrA), in which we measured 0.102 ± 0.006 and 0.112 ± 0.009 keV, respectively. We measured the emission measure of the LHB to be 2×10-3 cm-6 pc at medium Galactic latitudes (|b| 20). A monotonic increase in the SWCX contribution has been observed since the start of 2020, coincidental with the beginning of solar cycle 25. For Oph, SWCX has dominated the LHB in the 0.3-0.7 keV band intensity since eRASS2. We observed lower SWCX contributions in Cha II & III and CrA, consistent with the expected decreasing solar wind ion density at high heliographic latitudes.
CRIS-Team Scopus Importer:2023-08-11
Keywords: ISM: bubbles; ISM: clouds; Solar wind; X-rays: diffuse background; X-rays: ISM

Staring at 4U 1909+07 with Suzaku - Fürst, Felix; Pottschmidt, K.; Kreykenbohm, Ingo; Müller, Sebastian; Kühnel, Matthias; Wilms, Jörn; Rothschild, R. E. (Astronomy & Astrophysics, 2012)
We present an analysis of the neutron star high mass X-ray binary (HMXB) 4U 1909+07 mainly based on Suzaku data. We extend the pulse period evolution, which behaves in a random-walk like manner, indicative of direct wind accretion. Studying the spectral properties of 4U 1909+07 between 0.5 to 90 keV we find that a power-law with an exponential cutoff can describe the data well, when additionally allowing for a blackbody or a partially covering absorber at low energies.We find no evidence for a cyclotron resonant scattering feature (CRSF), a feature seen in many other neutron star HMXBs sources. By performing pulse phase resolved spectroscopy we investigate the origin of the strong energy dependence of the pulse profile, which evolves from a broad two-peak profile at low energies to a profile with a single, narrow peak at energies above 20 keV. Our data show that it is very likely that a higher folding energy in the high energy peak is responsible for this behavior. This in turn leads to the assumption that we observe the two magnetic poles and their respective accretion columns at different phases, and that these accretion columns have slightly different physical conditions.
Keywords: accretion; accretion disks; X-rays: binaries; stars: neutron

Statistical properties of flux variations in blazar light curves at GeV and TeV energies - Wagner, Sarah M.; Burd, P. R.; Dorner, D.; Mannheim, K.; Buson, S.; Gokus, Andrea; Madejski, G.; Scargle, J. D.; Arbet-Engels, A.; Baack, D.; Balbo, M.; Biederbeck, N.; et al. (Proceedings of Science, 2022)
Despite numerous detections of individual flares, the physical origin of the rapid variability observed from blazars remains uncertain. Using Bayesian blocks and the Eisenstein-Hut HOP algorithm, we characterize flux variations of high significance in the γ-ray light curves of two samples of blazars. Daily binned long-term light curves of TeV-bright blazars observed with the First G-APD Cherenkov Telescope (FACT) are compared to those of GeV-bright blazars observed with the Large Area Telescope on board the Fermi Gamma-ray Space Telescope (Fermi-LAT). We find no evidence for systematic asymmetry of the flux variations based on the derived rise and decay time scales. Additionally, we show that the daily-binned blazar light curves can be described by an exponential stochastic Ornstein-Uhlenbeck process with parameters depending on energy. Our analysis suggests that the flux variability in both samples is a superposition of faster fluctuations. This is, for instance, challenging to explain by shock-acceleration but expected for magnetic reconnection.
CRIS-Team Scopus Importer:2022-12-23

StrayCats: A Catalog of NuSTAR Stray Light Observations - Grefenstette, Brian W.; Ludlam, Renee M.; Thompson, Ellen T.; Garcia, Javier; Hare, Jeremy; Jaodand, Amruta D.; Krivonos, Roman A.; Madsen, Kristin K.; Mastroserio, Guglielmo; Slaughter, Catherine M.; Tomsick, John A.; Wik, Daniel; et al. (Astrophysical Journal, 2021)
We present StrayCats, a catalog of NuSTAR stray light observations of X-ray sources. Stray light observations arise for sources 1 -4 away from the telescope pointing direction. At this off-axis angle, X-rays pass through a gap between the optics and aperture stop and so do not interact with the X-ray optics; instead, they directly illuminate the NuSTAR focal plane. We have systematically identified and examined over 1400 potential observations resulting in a catalog of 436 telescope fields and 78 stray light sources that have been identified. The sources identified include historically known persistently bright X-ray sources, X-ray binaries in outburst, pulsars, and type I X-ray bursters. In this paper, we present an overview of the catalog, how we identified the StrayCats sources, and the analysis techniques required to produce high-level science products. Finally, we present a few brief examples of the science quality of these unique data.
CRIS-Team Scopus Importer:2021-04-09

Stripped Red Giants - Helium Core White Dwarf Progenitors and their sdB Siblings - Heber, Ulrich (2017)
Some gaps in the mosaic of binary star evolution have recently been filled by the discoveries of helium-core white dwarf progenitors (often called extremely low mass (ELM) white dwarfs) as stripped cores of first-giant branch objects. Two varieties can be distinguished. One class is made up by SB1 binaries, companions being white dwarfs as well. Another class, the so-called EL CVn stars, are composite spectrum binaries, with A-Type companions. Pulsating stars are found among both classes. A riddle is posed by the apparently single objects. There is a,one-to-one correspondence of the phenomena found for these new classes of star to those observed for sdB stars. In fact, standard evolutionary scenarios explain the origin of sdB stars as red giants that have been stripped close to the tip of first red giant branch. A subgroup of subluminous B stars can also be identified as stripped helium-cores of red giants. They form an extension of the ELM sequence to higher temperatures. Hence low mass white dwarfs of helium cores and sdB stars in binaries are close relatives in terms of stellar evolution.

Studying the Reflection Spectra of the New Black Hole X-Ray Binary Candidate MAXI J1631-479 Observed by NuSTAR: A Variable Broad Iron Line Profile - Xu, Yanjun; Harrison, Fiona A.; Tomsick, John A.; Walton, Dominic J.; Barret, Didier; Garcia, Javier; Hare, Jeremy; Parker, Michael L. (Astrophysical Journal, 2020)
We present results from the Nuclear Spectroscopic Telescope Array observations of the new black hole X-ray binary candidate MAXI J1631-479 at two epochs during its 2018-2019 outburst, which caught the source in a disk dominant state and a power-law dominant state. Strong relativistic disk reflection features are clearly detected, displaying significant variations in the shape and strength of the broad iron emission line between the two states. Spectral modeling of the reflection spectra reveals that the inner radius of the optically thick accretion disk evolves from r(g) (statistical errors at 90% confidence level) from the disk dominant to the power-law dominant state. Assuming in the former case that the inner disk radius is consistent with being at the innermost stable circular orbit, we estimate a black hole spin of a* > 0.94. Given that the bolometric luminosity is similar in the two states, our results indicate that the disk truncation observed in MAXI J1631-479 in the power-law dominant state is unlikely to be driven by a global variation in the accretion rate. We propose that it may instead arise from local instabilities in the inner edge of the accretion disk at high accretion rates. In addition, we find an absorption feature in the spectra centered at 7.33 0.03 keV during the disk dominant state, which is evidence for the rare case that an extremely fast disk wind (
CRIS-Team WoS Importer:2020-05-02

Study of a new central compact object: The neutron star in the supernova remnant G15.9+0.2 - Klochkov, Dmitry; Suleimanov, Valery; Sasaki, Manami; Santangelo, Andrea (Astronomy & Astrophysics, 2016)
We present our study of the central point source CXOUJ181852.0-150213 in the young Galactic supernova remnant (SNR) G15.9+0.2 based on the recent similar to 90 ks Chandra observations. The point source was discovered in 2005 in shorter Chandra observations and was hypothesized to be a neutron star associated with the SNR. Our X-ray spectral analysis strongly supports the hypothesis of a thermally emitting neutron star associated with G15.9+0.2. We conclude that the object belongs to the class of young cooling low-magnetized neutron stars referred to as central compact objects (CCOs). We modeled the spectrum of the neutron star with a blackbody spectral function and with our hydrogen and carbon neutron star atmosphere models, assuming that the radiation is uniformly emitted by the entire stellar surface. Under this assumption, only the carbon atmosphere models yield a distance that is compatible with a source located in the Galaxy. In this respect, CXOUJ181852.0-150213 is similar to two other well-studied CCOs, the neutron stars in Cas A and in HESSJ1731-347, for which carbon atmosphere models were used to reconcile their emission with the known or estimated distances.
Keywords: stars: neutron; ISM: supernova remnants; stars: atmospheres

Study of the excess Fe XXV line emission in the central degrees of the Galactic centre using XMM-Newton data - Anastasopoulou, K.; Ponti, G.; Sormani, M. C.; Locatelli, N.; Haberl, F.; Morris, M. R.; Churazov, E. M.; Schödel, R.; Maitra, C.; Campana, S.; Di Teodoro, E. M.; Jin, C.; et al. (Astronomy & Astrophysics, 2023)
The diffuse Fe XXV (6.7 keV) line emission observed in the Galactic ridge is widely accepted to be produced by a superposition of a large number of unresolved X-ray point sources. In the very central degrees of our Galaxy, however, the existence of an extremely hot ( 7 keV) diffuse plasma is still under debate. In this work we measure the Fe XXV line emission using all available XMM-Newton observations of the Galactic centre (GC) and inner disc (-10 < ℓ < 10, -2 < b < 2). We use recent stellar mass distribution models to estimate the amount of X-ray emission originating from unresolved point sources, and find that within a region of ℓ = ±1 and b = ±0.25 the 6.7keV emission is 1.3-1.5 times in excess of what is expected from unresolved point sources. The excess emission is enhanced towards regions where known supernova remnants are located, suggesting that at least a part of this emission is due to genuine diffuse very hot plasma. If the entire excess is due to very hot plasma, an energy injection rate of at least 6 × 1040 erg s-1 is required, which cannot be provided by the measured supernova explosion rate or past Sgr A∗ activity alone. However, we find that almost the entire excess we observe can be explained by assuming GC stellar populations with iron abundances 1.9 times higher than those in the bar/bulge, a value that can be reproduced by fitting diffuse X-ray spectra from the corresponding regions. Even in this case, a leftover X-ray excess is concentrated within ℓ = ±0.3 and b = ±0.15, corresponding to a thermal energy of 2 × 1052 erg, which can be reproduced by the estimated supernova explosion rate in the GC. Finally we discuss a possible connection to the observed GC Fermi-LAT excess.
CRIS-Team Scopus Importer:2023-03-24
Keywords: Galaxy: bulge; Galaxy: center; Galaxy: disk; X-rays: general; X-rays: ISM

Study of the many fluorescent lines and the absorption variability in GX 301-2 with XMM-Newton - Fürst, Felix; Suchy, S.; Kreykenbohm, Ingo; Barragan, L.; Wilms, Jörn; Pottschmidt, K.; Caballero, I.; Kretschmar, Peter; Ferrigno, Carlo; Rothschild, R. E. (Astronomy & Astrophysics, 2011)
We present an in-depth study of the high mass X-ray binary (HMXB) GX 301-2 during its pre-periastron flare using data from the XMM-Newton satellite. The energy spectrum shows a power law continuum absorbed by a large equivalent hydrogen column on the order of 10(24) cm(-2) and a prominent Fe K alpha fluorescent emission line. Besides the Fe K alpha line, evidence for Fe K beta, Ni K alpha, Ni K beta, S K alpha, Ar K alpha, Ca K alpha, and Cr K alpha fluorescent lines is found. The observed line strengths are consistent with fluorescence in a cold absorber. This is the first time that Cr K alpha is seen in emission in the X-ray spectrum of a HMXB. In addition to the modulation by the strong pulse period of similar to 685 s the source is highly variable and shows different states of activity. We perform time-resolved as well as pulse-to-pulse resolved spectroscopy to investigate differences between these states of activity. We find that fluorescent line fluxes are strongly variable and generally follow the overall flux. The N-H value is variable by a factor of 2, but not correlated to continuum normalization. We find an interval of low flux in the light curve in which the pulsations cease almost completely, without any indication of an increasing absorption column. We investigate this dip in detail and argue that it is most likely that during the dip the accretion ceased and the afterglow of the fluorescent iron accounted for the main portion of the X-ray flux. A similar dip was found earlier in RXTE data, and we compare our findings to these results.
Keywords: stars: neutron; accretion; accretion disks; X-rays: binaries; X-rays: individuals: GX 301-2

Sub-milliarcsecond imaging of a bright flare and ejection event in the extragalactic jet 3C 111 - Schulz, R.; Kadler, M.; Ros, E.; Perucho, M.; Krichbaum, T. P.; Agudo, I.; Beuchert, T.; Lindqvist, M.; Mannheim, K.; Wilms, Jörn; Zensus, J. A. (Astronomy & Astrophysics, 2020)
Context. Flares in radio-loud active galactic nuclei are thought to be associated with the injection of fresh plasma into the compact jet base. Such flares are usually strongest and appear earlier at shorter radio wavelengths. Hence, very long baseline interferometry (VLBI) at millimeter(mm)-wavelengths is the best-suited technique for studying the earliest structural changes of compact jets associated with emission flares. Aims. We study the morphological changes of the parsec-scale jet in the nearby (z = 0.049) γ-ray bright radio galaxy 3C 111 following a flare that developed into a major radio outburst in 2007. Methods. We analyse three successive observations of 3C 111 at 86 GHz with the Global mm-VLBI Array (GMVA) between 2007 and 2008 which yield a very high angular resolution of ∼45 μas. In addition, we make use of single-dish radio flux density measurements from the F-GAMMA and POLAMI programmes, archival single-dish and VLBI data. Results. We resolve the flare into multiple plasma components with a distinct morphology resembling a bend in an otherwise remarkably straight jet. The flare-associated features move with apparent velocities of ∼4.0c to ∼4.5c and can be traced also at lower frequencies in later epochs. Near the base of the jet, we find two bright features with high brightness temperatures up to ∼1011 K, which we associate with the core and a stationary feature in the jet. Conclusions. The flare led to multiple new jet components indicative of a dynamic modulation during the ejection. We interpret the bend-like feature as a direct result of the outburst which makes it possible to trace the transverse structure of the jet. In this scenario, the components follow different paths in the jet stream consistent with expectations for a spine-sheath structure, which is not seen during intermediate levels of activity. The possibility of coordinated multiwavelength observations during a future bright radio flare in 3C 111 makes this source an excellent target for probing the radio-γ-ray connection.
CRIS-Team Scopus Importer:2020-12-25
Keywords: Galaxies: active; Galaxies: individual: 3C 111; Galaxies: jets; Techniques: high angular resolution

Substellar companions and the formation of hot subdwarf stars - Geier, Stephan; Heber, Ulrich; Tillich, Alfred; Hirsch, Heiko; Kupfer, Thomas; Schaffenroth, Veronika; Classen, Lew; Maxted, Pierre F.L.; Østensen, Roy H.; Barlow, Brad N.; Marsh, Tom R.; Gänsicke, Boris T.; et al. (AIP Conference Proceedings, 2011)
We give a brief review over the observational evidence for close substellar companions to hot subdwarf stars. The formation of these core helium-burning objects requires huge mass loss of their red giant progenitors. It has been suggested that besides stellar companions substellar objects in close orbits may be able to trigger this mass loss. Such objects can be easily detected around hot subdwarf stars by medium or high resolution spectroscopy with an RV accuracy at the km s-1-level. Eclipsing systems of HW Vir type stick out of transit surveys because of their characteristic light curves. The best evidence that substellar objects in close orbits around sdBs exist and that they are able to trigger the required mass loss is provided by the eclipsing system SDSS J0820+0008, which was found in the course of the MUCHFUSS project. Furthermore, several candidate systems have been discovered. © 2011 American Institute of Physics.
CRIS-Team Scopus Importer:2020-12-21
Keywords: stars:binaries; stars:subdwarfs

Sub-stellar companions of intermediate-mass stars with CoRoT: CoRoT-34b, CoRoT-35b, and CoRoT-36b - Sebastian, Daniel; Guenther, E. W.; Deleuil, M.; Dorsch, Matti; Heber, Ulrich; Heuser, Christian; Gandolfi, D.; Grziwa, S.; Deeg, H. J.; Alonso, R.; Bouchy, F.; Csizmadia, Sz; et al. (Monthly Notices of the Royal Astronomical Society, 2022)
Theories of planet formation give contradicting results of how frequent close-in giant planets of intermediate mass stars (IMSs; 1.3 <= M-* <= 3.2 M-circle dot) are. Some theories predict a high rate of IMSs with close-in gas giants, while others predict a very low rate. Thus, determining the frequency of close-in giant planets of IMSs is an important test for theories of planet formation. We use the CoRoT survey to determine the absolute frequency of IMSs that harbour at least one close-in giant planet and compare it to that of solar-like stars. The CoRoT transit survey is ideal for this purpose, because of its completeness for gas-giant planets with orbital periods of less than 10 d and its large sample of main-sequence IMSs. We present a high precision radial velocity follow-up programme and conclude on 17 promising transit candidates of IMSs, observed with CoRoT. We report the detection of CoRoT-34b, a brown dwarf close to the hydrogen burning limit, orbiting a 1.1 Gyr A-type main-sequence star. We also confirm two inflated giant planets, CoRoT-35b, part of a possible planetary system around a metal-poor star, and CoRoT-36b on a misaligned orbit. We find that 0.12 +/- 0.10 per cent of IMSs between 1.3 <= M-* <= 1.6 M-circle dot observed by CoRoT do harbour at least one close-in giant planet. This is significantly lower than the frequency (0.70 +/- 0.16 per cent) for solar-mass stars, as well as the frequency of IMSs harbouring long-period planets (similar to 8 per cent).
CRIS-Team WoS Importer:2022-09-09

Supernova remnants and candidates detected in the XMM-Newton M31 large survey - Sasaki, Manami; Pietsch, Wolfgang; Haberl, Frank; Hatzidimitriou, Despina; Stiele, Holger; Williams, Benjamin F.; Kong, Albert; Kolb, Ulrich (Astronomy & Astrophysics, 2012)
Context. We carried out new observations of two fields in the star-forming northern ring of M 31 with XMM-Newton with each one of them consisting of two exposures of about 100 ks each. A previous XMM-Newton survey of the entire M 31 galaxy revealed extended diffuse X-ray emission in these regions. Aims: We study the population of X-ray sources in the northern disc of M 31 by compiling a complete list of X-ray sources down to a sensitivity limit of ̃7 × 1034 erg s-1 (0.5-2.0 keV) and improve the identification of the X-ray sources. The major objective of the observing programme was the study of the hot phase of the interstellar medium (ISM) in M 31. The analysis of the diffuse emission and the study of the ISM is presented in a separate paper. Methods: We analysed the spectral properties of all detected sources using hardness ratios and spectra if the statistics were high enough. We also checked for variability. In order to classify the sources detected in the new deep XMM-Newton observations, we cross-correlated the source list with the source catalogue of a new survey of the northern disc of M 31 carried out with the Chandra X-ray Observatory and the Hubble Space Telescope (Panchromatic Hubble Andromeda Treasury, PHAT) as well as with other existing catalogues. Results: We detected a total of 389 sources in the two fields of the northern disc of M 31 observed with XMM-Newton. We identified 43 foreground stars and candidates and 50 background sources. Based on a comparison with the results of the Chandra/PHAT survey, we classify 24 hard X-ray sources as new candidates for X-ray binaries. In total, we identified 34 X-ray binaries and candidates and 18 supernova remnants (SNRs) and candidates. We studied the spectral properties of the four brightest SNRs and confirmed five new X-ray SNRs. Three of the four SNRs, for which a spectral analysis was performed, show emission mainly below 2 keV, which is consistent with shocked ISM. The spectra of two of them also require an additional component with a higher temperature. The SNR [SPH11] 1535 has a harder spectrum and might suggest that there is a pulsar-wind nebula inside the SNR. For all SNRs in the observed fields, we measured the X-ray flux or calculated upper limits. We also carried out short-term and long-term variability studies of the X-ray sources and found five new sources showing clear variability. In addition, we studied the spectral properties of the transient source SWIFT J004420.1+413702, which shows significant variation in flux over a period of seven months (June 2015 to January 2016) and associated change in absorption. Based on the likely optical counterpart detected in the Chandra/PHAT survey, the source is classified as a low-mass X-ray binary.
Keywords: ISM: supernova remnants; galaxies: ISM; galaxies: individual: M31; X-rays: galaxies; X-rays: ISM

Supernova remnants in nearby galaxies - Sasaki, Manami (Astronomische Nachrichten, 2020)
Supernova remnants (SNRs) are the aftermath of stellar explosions, which inject large amounts of energy into the interstellar medium (ISM), carving out new structures and transferring kinetic energy to the ISM. They also act as recycling centers, which return elements processed in stars to the ISM, and cosmic particle accelerators. The evolution of SNRs can be best studied in soft X-ray line and continuum emission, since they mainly consist of very hot plasma (106–107 K). While it is difficult to observe these soft X-ray sources in our own Galaxy due to absorption by matter in the Galactic plane, the Magellanic Clouds as well as the nearby spiral galaxies M 31 and M 33 are ideal targets to study both particular SNRs in detail and the SNR population in a galaxy as a whole. Various studies of SNRs in the Local Group galaxies have been carried out with XMM-Newton or Chandra since the launch of the mission, and in the coming years the new X-ray all-sky survey performed with eROSITA will provide us with more complete data of SNRs in the nearby Universe to low flux limits.
CRIS-Team Scopus Importer:2020-03-10
Keywords: local group; magellanic clouds; milky way; supernova remnants

Surviving a supernova: Zombies and runaways - Raddi, Roberto; Heber, Ulrich; Hollands, Mark A. (Astronomy & Geophysics, 2019)
CRIS-Team Scopus Importer:2019-10-22

Suzaku observation of IGR J16318-4848 - Barragan, L.; Wilms, Jörn; Pottschmidt, K.; Nowak, M. A.; Kreykenbohm, Ingo; Walter, R.; Tomsick, J. A. (Astronomy & Astrophysics, 2009)
We report on the first Suzaku observation of IGR J16318-4848, the most extreme example of a new group of highly absorbed X-ray binaries that have recently been discovered by the International Gamma-Ray Astrophysics Laboratory (INTEGRAL). The Suzaku observation was carried out between 2006 August 14 and 17, with a net exposure time of 97 ks.The average X-ray spectrum of the source can be well described (chi(2)(red) = 0.99) with a continuum model typical for neutron stars i.e., a strongly absorbed power law continuum with a photon index of 0.676(42) and an exponential cutoff at 20.5(6) keV. The absorbing column is N-H = 1.95(3) x 10(24) cm(-2). Consistent with earlier work, strong fluorescent emission lines of Fe K alpha, Fe K beta, and Ni K alpha are observed. Despite the large N-H, no Compton shoulder is seen in the lines, arguing for a non-spherical and inhomogeneous absorber. Seen at an average 5-60 keV absorbed flux of 3.4x10(-10) erg cm(-2) s(-1), the source exhibits significant variability on timescales of hours.
Keywords: stars: individual IGR J16318-4848; binaries: general; X-rays: binaries

SUZAKU OBSERVATIONS OF 4U 1957+11: POTENTIALLY THE MOST RAPIDLY SPINNING BLACK HOLE IN (THE HALO OF) THE GALAXY - Nowak, Michael A.; Wilms, Jörn; Pottschmidt, Katja; Schulz, Norbert; Maitra, Dipankar; Miller, Jon (Astrophysical Journal, 2012)
We present three Suzaku observations of the black hole candidate 4U 1957+11 (V1408 Aql)-a source that exhibits some of the simplest and cleanest examples of soft, disk-dominated spectra. 4U 1957+11 also presents among the highest peak temperatures found from disk-dominated spectra. Such temperatures may be associated with rapid black hole spin. The 4U 1957+11 spectra also require a very low normalization, which can be explained by a combination of small inner disk radius and a large distance (>10 kpc) which places 4U 1957+11 well into the Galactic halo. We perform joint fits to the Suzaku spectra with both relativistic and Comptonized disk models. Assuming a low-mass black hole and the nearest distance (3 M-circle dot, 10 kpc), the dimensionless spin parameter a* equivalent to Jc/GM(2) greater than or similar to 0.9. Higher masses and farther distances yield a* approximate to 1. Similar conclusions are reached with Comptonization models; they imply a combination of small inner disk radii (or, equivalently, rapid spin) and large distance. Low spin cannot be recovered unless 4U 1957+11 is a low-mass black hole that is at the unusually large distance of greater than or similar to 40 kpc. We speculate whether the suggested maximal spin is related to how the system came to reside in the halo.
Keywords: accretion; accretion disks; black hole physics; radiation mechanisms: thermal; X-rays: binaries

Suzaku Observations of 4U 1957+11: The Most Rapidly Spinning Black Hole in the Galaxy? - Nowak, Michael A.; Wilms, Jörn; Pottschmidt, Katja; Schulz, Norbert; Miller, Jon; Maitra, Dipankar (2012)
We present three Suzaku observations of the black hole candidate 4U 1957+11-a source that exhibits some of the simplest and cleanest examples of soft, disk-dominated spectra. 4U 1957+11 also presents among the highest peak temperatures found from disk-dominated spectra. Such temperatures may be associated with rapid black hole spin. The 4U 1957+11 spectra also require a very low normalization, which can be explained by a combination of small inner disk radius and a large distance (> 10 kpc) which places 4U 1957+11 well into the Galactic halo. We perform joint fits to the Suzaku spectra with relativistic disk models. Assuming a low mass black hole and the nearest distance (3M(circle dot), 10 kpc), the dimensionless spin parameter a* = Jc/GM(2) greater than or similar to 0.9. Higher masses and farther distances yield a* approximate to 1. Low spin cannot be recovered unless 4U 1957+11 is a low mass black hole that is at the unusually large distance of greater than or similar to 40 kpc.
Keywords: accretion; accretion disks; black hole physics; X-rays: binaries

Suzaku observations of the 2013 outburst of KS 1947+300 - Ballhausen, Ralf; Kühnel, Matthias; Pottschmidt, Katja; Furst, Felix; Hemphill, Paul B.; Falkner, Sebastian; Gottlieb, Amy M.; Grinberg, Victoria; Kretschmar, Peter; Kreykenbohm, Ingo; Rothschild, Richard E.; Wilms, Jörn (Astronomy & Astrophysics, 2016)
We report on the timing and spectral analysis of two Suzaku observations with different flux levels of the high-mass X-ray binary KS 1947+300 during its 2013 outburst. In agreement with simultaneous NuSTAR observations, the continuum is well described by an absorbed power law with a cutoff and an additional blackbody component. In addition, we find fluorescent emission from neutral, He-like, and even H-like iron. We determine a pulse period of 18.8 s with the source showing a spin-up between the two observations. Both Suzaku observations show very similar behavior of the pulse profile, which is strongly energy dependent. This profile has an evolution from a profile with one peak at low energies to a profile with two peaks of different widths toward higher energies seen in both the Suzaku and NuSTAR data. Such an evolution to a more complex profile at higher energies is rarely seen in X-ray pulsars, most cases show the opposite behavior. Pulse phase-resolved spectral analysis shows a variation in the absorbing column density, N, over pulse phase. Spectra taken during the pulse profile minima are intrinsically softer compared to the pulse phase-averaged spectrum.
Keywords: Accretion; accretion disks; Pulsars: individual: KS 1947+300; X-rays: binaries

SUZAKU OBSERVATIONS OF THE HMXB 1A 1118-61 - Suchy, Slawomir; Pottschmidt, Katja; Rothschild, Richard E.; Wilms, Jörn; Fürst, Felix; Barragan, Laura; Caballero, Isabel; Grinberg, Victoria; Kreykenbohm, Ingo; Doroshenko, Victor; Santangelo, Andrea; Staubert, Ruediger; et al. (Astrophysical Journal, 2011)
We present broadband analysis of the Be/X-ray transient 1A 1118-61 by Suzaku at the peak of its third observed outburst in 2009 January and two weeks later when the source flux had decayed by an order of magnitude. The continuum was modeled with a cutoffpl model as well as a compTT model, with both cases requiring an additional blackbody component at lower energies. We confirm the detection of a cyclotron line at similar to 55 keV and discuss the possibility of a first harmonic at similar to 110 keV. Pulse profile comparisons show a change in the profile structure at lower energies, an indication for possible changes in the accretion geometry. Phase-resolved spectroscopy in the outburst data shows a change in the continuum throughout the pulse period. The decrease in the cyclotron resonance scattering feature centroid energy also indicates that the viewing angle on the accretion column is changing throughout the pulse period.
Keywords: pulsars: individual (1A 1118-61); stars: magnetic field; X-rays: binaries; X-rays: stars

Swift/BAT measurements of the cyclotron line energy decay in the accreting neutron star Hercules X-1: indication of an evolution of the magnetic field? - Klochkov, D.; Staubert, R.; Postnov, K.; Wilms, Jörn; Rothschild, R. E.; Santangelo, A. (Astronomy & Astrophysics, 2015)
Conclusions. The decay of E-cyc either indicates a local evolution of the magnetic field structure in the polar regions of the neutron star or a geometrical displacement of the line-forming region due to long-term changes in the structure of the X-ray emitting region. The shortness of the observed timescale of the decay, E-cyc/(E) over dot(cyc) similar to 100 yr, suggests that trend reversals and/or jumps of the line energy might be observed in the future.
Keywords: accretion; accretion disks; stars: neutron; stars: magnetic field

SXP 214: AN X-RAY PULSAR IN THE SMALL MAGELLANIC CLOUD, CROSSING THE CIRCUMSTELLAR DISK OF THE COMPANION - Hong, Jaesub; Antoniou, Vallia; Zezas, Andreas; Haberl, Frank; Drake, Jeremy J.; Plucinsky, Paul P.; Gaetz, Terrance; Sasaki, Manami; Williams, Benjamin; Long, Knox S.; Blair, William P.; Winkler, P. Frank; et al. (Astrophysical Journal, 2016)
Located in the Small Magellanic Cloud ( SMC), SXP 214 is an X-ray pulsar in a high mass X-ray binary system with a Be-star companion. A recent survey of the SMC under a Chandra X-ray Visionary program found that the source was in a transition when the X-ray flux was on a steady rise. The Lomb-Scargle periodogram revealed a pulse period of 211.49 +/- 0.42 s, which is significantly (> 5 sigma) shorter than the previous measurements made with XMM-Newton and RXTE. This implies that the system has gone through sudden spin-up episodes recently. The pulse profile shows a sharp eclipse-like feature with a modulation amplitude of >95%. The linear rise of the observed X-ray luminosity from less than or similar to 2x to 7 x 10(35) erg s(-1) is correlated with a steady softening of the X-ray spectrum, which can be described by the changes in the local absorption from N-H similar to 10(24) to less than or similar to 10(20) cm(-2) for an absorbed power-law model. The soft X-ray emission below 2 keV was absent in the early part of the observation when only the pulsating hard X-ray component was observed, whereas at later times, both soft and hard X-ray components were observed to be pulsating. A likely explanation is that the neutron star was initially hidden in the circumstellar disk of the companion, and later came out of the disk with the accreted material that continued fueling the observed pulsation.
Keywords: stars: neutron; X-rays: binaries

Synthetic pulsational line profile variations - Oreiro, R.; Telting, J. H.; Ostensen, R. H.; Briquet, M.; Aerts, Conny; Heber, Ulrich; Heber, Ulrich; Vuckovic, Maja (Astrophysics and Space Science, 2010)
We have produced simulated time series of high resolution spectroscopy for sdBs. We present the first results of testing classical mode identification techniques. Here, in particular, we analyse the behaviour of individual spectral lines and discuss the results and applicability of the moment method.
Keywords: Asteroseismology; Hot subdwarfs

Synthetic simulations of the extragalactic sky seen by eROSITA I. Pre-launch selection functions from Monte-Carlo simulations - Clerc, N.; Ramos-Ceja, M. E.; Ridl, J.; Lamer, G.; Brunner, H.; Hofmann, Florian; Comparat, J.; Pacaud, Florian; Kaefer, F.; Reiprich, T. H.; Merloni, A.; Schmid, Christian; et al. (Astronomy & Astrophysics, 2018)
Context. Studies of galaxy clusters provide stringent constraints on models of structure formation. Provided that selection effects are under control, large X-ray surveys are well suited to derive cosmological parameters, in particular those governing the dark energy equation of state.Aims. We forecast the capabilities of the all-sky eROSITA (extended ROentgen Survey with an Imaging Telescope Array) survey to be achieved by the early 2020s. We bring special attention to modelling the entire chain from photon emission to source detection and cataloguing.Methods. The selection function of galaxy clusters for the upcoming eROSITA mission is investigated by means of extensive and dedicated Monte-Carlo simulations. Employing a combination of accurate instrument characterisation and a state-of-the-art source detection technique, we determine a cluster detection efficiency based on the cluster fluxes and sizes.Results. Using this eROSITA cluster selection function, we find that eROSITA will detect a total of approximately 10(5) clusters in the extra-galactic sky. This number of clusters will allow eROSITA to put stringent constraints on cosmological models. We show that incomplete assumptions on selection effects, such as neglecting the distribution of cluster sizes, induce a bias in the derived value of cosmological parameters.Conclusions. Synthetic simulations of the eROSITA sky capture the essential characteristics impacting the next-generation galaxy cluster surveys and they highlight parameters requiring tight monitoring in order to avoid biases in cosmological analyses.
Keywords: cosmological parameters; surveys; large-scale structure of Universe; X-rays: galaxies: clusters; cosmology: observations; methods: data analysis

Systematic evaluation of variability detection methods for eROSITA - Buchner, Johannes; Boller, Thomas; Bogensberger, David; Malyali, Adam; Nandra, Kirpal; Wilms, Jörn; Dwelly, Tom; Liu, Teng (Astronomy & Astrophysics, 2022)
The reliability of detecting source variability in sparsely and irregularly sampled X-ray light curves is investigated. This is motivated by the unprecedented survey capabilities of eROSITA on board the Spektrum-Roentgen-Gamma observatory, providing light curves for many thousand sources in its final-depth equatorial deep-field survey. Four methods for detecting variability are evaluated: excess variance, amplitude maximum deviations, Bayesian blocks, and a new Bayesian formulation of the excess variance. We judge the false-detection rate of variability based on simulated Poisson light curves of constant sources, and calibrate significance thresholds. Simulations in which flares are injected favour the amplitude maximum deviation as most sensitive at low false detections. Simulations with white and red stochastic source variability favour Bayesian methods. The results are applicable also for the million sources expected in the eROSITA all-sky survey.
CRIS-Team WoS Importer:2022-06-17

TANAMI blazars in the IceCube PeV-neutrino fields - Krauß, Felicia; Kadler, Matthias; Mannheim, K.; Schulz, Robert; Truestedt, J.; Wilms, Jörn; Ojha, R.; Ros, Eduardo; Anton, Gisela; Baumgartner, W.; Beuchert, Tobias; Blanchard, J.; et al. (Astronomy & Astrophysics, 2014)
The IceCube Collaboration has announced the discovery of a neutrino flux in excess of the atmospheric background. Owing to the steeply falling atmospheric background spectrum, events at PeV energies most likely have an extraterrestrial origin. We present the multiwavelength properties of the six radio-brightest blazars that are positionally coincident with these events using contemporaneous data of the TANAMI blazar sample, including high-resolution images and spectral energy distributions. Assuming the X-ray to gamma-ray emission originates in the photoproduction of pions by accelerated protons, the integrated predicted neutrino luminosity of these sources is high enough to explain the two detected PeV events.
Keywords: neutrinos; galaxies: active; quasars: general

TANAMI monitoring of Centaurus A: The complex dynamics in the inner parsec of an extragalactic jet - Mueller, C.; Kadler, Matthias; Ojha, R.; Perucho, Manel; Großberger, Christoph; Ros, Eduardo; Wilms, Jörn; Blanchard, J.; Boeck, M.; Carpenter, B.; Dutka, M.; Edwards, P. G.; et al. (Astronomy & Astrophysics, 2014)
Context. Centaurus A (Cen A) is the closest radio-loud active galactic nucleus. Very Long Baseline Interferometry (VLBI) enables us to study the spectral and kinematic behavior of the radio jet-counterjet system on milliarcsecond scales, providing essential information for jet emission and propagation models.Aims. In the framework of the TANAMI monitoring, we investigate the kinematics and complex structure of Cen A on subparsec scales. We have been studying the evolution of the central parsec jet structure of CenA for over 3.5 years. The proper motion analysis of individual jet components allows us to constrain jet formation and propagation and to test the proposed correlation of increased high-energy flux with jet ejection events. Cen A is an exceptional laboratory for such a detailed study because its proximity translates to unrivaled linear resolution, where one milliarcsecond corresponds to 0.018 pc.Methods. As a target of the southern-hemisphere VLBI monitoring program TANAMI, observations of CenA are done approximately every six months at 8.4 GHz with the Australian Long Baseline Array (LBA) and associated telescopes in Antarctica, Chile, New Zealand, and South Africa, complemented by quasi-simultaneous 22.3 GHz observations.Results. The first seven epochs of high-resolution TANAMI VLBI observations at 8.4 GHz of CenA are presented, resolving the jet on (sub-) milliarcsecond scales. They show a differential motion of the subparsec scale jet with significantly higher component speeds farther downstream where the jet becomes optically thin. We determined apparent component speeds within a range of 0 : 1 c to 0 : 3 c and identified long-term stable features. In combination with the jet-to-counterjet ratio, we can constrain the angle to the line of sight to theta similar to 12 degrees-45 degrees.Conclusions. The high-resolution kinematics are best explained by a spine-sheath structure supported by the downstream acceleration occurring where the jet becomes optically thin. On top of the underlying, continuous flow, TANAMI observations clearly resolve individual jet features. The flow appears to be interrupted by an obstacle causing a local decrease in surface brightness and circumfluent jet behavior. We propose a jet-star interaction scenario to explain this appearance. The comparison of jet ejection times to high X-ray flux phases yields a partial overlap of the onset of the X-ray emission and increasing jet activity, but the limited data do not support a robust correlation.
Keywords: galaxies: active; galaxies: individual: Centaurus A; galaxies: individual: NGC 5128; techniques: high angular resolution; galaxies: jets

TANAMI: Tracking Active Galactic Nuclei with Austral Milliarcsecond Interferometry - Mueller, C.; Kadler, M.; Ojha, R.; Schulz, Robert; Truestedt, J.; Edwards, P. G.; Ros, E.; Carpenter, B.; Angioni, R.; Blanchard, J.; Böck, Moritz; Burd, P. R.; et al. (Astronomy & Astrophysics, 2018)
Context. TANAMI is a multiwavelength program monitoring active galactic nuclei (AGN) south of -30 degrees declination including high-resolution very long baseline interferometry (VLBI) imaging, radio, optical/UV, X-ray, and gamma-ray studies. We have previously published first-epoch 8.4 GHz VLBI images of the parsec-scale structure of the initial sample. In this paper, we present images of 39 additional sources. The full sample comprises most of the radio-and gamma-ray brightest AGN in the southern quarter of the sky, overlapping with the region from which high-energy (>100 TeV) neutrino events have been found.Aims. We characterize the parsec-scale radio properties of the jets and compare them with the quasi-simultaneous Fermi/LAT gamma-ray data. Furthermore, we study the jet properties of sources which are in positional coincidence with high-energy neutrino events compared to the full sample. We test the positional agreement of high-energy neutrino events with various AGN samples.Methods. TANAMI VLBI observations at 8.4 GHz are made with southern hemisphere radio telescopes located in Australia, Antarctica, Chile, New Zealand, and South Africa.Results. Our observations yield the first images of many jets below -30 degrees declination at milliarcsecond resolution. We find that gamma-ray loud TANAMI sources tend to be more compact on parsec-scales and have higher core brightness temperatures than gamma-ray faint jets, indicating higher Doppler factors. No significant structural difference is found between sources in positional coincidence with high-energy neutrino events and other TANAMI jets. The 22 gamma-ray brightest AGN in the TANAMI sky show only a weak positional agreement with high-energy neutrinos demonstrating that the >100 TeV IceCube signal is not simply dominated by a small number of the gamma-ray brightest blazars. Instead, a larger number of sources have to contribute to the signal with each individual source having only a small Poisson probability for producing an event in multi-year integrations of current neutrino detectors.
Keywords: galaxies: active; galaxies: jets; galaxies: nuclei; radio continuum: galaxies; techniques: high angular resolution; neutrinos

TANAMI: tracking active galactic nuclei with austral milliarcsecond interferometry I. First-epoch 8.4GHz images - Ojha, R.; Kadler, Matthias; Böck, Moritz; Booth, R.; Dutka, M. S.; Edwards, P. G.; Fey, A. L.; Fuhrmann, L.; Gaume, R. A.; Hase, H.; Horiuchi, S.; Jauncey, D. L.; et al. (Astronomy & Astrophysics, 2010)
Context. A number of theoretical models vie to explain the gamma-ray emission from active galactic nuclei (AGN). This was a key discovery of EGRET. With its broader energy coverage, higher resolution, wider field of view and greater sensitivity, the Large Area Telescope (LAT) of the Fermi Gamma-ray Space Telescope is dramatically increasing our knowledge of AGN gamma-ray emission. However, discriminating between competing theoretical models requires quasi-simultaneous observations across the electromagnetic spectrum. By resolving the powerful parsec-scale relativistic outflows in extragalactic jets and thereby allowing us to measure critical physical properties, Very Long Baseline Interferometry observations are crucial to understanding the physics of extragalactic gamma-ray objects.Aims. We introduce the TANAMI program (Tracking Active Galactic Nuclei with Austral Milliarcsecond Interferometry) which is monitoring an initial sample of 43 extragalactic jets located south of -30 degrees declination at 8.4GHz and 22GHz since 2007. All aspects of the program are discussed. First epoch results at 8.4GHz are presented along with physical parameters derived therefrom.Methods. These observations were made during 2007/2008 using the telescopes of the Australian Long Baseline Array in conjunction with Hartebeesthoek in South Africa. These data were correlated at the Swinburne University correlator.Results. We present first epoch images for 43 sources, some observed for the first time at milliarcsecond resolution. Parameters of these images as well as physical parameters derived from them are also presented and discussed. These and subsequent images from the TANAMI survey are available at http://pulsar.sternwarte.uni-erlangen.de/tanami/.Conclusions. We obtain reliable, high dynamic range images of the southern hemisphere AGN. All the quasars and BL Lac objects in the sample have a single-sided radio morphology. Galaxies are either double-sided, single-sided or irregular. About 28% of the TANAMI sample has been detected by LAT during its first three months of operations. Initial analysis suggests that when galaxies are excluded, sources detected by LAT have larger opening angles than those not detected by LAT. Brightness temperatures of LAT detections and non-detections seem to have similar distributions. The redshift distributions of the TANAMI sample and sub-samples are similar to those seen for the bright gamma-ray AGN seen by LAT and EGRET but none of the sources with a redshift above 1.8 have been detected by LAT.
Keywords: galaxies: active; galaxies: jets; galaxies: nuclei; gamma rays: observations; quasars: general

TELAMON: Effelsberg monitoring of AGN jets with very-high-energy astroparticle emission: I. Program description and sample characterization - Eppel, F.; Kadler, M.; Hea-Dörfer, J.; Benke, P.; Debbrecht, L.; Eich, J.; Gokus, A.; Hämmerich, Steven; Kirchner, D.; Paraschos, G. F.; Rösch, F.; Schulga, W.; et al. (Astronomy & Astrophysics, 2024)
Aims. We introduce the TELAMON program which is using the Effelsberg 100-m telescope to monitor the radio spectra of active galactic nuclei (AGN) under scrutiny in astroparticle physics, specifically TeV blazars and candidate neutrino-associated AGN. Here, we present and characterize our main sample of TeV-detected blazars. Methods. We analyzed the data sample from the first a2.5 yr of observations between August 2020 and February 2023 in the range from 14 GHz to 45 GHz. During this pilot phase, we observed all 59 TeV-detected blazars in the Northern Hemisphere (i.e., Deca- >a- 0) known at the time of observation. We discuss the basic data reduction and calibration procedures used for all TELAMON data and introduce a sub-band averaging method used to calculate average light curves for the sources in our sample. Results. The TeV-selected sources in our sample exhibit a median flux density of 0.12 Jy at 20 mm, 0.20 Jy at 14 mm, and 0.60 Jy at 7 mm. The spectrum for most of the sources is consistent with a flat radio spectrum and we found a median spectral index (S(ν)a- να) of αa- =a- a- 0.11. Our results on flux density and spectral index are consistent with previous studies of TeV-selected blazars. Compared to the GeV-selected F-GAMMA sample, TELAMON sources are significantly fainter in the radio band. This is consistent with the double-humped spectrum of blazars being shifted towards higher frequencies for TeV-emitters (in particular for high-synchrotron peaked BL Lac type objects), which results in a lower radio flux density. The spectral index distribution of our TeV-selected blazar sample is not significantly different from the GeV-selected F-GAMMA sample. Moreover, we present a strategy to track the light curve evolution of sources in our sample for future variability and correlation analysis.
CRIS-Team Scopus Importer:2024-04-05
Keywords: Astroparticle physics; BL Lacertae objects: general; Galaxies: active; Galaxies: jets; Methods: observational; Radio continuum: galaxies

Temporal variations of strength and location of the South Atlantic Anomaly as measured by RXTE - Fürst, Felix; Wilms, Jörn; Rothschild, Richard E.; Pottschmidt, Katja; Smith, David M.; Lingenfelter, Richard (Earth and Planetary Science Letters, 2009)
The evolution of the particle background at an altitude of similar to 540 km during the time interval between 1996 and 2007 is studied using the particle monitor of the High Energy X-ray Timing Experiment on board NASA's Rossi X-ray Timing Explorer. A special emphasis of this study is the location and strength of the South Atlantic Anomaly (SAA). The size and strength of the SAA are anti-correlated with the 10.7 cm radio flux of the Sun, which leads the SAA strength by similar to 1 year reflecting variations in solar heating of the upper atmosphere. The location of the SAA is also found to drift westwards with an average drift rate of about 0.3 degrees/yr following the drift of the geomagnetic-field configuration. Superimposed to this drift rate are irregularities, where the SAA suddenly moves eastwards and where furthermore the speed of the drift changes. The most prominent of these irregularities is found in the second quarter of 2003 and another event took place in 1999. We suggest that these events are previously unrecognized manifestations of the geomagnetic jerks of the Earth's magnetic field. (c) 2009 Elsevier B.V. All rights reserved.
Keywords: space radiation environment; South Atlantic Anomaly; radiation monitors; Rossi X-ray Timing Explorer

TESS first look at evolved compact pulsators Discovery and asteroseismic probing of the g-mode hot B subdwarf pulsator EC 21494-7018 - Heber, Ulrich; Charpinet, Stephane; Brassard, P.; Fontaine, G.; Van Grootel, V.; Zong, W.; Giammichele, N.; Heber, Ulrich; Bognar, Zs; Geier, S.; Green, E. M.; Hermes, J. J.; et al. (Astronomy & Astrophysics, 2019)
Context. The TESS satellite was launched in 2018 to perform high-precision photometry from space over almost the whole sky in a search for exoplanets orbiting bright stars. This instrument has opened new opportunities to study variable hot subdwarfs, white dwarfs, and related compact objects. Targets of interest include white dwarf and hot subdwarf pulsators, both carrying high potential for asteroseismology. Aims. We present the discovery and detailed asteroseismic analysis of a new g-mode hot B subdwarf (sdB) pulsator, EC 21494-7018 (TIC 278659026), monitored in TESS first sector using 120-s cadence. Methods. The TESS light curve was analyzed with standard prewhitening techniques, followed by forward modeling using our latest generation of sdB models developed for asteroseismic investigations. By simultaneously best-matching all the observed frequencies with those computed from models, we identified the pulsation modes detected and, more importantly, we determined the global parameters and structural configuration of the star. Results. The light curve analysis reveals that EC 21494-7018 is a sdB pulsator counting up to 20 frequencies associated with independent g-modes. The seismic analysis singles out an optimal model solution in full agreement with independent measurements provided by spectroscopy (atmospheric parameters derived from model atmospheres) and astrometry (distance evaluated from Gaia DR2 trigonometric parallax). Several key parameters of the star are derived. Its mass (0.391 +/- 0.009x2006;M-circle dot) is significantly lower than the typical mass of sdB stars and suggests that its progenitor has not undergone the He-core flash; therefore this progenitor could originate from a massive (greater than or similar to 2;M-circle dot) red giant, which is an alternative channel for the formation of sdBs. Other derived parameters include the H-rich envelope mass (0.0037 +/- 0.0010;M-circle dot), radius (0.1694 +/- 0.0081;R-circle dot), and luminosity (8.2 +/- 1.1;L-circle dot). The optimal model fit has a double-layered He+H composition profile, which we interpret as an incomplete but ongoing process of gravitational settling of helium at the bottom of a thick H-rich envelope. Moreover, the derived properties of the core indicate that EC 21494-7018 has burnt similar to 43% (in mass) of its central helium and possesses a relatively large mixed core (M-core;=;0.198 +/- 0.010;M-circle dot), in line with trends already uncovered from other g-mode sdB pulsators analyzed with asteroseismology. Finally, we obtain for the first time an estimate of the amount of oxygen (in mass; X(O)(core) = 0.16(-0.05)(+0.13)X(O)core=0.16-0.05+0.13 X(O)_core=0.16_-0.05<^>+0.13 ) produced at this stage of evolution by an helium-burning core. This result, along with the core-size estimate, is an interesting constraint that may help to narrow down the still uncertain C-12(alpha,;gamma)O-16 nuclear reaction rate.
Keywords: asteroseismology; stars; interiors; stars; oscillations; stars; horizontal-branch; stars; individual; TIC 278659026; subdwarfs

TESS first look at evolved compact pulsators Known ZZ Ceti stars of the southern ecliptic hemisphere as seen by TESS - Bognar, Zs; Kawaler, S. D.; Bell, K. J.; Schrandt, C.; Baran, A. S.; Bradley, P. A.; Hermes, J. J.; Charpinet, S.; Handler, G.; Mullally, S. E.; Murphy, S. J.; Raddi, Roberto; et al. (Astronomy & Astrophysics, 2020)
Context. We present our findings on 18 previously known ZZ Ceti stars observed by the TESS space telescope in 120 s cadence mode during the survey observation of the southern ecliptic hemisphere.
CRIS-Team WoS Importer:2020-07-24

TESSIM: A simulator for the Athena-X-IFU - Wilms, Jörn; Smith, S. J.; Peille, P.; Ceballos, M. T.; Cobo, B.; Dauser, Thomas; Brand, Thorsten; Den Hartog, R. H.; Bandler, S. R.; De Plaa, J.; Den Herder, J. W.A. (Space Telescopes and Instrumentation 2016: Ultraviolet to Gamma Ray, 2016)
We present the design of tessim, a simulator for the physics of transition edge sensors developed in the framework of the Athena end to end simulation effort. Designed to represent the general behavior of transition edge sensors and to provide input for engineering and science studies for Athena, tessim implements a numerical solution of the linearized equations describing these devices. The simulation includes a model for the relevant noise sources and several implementations of possible trigger algorithms. Input and output of the software are standard FITS-files which can be visualized and processed using standard X-ray astronomical tool packages. Tessim is freely available as part of the SIXTE package (http://www.sternwarte.uni-erlangen.de/research/sixte/).
Keywords: Athena; simulation; transition edge detectors; X-ray detector

Testing general relativity with x-ray reflection spectroscopy: The Konoplya-Rezzolla-Zhidenko parametrization - Nampalliwar, Sourabh; Xin, Shuo; Srivastava, Shubham; Abdikamalov, Askar B.; Ayzenberg, Dimitry; Bambi, Cosimo; Dauser, Thomas; Garcia, Javier; Tripathi, Ashutosh (Physical Review D, 2020)
X-ray reflection spectroscopy is a promising technique for testing general relativity in the strong-field regime as it can be used to test the Kerr black hole hypothesis. In this context, the parametrically deformed black hole metrics proposed by Konoplya, Rezzolla, and Zhidenko [Phys. Rev. D 93, 064015 (2016)] form an important class of non-Kerr black holes. We implement this class of black hole metrics in RELX1LL_NK, which is a framework we have developed for testing for non-Kerr black holes using x-ray reflection spectroscopy. We perform a qualitative analysis of the effect of the leading order strong-field deformation parameters on typical observables like the innermost stable circular orbits and the reflection spectra. We also present the first x-ray constraints on some of the deformation parameters of this metric, using Suzaku data from the supermassive black hole in Ark 564, and compare them with those obtained (or expected) from other observational techniques like gravitational waves and black hole imaging.
CRIS-Team WoS Importer:2021-01-15

Testing the Kerr Black Hole Hypothesis Using X-Ray Reflection Spectroscopy and a Thin Disk Model with Finite Thickness - Abdikamalov, Askar B.; Ayzenberg, Dimitry; Bambi, Cosimo; Dauser, Thomas; Garcia, Javier; Nampalliwar, Sourabh; Tripathi, Ashutosh; Zhou, Menglei (Astrophysical Journal, 2020)
X-ray reflection spectroscopy is a powerful tool for probing the strong gravity region of black holes and can be used for testing general relativity in the strong field regime. Simplifications of the available relativistic reflection models limit the capability of performing accurate measurements of the properties of black holes. In this paper, we present an extension of the model relxill-nk in which the accretion disk has a finite thickness rather than being infinitesimally thin. We employ the accretion disk geometry proposed by Taylor & Reynolds and we construct relativistic reflection models for different values of the mass accretion rate of the black hole. We apply the new model to high-quality Suzaku data of the X-ray binary GRS 1915+105 to explore the impact of the thickness of the disk on tests of the Kerr metric.
CRIS-Team Scopus Importer:2020-11-13

Testing the Kerr hypothesis using x-ray reflection spectroscopy with NuSTAR data of Cygnus X-1 in the soft state - Liu, Honghui; Abdikamalov, Askar B.; Ayzenberg, Dimity; Bambi, Cosimo; Dauser, Thomas; Garcia, Javier; Nampalliwar, Sourabh (Physical Review D, 2019)
We continue exploring the constraining capabilities of x-ray reflection spectroscopy to test the Kerr-nature of astrophysical black holes, and we present the results of our analysis of two NuSTAR observations of Cygnus X-1 in the soft state. We find that the final measurement can strongly depend on the assumption of the intensity profile. We conclude that Cygnus X-1 is not suitable for tests of general relativity using x-ray reflection spectroscopy, and we discuss the desired properties of a source to be a good candidate for our studies.
CRIS-Team WoS Importer:2019-07-02

Testing the Kerr metric using X-ray reflection spectroscopy: Spectral analysis of GX 339-4 - Wang, Jingyi; Abdikamalov, Askar B.; Ayzenberg, Dimitry; Bambi, Cosimo; Dauser, Thomas; Garcia, Javier; Nampalliwar, Sourabh; Steiner, James F. (Journal of Cosmology and Astroparticle Physics, 2020)
Signatures of X-ray reprocessing (reflection) out of an accretion disk are commonly observed in the high-energy spectrum of accreting black holes, and can be used to probe the strong gravity region around these objects. In this paper, we extend previous work in the literature and we employ a full emission model for relativistic reflection in non-Kerr spacetime to demonstrate an approach that tests the Kerr black hole hypothesis. We analyze a composite spectrum obtained with the Proportional Counter Array in the Rossi X-ray Timing Explorer (RXTE), of the stellar-mass black hole GX 339-4 in its brightest hard state. With a remarkable sensitivity of ∼0.1% and 40 million counts in the 3-45 keV band to capture the faint features in the reflection spectrum, we demonstrate that it is possible with existing data and an adequate model to place constraints on the black hole spin a∗ and the deformation parameter that quantifies the departure from the Kerr metric. Our measurement obtained with the best fit model, which should be regarded as principally a proof of concept, is a∗=0.92+0.07 -0.12 and α13=-0.76+0.78 -0.60 with a 90% confidence level and is consistent with the hypothesis that the compact object in GX 339-4 is a Kerr black hole. We also discuss how the physical model choice and the emissivity profile adopted could make an impact on the constraints of α13 and spin. To enable Kerr metric test using X-ray reflection spectroscopy, it is essential to improve our astrophysical understanding of accreting black holes, e.g., the natures of accretion flow and corona.
CRIS-Team Scopus Importer:2020-06-09
Keywords: astrophysical black holes; gravity; X-rays

Testing the Kerr Metric with X-Ray Reflection Spectroscopy of Mrk 335 Suzaku Data - Choudhury, Kishalay; Nampalliwar, Sourabh; Abdikamalov, Askar B.; Ayzenberg, Dimitry; Bambi, Cosimo; Dauser, Thomas; Garcia, Javier (Astrophysical Journal, 2019)
Einstein's gravity has undergone extensive tests in the weak field gravitational limit, with results in agreement with theoretical predictions. There exist theories beyond general relativity (GR) which modify gravity in the strong field regime but agree with GR in the weak field. Astrophysical black holes are believed to be described by the Kerr metric and serve as suitable candidates to test strong gravity with electromagnetic radiation. We perform such a test by fitting one Suzaku data set of the narrow-line Seyfert 1 (NLS1) galaxy Mrk 335 with X-ray reflection spectroscopy, using the Johannsen metric to model the black hole spacetime and test for deviations from Kerr. We find the data is best modeled with a hybrid model that includes both partial covering absorption and a reflection component. This is the first time such a model has been proposed for a high-flux (low reflection) Mrk. 335 data set. We constrain the Johannsen deformation parameter alpha(13) to 1.5 < alpha(13) < 0.6 with spin parameter a(*) > 0.8, and the alpha(22) parameter to -0.4 < alpha(22) < 2.1 with a(*) > 0.7, both at the 99% confidence level. Although additional solutions at large deviations from the Kerr metric show statistical similarity with the ones above, further analysis suggests these solutions may be manifestations of uncertainties beyond our control and do not represent the data. Hence, our results are in agreement with the idea that the supermassive compact object at the center of Mrk 335 is described by the Kerr metric.
CRIS-Team WoS Importer:2019-07-26

TeV Emission of Galactic Plane Sources with HAWC and HESS - Abdalla, H.; Mitchell, Alison; Aharonian, Felix; Spencer, Samuel; Benkhali, F. Ait; Anguner, E. O.; Arcaro, C.; Armand, C.; Armstrong, T.; Ashkar, H.; Backes, M.; Baghmanyan,; et al. (Astrophysical Journal, 2021)
The High Altitude Water Cherenkov (HAWC) observatory and the High Energy Stereoscopic System (H.E.S.S.) are two leading instruments in the ground-based very-high-energy gamma-ray domain. HAWC employs the water Cherenkov detection (WCD) technique, while H.E.S.S. is an array of Imaging Atmospheric Cherenkov Telescopes (IACTs). The two facilities therefore differ in multiple aspects, including their observation strategy, the size of their field of view, and their angular resolution, leading to different analysis approaches. Until now, it has been unclear if the results of observations by both types of instruments are consistent: several of the recently discovered HAWC sources have been followed up by IACTs, resulting in a confirmed detection only in a minority of cases. With this paper, we go further and try to resolve the tensions between previous results by performing a new analysis of the H.E.S.S. Galactic plane survey data, applying an analysis technique comparable between H.E.S.S. and HAWC. Events above 1 TeV are selected for both data sets, the point-spread function of H.E.S.S. is broadened to approach that of HAWC, and a similar background estimation method is used. This is the first detailed comparison of the Galactic plane observed by both instruments. H.E.S.S. can confirm the gamma-ray emission of four HAWC sources among seven previously undetected by IACTs, while the three others have measured fluxes below the sensitivity of the H.E.S.S. data set. Remaining differences in the overall gamma-ray flux can be explained by the systematic uncertainties. Therefore, we confirm a consistent view of the gamma-ray sky between WCD and IACT techniques.
CRIS-Team WoS Importer:2021-08-20

TeV Gamma-Ray Observations of the Binary Neutron Star Merger GW170817 with HESS - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arrieta, M.; Aubert, P.; Backes, Michael; Balzer, A.; Barnard, Monica; Becherini, Y.; et al. (Astrophysical Journal Letters, 2017)
We search for high-energy gamma-ray emission from the binary neutron star merger GW170817 with the H.E.S.S. Imaging Air Cherenkov Telescopes. The observations presented here have been obtained starting only 5.3 hr after GW170817. The H.E.S.S. target selection identified regions of high probability to find a counterpart of the gravitational-wave event. The first of these regions contained the counterpart SSS17a that has been identified in the optical range several hours after our observations. We can therefore present the first data obtained by a ground-based pointing instrument on this object. A subsequent monitoring campaign with the H.E.S.S. telescopes extended over several days, covering timescales from 0.22 to 5.2 days and energy ranges between 270 GeV to 8.55 TeV. No significant gamma-ray emission has been found. The derived upper limits on the very-high-energy gamma-ray flux for the first time constrain non-thermal, high-energy emission following the merger of a confirmed binary neutron star system.
CRIS-Team WoS Importer:2020-01-15

THE 2010 MAY FLARING EPISODE OF CYGNUS X-3 IN RADIO, X-RAYS, AND gamma-RAYS - Williams, Peter K. G.; Tomsick, John A.; Bodaghee, Arash; Bower, Geoffrey C.; Pooley, Guy G.; Pottschmidt, Katja; Rodriguez, Jerome; Wilms, Jörn; Migliari, Simone; Trushkin, Sergei A. (Astrophysical Journal Letters, 2011)
In 2009, Cygnus X-3 (Cyg X-3) became the first microquasar to be detected in the GeV gamma-ray regime, via the satellites Fermi and AGILE. The addition of this new band to the observational toolbox holds promise for building a more detailed understanding of the relativistic jets of this and other systems. We present a rich data set of radio, hard and soft X-ray, and gamma-ray observations of Cyg X-3 made during a flaring episode in 2010 May. We detect a similar to 3 day softening and recovery of the X-ray emission, followed almost immediately by a similar to 1 Jy radio flare at 15 GHz, followed by a 4.3 sigma gamma-ray flare (E > 100 MeV) similar to 1.5 days later. The radio sampling is sparse, but we use archival data to argue that it is unlikely the gamma-ray flare was followed by any significant unobserved radio flares. In this case, the sequencing of the observed events is difficult to explain in a model in which the gamma-ray emission is due to inverse Compton scattering of the companion star's radiation field. Our observations suggest that other mechanisms may also be responsible for gamma-ray emission from Cyg X-3.
Keywords: black hole physics; X-rays: binaries; X-rays: individual (Cygnus X-3)

The 2014 TeV γ-Ray Flare of Mrk 501 Seen with H.E.S.S.: Temporal and Spectral Constraints on Lorentz Invariance Violation - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Arrieta, M.; Backes, M.; Barnard, M.; Becherini, Y.; Tjus, J. Becker; et al. (Astrophysical Journal, 2019)
The blazar Mrk 501 (z = 0.034) was observed at very-high-energy (VHE, E ≳ 100 GeV) gamma-ray wavelengths during a bright flare on the night of 2014 June 23-24 (MJD 56832) with the H.E.S.S. phase-II array of Cherenkov telescopes. Data taken that night by H.E.S.S. at large zenith angle reveal an exceptional number of gamma-ray photons at multi-TeV energies, with rapid flux variability and an energy coverage extending significantly up to 20 TeV. This data set is used to constrain Lorentz invariance violation (LIV) using two independent channels: a temporal approach considers the possibility of an energy dependence in the arrival time of gamma-rays, whereas a spectral approach considers the possibility of modifications to the interaction of VHE gamma-rays with extragalactic background light (EBL) photons. The non-detection of energy-dependent time delays and the non-observation of deviations between the measured spectrum and that of a supposed power-law intrinsic spectrum with standard EBL attenuation are used independently to derive strong constraints on the energy scale of LIV (E QG ) in the subluminal scenario for linear and quadratic perturbations in the dispersion relation of photons. For the case of linear perturbations, the 95% confidence level limits obtained are E QG,1 > 3.6 ×10 17 GeV using the temporal approach and E QG,1 > 2.6 ×10 19 GeV using the spectral approach. For the case of quadratic perturbations, the limits obtained are E QG,2 > 8.5 ×10 10 GeV using the temporal approach and E QG,2 > 7.8 ×10 11 GeV using the spectral approach.
CRIS-Team Scopus Importer:2019-05-14
Keywords: astroparticle physics; BL Lacertae objects: individual (Mrk 501); gamma rays: galaxies

The 2017 Failed Outburst of GX 339-4: Relativistic X-Ray Reflection near the Black Hole Revealed by NuSTAR and Swift Spectroscopy - Garcia, Javier A.; Tomsick, John A.; Sridhar, Navin; Grinberg, Victoria; Connors, Riley M. T.; Wang, Jingyi; Steiner, James F.; Dauser, Thomas; Walton, Dominic J.; Xu, Yanjun; Harrison, Fiona A.; Foster, Karl; et al. (Astrophysical Journal, 2019)
We report on the spectroscopic analysis of the black hole binary GX 339-4 during its recent 2017-2018 outburst, observed simultaneously by the Swift and NuSTAR observatories. Although during this particular outburst the source failed to make state transitions, and despite Sun constraints during the peak luminosity, we were able to trigger four different observations sampling the evolution of the source in the hard state. We show that even for the lowest-luminosity observations the NuSTAR spectra show clear signatures of X-ray reprocessing (reflection) in an accretion disk. Detailed analysis of the highest signal-to-noise spectra with our family of relativistic reflection models relxill indicates the presence of both broad and narrow reflection components. We find that a dual-lamppost model provides a superior fit when compared to the standard single lamppost plus distant neutral reflection. In the dual-lamppost model two sources at different heights are placed on the rotational axis of the black hole, suggesting that the narrow component of the Fe K emission is likely to originate in regions far away in the disk, but still significantly affected by its rotational motions. Regardless of the geometry assumed, we find that the inner edge of the accretion disk reaches a few gravitational radii in all our fits, consistent with previous determinations at similar luminosity levels. This confirms a very low degree of disk truncation for this source at luminosities above ∼1% Eddington. Our estimates of R in reinforce the suggested behavior for an inner disk that approaches the innermost regions as the luminosity increases in the hard state.
CRIS-Team Scopus Importer:2021-04-20
Keywords: accretion; accretion disks; atomic processes; black hole physics; line: formation; X-rays: individual (GX 339-4)

The 35-day cycle in the X-ray binary HZ Her/Her X-1 - Kolesnikov, D.; Shakura, N.; Postnov, K.; Volkov, I.; Bikmaev, I.; Irsmambetova, T.; Staubert, R.; Wilms, Jörn; Irtuganov, E.; Shurygin, P.; Golysheva, P.; Shugarov, S.; et al. (Contributions of the Astronomical Observatory Skalnate Pleso, 2020)
We present the results of modelling the 35-day superorbital changes in the B and V lightcurves and X-ray flux of HZ Her/Her X-1. The model is implemented in a computer program written in the C programming language, with a module for parameter optimisation written in Python. The model includes a tilted precessing and warped accretion disc around a freely precessing neutron star. The disc is warped near its inner edge due to interaction with the rotating neutron star magnetosphere. The magnetic torque depends on the precessional phase of the neutron star. The neutron star X-ray emission flux also depends on the free precession phase, which modulates the X-ray illumination of the optical star's atmosphere and the intensity of gas streams. We demonstrate that this model is able to reproduce both the optical observations of HZ Her and the behaviour of the system's 35-day X-ray cycle.
CRIS-Team WoS Importer:2020-04-21

THE 5 hr PULSE PERIOD AND BROADBAND SPECTRUM OF THE SYMBIOTIC X-RAY BINARY 3A 1954+319 - Marcu, Diana M.; Fürst, Felix; Pottschmidt, Katja; Grinberg, Victoria; Müller, Sebastian; Wilms, Jörn; Postnov, Konstantin A.; Corbet, Robin H. D.; Markwardt, Craig B.; Cadolle Bel, Marion (Astrophysical Journal Letters, 2011)
We present an analysis of the highly variable accreting X-ray pulsar 3A 1954 + 319 using 2005-2009 monitoring data obtained with INTEGRAL and Swift. This considerably extends the pulse period history and covers flaring episodes in 2005 and 2008. In 2006 the source was identified as one of only a few known symbiotic X-ray binaries (SyXBs), i.e., systems composed of a neutron star accreting from the inhomogeneous medium around an M-giant star. The extremely long pulse period of similar to 5.3 hr is directly visible in the 2008 INTEGRAL-ISGRI outburst light curve. The pulse profile is double peaked and generally not significantly energy dependent although there is an indication of possible softening during the main pulse. During the outburst a strong spin-up of -1.8 x 10(-4) hr hr(-1) occurred. Between 2005 and 2008 a long-term spin-down trend of 2.1 x 10(-5) hr hr(-1) was observed for the first time for this source. The 3-80 keV pulse peak spectrum of 3A 1954 + 319 during the 2008 flare could be well described by a thermal Comptonization model. We interpret the results within the framework of a recently developed quasi-spherical accretion model for SyXBs.
Keywords: binaries: symbiotic; stars: individual (3A 1954+319); stars: neutron; X-rays: binaries

THE ACCRETION DISK CORONA AND DISK ATMOSPHERE OF 4U 1624-490 AS VIEWED BY THE CHANDRA-HIGH ENERGY TRANSMISSION GRATING SPECTROMETER - Xiang, Jingen; Lee, Julia C.; Nowak, Michael A.; Wilms, Jörn; Schulz, Norbert S. (Astrophysical Journal, 2009)
We present a detailed spectral study ( photoionization modeling and variability) of the "Big Dipper" 4U 1624-490 based on a Chandra-High Energy Transmission Grating Spectrometer ( HETGS) observation over the similar to 76 ks binary orbit of 4U 1624-490. While the continuum spectrum can be modeled using a blackbody plus power law, a slightly better fit is obtained using a single Gamma = 2.25 power-law partially ( 71%) covered by a local absorber of column density N-H, Local = 8.1(-0.6)(+0.7) x 10(22) cm(-2). The data show a possible quasi-sinusoidal modulation with period 43(-9)(+13) ks that might be due to changes in local obscuration. Photoionization modeling with the xstar code and variability studies of the observed strong Fe xxv and Fe XXVI absorption lines point to a two-temperature plasma for their origin: a highly ionized component of ionization parameter xi(hot) approximate to 10(4.3) erg cm s(-1) ( T similar to 3.0 x 10(6) K) associated with an extended accretion disk corona of radius R similar to 3 x 10(10) cm, and a less-ionized more variable component of xi approximate to 10(3.4) erg cm s(-1) ( T similar to 1.0 x 10(6) K) and xi approximate to 10(3.1) erg cm s(-1) ( T similar to 0.9 x 10(6) K) coincident with the accretion disk rim. We use this, with the observed Fe xxv and Fe XXVI absorption line variations ( in wavelength, strength, and width) to construct a viewing geometry that is mapped to changes in plasma conditions over the 4U 1624-490 orbital period.
Keywords: accretion; accretion disks; plasmas; X-rays: binaries; X-rays: individual (4U 1624-490)

The accretion environment in Vela X-1 during a flaring period using XMM-Newton - Martinez-Nunez, Silvia; Torrejon, J. M.; Kühnel, Matthias; Kretschmar, Peter; Stuhlinger, M.; Rodes-Roca, J. J.; Fuerst, F.; Kreykenbohm, Ingo; Martin-Carrillo, A.; Pollock, A. M. T.; Wilms, Jörn (Astronomy & Astrophysics, 2014)
We present analysis of 100 ks contiguous XMM-Newton data of the prototypical wind accretor Vela X-1. The observation covered eclipse egress between orbital phases 0.134 and 0.265, during which a giant flare took place, enabling us to study the spectral properties both outside and during the flare. This giant flare with a peak luminosity of 3.92(-0.09)(+0.42) x 10(37) erg s(-1) allows estimates of the physical parameters of the accreted structure with a mass of similar to 10(21) g. We have been able to model several contributions to the observed spectrum with a phenomenological model formed by three absorbed power laws plus three emission lines. After analysing the variations with orbital phase of the column density of each component, as well as those in the Fe and Ni fluorescence lines, we provide a physical interpretation for each spectral component. Meanwhile, the first two components are two aspects of the principal accretion component from the surface of the neutron star, the third component seems to be the X-ray light echo formed in the stellar wind of the companion.
Keywords: X-rays: binaries; pulsars: individual: Vela X-1

The ANTARES telescope neutrino alert system - Ageron, M.; Aguilar, J. A.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Jesus, A. C. Assis; Astraatmadja, T.; Aubert, J. -J.; et al. (Astroparticle Physics, 2012)
The ANTARES telescope has the capability to detect neutrinos produced in astrophysical transient sources. Potential sources include gamma-ray bursts, core collapse supernovae, and flaring active galactic nuclei. To enhance the sensitivity of ANTARES to such sources, a new detection method based on coincident observations of neutrinos and optical signals has been developed. A fast online muon track reconstruction is used to trigger a network of small automatic optical telescopes. Such alerts are generated for special events, such as two or more neutrinos, coincident in time and direction, or single neutrinos of very high energy. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: ANTARES; Neutrino astronomy; Transient sources; Optical follow-up

The ASKAP-EMU Early Science Project: 888 MHz radio continuum survey of the Large Magellanic Cloud - Pennock, Clara M.; Van Loon, Jacco Th; Filipović, Miroslav D.; Andernach, Heinz; Haberl, Frank; Kothes, Roland; Lenc, Emil; Rudnick, Lawrence; White, Sarah V.; Agliozzo, Claudia; Antón, Sonia; Bojičić, Ivan; et al. (Monthly Notices of the Royal Astronomical Society, 2021)
We present an analysis of a new 120 deg2 radio continuum image of the Large Magellanic Cloud (LMC) at 888 MHz with a bandwidth of 288 MHz and beam size of 13".9 × 12".1 from the Australian Square Kilometre Array Pathfinder processed as part of the Evolutionary Map of the Universe survey. The median root mean squared noise is 58 μJy beam-1. We present a catalogue of 54 612 sources, divided over a Gold list (30 866 sources) complete down to 0.5 mJy uniformly across the field, a Silver list (22 080 sources) reaching down to <0.2 mJy, and a Bronze list (1666 sources) of visually inspected sources in areas of high noise and/or near bright complex emission. We discuss detections of planetary nebulae and their radio luminosity function, young stellar objects showing a correlation between radio luminosity and gas temperature, novae and X-ray binaries in the LMC, and active stars in the Galactic foreground that may become a significant population below this flux level. We present examples of diffuse emission in the LMC (H ii regions, supernova remnants, bubbles) and distant galaxies showcasing spectacular interaction between jets and intracluster medium. Among 14 333 infrared counterparts of the predominantly background radio source population, we find that star-forming galaxies become more prominent below 3 mJy compared to active galactic nuclei. We combine the new 888 MHz data with archival Australia Telescope Compact Array data at 1.4 GHz to determine spectral indices; the vast majority display synchrotron emission but flatter spectra occur too. We argue that the most extreme spectral index values are due to variability.
CRIS-Team Scopus Importer:2021-08-20
Keywords: Magellanic Clouds; Planetary nebulae: general; Radio continuum: galaxies; Radio continuum: ISM; Radio continuum: stars; Surveys

The ASKAP EMU early Science project: Radio continuum survey of the Small Magellanic Cloud - Joseph, T. D.; Filipović, M. D.; Crawford, E. J.; Bojičić, I.; Alexander, E. L.; Wong, G. F.; Andernach, H.; Leverenz, H.; Norris, R. P.; Alsaberi, R. Z.E.; Anderson, C.; Barnes, L. A.; et al. (Monthly Notices of the Royal Astronomical Society, 2019)
We present two new radio continuum images from the Australian Square Kilometre Array Pathfinder (ASKAP) survey in the direction of the Small Magellanic Cloud (SMC). These images are part of the Evolutionary Map of the Universe (EMU) Early Science Project (ESP) survey of the Small and Large Magellanic Clouds. The two new source lists produced from these images contain radio continuum sources observed at 960 MHz (4489 sources) and 1320 MHz (5954 sources) with a bandwidth of 192 MHz and beam sizes of 30.0 × 30.0 arcsec2 and 16.3 × 15.1 arcsec2, respectively. The median root mean square (RMS) noise values are 186 μJy beam−1 (960 MHz) and 165 μJy beam−1 (1320 MHz). To create point source catalogues, we use these two source lists, together with the previously published Molonglo Observatory Synthesis Telescope (MOST) and the Australia Telescope Compact Array (ATCA) point source catalogues to estimate spectral indices for the whole population of radio point sources found in the survey region. Combining our ASKAP catalogues with these radio continuum surveys, we found 7736 point-like sources in common over an area of 30 deg2. In addition, we report the detection of two new, low surface brightness supernova remnant candidates in the SMC. The high sensitivity of the new ASKAP ESP survey also enabled us to detect the bright end of the SMC planetary nebula sample, with 22 out of 102 optically known planetary nebulae showing point-like radio continuum emission. Lastly, we present several morphologically interesting background radio galaxies.
CRIS-Team Scopus Importer:2019-11-29
Keywords: Catalogues; Magellanic Clouds

The Athena X-IFU Instrument Simulator xifusim - Kirsch, Christian; Lorenz, Maximilian; Peille, P.; Dauser, Thomas; Ceballos, M. T.; Cobo, B.; Merino-Alonso, P. E.; Cucchetti, E.; Smith, S. J.; Gottardi, L.; Hartog, R. H.den; Miniussi, A.; et al. (Journal of Low Temperature Physics, 2022)
We present the instrument simulator xifusim developed for the X-ray Integral Field Unit X-IFU aboard the planned Athena mission. xifusim aims to be an accurate representation of the entire instrument, starting from a full simulation of the Transition-Edge Sensor (TES) array receiving impact photons unconstrained by the small signal limit. Its output current is then propagated through the entire readout chain, including multiplexing, amplification and the digital readout. The final output consists of triggered records, which can be post-processed to reconstruct the photon energies. The readout chain itself is separated into individual, modular blocks with several possible models for each, allowing the simulation of different readout schemes or models of varying physical accuracy at the expense of run time. New models are implemented as necessary to enable studies of the overall readout chain. Such studies are also facilitated by fine-grained control of the simulation output, including the internal state of intermediate simulation blocks. In addition to its modularity, xifusim also allows the manipulation of certain internal parameters during a run, enabling the simulation of readout chain characterization measurements, environmental drifts or various kinds of crosstalk.
CRIS-Team Scopus Importer:2022-03-18
Keywords: Athena; Simulations; TES; X-IFU

The Athena X-ray Integral Field Unit: a consolidated design for the system requirement review of the preliminary definition phase - Barret, Didier; Albouys, Vincent; Den Herder, Jan-Willem; Piro, Luigi; Cappi, Massimo; Huovelin, Juhani; Kelley, Richard; Miguel Mas-Hesse, J.; Paltani, Stephane; Rauw, Gregor; Rozanska, Agata; Svoboda, Jiri; et al. (Experimental Astronomy, 2023)
The Athena X-ray Integral Unit (X-IFU) is the high resolution X-ray spectrometer studied since 2015 for flying in the mid-30s on the Athena space X-ray Observatory. Athena is a versatile observatory designed to address the Hot and Energetic Universe science theme, as selected in November 2013 by the Survey Science Committee. Based on a large format array of Transition Edge Sensors (TES), X-IFU aims to provide spatially resolved X-ray spectroscopy, with a spectral resolution of 2.5 eV (up to 7 keV) over a hexagonal field of view of 5 arc minutes (equivalent diameter). The X-IFU entered its System Requirement Review (SRR) in June 2022, at about the same time when ESA called for an overall X-IFU redesign (including the X-IFU cryostat and the cooling chain), due to an unanticipated cost overrun of Athena. In this paper, after illustrating the breakthrough capabilities of the X-IFU, we describe the instrument as presented at its SRR (i.e. in the course of its preliminary definition phase, so-called B1), browsing through all the subsystems and associated requirements. We then show the instrument budgets, with a particular emphasis on the anticipated budgets of some of its key performance parameters, such as the instrument efficiency, spectral resolution, energy scale knowledge, count rate capability, non X-ray background and target of opportunity efficiency. Finally, we briefly discuss the ongoing key technology demonstration activities, the calibration and the activities foreseen in the X-IFU Instrument Science Center, touch on communication and outreach activities, the consortium organisation and the life cycle assessment of X-IFU aiming at minimising the environmental footprint, associated with the development of the instrument. Thanks to the studies conducted so far on X-IFU, it is expected that along the design-to-cost exercise requested by ESA, the X-IFU will maintain flagship capabilities in spatially resolved high resolution X-ray spectroscopy, enabling most of the original X-IFU related scientific objectives of the Athena mission to be retained. The X-IFU will be provided by an international consortium led by France, The Netherlands and Italy, with ESA member state contributions from Belgium, Czech Republic, Finland, Germany, Poland, Spain, Switzerland, with additional contributions from the United States and Japan.
CRIS-Team WoS Importer:2023-03-17

The Athena X-ray Integral Field Unit (X-IFU) - Barret, Didier; Lam Trong, Thien; Den Herder, Jan Willem; Piro, Luigi; Barcons, Xavier; Huovelin, Juhani; Kelley, Richard; Mas-Hesse, J. Miguel; Mitsuda, Kazuhisa; Paltani, Stéphane; Rauw, Gregor; Rozanska, Agata; et al. (Space Telescopes and Instrumentation 2016: Ultraviolet to Gamma Ray, 2016)
The X-ray Integral Field Unit (X-IFU) on board the Advanced Telescope for High-ENergy Astrophysics (Athena) will provide spatially resolved high-resolution X-ray spectroscopy from 0.2 to 12 keV, with ∼ 5" pixels over a field of view of 5 arc minute equivalent diameter and a spectral resolution of 2.5 eV up to 7 keV. In this paper, we first review the core scientific objectives of Athena, driving the main performance parameters of the X-IFU, namely the spectral resolution, the field of view, the effective area, the count rate capabilities, the instrumental background. We also illustrate the breakthrough potential of the X-IFU for some observatory science goals. Then we brie y describe the X-IFU design as defined at the time of the mission consolidation review concluded in May 2016, and report on its predicted performance. Finally, we discuss some options to improve the instrument performance while not increasing its complexity and resource demands (e.g. count rate capability, spectral resolution).
Keywords: Athena; Instrumentation; Space telescopes; X-ray Integral Field Unit; X-ray spectroscopy

The Athena X-ray Integral Field Unit (X-IFU) - Pajot, F.; Barret, D.; Lam-Trong, T.; Den Herder, J. -W.; Piro, Luigi; Cappi, M.; Huovelin, Juhani; Kelley, R.; Mas-Hesse, J. M.; Mitsuda, K.; Paltani, S.; Rauw, G.; et al. (Journal of Low Temperature Physics, 2018)
The X-ray Integral Field Unit (X-IFU) of the Advanced Telescope for High-ENergy Astrophysics (Athena) large-scale mission of ESA will provide spatially resolved high-resolution X-ray spectroscopy from 0.2 to 12 keV, with 5 '' pixels over a field of view of 5 arc minute equivalent diameter and a spectral resolution of 2.5 eV (FWHM) up to 7 keV. The core scientific objectives of Athena drive the main performance parameters of the X-IFU. We present the current reference configuration of the X-IFU, and the key issues driving the design of the instrument.
Keywords: X-ray astronomy; Imaging spectroscopy; Microcalorimeter

The atmospheric monitoring system of the JEM-EUSO instrument - Adams, J. H.; Ahmad, S.; Albert, J. -N.; Allard, D.; Anchordoqui, L.; Andreev, V.; Anzalone, A.; Arai, Y.; Asano, K.; Ave Pernas, M.; Baragatti, P.; Barrillon, P.; et al. (Experimental Astronomy, 2015)
The JEM-EUSO telescope will detect Ultra-High Energy Cosmic Rays (UHECRs) from space, detecting the UV Fluorescence Light produced by Extensive Air Showers (EAS) induced by the interaction of the cosmic rays with the earth's atmosphere. The capability to reconstruct the properties of the primary cosmic ray depends on the accurate measurement of the atmospheric conditions in the region of EAS development. The Atmospheric Monitoring (AM) system of JEM-EUSO will host a LIDAR, operating in the UV band, and an Infrared camera to monitor the cloud cover in the JEM-EUSO Field of View, in order to be sensitive to clouds with an optical depth tau a parts per thousand yen 0.15 and to measure the cloud top altitude with an accuracy of 500 m and an altitude resolution of 500 m.
Keywords: Ultra high energy cosmic rays; Atmospheric monitoring; IR camera; LIDAR

THE Be/X-RAY BINARY SWIFT J1626.6-5156 AS A VARIABLE CYCLOTRON LINE SOURCE - Decesar, Megan E.; Boyd, Patricia T.; Pottschmidt, Katja; Wilms, Jörn; Suchy, Slawomir; Miller, M. Coleman (Astrophysical Journal, 2013)
Swift J1626.6-5156 is a Be/X-ray binary that was in outburst from 2005 December until 2008 November. We have examined Rossi X-ray Timing Explorer/Proportional Counter Array (PCA) and High Energy X-ray Timing Explorer spectra of three long observations of this source taken early in its outburst, when the PCA 2-20 keV count rate was > 70 counts s(-1) PCU-1, as well as several combined observations from different stages of the outburst. The spectra are best fit with an absorbed cutoff power law with a similar to 6.4 keV iron emission line and a Gaussian optical depth absorption line at similar to 10 keV. We present strong evidence that this absorption-like feature is a cyclotron resonance scattering feature, making Swift J1626.6-5156 a new candidate cyclotron line source. The redshifted energy of similar to 10 keV implies a magnetic field strength of similar to 8.6(1 + z) x 10(11) G in the region of the accretion column close to the magnetic poles where the cyclotron line is produced. Analysis of phase-averaged spectra spanning the duration of the outburst suggests a possible positive correlation between the fundamental cyclotron energy and source luminosity. Phase-resolved spectroscopy from a long observation reveals a variable cyclotron line energy, with phase dependence similar to a variety of other pulsars, as well as the first harmonic of the fundamental cyclotron line.
Keywords: magnetic fields; stars: individual (Swift J1626.6-5156); stars: neutron; X-rays: binaries

The broadband spectrum of cygnus X-1 - Wilms, Jörn; et al. (2007)
The Black Hole (BH) binary Cygnus X-1 has been observed simultaneously by INTEGRAL, RXTE, and XMM-Newton for four times in November and December 2004, when Cyg X-1 became first observable with XMM-Newton. During these observations the source was found in one of its transitional states between the hard state and the soft state. We obtained a high signal to noise spectrum of Cyg X-1 from 3 keV to 1 MeV which allows us to put constraints on the nature of the Comptonizing plasma by modeling the continuum with Comptonization models as eqpair [3]. Using XMM-Newton we were also able to confirm the presence of a relativistically broadened Fe K alpha line.
Keywords: stars : individual (Cyg X-1); black hole physics

The broad iron K alpha line of Cygnus X-1 as seen by XMM-Newton in the EPIC-pn modified timing mode - Duro, Refiz; Dauser, Thomas; Wilms, Jörn; Pottschmidt, K.; Nowak, M. A.; Fritz, S.; Kendziorra, E.; Kirsch, M. G. F.; Reynolds, C. S.; Staubert, R. (Astronomy & Astrophysics, 2011)
We present the analysis of the broadened, flourescent iron K alpha line in simultaneous XMM-Newton and RXTE data from the black hole Cygnus X-1. The XMM-Newton data were taken in a modified version of the timing mode of the EPIC-pn camera. In this mode the lower energy threshold of the instrument is increased to 2.8 keV to avoid telemetry drop outs due to the brightness of the source, while at the same time preserving the signal-to-noise ratio in the FeK alpha band. We find that the best-fit spectrum consists of the sum of an exponentially cutoff power-law and relativistically smeared, ionized reflection. The shape of the broadened FeKa feature is due to strong Compton broadening combined with relativistic broadening. Assuming a standard, thin accretion disk, the black hole is close to rotating maximally.
Keywords: X-rays: binaries; black hole physics; gravitation

The catalogue of radial velocity variable hot subluminous stars from the MUCHFUSS project - Geier, S.; Kupfer, Thomas; Heber, Ulrich; Schaffenroth, Veronika; Barlow, B. N.; Ostensen, R. H.; O'Toole, S. J.; Ziegerer, Eva; Heuser, Christian; Maxted, P. F. L.; Gaensicke, B. T.; Marsh, T. R.; et al. (Astronomy & Astrophysics, 2015)
The project Massive Unseen Companions to Hot Faint Underluminous Stars from SDSS (MUCHFUSS) aims to find sdBs with compact companions such as massive white dwarfs, neutron stars, or black holes. Here we provide classifications, atmospheric parameters, and a complete radial velocity (RV) catalogue containing 1914 single measurements for a sample of 177 hot subluminous stars discovered based on SDSS DR7; 110 stars show significant RV variability, while 67 qualify as candidates. We constrain the fraction of close massive compact companions of hydrogen-rich hot subdwarfs in our sample to be smaller than ∼1.3%, which is already close to the theoretical predictions. However, the sample might still contain such binaries with longer periods exceeding ∼8 d. We detect a mismatch between the ΔRVmax-distribution of the sdB and the more evolved sdOB and sdO stars, which challenges our understanding of their evolutionary connection. Furthermore, irregular RV variations of unknown origin with amplitudes of up to ∼180 km s-1 on timescales of years, days, and even hours have been detected in some He-sdO stars. They might be connected to irregular photometric variations in some cases.
CRIS-Team Scopus Importer:2020-12-21
Keywords: Binaries: spectroscopic; Stars: atmospheres; Stars: horizontal-branch; Subdwarfs

The catalogue of radial velocity variable hot subluminous stars from the MUCHFUSS project (vol 577, pg A26, 2015) - Geier, S.; Kupfer, T.; Heber, Ulrich; Schaffenroth, Veronika; Barlow, B. N.; Ostensen, R. H.; O'Toole, S. J.; Ziegerer, Eva; Heuser, Christian; Maxted, P. F. L.; Gansicke, B. T.; Marsh, T. R.; et al. (Astronomy & Astrophysics, 2017)
Keywords: binaries: spectroscopic; subdwarfs; stars: horizontal branch; stars: atmospheres; errata; addenda

The causal connection between disc and power-law variability in hard state black hole X-ray binaries - Uttley, P.; Wilkinson, T.; Cassatella, P.; Wilms, Jörn; Pottschmidt, K.; Hanke, Manfred; Böck, Moritz (Monthly Notices of the Royal Astronomical Society, 2011)
We use the XMM-Newton EPIC-pn instrument in timing mode to extend spectral time-lag studies of hard state black hole X-ray binaries into the soft X-ray band. We show that variations of the disc blackbody emission substantially lead variations in the power-law emission, by tenths of a second on variability time-scales of seconds or longer. The large lags cannot be explained by Compton scattering but are consistent with time delays due to viscous propagation of mass accretion fluctuations in the disc. However, on time-scales less than a second the disc lags the power-law variations by a few milliseconds, consistent with the disc variations being dominated by X-ray heating by the power law, with the short lag corresponding to the light traveltime between the power-law emitting region and the disc. Our results indicate that instabilities in the accretion disc are responsible for continuum variability on time-scales of seconds or longer and probably also on shorter time-scales.
Keywords: accretion; accretion discs; X-rays: binaries; X-rays: individual: GX 339-4

The Chandra ACIS Survey of M33 (ChAseM33): Transient X-ray sources discovered in M33 - Williams, Benjamin F.; Gaetz, Terrance J.; Haberl, Frank; Pietsch, Wolfgang; Shporer, Avi; Ghavamian, Parviz; Plucinsky, Paul P.; Mazeh, Tsevi; Sasaki, Manami; Pannuti, Thomas (Astrophysical Journal, 2008)
The Chandra ACIS Survey of M33 (ChASeM33) has acquired seven fields of ACIS data covering M33 with 200 ks of exposure in each field. A catalog from the first 10 months of data, along with archival Chandra observations dating back to the year 2000, is currently available. We have searched these data for transient sources that are measured to have a 0.35-8.0 keV unabsorbed luminosity of at least 4 x 10(35) ergs s(-1) in one epoch and are not detected in another epoch. This set of the survey data has yielded seven such sources, including one previously known supersoft source. We analyzed XMM-Newton data from the archive distributed over the years 2000-2003 to search for recurrent outbursts and to get a spectrum for the supersoft transient. We find only one recurrent transient in our sample. The X-ray spectra, light curves, and optical counterpart candidates of two of the other sources suggest that they are high-mass X-ray binaries. Archival Spitzer photometry and high X-ray absorption suggest that one of the sources is a highly variable background active galactic nucleus. The other three sources are more difficult to classify. The bright transient population of M33 appears to contain a large fraction of high-mass X-ray binaries compared with the transient populations of M31 and the Galaxy, reflecting the later morphology of M33.
Keywords: binaries : close; galaxies : individual (M33); X-rays : binaries; X-rays : stars

The clumpy absorber in the high-mass X-ray binary Vela X-1 - Grinberg, Victoria; Hell, Natalie; El Mellah, I.; Neilsen, J.; Sander, A. A. C.; Leutenegger, M.; Furst, F.; Huenemoerder, D. P.; Kretschmar, Peter; Kühnel, Matthias; Martinez-Nunez, Silvia; Niu, Shu; et al. (Astronomy & Astrophysics, 2017)
Bright and eclipsing, the high-mass X-ray binary Vela X-1 offers a unique opportunity to study accretion onto a neutron star from clumpy winds of O/B stars and to disentangle the complex accretion geometry of these systems. In Chandra-HETGS spectroscopy at orbital phase similar to 0.25, when our line of sight towards the source does not pass through the large-scale accretion structure such as the accretion wake, we observe changes in overall spectral shape on timescales of a few kiloseconds. This spectral variability is, at least in part, caused by changes in overall absorption and we show that such strongly variable absorption cannot be caused by unperturbed clumpy winds of O/B stars. We detect line features from high and low ionization species of silicon, magnesium, and neon whose strengths and presence depend on the overall level of absorption. These features imply a co-existence of cool and hot gas phases in the system, which we interpret as a highly variable, structured accretion flow close to the compact object such as has been recently seen in simulations of wind accretion in high-mass X-ray binaries.
Keywords: X-rays: individuals: Vela X-1; X-rays: binaries; stars: winds; outflows; stars: massive

The column density towards LMC X-1 - Hanke, Manfred; Wilms, Jörn; Nowak, M. A.; Barragan, L.; Schulz, N. S. (Astronomy & Astrophysics, 2010)
We measure the neutral absorption towards the black hole X-ray binary system LMC X-1 from six archival soft X-ray spectra obtained with the gratings and/or CCD detectors on Chandra, XMM-Newton, and Swift. Four spectral models for the soft continuum are investigated. While the power law model may overestimate N-H considerably, the others give consistent results. Taking the lower metalicity of the Large Magellanic Cloud into account, we find equivalent hydrogen column densities of N-H = (1.0-1.3) x 10(22) cm(-2), with a systematic dependence on the orbital phase. This variation in the neutral absorption can nearly explain the orbital modulation of the soft X-ray flux recently detected with the All Sky Monitor (ASM) on the Rossi X-ray Timing Explorer (RXTE).
Keywords: X-rays: individuals: LMC X-1; X-rays: binaries; X-rays: ISM; galaxies: abundances

THE COMPLEX ACCRETION GEOMETRY OF GX 339-4 AS SEEN BY NuSTAR AND SWIFT - Fuerst, F.; Nowak, M. A.; Tomsick, J. A.; Miller, J. M.; Corbel, S.; Bachetti, Matteo; Boggs, S. E.; Christensen, F. E.; Craig, W. W.; Fabian, A. C.; Gandhi, P.; Grinberg, Victoria; et al. (Astrophysical Journal, 2015)
We present spectral analyses of five Nuclear Spectroscopic Telescope Array and Swift observations of GX 339-4 taken during a failed outburst during the summer of 2013. These observations cover Eddington luminosity fractions in the range approximate to 0.9%-6%. Throughout this outburst GX 339-4 stayed in the hard state and all five observations show similar X-ray spectra, with a hard power law with a photon index near 1.6, and significant contribution from reflection. Using simple reflection models we find unrealistically high iron abundances. Allowing for different photon indices for the continuum incident on the reflector relative to the underlying observed continuum results in a statistically better fit and reduced iron abundances. With a photon index around 1.3, the input power law on the reflector is significantly harder than that which is directly observed. We study the influence of different emissivity profiles and geometries and consistently find an improvement when using separate photon indices. The inferred inner accretion disk radius is strongly model dependent, but we do not find evidence for a truncation radius larger than 100 r(g) in any model. The data do not allow independent spin constraints, but the results are consistent with the literature (i.e., a > 0). Our best-fit models indicate an inclination angle in the range 40 degrees-60 degrees, consistent with limits on the orbital inclination but higher than reported in the literature using standard reflection models. The iron line around 6.4 keV is clearly broadened, and we detect a superimposed narrow core as well. This core originates from a fluorescent region outside the influence of the strong gravity of the black hole. Additionally, we discuss possible geometries.
Keywords: accretion; accretion disks; stars: black holes; X-rays: binaries; X-rays: individual (GX 339-4)

The cool companion of AA Doradus-Brown dwarf or late M star? - Mueller, S.; Geier, Stephan; Heber, Ulrich (Astrophysics and Space Science, 2010)
AA Dor is one of only seven known eclipsing binaries consisting of a hot subdwarf star and a low-mass companion. Although AA Dor has been studied in many investigations, a controversy about the nature of its companion persists. Is it a brown dwarf or a low-mass main sequence star?We reanalyse high resolution spectra using metal enhanced LTE model atmospheres. The optical spectra are polluted by reflected light from the companion. Using spectra taken during secondary eclipse, we derive atmospheric parameters consistent with results from the light curve. For the first time we achieve a self-consistent solution that matches all available observations, i.e. the light and radial velocity curves, as well as the atmospheric parameters.The resulting masses M-1 = 0.510(-0.108)(+0.125) M-circle dot and M-2 = 0.085(-0.023)(+0.031) M-circle dot are consistent with the canonical mass of an sdB star and a low-mass main sequence star. However, a brown dwarf companion cannot be excluded.
Keywords: Stars: binaries: close; Binaries: eclipsing; Stars: atmospheres; Stars: individual: AA Dor

The cosmic ray shadow of the Moon observed with the ANTARES neutrino telescope - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. -J.; Aublin, J.; Avgitas, T.; Baret, B.; Barrios-Martit, J.; Basa, S.; Belhorma, B.; et al. (European Physical Journal C, 2018)
One of the main objectives of the ANTARES telescope is the search for point- like neutrino sources. Both the pointing accuracy and the angular resolution of the detector are important in this context and a reliableway to evaluate this performance is needed. In order to measure the pointing accuracy of the detector, one possibility is to study the shadow of the Moon, i. e. the deficit of the atmospheric muon flux from the direction of the Moon induced by the absorption of cosmic rays. Analysing the data taken between 2007 and 2016, theMoon shadow is observed with 3.5s statistical significance. The detector angular resolution for downwardgoing muons is 0.73. +/- 0.14.. The resulting pointing performance is consistent with the expectations. An independent check of the telescope pointing accuracy is realised with the data collected by a shower array detector onboard of a ship temporarily moving around the ANTARES location.

The defocused observations of bright sources with Athena /X-IFU - Kammoun, E. S.; Barret, D.; Peille, P.; Willingale, R.; Dauser, Thomas; Wilms, Jörn; Guainazzi, M.; Miller, J. M. (Astronomy & Astrophysics, 2022)
Context. The X-ray Integral Field Unit (X-IFU) is the high resolution X-ray spectrometer of ESA's Athena X-ray observatory. It will deliver X-ray data in the 0.2- 12 keV band with an unprecedented spectral resolution of 2.5 eV up to 7 keV. During the observation of very bright X-ray sources the X-IFU detectors will receive high photon rates. The count rate capability of the X-IFU will be improved by using the defocusing option, which will enable the observations of extremely bright sources with fluxes up to 1 Crab. In the defocused mode, the point spread function (PSF) of the telescope will be spread over a large number of pixels. In this case each pixel receives a small fraction of the overall flux. Due to the energy dependence of the PSF, this mode will generate energy-dependent artefacts increasing with count rate if not analysed properly. To account for the degradation of the energy resolution with pulse separation in a pixel, a grading scheme (of four grades) will be defined to realize the proper energy response to each event. This will create selection effects preventing the use of the nominal auxiliary response file (ARF) for all events. Aims. We present a new method for the reconstruction of the spectra obtained from observations performed with a PSF that varies as a function of energy. We apply our method to the case of the X-IFU spectra obtained during the defocused observations. Methods. We used the end-to-end SIXTE simulator to model defocused X-IFU observations. Then we estimated a new ARF for each of the grades by calculating the effective area at the level of each pixel. Results. Our method allows us to successfully reconstruct the spectra of bright sources when employed in the defocused mode, without any bias. Finally, we address how various sources of uncertainty related to our knowledge of the PSF as a function of energy affect our results.
CRIS-Team Scopus Importer:2022-08-19
Keywords: Instrumentation: detectors; Techniques: spectroscopic; X-rays: general

The design of the wide field monitor for LOFT - Brandt, Soren; Hernanz, Margarita; Alvarez, L.; Argan, A.; Artigues, B.; Azzarello, P.; Barret, D.; Bozzo, E.; Budtz-Jorgensen,; Campana, Riccardo; Cros, A.; Del Monte, E.; et al. (2014)
LOFT (Large Observatory For x-ray Timing) is one of the ESA M3 missions selected within the Cosmic Vision program in 2011 to carry out an assessment phase study and compete for a launch opportunity in 2022-2024. The phase-A studies of all M3 missions were completed at the end of 2013. LOFT is designed to carry on-board two instruments with sensitivity in the 2-50 keV range: a 10 m(2) class Large Area Detector (LAD) with a < 1 degrees collimated FoV and a wide field monitor (WFM) making use of coded masks and providing an instantaneous coverage of more than 1/3 of the sky. The prime goal of the WFM will be to detect transient sources to be observed by the LAD. However, thanks to its unique combination of a wide field of view (FoV) and energy resolution (better than 500 eV), the WFM will be also an excellent monitoring instrument to study the long term variability of many classes of X-ray sources. The WFM consists of 10 independent and identical coded mask cameras arranged in 5 pairs to provide the desired sky coverage. We provide here an overview of the instrument design, configuration, and capabilities of the LOFT WFM. The compact and modular design of the WFM could easily make the instrument concept adaptable for other missions.
Keywords: ESA Missions; LOFT Wide Field Monitor; Silicon Drift Detectors; Coded Mask Imaging; Compact Objects; Gamma Ray Bursts

THE DOUBLE-DEGENERATE NUCLEUS OF THE PLANETARY NEBULA TS 01: A CLOSE BINARY EVOLUTION SHOWCASE - Tovmassian, Gagik; Yungelson, Lev; Rauch, Thomas; Suleimanov, Valery; Napiwotzki, Ralf; Stasinska, Grazyna; Tomsick, John; Wilms, Jörn; Morisset, Christophe; Pena, Miriam; Richer, Michael G. (Astrophysical Journal, 2010)
We present a detailed investigation of SBS 1150+599A, a close binary star hosted by the planetary nebula PN G135.9+55.9 (TS 01). The nebula, located in the Galactic halo, is the most oxygen-poor known to date and is the only one known to harbor a double degenerate core. We present XMM-Newton observations of this object, which allowed the detection of the previously invisible component of the binary core, whose existence was inferred so far only from radial velocity (RV) and photometric variations. The parameters of the binary system were deduced from a wealth of information via three independent routes using the spectral energy distribution (from the infrared to X-rays), the light and RV curves, and a detailed model atmosphere fitting of the stellar absorption features of the optical/UV component. We find that the cool component must have a mass of 0.54 +/- 0.2 M(circle dot), an average effective temperature, T(eff), of 58,000 +/- 3000 K, a mean radius of 0.43 +/- 0.3 R(circle dot), a gravity, log g = 5.0 +/- 0.3, and that it nearly fills its Roche lobe. Its surface elemental abundances are found to be: 12 + log He/H = 10.95 +/- 0.04 dex, 12 + log C/H = 7.20 +/- 0.3 dex, 12 + log N/H < 6.92, and 12 + log O/H < 6.80, in overall agreement with the chemical composition of the planetary nebula. The hot component has T(eff) = 160-180 kK, a luminosity of about similar to 10(4) L(circle dot) and a radius slightly larger than that of a white dwarf. It is probably bloated and heated as a result of intense accretion and nuclear burning on its surface in the past. The total mass of the binary system is very close to the Chandrasekhar limit. This makes TS 01 one of the best Type Ia supernova progenitor candidates. We propose two possible scenarios for the evolution of the system up to its present stage.
Keywords: binaries: close; planetary nebulae: individual (PN G135.9+55.9; TS 01); stars: AGB and post-AGB; stars: atmospheres; stars: evolution; stars: individual (SBS1150+599A)

The dust-scattering component of X-ray extinction: Effects on continuum fitting and high-resolution absorption edge structure - Corrales, L. R.; Garcia, J.; Wilms, Jörn; Baganoff, F. (Monthly Notices of the Royal Astronomical Society, 2016)
Small angle scattering by dust grains causes a significant contribution to the total interstellar extinction for any X-ray instrument with sub-arcminute resolution (Chandra, Swift, XMM-Newton). However, the dust-scattering component is not included in the current absorption models: phabs, TBabs, and TBnew. We simulate a large number of Chandra spectra to explore the bias in the spectral fit and N measurements obtained without including extinction from dust scattering. We find that without incorporating dust scattering, the measured N will be too large by a baseline level of 25 per cent. This effect is modulated by the imaging resolution of the telescope, because some amount of unresolved scattered light will be captured within the aperture used to extract point source information. In high-resolution spectroscopy, dust scattering significantly enhances the total extinction optical depth and the shape of the photoelectric absorption edges. We focus in particular on the Fe-L edge at 0.7 keV, showing that the total extinction template fits well to the high-resolution spectrum of three X-ray binaries from the Chandra archive: GX 9+9, XTE J1817-330, and Cyg X-1. In cases where dust is intrinsic to the source, a covering factor based on the angular extent of the dusty material must be applied to the extinction curve, regardless of angular imaging resolution. This approach will be particularly relevant for dust in quasar absorption line systems and might constrain clump sizes in active galactic nuclei.
Keywords: Absorption lines; Extinction-quasars; Scattering-dust; X-rays: Binaries; X-rays: ISM

The effect of returning radiation on relativistic reflection - Dauser, Thomas; Garcia, Javier; Joyce, Amy; Licklederer, Stefan; Connors, R. M. T.; Ingram, A.; Reynolds, C. S.; Wilms, Jörn (Monthly Notices of the Royal Astronomical Society, 2022)
We study the effect of returning radiation on the shape of the X-ray reflection spectrum in the case of thin accretion discs. We show that the returning radiation mainly influences the observed reflection spectrum for a large black hole spin (a > 0.9) and a compact primary source of radiation close to the black hole at height h < 5r(g), and that it dominates the reflected flux for extreme values of spin and compactness. The main effect of the returning radiation is to increase the irradiating flux on to the outer parts of the accretion disc, leading to stronger reflection and a flatter overall emissivity profile. By analysing simulated observations we show that neglecting returning radiation in existing studies of reflection-dominated sources has likely resulted in overestimating the height of the corona above the black hole. An updated version of the publicly available relxill suite of relativistic reflection models which includes returning radiation is also presented.
CRIS-Team WoS Importer:2022-07-08

The effects of high density on the X-ray spectrum reflected from accretion discs around black holes - Garcia, Javier A.; Fabian, Andrew C.; Kallman, Timothy R.; Dauser, Thomas; Parker, Michael L.; Mcclintock, Jeffrey E.; Steiner, James F.; Wilms, Jörn (Monthly Notices of the Royal Astronomical Society, 2016)
Current models of the spectrum of X-rays reflected from accretion discs around black holes and other compact objects are commonly calculated assuming that the density of the disc atmosphere is constant within several Thomson depths from the irradiated surface. An important simplifying assumption of these models is that the ionization structure of the gas is completely specified by a single, fixed value of the ionization parameter ξ, which is the ratio of the incident flux to the gas density. The density is typically fixed at ne = 10 cm. Motivated by observations, we consider higher densities in the calculation of the reflected spectrum. We show by computing model spectra for ne ≥ 10 cm that high-density effects significantly modify reflection spectra. The main effect is to boost the thermal continuum at energies ≥2 keV. We discuss the implications of these results for interpreting observations of both active galactic nuclei and black hole binaries. We also discuss the limitations of our models imposed by the quality of the atomic data currently available.
Keywords: Accretion; accretion discs; Atomic processes; Line: formation; Radiative transfer; Relativistic processes; X-rays: general

The enhanced X-ray Timing and Polarimetry mission – eXTP: an update on its scientific cases, mission profile and development status - Zhang, Shuang Nan; Santangelo, Andrea; Xu, Yupeng; Feroci, Marco; Hernanz, Margarita; Lu, Fangjun; Chen, Yong; Feng, Hua; Nandra, Kirpal; Jiang, Weichun; Svoboda, Jiri; Brandt, Søren; et al. (Proceedings of SPIE - The International Society for Optical Engineering, 2022)
The enhanced X-ray Timing and Polarimetry mission (eXTP) is a flagship observatory for X-ray timing, spectroscopy and polarimetry developed by an International Consortium. Thanks to its very large collecting area, good spectral resolution and unprecedented polarimetry capabilities, eXTP will explore the properties of matter and the propagation of light in the most extreme conditions found in the Universe. eXTP will, in addition, be a powerful X-ray observatory. The mission will continuously monitor the X-ray sky, and will enable multiwavelength and multi-messenger studies. The mission is currently in phase B, which will be completed in the middle of 2022.
CRIS-Team Scopus Importer:2022-11-04
Keywords: black hole; equation of state; extreme density; extreme gravity; extreme magnetism; neutron star; X-ray polarimetry; X-ray timing

The enhanced X-ray Timing and Polarimetry mission-eXTP - Zhang, Shuangnan; Santangelo, Andrea; Feroci, Marco; Xu, Yupeng; Lu, Fangjun; Chen, Yong; Feng, Hua; Zhang, Shu; Brandt, Soren; Hernanz, Margarita; Baldini, Luca; Bozzo, Enrico; et al. (Science China-Physics Mechanics & Astronomy, 2019)
In this paper we present the enhanced X-ray Timing and Polarimetry mission-eXTP. eXTP is a space science mission designed to study fundamental physics under extreme conditions of density, gravity and magnetism. The mission aims at determining the equation of state of matter at supra-nuclear density, measuring effects of QED, and understanding the dynamics of matter in strong-field gravity. In addition to investigating fundamental physics, eXTP will be a very powerful observatory for astrophysics that will provide observations of unprecedented quality on a variety of galactic and extragalactic objects. In particular, its wide field monitoring capabilities will be highly instrumental to detect the electro-magnetic counterparts of gravitational wave sources. The paper provides a detailed description of: (1) the technological and technical aspects, and the expected performance of the instruments of the scientific payload; (2) the elements and functions of the mission, from the spacecraft to the ground segment.
CRIS-Team WoS Importer:2019-03-08

The EREBOS project: Investigating the effect of substellar and low-mass stellar companions on late stellar evolution Survey, target selection, and atmospheric parameters - Schaffenroth, V.; Barlow, B. N.; Geier, S.; Vuckovic, M.; Kilkenny, D.; Wolz, Maximilian; Kupfer, T.; Heber, Ulrich; Drechsel, Horst; Kimeswenger, S.; Marsh, T.; Wolf, M.; et al. (Astronomy & Astrophysics, 2019)
Eclipsing post-common-envelope binaries are highly important for resolving the poorly understood, very short-lived common-envelope phase of stellar evolution. Most hot subdwarfs (sdO/Bs) are the bare helium-burning cores of red giants that have lost almost all of their hydrogen envelope. This mass loss is often triggered by common-envelope interactions with close stellar or even substellar companions. Cool companions to hot subdwarf stars such as late-type stars and brown dwarfs are detectable from characteristic light-curve variations - reflection effects and often eclipses. In the recently published catalog of eclipsing binaries in the Galactic Bulge and in the Asteroid Terrestrial-impact Last Alert System (ATLAS) survey, we discovered 125 new eclipsing systems showing a reflection effect seen by visual inspection of the light curves and using a machine-learning algorithm, in addition to the 36 systems previously discovered by the Optical Gravitational Lesing Experiment (OGLE) team. The Eclipsing Reflection Effect Binaries from Optical Surveys (EREBOS) project aims at analyzing all newly discovered eclipsing binaries of the HW Vir type (hot subdwarf + close, cool companion) based on a spectroscopic and photometric follow up to derive the mass distribution of the companions, constrain the fraction of substellar companions, and determine the minimum mass needed to strip off the red-giant envelope. To constrain the nature of the primary we derived the absolute magnitude and the reduced proper motion of all our targets with the help of the parallaxes and proper motions measured by the Gaia mission and compared those to the Gaia white-dwarf candidate catalog. It was possible to derive the nature of a subset of our targets, for which observed spectra are available, by measuring the atmospheric parameter of the primary, confirming that less than 10% of our systems are not sdO/Bs with cool companions but are white dwarfs or central stars of planetary nebula. This large sample of eclipsing hot subdwarfs with cool companions allowed us to derive a significant period distribution for hot subdwarfs with cool companions for the first time showing that the period distribution is much broader than previously thought and is ideally suited to finding the lowest-mass companions to hot subdwarf stars. The comparison with related binary populations shows that the period distribution of HW Vir systems is very similar to WD+dM systems and central stars of planetary nebula with cool companions. In the future, several new photometric surveys will be carried out, which will further increase the sample of this project, providing the potential to test many aspects of common-envelope theory and binary evolution.
CRIS-Team WoS Importer:2019-10-11

The eROSITA extragalactic CalPV serendipitous catalog - Liu, Teng; Merloni, Andrea; Wolf, Julien; Salvato, Mara; Reiprich, Thomas H.; Comparat, Johan; Arcodia, Riccardo; Lamer, Georg; Georgakakis, Antonis; Dwelly, Tom; Sanders, Jeremy; Buchner, Johannes; et al. (Astronomy & Astrophysics, 2022)
Context. The eROSITA X-ray telescope on board the Spectrum-Roentgen-Gamma (SRG) observatory performed calibration and performance verification (CalPV) observations between September 2019 and December 2019, ahead of the planned 4-yr all-sky surveys. Most of them were deep, pointing-mode observations.
CRIS-Team WoS Importer:2022-09-16

The eROSITA Final Equatorial-Depth Survey (eFEDS) Presenting the demographics of X-ray emission from normal galaxies - Vulic, N.; Hornschemeier, A. E.; Haberl, F.; Basu-Zych, A. R.; Kyritsis, E.; Zezas, A.; Salvato, M.; Ptak, A.; Bogdan, A.; Kovlakas, K.; Wilms, Jörn; Sasaki, Manami; et al. (Astronomy & Astrophysics, 2022)
Context. The eROSITA Final Equatorial Depth Survey (eFEDS), completed in survey mode during the calibration and performance verification phase of the eROSITA instrument on Spectrum Roentgen Gamma, delivers data at and beyond the final depth of the 4-yr eROSITA all-sky survey (eRASS:8), f(0.5-2 keV) = 1.1 x 10(-14) erg s(-1) cm(-2), over 140 deg(2). It provides the first view of normal galaxy X-ray emission from X-ray binaries (XRBs) and the hot interstellar medium at the full depth of eRASS:8. Aims. We used the Heraklion Extragalactic Catalogue (HECATE) of galaxies to correlate with eFEDS X-ray sources and identify X-ray detected normal galaxies. This flux-limited X-ray survey is relatively free from selection effects and enables the study of integrated normal galaxy X-ray emission and its relation to galaxy parameters such as the stellar mass, star formation rate (SFR), and metallicity. Methods. We cross-correlated 32 646 eFEDS X-ray sources to 1181 HECATE normal galaxies and obtained 94 matches. We classified galaxies as star-forming, early-type, composite, and active galactic nuclei (AGN) using Sloan Digital Sky Survey (SDSS) and Six-degree Field (6dF) optical spectroscopy. Results. The eFEDS field harbours 37 normal galaxies: 36 late-type (star-forming) galaxies and one early-type galaxy. There are 1.9 times as many normal galaxies as predicted by scaling relations via simulations, with an overabundance of late-type galaxies and a dearth of early-type galaxies. When compared with empirical relations, eFEDS dwarf galaxies with a high specific SFR have elevated L-X/SFR at a fixed specific SFR and metallicity, indicating an increase in XRB emission due to low metallicity. We expect that eRASS:8 will detect 12 500 normal galaxies, the majority of which will be star-forming, with the caveat that there are unclassified sources in eFEDS and galaxy catalogue incompleteness issues that could increase the actual number of detected galaxies over these current estimates. Conclusions. eFEDS observations detected a rare population of galaxies - the metal-poor dwarf starbursts - that do not follow known scaling relations. eRASS is expected to discover significant numbers of these high-redshift analogues, which are important for studying the heating of the intergalactic medium at high redshift. Further investigation of the hot gas emission from normal galaxies and stochastic effects in the dwarf galaxy population are required to constrain their X-ray output.
CRIS-Team WoS Importer:2022-06-17

The eROSITA Final Equatorial-Depth Survey (eFEDS) The AGN catalog and its X-ray spectral properties - Liu, Teng; Buchner, Johannes; Nandra, Kirpal; Merloni, Andrea; Dwelly, Tom; Sanders, Jeremy S.; Salvato, Mara; Arcodia, Riccardo; Brusa, Marcella; Wolf, Julien; Georgakakis, Antonis; Boller, Thomas; et al. (Astronomy & Astrophysics, 2022)
Context. The eROSITA Final Equatorial Depth Survey (eFEDS), observed with eROSITA ahead of its planned 4-yr all-sky survey, is the largest contiguous-field X-ray survey at present. It yielded a large sample of X-ray sources with very rich multiband photometric and spectroscopic coverage.
CRIS-Team WoS Importer:2022-06-17

The eROSITA Final Equatorial Depth Survey (eFEDS): X-ray catalogue - Brunner, H.; Liu, T.; Lamer, G.; Georgakakis, A.; Merloni, A.; Brusa, M.; Bulbul, E.; Dennerl, K.; Friedrich, S.; Liu, A.; Maitra, C.; Nandra, K.; et al. (Astronomy & Astrophysics, 2022)
Context. The eROSITA X-ray telescope on board the Spectrum-Poentgen-Gamma (SPG) observatory combines a large field of view and a large collecting area in the energy range between 0.2 and 8.0 keV. This gives the telescope the capability to perform uniform scanning observations of large sky areas. Aims. SRG/eROSITA performed scanning observations of the 140 square degree eROSITA Final Equatorial Depth Survey field (the eFEDS field) as part of its performance verification phase ahead of the planned four year of all-sky scanning operations. The observing time of eFEDS was chosen to slightly exceed the depth expected in an equatorial field after the completion of the all-sky survey. While verifying the capability of eROSITA to perform large-area uniform surveys and saving as a test and training dataset to establish calibration and data analysis procedures, the eFEDS survey also constitutes the largest contiguous soft X-ray survey at this depth to date, supporting a range of early eROSITA survey science investigations. Here we (i) present a catalogue of detected X-ray sources in the eFEDS field providing information about source positions and extent, as well as fluxes in multiple energy bands, and (ii) document the suite of tools and procedures developed for eROSITA data processing and analysis, which were validated and optimised by the eFEDS work. Methods. The data were fed through a standard data processing pipeline, which appltes X-ray event calibration and provides a set of standard calibrated data products. A mutiti-stage source detection procedure, building in part on experience from XMM-Newton, was optimised and calibrated by performing realistic simulations of the eROSITA eFEDS observations. Source fluxes were computed in multiple standard energy bands by forced point source fitting and aperture photometry. We cross-matched the eROSITA eFEDS source catalogue with previous XMM-ATLAS observations, which confirmed the excellentt agreement of the eROSITA and XMM-ATLAS source fluxes. Astrometric corrections were performed by cross-matching the eROSITA source positions with an optical reference catalogue of quasars. Results. We present a primary catalogue of 27 910 X-ray sources (542 of which are significantly spatially extended) detected in the 0.2-2.3 keV energy range with detection likelihoods ≥6, corresponding to a (point source) flux limit of 6.5 × 10-15 erg cm-2 s-1 in the 0.5-2.0 keV energy band (80% completeness). A supplementary catalogue contains 4774 low-significance source candidates with detection likelihoods between 5 and 6. In addition, a hard-band sample of 246 sources detected in the energy range 22.3-5.0 keV above a detection likelihood of 10 is provided. In an appendix, we finally describe the dedicated data analysis software package, the eROSITA calibration database, and the standard calibrated data products.
CRIS-Team Scopus Importer:2022-06-03
Keywords: Catalogs; Surveys; X-rays: general

The eROSITA upper limits: Description and access to the data - Tubín-Arenas, Dusán; Krumpe, Mirko; Lamer, Georg; Haase, Jonas; Sanders, Jeremy; Brunner, Hermann; Homan, David; Schwope, Axel; Georgakakis, Antonis; Poppenhaeger, Katja; Traulsen, Iris; König, Ole; et al. (Astronomy & Astrophysics, 2024)
Context. The soft X-ray instrument eROSITA on board the Spectrum-Roentgen-Gamma (SRG) observatory has successfully completed four of the eight planned all-sky surveys, detecting almost one million X-ray sources during the first survey (eRASS1). The catalog of this survey will be released as part of the first eROSITA data release (DR1). Aims. Based on X-ray aperture photometry, we provide flux upper limits for eRASS1 in several energy bands. We cover galactic longitudes between 180 ≲ l ≲ 360 (eROSITA-DE). These data are crucial for studying the X-ray properties of variable and transient objects, as well as non-detected sources in the eROSITA all-sky survey data. Methods. We performed aperture photometry on every pixel of the SRG/eROSITA standard pipeline data products for all available sky tiles in the single detection band (0.2- 2.3 keV). Simultaneously, we performed the same analysis in the three-band detection at soft (0.2- 0.6 keV), medium (0.6- 2.3 keV), and hard (2.3- 5.0 keV) energy bands. Based on the combination of products for the individual bands, we are also able to provide aperture photometry products and flux upper limits for the 0.2- 5.0 keV energy band. The upper limits were calculated based on a Bayesian approach that utilizes detected counts and background within the circular aperture. Results. The final data products consist of tables with the aperture photometry products (detected counts, background counts, and exposure time), a close-neighbor flag, and the upper flux limit based on an absorbed power-law spectral model (Γ = 2.0, NH = 3 × 1020 cm-2). The upper limits are calculated using the one-sided 3σ confidence interval (CL) of a normal distribution, representing CL = 99.87%. The aperture photometry products allow for an easy computation of upper limits at any other confidence interval and spectral model. These data are stored in a database with hierarchical indexes in order to offer a fast query option. Conclusions. We provide a detailed description of the process of retrieving SRG/eROSITA upper limits for a large set of input positions, as well as of the eROSITA data, the X-ray aperture photometry, the upper limit calculation, and the final data products. The eROSITA upper flux limits represent either the maximum flux of potential non-detections or the 3σ upper flux uncertainty of detected sources. We emphasize the importance of choosing the right spectral model that ought to match the spectral shape of the source of interest: the wrong spectral model can produce discrepancies of up to 30% in the final flux upper limit value. We also describe the architecture of the database and the web tool, which are designed to handle large queries on input positions.
CRIS-Team Scopus Importer:2024-02-16
Keywords: Astronomical databases: miscellaneous; X-rays: general

The eROSITA X-ray telescope on SRG - Predehl, P.; Andritschke, R.; Arefiev, V.; Babyshkin, V.; Batanov, O.; Becker, W.; Böhringer, H.; Bogomolov, A.; Boller, T.; Borm, K.; Bornemann, W.; Bräuninger, H.; et al. (Astronomy & Astrophysics, 2021)
eROSITA (extended ROentgen Survey with an Imaging Telescope Array) is the primary instrument on the Spectrum-Roentgen-Gamma (SRG) mission, which was successfully launched on July 13, 2019, from the Baikonour cosmodrome. After the commissioning of the instrument and a subsequent calibration and performance verification phase, eROSITA started a survey of the entire sky on December 13, 2019. By the end of 2023, eight complete scans of the celestial sphere will have been performed, each lasting six months. At the end of this program, the eROSITA all-sky survey in the soft X-ray band (0.2-2.3 keV) will be about 25 times more sensitive than the ROSAT All-Sky Survey, while in the hard band (2.3-8 keV) it will provide the first ever true imaging survey of the sky. The eROSITA design driving science is the detection of large samples of galaxy clusters up to redshifts z > 1 in order to study the large-scale structure of the universe and test cosmological models including Dark Energy. In addition, eROSITA is expected to yield a sample of a few million AGNs, including obscured objects, revolutionizing our view of the evolution of supermassive black holes. The survey will also provide new insights into a wide range of astrophysical phenomena, including X-ray binaries, active stars, and diffuse emission within the Galaxy. Results from early observations, some of which are presented here, confirm that the performance of the instrument is able to fulfil its scientific promise. With this paper, we aim to give a concise description of the instrument, its performance as measured on ground, its operation in space, and also the first results from in-orbit measurements.
CRIS-Team Scopus Importer:2021-03-19
Keywords: Dark energy; Space vehicles: instruments; Surveys; X-rays: general

The ESO supernovae type Ia progenitor survey (SPY) The radial velocities of 643 DA white dwarfs - Napiwotzki, R.; Karl, C. A.; Lisker, T.; Catalan, S.; Drechsel, Horst; Heber, Ulrich; Homeier, D.; Koester, D.; Leibundgut, B.; Marsh, T. R.; Moehler, S.; Nelemans, G.; et al. (Astronomy & Astrophysics, 2020)
Close double degenerate binaries are one of the favoured progenitor channels for type Ia supernovae, but it is unclear how many suitable systems there are in the Galaxy. We report results of a large radial velocity survey for double degenerate (DD) binaries using the UVES spectrograph at the ESO VLT (ESO SN Ia Progenitor surveY - SPY). Exposures taken at different epochs are checked for radial velocity shifts indicating close binary systems. We observed 689 targets classified as DA white dwarfs (displaying hydrogen-rich atmospheres), of which 46 were found to possess a cool companion. We measured radial velocities (RV) of the remaining 643 DA white dwarfs. We managed to secure observations at two or more epochs for 625 targets, supplemented by eleven objects meeting our selection criteria from literature. The data reduction and analysis methods applied to the survey data are described in detail. The sample contains 39 double degenerate binaries, only four of which were previously known. Twenty are double-lined systems, in which features from both components are visible, the other 19 are single-lined binaries. We provide absolute RVs transformed to the heliocentric system suitable for kinematic studies. Our sample is large enough to sub-divide by mass: 16 out of 44 low mass targets (<= 0.45 M-circle dot) are detected as DDs, while just 23 of the remaining 567 targets with multiple spectra and mass > 0.45 M-circle dot are double. The detected fraction amongst the low mass objects (36.4 +/- 7.3%) is significantly higher than for the higher-mass, carbon-oxygen core dominated part of the sample (3.9 +/- 0.8%), but it is much lower than expected from the detection efficiency for companion masses of 0.05 M-circle dot or higher and a 100% binary fraction. This suggests either companion stars of with a mass below 0.05 M-circle dot or some of the low mass white dwarfs are single.
Keywords: techniques: radial velocities; binaries: close; binaries: spectroscopic; supernovae: general; white dwarfs

The ESO supernovae type Ia progenitor survey (SPY): The radial velocities of 643 DA white dwarfs - Napiwotzki, R.; Karl, C. A.; Lisker, T.; Catalan, S.; Drechsel, Horst; Heber, Ulrich; Homeier, D.; Koester, D.; Leibundgut, B.; Marsh, T. R.; Moehler, S.; Nelemans, G.; et al. (Astronomy & Astrophysics, 2020)
Close double degenerate binaries are one of the favoured progenitor channels for type Ia supernovae, but it is unclear how many suitable systems there are in the Galaxy. We report results of a large radial velocity survey for double degenerate (DD) binaries using the UVES spectrograph at the ESO VLT (ESO SN Ia Progenitor surveY - SPY). Exposures taken at different epochs are checked for radial velocity shifts indicating close binary systems. We observed 689 targets classified as DA white dwarfs (displaying hydrogen-rich atmospheres), of which 46 were found to possess a cool companion. We measured radial velocities (RV) of the remaining 643 DA white dwarfs. We managed to secure observations at two or more epochs for 625 targets, supplemented by eleven objects meeting our selection criteria from literature. The data reduction and analysis methods applied to the survey data are described in detail. The sample contains 39 double degenerate binaries, only four of which were previously known. Twenty are double-lined systems, in which features from both components are visible, the other 19 are single-lined binaries. We provide absolute RVs transformed to the heliocentric system suitable for kinematic studies. Our sample is large enough to sub-divide by mass: 16 out of 44 low mass targets (<= 0.45 M-circle dot) are detected as DDs, while just 23 of the remaining 567 targets with multiple spectra and mass > 0.45 M-circle dot are double. The detected fraction amongst the low mass objects (36.4 +/- 7.3%) is significantly higher than for the higher-mass, carbon-oxygen core dominated part of the sample (3.9 +/- 0.8%), but it is much lower than expected from the detection efficiency for companion masses of 0.05 M-circle dot or higher and a 100% binary fraction. This suggests either companion stars of with a mass below 0.05 M-circle dot or some of the low mass white dwarfs are single.
CRIS-Team WoS Importer:2020-07-24
Keywords: techniques: radial velocities; binaries: close; binaries: spectroscopic; supernovae: general; white dwarfs

The EUSO-Balloon pathfinder - Adams, J. H.; Ahmad, S.; Albert, J. -N.; Allard, D.; Anchordoqui, L.; Andreev, V.; Anzalone, Anna; Arai, Y.; Asano, K.; Ave Pernas, M.; Barrillon, P.; Batsch, T.; et al. (Experimental Astronomy, 2015)
EUSO-Balloon is a pathfinder for JEM-EUSO, the Extreme Universe Space Observatory which is to be hosted on-board the International Space Station. As JEM-EUSO is designed to observe Ultra-High Energy Cosmic Rays (UHECR)-induced Extensive Air Showers (EAS) by detecting their ultraviolet light tracks "from above", EUSO-Balloon is a nadir-pointing UV telescope too. With its Fresnel Optics and Photo-Detector Module, the instrument monitors a 50 km(2) ground surface area in a wavelength band of 290-430 nm, collecting series of images at a rate of 400,000 frames/sec. The objectives of the balloon demonstrator are threefold: a) perform a full end-to-end test of a JEM-EUSO prototype consisting of all the main subsystems of the space experiment, b) measure the effective terrestrial UV background, with a spatial and temporal resolution relevant for JEM-EUSO. c) detect tracks of ultraviolet light from near space for the first time. The latter is a milestone in the development of UHECR science, paving the way for any future space-based UHECR observatory. On August 25, 2014, EUSO-Balloon was launched from Timmins Stratospheric Balloon Base (Ontario, Canada) by the balloon division of the French Space Agency CNES. From a float altitude of 38 km, the instrument operated during the entire astronomical night, observing UV-light from a variety of ground-covers and from hundreds of simulated EASs, produced by flashers and a laser during a two-hour helicopter under-flight.
Keywords: UHECR; Air-fluorescence; JEM-EUSO; Balloon experiment

The evolution of structure and feedback with Arcus - Brenneman, Laura W.; Smith, Randall K.; Bregman, J.; Kaastra, J.; Brickhouse, N.; Allured, R.; Foster, A.; Wolk, S.; Wilms, Jörn; Valencic, L.; Willingale, R.; Grant, C.; et al. (Space Telescopes and Instrumentation 2016: Ultraviolet to Gamma Ray, 2016)
Arcus is a NASA/MIDEX mission under development in response to the anticipated 2016 call for proposals. It is a freeflying, soft X-ray grating spectrometer with the highest-ever spectral resolution in the 8-51 Å (0.24 - 1.55 keV) energy range. The Arcus bandpass includes the most sensitive tracers of diffuse million-degree gas: spectral lines from O VII and O VIII, H- and He-like lines of C, N, Ne and Mg, and unique density- and temperature-sensitive lines from Si and Fe ions. These capabilities enable an advance in our understanding of the formation and evolution of baryons in the Universe that is unachievable with any other present or planned observatory. The mission will address multiple key questions posed in the Decadal Survey and NASA's 2013 Roadmap: How do baryons cycle in and out of galaxies? How do black holes and stars influence their surroundings and the cosmic web via feedback? How do stars, circumstellar disks and exoplanet atmospheres form and evolve? Arcus data will answer these questions by leveraging recent developments in off-plane gratings and silicon pore optics to measure X-ray spectra at high resolution from a wide range of sources within and beyond the Milky Way. CCDs with strong Suzaku heritage combined with electronics based on the Swift mission will detect the dispersed X-rays. Arcus will support a broad astrophysical research program, and its superior resolution and sensitivity in soft X-rays will complement the forthcoming Athena calorimeter, which will have comparably high resolution above 2 keV.
Keywords: Accretion; Active galaxies; Gratings; Large-scale structure; Outflows; Spectroscopy; Stars; X-rays

The EXTraS project: Exploring the X-ray transient and variable sky - De Luca, A.; Salvaterra, R.; Belfiore, A.; Carpano, S.; D'Agostino, D.; Haberl, F.; Israel, G. L.; Law-Green, D.; Lisini, G.; Marelli, M.; Novara, G.; Read, A. M.; et al. (Astronomy & Astrophysics, 2021)
Temporal variability in flux and spectral shape is ubiquitous in the X-ray sky and carries crucial information about the nature and emission physics of the sources. The EPIC instrument on board the XMM-Newton observatory is the most powerful tool for studying variability even in faint sources. Each day, it collects a large amount of information about hundreds of new serendipitous sources, but the resulting huge (and growing) dataset is largely unexplored in the time domain. The project called Exploring the X-ray transient and variable sky (EXTraS) systematically extracted all temporal domain information in the XMM-Newton archive. This included a search and characterisation of variability, both periodic and aperiodic, in hundreds of thousands of sources spanning more than eight orders of magnitude in timescale and six orders of magnitude in flux, and a search for fast transients that were missed by standard image analysis. All results, products, and software tools have been released to the community in a public archive. A science gateway has also been implemented to allow users to run the EXTraS analysis remotely on recent XMM datasets. We give details on the new algorithms that were designed and implemented to perform all steps of EPIC data analysis, including data preparation, source and background modelling, generation of time series and power spectra, and search for and characterisation of different types of variabilities. We describe our results and products and give information about their basic statistical properties and advice on their usage. We also describe available online resources. The EXTraS database of results and its ancillary products is a rich resource for any kind of investigation in almost all fields of astrophysics. Algorithms and lessons learnt from our project are also a very useful reference for any current and future experiment in the time domain.
CRIS-Team Scopus Importer:2021-07-16
Keywords: Astronomical databases: miscellaneous; Catalogs; Methods: data analysis; X-rays: general

The fastest unbound star in our Galaxy ejected by a thermonuclear supernova - Geier, Stephan; Furst, Felix; Ziegerer, Eva; Kupfer, Thomas; Heber, Ulrich; Irrgang, Andreas; Wang, Bo; Liu, Z.; Han, Z.; Sesar, B.; Levitan, D.; Kotak, R.; et al. (Science, 2015)
Hypervelocity stars (HVSs) travel with velocities so high that they exceed the escape velocity of the Galaxy. Several acceleration mechanisms have been discussed. Only one HVS (US 708, HVS 2) is a compact helium star. Here we present a spectroscopic and kinematic analysis of US 708. Traveling with a velocity of similar to 1200 kilometers per second, it is the fastest unbound star in our Galaxy. In reconstructing its trajectory, the Galactic center becomes very unlikely as an origin, which is hardly consistent with the most favored ejection mechanism for the other HVSs. Furthermore, we detected that US 708 is a fast rotator. According to our binary evolution model, it was spun-up by tidal interaction in a close binary and is likely to be the ejected donor remnant of a thermonuclear supernova.

The fast-rotating, low-gravity subdwarf B star EC22081-1916: Remnant of a common envelope merger event - Geier, Stephan; Classen, Lew; Heber, Ulrich (Astrophysical Journal Letters, 2011)
Hot subdwarf B stars (sdBs) are evolved core helium-burning stars with very thin hydrogen envelopes. In order to form an sdB, the progenitor has to lose almost all of its hydrogen envelope right at the tip of the red-giant branch. In binary systems, mass transfer to the companion provides the extraordinary mass loss required for their formation. However, apparently single sdBs exist as well and their formation has been unclear for decades. The merger of helium white dwarfs (He-WDs) leading to an ignition of core helium burning or the merger of a helium core and a low-mass star during the common envelope phase have been proposed as processes leading to sdB formation. Here we report the discovery of EC22081-1916 as a fast-rotating, single sdB star of low gravity. Its atmospheric parameters indicate that the hydrogen envelope must be unusually thick, which is at variance with the He-WD merger scenario, but consistent with a common envelope merger of a low-mass, possibly substellar object with a red-giant core. © 2011. The American Astronomical Society. All rights reserved.
CRIS-Team Scopus Importer:2020-12-21
Keywords: branch; stars: horizontal; stars: individual (EC 22081-1916)

THE FIRST COMBINED SEARCH for NEUTRINO POINT-SOURCES in the SOUTHERN HEMISPHERE with the ANTARES and ICECUBE NEUTRINO TELESCOPES - Adrian-Martinez, S.; Albert, A.; Andre, Michel; Anton, Gisela; Ardid, Miguel; Aubert, J. -J.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; Bormuth, R.; et al. (Astrophysical Journal, 2016)
We present the results of searches for point-like sources of neutrinos based on the first combined analysis of data from both the ANTARES and IceCube neutrino telescopes. The combination of both detectors, which differ in size and location, forms a window in the southern sky where the sensitivity to point sources improves by up to a factor of 2 compared with individual analyses. Using data recorded by ANTARES from 2007 to 2012, and by IceCube from 2008 to 2011, we search for sources of neutrino emission both across the southern sky and from a preselected list of candidate objects. No significant excess over background has been found in these searches, and flux upper limits for the candidate sources are presented for E and E power-law spectra with different energy cut-offs.
Keywords: astroparticle physics; neutrinos

The first GeV flare of the radio-loud narrow-line Seyfert 1 galaxy PKS 2004-447 - Gokus, Andrea; Paliya, V. S.; Wagner, S. M.; Buson, S.; D'Ammando, F.; Edwards, P. G.; Kadler, M.; Meyer, M.; Ojha, R.; Stevens, J.; Wilms, Jörn (Astronomy & Astrophysics, 2021)
Context. On 2019 October 25, the Fermi-Large Area Telescope observed the first ever γ-ray flare from the radio-loud narrow-line Seyfert 1 galaxy PKS 2004-447 (z = 0.24). Prior to this discovery, only four sources of this type had shown a flare at gigaelectronvolt energies. Aims. We report on follow-up observations in the radio, optical-UV, and X-ray bands that were performed by ATCA, the Neil Gehrels Swift Observatory, XMM-Newton, and NuSTAR, respectively, and analyse these multi-wavelength data with a one-zone leptonic model in order to understand the physical mechanisms that were responsible for the flare. Methods. We study the source's variability across all energy bands and additionally produce γ-ray light curves with different time binnings to study the variability in γ-rays on short timescales during the flare. We examine the combined X-ray spectrum from 0.5 to 50 keV by describing the spectral shape with an absorbed power law. We analyse multi-wavelength datasets before, during, and after the flare and compare these with a low activity state of the source by modelling the respective spectral energy distributions (SEDs) with a one-zone synchrotron inverse Compton radiative model. Finally, we compare the variability and the SEDs to γ-ray flares previously observed from other γ-loud narrow-line Seyfert 1 galaxies. Results. At γ-ray energies (0.1-300 GeV) the flare reached a maximum flux of (1.3 ± 0.2) × 10-6 ph cm-2 s-1 in daily binning and a total maximum flux of (2.7 ± 0.6) × 10-6 ph cm-2 s-1 when a 3 h binning was used. With a photon index of Γ0.1-300 GeV = 2.42 ± 0.09 during the flare, this corresponds to an isotropic γ-ray luminosity of (2.9 ± 0.8) × 1047 erg s-1. The γ-ray, X-ray, and optical-UV light curves that cover the end of September to the middle of November show significant variability, and we find indications for flux-doubling times of ∼2.2 h at γ-ray energies. The soft X-ray excess, which is observed for most narrow-line Seyfert 1 galaxies, is not visible in this source. During the flare, the SED exhibits large Compton dominance. While the increase in the optical-UV range can be explained by enhanced synchrotron emission, the elevated γ-ray flux can be accounted for by an increase in the bulk Lorentz factor of the jet, similar to that observed for other flaring γ-ray blazars.
CRIS-Team Scopus Importer:2021-06-04
Keywords: Galaxies: active; Galaxies: jets; Gamma rays: galaxies; Quasars: individual: PKS 2004-447

The first look at narrow-line Seyfert 1 galaxies with eROSITA - Grünwald, G.; Boller, T.; Rakshit, S.; Buchner, J.; Dauser, Thomas; Freyberg, M.; Liu, T.; Salvato, M.; Schichtel, A. (Astronomy & Astrophysics, 2023)
We present the first look at the spectral and timing analysis of narrow-line Seyfert 1 galaxies (NLS1s) with the extended ROentgen Survey with an Imaging Telescope Array (eROSITA) on board the Spectrum-Roentgen-Gamma (SRG) mission. The sample of approximately 1200 NLS1s was obtained via a cross-match between the first eROSITA All-Sky Survey (eRASS1) catalogue and the catalogue of spectroscopically selected NLS1s from the twelfth data release of the Sloan Digital Sky Survey (SDSS) DR12. The X-ray spectral analysis is based on a simple power-law fit. The photon index distribution has a mean value of about 2.81-±-0.03, as expected from previous X-ray studies of NLS1s. Interestingly, it is positively skewed, and about 10% of the sources are located in the super-soft tail of photon indices larger than 4. These sources are of further interest as their source counts run into the X-ray background at values at around 1 keV. We argue that ionised outflows have been detected by eROSITA and may account for some of the extreme spectral steepness, which is supported by correlations found between the photon index and optical outflow parameters. We analysed the intrinsic X-ray variability of the eRASS1 to eRASS3 light curves of the sample but do not find significant variability either during the individual survey scans or between them.
CRIS-Team Scopus Importer:2023-01-13
Keywords: Accretion; Accretion discs; Galaxies: Seyfert; Surveys; X-rays: general

The first massive compact companion in a wide orbit around a hot subdwarf star - Geier, S.; Dorsch, M.; Dawson, H.; Pelisoli, I.; Munday, J.; Marsh, T. R.; Schaffenroth, V.; Heber, Ulrich (Astronomy & Astrophysics, 2023)
We report the discovery of the first hot subdwarf B (sdB) star with a massive compact companion in a wide (P = 892.5 ± 60.2 d) binary system. It was discovered based on an astrometric binary solution provided by the Gaia mission Data Release 3. We performed detailed analyses of the spectral energy distribution (SED) as well as spectroscopic follow-up observations and confirm the nature of the visible component as a sdB star. The companion is invisible despite of its high mass of Mcomp = 1.50- 0.45+0.37 M·. A main sequence star of this mass would significantly contribute to the SED and can be excluded. The companion must be a compact object, either a massive white dwarf or a neutron star. Stable Roche lobe overflow to the companion likely led to the stripping of a red giant and the formation of the sdB, the hot and exposed helium core of the giant. Based on very preliminary data, we estimate that ∼9% of the sdBs might be formed through this new channel. This binary might also be the prototype for a new progenitor class of supernovae type Ia, which has been predicted by theory.
CRIS-Team Scopus Importer:2023-09-15
Keywords: Binaries: general; Stars: horizontal-branch; Stars: neutron; Subdwarfs; Supernovae: general; White dwarfs

The First NuSTAR Observation of 4U 1538-522: Updated Orbital Ephemeris and a Strengthened Case for an Evolving Cyclotron Line Energy - Hemphill, Paul B.; Rothschild, Richard E.; Cheatham, Diana M.; Furst, Felix; Kretschmar, Peter; Kühnel, Matthias; Pottschmidt, Katja; Staubert, Ruediger; Wilms, Jörn; Wolff, Michael T. (Astrophysical Journal, 2019)
We have performed a comprehensive spectral and timing analysis of the first NuSTAR observation of the high-mass X-ray binary 4U 1538-522. The observation covers the X-ray eclipse of the source, plus the eclipse ingress and egress. We use the new measurement of the mid-eclipse time to update the orbital parameters of the system and find marginally significant evolution in the orbital period, with (P) over dot(orb)/P-orb = (-0.95 +/- 0.37) x 10(-6) yr(-1). The cyclotron line energy is found to be approximately 1.2 keV higher than RXTE measurements from 1997 to 2003, in line with the increased energy observed by Suzaku in 2012 and strengthening the case for secular evolution of 4U 1538-522's CRSF. We additionally characterize the behavior of the iron fluorescence and emission lines and line-of-sight absorption as the source moves into and out of eclipse.
Keywords: accretion; accretion disks; binaries: eclipsing; stars: individual (QV Nor); stars: magnetic field; X-rays: binaries X-rays: individual (4U 1538-522)

The Galactic LMXB Population and the Galactic Centre Region - Sazonov, S.; Paizis, A.; Bazzano, A.; Chelovekov, I.; Khabibullin, I.; Postnov, K.; Mereminskiy, I.; Fiocchi, M.; Bélanger, G.; Bird, A. J.; Bozzo, E.; Chenevez, J.; et al. (New Astronomy Reviews, 2020)
Seventeen years of hard X-ray observations with the instruments of the INTEGRAL observatory, with a focus on the Milky Way and in particular on the Galactic Centre region, have provided a unique database for exploration of the Galactic population of low-mass X-ray binaries (LMXBs). Our understanding of the diverse energetic phenomena associated with accretion of matter onto neutron stars and black holes has greatly improved. We review the large variety of INTEGRAL based results related to LMXBs. In particular, we discuss the spatial distribution of LMXBs over the Galaxy and their X-ray luminosity function as well as various physical phenomena associated with Atoll and Z sources, bursters, symbiotic X-ray binaries, ultracompact X-ray binaries and persistent black hole LMXBs. We also present an up-to-date catalogue of confirmed LMXBs detected by INTEGRAL, which comprises 166 objects. Last but not least, the long-term monitoring of the Galactic Centre with INTEGRAL has shed light on the activity of Sgr A* in the recent past, confirming previous indications that our supermassive black hole experienced a major accretion episode just 100 years ago. This exciting topic is covered in this review too.
CRIS-Team Scopus Importer:2020-08-28
Keywords: Accretion; Black holes; INTEGRAL observatory; Neutron stars; Sgr A*; X-ray binaries

The gamma-ray emitting radio-loud narrow-line Seyfert 1 galaxy PKS 2004-447: II. the radio view - Schulz, R.; Kreikenbohm, A.; Kadler, M.; Ojha, R.; Ros, E.; Stevens, J.; Edwards, P. G.; Carpenter, B.; Elsaesser, D.; Gehrels, N.; Großberger, Christoph; Hase, H.; et al. (Astronomy & Astrophysics, 2016)
Context. Γ-ray-detected radio-loud narrow-line Seyfert 1 (γ-NLS1) galaxies constitute a small but interesting sample of the γ-ray-loud AGN. The radio-loudest γ-NLS1 known, PKS 2004-447, is located in the southern hemisphere and is monitored in the radio regime by the multiwavelength monitoring programme TANAMI. Aims. We aim for the first detailed study of the radio morphology and long-term radio spectral evolution of PKS 2004-447, which are essential for understanding the diversity of the radio properties of γ-NLS1s. Methods. The TANAMI VLBI monitoring program uses the Australian Long Baseline Array (LBA) and telescopes in Antarctica, Chile, New Zealand, and South Africa to monitor the jets of radio-loud active galaxies in the southern hemisphere. Lower resolution radio flux density measurements at multiple radio frequencies over four years of observations were obtained with the Australia Telescope Compact Array (ATCA). Results. The TANAMI VLBI image at 8.4 GHz shows an extended one-sided jet with a dominant compact VLBI core. Its brightness temperature is consistent with equipartition, but it is an order of magnitude below other γ-NLS1s with the sample value varying over two orders of magnitude. We find a compact morphology with a projected large-scale size < 11 kpc and a persistent steep radio spectrum with moderate flux-density variability. Conclusions. PKS 2004-447 appears to be a unique member of the γ-NLS1 sample. It exhibits blazar-like features, such as a flat featureless X-ray spectrum and a core-dominated, one-sided parsec-scale jet with indications for relativistic beaming. However, the data also reveal properties atypical for blazars, such as a radio spectrum and large-scale size consistent with compact-steep-spectrum (CSS) objects, which are usually associated with young radio sources. These characteristics are unique among all γ-NLS1s and extremely rare among γ-ray-loud AGN.
Keywords: Galaxies: active; Galaxies: individual: PKS 2004-447; Galaxies: jets; Radio continuum: galaxies; Techniques: interferometric

The gamma-ray emitting radio-loud narrow-line Seyfert 1 galaxy PKS 2004-447. I. The X-ray View - Kreikenbohm, A.; Schulz, R.; Kadler, Matthias; Wilms, Jörn; Markowitz, Alex; Chang, C. S.; Carpenter, B.; Elsaesser, D.; Gehrels, N.; Mannheim, K.; Mueller, C.; Ojha, R.; et al. (Astronomy & Astrophysics, 2016)
As part of the TANAMI multiwavelength progam, we discuss new X-ray observations of the γ-ray and radio-loud narrow line Seyfert 1 galaxy (γ-NLS1) PKS 2004-447. The active galaxy is a member of a small sample of radio-loud NLS1s detected in γ-rays by the Fermi Large Area Telescope. It st and s out for being the radio-loudest and the only southern-hemisphere source in this sample. We present results from our X-ray monitoring program comprised of Swift snapshot observations from 2012 through 2014 and two new X-ray observations with XMM-Newton in 2012. Supplemented by archival data from 2004 and 2011, our data set allows for a careful analysis of the X-ray spectrum and variability of this peculiar source. The (0.5-10) keV spectrum is described well by a power law (Γ ∼ 1.6), which can be interpreted as non-thermal emission from a relativistic jet. The source exhibits moderate flux variability on timescales of both months and years. Correlated brightness variations in the (0.5-2) keV and (2-10) keV b and s are explained by a single variable spectral component, such as the one from the jet. A possible soft excess seen in the data from 2004 cannot be confirmed by the new XMM-Newton observations taken during low-flux states. Any contribution to the total flux in 2004 is less than 20% of the power-law component. The (0.5-10) keV luminosities of PKS 2004-447 are in the range of (0.5-2.7) × 10 erg s. A comparison of the X-ray properties among the known γ-NLS1 galaxies shows that in four out of five cases the X-ray spectrum is dominated by a flat power law without intrinsic absorption. These objects are moderately variable in their brightness, while spectral variability is observed in at least two sources. The major difference across the X-ray spectra of γ-NLS1s is the luminosity, which spans a range of almost two orders of magnitude from 10 erg s to 10 erg s in the (0.5-10) keV b and .
Keywords: galaxies: active; galaxies: individual: PKS 2004-447; galaxies: jets; galaxies: Seyfert; quasars: general; X-rays: general

The gamma-ray spectrum of the core of Centaurus A as observed with HESS and Fermi-LAT - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Armand, C.; Arrieta, M.; Backes, Michael; Balzer, A.; Barnard, M.; Becherini, Y.; et al. (Astronomy & Astrophysics, 2018)
Centaurus A (Cen A) is the nearest radio galaxy discovered as a very-high-energy (VHE; 100 GeV-100 TeV) gamma-ray source by the High Energy Stereoscopic System (H.E.S.S.). It is a faint VHE gamma-ray emitter, though its VHE flux exceeds both the extrapolation from early Fermi-LAT observations as well as expectations from a (misaligned) single-zone synchrotron-self Compton (SSC) description. The latter satisfactorily reproduces the emission from Cen A at lower energies up to a few GeV. New observations with H.E.S.S., comparable in exposure time to those previously reported, were performed and eight years of Fermi-LAT data were accumulated to clarify the spectral characteristics of the gamma-ray emission from the core of Cen A. The results allow us for the first time to achieve the goal of constructing a representative, contemporaneous gamma-ray core spectrum of Cen A over almost five orders of magnitude in energy. Advanced analysis methods, including the template fitting method, allow detection in the VHE range of the core with a statistical significance of 12 sigma on the basis of 213 hours of total exposure time. The spectrum in the energy range of 250 GeV-6 TeV is compatible with a power-law function with a photon index Gamma = 2.52 +/- 0.13(stat) +/- 0.20(sys). An updated Fermi-LAT analysis provides evidence for spectral hardening by Delta Gamma similar or equal to 0.4 +/- 0.1 at gamma-ray energies above 2.8(-0.6)(+1.0) GeV at a level of 4.0 sigma. The fact that the spectrum hardens at GeV energies and extends into the VHE regime disfavour a single-zone SSC interpretation for the overall spectral energy distribution (SED) of the core and is suggestive of a new gamma-ray emitting component connecting the high-energy emission above the break energy to the one observed at VHE energies. The absence of significant variability at both GeV and TeV energies does not yet allow disentanglement of the physical nature of this component, though a jet-related origin is possible and a simple two-zone SED model fit is provided to this end.
CRIS-Team WoS Importer:2020-01-15
Keywords: Radiation mechanisms: non-thermal; Gamma rays: galaxies

The giant outburst of 4U 0115+634 in 2011 with Suzaku and RXTE: Minimizing cyclotron line biases - Kühnel, Matthias; Kreykenbohm, Ingo; Ferrigno, Carlo; Pottschmidt, Katja; Marcu-Cheatham, Diana M.; Fuerst, Felix; Rothschild, Richard E.; Kretschmar, Peter; Klochkov, Dmitry; Hemphill, Paul; Hertel, Dominik; Müller, Sebastian; et al. (Astronomy & Astrophysics, 2020)
We present an analysis of X-ray spectra of the high-mass X-ray binary 4U 0115+634 as observed with Suzaku and RXTE in 2011 July, during the fading phase of a giant X-ray outburst. We used a continuum model consisting of an absorbed cutoff power law and an ad hoc Gaussian emission feature centered around 8.5 keV, which we attribute to cyclotron emission. Our results are consistent with a fundamental cyclotron absorption line centered at similar to 10.2 keV for all observed flux ranges. At the same time we rule out significant influence of the 8.5 kev Gaussian on the parameters of the cyclotron resonant scattering feature, which are not consistent with the cyclotron line energies or the depths of previously reported flux-dependent descriptions. We also show that some continuum models can lead to artificial line-like residuals in the analyzed spectra, which are then misinterpreted as unphysically strong cyclotron lines. Specifically, our results do not support the existence of a previously claimed additional cyclotron feature at similar to 15 keV. Apart from these features, we find for the first time evidence for a He-like FeXXV emission line at similar to 6.7 keV and weak H-like FeXXVI emission close to similar to 7.0 keV.
CRIS-Team WoS Importer:2020-03-13

The goodness of simultaneous fits in ISIS - Kühnel, Matthias; Falkner, Sebastian; Großberger, Christoph; Ballhausen, Ralf; Dauser, Thomas; Schwarm, Fritz-Walter; Kreykenbohm, Ingo; Nowak, Michael A.; Pottschmidt, Katja; Ferrigno, Carlo; Rothschild, Richard E.; Martínez-Núñez, Silvia; et al. (Acta Polytechnica, 2016)
In a previous work, we introduced a tool for analyzing multiple datasets simultaneously, which has been implemented into ISIS. This tool was used to fit many spectra of X-ray binaries. However, the large number of degrees of freedom and individual datasets raise an issue about a good measure for a simultaneous fit quality. We present three ways to check the goodness of these fits: we investigate the goodness of each fit in all datasets, we define a combined goodness exploiting the logical structure of a simultaneous fit, and we stack the fit residuals of all datasets to detect weak features. These tools are applied to all RXTE-spectra from GRO 1008−57, revealing calibration features that are not detected significantly in any single spectrum. Stacking the residuals from the best-fit model for the Vela X-1 and XTE J1859+083 data evidences fluorescent emission lines that would have gone undetected otherwise.
Keywords: Data analysis; Multiple datasets; X-rays binaries

The HESS Galactic plane survey - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Anguener, E. O.; Arakawa, M.; Arrieta, M.; Aubert, P.; Backes, Michael; Balzer, A.; Barnard, Monica; Becherini, Y.; et al. (Astronomy & Astrophysics, 2018)
We present the results of the most comprehensive survey of the Galactic plane in very high-energy (VHE) gamma-rays, including a public release of Galactic sky maps, a catalog of VHE sources, and the discovery of 16 new sources of VHE gamma-rays. The High Energy Spectroscopic System (H.E.S.S.) Galactic plane survey (HGPS) was a decade-long observation program carried out by the H.E.S.S. I array of Cherenkov telescopes in Namibia from 2004 to 2013. The observations amount to nearly 2700 h of quality-selected data, covering the Galactic plane at longitudes from l = 250 degrees to 65 degrees and latitudes vertical bar b vertical bar <= 3 degrees. In addition to the unprecedented spatial coverage, the HGPS also features a relatively high angular resolution (0.08 degrees approximate to 5 arcmin mean point spread function 68% containment radius), sensitivity (less than or similar to 1.5% Crab flux for point-like sources), and energy range (0.2-100 TeV). We constructed a catalog of VHE gamma-ray sources from the HGPS data set with a systematic procedure for both source detection and characterization of morphology and spectrum. We present this likelihood-based method in detail, including the introduction of a model component to account for unresolved, large-scale emission along the Galactic plane. In total, the resulting HGPS catalog contains 78 VHE sources, of which 14 are not reanalyzed here, for example, due to their complex morphology, namely shell-like sources and the Galactic center region. Where possible, we provide a firm identification of the VHE source or plausible associations with sources in other astronomical catalogs. We also studied the characteristics of the VHE sources with source parameter distributions. 16 new sources were previously unknown or unpublished, and we individually discuss their identifications or possible associations. We firmly identified 31 sources as pulsar wind nebulae (PWNe), supernova remnants (SNRs), composite SNRs, or gamma-ray binaries. Among the 47 sources not yet identified, most of them (36) have possible associations with cataloged objects, notably PWNe and energetic pulsars that could power VHE PWNe.
Keywords: gamma rays: general; surveys; Galaxy: general

The high energy Universe at ultra-high resolution: the power and promise of X-ray interferometry - Uttley, Phil; Hartog, Roland Den; Bambi, Cosimo; Barret, Didier; Bianchi, Stefano; Bursa, Michal; Cappi, Massimo; Casella, Piergiorgio; Cash, Webster; Costantini, Elisa; Dauser, Thomas; Trigo, Maria Diaz; et al. (Experimental Astronomy, 2021)
We propose the development of X-ray interferometry (XRI), to reveal the Universe at high energies with ultra-high spatial resolution. With baselines which can be accommodated on a single spacecraft, XRI can reach 100 μ as resolution at 10 Å (1.2 keV) and 20 μ as at 2 Å (6 keV), enabling imaging and imaging-spectroscopy of (for example) X-ray coronae of nearby accreting supermassive black holes (SMBH) and the SMBH ‘shadow’; SMBH accretion flows and outflows; X-ray binary winds and orbits; stellar coronae within ∼ 100 pc and many exoplanets which transit across them. For sufficiently luminous sources XRI will resolve sub-pc scales across the entire observable Universe, revealing accreting binary SMBHs and enabling trigonometric measurements of the Hubble constant with X-ray light echoes from quasars or explosive transients. A multi-spacecraft ‘constellation’ interferometer would resolve well below 1 μ as, enabling SMBH event horizons to be resolved in many active galaxies and the detailed study of the effects of strong field gravity on the dynamics and emission from accreting gas close to the black hole.
CRIS-Team Scopus Importer:2021-06-04
Keywords: Instrumentation; Interferometry; X-ray astronomy

The high energy X-ray probe (HEX-P): a new window into neutron star accretion - Ludlam, R. M.; Malacaria, C; Sokolova-Lapa, Ekaterina; Fuerst, Felix; Pradhan, P; Shaw, A. W.; Pottschmidt, Katja; Pike, S; Vasilopoulos, G; Wilms, Jörn; Garciá, J. A.; Madsen, K. K.; et al. (Frontiers in Astronomy and Space Sciences, 2023)
Accreting neutron stars (NSs) represent a unique laboratory for probing the physics of accretion in the presence of strong magnetic fields (B ≳ 108 G). Additionally, the matter inside the NS itself exists in an ultra-dense, cold state that cannot be reproduced in Earth-based laboratories. Hence, observational studies of these objects are a way to probe the most extreme physical regimes. Here we present an overview of the field and discuss the most important outstanding problems related to NS accretion. We show how these open questions regarding accreting NSs in both low-mass and high-mass X-ray binary systems can be addressed with the High-Energy X-ray Probe (HEX-P) via simulated data. In particular, with the broad X-ray passband and improved sensitivity afforded by a low X-ray background, HEX-P will be able to 1) distinguish between competing continuum emission models; 2) provide tighter upper limits on NS radii via reflection modeling techniques that are independent and complementary to other existing methods; 3) constrain magnetic field geometry, plasma parameters, and accretion column emission patterns by characterizing fundamental and harmonic cyclotron lines and exploring their behavior with pulse phase; 4) directly measure the surface magnetic field strength of highly magnetized NSs at the lowest accretion luminosities; as well as 5) detect cyclotron line features in extragalactic sources and probe their dependence on luminosity in the super-Eddington regime in order to distinguish between geometrical evolution and accretion-induced decay of the magnetic field. In these ways HEX-P will provide an essential new tool for exploring the physics of NSs, their magnetic fields, and the physics of extreme accretion.<br

The High-Energy X-ray Probe (HEX-P) - Morrissey, Patrick; Madsen, Kristin; Amini, Rashied; Dawson, Douglas; Grefenstette, Brian; Abramovici, Alex; Bandyopadhyay, Saptarshi; Vila, Guillem Casadesus; Franklin, Steve; Johnson, William; Kedar, Sharon; Lane, Marc; et al. (Proceedings of SPIE - The International Society for Optical Engineering, 2023)
HEX-P is a probe-class mission concept that will combine high angular resolution (< 5′′ at 6 keV) X-ray imaging and broad energy sensitivity (0.2 − 80 keV) to enable revolutionary new insights into black holes, neutron stars, and other extreme environments powering the high energy universe. HEX-P prioritizes broad band imagery and high resolution simultaneously, providing a wealth of information not possible with any other planned or operating observatory. HEX-P achieves its breakthrough performance by combining technologies developed by experienced partners: high resolution low energy imagery with silicon segmented mirrors provided by the Goddard Space Flight Center (GSFC, Greenbelt, MD); state of the art high energy imagery from nickel shell mirror technology developed by Media Lario (Bosisio Parini, Italy) and the National Institute for Astrophysics (INAF, Merate, Italy) through a contribution from the Italian Space Agency (ASI, Rome, Italy); high speed, high resolution Depleted P-Channel Field Effect Transistor (DEPFET) detectors through a contribution from the Max Planck Institute for Extraterrestrial Physics (MPE, Garching, Germany); photon counting high energy detectors from the NuSTAR team at the California Institute of Technology (Caltech, Pasadena CA); and a spacecraft and payload structure with a 20 m deployable boom developed by Northrop Grumman (Falls Church, VA).
CRIS-Team Scopus Importer:2023-11-24
Keywords: CdZnTe; DEPFET; deployable; Instrumentation; NASA; NuSTAR; Probe; Wolter I; X-ray

The high energy X-ray probe (HEX-P): constraining supermassive black hole growth with population spin measurements - Piotrowska, J. M.; García, J. A.; Walton, D. J.; Beckmann, R. S.; Stern, D.; Ballantyne, D. R.; Wilkins, D. R.; Bianchi, S.; Boorman, P. G.; Buchner, J.; Chen, C. T.; Coppi, P.; et al. (Frontiers in Astronomy and Space Sciences, 2024)
Constraining the primary growth channel of supermassive black holes (SMBHs) remains one the most actively debated questions in the context of cosmological structure formation. Owing to the expected connection between SMBH spin parameter evolution and the accretion and merger history of individual black holes, population spin measurements offer a rare observational window into the cosmic growth of SMBHs. As of today, the most common method for estimating SMBH spin relies on modeling the relativistically broaden atomic profiles in the reflection spectrum observed in X-rays. In this paper, we study the observational requirements needed to confidently distinguish between the primary SMBH growth channels based on their distinct spin-mass distributions predicted by the Horizon-AGN cosmological simulation. Indoing so, we characterize outstanding limitations associated with the existing measurements and discuss the landscape of future observational campaigns which could be planned and executed with future X-ray observatories. We focus our attention on the High-Energy X-ray Probe (HEX-P), a proposed probe-class mission designed to serve the high-energy community in the 2030s.
CRIS-Team Scopus Importer:2024-04-19
Keywords: AGN; black hole growth; black hole spin; future X-ray observatories; supermassive black holes

The high energy X-ray probe (HEX-P): instrument and mission profile - Madsen, Kristin K.; García, Javier A.; Stern, Daniel; Amini, Rashied; Basso, Stefano; Coutinho, Diogo; Grefenstette, Brian W.; Kenyon, Steven; Moretti, Alberto; Morrissey, Patrick; Nandra, Kirpal; Pareschi, Giovanni; et al. (Frontiers in Astronomy and Space Sciences, 2024)
The High Energy X-ray Probe (HEX-P) is a proposed NASA probe-class mission that combines the power of high angular resolution with a broad X-ray bandpass to provide the necessary leap in capabilities to address the important astrophysical questions of the next decade. HEX-P achieves breakthrough performance by combining technologies developed by experienced international partners. To meet the science goals, the payload consists of a suite of co-aligned X-ray telescopes designed to cover the 0.2–80 keV bandpass. The High Energy Telescope (HET) has an effective bandpass of 2–80 keV, and the Low Energy Telescope (LET) has an effective bandpass of 0.2–20 keV. HEX-P will be launched into L1 to enable high observing efficiency, and the combination of bandpass and high observing efficiency delivers a powerful platform for broad science to serve a wide community. The baseline mission is 5 years, with 30% of the observing time dedicated to the PI-led program and 70% to a General Observer (GO) program. The General Observer program will be executed along with the PI-led program.
CRIS-Team Scopus Importer:2024-03-29
Keywords: future concept; HEX-P; instrumentation; mission; X-ray

The HYPERMUCHFUSS campaign - An undiscovered high velocity population - Tillich, Alfred; Geier, Stephan; Heber, Ulrich; Hirsch, Heiko; Maxted, Pierre; Gaensicke, Boris; Marsh, Tom; Napiwotzki, Ralf; Ostensen, Roy; Copperwheat, Chris (Journal of Physics: Conference Series, 2009)
We present an overview and a status report of HYPERMUCHFUSS (HYPER velocity or Massive Unseen Companions of Hot Faint Underluminious Stars Survey) aiming at the detection of a population of high velocity subluminous B stars and white dwarfs. The first class of targets consists of hot subdwarf binaries with massive compact companions, which are expected to show huge radial velocity variations. The second class is formed by the recently discovered Hyper-velocity stars, which are moving so fast that the dynamical ejection by a supermassive black hole seems to be the only explanation for their origin. Until now only one old HVS has been found, but we expect a larger population. We applied an effecient selection technique for hot subdwarfs and white dwarfs with high galactic restframe velocities from the SDSS spectral data base, which serve as first epoch observations for our campaign with the ESO VLT and NTT in Chile, the 3.5 m telescope at DSAZ observatory (Calar Alto) in Spain and the WHT on La Palma. The survey is nearing completion and provides us with promising candidates which will be followed up to measure their RV-curves to uncover massive companions or prove their nature as HVS. © 2009 IOP Publishing Ltd.
CRIS-Team Scopus Importer:2020-12-21

The Hyper-MUCHFUSS project: Probing the Galactic halo with sdB stars - Tillich, A.; Heber, Ulrich; Geier, Stephan; Hirsch, H.; Maxted, P. F. L.; Gaensicke, B. T.; Marsh, T. R.; Napiwotzki, R.; Ostensen, R. H.; Scholz, R. -D. (Astronomy & Astrophysics, 2011)
Context. High-velocity stars in the Galactic halo, e.g. the so-called hyper-velocity stars (HVS), are important tracers of the properties of the dark matter halo, in particular its mass. Aims. A search for the fastest stars among hot subdwarfs (sdB) in the halo is carried out to identify HVS, unbound to the Galaxy, and bound population II stars, in order to derive a lower limit to the halo mass. Methods. Based on the SDSS DR6 spectral database we selected stars with high rest-frame velocities. These radial velocity (RV) measurements were verified at several telescopes to exclude RV variable stars. Out of 88 stars observed in the follow-up campaign, 39 stars were found to have constant RVs. For twelve of them we measured a proper motion significantly different from zero and obtained spectroscopic distances from quantitative spectral analysis to construct the full 6D phase space information for a kinematical study. Results. All but one programme sdB show halo characteristics, but can be distinguished as two kinematical groups, one (G1) with the low Galactic rotation typical of halo stars and a second one (G2) with rapid retrograde motion. We also investigate the possibility that the programme stars are not genuine halo stars but ejected from the Galactic disc or bulge. The G1 objects crossed the Galactic plane in the central bulge, whereas the G2 stars did so in the outer Galactic disc. J1211+1437 (G2) is an HVS candidate, as it is unbound to the Galaxy if the standard Galactic potential is adopted. Conclusions. We conclude that in the ejection scenario, G1 stars might have been formed via the slingshot mechanism that invokes acceleration by tidal interaction of a binary with the central supermassive black hole. The G2 stars, however, would originate in the outskirts of the Galactic disc and not in the central bulge. J1211+1437 is the first unbound subdwarf B star, for which we can rule out the slingshot mechanism. Alternatively, we may assume that the stars are old population II stars and so they have to be bound. Then the kinematics of J1211+1437 set a lower limit of 2 × 1012 Mâš™ to the mass of the Galactic dark matter halo. © 2011 ESO.
CRIS-Team Scopus Importer:2020-12-21
Keywords: Galaxy: halo; line: profiles; proper motions; stars: atmospheres; stars: kinematics and dynamics; subdwarfs

The HYPER-MUCHFUSS project-target selection and analysis - Tillich, A.; Geier, S.; Heber, Ulrich; Hirsch, H.; Maxted, P. F. L.; Marsh, T.; Gansicke, B.; Napiwotzki, R.; Ostensen, R.; Scholz, R-D (Astrophysics and Space Science, 2010)
The HYPER-MUCHFUSS project targets a population of high velocity subluminous B stars to discover either close binaries with massive unseen companions or hyper-velocity stars. Our starting point is the enormous database of SDSS. We preselected sdO/B candidates by colour and classified them by visual inspection of their spectra. We measured the radial velocity from the coadded SDSS spectra, which serves as first epoch measurement. Stars with high Galactic rest-frame velocities were selected and second epoch observations were obtained starting in 2007 at several sites. For the brighter targets we also included the SDSS individual spectra as additional information. In the course of our survey we observed 88 out of 265 stars from our target list. We discovered 39 HVS candidates as well as 49 close binaries. In addition we analysed all single spectra of sdBs from SDSS and found 120 close binaries. For the targets with constant RVs we performed a proper motion analysis with the highest possible accuracy from the available digitised photographic plates. Together with the analysed spectra and the calculation of the spectroscopic distance, we calculated complete trajectories and deduced the origins of these stars. Targets with high RV variability on short timescales were selected for follow-up. Numerical simulations based on the period and companion mass distribution of the known sdB binary sample were carried out to optimise the target selection and single out candidate binaries with massive companions. The follow-up campaign using WHT/ISIS and CAHA-3.5m/TWIN started in 2009.
Keywords: Kinematics; Individual; Atmospheres; Line profiles

The HYPER-MUCHFUSS project-the constant high-velocity population - Tillich, A.; Geier, Stephan; Heber, Ulrich; Hirsch, H.; Maxted, P. F. L.; Marsh, T.; Gaensicke, Boris T; Napiwotzki, R.; Otensen, R.; Scholz, R-D (Astrophysics and Space Science, 2010)
The HYPER-MUCHFUSS (HYPER-velocity stars or Massive Unseen Companions of Hot Faint Underluminous Stars from SDSS) project targets a population of high-velocity subluminous B stars to discover either close binaries with massive unseen companions or hyper-velocity stars. We re-observed high-velocity subdwarf selected candidates from the SDSS spectroscopic Data Release 6. Starting in 2007 we used several instruments and have now reached a completion level of 33% (from 265 targets), whereas we found at least 16 close binaries. Here we present results for two of our 39 hyper-velocity star candidates. From the available Digitized Sky Surveys photographic plates we measured a significant proper motion for 14 stars. Combining this information with a detailed spectroscopic analysis allows for the first time a complete determination of the 3D-trajectories for a high-velocity sample. We present our preliminary results for the two subdwarfs J1644+4523 and J1211+1437. Assuming the Standard Allen and Santillan (Rev. Mex. Astron. Astrofis. 22:255, 1991) potential the first one is bound and originates in the central region of the Galaxy. The subdwarf B star J1211+1437 is possibly unbound and seems to originate in the Galactic rim. We also performed numerical kinematical experiments with increased dark matter halo mass. and found that the origin of J1644+4523 in the central region is not changed but the time-of-flight is drastically shortened. J1211+1437 would be bound and probably belongs to population II.
Keywords: Kinematics; Individual; Atmospheres; Line profiles

The impact of crosstalk in the X-IFU instrument on Athena science cases - Den Hartog, R.; Peille, P.; Dauser, Thomas; Jackson, B.; Bandler, S.; Barret, D.; Brand, Thorsten; Den Herder, J. W.; Kiviranta, M.; Van Der Kuur, J.; Smith, S.; Wilms, Jörn (Space Telescopes and Instrumentation 2016: Ultraviolet to Gamma Ray, 2016)
In this paper we present a first assessment of the impact of various forms of instrumental crosstalk on the science performance of the X-ray Integral Field Unit (X-IFU) on the Athena X-ray mission. This assessment is made using the SIXTE end-to-end simulator in the context of one of the more technically challenging science cases for the XIFU instrument. Crosstalk considerations may influence or drive various aspects of the design of the array of high-countrate Transition Edge Sensor (TES) detectors and its Frequency Domain Multiplexed (FDM) readout architecture.
Keywords: Athena; crosstalk; energy resolution; FDM; SIXTE; TES detectors; X-IFU

The impact of precession on the observed population of ULXs - Khan, Norman; Middleton, Matthew J.; Wiktorowicz, Grzegorz; Dauser, Thomas; Roberts, Timothy P.; Wilms, Jörn (Monthly Notices of the Royal Astronomical Society, 2022)
The discovery of neutron stars (NSs) powering several ultraluminous X-ray sources (ULXs) raises important questions about the nature of the underlying population. In this paper, we build on previous work studying silated populations by incorporating a model where the emission originates from a precessing, geometrically beamed wind-cone, created by a supercritical inflow. We obtain estimates - independent of the prescription for the precession period of the wind - for the relative number of ULXs that are potentially visible (persistent or transient) for a range of underlying factors such as the relative abundance of black holes or NSs within the population, maxim precessional angle, and low-mass X-ray binary duty cycle. We make initial comparisons to existing data using a catalogue compiled from XMM-Newton. Finally, based on estimates for the precession period, we deteine how the eROSITA all-sky survey (eRASS) will be able to constrain the underlying demographic.
CRIS-Team Scopus Importer:2021-12-24
Keywords: binaries; black holes; neutron; stars; stars; X-rays

The infrared camera onboard JEM-EUSO - Adams, J. H.; Ahmad, S.; Albert, J. -N.; Allard, D.; Anchordoqui, L.; Andreev, V.; Anzalone, A.; Arai, Y.; Asano, K.; Ave Pernas, M.; Baragatti, P.; Barrillon, P.; et al. (Experimental Astronomy, 2015)
The Extreme Universe Space Observatory on the Japanese Experiment Module (JEM-EUSO) on board the International Space Station (ISS) is the first space-based mission worldwide in the field of Ultra High-Energy Cosmic Rays (UHECR). For UHECR experiments, the atmosphere is not only the showering calorimeter for the primary cosmic rays, it is an essential part of the readout system, as well. Moreover, the atmosphere must be calibrated and has to be considered as input for the analysis of the fluorescence signals. Therefore, the JEM-EUSO Space Observatory is implementing an Atmospheric Monitoring System (AMS) that will include an IR-Camera and a LIDAR. The AMS Infrared Camera is an infrared, wide FoV, imaging system designed to provide the cloud coverage along the JEM-EUSO track and the cloud top height to properly achieve the UHECR reconstruction in cloudy conditions. In this paper, an updated preliminary design status, the results from the calibration tests of the first prototype, the simulation of the instrument, and preliminary cloud top height retrieval algorithms are presented.
Keywords: JEM-EUSO; Space observatory; IR-camera; Ultra-High Energy Cosmic Rays (UHECR)

The INTEGRAL view on black hole X-ray binaries - Motta, S. E.; Rodriguez, J.; Jourdain, E.; Del Santo, M.; Belanger, G.; Cangemi, F.; Grinberg, V.; Kajava, J. J.E.; Kuulkers, E.; Malzac, J.; Pottschmidt, K.; Roques, J. P.; et al. (New Astronomy Reviews, 2021)
INTEGRAL is an ESA mission in fundamental astrophysics that was launched in October 2002. It has been in orbit for over 18 years, during which it has been observing the high-energy sky with a set of instruments specifically designed to probe the emission from hard X-ray and soft γ-ray sources. This paper is devoted to the subject of black hole binaries, which are among the most important sources that populate the high-energy sky. We present a review of the scientific literature based on INTEGRAL data, which has significantly advanced our knowledge in the field of relativistic astrophysics. We briefly summarise the state-of-the-art of the study of black hole binaries, with a particular focus on the topics closer to the INTEGRAL science. We then give an overview of the results obtained by INTEGRAL and by other observatories on a number of sources of importance in the field. Finally, we review the main results obtained over the past 18 years on all the black hole binaries that INTEGRAL has observed. We conclude with a summary of the main contributions of INTEGRAL to the field, and on the future perspectives.
CRIS-Team Scopus Importer:2021-07-30
Keywords: Accretion disc; Binary stars; Black hole physics; Gamma-rays: General; Jets; X-rays: General

The JEM-EUSO mission: An introduction - Adams, J. H.; Ahmad, S.; Albert, J. -N.; Allard, D.; Anchordoqui, L.; Andreev, V.; Anzalone, A.; Arai, Y.; Asano, K.; Pernas, M. Ave; Baragatti, P.; Barrillon, P.; et al. (Experimental Astronomy, 2015)
The Extreme Universe Space Observatory on board the Japanese Experiment Module of the International Space Station, JEM-EUSO, is being designed to search from space ultra-high energy cosmic rays. These are charged particles with energies from a few 10(19) eV to beyond 10(20) eV, at the very end of the known cosmic ray energy spectrum. JEM-EUSO will also search for extreme energy neutrinos, photons, and exotic particles, providing a unique opportunity to explore largely unknown phenomena in our Universe. The mission, principally based on a wide field of view (60 degrees) near-UV telescope with a diameter of similar to 2.5 m, will monitor the earth's atmosphere at night, pioneering the observation from space of the ultraviolet tracks (290-430 nm) associated with giant extensive air showers produced by ultra-high energy primaries propagating in the earth's atmosphere. Observing from an orbital altitude of similar to 400 km, the mission is expected to reach an instantaneous geometrical aperture of A (g e o) a parts per thousand yen 2 x 10(5) km(2) sr with an estimated duty cycle of similar to 20 %. Such a geometrical aperture allows unprecedented exposures, significantly larger than can be obtained with ground-based experiments. In this paper we briefly review the history of space-based search for ultra-high energy cosmic rays. We then introduce the special issue of Experimental Astronomy devoted to the various aspects of such a challenging enterprise. We also summarise the activities of the on-going JEM-EUSO program.
Keywords: Ultra-high energy cosmic rays; Neutrinos

The JEM-EUSO observation in cloudy conditions - Adams, J. H.; Ahmad, S.; Albert, J. -N.; Allard, D.; Anchordoqui, L.; Andreev, V.; Anzalone, A.; Arai, Y.; Asano, K.; Ave Pernas, M.; Baragatti, P.; Barrillon, P.; et al. (Experimental Astronomy, 2015)
The JEM-EUSO (Extreme Universe Space Observatory on-board the Japanese Experiment Module) mission will conduct extensive air shower (EAS) observations on the International Space Station (ISS). Following the ISS orbit, JEM-EUSO will experience continuous changes in the atmospheric conditions, including cloud presence. The influence of clouds on space-based observation is, therefore, an important topic to investigate from both EAS property and cloud climatology points of view. In the present work, the impact of clouds on the apparent profile of EAS is demonstrated through the simulation studies, taking into account the JEM-EUSO instrument and properties of the clouds. These results show a dependence on the cloud-top altitude and optical depth of the cloud. The analyses of satellite measurements on the cloud distribution indicate that more than 60 % of the cases allow for conventional EAS observation, and an additional similar to 20 % with reduced quality. The combination of the relevant factors results in an effective trigger aperture of EAS observation similar to 72 %, compared to the one in the clear atmosphere condition.
Keywords: JEM-EUSO; Ultra-high energy cosmic ray; Extensive air shower

The Large Area Detector of LOFT: the Large Observatory for X-ray Timing - Zane, S.; Walton, D.; Kennedy, T.; Feroci, Marco; Den Herder, J. -W.; Ahangarianabhari, M.; Argan, A.; Azzarello, P.; Baldazzi, Giuseppe; Barbera, Marco; Barret, D.; Bertuccio, G.; et al. (2014)
LOFT (Large Observatory for X-ray Timing) is one of the five candidates that were considered by ESA as an M3 mission (with launch in 2022-2024) and has been studied during an extensive assessment phase. It is specifically designed to perform fast X-ray timing and probe the status of the matter near black holes and neutron stars. Its pointed instrument is the Large Area Detector (LAD), a 10 m(2)-class instrument operating in the 2-30keV range, which holds the capability to revolutionise studies of variability from X-ray sources on the millisecond time scales.The LAD instrument has now completed the assessment phase but was not down-selected for launch. However, during the assessment, most of the trade-offs have been closed leading to a robust and well documented design that will be re-proposed in future ESA calls. In this talk, we will summarize the characteristics of the LAD design and give an overview of the expectations for the instrument capabilities.
Keywords: X-ray; Timing; Compact Objects

The Large Observatory For x-ray Timing - Feroci, Marco; Den Herder, J. W.; Bozzo, E.; Barret, D.; Brandt, Soren; Hernanz, Margarita; Van Der Klis, M.; Pohl, M.; Santangelo, A.; Stella, L.; Watts, A.; Wilms, Jörn; et al. (2014)
The Large Observatory For x-ray Timing (LOFT) was studied within ESA M3 Cosmic Vision framework and participated in the final downselection for a launch slot in 2022-2024. Thanks to the unprecedented combination of effective area and spectral resolution of its main instrument, LOFT will study the behaviour of matter under extreme conditions, such as the strong gravitational field in the innermost regions of accretion flows close to black holes and neutron stars, and the supranuclear densities in the interior of neutron stars. The science payload is based on a Large Area Detector (LAD, 10 m(2) effective area, 2-30 keV, 240 eV spectral resolution, 1 degrees collimated field of view) and a Wide Field Monitor (WFM, 2-50 keV, 4 steradian field of view, 1 arcmin source location accuracy, 300 eV spectral resolution). The WFM is equipped with an on-board system for bright events (e.g. GRB) localization. The trigger time and position of these events are broadcast to the ground within 30 s from discovery. In this paper we present the status of the mission at the end of its Phase A study.
Keywords: X-ray timing; X-ray spectroscopy; X-ray imaging; compact objects; X-ray detectors; microchannel plates

The Large Observatory for X-ray Timing (LOFT) - Feroci, Marco; Stella, L.; Van Der Klis, M.; Courvoisier, T. J. -L.; Hernanz, Margarita; Hudec, R.; Santangelo, A.; Walton, D.; Zdziarski, A.; Barret, D.; Belloni, T.; Braga, J.; et al. (Experimental Astronomy, 2012)
High-time-resolution X-ray observations of compact objects provide direct access to strong-field gravity, to the equation of state of ultradense matter and to black hole masses and spins. A 10 m(2)-class instrument in combination with good spectral resolution is required to exploit the relevant diagnostics and answer two of the fundamental questions of the European Space Agency (ESA) Cosmic Vision Theme "Matter under extreme conditions", namely: does matter orbiting close to the event horizon follow the predictions of general relativity? What is the equation of state of matter in neutron stars? The Large Observatory For X-ray Timing (LOFT), selected by ESA as one of the four Cosmic Vision M3 candidate missions to undergo an assessment phase, will revolutionise the study of collapsed objects in our galaxy and of the brightest supermassive black holes in active galactic nuclei. Thanks to an innovative design and the development of large-area monolithic silicon drift detectors, the Large Area Detector (LAD) on board LOFT will achieve an effective area of similar to 12 m(2) (more than an order of magnitude larger than any spaceborne predecessor) in the 2-30 keV range (up to 50 keV in expanded mode), yet still fits a conventional platform and small/medium-class launcher. With this large area and a spectral resolution of < 260 eV, LOFT will yield unprecedented information on strongly curved spacetimes and matter under extreme conditions of pressure and magnetic field strength.
Keywords: Missions; X-ray timing; compact objects; black holes; neutron stars

The LOFT Ground Segment - Bozzo, E.; Antonelli, A.; Argan, A.; Barret, D.; Binko, P.; Brandt, Soren; Cavazzuti, E.; Courvoisier, T.; Den Herder, J. W.; Feroci, Marco; Ferrigno, C.; Giommi, Paolo; et al. (2014)
LOFT, the Large Observatory For X-ray Timing, was one of the ESA M3 mission candidates that completed their assessment phase at the end of 2013. LOFT is equipped with two instruments, the Large Area Detector (LAD) and the Wide Field Monitor (WFM). The LAD performs pointed observations of several targets per orbit (similar to 90 minutes), providing roughly similar to 80 GB of proprietary data per day (the proprietary period will be 12 months). The WFM continuously monitors about 1/3 of the sky at a time and provides data for about similar to 100 sources a day, resulting in a total of similar to 20 GB of additional telemetry. The LOFT Burst alert System additionally identifies on-board bright impulsive events (e.g., Gamma-ray Bursts, GRBs) and broadcasts the corresponding position and trigger time to the ground using a dedicated system of similar to 15 VHF receivers. All WFM data are planned to be made public immediately. In this contribution we summarize the planned organization of the LOFT ground segment (GS), as established in the mission Yellow Book1. We describe the expected GS contributions from ESA and the LOFT consortium. A review is provided of the planned LOFT data products and the details of the data flow, archiving and distribution. Despite LOFT was not selected for launch within the M3 call, its long assessment phase (>2 years) led to a very solid mission design and an efficient planning of its ground operations.
Keywords: LOFT; X-rays; ground segment; space mission

The LOFT mission concept: A status update - Feroci, M.; Bozzo, E.; Brandt, S.; Hernanz, M.; Van Der Klis, M.; Liu, L. P.; Orleanski, P.; Pohl, M.; Santangelo, A.; Schanne, S.; Stella, L.; Takahashi, T.; et al. (Space Telescopes and Instrumentation 2016: Ultraviolet to Gamma Ray, 2016)
The Large Observatory For x-ray Timing (LOFT) is a mission concept which was proposed to ESA as M3 and M4 candidate in the framework of the Cosmic Vision 2015-2025 program. Thanks to the unprecedented combination of effective area and spectral resolution of its main instrument and the uniquely large field of view of its wide field monitor, LOFT will be able to study the behaviour of matter in extreme conditions such as the strong gravitational field in the innermost regions close to black holes and neutron stars and the supra-nuclear densities in the interiors of neutron stars. The science payload is based on a Large Area Detector (LAD, >8m effective area, 2-30 keV, 240 eV spectral resolution, 1 degree collimated field of view) and a Wide Field Monitor (WFM, 2-50 keV, 4 steradian field of view, 1 arcmin source location accuracy, 300 eV spectral resolution). The WFM is equipped with an on-board system for bright events (e.g., GRB) localization. The trigger time and position of these events are broadcast to the ground within 30 s from discovery. In this paper we present the current technical and programmatic status of the mission.
Keywords: Silicon detectors; spectroscopy; timing; X-ray astronomy

The Long Stare at Hercules X-1. I. Emission Lines from the Outer Disk, the Magnetosphere Boundary, and the Accretion Curtain - Kosec, P.; Kara, E.; Fabian, A. C.; Furst, F.; Pinto, Ciro; Psaradaki, I.; Reynolds, C. S.; Rogantini, D.; Walton, D. J.; Ballhausen, R.; Canizares, C.; Dyda, S.; et al. (Astrophysical Journal, 2022)
Hercules X-1 is a nearly edge-on accreting X-ray pulsar with a warped accretion disk, precessing with a period of about 35 days. The disk precession allows for unique and changing sightlines toward the X-ray source. To investigate the accretion flow at a variety of sightlines, we obtained a large observational campaign on Her X-1 with XMM-Newton (380 ks exposure) and Chandra (50 ks exposure) for a significant fraction of a single disk precession cycle, resulting in one of the best data sets taken to date on a neutron star X-ray binary. Here we present the spectral analysis of the high state high-resolution grating and CCD data sets, including the extensive archival data available for this famous system. The observations reveal a complex Fe K region structure, with three emission line components of different velocity widths. Similarly, the high-resolution soft X-ray spectra reveal a number of emission lines of various widths. We correct for the uncertain gain of the European Photon Imaging Camera pn Timing mode spectra, and track the evolution of these spectral components with Her X-1 precession phase and observed luminosity. We find evidence for three groups of emission lines, the first of which originates in the outer accretion disk (10(5) R (G) from the neutron star). The second line group plausibly originates at the boundary between the inner disk and the pulsar magnetosphere (10(3) R (G)). The last group is too broad to arise in the magnetically truncated disk and instead must originate very close to the neutron star surface, likely from X-ray reflection from the accretion curtain (similar to 10(2) R (G)).
CRIS-Team WoS Importer:2022-09-23

The Low-temperature Corona in ESO 511−G030 Revealed by NuSTAR and XMM-Newton - Zhang, Zuobin; Jiang, Jiachen; Liu, Honghui; Bambi, Cosimo; Reynolds, Christopher S.; Fabian, Andrew C.; Dauser, Thomas; Madsen, Kristin; Young, Andrew; Gallo, Luigi; Yu, Zhibo; Tomsick, John (Astrophysical Journal, 2023)
We present the results from a coordinated XMM-Newton + NuSTAR observation of the Seyfert 1 galaxy ESO 511−G030. With this joint monitoring program, we conduct a detailed variability and spectral analysis. The source remained in a low flux and very stable state throughout the observation period, although there are slight fluctuations of flux over long timescales. The broadband (0.3-78 keV) spectrum shows the presence of a power-law continuum with a soft excess below 2 keV, a relatively narrow iron Kα emission (∼6.4 keV), and an obvious cutoff at high energies. We find that the soft excess can be modeled by two different possible scenarios: a warm (kT e ∼ 0.19 keV) and optically thick (τ = 18-25) Comptonizing corona or a relativistic reflection from a high-density ( log [ n e / cm − 3 ] = 17.1 - 18.5 ) inner disk. All models require a low temperature (kT e ∼ 13 keV) for the hot corona.
CRIS-Team Scopus Importer:2023-06-02

The Magnetospheres of (Accreting) Neutron Stars - Wilms, Jörn (2014)
I give an overview of the most important observational tools to study the magnetospheres of accreting neutron stars, with a focus on accreting neutron stars in high mass X-ray binary systems. Topics covered are the different types of accretion onto neutron stars and the structure of the accretion column, and how models for these can be tested with observations.

The MUCHFUSS photometric campaign - Schaffenroth, Veronika; Geier, S.; Heber, Ulrich; Gerber, Raoul; Schneider, David; Ziegerer, Eva; Cordes, O. (Astronomy & Astrophysics, 2018)
Hot subdwarfs (sdO/Bs) are the helium-burning cores of red giants, which have lost almost all of their hydrogen envelope. This mass loss is often triggered by common envelope interactions with close stellar or even substellar companions. Cool companions like late-type stars or brown dwarfs are detectable via characteristic light-curve variations like reflection effects and often also eclipses. To search for such objects, we obtained multi-band light curves of 26 close sdO/B binary candidates from the MUCHFUSS project with the BUSCA instrument. We discovered a new eclipsing reflection effect system (P = 0 : 168938 d) with a low-mass M dwarf companion (0.116 M-circle dot). Three more reflection effect binaries found in the course of the campaign have already been published; two of them are eclipsing systems, and in one system only showing the reflection effect but no eclipses, the sdB primary is found to be pulsating. Amongst the targets without reflection effect a new long-period sdB pulsator was discovered and irregular light variations were found in two sdO stars. The found light variations allowed us to constrain the fraction of reflection effect binaries and the substellar companion fraction around sdB stars. The minimum fraction of reflection effect systems amongst the close sdB binaries might be greater than 15% and the fraction of close substellar companions in sdB binaries may be as high as 8 .0%. This would result in a close substellar companion fraction to sdB stars of about 3%. This fraction is much higher than the fraction of brown dwarfs around possible progenitor systems, which are solar-type stars with substellar companions around 1AU, as well as close binary white dwarfs with brown dwarf companions. This might suggest that common envelope interactions with substellar objects are preferentially followed by a hot subdwarf phase.
Keywords: subdwarfs; binaries: eclipsing; binaries: spectroscopic; brown dwarfs; stars: fundamental parameters

The MUCHFUSS project - Searching for hot subdwarf binaries with massive unseen companions: Survey, target selection and atmospheric parameters - Geier, Stephan; Hirsch, H.; Tillich, A.; Maxted, P. F. L.; Bentley, S. J.; Ostensen, R. H.; Heber, Ulrich; Gaensicke, B. T.; Marsh, T. R.; Napiwotzki, R.; Barlow, B. N.; O'Toole, S. J. (Astronomy & Astrophysics, 2011)
The project Massive Unseen Companions to Hot Faint Underluminous Stars from SDSS (MUCHFUSS) aims at finding sdBs with compact companions like supermassive white dwarfs (M > 1.0 M⊙), neutron stars or black holes. The existence of such systems is predicted by binary evolution theory and recent discoveries indicate that they are likely to exist in our Galaxy. A determination of the orbital parameters is sufficient to put a lower limit on the companion mass by calculating the binary mass function. If this lower limit exceeds the Chandrasekhar mass and no sign of a companion is visible in the spectra, the existence of a massive compact companion is proven without the need for any additional assumptions. We identified about 1100 hot subdwarf stars from the SDSS by colour selection and visual inspection of their spectra. Stars with high velocities have been reobserved and individual SDSS spectra have been analysed. In total 127 radial velocity variable subdwarfs have been discovered. Binaries with high RV shifts and binaries with moderate shifts within short timespans have the highest probability of hosting massive compact companions. Atmospheric parameters of 69 hot subdwarfs in these binary systems have been determined by means of a quantitative spectral analysis. The atmospheric parameter distribution of the selected sample does not differ from previously studied samples of hot subdwarfs. The systems are considered the best candidates to search for massive compact companions by follow-up time resolved spectroscopy. © 2011 ESO.
CRIS-Team Scopus Importer:2020-12-21
Keywords: binaries: spectroscopic; subdwarfs

The MUCHFUSS project - Searching for massive compact companions to hot subdwarf stars - Geier, Stephan; Heber, Ulrich; Tillich, A.; Hirsch, H.; Müller, S.; Kupfer, T.; Schaffenroth, Veronika; Classen, Lew; Maxted, P. F.L.; Østensen, R. H.; Barlow, B. N.; Marsh, T. R.; et al. (AIP Conference Proceedings, 2010)
The project Massive Unseen Companions to Hot Faint Underluminous Stars from SDSS (MUCHFUSS) aims at finding hot subdwarf stars with massive compact companions like supermassive white dwarfs (M>1.0M⊙), neutron stars or stellar mass black holes. The existence of such systems is predicted by binary evolution theory and recent discoveries indicate that they exist in our Galaxy. We classified about 1500 hot subdwarf stars from the Sloan Digital Sky Survey (SDSS) by colour selection and visual inspection of their spectra. Stars with high velocities have been reobserved and individual SDSS spectra have been analysed. In total about 170 radial velocity variable subdwarfs have been discovered and about 80 of them have been selected as good candidates for follow-up time resolved spectroscopy to derive their orbital parameters. Up to now we found seven close binary sdBs with short orbital periods ranging from ≃0.21 d to 1.5 d. In our photometric follow-up campaign we discovered two eclipsing binaries with most likely substellar companions. © 2010 American Institute of Physics.
CRIS-Team Scopus Importer:2020-12-21
Keywords: stars:binaries; stars:subdwarfs

The Nature of Soft Excess in ESO 362-G18 Revealed by XMM-Newton and NuSTAR Spectroscopy - Xu, Yerong; Garcia, Javier; Walton, Dominic J.; Connors, Riley M. T.; Madsen, Kristin; Harrison, Fiona A. (Astrophysical Journal, 2021)
We present a detailed spectral analysis of the joint XMM-Newton and NuSTAR observations of the active galactic nuclei (AGNs) in the Seyfert 1.5 Galaxy ESO 362-G18. The broadband (0.3-79 keV) spectrum shows the presence of a power-law continuum with a soft excess below 2 keV, iron Kα emission (∼6.4 keV), and a Compton hump (peaking at ∼20 keV). We find that the soft excess can be modeled by two different possible scenarios: a warm (kT e ∼ 0.2 keV) and optically thick (τ ∼ 34) Comptonizing corona, or with a relativistically blurred reflection off a high-density () inner disk. These two models cannot be easily distinguished solely from their fit statistics. However, the low temperature (kT e ∼ 20 keV) and the thick optical depth (τ ∼ 5) of the hot corona required by the warm corona scenario are uncommon for AGNs. We also fit a "hybrid"model, which includes both disk reflection and a warm corona. Unsurprisingly, as this is the most complex of the models considered, this provides the best fit, and more reasonable coronal parameters. In this case, the majority of the soft excess flux arises in the warm corona component. However, based on recent simulations of warm coronae, it is not clear whether such a structure can really exist at the low accretion rates relevant for ESO 362-G18 (˙m∼ 0.015). This may therefore argue in favor of a scenario in which the soft excess is instead dominated by the relativistic reflection. Based on this model, we find that the data would require a compact hot corona (h ∼ 3 R Horizon) around a rapidly spinning (a ∗ > 0.927) black hole.
CRIS-Team Scopus Importer:2021-06-11

The nature of the extreme X-ray variability in the NLS1 1H 0707-495 - Parker, M. L.; Alston, W. N.; Härer, Lucia; Igo, Z.; Joyce, Amy; Buisson, D. J. K.; Chainakun, P.; Fabian, A. C.; Jiang, J.; Kosec, P.; Matzeu, G. A.; Pinto, C.; et al. (Monthly Notices of the Royal Astronomical Society, 2021)
We examine archival XMM Newton data on the extremely variable narrow-line Seyfert 1 active galactic nucleus (AGN) 1H 0707-495. We construct fractional excess variance (F-var) spectra for each epoch, including the recent 2019 observation taken simultaneously with eROSITA. We explore both intrinsic and environmental absorption origins for the variability in different epochs, and examine the effect of the photoionized emission lines from outflowing gas. In particular, we show that the unusual soft variability first detected by eROSITA in 2019 is due to a combination of an obscuration event and strong suppression of the variance at 1 keV by photoionized emission, which makes the variance below 1 keV appear more extreme. We also examine the variability on long time-scales, between observations, and find that it is well described by a combination of intrinsic variability and absorption variability. We suggest that the typical extreme high frequency variability, which 1H 0707-495 is known for, is intrinsic to the source, but the large amplitude, low frequency variability that causes prolonged low-flux intervals is likely dominated by variable low-ionization, low-velocity absorption.
CRIS-Team WoS Importer:2021-12-03

The nature of the hyper-runaway candidate HIP60350 - Irrgang, Andreas; Przybilla, Norbert; Heber, Ulrich; Nieva, M. Fernanda; Schuh, Sonja (Astrophysical Journal, 2010)
Young, massive stars in the Galactic halo are widely supposed to be the result of an ejection event from the Galactic disk forcing some stars to leave their place of birth as so-called runaway stars. Here, we present a detailed spectroscopic and kinematic analysis of the runaway B star HIP 60350 to determine which runaway scenario - a supernova explosion disrupting a binary system or dynamical interaction in star clusters - may be responsible for HIP 60350's peculiar orbit. Based on a non-local thermodynamic equilibrium approach, a high-resolution optical echelle spectrum was examined to revise spectroscopic quantities and for the first time to perform a differential chemical abundance analysis with respect to the B-type star 18 Peg. The results together with proper motions from the Hipparcos Catalog further allowed the three-dimensional kinematics of the star to be studied numerically. The abundances derived for HIP 60350 are consistent with a slightly supersolar metallicity agreeing with the kinematically predicted place of birth ∼6 kpc away from the Galactic center. However, they do not exclude the possibility of an α-enhanced abundance pattern expected in the case of the supernova scenario. Its outstanding high Galactic rest-frame velocity of 530 ± 35 km s-1 is a consequence of ejection in the direction of Galactic rotation and slightly exceeds the local Galactic escape velocity in a standard Galactic potential. Hence, HIP 60350 may be unbound to the Galaxy. © 2010. The American Astronomical Society.
CRIS-Team Scopus Importer:2020-12-21
Keywords: Stars: abundances; Stars: atmospheres; Stars: distances; Stars: early-type; Stars: individual (HIP 60350; 18 Peg); Stars: kinematics and dynamics

The next-generation X-ray galaxy survey with eROSITA - Basu-Zych, Antara R.; Hornschemeier, Ann E.; Haberl, Frank; Vulic, Neven; Wilms, Jörn; Zezas, Andreas; Kovlakas, Konstantinos; Ptak, Andrew; Dauser, Thomas (Monthly Notices of the Royal Astronomical Society, 2020)
eROSITA, launched on 2019 July 13, will be completing the first all-sky survey in the soft and medium X-ray band in nearly three decades. This 4-yr survey, finishing in late 2023, will present a rich legacy for the entire astrophysics community and complement upcoming multiwavelength surveys (with, e.g. the Large Synoptic Survey Telescope and the Dark Energy Survey). Besides the major scientific aim to study active galactic nuclei (AGNs) and galaxy clusters, eROSITAwill contribute significantly to X-ray studies of normal (i.e. not AGN) galaxies. Starting from multiwavelength catalogues, we measure star formation rates and stellar masses for 60 212 galaxies constrained to distances of 50-200 Mpc. We chose this distance range to focus on the relatively unexplored volume outside the local Universe, where galaxies will be largely spatially unresolved and probe a range of X-ray luminosities that overlap with the low luminosity and/or highly obscured AGN population. We use the most recent X-ray scaling relations as well as the on-orbit eROSITA instrument performance to predict the X-ray emission from XRBs and diffuse hot gas and to perform both an analytic prediction and an end-to-end simulation using the mission simulation software, sixte. We consider potential contributions from hidden AGN and comment on the impact of normal galaxies on the measurement of the faint end of the AGN luminosity function. We predict that the eROSITA 4-yr survey, will detect ≳15 000 galaxies (3σ significance) at 50-200 Mpc, which is ∼100 × more normal galaxies than detected in any X-ray survey to date.
CRIS-Team Scopus Importer:2020-12-04
Keywords: galaxies: Statistics; surveys; X-rays: Galaxies

The NICER "Reverberation Machine": A Systematic Study of Time Lags in Black Hole X-Ray Binaries - Wang, Jingyi; Kara, Erin; Lucchini, Matteo; Ingram, Adam; Van Der Klis, Michiel; Mastroserio, Guglielmo; Garcia, Javier A.; Dauser, Thomas; Connors, Riley; Fabian, Andrew C.; Steiner, James F.; Remillard, Ron A.; et al. (Astrophysical Journal, 2022)
We perform the first systematic search of all NICER archival observations of black hole (and candidate) low-mass X-ray binaries for signatures of reverberation. Reverberation lags result from the light travel time difference between the direct coronal emission and the reflected disk component, and therefore their properties are a useful probe of the disk-corona geometry. We detect new signatures of reverberation lags in eight sources, increasing the total sample from three to 11, and study the evolution of reverberation lag properties as the sources evolve in outbursts. We find that in all of the nine sources with more than one reverberation lag detection, the reverberation lags become longer and dominate at lower Fourier frequencies during the hard-to-soft state transition. This result shows that the evolution in reverberation lags is a global property of the state transitions of black hole low-mass X-ray binaries, which is valuable in constraining models of such state transitions. The reverberation lag evolution suggests that the corona is the base of a jet that vertically expands and/or gets ejected during state transition. We also discover that in the hard state, the reverberation lags get shorter, just as the quasiperiodic oscillations (QPOs) move to higher frequencies, but then in the state transition, while the QPOs continue to higher frequencies, the lags get longer. We discuss the implications of the coronal geometry and physical models of QPOs in light of this new finding.
CRIS-Team WoS Importer:2022-05-13

The NuSTAR X-Ray Spectrum of Hercules X-1: A Radiation-dominated Radiative Shock - Wolff, Michael T.; Becker, Peter A.; Gottlieb, Amy M.; Fuerst, Felix; Hemphill, Paul B.; Marcu-Cheatham, Diana M.; Pottschmidt, Katja; Schwarm, Fritz-Walter; Wilms, Jörn; Wood, Kent S. (Astrophysical Journal, 2016)
Keywords: methods: data analysis; radiative transfer; stars: individual: Her X-1; stars: neutron; X-rays: binaries

The OmegaWhite survey for short-period variable stars - VII. High amplitude short-period blue variables - Ramsay, Gavin; Woudt, Patrick A.; Kupfer, Thomas; Van Roestel, Jan; Paterson, Kerry; Warner, Brian; Buckley, David A. H.; Groot, Paul J.; Heber, Ulrich; Irrgang, Andreas; Jeffery, C. Simon; Motsoaledi, Mokhine; et al. (Monthly Notices of the Royal Astronomical Society, 2022)
Blue Large-Amplitude Pulsators (BLAPs) are a relatively new class of blue variable stars showing periodic variations in their light curves with periods shorter than a few tens of minutes and amplitudes of more than 10 per cent. We report nine blue variable stars identified in the OmegaWhite survey conducted using ESO's VST, which shows a periodic modulation in the range 7-37 min and an amplitude in the range 0.11-0.28 mag. We have obtained a series of followup photometric and spectroscopic observations made primarily using SALT and telescopes at SAAO. We find four stars which we identify as BLAPs, one of which was previously known. One star, OW J0820-3301, appears to be a member of the V361 Hya class of pulsating stars and is spatially close to an extended nebula. One further star, OW J1819-2729, has characteristics similar to the sdAV pulsators. In contrast, OW J0815-3421 is a binary star containing an sdB and a white dwarf with an orbital period of 73.7 min, making it only one of six white dwarf-sdB binaries with an orbital period shorter than 80 min. Finally, high cadence photometry of four of the candidate BLAPs show features that we compare with notch-like features seen in the much longer period Cepheid pulsators.
CRIS-Team WoS Importer:2022-05-20

The origin of early-type runaway stars from open clusters - Bhat, Aakash; Irrgang, A.; Heber, U. (Astronomy & Astrophysics, 2022)
Runaway stars are ejected from their place of birth in the Galactic disk, with some young B-type runaways found several tens of kiloparsecs from the plane traveling at speeds beyond the escape velocity, which calls for violent ejection processes. Young open clusters are a likely place of origin, and ejection may be either through N-body interactions or in binary supernova explosions. The most energetic events may require dynamical interaction with massive black holes. The excellent quality of Gaia astrometry opens up the path to study the kinematics of young runaway stars to such a high precision that the place of origin in open stellar clusters can be identified uniquely even when the star is a few kiloparsecs away. We developed an efficient minimization method to calculate whether two or more objects may come from the same place, which we tested against samples of Orion runaways. Our fitting procedure was then used to calculate trajectories for known runaway stars, which have previously been studied from HIPPARCOS astrometry as well as known open clusters. For runaways in our sample we used Gaia data and updated radial velocities, and found that only half of the sample could be classified as runaways. The other half of the sample moves so slowly (< 30 km s(-1)) that they have to be considered as walkaway stars. Most of the latter stars turned out to be binaries. We identified parent clusters for runaways based on their trajectories. We then used cluster age and flight time of the stars to investigate whether the ejection was likely due to a binary supernova or due to a dynamical ejection. In particular we show that the classical runaways AE Aurigae and mu Columbae might not have originated together, with mu Columbae having an earlier ejection from Collinder 69, a cluster near the ONC. The second sample investigated comprises a set of distant runaway B stars in the halo which have been studied carefully by quantitative spectral analyses. We are able to identify candidate parent clusters for at least four stars including the hyper-runaway candidate HIP 60350. The ejection events had to be very violent, ejecting stars at velocities as large as 150-400 km s(-1).
CRIS-Team WoS Importer:2022-07-22

The origin of subluminous O stars - Heber, Ulrich; Hirsch, Heiko (AIP Conference Proceedings, 2010)
Amongst the hot subdwarf stars, the helium enriched sdOs still remain a mystery. Rivalling scenarios for their origin include mergers of He white dwarfs, first proposed by Ron Webbink, and the so-called "late hot flasher" where a star undergoes a delayed helium flash long after leaving the RGB. Recent NLTE spectral analyses revealed that an evolutionary link between sdO stars and their cooler cousins, the sdB stars, is plausible only for the helium-deficient sdO stars, i.e. they are the likely successors to sdB stars. A large sample of sdO stars has recently been analysed using NLTE model atmospheres to derive carbon and nitrogen abundances. The stars are generally speaking either C-rich or N-rich - a few are both. The N-rich stars are on average significantly cooler than the C-rich, whereas both subsample have the same mean surface gravity. The surface composition of N-rich He-sdOs are best explained by the merger of two helium white dwarfs or of a helium white dwarf with a post-sdB star. Only the late flasher model seems to be capable to explain the C-rich sdO stars. Closer inspection, however, reveals problems for both scenarios to explain the distribution of the stars in the (Teff, log g)-plane as well as the rotational properties. A hyper-velocity sdO star moving so fast that it is unbound to the Galaxy possibly has been ejected by the super-massive black hole in the Galactic centre. © 2010 American Institute of Physics.
CRIS-Team Scopus Importer:2020-12-21
Keywords: Chemical Composition; Hot Subluminous stars; Stellar binary evolution

The Performance of the Athena X-ray Integral Field Unit at Very High Count Rates - Peille, Philippe; Dauser, Thomas; Kirsch, Christian; Den Hartog, R.; Cucchetti, E.; Wilms, Jörn; Barret, D.; Den Herder, J. -W.; Piro, Luigi (Journal of Low Temperature Physics, 2018)
The Athena X-ray Integral Field Unit (X-IFU) will operate at 90 mK a hexagonal matrix of 3840 Transition Edge Sensor pixels providing spatially resolved high-resolution spectroscopy (2.5 eV FWHM up to 7 keV) between 0.2 and 12 keV. During the observation of very bright X-ray sources, the X-IFU detectors will receive high photon rates going up to several tens of counts per second per pixel and hundreds per readout channel, well above the normal operating mode of the instrument. In this paper, we investigate through detailed end-to-end simulations the performance achieved by the X-IFU at the highest count rates. Special care is notably taken to model and characterize pulse processing limitations, readout-chain saturation effects, as well as the non-Gaussian degradation of the energy redistribution from crosstalk at the focal plane level (both thermal and electrical). Overall, we show that the instrument performance should safely exceed the scientific requirements, and in particular that more than 50% throughput at 1 Crab in the 5-8 keV band can be achieved with better than 10 eV average resolution with the use of a Beryllium filter, enabling breakthrough science in the field of bright sources.
Keywords: X-IFU; X-ray microcalorimeters; TES; Crosstalk; FDM

The population of hot subdwarf stars studied with Gaia. II. The Gaia DR2 catalogue of hot subluminous stars - Geier, S.; Raddi, Roberto; Fusillo, N. P. Gentile; Marsh, T. R. (Astronomy & Astrophysics, 2019)
Based on data from the ESA Gaia Data Release 2 (DR2) and several ground-based, multi-band photometry surveys we have compiled an all-sky catalogue of 39 800 hot subluminous star candidates selected in Gaia DR2 by means of colour, absolute magnitude, and reduced proper motion cuts. We expect the majority of the candidates to be hot subdwarf stars of spectral type B and O, followed by blue horizontal branch stars of late B-type (HBB), hot post-AGB stars, and central stars of planetary nebulae. The contamination by cooler stars should be about 10%. The catalogue is magnitude limited to Gaia G < 19 mag and covers the whole sky. Except within the Galactic plane and LMC/SMC regions, we expect the catalogue to be almost complete up to about 1.5 kpc. The main purpose of this catalogue is to serve as input target list for the large-scale photometric and spectroscopic surveys which are ongoing or scheduled to start in the coming years. In the long run, securing a statistically significant sample of spectroscopically confirmed hot subluminous stars is key to advance towards a more detailed understanding of the latest stages of stellar evolution for single and binary stars.
CRIS-Team Scopus Importer:2019-07-16
Keywords: Catalogs; Stars: horizontal-branch; Subdwarfs

The population of X-ray supernova remnants in the Large Magellanic Cloud - Sasaki, Manami; et al. (Astronomy & Astrophysics, 2016)
Aims: We present a comprehensive X-ray study of the population of supernova remnants (SNRs) in the Large Magellanic Cloud (LMC). Using primarily XMM-Newton observations, we conduct a systematic spectral analysis of LMC SNRs to gain new insight into their evolution and the interplay with their host galaxy. Methods: We combined all the archival XMM-Newton observations of the LMC with those of our Very Large Programme LMC survey. We produced X-ray images and spectra of 51 SNRs, out of a list of 59 objects compiled from the literature and augmented with newly found objects. Using a careful modelling of the background, we consistently analysed all the X-ray spectra and measure temperatures, luminosities, and chemical compositions. The locations of SNRs are compared to the distributions of stars, cold gas, and warm gas in the LMC, and we investigated the connection between the SNRs and their local environment, characterised by various star formation histories. We tentatively typed all LMC SNRs, in order to constrain the ratio of core-collapse to type Ia SN rates in the LMC. We also compared the column densities derived from X-ray spectra to H I maps, thus probing the three-dimensional structure of the LMC. Results: This work provides the first homogeneous catalogue of the X-ray spectral properties of SNRs in the LMC. It offers a complete census of LMC remnants whose X-ray emission exhibits Fe K lines (13% of the sample), or reveals the contribution from hot supernova ejecta (39%), which both give clues to the progenitor types. The abundances of O, Ne, Mg, Si, and Fe in the hot phase of the LMC interstellar medium are found to be between 0.2 and 0.5 times the solar values with a lower abundance ratio [α/Fe] than in the Milky Way. The current ratio of core-collapse to type Ia SN rates in the LMC is constrained to NCC/NIa=1.35(-0.24+0.11), which is lower than in local SN surveys and galaxy clusters. Our comparison of the X-ray luminosity functions of SNRs in Local Group galaxies (LMC, SMC, M31, and M33) reveals an intriguing excess of bright objects in the LMC. Finally, we confirm that 30 Doradus and the LMC Bar are offset from the main disc of the LMC to the far and near sides, respectively.
Keywords: ISM: supernova remnants; Magellanic Clouds; ISM: abundances; supernovae: general; stars: formation; X-rays: ISM

The positioning system of the ANTARES Neutrino Telescope - Adrian-Martinez, S.; Ageron, M.; Aguilar, J. A.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Jesus, A. C. Assis; Astraatmadja, T.; et al. (Journal of Instrumentation, 2012)
The ANTARES neutrino telescope, located 40km off the coast of Toulon in the Mediterranean Sea at a mooring depth of about 2475m, consists of twelve detection lines equipped typically with 25 storeys. Every storey carries three optical modules that detect Cherenkov light induced by charged secondary particles (typically muons) coming from neutrino interactions. As these lines are flexible structures fixed to the sea bed and held taut by a buoy, sea currents cause the lines to move and the storeys to rotate. The knowledge of the position of the optical modules with a precision better than 10cm is essential for a good reconstruction of particle tracks. In this paper the ANTARES positioning system is described. It consists of an acoustic positioning system, for distance triangulation, and a compass-tiltmeter system, for the measurement of the orientation and inclination of the storeys. Necessary corrections are discussed and the results of the detector alignment procedure are described.
Keywords: Timing detectors; Detector modelling and simulations II (electric fields; charge transport; multiplication and induction; pulse formation; electron emission; etc); Detector alignment and calibration methods (lasers; sources; particle-beams); Detector control systems (detector and experiment monitoring and slow-control systems; architecture; hardware; algorithms; databases)

The pre-outburst flare of the A 0535+26 August/September 2005 outburst - Caballero, I.; Santangelo, A.; Kretschmar, Peter; Staubert, R.; Postnov, Konstantin; Klochkov, D.; Camero-Arranz, A.; Finger, M. H.; Kreykenbohm, Ingo; Pottschmidt, K.; Rothschild, R. E.; Suchy, S.; et al. (Astronomy & Astrophysics, 2008)
We study the spectral and temporal behavior of the High Mass X-ray Binary A 0535+26 during a "pre-outburst flare" which took place similar to 5d before the peak of a normal (type I) outburst in August/September 2005. We compare the studied behavior with that observed during the outburst.Methods. We analyse RXTE observations that monitored A 0535+26 during the outburst. We complete spectral and timing analyses of the data. We study the evolution of the pulse period, present energy-dependent pulse profiles both at the initial pre-outburst flare and close to outburst maximum, and measure how the cyclotron resonance-scattering feature (hereafter CRSF) evolves.Results. We present three main results: a constant period P = 103.3960(5) s is measured until periastron passage, followed by a spin-up with a decreasing period derivative of. P = (-1.69 +/- 0.04) x 10(-8) s s(-1) at MJD 53 618, and P remains constant again at the end of the main outburst. The spin-up provides evidence for the existence of an accretion disk during the normal outburst. We measure a CRSF energy of E-cyc similar to 50 keV during the pre-outburst flare, and E-cyc similar to 46 keV during the main outburst. The pulse shape, which varies significantly during both pre-outburst flare and main outburst, evolves strongly with photon energy.
Keywords: X-rays : binaries; stars : magnetic fields; stars : individual : A 0535+26

The prototype detection unit of the KM3NeT detector: KM3NeT Collaboration - Adrian-Martinez, S.; Ageron, M.; Aharonian, F.; Aiello, S.; Albert, A.; Ameli, F.; Anassontzis, E. G.; Androulakis, G. C.; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, M.; et al. (European Physical Journal C: Particles and Fields, 2016)
A prototype detection unit of the KM3NeT deep-sea neutrino telescope has been installed at 3500m depth 80 km offshore the Italian coast. KM3NeT in its final configuration will contain several hundreds of detection units. Each detection unit is a mechanical structure anchored to the sea floor, held vertical by a submerged buoy and supporting optical modules for the detection of Cherenkov light emitted by charged secondary particles emerging from neutrino interactions. This prototype string implements three optical modules with 31 photomultiplier tubes each. These optical modules were developed by the KM3NeT Collaboration to enhance the detection capability of neutrino interactions. The prototype detection unit was operated since its deployment in May 2014 until its decommissioning in July 2015. Reconstruction of the particle trajectories from the data requires a nanosecond accuracy in the time calibration. A procedure for relative time calibration of the photomultiplier tubes contained in each optical module is described. This procedure is based on the measured coincidences produced in the sea by the ^4040K background light and can easily be expanded to a detector with several thousands of optical modules. The time offsets between the different optical modules are obtained using LED nanobeacons mounted inside them. A set of data corresponding to 600 h of livetime was analysed. The results show good agreement with Monte Carlo simulations of the expected optical background and the signal from atmospheric muons. An almost background-free sample of muons was selected by filtering the time correlated signals on all the three optical modules. The zenith angle of the selected muons was reconstructed with a precision of about 3^° ∘.

The reawakening of the sleeping X-ray pulsar XTE J1946+274 - Müller, Sebastian; Kühnel, Matthias; Caballero, I.; Pottschmidt, K.; Fürst, Felix; Kreykenbohm, Ingo; Sagredo, Macarena; Obst, M.; Wilms, Jörn; Ferrigno, C.; Rothschild, R. E.; Staubert, R. (Astronomy & Astrophysics, 2012)
We report on a series of outbursts of the high-mass X-ray binary XTE J1946+274 in 2010/2011 observed with INTEGRAL, RXTE, and Swift. We discuss possible mechanisms resulting in the extraordinary outburst behavior of this source. The X-ray spectra can be described by standard phenomenological models, enhanced by an absorption feature of unknown origin at about 10 keV and a narrow iron K alpha fluorescence line at 6.4 keV, which are variable in flux and pulse phase. We find possible evidence for a cyclotron resonance scattering feature at about 25 keV at the 93% level. The presence of a strong cyclotron line at 35 keV seen in data from the source's 1998 outburst that was confirmed by a reanalysis of these data can be excluded. This result indicates that the cyclotron line feature in XTE J1946+274 is variable between individual outbursts.
Keywords: X-rays: binaries; accretion; accretion disks

THE REFLECTION COMPONENT FROM CYGNUS X-1 IN THE SOFT STATE MEASURED BY NuSTAR AND SUZAKU - Tomsick, John A.; Nowak, Michael A.; Parker, Michael; Miller, Jon M.; Fabian, Andy C.; Harrison, Fiona A.; Bachetti, Matteo; Barret, Didier; Boggs, Steven E.; Christensen, Finn E.; Craig, William W.; Forster, Karl; et al. (Astrophysical Journal, 2014)
The black hole binary Cygnus X-1 was observed in late 2012 with the Nuclear Spectroscopic Telescope Array (NuSTAR) and Suzaku, providing spectral coverage over the similar to 1-300 keV range. The source was in the soft state with a multi-temperature blackbody, power law, and reflection components along with absorption from highly ionized material in the system. The high throughput of NuSTAR allows for a very high quality measurement of the complex iron line region as well as the rest of the reflection component. The iron line is clearly broadened and is well described by a relativistic blurring model, providing an opportunity to constrain the black hole spin. Although the spin constraint depends somewhat on which continuum model is used, we obtain a(*) > 0.83 for all models that provide a good description of the spectrum. However, none of our spectral fits give a disk inclination that is consistent with the most recently reported binary values for Cyg X-1. This may indicate that there is a > 13 degrees misalignment between the orbital plane and the inner accretion disk (i.e., a warped accretion disk) or that there is missing physics in the spectral models.
Keywords: accretion; accretion disks; black hole physics; stars: individual (Cygnus X-1); X-rays: general; X-rays: stars

The role of the reflection fraction in constraining black hole spin - Dauser, Thomas; Garcia, Javier; Parker, M. L.; Fabian, A. C.; Wilms, Jörn (Monthly Notices of the Royal Astronomical Society, 2014)
In many active galaxies, the X-ray reflection features from the innermost regions of the accretion disc are relativistically distorted. This distortion allows us to measure parameters of the black hole such as its spin. The ratio in flux between the direct and the reflected radiation, the so-called reflection fraction, is determined directly from the geometry and location of primary source of radiation. We calculate the reflection fraction in the lamp post geometry in order to determine its maximal possible value for a given value of black hole spin. We show that high reflection fractions in excess of two are only possible for rapidly rotating black holes, suggesting that the high spin sources produce the strongest relativistic reflection features. Using simulations we show that taking this constraint into account does significantly improve the determination of the spin values. We make software routines for the most popular X-ray data analysis packages available that incorporate these additional constraints.
Keywords: accretion; accretion discs; black hole physics; line: profiles; galaxies: active; galaxies: nuclei

The search for high-energy neutrinos coincident with fast radio bursts with the ANTARES neutrino telescope - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J-J; Aublin, J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Belhorma, B.; et al. (Monthly Notices of the Royal Astronomical Society, 2019)
In the past decade, a new class of bright transient radio sources with millisecond duration has been discovered. The origin of these so-called fast radio bursts (FRBs) is still a mystery, despite the growing observational efforts made by various multiwavelength and multimessenger facilities. To date, many models have been proposed to explain FRBs, but neither the progenitors nor the radiative and the particle acceleration processes at work have been clearly identified. In this paper, we assess whether hadronic processes may occur in the vicinity of the FRB source. If they do, FRBs may contribute to the high-energy cosmic-ray and neutrino fluxes. A search for these hadronic signatures was carried out using the ANTARES neutrino telescope. The analysis consists in looking for high-energy neutrinos, in the TeV-PeV regime, that are spatially and temporally coincident with the detected FRBs. Most of the FRBs discovered in the period 2013-2017 were in the field of view of the ANTARES detector, which is sensitive mostly to events originating from the Southern hemisphere. From this period, 12 FRBs were selected and no coincident neutrino candidate was observed. Upper limits on the per-burst neutrino fluence were derived using a power-law spectrum, dN/DE nu proportional to E-nu(-gamma), for the incoming neutrino flux, assuming spectral indexes gamma = 1.0, 2.0, 2.5. Finally, the neutrino energy was constrained by computing the total energy radiated in neutrinos, assuming different distances for the FRBs. Constraints on the neutrino fluence and on the energy released were derived from the associated null results.
Keywords: acceleration of particles; neutrinos; astroparticle physics; radio continuum: transients; methods: data analysis

The Search for Neutrinos from TXS 0506+056 with the ANTARES Telescope - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J-J; Aublin, J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Belhorma, B.; et al. (Astrophysical Journal Letters, 2018)
The results of three different searches for neutrino candidates, associated with the IceCube-170922A event or from the direction of TXS 0506+056, by the ANTARES neutrino telescope, are presented. The first search refers to the online follow-up of the IceCube alert; the second is based on the standard time-integrated method employed by the Collaboration to search for point-like neutrino sources; the third uses information from the IceCube time-dependent analysis that reported bursting activity centered on 2014 December 13, as input for an ANTARES time-dependent analysis. The online follow-up and the time-dependent analysis yield no events related to the source. The time-integrated study performed over a period from 2007 to 2017 fits 1.03 signal events, which corresponds to a p-value of 3.4% (not considering trial factors). Only for two other astrophysical objects in our candidate list has a smaller p-value been found. When considering that 107 sources have been investigated, the post-trial p-value for TXS 0506+056 corresponds to 87%.
Keywords: astroparticle physics; elementary particles; galaxies: active

THESEUS insights into axionlike particles, dark photon, and sterile neutrino dark matter - Thorpe-Morgan, Charles; Malyshev, Denys; Santangelo, Andrea; Jochum, Josef; Jaeger, Barbara; Sasaki, Manami; Saeedi, Sara (Physical Review D, 2020)
Through a series of simulated observations, we investigate the capability of the instruments aboard the forthcoming THESEUS mission for the detection of a characteristic signal from decaying dark matter (DM) in the keV-McV energy range. We focus our studies on three well studied Standard Model extensions hosting axionlike particles, dark photon, and sterile neutrino DM candidates. We show that, due to the sensitivity of THESEUS' x and gamma imaging spectrometer instrument, existing constraints on dark matter parameters can be improved by a factor of up to similar to 300, depending on the considered DM model and assuming a zero level of systematic uncertainty. We also show that even a minimal level of systematic uncertainty of 1% can impair potential constraints by one to two orders of magnitude. We argue that nonetheless, the constraints imposed by THESEUS will be substantially better than existing ones and will well complement the constraints of upcoming missions such as eXTP and Athena. Ultimately, the limits imposed by THESEUS and future missions will ensure a robust and thorough coverage of the parameter space for decaying DM models, enabling either a detection of dark matter or a significant improvement of relevant limits.
CRIS-Team WoS Importer:2021-01-01

The simultaneous low state spectral energy distribution of 1ES 2344+514 from radio to very high energies - Aleksic, J.; Antonelli, L. A.; Antoranz, Pedro; Asensio, M.; Backes, Michael; De Almeida, U. Barres; Barrio, J. A.; Bednarek, Wlodek; Berger, K.; Bernardini, E.; Biland, A.; Blanch, O.; et al. (Astronomy & Astrophysics, 2013)
Context. BL Lacertae objects are variable at all energy bands on time scales down to minutes. To construct and interpret their spectral energy distribution (SED), simultaneous broad-band observations are mandatory. Up to now, the number of objects studied during such campaigns is very limited and biased towards high flux states.Aims. We present the results of a dedicated multi-wavelength study of the high-frequency peaked BL Lacertae (HBL) object and known TeV emitter 1ES 2344+514 by means of a pre-organised campaign.Methods. The observations were conducted during simultaneous visibility windows of MAGIC and AGILE in late 2008. The measurements were complemented by Mets hovi, RATAN-600, KVA+Tuorla, Swift and VLBA pointings. Additional coverage was provided by the ongoing long-term F-GAMMA and MOJAVE programs, the OVRO 40-m and CrAO telescopes as well as the Fermi satellite. The obtained SEDs are modelled using a one-zone as well as a self-consistent two-zone synchrotron self-Compton model.Results. 1ES 2344+514 was found at very low flux states in both X-rays and very high energy gamma rays. Variability was detected in the low frequency radio and X-ray bands only, where for the latter a small flare was observed. The X-ray flare was possibly caused by shock acceleration characterised by similar cooling and acceleration time scales. MOJAVE VLBA monitoring reveals a static jet whose components are stable over time scales of eleven years, contrary to previous findings. There appears to be no significant correlation between the 15 GHz and R-band monitoring light curves. The observations presented here constitute the first multi-wavelength campaign on 1ES 2344+514 from radio to VHE energies and one of the few simultaneous SEDs during low activity states. The quasi-simultaneous Fermi-LAT data poses some challenges for SED modelling, but in general the SEDs are described well by both applied models. The resulting parameters are typical for TeV emitting HBLs. Consequently it remains unclear whether a so-called quiescent state was found in this campaign.
Keywords: galaxies: active; BL Lacertae objects: individual: 1ES 2344+514; gamma rays: galaxies; X-rays: individuals: 1ES 2344+514; radiation mechanisms: non-thermal

The soft state of Cygnus X-1 observed with nustar: A variable corona and a stable inner disk - Walton, D. J.; Tomsick, J. A.; Madsen, K. K.; Grinberg, V.; Barret, D.; Boggs, S. E.; Christensen, F. E.; Clavel, Maica; Craig, W. W.; Fabian, A. C.; Fuerst, F.; Hailey, C. J.; et al. (Astrophysical Journal, 2016)
We present a multi-epoch hard X-ray analysis of Cygnus X-1 in its soft state based on four observations with the Nuclear Spectroscopic Telescope Array (NuSTAR). Despite the basic similarity of the observed spectra, there is clear spectral variability between epochs. To investigate this variability, we construct a model incorporating both the standard disk-corona continuum and relativistic reflection from the accretion disk, based on prior work on Cygnus X-1, and apply this model to each epoch independently. We find excellent consistency for the black hole spin and the iron abundance of the accretion disk, which are expected to remain constant on observational timescales. In particular, we confirm that Cygnus X-1 hosts a rapidly rotating black hole, 0.93 a 0.96, in broad agreement with the majority of prior studies of the relativistic disk reflection and constraints on the spin obtained through studies of the thermal accretion disk continuum. Our work also confirms the apparent misalignment between the inner disk and the orbital plane of the binary system reported previously, finding the magnitude of this warp to be ∼10°-15°. This level of misalignment does not significantly change (and may even improve) the agreement between our reflection results and the thermal continuum results regarding the black hole spin. The spectral variability observed by NuSTAR is dominated by the primary continuum, implying variability in the temperature of the scattering electron plasma. Finally, we consistently observe absorption from ionized iron at ∼6.7 keV, which varies in strength as a function of orbital phase in a manner consistent with the absorbing material being an ionized phase of the focused stellar wind from the supergiant companion star.
Keywords: Black hole physics; X-rays: Binaries; X-rays: Individual (Cygnus X-1)

The spectral-timing analysis of Cygnus X-1 with Insight-HXMT - Zhou, M.; Grinberg,; Bu, Q-C; Santangelo, A.; Cangemi, F.; Diez, C. M.; König, Ole; Ji, Long; Nowak, M. A.; Pottschmidt, K.; Rodriguez, J.; Wilms, Jörn; et al. (Astronomy & Astrophysics, 2022)
Cygnus X-1, as the first discovered black hole binary, is a key source for understanding the mechanisms of state transitions and the scenarios of accretion in extreme gravity fields. We present a spectral-timing analysis of observations taken with the Insight-Hard X-ray Modulation Telescope (HXMT) mission, focusing on the spectral-state-dependent timing properties in the broad energy range of 1-150 keV, thus extending previous studies based on Rossi X-ray Timing Explorer (RXTE) to both lower and higher energies. Our main results are the following: (a) We successfully use a simple empirical model to fit all spectra, confirming that the reflection component is stronger in the soft state than in the hard state. (b) The evolution of the total fractional root mean square (rms) depends on the selected energy band and the spectral shape, which is a direct result of the evolution of the power spectral densities (PSDs). (c) In the hard/intermediate state, we see clear short-term variability features and a positive correlation between the central frequencies of the variability components and the soft photon index Gamma(1), which we also see at energies above 15 keV. In the soft state, the power spectrum is instead dominated by red noise. These behaviors can be traced to at least 90 keV. (d) Finally, the coherence and the phase-lag spectra show different behaviors, depending on the different spectral shapes.
CRIS-Team WoS Importer:2022-11-11

The spin measurement of the black hole in 4U 1543-47 constrained with the X-ray reflected emission - Dong, Yanting; Garcia, Javier; Steiner, James F.; Gou, Lijun (Monthly Notices of the Royal Astronomical Society, 2020)
4U 1543-47 is a low-mass X-ray binary that harbours a stellar-mass black hole located in our Milky Way galaxy. In this paper, we revisit seven data sets that were in the Steep Power Law state of the 2002 outburst. The spectra were observed by the Rossi X-ray Timing Explorer. We have carefully modelled the X-ray reflection spectra and made a joint-fit to these spectra with relxill for the reflected emission.We found a moderate black hole spin, which is 0.67+0.15 -0.08 at 90 per cent statistical confidence. Negative and low spins (<0.5) at more than 99 per cent statistical confidence are ruled out. In addition, our results indicate that the model requires a supersolar iron abundance: 5.05+1.21-0.26, and the inclination angle of the inner disc is 36.3+5.3-3.4 deg. This inclination angle is appreciably larger than the binary orbital inclination angle ( 21 deg); this difference is possibly a systematic artefact of the artificially low density employed in the reflection model for this X-ray binary system.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Accretion; accretion discs; Stars: individual: IL Lupi; 4U 1543-47; X-rays: binaries

The starburst galaxy NGC 253 revisited by H.E.S.S. and Fermi-LAT - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Arrieta, M.; Backes, Michael; Barnard, Monica; Becherini, Y.; Tjus, J. Becker; et al. (Astronomy & Astrophysics, 2018)
Context. NGC 253 is one of only two starburst galaxies found to emit gamma-rays from hundreds of MeV to multi-TeV energies. Accurate measurements of the very-high-energy (VHE; E> 100 GeV) and high-energy (HE; E > 60 MeV) spectra are crucial to study the underlying particle accelerators, probe the dominant emission mechanism(s) and to study cosmic-ray interaction and transport.
CRIS-Team WoS Importer:2020-01-15
Keywords: Astroparticle physics; Galaxies: starburst; Gamma rays: galaxies

The subdwarf B star SB 290-A fast rotator on the extreme horizontal branch - Geier, Stephan; Heber, Ulrich; Heuser, Christian; Classen, Lew; O'Toole, S. J.; Edelmann, Heinz (Astronomy & Astrophysics, 2013)
Hot subdwarf B stars (sdBs) are evolved core helium-burning stars with very thin hydrogen envelopes. To form an sdB, the progenitor has to lose almost all of its hydrogen envelope right at the tip of the red giant branch. In close binary systems, mass transfer to the companion provides the extraordinary mass loss required for their formation. However, apparently single sdBs exist as well, and their formation has been unclear for decades. The merger of helium white dwarfs leading to an ignition of core helium-burning or the merger of a helium core and a low-mass star during the common envelope phase have been proposed. Here we report the discovery of SB 290 as the first apparently single, fast-rotating sdB star located on the extreme horizontal branch, indicating that those stars may form from mergers. © 2013 ESO.
CRIS-Team Scopus Importer:2020-12-21
Keywords: Binaries: spectroscopic; Stars: rotation; Subdwarfs

The supernova remnant population of the Small Magellanic Cloud - Maggi, Pierre; Filipovic, Miroslav D.; Vukotic, Branislav; Ballet, Jean; Haberl, Frank; Maitra, Chandreyee; Kavanagh, Patrick; Sasaki, Manami; Stupar, Milorad (Astronomy & Astrophysics, 2019)
Aims. We present a comprehensive study on the supernova remnant (SNR) population of the Small Magellanic Cloud (SMC). We measured multiwavelength properties of the SMC SNRs and compare them to those of the Large Magellanic Cloud (LMC) population.
CRIS-Team WoS Importer:2019-12-10

The supernova remnant W49B as seen with HESS and Fermi-LAT - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Andersson, T.; Anguener, O.; Arrieta, M.; Aubert, P.; Backes, Michael; Balzer, A.; Barnard, Monica; et al. (Astronomy & Astrophysics, 2018)
The supernova remnant (SNR) W49B originated from a core-collapse supernova that occurred between one and four thousand years ago, and subsequently evolved into a mixed-morphology remnant, which is interacting with molecular clouds (MC). Gamma-ray observations of SNR-MC associations are a powerful tool to constrain the origin of Galactic cosmic rays, as they can probe the acceleration of hadrons through their interaction with the surrounding medium and subsequent emission of non-thermal photons. We report the detection of a gamma-ray source coincident with W49B at very high energies (VHE; E > 100 GeV) with the H.E.S.S. Cherenkov telescopes together with a study of the source with five years of Fermi-LAT high-energy gamma-ray (0.06-300 GeV) data. The smoothly connected, combined source spectrum, measured from 60 MeV to multi-TeV energies, shows two significant spectral breaks at 304 +/- 20 MeV and 8.4(-2.5)(+2.5) GeV; the latter is constrained by the joint fit from the two instruments. The detected spectral features are similar to those observed in several other SNR-MC associations and are found to be indicative of gamma-ray emission produced through neutral-pion decay.
Keywords: gamma rays: general; ISM: supernova remnants; ISM: clouds

The SUrvey for Pulsars and Extragalactic Radio Bursts - II. New FRB discoveries and their follow-up - Bhandari, S.; Keane, E. F.; Barr, E. D.; Jameson, A.; Petroff, E.; Johnston, Simon; Bailes, Matthew; Bhat, N. D. R.; Burgay, M.; Burke-Spolaor, S.; Caleb, M.; Eatough, R. P.; et al. (Monthly Notices of the Royal Astronomical Society, 2018)
We report the discovery of four Fast Radio Bursts (FRBs) in the ongoing SUrvey for Pulsars and Extragalactic Radio Bursts at the Parkes Radio Telescope: FRBs 150610, 151206, 151230 and 160102. Our real-time discoveries have enabled us to conduct extensive, rapid multimessenger follow-up at 12 major facilities sensitive to radio, optical, X-ray, gamma-ray photons and neutrinos on time-scales ranging from an hour to a few months post-burst. No counterparts to the FRBs were found and we provide upper limits on afterglow luminosities. None of the FRBs were seen to repeat. Formal fits to all FRBs show hints of scattering while their intrinsic widths are unresolved in time. FRB 151206 is at low Galactic latitude, FRB 151230 shows a sharp spectral cut-off, and FRB 160102 has the highest dispersion measure (DM = 2596.1 +/- 0.3 pc cm(-3)) detected to date. Three of the FRBs have high dispersion measures (DM > 1500 pc cm(-3)), favouring a scenario where the DMis dominated by contributions from the intergalactic medium. The slope of the Parkes FRB source counts distribution with fluences > 2 Jy ms is alpha = - 2.2(-1.2)(+0.6) and still consistent with a Euclidean distribution (alpha = -3/2). We also find that the all-sky rate is 1.7(-0.9)(+1.5) x 10(3)FRBs/(4 pi sr)/day above similar to 2 Jy ms and there is currently no strong evidence for a latitude- dependent FRB sky rate.
Keywords: radiation mechanisms: general; methods: data analysis; methods: observational; surveys; intergalactic medium; radio continuum: general

The TANAMI Multiwavelength Program: Dynamic spectral energy distributions of southern blazars - Krauß, Felicia; Wilms, Jörn; Kadler, Matthias; Ojha, R.; Schulz, Robert; Truestedt, J.; Edwards, P. G.; Stevens, J.; Ros, Eduardo; Baumgartner, W.; Beuchert, Tobias; Blanchard, J.; et al. (Astronomy & Astrophysics, 2016)
Context. Simultaneous broadband spectral and temporal studies of blazars are an important tool for investigating active galactic nuclei (AGN) jet physics. Aims. We study the spectral evolution between quiescent and flaring periods of 22 radio-loud AGN through multiepoch, quasi-simultaneous broadband spectra. For many of these sources these are the first broadband studies. Methods. We use a Bayesian block analysis of Fermi/LAT light curves to determine time ranges of constant flux for constructing quasi-simultaneous spectral energy distributions (SEDs). The shapes of the resulting 81 SEDs are described by two logarithmic parabolas and a blackbody spectrum where needed. Results. The peak frequencies and luminosities agree well with the blazar sequence for low states with higher luminosity implying lower peak frequencies. This is not true for sources in high states. The γ-ray photon index in Fermi/LAT correlates with the synchrotron peak frequency in low and intermediate states. No correlation is present in high states. The black hole mass cannot be determined from the SEDs. Surprisingly, the thermal excess often found in FSRQs at optical/UV wavelengths can be described by blackbody emission and not an accretion disk spectrum. Conclusions. The so-called harder-when-brighter trend, typically seen in X-ray spectra of flaring blazars, is visible in the blazar sequence. Our results for low and intermediate states, as well as the Compton dominance, are in agreement with previous results. Black hole mass estimates using recently published parameters are in agreement with some of the more direct measurements. For two sources, estimates disagree by more than four orders of magnitude, possibly owing to boosting effects. The shapes of the thermal excess seen predominantly in flat spectrum radio quasars are inconsistent with a direct accretion disk origin.
Keywords: BL Lacertae objects: general; Galaxies: active; Quasars: general; Relativistic processes

The Tidal Disruption Event AT2021ehb: Evidence of Relativistic Disk Reflection, and Rapid Evolution of the Disk-Corona System - Yao, Yuhan; Lu, Wenbin; Guolo, Muryel; Pasham, Dheeraj R.; Gezari, Suvi; Gilfanov, Marat; Gendreau, Keith C.; Harrison, Fiona; Cenko, S. Bradley; Kulkarni, S. R.; Miller, Jon M.; Walton, Dominic J.; et al. (Astrophysical Journal, 2022)
We present X-ray, UV, optical, and radio observations of the nearby (approximate to 78 Mpc) tidal disruption event AT2021ehb/ZTF21aanxhjv during its first 430 days of evolution. AT2021ehb occurs in the nucleus of a galaxy hosting a approximate to 10(7) M-circle dot black hole (M-BH inferred from host galaxy scaling relations). High-cadence Swift and Neutron Star Interior Composition Explorer (NICER) monitoring reveals a delayed X-ray brightening. The spectrum first undergoes a gradual soft -> hard transition and then suddenly turns soft again within 3 days at delta t approximate to 272 days during which the X-ray flux drops by a factor of 10. In the joint NICER+NuSTAR observation (delta t= 264 days, harder state), we observe a prominent nonthermal component up to 30 keV and an extremely broad emission line in the iron K band. The bolometric luminosity of AT2021ehb reaches a maximum of 6.0(-3.8)(+10.4)%L(Edd )when the X-ray spectrum is the hardest. During the dramatic X-ray evolution, no radio emission is detected, the UV/optical luminosity stays relatively constant, and the optical spectra are featureless. We propose the following interpretations: (i) the soft -> hard transition may be caused by the gradual formation of a magnetically dominated corona; (ii) hard X-ray photons escape from the system along solid angles with low scattering optical depth (similar to a few) whereas the UV/optical emission is likely generated by reprocessing materials with much larger column density-the system is highly aspherical; and (iii) the abrupt X-ray flux drop may be triggered by the thermal-viscous instability in the inner accretion flow, leading to a much thinner disk.
CRIS-Team WoS Importer:2022-09-30

THE TRANSIENT ACCRETING X-RAY PULSAR XTE J1946+274: STABILITY OF X-RAY PROPERTIES AT LOW FLUX AND UPDATED ORBITAL SOLUTION - Marcu-Cheatham, Diana M.; Pottschmidt, Katja; Kühnel, Matthias; Müller, Sebastian; Falkner, Sebastian; Caballero, Isabel; Finger, Mark H.; Jenke, Peter J.; Wilson-Hodge, Colleen A.; Fuerst, Felix; Grinberg, Victoria; Hemphill, Paul B.; et al. (Astrophysical Journal, 2015)
We present a timing and spectral analysis of the X-ray pulsar XTE J1946+274 observed with Suzaku during an outburst decline in 2010 October and compare with previous results. XTE J1946+274 is a transient X-ray binary consisting of a Be-type star and a neutron star with a 15.75 s pulse period in a 172 days orbit with 2-3 outbursts per orbit during phases of activity. We improve the orbital solution using data from multiple instruments. The X-ray spectrum can be described by an absorbed Fermi-Dirac cut-off power-law model along with a narrow Fe K alpha line at 6.4 keV and a weak Cyclotron Resonance Scattering Feature (CRSF) at similar to 35 keV. The Suzaku data are consistent with the previously observed continuum flux versus iron line flux correlation expected from fluorescence emission along the line of sight. However, the observed iron line flux is slightly higher, indicating the possibility of a higher iron abundance or the presence of non-uniform material. We argue that the source most likely has only been observed in the subcritical (non-radiation dominated) state since its pulse profile is stable over all observed luminosities and the energy of the CRSF is approximately the same at the highest (similar to 5 x 10(37) erg s(-1)) and lowest (similar to 5. x 10(36) erg s(-1)) observed 3-60 keV luminosities.
Keywords: accretion; accretion disks; pulsars: individual (XTE J1946+274); X-rays: binaries

The unaltered pulsar: GRO J1750-27, a supercritical X-ray neutron star that does not blink an eye - Malacaria, C.; Ducci, L.; Falanga, M.; Altamirano, D.; Bozzo, E.; Guillot, S.; Jaisawal, G. K.; Kretschmar, P.; Ng, M.; Pradhan, P.; Rothschild, R.; Sanna, A.; et al. (Astronomy & Astrophysics, 2023)
When accreting X-ray pulsars (XRPs) undergo bright X-ray outbursts, their luminosity-dependent spectral and timing features can be analyzed in detail. The XRP GRO J1750-27 recently underwent one such episode, during which it was observed with NuSTAR and monitored with NICER. Such a data set is rarely available, as it samples the outburst over more than 1 month at a luminosity that is always exceeding E 5 ×1037-erg s-1. This value is larger than the typical critical luminosity value, where a radiative shock is formed above the surface of the neutron star. Our data analysis of the joint spectra returns a highly (NH- -(5- -8)- Ã -1022-cm-2) absorbed spectrum showing a Kα iron line, a soft blackbody component likely originating from the inner edge of the accretion disk, and confirms the discovery of one of the deepest cyclotron lines ever observed, at a centroid energy of E 44-keV corresponding to a magnetic field strength of 4.7 ×1012-G. This value is independently supported by the best-fit physical model for spectral formation in accreting XRPs which, in agreement with recent findings, favors a distance of 14 kpc and also reflects a bulk-Comptonization-dominated accretion flow. Contrary to theoretical expectations and observational evidence from other similar sources, the pulse profiles as observed by NICER remain remarkably steady through the outburst rise, peak and decay. The NICER spectrum, including the iron Kα line best-fit parameters, also remain almost unchanged at all probed outburst stages, similar to the pulsed fraction behavior. We argue that all these phenomena are linked and interpret them as resulting from a saturation effect of the emission from the accretion column, which occurs in the high-luminosity regime.
CRIS-Team Scopus Importer:2023-01-13
Keywords: Accretion; accretion disks; Magnetic fields; Pulsars: individual: GRO J1750-27; Stars: neutron; X-rays: binaries; X-rays: general

The unusual multiwavelength properties of the gamma-ray source PMN J1603-4904 - Müller, Cornelia; Kadler, Matthias; Ojha, R.; Boeck, M.; Krauß, Felicia; Taylor, G. B.; Wilms, Jörn; Blanchard, J.; Carpenter, B.; Dauser, Thomas; Dutka, M.; Edwards, P. G.; et al. (Astronomy & Astrophysics, 2014)
Context. We investigate the nature and classification of PMN J1603-4904, a bright radio source close to the Galactic plane, which is associated with one of the brightest hard-spectrum gamma-ray sources detected by Fermi/LAT. It has previously been classified as a low-peaked BL Lac object based on its broadband emission and the absence of optical emission lines. Optical measurements, however, suffer strongly from extinction and the absence of pronounced short-time gamma-ray variability over years of monitoring is unusual for a blazar.Aims. In this paper, we are combining new and archival multiwavelength data of PMN J1603-4904 in order to reconsider the classification and nature of this unusual gamma-ray source.Methods. For the first time, we study the radio morphology of PMN J1603-4904 at 8.4 GHz and 22.3 GHz, and its spectral properties on milliarcsecond scales, based on VLBI observations from the TANAMI program. We combine the resulting images with multiwavelength data in the radio, IR, optical/UV, X-ray, and gamma-ray regimes.Results. PMN J1603-4904 shows a symmetric brightness distribution at 8.4 GHz on milliarcsecond scales, with the brightest, and most compact component in the center of the emission region. The morphology is reminiscent of a compact symmetric object (CSO). Such objects, thought to be young radio galaxies, have been predicted to produce gamma-ray emission but have not been detected as a class by the Fermi gamma-ray telescope so far. Sparse (u, v)-coverage at 22.3 GHz prevents an unambiguous modeling of the source morphology at this higher frequency. Moreover, infrared measurements reveal an excess in the spectral energy distribution (SED), which can be modeled with a blackbody with a temperature of about 1600 K, and which is usually not present in blazar SEDs.Conclusions. The TANAMI VLBI data and the shape of the broadband SED challenge the current blazar classification of one of the brightest gamma-ray sources in the sky. PMN J1603-4904 seems to be either a highly peculiar BL Lac object or a misaligned jet source. In the latter case, the intriguing VLBI structure opens room for a possible classification of PMN J1603-4904 as a gamma-ray bright CSO.
Keywords: galaxies: active; galaxies: individual: PMNJ1603-4904; radio continuum: general; gamma rays: galaxies; techniques: interferometric; X-rays: galaxies

The UV-Excess survey of the northern Galactic plane - Groot, Paul J.; Verbeek, Kars; Greimel, Robert; Irwin, Mike; Gonzalez-Solares, Eduardo; Gaensicke, Boris T.; De Groot, Eelco; Drew, Janet; Augusteijn, Thomas; Aungwerojwit, Amornrat; Barlow, Mike; Barros, Susana; et al. (Monthly Notices of the Royal Astronomical Society, 2009)
The UV-Excess survey of the northern Galactic plane images a 10 degrees x 185 degrees wide band, centred on the Galactic equator using the 2.5-m Isaac Newton Telescope in four bands (U, g, r, He 15875) down to similar to 21-22 mag (similar to 20 in He 15875). The setup and data reduction procedures are described. Simulations of the colours of main-sequence stars, giant, supergiants, DA and DB white dwarfs and AM Canum Venaticorum stars are made, including the effects of reddening. A first look at the data of the survey (currently 30 per cent complete) is given.
Keywords: surveys; stars: general; ISM: general; Galaxy: disc; Galaxy: stellar content; Galaxy: structure

The warm-hot circumgalactic medium of the Milky Way as seen by eROSITA - Locatelli, N.; Ponti, G.; Zheng, X.; Merloni, A.; Becker, W.; Comparat, J.; Dennerl, K.; Freyberg, M. J.; Sasaki, Manami; Yeung, M. C.H. (Astronomy & Astrophysics, 2024)
The first all-sky maps of the diffuse emission of high ionization lines observed in X-rays by SRG/eROSITA provide an excellent probe for the study of the warm-hot phase (T ∼ 106 K) of the circumgalactic medium (CGM) of the Milky Way. In this work, we analyze the O VIII line detected in the first eROSITA All-Sky Survey data (eRASS1). We fit a sky map made in a narrow energy bin around this line with physical emission models embedded in a 3D geometry in order to constrain the density distribution of the warm-hot gas around the Galaxy, with a focus on mid and high (absolute) Galactic latitudes. By masking out the eROSITA bubbles and other bright, extended foreground sources, we find that an oblate geometry of the warm-hot gas (T ≡ 0.15−0.17 keV), flattened around the Galactic disk with scale height zh ∼ 1−3 kpc, best describes the eRASS1 O VIII map, with most of the observed emission shown as being produced within a few kiloparsecs from the Sun. The additional presence of a large-scale warm-hot spherical halo, while providing a minor contribution to the X-ray emission, accounts for the high O VII absorption column densities detected with XMM-Newton as well as most of the baryon budget of the CGM of the Milky Way. To date, the eROSITA data carry the greatest amount of information and detail of the O VIII CGM intensities, allowing for a significant reduction in the statistical uncertainties of the inferred physical parameters.
CRIS-Team Scopus Importer:2024-02-16
Keywords: Galaxy: general; X-rays: diffuse background

The Wide-Field Imager for IXO: Status and future activities - Strueder, Lothar; Aschauer, Florian; Bautz, Mark; Bombelli, Luca; Burrows, David; Fiorini, Carlo; Fraser, George; Herrmann, Sven; Kendziorra, Eckhard; Kuster, Markus; Lauf, Thomas; Lechner, Peter; et al. (2010)
The Wide Field Imager (WFI) of the International X-ray Observatory (IXO) is an X-ray imaging spectrometer based on a large monolithic DePFET (Depleted P-channel Field Effect Transistor) Active Pixel Sensor. Filling an area of 10 x 10 cm(2) with a format of 1024 x 1024 pixels it will cover a field of view of 18 arcmin. The pixel size of 100 x 100 mu m(2) corresponds to a fivefold oversampling of the telescope's expected 5 arcsec point spread function. The WFI's basic DePFET structure combines the functionalities of sensor and integrated amplifier with nearly Fano-limited energy resolution and high efficiency from 100 eV to 15 keV. The development of dedicated control and amplifier ASICs allows for high frame rates up to 1 kHz and flexible readout modes. Results obtained with representative prototypes with a format of 256 x 256 pixels are presented.
Keywords: International X-ray Observatory; IXO; Wide Field Imager; WFI; X-ray Astronomy; X-ray Spectroscopy; X-ray Imaging; DePFET; Active Pixel Sensor

The Wide Field Imager Instrument for Athena - Meidinger, Norbert; Nandra, Kirpal; Plattner, Markus; Porro, Matteo; Rau, Arne; Santangelo, Andrea; Tenzer, Chris; Wilms, Jörn (2014)
The "Hot and Energetic Universe" has been selected as the science theme for ESA's L2 mission, scheduled for launch in 2028. The proposed Athena X-ray observatory provides the necessary capabilities to achieve the ambitious goals of the science theme. The X-ray mirrors are based on silicon pore optics technology and will have a 12 m focal length. Two complementary camera systems are foreseen which can be moved in and out of the focal plane by an interchange mechanism. These instruments are the actively shielded micro-calorimeter spectrometer X-IFU and the Wide Field Imager (WFI).The WFI will combine an unprecedented survey power through its large field of view of 40 arcmin with a high count-rate capability (approx. 1 Crab). It permits a state-of-the-art energy resolution in the energy band of 0.1 keV to 15 keV during the entire mission lifetime (e.g. FWHM <= 150 eV at 6 keV). This performance is accomplished by a set of DEPFET active pixel sensor matrices with a pixel size matching the angular resolution of 5 arcsec (on-axis) of the mirror system. Each DEPFET pixel is a combined detector-amplifier structure with a MOSFET integrated onto a fully depleted 450 micron thick silicon bulk. The signal electrons generated by an X-ray photon are collected in a so-called internal gate below the transistor channel. The resulting change of the conductivity of the transistor channel is proportional to the number of electrons and thus a measure for the photon energy. DEPFETs have already been developed for the "Mercury Imaging X-ray Spectrometer" on-board of ESA's BepiColombo mission. For Athena we develop enhanced sensors with integrated electronic shutter and an additional analog storage area in each pixel. These features improve the peak-to-background ratio of the spectra and minimize dead time. The sensor will be read out with a new, fast, low-noise multi-channel analog signal processor with integrated sequencer and serial analog output. The architecture of sensor and readout ASIC allows readout in full frame mode and window mode as well by addressing selectively arbitrary sub-areas of the sensor allowing time resolution in the order of 10 mu s. The further detector electronics has mainly the following tasks: digitization, pre-processing and telemetry of event data as well as supply and control of the detector system. Although the sensor will already be equipped with an on-chip light blocking filter, a filter wheel is necessary to provide an additional external filter, an on-board calibration source, an open position for outgassing, and a closed position for protection of the sensor. The sensor concept provides high quantum efficiency over the entire energy band and we intend to keep the instrumental background as low as possible by designing a graded Z-shield around the sensor.All these properties make the WFI a very powerful survey instrument, significantly surpassing currently existing observatories and in addition allow high-time resolution of the brightest X-ray sources with low pile-up and high efficiency. This manuscript will summarize the current instrument concept and design, the status of the technology development, and the envisaged baseline performance.
Keywords: Active pixel sensor; Athena; DEPFET; focal plane camera; hot and energetic universe; WFI; X-ray detector

The Wide Field Imager of the International X-ray Observatory - Stefanescu, A.; Bautz, M. W.; Burrows, D. N.; Bombelli, L.; Fiorini, C.; Fraser, G.; Heinzinger, K.; Herrmann, S.; Kuster, Markus; Lauf, T.; Lechner, P.; Lutz, G.; et al. (ELSEVIER SCIENCE BV, 2010)
The International X-ray Observatory (IXO) will be a Joint X-ray observatory mission by ESA NASA and JAXA It will have a large effective area (3 m(2) at 1 25 key) grazing incidence mirror system with good angular resolution (5 arcsec at 0 1-10 keV) and will feature a comprehensive suite of scientific instruments an X-ray Microcalorimeter Spectrometer a High Time Resolution Spectrometer an X-ray Polarimeter an X-ray Grating Spectrometer a Hard X-ray Imager and a Wide-Field ImagerThe Wide Field Imager (WFI) has a field-of-view of 18 ft x 18 ft It will be sensitive between 01 and 15 keV offer the full angular resolution of the mirrors and good energy resolution The WFI will be Implemented as a 6 in wafer-scale monolithical array of 1024 x 1024 pixels 01 100 x 100 mu m(2) size The DEpleted P-channel Field-Effect Transistors (DEPFET) forming the individual pixels are devices combining the functionalities of both detector and amplifier Signal electrons are collected in a potential well below the transistor s gate modulating the transistor current Even when the device is powered off the signal charge is collected and kept in the potential well below the gate until it is explicitly cleared This makes flexible and fast readout modes possible (C) 2010 Elsevier B V All rights reserved
Keywords: IXO; X ray astronomy; DEPFET; Active Pixel Sensor; Imaging; Spectroscopy

The XMM-Newton view of the crab - Kirsch, Marcus G F; Schönherr, Gabriele; Kendziorra, Eckhard; Freyberg, Michael; Martin, Michael; Wilms, Jörn; Mukerjee, K.; Breitfellner, Michael; Smith, M. J. S.; Staubert, Rüdiger (Astronomy & Astrophysics, 2006)
Aims. We discuss the current X-ray view of the Crab Nebula and Pulsar, summarising our analysis of observations of the source with the EPIC-pn camera on board the XMM-Newton observatory. Different modes of EPIC-pn were combined in order to yield a complete scenario of the spectral properties of the Crab resolved in space and time ( pulse phase). In addition we give a description of the special EPIC-pn Burst mode and guidance for data reduction in that mode.Methods. We analysed spectra for the nebula and pulsar separately in the 0.6-12.0 keV energy band. All data were processed with the SAS 6.0.0 XMM-Newton Scientific Analysis System package; models were fitted to the data with XSPEC 11. The high time resolution of EPIC-pn in its Burst mode (7 mu s) was used for a phase resolved analysis of the pulsar spectrum, after determination of the period with epoch folding techniques. Data from the Small Window mode were processed and corrected for pile-up allowing for spectroscopy simultaneously resolved in space and time.Results. The spatial variation of the spectrum over the entire region of the Crab shows a gradual spectral softening from the inner pulsar region to the outer nebula region with a variation in photon index, Gamma, from 2.0 to 2.4. Pulse phase resolved spectroscopy of the Crab Pulsar reveals a phase dependent modulation of the photon index in form of a significant hardening of the spectrum in the inter-peak phase from Gamma = 1.7 during the pulse peak to Gamma = 1.5.
Keywords: instrumentation : detectors; stars : neutron; stars : pulsars : individual : PSR 0531+21; X-rays : stars

The X-ray disc/wind degeneracy in AGN - Parker, M. L.; Matzeu, G. A.; Matthews, J. H.; Middleton, M. J.; Dauser, Thomas; Jiang, J.; Joyce, Amy (Monthly Notices of the Royal Astronomical Society, 2022)
Relativistic Fe K emission lines from accretion discs and from disc winds encode key information about black holes, and their accretion and feedback mechanisms. We show that these two processes can in principle produce indistinguishable line profiles, such that they cannot be disentangled spectrally. We argue that it is likely that in many cases both processes contribute to the net line profile, and their relative contributions cannot be constrained purely by Fe K spectroscopy. In almost all studies of Fe K emission to date, a single process (either disc reflection or wind Compton scattering) is assumed to dominate the total line profile. We demonstrate that fitting a single process emission model (pure reflection or pure wind) to a hybrid line profile results in large systematic biases in the estimates of key parameters, such as mass outflow rate and spin. We discuss various strategies to mitigate this effect, such as including high-energy data covering the Compton hump, and the implications for future X-ray missions.
CRIS-Team WoS Importer:2022-05-06

The X-ray Integral Field Unit (X-IFU) for Athena - Ravera, Laurent; Barret, Didier; Den Herder, Jan Willem; Piro, Luigi; Cledassou, Rodolphe; Pointecouteau, Etienne; Peille, Philippe; Pajot, Francois; Arnaud, Monique; Pigot, Claude; Duband, Lionel; Cara, Christophe; et al. (2014)
Athena is designed to implement the Hot and Energetic Universe science theme selected by the European Space Agency for the second large mission of its Cosmic Vision program. The Athena science payload consists of a large aperture high angular resolution X-ray optics (2 m(2) at 1 keV) and twelve meters away, two interchangeable focal plane instruments: the X-ray Integral Field Unit (X-IFU) and the Wide Field Imager. The X-IFU is a cryogenic X-ray spectrometer, based on a large array of Transition Edge Sensors (TES), offering 2.5 eV spectral resolution, with similar to 5" pixels, over a field of view of 5' in diameter. In this paper, we present the X-IFU detector and readout electronics principles, some elements of the current design for the focal plane assembly and the cooling chain. We describe the current performance estimates, in terms of spectral resolution, effective area, particle background rejection and count rate capability. Finally, we emphasize on the technology developments necessary to meet the demanding requirements of the X-IFU, both for the sensor, readout electronics and cooling chain.
Keywords: X-ray; missions; micro-calorimeter; Athena

The X-Ray Pulsar XTE J1858+034 Observed with NuSTAR and Fermi/GBM: Spectral and Timing Characterization plus a Cyclotron Line - Malacaria, C.; Kretschmar, P.; Madsen, K. K.; Wilson-Hodge, C. A.; Coley, Joel B.; Jenke, P.; Lutovinov, Alexander A.; Pottschmidt, Katja; Tsygankov, Sergey S.; Wilms, Jörn (Astrophysical Journal, 2021)
Accreting X-ray pulsars (XRPs) undergo luminous X-ray outbursts during which the spectral and timing behavior of the neutron star can be studied in detail. We analyze a NuSTAR observation of the XRP XTE J1858+034 during its outburst in 2019. The spectrum is fit with a phenomenological, a semiempirical, and a physical spectral model. A candidate cyclotron line is found at 48 keV, implying a magnetic field of 5.4 x 10(12) G at the site of emission. This is also supported by the physical best-fit model. We propose an orbital period of about 81 days based on the visual inspection of the X-ray outburst recurrence time. Based on Fermi/GBM data, the standard disk accretion-torque theory allowed us to infer a distance of 10.9 1.0 kpc. Pulse profiles are single-peaked and show a pulsed fraction that is strongly energy-dependent at least up to 40 keV.
CRIS-Team WoS Importer:2021-03-26

The X-ray spectral-timing contribution of the stellar wind in the hard state of Cyg X-1 - Lai, E.; De Marco, B.; Zdziarski, A. A.; Belloni, T. M.; Mondal, S.; Uttley, P.; Grinberg,; Wilms, Jörn; Rozanska, A. (Monthly Notices of the Royal Astronomical Society, 2022)
The clumpy stellar wind from the companion star in high-mass X-ray binaries causes variable, partial absorption of the emission from the X-ray source. We studied XMM-Newton observations from a 7.22 d long monitoring campaign, in order to constrain the effects of the stellar wind on the short-time-scale X-ray spectral-timing properties of Cygnus X-1. We find these properties to change significantly in the presence of the wind. In particular, the longest sampled time-scales (corresponding to temporal frequencies of ν ∼0.1-1 Hz) reveal an enhancement of the fractional variability power, while on the shortest sampled time-scales (ν ∼1-10 Hz), the variability is suppressed. In addition, we observe a reduction (by up to a factor of ∼1.8) of the otherwise high coherence between soft and hard band light curves, as well as of the amplitude of the hard X-ray lags intrinsic to the X-ray continuum. The observed increase of low-frequency variability power can be explained in terms of variations of the wind column density as a consequence of motions of the intervening clumps. In this scenario (and assuming a terminal velocity of v∞ = 2400 km s-1), we obtain an estimate of l ∼0.5-1.5 × 10-4R∗ for the average radial size of a clump. On the other hand, we suggest the behaviour at high frequencies to be due to scattering in an optically thicker medium, possibly formed by collision of the stellar wind with the edge of the disc.
CRIS-Team Scopus Importer:2022-04-29
Keywords: black hole physics; stars: winds; outflows; X-rays: binaries; X-rays: individual: Cyg X-1

The XSTAR atomic database - Mendoza, Claudio; Bautista, Manuel A.; Deprince, Jerome; Garcia, Javier; Gatuzz, Efrain; Gorczyca, Thomas W.; Kallman, Timothy R.; Palmeri, Patrick; Quinet, Pascal; Witthoeft, Michael C. (Atoms, 2021)
We describe the atomic database of the XSTAR spectral modeling code, summarizing the systematic upgrades carried out in the past twenty years to enable the modeling of K-lines from chemical elements with atomic number Z ≤ 30 and recent extensions to handle high-density plasmas. Such plasma environments are found, for instance, in the inner region of accretion disks round compact objects (neutron stars and black holes), which emit rich information about the system’s physical properties. Our intention is to offer a reliable modeling tool to take advantage of the outstanding spectral capabilities of the new generation of X-ray space telescopes (e.g., XRISM and ATHENA) to be launched in the coming years. Data curatorial aspects are discussed and an updated list of reference sources is compiled to improve the database provenance metadata. Two XSTAR spin-offs—the ISMabs absorption model and the uaDB database—are also described.
CRIS-Team Scopus Importer:2021-04-09
Keywords: Atomic databases; Atomic processes; High-density plasmas; Line formation; X-rays; XSTAR

Three-dimensional geometry and dust/gas ratios in massive star-forming regions over the entire LMC as revealed by the IRSF/SIRIUS survey - Furuta, Takuya; Kaneda, Hidehiro; Kokusho, Takuma; Nakajima, Yasushi; Fukui, Yasuo; Tsuge, Kisetsu (Publications of the Astronomical Society of Japan, 2022)
We derive the entire dust extinction (A(V)) map for the Large Magellanic Cloud (LMC) estimated from the color excess at near-infrared wavelengths. Using the percentile method we recently adopted to evaluate A(V) distribution along the line of sight, we derive three-dimensional (3D) A(V) maps of the three massive star-forming regions of N44, N79, and N11 based on the IRSF/SIRIUS point source catalog. The 3D A(V) maps are compared with the hydrogen column densities N(H) of three different velocity components where one is of the LMC disk velocity and the other two are of velocities lower than the disk velocity. As a result, we obtain a 3D dust geometry suggesting that gas collision is ongoing between the different velocity components. We also find differences in the timing of the gas collision between the massive star-forming regions, which indicates that the gas collision in N44, N79, and N11 occurred later than that in 30 Doradus. In addition, a difference of a factor of two in A(V)/N(H) is found between the velocity components for N44, while a significant difference is not found for N79 and N11. From the 3D geometry and A(V)/N(H) in each star-forming region, we suggest that the massive star formation in N44 was induced by an external trigger of tidal interaction between the LMC and the Small Magellanic Cloud, while that in N79 and N11 is likely to have been induced by internal triggers such as gas converging from the galactic spiral arm and expansion of a supershell, although the possibility of tidal interaction cannot be ruled out.
CRIS-Team WoS Importer:2022-06-03

Time calibration with atmospheric muon tracks in the ANTARES neutrino telescope - Adrian-Martinez, S.; Albert, A.; Andre, M.; Anton, Gisela; Ardid, M.; Aubert, J. -J.; Baret, B.; Barrios-Marti, Javier; Basa, S.; Bertin, V.; Biagi, Simone; Bogazzi, C.; et al. (Astroparticle Physics, 2016)
The ANTARES experiment consists of an array of photomultipliers distributed along 12 lines and located deep underwater in the Mediterranean Sea. It searches for astrophysical neutrinos collecting the Cherenkov light induced by the charged particles, mainly muons, produced in neutrino interactions around the detector. Since at energies of ∼10 TeV the muon and the incident neutrino are almost collinear, it is possible to use the ANTARES detector as a neutrino telescope and identify a source of neutrinos in the sky starting from a precise reconstruction of the muon trajectory. To get this result, the arrival times of the Cherenkov photons must be accurately measured. A to perform time calibrations with the precision required to have optimal performances of the instrument is described. The reconstructed tracks of the atmospheric muons in the ANTARES detector are used to determine the relative time offsets between photomultipliers. Currently, this method is used to obtain the time calibration constants for photomultipliers on different lines at a precision level of 0.5 ns. It has also been validated for calibrating photomultipliers on the same line, using a system of LEDs and laser light devices.
Keywords: ANTARES; Atmospheric muon tracks; Neutrino Telescopes; Time calibration

Time-dependent search for neutrino emission from X-ray binaries with the ANTARES telescope - Albert, A.; Andre, Michel; Anton, Gisela; Ardid, Miguel; Aubert, J. -J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; Bormuth, R.; et al. (Journal of Cosmology and Astroparticle Physics, 2017)
ANTARES is currently the largest neutrino telescope operating in the Northern Hemisphere, aiming at the detection of high-energy neutrinos from astrophysical sources. Neutrino telescopes constantly monitor at least one complete hemisphere of the sky, and are thus well-suited to detect neutrinos produced in transient astrophysical sources. A time-dependent search has been applied to a list of 33 X-ray binaries undergoing high flaring activities in satellite data (RXTE/ASM, MAXI and Swift/BAT) and during hardness transition states in the 2008-2012 period. The background originating from interactions of charged cosmic rays in the Earth's atmosphere is drastically reduced by requiring a directional and temporal coincidence with astrophysical phenomena. The results of this search are presented together with comparisons between the neutrino flux upper limits and the neutrino flux predictions from astrophysical models. The neutrino flux upper limits resulting from this search limit the jet parameter space for some astrophysical models.
Keywords: neutrino astronomy; X-ray binaries; X-ray telescopes

Time-resolved hadronic particle acceleration in the recurrent nova RS Ophiuchi - Aharonian, F.; Benkhali, F. Ait; Anguener, E. O.; Ashkar, H.; Backes, M.; Baghmanyan, V.; Martins, V. Barbosa; Batzofin, R.; Becherini, Y.; Berge, D.; Bernloehr, K.; Bi, B.; et al. (Science, 2022)
Recurrent novae are repeating thermonuclear explosions in the outer layers of white dwarfs, due to the accretion of fresh material from a binary companion. The shock generated when ejected material slams into the companion star's wind can accelerate particles. We report very-high-energy [VHE: greater than or similar to 100 giga-electron volts] gamma rays from the recurrent nova RS Ophiuchi, up to 1 month after its 2021 outburst, observed using the High Energy Stereoscopic System (H.E.S.S.). The temporal profile of VHE emission is similar to that of lower-energy giga-electron volt emission, indicating a common origin, with a 2-day delay in peak flux. These observations constrain models of time-dependent particle energization, favoring a hadronic emission scenario over the leptonic alternative. Shocks in dense winds provide favorable environments for efficient acceleration of cosmic rays to very high energies.
CRIS-Team WoS Importer:2022-06-03

Time-resolved high-resolution spectroscopy of the pulsating sdB star QQ Vir (PG1325+101) - Telting, J.; Ostensen, R.; Oreiro, R.; Heber, Ulrich; Vuckovic, Maja; Randall, S.; Baran, Andrzej (Astrophysics and Space Science, 2010)
In March 2008 we obtained 2 nights of time-resolved high-resolution spectroscopy with UVES@VLT of the pulsating sdB QQ Vir (PG1325+101), totalling more than 750 spectra. We aim to study in detail the atmospheric response to the pulsations, and to derive observational constraints on the eigenmode of the main pulsation. In this paper we present the first preliminary results.We follow the technique outlined in Telting et al. (Astron. Astrophys. 492:815, 2008) in order to obtain high-quality line-profile variations from phase-folded spectra. From the modelling of such line-profile variations we aim to derive constraints on the pulsational degree a"" and azimuthal number m of the main pulsation mode in this star.To facilitate accurate frequency determination of the pulsations in QQ Vir, and to strengthen the derivation of the degree a"" of the main mode, we organised a photometric campaign around the spectroscopic observations. This photometric campaign will be discussed in a separate contribution (Baran et al. in Astrophys. Space Sci. 2010, this volume).
Keywords: Stellar pulsations; Subdarf B stars; QQ Vir (PG1325+101); Pulsation-mode identification; Time-resolved spectroscopy; Internal stellar structure; Stellar evolution

Time-resolved spectroscopy of the sdBV V338 Serpentis - Ostensen, R. H.; Telting, J. H.; Oreiro, R.; Heber, Ulrich; Heber, Ulrich; De Beck, Elvire; Reed, Michael (Astrophysics and Space Science, 2010)
We obtained 1955 high-resolution spectra of the high-amplitude pulsating subdwarf B star V338 Ser with the FIES spectrograph at the 2.5 m Nordic Optical Telescope covering 4 full nights in May-June 2009. Here we present the first results from phase-folding the data on the main pulsation mode, as revealed by simultaneous B-band photometry obtained with the Mercator 1.25 m and Baker 0.4 m telescopes. We compare the results with a sample line-profile model produced with LTE atmospheres and bruce+kylie.
Keywords: Subdwarfs; Pulsators; Line-profile variations

Toward More Accurate Synthetic Reflection Spectra: Improving the Calculations of Returning Radiation - Mirzaev, Temurbek; Riaz, Shafqat; Abdikamalov, Askar B.; Bambi, Cosimo; Dauser, Thomas; Garcia, Javier A.; Jiang, Jiachen; Liu, Honghui; Shashank, Swarnim (Astrophysical Journal, 2024)
We present a new model to calculate reflection spectra of thin accretion disks in Kerr spacetimes. Our model includes the effect of returning radiation, which is the radiation that is emitted by the disk and returns to the disk because of the strong light bending near a black hole. The major improvement with respect to the existing models is that it calculates the reflection spectrum at every point on the disk by using the actual spectrum of the incident radiation. Assuming a lamppost coronal geometry, we simulate simultaneous observations of NICER and NuSTAR of bright Galactic black holes and we fit the simulated data with the latest version of relxill (modified to read the table of reflionx, which is the nonrelativistic reflection model used in our calculations). We find that relxill with returning radiation cannot fit well the simulated data when the black hole spin parameter is very high and the coronal height and disk’s ionization parameter are low, and some parameters can be significantly overestimated or underestimated. We can find better fits and recover the correct input parameters as the value of the black hole spin parameter decreases and the value of the coronal height increases.
CRIS-Team Scopus Importer:2024-04-19

Toward Precision Tests of General Relativity with Black Hole X-Ray Reflection Spectroscopy - Tripathi, Ashutosh; Nampalliwar, Sourabh; Abdikamalov, Askar B.; Ayzenberg, Dimitry; Bambi, Cosimo; Dauser, Thomas; Garcia, Javier; Marinucci, Andrea (Astrophysical Journal, 2019)
Astrophysical black hole systems are the ideal laboratories for testing Einstein's theory of gravity in the strong field regime. We have recently developed a framework that uses the reflection spectrum of black hole systems to perform precision tests of general relativity by testing the Kerr black hole hypothesis. In this paper, we analyze XMM-Newton and NuSTAR observations of the supermassive black hole in the Seyfert.
CRIS-Team Scopus Importer:2019-06-21
Keywords: accretion; accretion disks; black hole physics; gravitation

Towards a consistent model of the hot quadruple system HD 93206=QZ Carinae - Mayer, P.; Harmanec, P.; Zasche, P.; Broz, M.; Catalan-Hurtado, R.; Barlow, B. N.; Frondorf, W.; Wolf, M.; Drechsel, Horst; Chini, R.; Nasseri, A.; Pigulski, A.; et al. (Astronomy & Astrophysics, 2022)
The hot nine-component system HD 93206, which contains a gravitationally bounded eclipsing Ac1+Ac2 binary (P=5:9987 d) and a spectroscopic Aa1+Aa2 (P=20 :734 d) binary can provide important insights into the origin and evolution of massive stars. Using archival and new spectra, and a rich collection of ground-based and space photometric observations, we carried out a detailed study of this object. We provide a much improved description of both short orbits and a good estimate of the mutual period of both binaries of about 14 500 d (i.e. 40 years). For the first time, we detected weak lines of the fainter component of the 6.0 d eclipsing binary in the optical region of the spectrum, measured their radial velocities, and derived a mass ratio of M-Ac2/M-Ac1 = 1 :29, which is the opposite of what was estimated from the International Ultraviolet explorer (IUE) spectra. We confirm that the eclipsing subsystem Ac is semidetached and is therefore in a phase of large-scale mass transfer between its components. The Roche-lobe filling and spectroscopically brighter component Ac1 is the less massive of the two and is eclipsed in the secondary minimum. We show that the bulk of the H alpha emission, so far believed to be associated with the eclipsing system, moves with the primary O9.7 I component Aa1 of the 20.73 d spectroscopic binary. However, the weak emission in the higher Balmer lines seems to be associated with the accretion disc around component Ac2. We demonstrate that accurate masses and other basic physical properties including the distance of this unique system can be obtained but require a more sophisticated modelling. A first step in this direction is presented in the accompanying Paper II (Broz et al.).
CRIS-Team WoS Importer:2022-11-04

Towards a consistent model of the hot quadruple system HD 93206=QZ Carin ae II. N-body model - Broz, M.; Harmanec, P.; Zasche, P.; Catalan-Hurtado, R.; Barlow, B. N.; Frondorf, W.; Wolf, M.; Drechsel, Horst; Chini, R.; Nasseri, A.; Labadie-Bartz, J.; Christie, G. W.; et al. (Astronomy & Astrophysics, 2022)
Aims. HD 93206 is a massive early-type stellar system composed of components resolved by direct imaging (Ab, Ad, B, C, D) and a compact subsystem (Aa1, Aa2, Ac1, Ac2). Its geometry was already determined on the basis of extensive photometric, spectroscopic, and interferometric observations. However, the fundamental absolute parameters are still not known precisely enough.
CRIS-Team WoS Importer:2022-11-04

Towards a Unified View of Inhomogeneous Stellar Winds in Isolated Supergiant Stars and Supergiant High Mass X-Ray Binaries - Martinez-Nunez, Silvia; Kretschmar, Peter; Bozzo, Enrico; Oskinova, Lidia M.; Puls, Joachim; Sidoli, Lara; Sundqvist, Jon Olof; Blay, Pere; Falanga, Maurizio; Furst, Felix; Gimenez-Garcia, Angel; Kreykenbohm, Ingo; et al. (Space Science Reviews, 2017)
Massive stars, at least similar to 10 times more massive than the Sun, have two key properties that make them the main drivers of evolution of star clusters, galaxies, and the Universe as a whole. On the one hand, the outer layers of massive stars are so hot that they produce most of the ionizing ultraviolet radiation of galaxies; in fact, the first massive stars helped to re-ionize the Universe after its Dark Ages. Another important property of massive stars are the strong stellar winds and outflows they produce. This mass loss, and finally the explosion of a massive star as a supernova or a gamma-ray burst, provide a significant input of mechanical and radiative energy into the interstellar space. These two properties together make massive stars one of the most important cosmic engines: they trigger the star formation and enrich the interstellar medium with heavy elements, that ultimately leads to formation of Earth-like rocky planets and the development of complex life. The study of massive star winds is thus a truly multidisciplinary field and has a wide impact on different areas of astronomy.In recent years observational and theoretical evidences have been growing that these winds are not smooth and homogeneous as previously assumed, but rather populated by dense "clumps". The presence of these structures dramatically affects the mass loss rates derived from the study of stellar winds. Clump properties in isolated stars are nowadays inferred mostly through indirect methods (i.e., spectroscopic observations of line profiles in various wavelength regimes, and their analysis based on tailored, inhomogeneous wind models). The limited characterization of the clump physical properties (mass, size) obtained so far have led to large uncertainties in the mass loss rates from massive stars. Such uncertainties limit our understanding of the role of massive star winds in galactic and cosmic evolution.Supergiant high mass X-ray binaries (SgXBs) are among the brightest X-ray sources in the sky. A large number of them consist of a neutron star accreting from the wind of a massive companion and producing a powerful X-ray source. The characteristics of the stellar wind together with the complex interactions between the compact object and the donor star determine the observed X-ray output from all these systems. Consequently, the use of SgXBs for studies of massive stars is only possible when the physics of the stellar winds, the compact objects, and accretion mechanisms are combined together and confronted with observations.This detailed review summarises the current knowledge on the theory and observations of winds from massive stars, as well as on observations and accretion processes in wind-fed high mass X-ray binaries. The aim is to combine in the near future all available theoretical diagnostics and observational measurements to achieve a unified picture of massive star winds in isolated objects and in binary systems.
Keywords: Massive stars; Stellar outflows; X-ray binary; Wind-fed systems; Accretion processes; SgXBs; SFXTs

Towards Precision Measurements of Accreting Black Holes Using X-Ray Reflection Spectroscopy - Bambi, Cosimo; Brenneman, Laura W.; Dauser, Thomas; Garcia, Javier; Grinberg, Victoria; Ingram, Adam; Jiang, Jiachen; Liu, Honghui; Lohfink, Anne M.; Marinucci, Andrea; Mastroserio, Guglielmo; Middei, Riccardo; et al. (Space Science Reviews, 2021)
Relativistic reflection features are commonly observed in the X-ray spectra of accreting black holes. In the presence of high quality data and with the correct astrophysical model, X-ray reflection spectroscopy can be quite a powerful tool to probe the strong gravity region, study the morphology of the accreting matter, measure black hole spins, and possibly test Einstein's theory of general relativity in the strong field regime. In the last decade, there has been significant progress in the development of the analysis of these features, thanks to more sophisticated astrophysical models and new observational facilities. Here we review the state-of-the-art in relativistic reflection modeling, listing assumptions and simplifications that may affect, at some level, the final measurements and may be investigated better in the future. We review black hole spin measurements and the most recent efforts to use X-ray reflection spectroscopy for testing fundamental physics.
CRIS-Team WoS Importer:2021-07-30

Tracking down the origin of superbubbles and supergiant shells in the Magellanic Clouds with Minkowski tensor analysis - Collischon, Caroline; Sasaki, Manami; Mecke, Klaus; Points, Sean D.; Klatt, Michael A. (Astronomy & Astrophysics, 2021)
Aims. We develop an automatic bubble-recognition routine based on Minkowski functionals (MF) and tensors (MT) to detect bubble-like interstellar structures in optical emission line images. Methods. Minkowski functionals and MT are powerful mathematical tools for parameterizing the shapes of bodies. Using the papaya2-library, we created maps of the desired MF or MT of structures at a given window size. We used maps of the irreducible MT ψ2, which is sensitive to elongation, to find filamentary regions in Hα, [S II], and [O III] images of the Magellanic Cloud Emission Line Survey. Using the phase of ψ2, we were able to draw lines perpendicular to each filament and thus obtain line-density maps. This allowed us to find the center of a bubble-like structure and to detect structures at different window sizes. Results. The detected bubbles in all bands are spatially correlated to the distribution of massive stars, showing that we indeed detect interstellar bubbles without large spatial bias. Eighteen out of 59 supernova remnants in the Large Magellanic Cloud (LMC) and 13 out of 20 superbubbles are detected in at least one wavelength. The lack of detection is mostly due to surrounding emission that disturbs the detection, a too small size, or the lack of a (circular) counterpart in our emission line images. In line-density maps at larger scales, maxima can be found in regions with high star formation in the past, often inside supergiant shells (SGS). In SGS LMC 2, there is a maximum west of the shell where a collision of large gas clouds is thought to have occurred. In the Small Magellanic Cloud (SMC), bubble detection is impaired by the more complex projected structure of the galaxy. Line maps at large scales show large filaments in the SMC in a north-south direction, especially in the [S II] image. The origin of these filaments is unknown.
CRIS-Team Scopus Importer:2021-09-17
Keywords: ISM: structure; Magellanic Clouds; Methods: data analysis; Methods: statistical

Tracking the orbital and superorbital periods of SMC X-1 - Wilms, Jörn; et al. (Astrophysical Journal, 2007)
The high-mass X-ray binary (HMXB) SMCX-1 demonstrates an orbital variation of similar to 3.89 days and a superorbital variation with an average length of similar to 55 days. As we show here, however, the length of the superorbital cycle varies by almost a factor of 2, even across adjacent cycles. To study both the orbital and superorbital variation, we utilize light curves from the Rossi X-Ray Timing Explorer All-Sky Monitor (RXTE ASM). We employ the orbital ephemeris from P. Wojdowski et al. to obtain the average orbital profile, and we show that this profile exhibits complex modulation during noneclipse phases. In addition, a very interesting "bounceback" in X-ray count rate is seen during mid-orbital eclipse phases, with a softening of the emission during these periods. This bounceback has not been previously identified in pointed observations. We then define a superorbital ephemeris ( the phase of the superorbital cycle as a function of date) based on the ASM light curve and analyze the trend and distribution of superorbital cycle lengths. SMC X-1 exhibits a bimodal distribution of these lengths, similar to what has been observed in other systems ( e. g., Her X-1), but with more dramatic changes in cycle length. There is some hint, but not conclusive evidence, for a dependence of the superorbital cycle length on the underlying orbital period, as has been observed previously for Her X-1 and Cyg X-2. Using our superorbital ephemeris, we are also able to create an average superorbital profile over the 71 observed cycles, for which we witness overall hardening of the spectrum during low count rate times. We combine the orbital and superorbital ephemerides to study the correlation between the orbital and superorbital variations in the system, but find that the ASM light curve provides insufficient statistics to draw any definitive conclusions on possible correlations.
Keywords: accretion; accretion disks; X-rays : binaries

Transiting Sub-stellar companions of Intermediate-mass stars - Sebastian, Daniel; Guenther, Eike W.; Heber, Ulrich; Geier, Stephan; Grziwa, Sascha (2015)
We use the CoRoT-survey to search for transiting close-in planets of intermediate-mass stars (M-* = 1.3 - 2.1 M-circle dot). We present recent results of our survey. RV-surveys and direct imaging campaigns showed, that intermediate-mass main-sequence stars have more massive planets then solar-like stars. Even brown dwarfs have been found. In our study we concentrated on short-period planets for which a mass-determination is possible. The detection of close-in planets of intermediate-mass stars put strong constraints on the timescales of the formation and migration. We already have identified transiting Jupiter-like planet candidates with short orbital periods and observed these candidates with high-resolution echelle-spectrographs at various Telescopes.

Two candidate brown dwarf companions around core helium-burning stars - Schaffenroth, Veronika; Classen, Lew; Nagel, K.; Geier, S.; Koen, C.; Heber, Ulrich; Edelmann, Heinz (Astronomy & Astrophysics, 2014)
Hot subdwarf stars of spectral type B (sdBs) are evolved, core helium-burning objects. The formation of those objects is puzzling, because the progenitor star has to lose almost its entire hydrogen envelope in the red-giant phase. Binary interactions have been invoked, but single sdBs exist as well. We report the discovery of two close hot subdwarf binaries with small radial velocity amplitudes. Follow-up photometry revealed reflection effects originating from cool irradiated companions, but no eclipses. The lower mass limits for the companions of CPD-64°481 (0.048 M) and PHL 457 (0.027 M) are significantly below the stellar mass limit. Hence they could be brown dwarfs unless the inclination is unfavourable. Two very similar systems have already been reported. The probability that none of them is a brown dwarf is very small, 0.02%. Hence we provide further evidence that substellar companions with masses that low are able to eject a common envelope and form an sdB star. Furthermore, we find that the properties of the observed sample of hot subdwarfs in reflection effect binaries is consistent with a scenario where single sdBs can still be formed via common envelope events, but their low-mass substellar companions do not survive.
CRIS-Team Scopus Importer:2020-12-21
Keywords: Binaries: spectroscopic; Brown dwarfs; Subdwarfs

Two evolved close binary stars: GALEX J015054.4+310745 and the central star of the planetary nebula Hen 2-84 - Hillwig, Todd C.; Reindl, Nicole; Rotter, Hannah M.; Rengstorf, Adam W.; Heber, Ulrich; Irrgang, Andreas (Monthly Notices of the Royal Astronomical Society, 2022)
As part of a survey to find close binary systems among central stars of planetary nebula, we present two newly discovered binary systems. GALEX J015054.4+310745 is identified as the central star of the possible planetary nebula Fr 2-22. We find it to be a single-lined spectroscopic binary with an orbital period of 0.2554435(10) d. We support the previous identification of GALEX J015054.4+310745 as an sdB star and provide physical parameters for the star from spectral modelling. We identify its undetected companion as a likely He white dwarf. Based on this information, we find it unlikely that Fr 2-22 is a true planetary nebula. In addition, the central star of the true planetary nebula Hen 2-84 is found to be a photometric variable, likely due to the irradiation of a cool companion. The system has an orbital period of 0.485645(30) d. We discuss limits on binary parameters based on the available light-curve data. Hen 2-84 is a strongly shaped bipolar planetary nebula, which we now add to the growing list of axially or point-symmetric planetary nebulae with a close binary central star.
CRIS-Team WoS Importer:2022-03-11

Two evolved supernova remnants with newly identified Fe-rich cores in the Large Magellanic Cloud - Kavanagh, Patrick J.; Sasaki, Manami; Bozzetto, L. M.; Points, Sean; Crawford, H. J.; Dickel, John; Filipovic, M. D.; Haberl, Frank; Maggi, Pierre; Whelan, Emma (Astronomy & Astrophysics, 2016)
Aims. We present a multi-wavelength analysis of the evolved supernova remnants MCSNR J0506−7025 and MCSNR J0527−7104 in the Large Magellanic Cloud. Methods. We used observational data from XMM-Newton, the Australian Telescope Compact Array, and the Magellanic Cloud Emission Line Survey to study their broad-band emission and used Spitzer and H  data to gain a picture of the environment into which the remnants are expanding. We performed a multi-wavelength morphological study and detailed radio and X-ray spectral analyses to determine their physical characteristics. Results. Both remnants were found to have bright X-ray cores, dominated by Fe L-shell emission, which is consistent with reverse shock-heated ejecta with determined Fe masses in agreement with Type Ia explosion yields. A soft X-ray shell, which is consistent with swept-up interstellar medium, was observed in MCSNR J0506−7025, suggestive of a remnant in the Sedov phase. Using the spectral fit results and the Sedov self-similar solution, we estimated the age of MCSNR J0506−7025 to be ∼16−28 kyr, with an initial explosion energy of (0.07−0.84) × 1051 erg. A soft shell was absent in MCSNR J0527−7104, with only ejecta emission visible in an extremely elongated morphology that extends beyond the optical shell. We suggest that the blast wave has broken out into a low density cavity, allowing the shock heated ejecta to escape. We find that the radio spectral index of MCSNR J0506−7025 is consistent with the standard −0.5 for supernova remnants. Radio polarisation at 6 cm indicates a higher degree of polarisation along the western front and at the eastern knot with a mean fractional polarisation across the remnant of P 􏰨 (20 ± 6)%. Conclusions. The detection of Fe-rich ejecta in the remnants suggests that both resulted from Type Ia explosions. The newly identi- fied Fe-rich cores in MCSNR J0506−7025 and MCSNR J0527−7104 make them members of the expanding class of evolved Fe-rich remnants in the Magellanic Clouds.
Keywords: ISM: supernova remnants; Magellanic Clouds; X-rays: ISM

Two giant outbursts of V0332+53 observed with INTEGRAL - Ferrigno, Carlo; Ducci, Lorenzo; Bozzo, Enrico; Kretschmar, Peter; Kühnel, Matthias; Malacaria, Christian; Pottschmidt, Katja; Santangelo, Andrea; Savchenko, Volodymyr; Wilms, Jörn (Astronomy & Astrophysics, 2016)
Context. In July 2015, the high-mass X-ray binary V0332+53 underwent a giant outburst, a decade after the previous one. V0332+53 hosts a strongly magnetized neutron star. During the 2004-2005 outburst, an anti-correlation between the centroid energy of its fundamental cyclotron resonance scattering features (CRSFs) and the X-ray luminosity was observed. Aims. The long (≈ 100 d) and bright (L ≈ 10 erg s) 2015 outburst provided the opportunity to study the unique properties of the fundamental CRSF during another outburst and to study its dependence on the X-ray luminosity. Methods. The source was observed by the INTEGRAL satellite for 330 ks. We exploit the spectral resolution at high energies of the SPectrometer on INTEGRAL (SPI) and the Joint European X-ray Monitors to characterize its spectral properties, focusing in particular on the CRSF-luminosity dependence. We complement the data of the 2015 outburst with those collected by SPI in 2004-2005, which have so far been left unpublished. Results. We find a highly significant anti-correlation of the centroid energy of the fundamental CRSF and the 3-100 keV luminosity of E α -0.095(8)L keV. This trend is observed for both outbursts. We confirm the correlation between the width of the fundamental CRSF and the X-ray luminosity previously found in the JEM-X and IBIS dataset of the 2004-2005 outburst. By exploiting the RXTE/ASM and Swift/BAT monitoring data, we also report on the detection of a 34 d modulation superimposed on the mean profiles and roughly consistent with the orbital period of the pulsar. We discuss possible interpretations of such variability.
Keywords: pulsars: individual: V0332+53; stars: neutron; X-rays: binaries

Two similar to 35 day clocks in Hercules X-1: evidence for neutron star free precession - Staubert, R.; Klochkov, D.; Postnov, Konstantin; Shakura, N.; Wilms, Jörn; Rothschild, R. E. (Astronomy & Astrophysics, 2009)
We present evidence for the existence of two similar to 35 day clocks in the Her X-1/HZ Her binary system. similar to 35 day modulations are observed 1) in the Turn-On cycles with two on-and two off-states and 2) in the changing shape of the pulse profiles which re-appears regularly. The two ways of counting the 35 day cycles are generally in synchronization. This synchronization did apparently break down temporarily during the long Anomalous Low (AL3), which Her X-1 experienced in 1999/2000, in the sense that there must have been one extra Turn-On cycle. Our working hypothesis is that there are two clocks in the system, both with a period of about similar to 35 days: precession of the accretion disk (the less stable "Turn-On clock") and free precession of the neutron star (the more stable "Pulse profile clock"). We suggest that free precession of the neutron star is the master clock and that the precession of the accretion disk is basically synchronized to that of the neutron star through a feedback mechanism in the binary system. However, the Turn-On clock can slip against its master when the accretion disk has a very low inclination, as is observed to be the case during AL3. We take the apparent correlation between the histories of the Turn-Ons, of the Anomalous Lows and of the pulse period evolution, with a 5 yr quasi-periodicity, as evidence for strong physical interaction and feedback between the major components in the system. We speculate that the 5 yr (10 yr) period is due either to a corresponding activity cycle of HZ Her or a natural ringing period of the physical system of coupled components. The question of whether free precession really exists in neutron stars is very important for understanding matter with supra-nuclear density.
Keywords: stars: binaries: general; accretion; accretion disks; stars: neutron; X-rays: general; X-rays: binaries; X-rays: individuals: Her X-1

Ultra high energy photons and neutrinos with JEM-EUSO (vol 40, pg 215, 2015) - Adams, J. H.; Ahmad, S.; Albert, J. -N.; Allard, D.; Anchordoqui, L.; Andreev, V.; Anzalone, A.; Arai, Y.; Asano, K.; Ave Pernas, M.; Baragatti, P.; Barrillon, P.; et al. (Experimental Astronomy, 2015)

Ultra-violet imaging of the night-time earth by EUSO-Balloon towards space-based ultra-high energy cosmic ray observations - Abdellaoui, G.; Abe, S.; Adams, J. H.; Ahriche, A.; Allard, D.; Allen, L.; Alonso, G.; Anchordoqui, L.; Anzalone, A.; Arai, Y.; Asano, K.; Attallah, R.; et al. (Astroparticle Physics, 2019)
The JEM-EUSO (Joint Experiment Missions for the Extreme Universe Space Observatory) program aims at developing Ultra-Violet (UV) fluorescence telescopes for efficient detections of Extensive Air Showers (EASs) induced by Ultra-High Energy Cosmic Rays (UHECRs) from satellite orbit. In order to demonstrate key technologies for JEM-EUSO, we constructed the EUSO-Balloon instrument that consists of a ∼1 m 2 refractive telescope with two Fresnel lenses and an array of multi-anode photo-multiplier tubes at the focus. Distinguishing it from the former balloon-borne experiments, EUSO-Balloon has the capabilities of single photon counting with a gate time of 2.3 µs and of imaging with a total of 2304 pixels. As a pathfinder mission, the instrument was launched for an 8 h stratospheric flight on a moonless night in August 2014 over Timmins, Canada. In this work, we analyze the count rates over ∼2.5 h intervals. The measurements are of diffuse light, e.g. of airglow emission, back-scattered from the Earth's atmosphere as well as artificial light sources. Count rates from such diffuse light are a background for EAS detections in future missions and relevant factor for the analysis of EAS events. We also obtain the geographical distribution of the count rates over a ∼780 km 2 area along the balloon trajectory. In developed areas, light sources such as the airport, mines, and factories are clearly identified. This demonstrates the correct location of signals that will be required for the EAS analysis in future missions. Although a precise determination of count rates is relevant for the existing instruments, the absolute intensity of diffuse light is deduced for the limited conditions by assuming spectra models and considering simulations of the instrument response. Based on the study of diffuse light by EUSO-Balloon, we also discuss the implications for coming pathfinders and future space-based UHECR observation missions.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Airglow; EUSO-Balloon; Extensive air shower; JEM-EUSO; Ultra-high energy cosmic ray

Unity among Black Holes: Observational Similarities between Galactic Black Holes and Active Galactic Nuclei - Wilms, Jörn (SCIENCE PRESS, 2008)
A brief overview of recent observational work on the similarities of Galactic and supermassive black holes is given. It is shown that Galactic black holes and Active Galactic Nuclei both show relativistically broadened iron lines, follow the same relationship between their X-ray and their radio luminosity (L-radio alpha L-X(0.7)), and show similar X-ray variability. These observations indicate that the accretion flows around black holes scale over many orders of magnitude in mass and luminosity.
Keywords: X-rays: binaries; galaxies: active; accretion; accretion physics; black hole physics

UNVEILING THE NATURE OF IGR J17177-3656 WITH X-RAY, NEAR-INFRARED, AND RADIO OBSERVATIONS - Paizis, Adamantia; Nowak, M. A.; Wilms, Jörn; Chaty, Sylvain; Corbel, S.; Rodriguez, Jerome; Del Santo, Melania; Ubertini, P.; Chini, R. (Astrophysical Journal, 2011)
We report on the first broadband (1-200 keV) simultaneous Chandra-INTEGRAL observations of the recently discovered hard X-ray transient IGR J17177-3656 that took place on 2011 March 22, about two weeks after the source discovery. The source had an average absorbed 1-200 keV flux of about 8 x 10(-10) erg cm(-2) s(-1). We extracted a precise X-ray position of IGR J17177-3656, alpha(J2000) = 17(h)17(m)42(s).62, delta(J2000) = -36 degrees 56'04 ''.5 (90% uncertainty of 0 ''.6). We also report Swift, near-infrared, and quasi-simultaneous radio follow-up observations. With the multi-wavelength information at hand, we propose IGR J17177-3656 is a low-mass X-ray binary, seen at high inclination, probably hosting a black hole.
Keywords: accretion; accretion disks; binaries: close; stars: individual (IGR J17177-3656); X-rays: binaries

Unveiling the nature of IGR J17497-2821 using X-ray and near-infrared observations - Wilms, Jörn; et al. (Astrophysical Journal, 2007)
We report on a Chandra grating observation of the recently discovered hard X-ray transient IGR J17497-2821. The observation took place about 2 weeks after the discovery of the source at a flux level of about 20 mcrab in the 0.8-8 keV range. We extracted the most precise X-ray position of IGR J17497-2821, i.e., alpha(J2000) = 17(h)49(m)38.037(s), delta(J2000) = -28 degrees 21'17.37" (with a 90% uncertainty of 0.6"). We also report on optical and near-infrared photometric follow-up observations based on this position. With the multiwavelength information at hand, we discuss the possible nature of the source, proposing that IGR J17497-2821 is a low-mass X-ray binary, most likely hosting a black hole, with a red giant K-type companion.
Keywords: binaries : close; stars : individual (IGR J17497-2821); X-rays : binaries

Updating the orbital ephemeris of Hercules X-1; rate of decay and eccentricity of the orbit - Staubert, R.; Klochkov, D.; Wilms, Jörn (Astronomy & Astrophysics, 2009)
We present an update of the orbital ephemeris of the binary X-ray pulsar Her X-1 and determine an improved value for the rate of orbital decay. In addition, we report the first measurement of the orbital eccentricity. We analyzed pulse timing data of Her X-1 from X-ray observations by RXTE (Rossi X-Ray Timing Explorer) and INTEGRAL over the period 1996-2007. Accurate pulse arrival times were determined from solar system bary-centered photon arrival times by generating pulse profiles averaged over appropriately short integration times. Applying pulse phase connection techniques, it was possible to determine sufficiently accurate local ephemeris data for seven observation periods distributed over 12 years. Combining the new local T(pi/2) values with historical values from the literature we update the orbital ephemeris of Her X-1 to T(pi/2) = MJD 46 359.871940(6) and P(orb) = 1.700167590(2) d and measure a continuous change of the orbital period of dP(orb/dt) = -(4.85 +/- 0.13) x 10(-11) s s(-1). For the first time, a value for the eccentricity of the orbit of Her X-1 has been measured: is an element of = (4.2 +/- 0.8) x 10(-4).
Keywords: stars: binaries: general; stars: neutron; X-rays: general; X-rays: binaries; X-rays: individuals: Her X-1; ephemerides

Upper limits on very-high-energy gamma-ray emission from core-collapse supernovae observed with HESS - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Anguener, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Ashkar, H.; Backes, Michael; Martins, V. Barbosa; Barnard, M.; Becherini, Y.; et al. (Astronomy & Astrophysics, 2019)
Young core-collapse supernovae with dense-wind progenitors may be able to accelerate cosmic-ray hadrons beyond the knee of the cosmic-ray spectrum, and this may result in measurable gamma-ray emission. We searched for gamma-ray emission from ten super- novae observed with the High Energy Stereoscopic System (H.E.S.S.) within a year of the supernova event. Nine supernovae were observed serendipitously in the H.E.S.S. data collected between December 2003 and December 2014, with exposure times ranging from 1.4 to 53 h. In addition we observed SN 2016adj as a target of opportunity in February 2016 for 13 h. No significant gamma-ray emission has been detected for any of the objects, and upper limits on the >1 TeV gamma-ray flux of the order of similar to 10(-13) cm(-)(2)s(-1) are established, corresponding to upper limits on the luminosities in the range similar to 2 x 10(39) to similar to 1 x 10(42) erg s(-1). These values are used to place model-dependent constraints on the mass-loss rates of the progenitor stars, implying upper limits between similar to 2 x 10(-5) and similar to 2 x 10(-3) M-circle dot yr(-1) under reasonable assumptions on the particle acceleration parameters.
CRIS-Team WoS Importer:2019-06-28

USING THE X-RAY DUST SCATTERING HALO OF CYGNUS X-1 TO DETERMINE DISTANCE AND DUST DISTRIBUTIONS - Xiang, Jingen; Lee, Julia C.; Nowak, Michael A.; Wilms, Jörn (Astrophysical Journal, 2011)
We present a detailed study of the X-ray dust scattering halo of the black hole candidate Cygnus X-1 based on two Chandra High Energy Transmission Gratings Spectrometer observations. Using 18 different dust models, including one modified by us (eponymously dubbed XLNW), we probe the interstellar medium between us and this source. A consistent description of the cloud properties along the line of sight (LOS) that describes at the same time the halo radial profile, the halo light curves, and the column density from source spectroscopy is best achieved with a small subset of these models. Combining the studies of the halo radial profile and the halo light curves, we favor a geometric distance to Cygnus X-1 of d = 1.81 +/- 0.09 kpc. Our study also shows that there is a dense cloud, which contributes similar to 50% of the dust grains along the LOS to Cygnus X-1, located at similar to 1.6 kpc from us. The remainder of the dust along the LOS is close to the black hole binary.
Keywords: dust; extinction; scattering; X-rays: binaries; X-rays: individual (Cyg X-1); X-rays: ISM

Vacuum polarization alters the spectra of accreting X-ray pulsars - Sokolova-Lapa, Ekaterina; Stierhof, Jakob; Dauser, Thomas; Wilms, Jörn (Astronomy & Astrophysics, 2023)
It is a common belief that for magnetic fields typical of accreting neutron stars in high-mass X-ray binaries vacuum polarization only affects the propagation of polarized emission in the neutron star magnetosphere. We show that vacuum resonances can significantly alter the emission from the poles of accreting neutron stars. The effect is similar to vacuum polarization in the atmospheres of isolated neutron stars and can result in suppression of the continuum and the cyclotron lines. It is enhanced by magnetic Comptonization in the hot plasma and proximity to the electron cyclotron resonance. We present several models to illustrate the vacuum polarization effect for various optically thick media and discuss how the choice of polarization modes affects the properties of the emergent radiation by simulating polarized energy- and angle-dependent radiative transfer. Polarization effects, including vacuum polarization, crucially alter the emission properties. Together with strongly angle- and energy-dependent magnetic Comptonization, they result in a complex spectral shape, which can be described by dips and humps on top of a power-law-like continuum with high-energy cutoff. These effects provide a possible explanation for the common necessity of additional broad Gaussian components and two-component Comptonization models that are used to describe spectra of accreting X-ray pulsars. We also demonstrate the character of depolarization introduced by the radiation fielda's propagation inside the inhomogeneous emission region.
CRIS-Team Scopus Importer:2023-06-30
Keywords: Magnetic fields; Methods: numerical; Polarization; Radiative transfer; Stars: neutron; X-rays: binaries

Variability in high-mass X-ray binaries - Fuerst, Felix; Kretschmar, Peter; Grinberg,; Pottschmidt, K.; Wilms, Jörn; Kühnel, Matthias; El Mellah,; Martinez-Nunez, Silvia (Astronomische Nachrichten, 2019)
Strongly magnetized, accreting neutron stars show periodic and aperiodic variability over a wide range of time scales. By obtaining spectral and timing information on these different time scales, we can have a closer look into the physics of accretion close to the neutron star and the properties of the accreted material. One of the most prominent time scales is the strong pulsation, i.e., the rotation period of the neutron star itself. Over one rotation, our view of the accretion column and the X-ray producing region changes significantly. This allows us to sample different physical conditions within the column but at the same time requires that we have viewing-angle-resolved models to properly describe them. In wind-fed high-mass X-ray binaries, the main source of aperiodic variability is the clumpy stellar wind, which leads to changes in the accretion rate (i.e., luminosity) as well as absorption column. This variability allows us to study the behavior of the accretion column as a function of luminosity, as well as to investigate the structure and physical properties of the wind, which we can compare to winds in isolated stars.
CRIS-Team WoS Importer:2021-10-18

Variable cyclotron line in her X-1 - Wilms, Jörn; et al. (2007)
We present new results on the cyclotron resonance scattering feature (CRSF) in the X-ray spectrum of the binary X-ray pulsar Her X-1 from repeated observations by RXTE between 2000 and 2005, together with earlier results from RXTE and historical data. The centroid line energy E, in pulse phase averaged spectra shows considerable variation, both in the long-term historical development as well as during the time of the RXTE observations. Using RXTE data only, we find that the cyclotron line energy correlates with the observed maximum flux of the corresponding 35 day Main-On state, as measured by the RXTE/ASM. Contrary to what is observed in some high luminosity transient pulsars, the correlation found here is positive, with a change of similar to 5% in E-c for a change of a factor of two in X-ray flux. We suggest that this behaviour is expected in the case of sub-Eddington accretion and present a calculation of a quantitative estimate.
Keywords: X-ray binaries; X-ray pulsars; neutron stars; cyclotron lines

Variable neutron star free precession in Hercules X-1 from evolution of RXTE X-ray pulse profiles with phase of the 35-d cycle - Postnov, Konstantin; Shakura, N.; Staubert, R.; Kochetkova, A.; Klochkov, D.; Wilms, Jörn (Monthly Notices of the Royal Astronomical Society, 2013)
Accretion of matter on to the surface of a freely precessing neutron star (NS) with a complex non-dipole magnetic field can explain the change of X-ray pulse profiles of Her X-1 observed by RXTE with the phase of the 35-d cycle. We demonstrate this using all available measurements of X-ray pulse profiles in the 9-13 keV energy range obtained with the RXTE/Proportional Counter Array (PCA). The measured profiles guided the elaboration of a geometrical model and the definition of locations of emitting poles, arcs and spots on the NS surface which satisfactorily reproduce the observed pulse profiles and their dependence on free precession phase. We have found that the observed trend of the times of the 35-d turn-ons on the O-C diagram, which can be approximated by a collection of consecutive linear segments around the mean value, can be described by our model by assuming a variable free precession period, with a fractional period change of about a few per cent. Under this assumption and using our model, we have found that the times of phase zero of the NS free precession (which we identify with the maximum separation of the brightest spot on the NS surface with the NS spin axis) occur about 1.6 d after the mean turn-on times inside each 'stable' epoch, producing a linear trend on the O-C diagram with the same slope as the observed times of turn-ons. We propose that the 2.5 per cent changes in the free precession period that occur on time scales of several to tens of 35-d cycles can be related to wandering of the principal inertia axis of the NS body due to variations in the patterns of accretion on to the NS surface. The closeness of periods of the disc precession and the NS free precession can be explained by the presence of a synchronization mechanism in the system, which modulates the dynamical interaction of the gas streams and the accretion disc with the NS free precession period.
Keywords: accretion; accretion discs; stars: neutron; X-rays: binaries

Variable precession of the NS in Her X-1 - Staubert, R.; Klochkov, D.; Postnov, Konstantin; Shakura, N.; Wilms, Jörn; Rothschild, R. E. (2010)
We present evidence for an identical behavior of the precession of the accretion disk and that of the neutron star (NS) in Her X-1, based on investigating the well established 35 day modulation in Her X-1 in two different ways: 1) following the turn-ons, thought to be due to the precession of the accretion disk, and 2) following the re-appearance of the shape of the pulse profiles, which we assume to be due to precession of the NS. The turn-on evolution and the evolution of the 'phase-zero' values of the precessing NS (as determined from the pulse profiles) track each other very closely. Since the turn-on evolution is strongly correlated with the pulse period evolution, this means that there is also a strong correlation between the spin and the precession of the NS. There is a very strong physical coupling between the NS and the accretion disk, we suggest through physical feedback in the binary system. The apparent long-term stability of the 35 d clock may be due to the 'interior' of the NS, the coupling of which to the observable surface effects is of general importance for the physics of super-dense, highly magnetized material.
Keywords: Neutron stars; free precession; X-ray binaries; strong magnetic field; Her X-1

Variable pulse profiles of Hercules X-1 repeating with the same irregular 35 d clock as the turn-ons - Staubert, R.; Klochkov, D.; Vasco, D.; Postnov, Konstantin; Shakura, N.; Wilms, Jörn; Rothschild, R. E. (Astronomy & Astrophysics, 2013)
The accreting X-ray pulsar Her X-1 shows two types of long-term variations, both with periods of similar to 35 days: 1) turn-on cycles, a modulation of the flux, with a ten-day long main-on and a five-day long short-on, separated by two off-states, and 2) a systematic variation in the shape of the 1.24 s pulse profile. While there is general consensus that the flux modulation is due to variable shading of the X-ray emitting regions on the surface of the neutron star by the precessing accretion disk, the physical reason for the variation in the pulse profiles has remained controversial. Following the suggestion that free precession of the neutron star may be responsible for the variation in the pulse profiles, we developed a physical model of strong feedback interaction between the neutron star and the accretion disk in order to explain the seemingly identical values for the periods of the two types of variations, which were found to be in basic synchronization. In a deep analysis of pulse profiles observed by several different satellites over the last three decades we now find that the clock behind the pulse profile variations shows exactly the same erratic behavior as the turn-on clock, even on short time scales (a few 35 d cycles), suggesting that there may in fact be only one 35 d clock in the system. If this is true, it raises serious questions with respect to the idea of free precession of the neutron star, namely how the neutron star can change its precessional period every few years by up to 2.5% and how the feedback can be so strong, such that these changes can be transmitted to the accretion disk on rather short time scales.
Keywords: binaries: general; stars: individual: Her-X-1; X-rays: binaries; X-rays: stars; pulsars: general

Vertical wind structure in an X-ray binary revealed by a precessing accretion disk - Kosec, P.; Kara, E.; Fabian, A. C.; Fuerst, F.; Pinto, C.; Psaradaki, I.; Reynolds, C. S.; Rogantini, D.; Walton, D. J.; Ballhausen, R.; Canizares, C.; Dyda, S.; et al. (Nature Astronomy, 2023)
Kosec et al. analyse X-ray spectroscopic observations of outflowing hot material from an accreting neutron star. An innovative technique reveals the vertical distribution of the outflow structure, which is challenging to measure otherwise.
CRIS-Team WoS Importer:2023-05-26

Very high energy gamma-ray emission from two blazars of unknown redshift and upper limits on their distance - Abdalla, H.; Adam, R.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Armstrong, T.; Ashkar, H.; Backes, M.; Baghmanyan, V.; et al. (Monthly Notices of the Royal Astronomical Society, 2020)
We report on the detection of very high energy (VHE; E > 100 GeV) gamma-ray emission from the BL Lac objects KUV 00311-1938 and PKS 1440-389 with the High Energy Stereoscopic System (H.E.S.S.). H.E.S.S. observations were accompanied or preceded by multiwavelength observations with Fermi/LAT, XRT and UVOT onboard the Swift satellite, and ATOM. Based on an extrapolation of the Fermi/LAT spectrum towards the VHE gamma-ray regime, we deduce a 95 per cent confidence level upper limit on the unknown redshift of KUV 00311-1938 of z < 0.98 and of PKS 1440-389 of z < 0.53. When combined with previous spectroscopy results, the redshift of KUV 00311-1938 is constrained to 0.51 <= z < 0.98 and of PKS 1440-389 to 0.14 (sic) z < 0.53.
CRIS-Team WoS Importer:2020-06-26

VHE gamma-ray discovery and multiwavelength study of the blazar 1ES 2322-409 - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Arrieta, M.; Backes, M.; Barnard, M.; Becherini, Y.; Tjus, J. Becker; et al. (Monthly Notices of the Royal Astronomical Society, 2019)
A hotspot at a position compatible with the BL. Lac object 1ES 2322-409 was serendipitously detected with H.E.S.S. during observations performed in 2004 and 2006 on the blazar PKS 2316-423. Additional data on 1ES 2322-409 were taken in 2011 and 2012, leading to a total live-time of 22.3 h. Point-like very-high-energy (VHE; E > 100 GeV) gamma-ray emission is detected from a source centred on the IFS 2322-409 position, with an excess of 116.7 events at a significance of 6.0 sigma. The average VHE gamma-ray spectrum is well described with a power law with a photon index Gamma = 3.40 +/- 0.66(stat) +/- 0.20(sys) and an integral flux Phi(E > 200 GeV) = (3.11 +/- 0.71(stat) 0.62(sys)) x 10(-2)cm(-2)s(-1), which corresponds to 1.1 per cent of the Crab nebula flux above 200 GeV. Multiwavelength data obtained with Fermi LAT, Swift XRT and UVOT, RXTE PCA, ATOM, and additional data from WISE, GROND, and Catalina are also used to characterize the broad-band non-thermal emission of lES 2322-409. The multiwavelength behaviour indicates day-scale variability. Swift UVOT and XRT data show strong variability at longer scales. A spectral energy distribution (SED) is built from contemporaneous observations obtained around a high state identified in Swift data. A modelling of the SED is performed with a stationary homogeneous one-zone synchrotronself-Compton leptonic model. The redshift of the source being unknown, two plausible values were tested for the modelling. A systematic scan of the model parameters space is performed, resulting in a well-constrained combination of values providing a good description of the broad-band behaviour of 1ES 2322-409.
CRIS-Team WoS Importer:2019-04-09
Keywords: BL Lacertae objects: individual: 1ES 2322-409; galaxies: active; gamma-rays: galaxies; Radiation mechanisms: non-thermal

VLBA polarimetric monitoring of 3C 111 - Beuchert, Tobias; Kadler, M.; Perucho, M.; Grossberger, C.; Schulz, R.; Agudo, I.; Casadio, C.; Gomez, J. L.; Gurwell, Mark; Homan, D.; Kovalev, Y. Y.; Lister, M. L.; et al. (Astronomy & Astrophysics, 2018)
Context. While studies of large samples of jets of active galactic nuclei (AGN) are important in order to establish a global picture, dedicated single-source studies are an invaluable tool for probing crucial processes within jets on parsec scales. These processes involve in particular the formation and geometry of the jet magnetic held as well as the flow itself.Aims. We aim to better understand the dynamics within relativistic magneto-hydrodynamical flows in the extreme environment and close vicinity of supermassive black holes.Methods. We analyze the peculiar radio galaxy 3C 111, for which long-term polarimetric observations are available. We make use of the high spatial resolution of the VLBA network and the MOJAVE monitoring program, which provides high data quality also for single sources and allows us to study jet dynamics on parsec scales in full polarization with an evenly sampled time-domain. While electric vectors can probe the underlying magnetic field, other properties of the jet such as the variable (polarized) flux density, feature size, and brightness temperature, can give valuable insights into the flow itself. We complement the VLBA data with data from the IRAM 30-m Telescope as well as the SMA.Results. We observe a complex evolution of the polarized jet. The electric vector position angles (EVPAs) of features traveling down the jet perform a large rotation of greater than or similar to 180 degrees across a distance of about 20 pc. As opposed to this smooth swing, the EVPAs are strongly variable within the first parsecs of the jet. We find an overall tendency towards transverse EVPAs across the jet with a local anomaly of aligned vectors in between. The polarized flux density increases rapidly at that distance and eventually saturates towards the outermost observable regions. The transverse extent of the flow suddenly decreases simultaneously to a jump in brightness temperature around where we observe the EVPAs to turn into alignment with the jet flow. Also the gradient of the feature size and particle density with distance steepens significantly at that region.Conclusions. We interpret the propagating polarized features as shocks and the observed local anomalies as the interaction of these shocks with a localized recollimation shock of the underlying flow. Together with a sheared magnetic field, this shock-shock interaction can explain the large rotation of the EVPA. The superimposed variability of the EVPAs close to the core is likely related to a clumpy Faraday screen, which also contributes significantly to the observed EVPA rotation in that region.
Keywords: galaxies: active; galaxies: jets; galaxies: individual: 3C 111; galaxies: magnetic fields; radio continuum: galaxies; polarization

Warm Front End Electronic Modelization for the X-IFU ATHENA Readout Chain Simulation - Prele, Damien; Chen, Si; Coleiro, Alexis; Varniere, Peggy; Peille, Philippe; Ravera, Laurent; Kirsch, Christian (SPACE TELESCOPES AND INSTRUMENTATION 2020: ULTRAVIOLET TO GAMMA RAY, 2021)
CRIS-Team WoS Importer:2021-08-27

Weighing the galactic dark matter halo: A lower mass limit from the fastest halo star known - Przybilla, Norbert; Tillich, Alfred; Heber, Ulrich; Scholz, Ralf-Dieter (Astrophysical Journal, 2010)
The mass of the Galactic dark matter halo is under vivid discussion. A recent study by Xue et al. revised the Galactic halo mass downward by a factor of ∼2 relative to previous work, based on the line-of-sight velocity distribution of ∼2400 blue horizontal-branch (BHB) halo stars. The observations were interpreted with a statistical approach using cosmological galaxy formation simulations, as only four of the six-dimensional phase-space coordinates were determined. Here we concentrate on a close investigation of the stars with the highest negative radial velocity from that sample. For one star, SDSSJ153935.67+023909.8 (J1539+0239 for short), we succeed in measuring a significant proper motion, i.e., full phase-space information is obtained. We confirm the star to be a Population II BHB star from an independent quantitative analysis of the Sloan Digital Sky Survey (SDSS) spectrum - providing the first non-LTE (NLTE) study of any halo BHB star - and reconstruct its three-dimensional trajectory in the Galactic potential. J1539+0239 turns out to be the fastest halo star known to date, with a Galactic rest-frame velocity of 694+300-221 km s-1 (full uncertainty range from Monte Carlo error propagation) at its current position. The extreme kinematics of the star allows a significant lower limit to be put on the halo mass in order to keep it bound, of Mhalo ≥ 1.7+2.3-1.1 × 1012 M⊙. We conclude that the Xue et al. results tend to underestimate the true halo mass as their most likely mass value is consistent with our analysis only at a level of 4%. However, our result confirms other studies that make use of the full phase-space information.
CRIS-Team Scopus Importer:2020-12-21
Keywords: Dark matter; Galaxy: halo; Stars: atmospheres; Stars: horizontal-branch; Stars: kinematics and dynamics; Stars: Population II

White dwarf pollution by hydrated planetary remnants: hydrogen and metals in WDJ204713.76-125908.9 - Hoskin, Matthew J.; Toloza, Odette; Gansicke, Boris T.; Raddi, Roberto; Koester, Detlev; Pala, Anna F.; Manser, Christopher J.; Farihi, Jay; Belmonte, Maria Teresa; Hollands, Mark; Fusillo, Nicola Gentile; Swan, Andrew (Monthly Notices of the Royal Astronomical Society, 2020)
WDJ204713.76-125908.9 is a new addition to the small class of white dwarfs with helium-dominated photospheres that exhibit strong Balmer absorption lines and atmospheric metal pollution. The exceptional abundances of hydrogen observed in these stars may be the result of accretion of water-rich rocky bodies. We obtained far-ultraviolet and optical spectroscopy of WDJ204713.76-125908.9 using the Cosmic Origin Spectrograph on-board the Hubble Space Telescope and X-shooter on the Very Large Telescope, and identify photospheric absorption lines of nine metals: C, O, Mg, Si, P, S, Ca, Fe, and Ni. The abundance ratios are consistent with the steady-state accretion of exo-planetesimal debris rich in the volatile elements carbon and oxygen, and the transitional element sulphur, by factors of 17, 2, and 4, respectively, compared to the bulk Earth. The parent body has a composition akin to Solar system carbonaceous chondrites, and the inferred minimum mass, 1.6 x 10(20) g, is comparable to an asteroid 23 km in radius. We model the composition of the disrupted parent body, finding from our simulations a median water mass fraction of 8 per cent.
CRIS-Team WoS Importer:2020-12-04

Wide field imager instrument for the Advanced Telescope for High Energy Astrophysics - Meidinger, Norbert; Nandra, Kirpal; Plattner, Markus; Porro, Matteo; Rau, Arne; Santangelo, Andrea; Tenzer, Chris; Wilms, Jörn (Journal of Astronomical Telescopes, Instruments, and Systems, 2015)
The Advanced Telescope for High Energy Astrophysics (Athena) has been selected for ESA's L2 mission, scheduled for launch in 2028. It will provide the necessary capabilities to achieve the ambitious goals of the science theme "The Hot and Energetic Universe." Athena's x-ray mirrors will be based on silicon pore optics technology with a 12-m focal length. Two complementary focal plane camera systems are foreseen, which can be moved interchangeably to the focus of the mirror system: the actively shielded micro-calorimeter spectrometer X-IFU and the wide field imager (WFI). The WFI camera will provide an unprecedented survey power through its large field of view of 40 arc min with a high count-rate capability (similar to 1 Crab). It permits a state-of-the-art energy resolution in the energy band of 0.1 to 15 keV during the entire mission lifetime (e.g., full width at half maximum <= 150 eV at 6 keV). This performance is accomplished by a set of depleted P-channel field effect transistor (DEPFET) active pixel sensor matrices with a pixel size well suited to the angular resolution of 5 arc sec (on-axis) of the mirror system. Each DEPFET pixel is a combined detector-amplifier structure with a MOSFET integrated onto a fully depleted 450-mu m-thick silicon bulk. This manuscript will summarize the current instrument concept and design, the status of the technology development, and the envisaged baseline performance. (C) The Authors. Published by SPIE under a Creative Commons Attribution 3.0 Unported License. Distribution or reproduction of this work in whole or in part requires full attribution of the original publication, including its DOI.
Keywords: camera; detector; imaging; silicon; spectroscopy; x-ray

XIPE: The X-ray imaging polarimetry explorer - Soffitta, P.; Bellazzini, R.; Bozzo, E.; Burwitz, V.; Castro-Tirado, A. J.; Costa, E.; Courvoisier, T.; Feng, H.; Gburek, S.; Goosmann, R.; Karas, V.; Matt, G.; et al. (Space Telescopes and Instrumentation 2016: Ultraviolet to Gamma Ray, 2016)
XIPE, the X-ray Imaging Polarimetry Explorer, is a mission dedicated to X-ray Astronomy. At the time of writing XIPE is in a competitive phase A as fourth medium size mission of ESA (M4). It promises to reopen the polarimetry window in high energy Astrophysics after more than 4 decades thanks to a detector that efficiently exploits the photoelectric effect and to X-ray optics with large effective area. XIPE uniqueness is time-spectrally-spatially-resolved X-ray polarimetry as a breakthrough in high energy astrophysics and fundamental physics. Indeed the payload consists of three Gas Pixel Detectors at the focus of three X-ray optics with a total effective area larger than one XMM mirror but with a low weight. The payload is compatible with the fairing of the Vega launcher. XIPE is designed as an observatory for X-ray astronomers with 75 % of the time dedicated to a Guest Observer competitive program and it is organized as a consortium across Europe with main contributions from Italy, Germany, Spain, United Kingdom, Poland, Sweden.
Keywords: Gas Pixel Detector; Polarimetry; X-ray Astronomy; X-ray optics

XMM-Newton and Fermi /LAT view on the supernova remnant 3C434.1 - Doroshenko, Victor; Malyshev, Dmitry; Pühlhofer, G.; Dincel, Baha; Sasaki, Manami; Santangelo, Andrea (Astronomy & Astrophysics, 2019)
We report on XMM-Newton observations of the supernova remnant (SNR) 3C434.1 (G94.0+1.0), the first in X-rays since the ROSAT era. Our analysis confirms the thermal origin of the observed extended X-ray emission, whose morphology appears more complex than previously reported. In particular, part of the shell shows a significantly harder spectrum which is consistent with a power law, and it is, therefore, likely of non-thermal origin. Motivated by these finding, we revisited the GeV observations of the field taken with the Fermi observatory. A significant excess associated with the remnant was detected, which is likely associated with non-thermal X-ray emission from part of the shell. The analysis of the Fermi data resulted in the serendipity discovery of GeV emission from the nearby SNR G093.7-00.2. Finally, we searched for a possible compact remnants within the shell, however, no obvious candidates could be identified due to the fairly large positional uncertainties.
CRIS-Team Scopus Importer:2019-12-10
Keywords: Gamma rays: general; ISM: supernova remnants; Stars: neutron

XMM-Newton EPIC observation of SMC SNR 0102-72.3 - Sasaki, Manami; Stadlbauer, Thomas; Haberl, Frank; Filipovic, M. D.; Bennie, P. J. (Astronomy & Astrophysics, 2001)
Results from observations of the young oxygen-rich supernova remnant SNR0102-72.3 in the Small Magellanic Cloud during the calibration phase of the XMM-Newton Observatory are presented. Both EPIC-PN and MOS observations show a ringlike structure with a radius of similar to 15" already known from Einstein, ROSAT and Chandra observations. Spectra of the entire SNR as well as parts in the eastern half were analyaed confirming shocked hot plasma in non-uniform ionization stages as the origin of the X-ray emission. The spectra differ in the northeastern and the southeastern part; of the X-ray ring, showing emission line features of different strength. The temperature in the northeastern part is significantly higher than in the southeast, reflected by the lines of higher ionization stages and the harder continuum. Comparison to radio data shows the forward shock of the blast wave dominating in the northern part of the SNR, while the southern emission is most likely produced by the recently formed reverse shock in the ejecta. In the case of the overall spectrum of SNR0102-72.3, the two-temperature non-equilibrium ionization model is more consistent with the data in comparison to the single plane-parallel shock model. The structure of SNR0102-72.3 is complex due to variations in shock propagation leading to spatially differing X-ray spectra.
Keywords: shock waves; ISM : supernova remnants; galaxies : Magellanic Clouds; X-rays : ISM

XMM-Newton observation of the Galactic supernova remnant W51C (G49.1-0.1) - Sasaki, Manami; Heinitz, Cornelia; Gabriele, Warth; Puehlhofer, Gerd (Astronomy & Astrophysics, 2014)
Context. The supernova remnant (SNR) W51C is a Galactic object located in a strongly inhomogeneous interstellar medium with signs of an interaction of the SNR blast wave with dense molecular gas. Aims: Diffuse X-ray emission from the interior of the SNR can reveal element abundances in the different emission regions and shed light on the type of supernova (SN) explosion and its progenitor. The hard X-ray emission helps to identify possible candidates for a pulsar formed in the SN explosion and for its pulsar wind nebula (PWN). Methods: We have analysed X-ray data obtained with XMM-Newton. Spectral analyses in selected regions were performed. Results: Ejecta emission in the bright western part of the SNR, located next to a complex of dense molecular gas, was confirmed. The Ne and Mg abundances suggest a massive progenitor with a mass of >20 M☉. Two extended regions emitting hard X-rays were identified (corresponding to the known sources [KLS2002] HX3 west and CXO J192318.5+140305 discovered with ASCA and Chandra, respectively), each of which has an additional point source inside and shows a power-law spectrum with Γ ≈ 1.8. Based on their X-ray emission, both sources can be classified as PWN candidates.
Keywords: shock waves; HII regions; X-rays: ISM; X-rays: individuals: individual: SNR W51C

XMM-Newton observation of the interacting galaxies NGC 1512 and NGC 1510 - Ducci, Lorenzo; Kavanagh, Patrick J.; Sasaki, Manami; Koribalski, B. S. (Astronomy & Astrophysics, 2014)
Context. The galaxy NGC 1512 is interacting with the smaller galaxy NGC 1510 and shows a peculiar morphology, characterised by two extended arms immersed in an HI disc whose size is about four times larger than the optical diameter of NGC 1512. Aims. For the first time we performed a deep X-ray observation of the galaxies NGC 1512 and NGC 1510 with XMM-Newton to gain information on the population of X-ray sources and diffuse emission in a system of interacting galaxies. Methods. We identified and classified the sources detected in the XMM-Newton field of view by means of spectral analysis, hardness- ratios calculated with a Bayesian method, X-ray variability, and cross-correlations with catalogues in optical, infrared, and radio wavelengths. We also made use of archival Swift (X-ray) and Australia Telescope Compact Array (radio) data to better constrain the nature of the sources detected with XMM-Newton. Results. We detected 106 sources in the energy range of 0.2−12 keV, out of which 15 are located within the D25 regions of NGC 1512 and NGC 1510 and at least six sources coincide with the extended arms. We identified and classified six background objects and six foreground stars. We discussed the nature of a source within the D25 ellipse of NGC 1512, whose properties indicate a quasi-stellar object or an intermediate ultra-luminous X-ray source. Taking into account the contribution of low-mass X-ray binaries and active galactic nuclei, the number of high-mass X-ray binaries detected within the D25 region of NGC 1512 is consistent with the star formation rate obtained in previous works based on radio, infrared optical, and UV wavelengths. We detected diffuse X-ray emission from the interior region of NGC 1512 with a plasma temperature of kT = 0.68 (0.31−0.87) keV and a 0.3–10 keV X-ray luminosity of 1.3 × 1038 erg s−1, after correcting for unresolved discrete sources.
Keywords: galaxies: individual: NGC 1512; X-rays: galaxies; galaxies: individual: NGC 1510

XMM-Newton observation of the TeV-discovered supernova remnant HESS J1534-571 - Nguyen-Dang, N. T.; Pühlhofer, G.; Sasaki, Manami; Bamba, A.; Doroshenko, V.; Santangelo, A. (Astronomy & Astrophysics, 2023)
We report the results obtained from XMM-Newton observations of the TeV-detected supernova remnant (SNR) HESS J1534-571. We focus on the nature of the cosmic-ray particle content in the SNR, which is revealed by its γ-ray emission. No signatures of X-ray synchrotron emission were detected from the SNR. This is consistent with earlier results obtained with Suzaku from other regions of the object. A joint modeling of the XMM-Newton and Suzaku spectra yields an upper limit for the total X-ray flux from the SNR area of ∼5.62 × 10-13 erg cm-2 s-1 (95% C.I.) in the energy band of 2.0-10.0 keV for an assumed photon index of 2.0. On the other hand, we do find evidence in the XMM-Newton data for a line-like emission feature at 6.4 keV from localized regions, again confirming earlier Suzaku measurements. We discuss the findings in the context of the origin of the observed γ-ray emission. Although neither hadronic nor leptonic scenarios can be fully ruled out, the observed line emission can be interpreted as the result of interactions between lower-energy (∼ MeV) cosmic-ray protons with high gas-density regions in and around HESS J1534-571, and thus potentially be associated with particles accelerated in the SNR.
CRIS-Team Scopus Importer:2023-11-24
Keywords: Astroparticle physics; Cosmic rays; Gamma rays: ISM; ISM: supernova remnants; X-rays: individuals: HESS J1534-571

XMM-Newton observations of high Mass X-ray binaries in the SMC - Sasaki, Manami; Pietsch, Wolfgang; Haberl, Frank (Astronomy & Astrophysics, 2003)
Based on XMM-Newton EPIC data of four pointings towards the Small Magellanic Cloud (SMC), results on timing and spectral analyses of 16 known high mass X-ray binaries (HMXBs) and HMXB candidates in the SMC are presented. We confirm the pulse periods of four sources which were known to show pulsations. In addition, two new X-ray pulsars are discovered: XMMU J005605.2-722200 with P-pulse = 140.1 +/- 0.3 s and RX J0057.8-7207 with P-pulse = 152.34 +/- 0.05 s. Due to the low Galactic foreground absorption, X-ray binary systems in the Magellanic Clouds are well suited for studies of the soft component in their X-ray spectrum. Spectral analysis reveals soft emission besides a power law component in the spectra of three sources. The existence of emission lines in at least one of them corroborates the thermal nature of this emission with temperatures of 0.2-0.3 keV and heavy element abundances lower than solar. For the HMXB SMCX-2 which was in a low luminosity state, we determine a flux upper limit of 1.5 x 10(-14) erg cm(-2) s(-1) (0.3-10.0 keV). Furthermore, two new sources (XMMU J005735.7-721932 and XMMU J010030.2-722035) with hard spectrum and emission line objects as likely optical counterparts are proposed as new X-ray binary candidates.
Keywords: X-rays : galaxies; X-rays : binaries; stars : neutron; Magellanic Clouds

XMM-Newton observations of the brightest ultraluminous X-ray sources - Stobbarts, A.-M.; Roberts, Timothy; Wilms, Jörn (Monthly Notices of the Royal Astronomical Society, 2006)
We present an analysis of 13 of the best quality ultraluminous X-ray source (ULX) data sets available from XMM-Newton European Photon Imaging Camera (EPIC) observations. We utilize the high signal-to-noise in these ULX spectra to investigate the best descriptions of their spectral shape in the 0.3-10 keV range. Simple models of an absorbed power law or multicolour disc blackbody prove inadequate at describing the spectra. Better fits are found using a combination of these two components, with both variants of this model - a cool (similar to 0.2 keV) disc blackbody plus hard power-law continuum, and a soft power-law continuum, dominant at low energies, plus a warm (similar to 1.7 keV) disc blackbody - providing good fits to 8/13 ULX spectra. However, by examining the data above 2 keV, we find evidence for curvature in the majority of data sets (8/13 with at least marginal detections), inconsistent with the dominance of a power law in this regime. In fact, the most successful empirical description of the spectra proved to be a combination of a cool (similar to 0.2 keV) classic blackbody spectrum, plus a warm disc blackbody that fits acceptably to 10/13 ULXs. The best overall fits are provided by a physically self-consistent accretion disc plus Comptonized corona model (DISKPN + EQPAIR), which fits acceptably to 11/13 ULXs. This model provides a physical explanation for the spectral curvature, namely that it originates in an optically thick corona, though the accretion disc photons seeding this corona still originate in an apparently cool disc. We note similarities between this fit and models of Galactic black hole binaries at high accretion rates, most notably the model of Done & Kubota. In this scenario the inner disc and corona become energetically coupled at high accretion rates, resulting in a cooled accretion disc and optically thick corona. We conclude that this analysis of the best spectral data for ULXs shows it to be plausible that the majority of the population are high accretion rate stellar-mass (perhaps up to 80 M-circle dot) black holes, though we cannot categorically rule out the presence of larger, similar to 1000-M-circle dot intermediate-mass black holes (IMBHs) in individual sources with the current X-ray data.
Keywords: accretion; accretion discs; black hole physics; X-rays : binaries; X-rays : galaxies

XMM-Newton observations of the Galactic supernova remnant CTB 109 (G109.1-1.0) - Sasaki, Manami; Plucinsky, Paul P.; Gaetz, Terrance J.; Smith, Randall; Edgar, Richard; Slane, Patrick (Astrophysical Journal, 2004)
We present the analysis of the X-ray Multimirror Mission (XMM-Newton) European Photon Imaging Camera (EPIC) data of the Galactic supernova remnant (SNR) CTB 109 (G109.1-1.0). CTB 109 is associated with the anomalous X-ray pulsar (AXP) 1E 2259+586 and has an unusual semicircular morphology in both the X-ray and the radio and an extended X-ray bright interior region known as the "Lobe.'' The deep EPIC mosaic image of the remnant shows no emission toward the west where a giant molecular cloud complex is located. No morphological connection between the Lobe and the AXP is found. We find remarkably little spectral variation across the remnant given the large intensity variations. All spectra of the shell and the Lobe are well fitted by a single-temperature nonequilibrium ionization model for a collisional plasma with solar abundances [kTapproximate to0.5-0.7 keV, tau=integral n(e) dt approximate to(1-4)x10(11) s cm(-3), N(H)approximate to(5-7)x10(21) cm(-2)]. There is no indication of nonthermal emission in the Lobe or the shell. We conclude that the Lobe originated from an interaction of the SNR shock wave with an interstellar cloud. Applying the Sedov solution for the undisturbed eastern part of the SNR and assuming full equilibration between the electrons and ions behind the shock front, the SNR shock velocity is derived as v(s)=720+/-60 km s(-1), the remnant age as t=(8.8+/-0.9)x10(3)d(3) yr, the initial energy as E-0=(7.4+/-2.9)x10(50) d(3)(2.5) ergs, and the preshock density of the nuclei in the ambient medium as n(0)=(0.16+/-0.02)d(3)(-0.5) cm(-3), at an assumed distance of D=3.0d(3) kpc. Assuming that CTB 109 and 1E 2259+586 are associated, these values constrain the age and the environment of the progenitor of the SNR and the pulsar.
Keywords: ISM : individual (CTB 109); shock waves; supernova remnants; X-rays : individual (CTB 109)

XMM-Newton observations of the narrow-line Seyfert 1 galaxy IRAS 13224-3809: X-ray spectral analysis II - Jiang, Jiachen; Dauser, Thomas; Fabian, Andrew C.; Alston, William N.; Gallo, Luigi C.; Parker, Michael L.; Reynolds, Christopher S. (Monthly Notices of the Royal Astronomical Society, 2022)
Previously, we modelled the X-ray spectra of the narrow-line Seyfert 1 galaxy IRAS 13224-3809 using a disc reflection model with a fixed electron density of 10(15) cm(-3). An additional blackbody component was required to fit the soft X-ray excess below 2 keV. In this work, we analyse simultaneously five flux-resolved XMM-Newton spectra of this source comprising data collected over 2 Ms. A disc reflection model with an electron density of n(e) approximate to 10(20) cm(-3) and an iron abundance of Z(Fe) = 3.2 +/- 0.5 Z(circle dot) is used to fit the broad-band spectra of this source. No additional component is required to fit the soft excess. Our best-fitting model provides consistent measurements of black hole spin and disc inclination angle as previous models where a low disc density was assumed. In the end, we calculate the average illumination distance between the corona and the reflection region in the disc of IRAS 13224-3809 based on best-fitting density and ionization parameters, which changes from 0.43 root integral(AD)/integral(INF) r(g) in the lowest flux state to 1.71 root integral(AD)/integral(INF) r(g) in the highest flux state assuming a black hole mass of 2 x 10(6) M-circle dot. f(AD)/f(INF) is the ratio between the flux of the coronal emission that reaches the accretion disc and infinity. This ratio depends on the geometry of the coronal region in IRAS 13224-3809. So we only discuss its value based on the simple 'lamppost' model, although detailed modelling of the disc emissivity profile of IRAS 13224-3809 is required in future to reveal the exact geometry of the corona.
CRIS-Team WoS Importer:2022-06-24

XMM-newton observations of the Small Magellanic Cloud: XMMUJ004814.1-731003, a 25.55 s Be/X-ray binary pulsar - Haber, F.; Eger, P.; Pietsch, W.; Corbet, R. H. D.; Sasaki, Manami (Astronomy & Astrophysics, 2008)
Aims: To investigate candidates for Be/X-ray binaries in the Small Magellanic Cloud (SMC), we observed a region around the emission nebula N19 with XMM-Newton in October 2006. Methods: We analysed the EPIC data of the detected point sources to derive their spectral and temporal characteristics. Results: We detected X-ray pulsations with a period of 25.550(2) s from the second-brightest source in the field, which we designate XMMU J004814.1-731003. The X-ray spectrum is well modelled by a highly absorbed (NH = 5 × 1022 cm-2) power-law with photon index 1.33 ± 0.27. The precise X-ray position allows us to identify a Be star as the optical counterpart. XMMU J004814.1-731003 is located within the error circle of the transient ASCA source AX J0048.2-7309, but its position is inconsistent with that of the proposed optical counterpart of AX J0048.2-7309 (the emission line star [MA93] 215). It remains unclear if XMMU J004814.1-731003 is associated with AX J0048.2-7309. XMMU J004814.1-731003 might be identical to an RXTE pulsar that was discovered with a period of 25.5 s, but which is listed as a 51 s pulsar in the recent literature.
Keywords: galaxies : individual : small Magellanic Cloud; galaxy : stellar content; stars : emission-line; Be; stars : neutron; X-rays : binaries

XMM-Newton observations of the superbubble in N 158 in the LMC - Sasaki, Manami; Breitschwerdt, Dieter; Baumgartner, Verena; Haberl, Frank (Astronomy & Astrophysics, 2011)
Aims: We study the diffuse X-ray emission observed in the field of view of the pulsar B 0540-69 in the Large Magellanic Cloud (LMC) by XMM-Newton. We wish to understand the nature of this soft diffuse emission, which coincides with the superbubble in the H ii region N 158, and improve our understanding of the evolution of superbubbles. Methods: We analyse the XMM-Newton spectra of the diffuse emission. Using the parameters obtained from the spectral fit, we perform calculations of the evolution of the superbubble. The mass loss and energy input rates are based on the initial mass function (IMF) of the observed OB association inside the superbubble. Results: The analysis of the spectra shows that the soft X-ray emission arises from hot shocked gas surrounded by a thin shell of cooler, ionised gas. We show that the stellar winds alone cannot account for the energy inside the superbubble, but the energy release of 2-3 supernova explosions in the past 1 Myr provides a possible explanation. Conclusions: The combination of high sensitivity X-ray data, which permits a spectral analysis, and analytical models for superbubbles can provide insight into the evolutionary state of interstellar bubbles, if the stellar content is known.
Keywords: shock waves; ISM: bubbles; evolution; HII regions; X-rays: ISM

XMM-Newton study of the Draco dwarf spheroidal galaxy - Saeedi, Sara; Sasaki, Manami; Ducci, Lorenzo (Astronomy & Astrophysics, 2016)
Aims. We present the results of the analysis of five XMM-Newton observations of the Draco dwarf spheroidal galaxy (dSph). The aim of the work is the study of the X-ray population in the field of the Draco dSph. Methods. We classified the sources on the basis of spectral analysis, hardness ratios, X-ray-to-optical flux ratio, X-ray variability, and cross-correlation with available catalogues in X-ray, optical, infrared, and radio wavelengths. Results. We detected 70 X-ray sources in the field of the Draco dSph in the energy range of 0.2−12 keV and classified 18 AGNs, 9 galaxies and galaxy candidates, 6 sources as foreground stars, 4 low-mass X-ray binary candidates, 1 symbiotic star, and 2 binary system candidates. We also identified 9 sources as hard X-ray sources in the field of the galaxy. We derived the X-ray luminosity function of X-ray sources in the Draco dSph in the 2−10 keV and 0.5−2 keV energy bands. Using the X-ray luminosity function in the energy range of 0.5−2 keV, we estimate that ∼10 X-ray sources are objects in the Draco dSph. We have also estimated the dark matter halo mass that would be needed to keep the low-mass X-ray binaries gravitationally bound to the galaxy.
Keywords: galaxies: individual: Draco dwarf spheroidal galaxy; X-rays: galaxies; X-rays: binaries

XMM-Newton study of the Sculptor dwarf spheroidal galaxy - Saeedi, Sara; Sasaki, Manami (Monthly Notices of the Royal Astronomical Society, 2022)
We analysed observations with XMM-Newton in the field of the Sculptor dwarf spheroidal galaxy (dSph). The aim of the study was the classification of X-ray binaries and accreting white dwarfs belonging to the Sculptor dSph. Using different methods of X-ray timing and spectral analyses, together with an extensive multiwavelength study of the optical and infrared counterparts of the X-ray sources, we classified the sources detected with XMM-Newton in the field of the Sculptor dSph. The long-term variability of the sources has been studied over two XMM-Newton observations. None of the members of the Sculptor dSph show significant long-term variability over these two observations. We also searched for periodicity and pulsation using the Lomb-Scargle and Rayleigh Z(n)(2), techniques. No signals of pulsation or periodicity have been found for the X-ray sources. The results show the presence of a noticeable number of background X-ray sources in the field of this galaxy. We classified 43 sources as active galactic nuclei, galaxies, and galaxy candidates. Three Galactic foreground stars have been identified in the field of the Sculptor dSph, and one of them is an M-dwarf candidate. Moreover, we classified four symbiotic-star candidates and three quiescent low-mass X-ray binary candidates in the Sculptor dSph. The luminosity of these X-ray sources is similar to 10(33-35) erg s(-1).
CRIS-Team WoS Importer:2022-05-13

XMM-Newton study of X-ray sources in the field of Willman 1 dwarf spheroidal galaxy - Saeedi, Sara; Sasaki, Manami (Monthly Notices of the Royal Astronomical Society, 2020)
We present the results of the analysis of three XMM-Newton observations of the Willman 1 dwarf spheroidal galaxy (Wil 1). X-ray sources are classified on the basis of spectral analysis, hardness ratios, X-ray-to-optical flux ratio, X-ray variability, and cross-correlation with available catalogues in optical and infrared wavelengths. We catalogued 97 sources in the field of Wil 1. Our classification shows the presence of a β-type symbiotic star in Wil 1. We classified one M dwarf foreground star in the field of Wil 1. Moreover, 54 sources are classified as background active galactic nuclei and galaxies. Our study shows that the luminosity of the X-ray sources of Wil 1 does not exceed ∼1034 erg s−1 in the energy range of 0.2-12.0 keV, which is similar to observed luminosities of sources in nearby dwarf spheroidal galaxies.
CRIS-Team Scopus Importer:2020-12-11
Keywords: (Star:) binaries: symbiotic; Galaxies: dwarf galaxies; X-rays: binaries

XMM-Newton view of the N 206 superbubble in the Large Magellanic Cloud - Kavanagh, Patrick; Sasaki, Manami; Points, Sean (Astronomy & Astrophysics, 2012)
Conclusions. Using the high-sensitivity X-ray data from XMM-Newton and optical data from the Magellanic Cloud Emission Line Survey has allowed us to better understand the physical properties of the N 206 superbubble and address some key questions of superbubble evolution.
Keywords: Magellanic Clouds; ISM: bubbles; evolution; HII regions; X-rays: ISM

XMMU J050722.1-684758: Discovery of a new Be X-ray binary pulsar likely associated with the supernova remnant MCSNR J0507-6847 - Maitra, C.; Haberl, F.; Maggi, P.; Kavanagh, P. J.; Vasilopoulos, G.; Sasaki, Manami; Filipovic, M. D.; Udalski, A. (Monthly Notices of the Royal Astronomical Society, 2021)
We report the discovery of a new high-mass X-ray binary pulsar, XMMU J050722.1-684758, possibly associated with the supernova remnant (SNR) MCSNR J0507-6847 in the Large Magellanic Cloud, using XMM-NewtonX-ray observations. Pulsations with a periodicity of 570 s are discovered from the Be X-ray binary XMMU J050722.1-684758 confirming its nature as a HMXB pulsar. The HMXB is located near the geometric centre of the SNR MCSNR J0507-6847(0.9 arcmin from the centre) which supports the XRB-SNR association. The estimated age of the SNR is 43-63 kyr years which points to a middle aged to old SNR. The large diameter of the SNR combined with the lack of distinctive shell counterparts in optical and radio indicates that the SNR is expanding into the tenuous environment of the superbubble N103. The estimated magnetic field strength of the neutron star is B 1014 G assuming a spin equilibrium condition which is expected from the estimated age of the parent remnant and assuming that the measured mass-accretion rate remained constant throughout.
CRIS-Team Scopus Importer:2021-06-25
Keywords: ISM: supernova remnants; Magellanic Clouds; Radiation mechanisms: general; Radio continuum: ISM; X-rays: individuals: MCSNR J0507-6847; X-rays: individuals: XMMU J050722.1-684758

X-RAY AND NEAR-INFRARED OBSERVATIONS OF THE OBSCURED ACCRETING PULSAR IGR J18179-1621 - Nowak, M. A.; Paizis, Adamantia; Rodriguez, Jerome; Chaty, Sylvain; Del Santo, Melania; Grinberg, Victoria; Wilms, Jörn; Ubertini, P.; Chini, R. (Astrophysical Journal, 2012)
IGR J18179-1621 is an obscured accreting X-ray pulsar discovered by INTEGRAL on 2012 February 29. We report on our 20 ks Chandra-High Energy Transmission Gratings Spectrometer observation of the source performed on 2012 March 17, on two short contemporaneous Swift observations, and on our two near-infrared (K-s, H-n, and J(n)) observations performed on 2012 March 13 and 26. We determine the most accurate X-ray position of IGR J18179-1621, alpha(J2000) = 18(h)17(m)52.(s)18, delta(J2000) = -16 degrees 21'31.'' 68 (90% uncertainty of 0.'' 6). A strong periodic variability at 11.82 s is clearly detected in the Chandra data, confirming the pulsating nature of the source, with the light-curve softening at the pulse peak. The quasi-simultaneous Chandra-Swift spectra of IGR J18179-1621 can be well fit by a heavily absorbed hard power law (N-H = 2.2 +/- 0.3 x 10(23) cm(-2) and photon index Gamma = 0.4 +/- 0.1) with an average absorbed 2-8 keV flux of 1.4x10(-11) erg cm(-2) s(-1). At the Chandra-based position, a source is detected in our near-infrared (NIR) maps with K-s = 13.14 +/- 0.04 mag, H-n = 16 +/- 0.1 mag, and no J(n)-band counterpart down to similar to 18 mag. The NIR source, compatible with 2MASS J18175218-1621316, shows no variability between 2012 March 13 and 26. Searches of the UKIDSS database show similar NIR flux levels at epochs six months prior to and after a 2007 February 11 archival Chandra observation where the source's X-ray flux was at least 87 times fainter. In many ways IGR J18179-1621 is unusual: its combination of a several week long outburst (without evidence of repeated outbursts in the historical record), high absorption column (a large fraction of which is likely local to the system), and 11.82 s period does not fit neatly into existing X-ray binary categories.
Keywords: accretion; accretion disks; binaries: close; stars: individual; X-rays: binaries

X-ray detection of a nova in the fireball phase - König, Ole; Wilms, Jörn; Arcodia, Riccardo; Dauser, Thomas; Dennerl, Konrad; Doroshenko, Victor; Haberl, Frank; Hämmerich, Steven; Kirsch, Christian; Kreykenbohm, Ingo; Lorenz, Maximilian; Malyali, Adam; et al. (Nature, 2022)
Novae are caused by runaway thermonuclear burning in the hydrogen-rich envelopes of accreting white dwarfs, which leads to a rapid expansion of the envelope and the ejection of most of its mass1,2. Theory has predicted the existence of a ‘fireball’ phase following directly on from the runaway fusion, which should be observable as a short, bright and soft X-ray flash before the nova becomes visible in the optical3–5. Here we report observations of a bright and soft X-ray flash associated with the classical Galactic nova YZ Reticuli 11 h before its 9 mag optical brightening. No X-ray source was detected 4 h before and after the event, constraining the duration of the flash to shorter than 8 h. In agreement with theoretical predictions4,6–8, the source’s spectral shape is consistent with a black-body of 3.27+0.11−0.33 × 105 K (28.2+0.9−2.8 eV), or a white dwarf atmosphere, radiating at the Eddington luminosity, with a photosphere that is only slightly larger than a typical white dwarf.
CRIS-Team Scopus Importer:2022-06-03

X-ray emission from magnetized neutron star atmospheres at low mass-accretion rates: I. Phase-averaged spectrum - Sokolova-Lapa, Ekaterina; Gornostaev, M.; Wilms, Jörn; Ballhausen, Ralf; Falkner, Sebastian; Postnov, K.; Thalhammer, Philipp; Fürst, F.; Garcia, Javier; Shakura, N.; Becker, P. A.; Wolff, M. T.; et al. (Astronomy & Astrophysics, 2021)
Recent observations of X-ray pulsars at low luminosities allow, for the first time, the comparison of theoretical models of the emission from highly magnetized neutron star atmospheres at low mass-accretion rates (M ≤ 1015 g s-1) with the broadband X-ray data. The purpose of this paper is to investigate spectral formation in the neutron star atmosphere at low á¹€ and to conduct a parameter study of the physical properties of the emitting region. We obtain the structure of the static atmosphere, assuming that Coulomb collisions are the dominant deceleration process. The upper part of the atmosphere is strongly heated by the braking plasma, reaching temperatures of 30-40 keV, while its denser isothermal interior is much cooler (∼2 keV). We numerically solve the polarized radiative transfer in the atmosphere with magnetic Compton scattering, free-free processes, and nonthermal cyclotron emission due to possible collisional excitations of electrons. The strongly polarized emitted spectrum has a double-hump shape that is observed in low-luminosity X-ray pulsars. A low-energy "thermal"component is dominated by extraordinary photons that can leave the atmosphere from deeper layers because of their long mean free path at soft energies. We find that a high-energy component is formed because of resonant Comptonization in the heated nonisothermal part of the atmosphere even in the absence of collisional excitations. However, these latter, if present, affect the ratio of the two components. A strong cyclotron line originates from the optically thin, uppermost zone. A fit of the model to NuSTAR and Swift/XRT observations of GX 304-1 provides an accurate description of the data with reasonable parameters. The model can thus reproduce the characteristic double-hump spectrum observed in low-luminosity X-ray pulsars and provides insights into spectral formation.
CRIS-Team Scopus Importer:2021-07-16
Keywords: Magnetic fields; Methods: numerical; Polarization; Radiative transfer; Stars: neutron; X-rays: binaries

X-ray emitting structures in the Vela SNR: Ejecta anisotropies and progenitor stellar wind residuals - Sapienza, V.; Miceli, M.; Peres, G.; Bocchino, F.; Orlando, S.; Greco, E.; Combi, J. A.; Garciá, F.; Sasaki, Manami (Astronomy & Astrophysics, 2021)
Context. The Vela supernova remnant (SNR) shows several ejecta fragments (or shrapnel) protruding beyond the forward shock, which are most likely relics of anisotropies that developed during the supernova (SN) explosion. Recent studies have revealed high Si abundance in two shrapnel (shrapnel A and G), located in opposite directions with respect to the SNR center. This suggests the possible existence of a Si-rich jet-counterjet structure, similar to that observed in the SNR Cassiopea A. Aims. We analyzed an XMM-Newton observation of a bright clump, behind shrapnel G, which lies along the direction connecting shrapnel A and G. The aim is to study the physical and chemical properties of this clump to ascertain whether it is part of this putative jet-like structure. Methods. We produced background-corrected and adaptively-smoothed count-rate images and median photon energy maps, and performed a spatially resolved spectral analysis. Results. We identified two structures with different physical properties. The first one is remarkably elongated along the direction connecting shrapnel A and G. Its X-ray spectrum is much softer than that of the other two shrapnel, to the point of hindering the determination of the Si abundance; however, its physical and chemical properties are consistent with those of shrapnel A and shrapnel G. The second structure, running along the southeast-northwest direction, has a higher temperature and appears similar to a thin filament. By analyzing the ROSAT data, we have found that this filament is part of a very large and coherent structure that we identified in the western rim of the shell. Conclusions. We obtained a thorough description of the collimated, jet-like tail of shrapnel G in Vela SNR. In addition we discovered a coherent and very extended feature roughly perpendicular to the jet-like structure that we interpret as a signature of an earlier interaction of the remnant with the stellar wind of its progenitor star. The peculiar Ne/O ratio we found in the wind residual may be suggestive of a Wolf-Rayet progenitor for Vela SNR, though further analysis is required to address this point.
CRIS-Team Scopus Importer:2021-05-21
Keywords: ISM: individual objects: Vela SNR; ISM: supernova remnants; X-rays: ISM

X-ray monitoring of the radio and gamma-ray loud Narrow-Line Seyfert 1 Galaxy PKS 2004-447 - Kreikenbohm, A.; Kadler, M.; Wilms, Jörn; Schulz, R.; Mueller, C.; Ojha, R.; Ros, E.; Mannheim, K.; Elsaesser, D. (2013)
We present preliminary results of the X-ray analysis of XMM-Newton and Swift observations as part of a multi-wavelength monitoring campaign in 2012 of the radio-loud narrow line Seyfert 1 galaxy PKS 2004-447. The source was recently detected in gamma-rays by Fermi/LAT among only four other galaxies of that type. The 0.5 - 10 keV X-ray spectrum is well-described by a simple absorbed powerlaw (Gamma similar to 1.6). The source brightness exhibits variability on timescales of months to years with indications for spectral variability, which follows a "bluer-when-brighter" behaviour, similar to blazars.

X-RAY REFLECTED SPECTRA FROM ACCRETION DISK MODELS. III. A COMPLETE GRID OF IONIZED REFLECTION CALCULATIONS - Garcia, Javier; Dauser, Thomas; Reynolds, C. S.; Kallman, T. R.; Mcclintock, J. E.; Wilms, Jörn; Eikmann, Wiebke (Astrophysical Journal, 2013)
We present a new and complete library of synthetic spectra for modeling the component of emission that is reflected from an illuminated accretion disk. The spectra were computed using an updated version of our code XILLVER that incorporates new routines and a richer atomic database. We offer in the form of a table model an extensive grid of reflection models that cover a wide range of parameters. Each individual model is characterized by the photon index G of the illuminating radiation, the ionization parameter xi at the surface of the disk (i.e., the ratio of the X-ray flux to the gas density), and the iron abundance A(Fe) relative to the solar value. The ranges of the parameters covered are 1.2 <= Gamma <= 3.4, 1 <= xi <= 10(4), and 0.5 <= A(Fe) <= 10. These ranges capture the physical conditions typically inferred from observations of active galactic nuclei, and also stellar-mass black holes in the hard state. This library is intended for use when the thermal disk flux is faint compared to the incident power-law flux. The models are expected to provide an accurate description of the Fe K emission line, which is the crucial spectral feature used to measure black hole spin. A total of 720 reflection spectra are provided in a single FITS file (http://hea-www.cfa.harvard.edu/similar to javier/xillver/) suitable for the analysis of X-ray observations via the atable model in XSPEC. Detailed comparisons with previous reflection models illustrate the improvements incorporated in this version of XILLVER.
Keywords: accretion; accretion disks; atomic processes; black hole physics; line: formation; radiative transfer; X-rays: general

X-Ray Reverberation Mapping of Ark 564 Using Gaussian Process Regression - Lewin, Collin; Kara, Erin; Wilkins, Dan; Mastroserio, Guglielmo; Garcia, Javier A.; Zhang, Rachel C.; Alston, William N.; Connors, Riley; Dauser, Thomas; Fabian, Andrew; Ingram, Adam; Jiang, Jiachen; et al. (Astrophysical Journal, 2022)
Ark 564 is an extreme high-Eddington Narrow-line Seyfert 1 galaxy, known for being one of the brightest, most rapidly variable soft X-ray AGN, and for having one of the lowest temperature coronae. Here we present a 410-ks NuSTAR observation and two 115-ks XMM-Newton observations of this unique source, which reveal a very strong, relativistically broadened iron line. We compute the Fourier-resolved time lags by first using Gaussian processes to interpolate the NuSTAR gaps, implementing the first employment of multi-task learning for application in AGN timing. By fitting simultaneously the time lags and the flux spectra with the relativistic reverberation model RELTRANS, we constrain the mass at 2.3+2.6/-1.3x10(6)M?, although additional components are required to describe the prominent soft excess in this source. These results motivate future combinations of machine learning, Fourier-resolved timing, and the development of reverberation models.
CRIS-Team WoS Importer:2022-12-02

X-ray source population study of the starburst galaxy M 83 with XMM-Newton - Ducci, Lorenzo; Sasaki, Manami; Haberl, Frank; Pietsch, Wolfgang (Astronomy & Astrophysics, 2013)
Results. We identified and classified 12 background objects, five foreground stars, two X-ray binaries, one supernova remnant candidate, one super-soft source candidate and one ultra-luminous X-ray source. Among these sources, we classified for the first time three active galactic nuclei (AGN) candidates. We derived X-ray luminosity functions of the X-ray sources in M83 in the 2-10 keV energy range, within and outside the D-25 ellipse, correcting the total X-ray luminosity function for incompleteness and subtracting the AGN contribution. The X-ray luminosity function inside the D25 ellipse is consistent with that previously observed by Chandra. The Kolmogorov-Smirnov test shows that the X-ray luminosity function of the outer disc and the AGN luminosity distribution are uncorrelated with a probability of similar to 99.3%. We also found that the X-ray sources detected outside the D25 ellipse and the uniform spatial distribution of AGNs are spatially uncorrelated with a significance of 99.5%. We interpret these results as an indication that part of the observed X-ray sources are X-ray binaries in the outer disc of M83.
Keywords: galaxies: individual: M33; X-rays: galaxies

X-ray spectral and flux variability of the microquasar GRS 1758-258 on timescales from weeks to years - Hirsch, Maria; Pottschmidt, Katja; Smith, David M.; Bodaghee, Arash; Cadolle Bel, Marion; Grinberg, Victoria; Hell, Natalie; Krauß, Felicia; Kreykenbohm, Ingo; Lohfink, Anne; Nowak, Michael A.; Rodrigues, Bárbara H.; et al. (Astronomy & Astrophysics, 2020)
We present the spectral and timing evolution of the persistent black hole X-ray binary GRS 1758-258 based on almost 12 years of observations using the Rossi X-ray Timing Explorer Proportional Counter Array. While the source was predominantly found in the hard state during this time, it entered the thermally dominated soft state seven times. In the soft state GRS 1758-258 shows a strong decline in flux above 3 keV rather than the pivoting flux around 10 keV more commonly shown by black hole transients. In its 3-20 keV hardness intensity diagram, GRS 1758-258 shows a hysteresis of hard and soft state fluxes typical for transient sources in outburst. The RXTE-PCA and RXTE-ASM long-term light curves do not show any orbital modulations in the range of 2-30 d. However, in the dynamic power spectra significant peaks drift between 18.47 and 18.04 d for the PCA data, while less significant signatures between 19 d and 20 d are seen for the ASM data as well as for the Swift/BAT data. We discuss different models for the hysteresis behavior during state transitions as well as possibilities for the origin of the long term variation in the context of a warped accretion disk.
CRIS-Team Scopus Importer:2020-05-02
Keywords: X-rays: binaries; X-rays: individuals: GRS 1758-258

X-ray spectroscopy of MXB 1728-34 with XMM-Newton - Egron, Elise; Di Salvo, Tiziana; Burderi, L.; Papitto, Alessandro; Barragan, L.; Dauser, Thomas; Wilms, Jörn; D'Ai, Antonino; Riggio, Alessandro; Iaria, Rosario; Robba, N. R. (Astronomy & Astrophysics, 2011)
We analyzed an XMM-Newton observation of the low-mass X-ray binary and atoll source MXB 1728-34. The source was in a low-luminosity state during the XMM-Newton observation, corresponding to a bolometric X-ray luminosity of 5 x 10(36) d(5.1kpc)(2) erg s(-1). The 1-11 keV X-ray spectrum of the source, obtained combining data from all the five instruments on-board XMM-Newton, is well fitted by a Comptonized continuum. Evident residuals are present at 6-7 keV, which are ascribed to the presence of a broad iron emission line. This feature can be equally well fitted by a relativistically smeared line or by a self-consistent, relativistically smeared reflection model. Under the hypothesis that the iron line is produced by reflection from the inner accretion disk, we can infer important information on the physical parameters of the system, such as the inner disk radius, R-in = 25-100 km, and the inclination of the system, 44 degrees < i < 60 degrees.
Keywords: line: formation; line: identification; stars: neutron; stars: individual: MXB 1728-34; X-rays: binaries; X-rays: general

X-ray variation statistics and wind clumping in Vela X-1 - Fürst, Felix; Kreykenbohm, Ingo; Pottschmidt, K.; Wilms, Jörn; Hanke, Manfred; Rothschild, R. E.; Kretschmar, Peter; Schulz, N. S.; Huenemoerder, D. P.; Klochkov, D.; Staubert, R. (Astronomy & Astrophysics, 2010)
We investigate the structure of the wind in the neutron star X-ray binary system Vela X-1 by analyzing its flaring behavior. Vela X-1 shows constant flaring, with some flares reaching fluxes of more than 3.0 Crab between 20-60 keV for several 100 s, while the average flux is around 250 mCrab. We analyzed all archival INTEGRAL data, calculating the brightness distribution in the 20-60 keV band, which, as we show, closely follows a log-normal distribution. Orbital resolved analysis shows that the structure is strongly variable, explainable by shocks and a fluctuating accretion wake. Analysis of RXTE ASM data suggests a strong orbital change of N(H). Accreted clump masses derived from the INTEGRAL data are on the order of 5x10(19) - 10(21) g. We show that the lightcurve can be described with a model of multiplicative random numbers. In the course of the simulation we calculate the power spectral density of the system in the 20-100 keV energy band and show that it follows a red-noise power law. We suggest that a mixture of a clumpy wind, shocks, and turbulence can explain the measured mass distribution. As the recently discovered class of supergiant fast X-ray transients (SFXT) seems to show the same parameters for the wind, the link between persistent HMXB like Vela X-1 and SFXT is further strengthened.
Keywords: accretion; accretion disks; X-rays: binaries; X-rays: individuals: Vela X-1; methods: statistical

XRBcats: Galactic low-mass X-ray binary catalogue - Avakyan, A.; Neumann, M.; Zainab, A.; Doroshenko, V.; Wilms, Jörn; Santangelo, A. (Astronomy & Astrophysics, 2023)
We present a new catalogue of low-mass X-ray binaries (LMXBs) in the Galaxy. The catalogue contains source names, coordinates, source types, fluxes, distances, system parameters, and other characteristic properties of 349 LMXBs, including systems that have been newly discovered or reclassified since the most recently reported LMXB catalogues. The aim of this catalogue is to provide a list of all currently known Galactic objects identified as LMXBs with some basic information on each system (including X-ray and optical/IR properties where possible). Literature published before May 2023 has been taken into account where possible when compiling this information. References for all reported properties as well as object-finding charts in several energy bands are provided as part of the catalogue. We plan to update the catalogue regularly, in particular to reflect new objects discovered in the ongoing large-scale surveys such as Gaia and eROSITA.
CRIS-Team Scopus Importer:2023-08-11
Keywords: Binaries: close; Catalogs; Stars: late-type; X-rays: binaries

γ Columbae as a recently stripped pulsating core of a massive star - Irrgang, Andreas; Przybilla, Norbert; Meynet, Georges (Nature Astronomy, 2022)
Stellar cores, that is, the central regions where densities and temperatures are high enough for nuclear fusion processes to take place, are usually covered by an opaque envelope. Only in very rare cases, stars may expose their cores, for example, when a tiny fraction of them evolve into Wolf–Rayet or helium hot subdwarf stars. However, for the vast majority of stars, namely unevolved stars that burn hydrogen into helium in their centres, direct observational clues on the cores are still missing. On the basis of a spectroscopic and photometric analyses, here we show that the bright B-type-star γ Columbae is the stripped pulsating core (with a mass of 4–5 M⊙, where M⊙ is the mass of the Sun) of a previously much more massive star of roughly 12 M⊙ that just finished central hydrogen fusion. The discovery of this star, which is still in a short-lived post-stripping structural re-adjustment phase, paves the way to obtain invaluable insights into the physics of both single and binary stars with respect to nuclear astrophysics and common-envelope evolution. In particular, it provides observational constraints on the structure and evolution of stripped-envelope stars.
CRIS-Team Scopus Importer:2022-11-11

γ-ray emission in radio galaxies under the VLBI scope: II. The relationship between γ-ray emission and parsec-scale jets in radio galaxies - Angioni, R.; Ros, E.; Kadler, M.; Ojha, R.; Mueller, C.; Edwards, P. G.; Burd, P. R.; Carpenter, B.; Dutka, M. S.; Gulyaev, S.; Hase, H.; Horiuchi, S.; et al. (Astronomy & Astrophysics, 2020)
Aims. This is the second paper in our series studying the evolution of parsec-scale radio emission in radio galaxies in the Southern Hemisphere. Following our study of the radio and high-energy properties of γ-ray-emitting sources, here we investigate the kinematic and spectral properties of the parsec-scale jets of radio galaxies that have not yet been detected by the Fermi Large Area Telescope (Fermi-LAT) instrument on board NASA's Fermi Gamma-ray Space Telescope. For many sources, these results represent the first milliarcsecond resolution information in the literature. These studies were conducted within the framework of the Tracking Active Nuclei with Austral Milliarcsecond Interferometry (TANAMI) monitoring program and in the context of high-energy γ-ray observations from Fermi-LAT. Methods. We took advantage of the regular 8.4 GHz and 22.3 GHz Very Long Baseline Interferometry (VLBI) observations provided by the TANAMI monitoring program, and explored the kinematic properties of six γ-ray-faint radio galaxies. We complemented this with ∼8.5 years of Fermi-LAT data, deriving updated upper limits on the γ-ray emission from this subsample of TANAMI radio galaxies. We included publicly available VLBI kinematics of γ-ray-quiet radio galaxies monitored by the MOJAVE program and performed a consistent Fermi-LAT analysis. We combined these results with those from our previous paper to construct the largest sample of radio galaxies with combined VLBI and γ-ray measurements to date. The connection between parsec-scale jet emission and high-energy properties in the misaligned jets of radio galaxies was explored. Results. For the first time, we report evidence of superluminal motion up to βappâ€., =â€., 3.6 in the jet of the γ-ray-faint radio galaxy PKS 2153-69. We find a clear trend of higher apparent speed as a function of distance from the jet core, which indicates that the jet is still being accelerated on scales of tens of parsecs, or ∼105â€† Rs, corresponding to the end of the collimation and acceleration zone in nearby radio galaxies. We find evidence of subluminal apparent motion in the jets of PKS 1258-321 and IC 4296, and no measurable apparent motion for PKS 1549-79, PKS 1733-565, and PKS 2027-308. For all these sources, TANAMI provides the first multi-epoch kinematic analysis on parsec scales. We then compare the VLBI properties of γ-ray-detected and undetected radio galaxies, and find that the two populations show a significantly different distribution of median core flux density, and, possibly, of median core brightness temperature. In terms of correlation between VLBI and γ-ray properties, we find a significant correlation between median core flux density and γ-ray flux, but no correlation with typical Doppler boosting indicators such as median core brightness temperature and core dominance. Conclusions. Our study suggests that high-energy emission from radio galaxies is related to parsec-scale radio emission from the inner jet, but is not driven by Doppler boosting effects, in contrast to the situation in their blazar counterparts. This implies that γ-ray loudness does not necessarily reflect a higher prevalence of boosting effects.
CRIS-Team Scopus Importer:2020-10-23
Keywords: Galaxies: active; Galaxies: jets; Galaxies: nuclei; Gamma rays: galaxies

Radio galaxies at TeV energies: Preface - Glawion, Dorit (Galaxies, 2020)
The majority of the known extragalactic sky from TeV gamma-ray energies consists of blazars having plasma jets pointing in the direction of the line-of-sight, which results in a large Doppler boosting of their emission. Up to now, only six galaxies with a larger viewing angle have been detected in the TeV range. These objects also show fascinating properties, such as fast variability or spectral features and are called "radio galaxies". The TeV radio galaxies provide a unique laboratory for studying key aspects of active galactic nuclei. This Special Issue of Galaxies targets these exciting objects.
CRIS-Team Scopus Importer:2020-03-27
Keywords: Active galactic nuclei; Emission: non-thermal; Gamma-rays; Radio galaxies